Suicidal attempt with intracranial sewing needle in a female adult with major depressive disorder, case report - Derakhshan, N.; Yaghamei, S.; Mostafeenezhad, N. (Middle East Current Psychiatry, 2020)
Background: Major depressive disorder is one of the most common psychiatric illnesses. It is counted as an important suicide-attempting factor. Beside common and known suicide methods such as pesticide poisoning and hanging, some unusual methods (adapted by major depressive disorder patients) are reported in the literature. One of these methods is intracranial swing needle insertion. Case presentation: Hereby, we detail a 44-year-old woman who was admitted to our hospital due to a sewing needle in her brain tissue. The first sign suggesting the existence of a metal foreign body in her brain was the rejection of magnetic resonance imaging ordered (follow-up of a previous admission). Later, a sewing needle was observed in her skull inserted in a suicidal attempt. Her denial of the attempt has aroused the medical team attention to make further study of the patient from a psychiatric point of view. The psychiatric study expressed major depressive disorder in the patient which can justify her suicide intention in the needle insertion. Conclusions: Treating such patients should be tackled in two fronts. From neurosurgical point of view, it should be decided whether to extract the foreign body or conduct a follow-up in order to determine the necessary time for operation. On the other hand, from a psychiatric point of view, rigorous consult sessions with patient and family members are required to prevent recurrence of such attempts. © 2020, The Author(s).
Keywords: Case report; Intracranial sewing needle; Major depressive disorder; Rare suicidal attempt

Reducing the risk of unintended retained surgical sponges: A quality improvement project - Grant, E.K.; Gattamorta, K.A.; Foronda, C.L. (Perioperative Care and Operating Room Management, 2020)
Background: Unintended retained surgical sponges (URSSs) are preventable catastrophic events that occur in the surgical environment. Purpose: A community hospital in the southern United States sought to reduce the occurrence of URSSs by implementing a quality improvement initiative. Methods: We conducted a practice improvement project that incorporated safety-sponge technology preceded by education and training. Staff knowledge and practice expectations were assessed using a pre-post-intervention survey followed by internal audit. Results: Staff knowledge significantly improved after the tailored education and training. A chart audit conducted 15 weeks after the intervention showed compliance with the technology was 99.4%, incorrect surgical counts went from 4% to 0.8%, and number of URSSs went from 2 to 0. Conclusion: The project demonstrated a reduced risk of incorrect surgical counts and URSSs in the facility. © 2020

Does the Inion OTPSTM absorbable plating system induce higher foreign-body reaction than titanium implants? An experimental randomized comparative study in rabbits - Chalidis, B.; Kitridis, D.; Savvidis, P.; Papalois, A.; Givissis, P. (Biomedical Materials (Bristol), 2020)
Hardware removal after complete fracture healing is a laborious and traumatic procedure that bears the risks of refracture, infection, and soft tissue damage. Absorbable materials for fracture fixation have the advantage of eliminating the need for removal; however, they may stimulate a considerable inflammatory response. For that reason, we compared in a prospective randomized experimental animal model study the incidence of foreign-body reactions between Inion OTPSTM absorbable plate implants, consisting of carbon trimethylene, L-polylactic acid, and D, L-polylactic acid, and conventional titanium plates. Seventy rabbits were equally divided into two groups. Titanium (Group A) or absorbable (Group B) plates and screws were implanted in the femoral shaft of the rabbits. Wound reaction and laboratory tests including white blood cell count (WBC), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) values were measured and compared at different time points. Radiographs and histological analysis of tissue samples from all animals were also used to identify potential foreign-body reactions. WBC showed normal values in both groups. In Group A, ESR levels were higher at all time points but CRP values were normalized at 3 weeks postoperatively. In Group B, ESR and CRP levels reached a peak at 3 weeks and were above normal values throughout the whole experiment (p < 0.001). Radiologic examination revealed periosteal thickening and surrounding sclerosis in 23 out of 35 animals of Group B (66%). All Group A animals had normal radiographic findings. Histopathology showed a typical non-specific foreign-body reaction in all animals in Group B (100%) but none in Group A. However, only four of them (11.8%) developed non-infected wound complications and showed significantly elevated CRP and ESR values (p = 0.054). Although Inion OTPSTM Biodegradable Plating System stimulates a foreign-body reaction, only a small but not negligible percentage of almost 12% may lead to wound problems. However, this difference compared to titanium plates was of borderline not statistically significant. Future studies should focus on the development of absorbable implants with improved biocompatibility aiming to further decrease the potential of foreign-body reaction and eliminate the need for additional reoperative procedures. © 2020 IOP Publishing Ltd
Keywords: Absorbable implants; Animal study; Foreign-body reaction; Rabbits

Clinical Issues-November 2020 - Seeman, K. (AORN journal, 2020)
Using adhesive tape for patient positioning Key words: adhesive tape, surgical tape, patient positioning, pressure injury, contamination. Border sterility of open sterile wrappers Key words: wrapped sterile item, unsterile border, wrapper flap, contaminated, aseptic technique. Cost per minute of OR time Key words: cost comparison, direct costs, cost savings, perioperative efficiency, product evaluation. Packages containing an incorrect number of suture needles Key words: multipack, retained surgical item (RSI), counting, needle, package. © AORN, Inc, 2020.

Abdominal skin inflammation as an initial symptom of a perforating gastric foreign body: A case report - Zhang, L.; Liu, L.; Shao, J.; Sun, F.; Zhao, L. (Medicine, 2020)
RATIONALE: Foreign bodies are frequently ingested, but only approximately 1% of them cause perforation. Perforations in the lesser curvature of the stomach are exceedingly rare. Here, we report a case of gastric perforation in the lesser curvature caused by a foreign body. The patient presented to the clinic complaining of abdominal skin swelling and reddening with upper abdominal discomfort as the initial symptoms. PATIENT CONCERNS: An 83-year-old female presented with a mass in the middle of the epigastrium for 10 days. Physical examination found an apparent local tenderness and inflammatory mass in the upper abdominal wall. Her body temperature was normal (37.5°C) and the white blood cell count was elevated (8.12 × 10/L [reference value 3.5-9.5 × 10/L]). DIAGNOSES: The ultrasound examination of the abdomen revealed a 4 cm strip-like hyperechoic object entangled in the muscles of the abdominal wall. The computed tomography scan revealed a thin strip of bone-like hyperdense shadow. Intraoperative findings showed a sharp fishbone protruding from the lesser curvature of the stomach into the abdominal cavity, part of which remained in the gastric cavity. The postoperative pathological report revealed chronic suppurative inflammation with abscess and sinus canal formation. INTERVENTIONS & OUTCOMES: The patient underwent a gastric foreign body removal with partial gastrectomy. Anti-inflammatory treatment post-surgery rapidly relieved the patient's symptoms of discomfort in the upper abdomen. At the 1-month follow-up, the patient showed no discomfort in the upper abdomen and the inflammatory mass was no longer present. LESSONS: A foreign body had penetrated through the lesser curvature of the stomach, an area with a flat gastric wall, which occurs infrequently. In such cases, computed tomography is the gold standard for diagnosis of foreign bodies in the digestive tract. Ultrasound can also be used as a supplemental diagnostic technique. It is recommended that people who wear dentures should exercise caution while eating, especially when the food contains bones.

Intracardiac foreign body: A rare cause of recurrent fungemia - Wong, M.K.H.; Rocha, B.A.; Au, T.W.K. (Journal of Cardiac Surgery, 2020)
Background: An intracardiac foreign body causing recurrent fungemia is a rare clinical situation. Clinicians should be that aware of rare sources of sepsis despite a thorough history and examination. Results: The authors describe a 63 year-old man, with unremarkable past medical history, who presented with a fever for 2 weeks. Blood cultures persistently grew Candida albicans and Streptococcus constellatus. Echocardiogram assessment showed a suspected vegetation over the tricuspid valve. Surgical exploration with median sternotomy and cardiopulmonary bypass revealed a tooth-pick impacted within the right atrium surrounded by vegetation. The authors postulate accidental ingestion of the foreign body and translocation into the right atrium via the esophagus and thoracic cavity. Conclusion: Surgical removal of symptomatic intracardiac foreign bodies is highly recommended. © 2020 Wiley Periodicals LLC
Keywords: candida endocarditis; intracardiac foreign body; tricuspid valve

A rare peritoneal egg: Case report with literature review - Dhoot, N.M.; Afzalpurkar, S.; Goenka, U.; Mahendra, V.; Khan, E.M.; Sutradhar, A.; Goenka, M. (Radiology Case Reports, 2020)
The occurrence of peritoneal loose bodies has been known for hundreds of years. Although rarely, they attain a diameter of more than 5 cm and are then named “giant” peritoneal bodies (gPLBs). Even these huge peritoneal bodies are generally symptom free, but may be linked with chronic symptoms like abdominal pain or discomfort. Many a times, these gPLBs are misinterpreted as intraabdominal tumors or foreign bodies and unnecessary surgical interventions are carried out. We report a rare case of a 75-year-old male, who presented to our tertiary care center emergency department with history of chronic intermittent abdominal discomfort with acute diarrhea and peri-anal pain. Contrast enhanced computed tomography of the abdomen and pelvis revealed round to oval mass in the pelvis measuring 6.2 cm × 5.8 cm. On laparoscopy, a hard, free floating object with the appearance of a boiled egg could just be scooped out from the pelvis. The postoperative pathological examination revealed laminated strands of hyalinized fibro collagenous tissue with central fat necrosis confirming the diagnosis of gPLB. Postoperative period was uneventful. Peritoneal bodies are rare intraabdominal bodies which are either detected incidentally or present with vague symptoms and require interdisciplinary management. © 2020
Keywords: Boiled egg; Fibro collagenous tissue; Free floating; Giant; Peritoneal body

Using Radiofrequency Technology to Prevent Retained Sponges and Improve Patient Outcomes - Primiano, M.; Sparks, D.; Murphy, J.; Glaser, K.; McNett, M. (AORN Journal, 2020)
Retained items (eg, sponges, sharps) after surgical procedures are reportable errors that can result in patient harm or death and increased patient and health care system costs. Perioperative use of radiofrequency (RF) technology may decrease the number of retained sponges and reduce hospital costs. We sought to determine whether the use of RF technology may be associated with fewer retained sponges, improved patient outcomes, and decreased hospital costs. We completed a retrospective evaluation of incident reports before and after implementing the use of an RF system for retained surgical sponges. We found that using RF technology was associated with fewer retained sponges and improved outcomes at our facility. We also determined that mortality rates before and after RF technology implementation were similar, and we estimated that our hospital’s costs were reduced. © AORN, Inc, 2020
Keywords: human error; manual surgical count; radiofrequency (RF) technology; retained surgical item; surgical sponge

Clinical Issues-September 2020 - Jones, E.; Wood, A. (AORN journal, 2020)
THIS MONTH: Surgical counts during a partial cystectomy Key words: partial cystectomy, retained surgical item (RSI), counts, bladder, guidewire. Preparing the OR for patients who require both airborne and contact precautions Key words: airborne precautions, contact precautions, contamination, Coronavirus Disease 2019 (COVID-19), negative pressure. Preoperative transport of patients who require both airborne and contact precautions Key words: preoperative patient transport, hand hygiene, personal protective equipment (PPE), N95 respirator, Coronavirus Disease 2019 (COVID-19). Postoperative transport of patients who require both airborne and contact precautions Key words: postoperative patient transport, hand hygiene, personal protective equipment (PPE), N95 respirator, Coronavirus Disease 2019 (COVID-19). © AORN, Inc, 2020.

Peach pit impaction presenting as gallstone ileus - Syed, A.S.; Bonte, A.; Allaham, L.A.; Goodman, E.R. (BMJ Case Reports, 2020)
Small bowel obstruction (SBO) secondary to fruit pit impaction is rare. The presence of an ovoid, stony body in the bowel lumen on radiologic imaging in a patient presenting with signs and symptoms of SBO is likely to raise concern for gallstone ileus. We report the case of a 56-year-old man who presented with a 1-day history of intermittent left-sided abdominal pain and nausea associated with a single episode of vomiting. CT scan of the abdomen and pelvis revealed a 3.3 cm impacted stony mass in the terminal ileum resulting in high-grade partial SBO. The mass had a hypodense centre encased within a hyperdense, ridged outer layer. The diagnostic impression was gallstone ileus. The object was removed via enterotomy and was found to be a peach pit. © BMJ Publishing Group Limited 2020. No commercial re-use. See rights and permissions. Published by BMJ.
Keywords: gastrointestinal surgery; radiology

Surgical outcomes of the removal of posterior segment metallic intraocular foreign bodies - Peng, K.-L.; Kung, Y.-H.; Hsu, P.-S.; Wu, T.-T. (BMC Ophthalmology, 2020)
Background: Posterior segment metallic intraocular foreign bodies (IOFBs) are a leading cause of visual morbidity and blindness, especially among young and middle-aged working populations. Here, we aimed to evaluate the surgical outcomes of the removal of such IOFBs that result from injuries. Methods: In this retrospective study, 39 patients injured by metallic posterior segment IOFBs and who underwent primary repair procedures, vitrectomies, and IOFBs removal with or without procedures for traumatic cataract removal, scleral buckling and intraoperative tamponade application from January, 2008 to January, 2019. We analyzed the preoperative, intraoperative and postoperative related factors that affect the final visual outcomes. Results: The mean age of the 39 patients was 40.51 ± 12.48 years with the male being predominent (100%).The mean preoperative vision measured 1.50 [Snellen Equivalent (SE), 20/645] ± 1.12 logMAR with the mean final vision measuring 0.93 (SE, 20/172) ± 1.09 logMAR. The related factors that were determined to affect the final visual outcomes included preoperative vision (P = 0.025), IOFB-related macula injuries (P = 0.001) and the development of postoperative complications (P = 0.005) especially retinal detachment (P = 0.002) with the mean final vision measuring 2.12 (SE, counting finger to hand motion) ±1.23 logMAR. Concerning the preoperative signs, the patients with preoperative endophthalmitis also obtained poor mean final vision measuring 1.30 (SE,20/400) ± 1.40 logMAR. Conclusion: IOFB-related macula injuries and postoperative retinal detachment were important related factors of poor final visual prognoses in cases involving posterior segment metallic IOFBs. Removing IOFB as early as possible may prevent preoperative endophthalmitis which could lead poor final visions even without significance. © 2020 The Author(s).
Keywords: Endophthalmitis; Metallic intraocular foreign bodies; Posterior segment; Retinal detachment; Scleral buckling; Tamponade; Vitrectomy

MRI diagnosis of rubber band constriction syndrome - Sosnouski, D.; Chapin, R.W.; Thacker, P.G.; Walton, Z.J.; Mooney, J.F. (Radiology Case Reports, 2020)
Rubber band syndrome is caused by constriction of the wrist from elastic bracelets worn for decorative purposes. Overtime, the fixed or elastic band burrows into the skin and becomes invisible. We present the case of a 2.5-year-old female child presenting to our institution with signs of circumferential swelling and inflammatory changes about the right wrist. MRI of the wrist demonstrated a subcutaneous circular foreign body, which was confirmed at surgery to be a rubber band. Although this disease entity is rare, radiologists can be instrumental in suggesting this diagnosis based on the location involved, ie, wrist, and the imaging findings. © 2020
Keywords: Bracelet; Children; MRI; Rubber band; Wrist

A systematic review on current osteosynthesis-associated infection animal fracture models - Wong, R.M.Y.; Li, T.-K.; Li, J.; Ho, W.-T.; Chow, S.K.-H.; Leung, S.S.Y.; Cheung, W.-H.; Ip, M. (Journal of Orthopaedic Translation, 2020)
Objective: Osteosynthesis-associated infection is a challenging complication post fracture fixation, burdening the patients and the orthopaedic surgeons alike. A clinically relevant animal model is critical in devising new therapeutic strategies. Our aim was to perform a systematic review to evaluate existing preclinical models and identify their applications in aspects of animal selection, bacterial induction, fracture fixation and complications. Methods: A systematic literature research was conducted in PubMed and Embase up to February 2020. A total of 31 studies were included. Information on the animal, bacterial induction, fracture fixation, healing result and complications were extracted. Results: Animals selected included murine (23), rabbit (6), ewe (1) and goat (1). Larger animals had enabled the use of human-sized implant, however small animals were more economical and easier in handling. Staphylococcus aureus (S. aureus) was the most frequently chosen bacteria for induction. Bacterial inoculation dose ranged from 102−8 ​CFU. Consistent and replicable infections were observed from 104 ​CFU in general. Methods of inoculation included injections of bacterial suspension (20), placement of foreign objects (8) and pretreatment of implants with established biofilm (3). Intramedullary implants (13), plates and screws (18) were used in most models. Radiological (29) and histological evaluations (24) in osseous healing were performed. Complications such as instability of fracture fixation (7), unexpected surgical death (5), sepsis (1) and persistent lameness (1) were encountered. Conclusion: The most common animal model is the S. aureus infected open fracture internally fixated. Replicable infections were mainly from 104 ​CFU of bacteria. However, with the increase in antibiotic resistance, future directions should explore polymicrobial and antibiotic resistant strains, as these will no doubt play a major role in bone infection. Currently, there is also a lack of osteoporotic bone infection models and the pathophysiology is unexplored, which would be important with our aging population. The translational potential of this article: This systematic review provides an updated overview and compares the currently available animal models of osteosynthesis-associated infections. A discussion on future research directions and suggestion of animal model settings were made, which is expected to advance the research in this field. © 2020 The Authors
Keywords: Animal models; Fracture; Infection models; Osteosynthesis-associated infection; Systematic review

A national survey on esophageal perforation: study of cases at accredited institutions by the Japanese Esophagus Society - Sohda, M.; Kuwano, H.; Sakai, M.; Miyazaki, T.; Kakeji, Y.; Toh, Y.; Matsubara, H. (Esophagus, 2020)
Objective: To get a clear view of the current state of treatment for esophageal perforation in Japan. Summary background data: Esophagus perforations are the most serious gastrointestinal tract perforations and are associated with high morbidity and mortality. The optimal treatment choice remains unknown. Methods: We conducted a retrospective clinical review of 182 esophageal perforation cases at 108 hospitals accredited by the Japanese Esophageal Society between January 2010 and December 2015. Results: We found that 20.9% of patients were incorrectly diagnosed initially. We observed mediastinum emphysema in 83.5% of patients, and serious abscess formations of the mediastinum and intrathoracic cavity in 38.6% and 29.6%, respectively. The lower esophagus was the most commonly perforated site (77.7%). Management of esophageal perforations included nonoperative treatment in 20 patients (11%) and operative treatment in 162 patients (89%). The overall mortality rate was 6.9%. The survivors had significantly shorter times from symptom appearance to visit (p = 0.0016), and from time to visit to diagnosis confirmation (p = 0.0011). Moreover, patients older than 65 years, white blood cells less than 3000/mm3, C-reactive protein > 10 mg/L, or abscesses in the thoracic cavity showed significantly higher mortality than others. Conclusion: Shortening the time from onset to the start of treatment contributes to reduce mortality in patients with esophageal perforation. Moreover, strict medical treatment is necessary to lower the mortality rate of elderly patients with strong inflammation and abscesses in the thoracic cavity. © 2020, The Japan Esophageal Society.
Keywords: Esophageal perforation; Survey

Automatic gauze tracking in laparoscopic surgery using image texture analysis - de la Fuente López, E.; Muñoz García, Á.; Santos del Blanco, L.; Fraile Marinero, J.C.; Pérez Turiel, J. (Computer Methods and Programs in Biomedicine, 2020)
Background and Objective: Inadvertent retained surgical gauzes are an infrequent medical error but can have devastating consequences in the patient health and in the surgeon professional reputation. This problem seems easily preventable implementing standardized protocols for counting but due to human errors it still persists in surgery. The omnipresence of gauzes, their small size, and their similar appearance with tissues when they are soaked in blood make this error eradication really complex. In order to reduce the risk of accidental retention of surgical sponges in laparoscopy operations, in this paper we present an image processing system that tracks the gauzes on the video captured by the endoscope. Methods: The proposed image processing application detects the presence of gauzes in the video images using texture analysis techniques. The process starts dividing the video frames into square blocks and each of these blocks is analyzed to determine whether it is similar to the gauze pattern. The video processing algorithm has been tested in a laparoscopic simulator under different conditions: with clean, slightly stained and soaked in blood gauzes as well as against different biological background tissues. Several methods, including different Local Binary Patterns (LBP) techniques and a convolutional neural network (CNN), have been analyzed in order to achieve a reliable detection in real time. Results: The proposed LBP algorithm classifies the individual blocks in the image with 98% precision and 94% sensitivity which is sufficient to make a robust detection of any gauze that appears in the endoscopic video even if it is stained or soaked in blood. The results provided by the CNN are superior with 100% precision and 97% sensitivity, but due to the high computational demand, real-time video processing is not attainable in this case with standard hardware. Conclusions: The algorithm presented in this paper is a valuable tool to avoid the retention of surgical gauzes not only because of its reliability but also because it processes the video transparently and unattended, without the need for additional manipulation of special equipment in the operating room. © 2020
Keywords: Computer-aided-surgery; Convolutional Neural Networks; Gossypiboma; Image Texture Analysis; Local Binary Patterns (LBP); Minimally Invasive Surgery

Isolating Crucial Steps in Induction of Infective Endocarditis With Preclinical Modeling of Host Pathogen Interaction - Schwarz, C.; Hoerr, V.; Töre, Y.; Hösker, V.; Hansen, U.; Van de Vyver, H.; Niemann, S.; Kuhlmann, M.T.; Jeibmann, A.; Wildgruber, M.; Faber, C. (Frontiers in Microbiology, 2020)
Animal models of Staphylococcus aureus infective endocarditis (IE), especially in rodents, are commonly used to investigate the underlying pathogenesis, disease progression, potential diagnostic approaches, and therapeutic treatment. All these models are based on surgical interventions, and imply valve trauma by placing a polyurethane catheter at the aortic root. While the influence of endothelial damage and inflammation on the induction of IE has been studied intensively, the role of the catheter, as permanent source of bacteremia, and the interplay with bacterial virulence factors during the formation of IE is poorly understood. In our study, we aimed at identifying which set of preconditions is required for induction and formation of IE: (1) tissue injury, (2) permanent presence of bacteria, and (3) presence of the full bacterial repertoire of adhesion proteins. We investigated the manifestation of the disease in different modifications of the animal model, considering different degrees of endothelial damage and the presence or absence of the catheter. In four infection models the induction of IE was assessed by using two bacterial strains with different expression patterns of virulence factors – S. aureus 6850 and Newman. In vivo magnetic resonance imaging showed conspicuous morphological structures on the aortic valves, when an endothelial damage and a continuous bacterial source were present simultaneously. Cellular and inflammatory pathophysiology were characterized additionally by histology, real-time quantitative polymerase chain reaction analysis, and bacterial counts, revealing strain-specific pathogenesis and manifestation of IE, crucially influenced by bacterial adherence and toxicity. The severity of IE was dependent on the degree of endothelial irritation. However, even severe endothelial damage in the absence of a permanent bacterial source resulted in reduced valve infection. The spread of bacteria to other organs was also dependent on the pathogenic profile of the infectious agent. © Copyright © 2020 Schwarz, Hoerr, Töre, Hösker, Hansen, Van de Vyver, Niemann, Kuhlmann, Jeibmann, Wildgruber and Faber.
Keywords: endocarditis; foreign body; mouse model; MRI; Staphylococcus aureus

A case of ultrasound diagnosis of retroperitoneal lesion caused by unnoticed foreign body ingestion - Tynecki, W.; Tynecki, A.; Grobelna, A.; Baranowski, T.; Siemiaszko, G.; Łapiński, T.; Wilczek, J. (Journal of Ultrasonography, 2020)
We report the case of a 52-year-old patient who was initially admitted to the District Hospital’s Surgery Ward with strong abdominal pain. The patient’s medical history before the hospitalization was unremarkable. The man did not recall any worrisome situations before the onset of pain. During the hospital stay, he underwent an ultrasound scan, computed tomography and magnetic resonance imaging evaluations, and laboratory tests suggesting that para-duodenal abscess or gastrointestinal stromal tumor should be considered. The patient was referred to the provincial hospital in order to undergo endoscopic ultrasonography. This was when a retroperitoneal foreign body, a toothpick, was found and removed. © Polish Ultrasound Society.
Keywords: Foreign body ingestion; Gastric perforation; Toothpick

Clinical Analysis of Denture Impaction in the Esophagus of Adults - Wang, F.; Yang, N.; Wang, Z.; Guo, X.; Hui, L. (Dysphagia, 2020)
Denture impacted in the esophagus of adults has been a complex foreign body for otolaryngologists. We reviewed clinical characteristics, diagnosis, and treatment of these patients and evaluated computed tomography (CT) scans to identify a better method of dealing with such tricky situations. Twenty-nine patients who underwent rigid esophagoscopy were included in this retrospective study conducted at the University hospital. The patients underwent preoperative tests and examinations, including complete blood count, blood type and coagulation, electrocardiogram, and CT. The commonest symptoms were retrosternal pain, dysphagia, and odynophagia. Duration of the foreign body impacted within 24 h was 65.5%. CT findings revealed that 4 of 24 cases had complications in the upper esophagus, with 3 of the 4 cases in the mid-esophagus and 1 in the lower esophagus. Complications were related to the duration and location of the obstruction (P < 0.05). The location and complications based on CT findings were coherent with rigid esophagoscopy findings. Denture impaction in the esophagus can be fatal. Early intervention is crucial for prognosis. CT is used for diagnosing and guiding doctors in managing. The commonest location of impacted dentures was the upper esophagus with a lower incidence of complications. The incidence of an impacted denture in the mid-esophagus was low but with a high risk of complications. The incidence of an impacted denture in the lower esophagus was rare. Surgery and proper treatment ensure a good prognosis. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Computed tomography (CT); Deglutition; Deglutition disorders; Dentures; Foreign body; Rigid esophagoscopy

Comparison of Mechanical Characteristics of Commonly Used Vaginal Packing Materials - Azadi, A.; Pinhasov, K.; Ware, K.; Marchand, G.J.; Ostergard, D.R. (Surgical technology international, 2020)
INTRODUCTION: Clinically, vaginal packing provides the benefit of hemostasis and is designed to prevent the formation of postoperative hematomas. Despite the common use of vaginal packing in pelvic surgery, there is limited data to indicate which material has the ideal characteristics for vaginal packing. MATERIALS AND METHODS: Three packing materials were used: DeRoyal® Fluftex™ (DeRoyal Industries, Inc., Powell, Tennessee), NHP Surgi-Pak™ vaginal packing (NHP Industries, Inc., City of Industry, California), and Curad® Plain Packing Strips (Medline Industries, Inc., Northfield, Illinois). A fluid with similar viscosity to human blood, defibrinated sheep's blood (Remel Laboratories, Nenexa Kansas) was used to saturate the materials. The primary outcome was the amount of fluid absorbance of each product in both the handpacked and unpacked state. The number of drops used to saturate each material were counted and converted to mL/g. Each product was tested three times and the results were measured by counting the number of drops needed to saturate the material in each experiment. Experiment: Three materials were obtained and conducted into two different experiments to test absorbance. The packed trial consisted of 0.1g of material and was compacted in a 146mm standard Pasteur pipette (Sigma-Aldrich Corp., St. Louis, Missouri). Droplets of sheep's blood were dispensed until each material had reached its capacity, which was determined by counting the last sequential drop received onto the respective material before the first of the fluid fell from the material into the collecting container. Trials were conducted three times per material and an average of the three trials was calculated. The second experiment tested 1g of each material unpacked and folded into eight layers. Droplets of blood were placed onto the material until each material leaked, which was defined again as the first fluid to fall from the material into the collecting container that it was suspended above. The number of drops needed to produce this effect was recorded. All droplets were counted and converted to mL/g. Standard deviation was calculated for each material in both experiments and an analysis of variance (ANOVA) single factor test was done. RESULTS: Three trials were conducted per material and there was a difference in absorbance between each packing material (p=0.02 packed, p=0.001 unpacked). Additionally, the plain packing strip absorbed the least amount of blood product in the packed and unpacked state compared to DeRoyal® Fluftex™ and NHP Surgi-Pak™ vaginal packing. The average absorbance of the packed materials was 7.7mL/g for DeRoyal® Fluftex™, 9.8mL/g for NHP Surgi-Pak™ vaginal packing, and 7.5mL/g for the Curad® Plain Packing Strips. There was a standard deviation of 2.08 drops for DeRoyal® Fluftex™, 3.51 drops for NHP Surgi-Pak™ vaginal packing, and 1.73 drops for Curad® Plain Packing Strips. Absorbance for DeRoyal® Fluftex™ unpacked was 8.2mL/g, NHP Surgi-Pak™ vaginal packing unpacked was 7.00mL/g, and Curad® Plain Packing Strips was 4.8mL/g. The standard deviation for the unpacked experiment was 29.02 drops for DeRoyal® Fluftex™, 13.61 drops for NHP Surgi-Pak™ vaginal packing, and 15.59 drops for Curad® Plain Packing Strips. A p-value of less than .05 in a confidence interval of 95% was determined. CONCLUSION: Even though there are studies showing the clinical benefits of vaginal packing after a variety of gynecological surgeries, there is less known about the characteristics of the ideal material. Minimal foreign body reaction, decreased adherence to surgical scars, X-ray visualization, low cost, and easy availability are among the ideal characteristics of the presumed ideal material used for vaginal packing. In this study, we compared the absorbance between three commonly used materials and did not find any statistical differences. Further studies are needed to show the clinical benefits and mechanical characteristics of material used for vaginal packing. Due to the lack of a statistically significant difference in absorbance between the materials, evaluation of mechanical characteristics may be beneficial in determining an ideal vaginal packing product.

Inferior Vena Cava Filter Migration to the Left Internal Iliac Vein - Chen, L.; Zhang, J.; Yang, Z. (Annals of Vascular Surgery, 2020)
Inferior vena cava filter placement is an important method for managing deep venous thrombosis of the lower extremities and has a high risk of pulmonary embolism. Filter migration is rare but potentially fatal. We describe a case of migration of an inferior vena cava filter to the left internal iliac vein. The filter perforated the internal iliac vein, resulting in hemorrhagic shock, and was removed with open surgery. To our knowledge, this is the first reported case of migration of an inferior vena cava filter to an internal iliac vein. © 2019

Comparison of mechanical characteristics of commonly used vaginal packing materials - Azadi, A.; Pinhasov, K.; Ware, K.; Marchand, G.J.; Ostergard, D.R. (Surgical Technology International, 2020)
Introduction: Clinically, vaginal packing provides the benefit of hemostasis and is designed to prevent the for-mation of postoperative hematomas. Despite the common use of vaginal packing in pelvic surgery, there is lim-ited data to indicate which material has the ideal characteristics for vaginal packing. Materials and Methods: Three packing materials were used: DeRoyal® Fluftex™ (DeRoyal Industries, Inc., Powell, Tennessee), NHP Surgi-Pak™ vaginal packing (NHP Industries, Inc., City of Industry, California), and Curad® Plain Packing Strips (Medline Industries, Inc., Northfield, Illinois). A fluid with similar viscosity to human blood, defibrinated sheep’s blood (Remel Laboratories, Nenexa Kansas) was used to saturate the materials. The primary outcome was the amount of fluid absorbance of each product in both the handpacked and unpacked state. The number of drops used to saturate each material were counted and converted to mL/g. Each product was tested three times and the results were measured by counting the number of drops needed to saturate the material in each experiment. Experiment: Three materials were obtained and conducted into two different experiments to test absorbance. The packed trial consisted of 0.1g of material and was compacted in a 146mm standard Pasteur pipette (Sigma-Aldrich Corp., St. Louis, Missouri). Droplets of sheep’s blood were dispensed until each material had reached its capacity, which was determined by counting the last sequential drop received onto the respective material before the first of the fluid fell from the material into the collecting container. Trials were conducted three times per material and an average of the three trials was calculated. The second experiment tested 1g of each material unpacked and folded into eight layers. Droplets of blood were placed onto the material until each material leaked, which was defined again as the first fluid to fall from the material into the collecting container that it was suspended above. The number of drops needed to produce this effect was recorded. All droplets were counted and converted to mL/g. Standard deviation was calculated for each material in both experiments and an analysis of variance (ANOVA) single factor test was done. Results: Three trials were conducted per material and there was a difference in absorbance between each packing material (p=0.02 packed, p=0.001 unpacked). Additionally, the plain packing strip absorbed the least amount of blood product in the packed and unpacked state compared to DeRoyal® Fluftex™ and NHP Surgi-Pak™ vaginal packing. The average absorbance of the packed materials was 7.7mL/g for DeRoyal® Fluftex™, 9.8mL/g for NHP Surgi-Pak™ vaginal packing, and 7.5mL/g for the Curad® Plain Packing Strips. There was a standard deviation of 2.08 drops for DeRoyal® Fluftex™, 3.51 drops for NHP Surgi-Pak™ vaginal packing, and 1.73 drops for Curad® Plain Packing Strips. Absorbance for DeRoyal® Fluftex™ unpacked was 8.2mL/g, NHP Surgi-Pak™ vaginal packing unpacked was 7.00mL/g, and Curad® Plain Packing Strips was 4.8mL/g. The standard deviation for the unpacked experiment was 29.02 drops for DeRoyal® Fluftex™, 13.61 drops for NHP Surgi-Pak™ vaginal packing, and 15.59 drops for Curad® Plain Packing Strips. A p-value of less than .05 in a confidence interval of 95% was determined. Conclusion: Even though there are studies showing the clinical benefits of vaginal packing after a variety of gynecological surgeries, there is less known about the characteristics of the ideal material. Minimal foreign body reaction, decreased adherence to surgical scars, X-ray visualization, low cost, and easy availability are among the ideal characteristics of the presumed ideal material used for vaginal packing. In this study, we compared the absorbance between three commonly used materials and did not find any statistical differences. Further studies are needed to show the clinical benefits and mechanical characteristics of material used for vaginal packing. Due to the lack of a statistically significant difference in absorbance between the materials, evaluation of mechanical characteristics may be beneficial in determining an ideal vaginal packing product. © 2020 Surgical Technology International™.

Endoscopic combined intrarenal surgery in the prone-split leg position for successful single session removal of an encrusted ureteral stent: A case report - Wang, D.; Sun, H.; Chen, L.; Liu, Z.; Zhang, D.; Yu, D.; Ding, D. (BMC Urology, 2020)
Background: The most serious complication of ureter stent is long-term retention of ureteral stent and stone formation around the stent. Case presentation: A 51-year old female patient with left ureteral stent placed 2 years before developed both pyelic and vesical stones on the two ends of the double J was admitted to our hospital. Intravesical lithotripsy, retrograde ureteroscopy, and percutaneous nephrolithotripsy were performed with the patient in the prone split-leg position. All the stones and the ureteral stent were successfully removed in a single session. Conclusions: Combined endoscopic techniques in the prone split-leg position can effectively and safely manage severely encrusted stents. © 2020 The Author(s).
Keywords: Encrusted ureteral stent; Endoscopic combined intrarenal surgery; Prone-split leg position

A qualitative content analysis of retained surgical items: Learning from root cause analysis investigations - Hibbert, P.D.; Thomas, M.J.W.; Deakin, A.; Runciman, W.B.; Carson-Stevens, A.; Braithwaite, J. (International Journal for Quality in Health Care, 2020)
Objective: To describe incidents of retained surgical items, including their characteristics and the circumstances in which they occur. Design: A qualitative content analysis of root cause analysis investigation reports. Setting: Public health services in Victoria, Australia, 2010-2015. Participants: Incidents of retained surgical items as described by 31 root cause analysis investigation reports. Main Outcome Measure(s): The type of retained surgical item, the length of time between the item being retained and detected and qualitative descriptors of the contributing factors and the circumstances in which the retained surgical items occurred. Results: Surgical packs, drain tubes and vascular devices comprised 68% (21/31) of the retained surgical items. Nearly one-quarter of the retained surgical items were detected either immediately in the post-operative period or on the day of the procedure (7/31). However, about one-sixth (5/31) were only detected after 6 months, with the longest period being 18 months. Contributing factors included complex or multistage surgery; the use of packs not specific to the purpose of the surgery; and design features of the surgical items. Conclusion: Retained drains occurred in the post-operative phase where surgical counts are not applicable and clinician situational awareness may not be as great. Root cause analysis investigation reports can be a valuable means of characterizing infrequently occurring adverse events such as retained surgical items. They may detect incidents that are not detected by other data collections and can inform the design enhancements and development of technologies to reduce the impact of retained surgical items. © The Author(s) 2020. Published by Oxford University Press in association with the International Society for Quality in Health Care. All rights reserved.
Keywords: Enablers; Healthcare teams; Psychological safety

Traumatic endophthalmitis and the outcome after vitrectomy in young children - Zhou, Y.-L.; Wang, Y.-X.; Yao, T.-T.; Yang, Y.; Wang, Z.-Y. (International Journal of Ophthalmology, 2020)
AIM: To explore the traumatic endophthalmitis in young children and the outcome of pars plana vitrectomy (PPV). METHODS: Twenty-two eyes of 22 cases of young children consecutive pediatric traumatic endophthalmitis treated and followed up between September 2014 and May 2018 were included. Aqueous humor or vitreous samples were taken for bacterial culture and sensitivity tests. Intravitreal antibiotics (norvancomycin and ceftazidime) injection, combined with 23-gauge PPV, were administered in 22 eyes. Silicone oil (SO; 5000 centistoke) tamponade or perfluoropropane gas (C3F8) was used in all patients. Main outcome measures were best-corrected visual acuity (BCVA) and retinal attachment, the ratio of penetrating injury, and the existence of intraocular foreign body. RESULTS: The mean age of patients was 6.9±2.2 (range, 3-10)y. All injured eyes suffered from penetrating ocular injury with retained intraocular foreign body in one eye. Bacterial culture was positive in only 2 eyes. The mean follow-up time was 21.1±4.7 (range, 12-30)mo. In the primary PPV, intravitreal antibiotics was administrated in all eyes, SO in 18 eyes, and C3F8 in 4 eyes. The secondary operation of SO removal and C3F8 endotamponade was performed in 16 eyes and a second SO endotamponade due to emulsification of the oil and retinal detachment (RD) was operated in 7 eyes underwent 3 to 11.5mo after primary PPV. A third operation was done in 7 eyes. The final intraocular pressure (IOP) was 8.9±1.8 (range, 6.9-11.4) mm Hg. The final BCVAs were 20/200 or better in 5, counting fingers in 2, and light perception to hand movement in 8 eyes. Whose (66.7%) had retinal injury exhibited worse BCVA (P=0.019, Fisher's exact test). Eyes underwent SO tamponade exhibited worse final BCVA than that with C3F8 in the primary PPV (P=0.026, Fisher's exact test). CONCLUSION: Traumatic endophthalmitis in children is generally more severe and associated with more complicated surgical procedures. Most patients have retinal injury need multiple operations and the final BCVA is poor. Prevention of ocular trauma, especially in children, is still critical. © 2020 International Journal of Ophthalmology (c/o Editorial Office). All rights reserved.
Keywords: Pars plana vitrectomy; Pediatric; Penetrating eye injury; Traumatic endophthalmitis

No Surgical Items Left Behind: A Multidisciplinary Approach to the Surgical Count Process - Kertesz, L.; Cordella, C.M.; Nadera, N.M.; Nelson, P.E.; Kahil, M.; Shim, S.-H.; Holtzman, J.S. (Journal of Radiology Nursing, 2020)
The counting process is designed to prevent retained foreign bodies while providing optimal perioperative patient safety. Intraoperative distractions are prevalent and potentially contribute to patient safety risks. Counting is an important preventative measure that is a human process prone to error, especially in this busy environment where multiple things are happening simultaneously. We sought to evaluate the impact of distractions during the count process on patient safety. Trained, nationally certified registered nurses used a validated tool to observe the number of interruptions that occurred during the count process in cardiac surgery. Observation included the key personnel that lead the count process including the scrub person, circulating nurse, attending surgeons, fellows, and residents of all disciplines. Observation included scheduled cases in the cardiac specialty for the adult population including all shifts (24 hours). The predictor in this study was distraction. The primary measure of distraction was the total number of distraction for each case. There are different distraction levels for each distraction. Thus, weighted distraction score for each case was created as the summation of distraction level and it is the secondary measure of distraction. To detect a medium effect size with 80% power at 0.05 level, we needed a minimum sample size of 54. We correlated the relationship between the number of interruptions observed and sequelae. Working together as a cohesive team to minimize interruptions can enhance patient safety and decrease additional workload across departments. © 2020
Keywords: Interruptions; Operating room; Retained foreign body; Surgical counts

An unusual case of nine cilia embedded in the retina after a perforating ocular injury - Ramos, G.Z.; Goncalves, T.B.; Bordon, A.F. (American Journal of Ophthalmology Case Reports, 2020)
Purpose: To report an extremely rare case involving a 41-year-old man with nine intraocular cilia embedded in the retina after a perforating ocular injury caused by a metal wire. This case is particularly rare because of the number and location of the cilia. Observations: The patient underwent an uneventful corneal suturing and extracapsular extraction of the damaged lens of his right eye. Intraocular foreign bodies were discovered following surgery and were removed at a later date. Following lens extraction and ocular repair, the patient's best-corrected visual acuity (BCVA) was counting fingers. Fundus examination during follow-up revealed several eyelashes embedded in the retina. Thirty-two days after the injury, the patient showed signs of ocular inflammation. Therefore, the patient underwent vitrectomy and intraocular foreign body removal. Nine cilia were embedded in the retina at the posterior perforation site. At the final follow-up visit, his BCVA was 20/25. Conclusion and importance: This report describes an unusual case where intraocular cilia were embedded in the retina after a perforating ocular injury. The eyelashes caused an intraocular inflammatory reaction that subsided after their removal. © 2020 The Authors
Keywords: Cilia; Ocular foreign body; Retina; Vitrectomy

Shiny Foreign Body in the Frontal Sinus Causing Epidural Abscess - Kim, J.S.; Kwon, S.H.; Lee, E.J. (Ear, Nose and Throat Journal, 2020)

Size matters—in vitro behaviour of human fibroblasts on textured silicone surfaces with different pore sizes - Tolksdorf, J.; Horch, R.E.; Grüner, J.S.; Schmid, R.; Kengelbach-Weigand, A.; Schubert, D.W.; Werner, S.; Schneidereit, D.; Friedrich, O.; Ludolph, I. (Journal of Materials Science: Materials in Medicine, 2020)
Capsular contracture remains a challenge in plastic surgery and represents one of the most common postoperative complications following alloplastic breast reconstruction. The impact of the surface structure of silicone implants on the foreign body reaction and the behaviour of connective tissue-producing cells has already been discussed. The aim of this study was to investigate different pore sizes of silicone surfaces and their influence on human fibroblasts in an in vitro model. Four different textures (no, fine, medium and coarse texture) produced with the salt-loss technique, have been assessed in an in vitro model. Human fibroblasts were seeded onto silicone sheets and evaluated after 1, 4 and 7 days microscopically, with viability assay and gene expression analysis. Comparing the growth behaviour and adhesion of the fibroblasts on the four different textures, a dense cell layer, good adhesion and bridge-building ability of the cells could be observed for the fine and medium texture. Cell number and viability of the cells were increasing during the time course of experiments on every texture. TGFß1 was lowest expressed on the fine and medium texture indicating a trend for decreased fibrotic activity. For silicone surfaces produced with the salt-loss technique, we were able to show an antifibrotic effect of smaller sized pores. These findings underline the hypothesis of a key role of the implant surface and the pore size and pore structure in preventing capsular contracture. © 2020, The Author(s).

In Vivo Comparison of MONOFIX, A Novel Barbed Suture with a Triangular Stopper, with Pre-existing Products in a Porcine Model - Kim, J.; Eom, H.J.; Shin, H.; Jeong, S.Y.; Kim, M.S.; Yoon, H.S.; In, C.H.; Kim, B.-G.; Bae, D.-S.; Lee, J.-W. (Journal of Minimally Invasive Gynecology, 2020)
Study Objective: MONOFIX, a new absorbable barbed suture device, has a triangular stopper at the end to hold the suture to the tissue without hooking the looped end or knotting. The aim of this study was to compare the biomechanical strength and histologic features of MONOFIX with other barbed suture devices using a porcine model. Design: Well-designed, controlled trial without randomization. Setting: Animal laboratory in university hospital. Subjects: Sixteen, 60-kg, mature female domestic pigs (skin closure group) and 5, 60-kg, mature female domestic pigs (fascial closure group). Interventions: In the skin closure group, 3-0 MONOFIX versus 2 widely used 3-0 absorbable barbed sutures (3-0 V-Loc 180 or Stratafix). In the fascial closure group, 2-0 MONOFIX versus 1 widely used 2-0 absorbable barbed sutures (2-0 Stratafix). Measurements and Main Results: In the skin closure group, the biomechanical wound strength of skin sutured with size 3-0 MONOFIX, V-Loc 180, or Stratafix was evaluated by postoperative day assessment (days 0, 3, 7, 14, and 28). In the fascial closure group, pigs underwent 2 paramedian incisions and were sutured with 2-0 MONOFIX or with 2-0 Stratafix to evaluate histologic reaction. At 6 weeks the tissues around the suture line were excised and microscopically evaluated. The biomechanical strength of the MONOFIX had similar tissue tensile strength compared with the control, regardless of postoperative day. In the fascial closure model, there was no significant difference in the average tissue reaction score between MONOFIX and Stratafix (1.2 ±.3 vs 1.3 ±.3, p = .478). Conclusion: This study demonstrated that MONOFIX has equivalent tensile strength and histologic reaction when compared with commonly used barbed suture devices. Accordingly, this preclinical study suggests that the use of MONOFIX is a safe alternative to other barbed suture devices. © 2019
Keywords: Barbed suture; Biomechanics; Histology; In vivo; Laparoscopic surgery

Intra-abdominal Gossypibomas: Clinical Manifestations, Risk Factors and Prevention - Iype, G.R.; Samarasam, I.; Senthilnathan, K.; Yacob, M.; Abraham, V.P. (Indian Journal of Surgery, 2020)
Gossypibomas are masses formed by accidentally retained cotton matrix anywhere in the body, following a surgical procedure. It has catastrophic effects not only on patients but also on the health professionals and health care providers. We have retrospectively reviewed 6 patients of intra-abdominal gossypibomas who had presented over a 10-year period, to our centre. The relevant preoperative and intraoperative details along with the clinical course of these patients have been described. Through the management of these patients, we have shared our experience in relation to the clinical presentations, probable risk factors, and radiological features for diagnosis and treatment, along with the ethical and medicolegal implications of the issue. The safety measures that exist are also reviewed. An intraoperative “correct count” during a surgical operation does not always exclude the possibility of a gossypiboma or a retained foreign body. Increased awareness, familiarity with the existing local protocols, and strict adherence of these protocols, along with open communication, are essential in minimizing the frequency of such events. A concerted effort by the entire surgical team is crucial. Newer technology such as barcoding of sponges and radiofrequency identification (RFID) tagging may help decrease the occurrence of this problem. © 2020, Association of Surgeons of India.
Keywords: Gossypiboma; Retained surgical items; Retained surgical sponge; Textiloma

Gossypiboma: A Case Series and Literature Review - Alemu, B.N.; Tiruneh, A.G. (Ethiopian journal of health sciences, 2020)
Background: Gossypiboma (retained surgical sponge) is a rare medical event. It could cause a serious complication that can threaten patients' life. Its diagnosis is usually difficult because the clinical symptoms are nonspecific and the imaging findings are often inconclusive. Case Presentations: We present two cases, a 32 years old woman who passed a retained surgical sponge via rectum 5 months after cesarean section and a 30 years old lady presented with an acute abdomen that later found to have localized right lower quadrant abscess with a retained surgical sponge. Conclusion: The most important approach to reduce the incidence of gossypiboma is prevention. At the end of the surgery, a correct count is always the gold standard safeguard against it. Although errors are not to be completely avoided, continuous CPD and strict adherence to rules of the operating room will reduce its incidence to a minimum. © 2020 Berhanu N.A., et al.
Keywords: abdominal abscess; foreign body; Gossypiboma; retained surgical sponge

Can a detached DSAEK donor lenticule still work? - Farooqui, J.H.; Kapur, N.; Jha, U.P.; Patel, N.V.; Mathur, U. (Journal Francais d'Ophtalmologie, 2020)

Rupture of an infected iliac artery pseudoaneurysm caused by asymptomatic gastrointestinal foreign body perforation - Lun, Y.; Jiang, H.; Xin, S.; Zhang, J. (Journal of International Medical Research, 2020)
We report a unique case of a ruptured iliac artery pseudoaneurysm caused by asymptomatic gastrointestinal perforation and retroperitoneal abscess formation. A 46-year-old man presented to the Emergency Department of our institution. Angiography showed a ruptured iliac artery pseudoaneurysm caused by retroperitoneal abscess formation. After endovascular repair and surgical drainage, the cause of the abscess was finally identified as a toothpick. Findings from this case show that asymptomatic gastrointestinal foreign body perforation can be a rare, but insidious, cause of an infected pseudoaneurysm. Prompt surgical intervention is sometimes necessary when treating patients with arterial pseudoaneurysm caused by a perivascular abscess. © The Author(s) 2020.
Keywords: abscess; foreign body; gastrointestinal; infection; perforation; Pseudoaneurysm

The inflammatory and foreign body reaction of polymethyl methacrylate glaucoma drainage device in the rabbit eye - Oktariana Asrory, V.D.; Sitompul, R.; Artini, W.; Estuningsih, S.; Noviana, D.; Morgan, W.H. (Translational Vision Science and Technology, 2020)
Purpose: To assess the safety and tissue response of a polymethyl methacrylate (PMMA) glaucoma drainage device (GDD) in the rabbit eye. Methods: Specially constructed PMMA GDD devices were implanted into rabbit eyes and evaluated histopathologically following euthanasia on days 5, 30, and 60 after implantation surgery. Hematoxylin-eosin, Masson’s trichrome, and periodic acid-Schiff were used to stain tissue specimens dissected from the surgical site. Inflammatory cell count and capsule thickness measurements were performed. Results: Three rabbits were sacrificed on day 5, 3 on day 30, and 4 on day 60. Macrophage and lymphocyte counts increased from day 5 to day 30 then decreased (P = 0.0000) with greater counts seen in the superior regions. At day 30, a fibrous capsule had formed around the plate area. Fibroblast counts increased significantly between day 5 to day 30 and again to day 60 (P = 0.001) with greatest numbers anteriorly. The inferior capsule thickness at day 60 was 243 μm (standard deviation, 120; 95% confidence interval: 53-433). The superior capsule thickness was 388 μm (standard deviation, 136; 95% confidence interval: 172-604). No adverse reactions were seen. Conclusions: Histopathologically, the inflammatory response toward this PMMA glaucoma drainage device was comparable to other reported GDDs. No accentuated response or adverse event was seen suggesting that PMMA may be useful as a GDD material. Translational Relevance: An affordable, locally built GDD is needed in Indonesia because of the high prevalence of severe glaucoma. This rabbit study is a significant step toward justifying the use of PMMA as a GDD material. PMMA is cheap and easily manufactured and sterilized in developing economies. © 2020, Association for Research in Vision and Ophthalmology Inc.. All rights reserved.
Keywords: Foreign body reaction; Glaucoma drainage device; Inflammatory reaction; Polymethyl methacrylate

Recognising eosinophilic oesophagitis as a cause of food bolus obstruction - Ntuli, Y.; Bough, I.; Wilson, M. (Frontline Gastroenterology, 2020)
Eosinophilic oesophagitis (EoE) is a chronic, inflammatory condition of the oesophagus, characterised by intermittent dysphagia, food bolus obstruction (FBO) and histologically proven, eosinophil-mediated inflammation. EoE is identified in up to 50% of FBO presentations. To evaluate the management of patients presenting with FBO to our centre against current clinical guidelines. Design A retrospective analysis of acute FBO was performed between January 2008 and August 2014. Patients were identified using the ICD 10 code T18.1, foreign body in oesophagus' in their electronic discharge document. Data were collected on admitting specialty, previous FBO, endoscopy findings, biopsy sites and findings, eosinophil count and diagnosis of EoE. Results 310 acute episodes of FBO were included in the final study cohort. 202 (65.2%) flexible oesophagogastroduodenoscopies (OGDs) were performed, with 50 (34.5%) of those occurring in those admitted under ENT (n=145), versus 28 (93.3%) and 124 (91.9%) in general medicine (n=30) and surgery (n=135), respectively. 80 (39.6%) had oesophageal biopsies taken, and 21 novel diagnoses of EoE were made (26.3% biopsy-proven rate). Five (23.8%) of the novel diagnoses had a formal eosinophil count included in the histopathology report, and eight (38.1%) had up to three previous OGDs that had not diagnosed their condition of EoE. Conclusion Our study highlights wide variation in adherence to the guidelines for the management of FBO depending on admitting specialty. We advocate an FBO protocol involving single specialty management, flexible OGD, ≥6 biopsies from the upper and lower oesophagus, and standardisation of oesophageal biopsy reports with a formal eosinophil count. © Author(s) (or their employer(s)) 2020. No commercial re-use. See rights and permissions. Published by BMJ.
Keywords: dysphagia; eosinophilic oesophagitis; food bolus

Laparoscopic treatment of right colic flexure perforation by an ingested wooden toothpick - Casoni Pattacini, G.; Pecchini, F.; Mullineris, B.; De Maria, R.; Trapani, V.; Francescato, A.; Piccoli, M. (International Journal of Surgery Case Reports, 2020)
Introduction: Ingestion of a toothpick, both accidentally and intentionally, is a rare event. Presentation of case: We present the case of a 42-years old man who was admitted to the emergency department at our Institution presenting with a 5-days history of right sided abdominal pain. Laboratory blood count reported leukocytosis and alteration of principal inflammation index; at the abdominal ultrasound no signs of perforation or collection were described. Discussion: Indication to surgery was posed and an explorative laparoscopy was performed. The presence of local peritonitis at the right colonic flexure secondary to a full thickness bowel perforation caused by a toothpick was found. There was also an acute phlegmonous appendicitis. A laparoscopic appendectomy and a full-thickness double running suture of the perforation were performed. Conclusion: Awareness about dangers of ingested toothpicks needs to be taken and the intestinal track/trace of the toothpick is mandatory until its expulsion. © 2020
Keywords: Foreign bodies; Laparoscopic suture; Wooden toothpick

Intrathoracic gossypiboma: An overlooked entity - Othman, S.A.; Alsafwani, J.Q.; Alsahwan, A.G.; Aljehani, Y. (American Journal of Case Reports, 2020)
Objective: Rare disease Background: During any surgical procedure, there are several factors that may lead to morbidity and mortality. One of those factors is a retained cotton or gauze surgical sponge inadvertently left in the body during an operation, known as gossypiboma. This clinical oversight may cause serious postoperative complications and increase the risk of mortality, particularly if left undiscovered. Furthermore, this issue adds to the economic burden on healthcare systems by increasing the rate of reoperation and rehospitalization. The length of postoperative gossypiboma diagnosis varies greatly, as patients may either present acutely with symptoms such as a palpable mass, pain, nausea, and vomiting, or remain asymptomatic for several years. Case Report: We report the case of a 48-year-old man who underwent a thoracotomy after a road traffic accident. The resulting empyema led to the intraoperative discovery of an intrathoracic gossypiboma, which was initially interpreted radiologically as a part of the previous surgical staple line. The causative agent was discovered by the team’s nurses during the postsurgical count of instruments and sponges, and who were alerted to a recovered sponge differing in appearance from the sponges used for that procedure. Conclusions: In general, proper counting and adherence to the World Health Organization ‘Surgical Safety Checklist’ can greatly improve the outcome of any surgery. The diagnosis of gossypiboma is often late or missed entirely and leads to additional interventions that can be avoided or detected early when the material contains a radiopaque marker. In cases under suspicion of any mistakenly left object, the use of intraoperative radiology before skin closure is highly recommended to prevent postoperative complications for the patient and organization. © Am J Case Rep, 2020.
Keywords: Empyema; Gossypium; Thoracotomy

Difluprednate 0.05% versus prednisolone acetate post-phacoemulsification for inflammation and pain: An efficacy and safety clinical trial - Palacio-Pastrana, C.; Mondragón, E.C.; Soto-Gómez, A.; Suárez-Velasco, R.; Montes-Salcedo, M.; de Ortega, L.F.; Nasser-Nasser, L.; Baiza-Durán, L.; Olvera-Montaño, O.; Muñoz-Villegas, P. (Clinical Ophthalmology, 2020)
Background: The purpose of this study was to compare the efficacy and safety of difluprednate 0.05% (PRO-145) versus prednisolone acetate 1% (Prednefrin® SF), for management of postoperative inflammation and pain, after cataract surgery. Methods: This was a Phase III, multicenter, prospective, double-blind, clinical trial. Intentto-treat population included 178 post-phacoemulsification patients that were assigned to receive either PRO-145, or prednisolone. One day after unilateral eye surgery, patients instilled a drop 4 times a day for 14 days (then tapering the dose downward for 14 days). The primary efficacy endpoints were anterior chamber (AC) cell grade and flare. Other parameters measured included: retinal central thickness (measured via OCT), conjunctival hyperemia, edema, pain and photophobia. Tolerability and safety were assessed through burning, itching, foreign body sensation, visual acuity (VA), intraocular pressure (IOP) and incidence of adverse events (AE). Results: A total of 171 subjects were randomized (1:1) and completed the study. Compared to day 1, there was a significant improvement in the AC cell count and flare in both groups by the final visit (80.2% vs 88.4%, p=1.000). Conjunctival hyperemia improved in a similar fashion (81.2% vs 79%, p=0.234) in both PRO-145 and prednisolone groups, without differences between them. This was also observed for edema (82.4% vs 82.5%, p=0.246), pain (15.3% vs 7%, p=0.497) and photophobia (16.4% vs 15.1%, p=0.246), respectively. There was no significant difference between treatments for any tolerability parameter studied. Finally, at the 4-week postoperative visit, there were no significant differences between treatments for VA, IOP and AE results (p-values; 0.095, 0.053 and 0.099, respectively). Conclusion: The results of this study suggest that PRO-145 is as effective and safe as prednisolone acetate in treating postoperative inflammation and pain in patients undergoing phacoemulsification. The study was registered at ClinicalTrials.gov as NCT03693989. © 2020 Palacio-Pastrana et al.
Keywords: Cataract surgery; Difluprednate; Dose-reduction; Ophthalmic corticosteroids

Rotator cuff repair with biological graft augmentation causes adverse tissue outcomes - Rashid, M.S.; Smith, R.D.J.; Nagra, N.; Wheway, K.; Watkins, B.; Snelling, S.; Dakin, S.G.; Carr, A.J. (Acta Orthopaedica, 2020)
Background and purpose — Biological patches can be used to augment rotator cuff tendon repair in an attempt to improve healing and reduce rates of re-rupture. However, little is known about the in vivo tissue response to these patches. We assessed native rotator cuff tissue response after surgical repair and augmentation with 2 commercially available extracellular matrix (ECM) patches. Patients and methods — Patients underwent a rotator cuff repair augmented with either GraftJacket (Wright Medical), Permacol (Zimmer Biomet), or no patch (Control), applied using an onlay technique. A sample of supraspinatus tendon was collected intraoperatively and 4 weeks post-surgery, using ultrasound-guided biopsy. Histology and immunohistochemistry were performed on all samples. Results — The Permacol group (n = 3) and GraftJacket group (n = 4) demonstrated some changes in native tendon ECM compared with the control group (n = 3). Significant disruption of the extracellular matrix of the repaired native supraspinatus, underlying both patches, was observed. The patches did not generally increase cellularity, foreign body giant cell count, or vascularity compared to the control group. 1 patient in the Permacol group had an adverse tissue immune response characterized by extensive infiltration of IRF5+, CD68+, and CD206+ cells, suggesting involvement of macrophages with a pro-inflammatory phenotype. No significant differences in protein expression of CD4, CD45, CD68, CD206, BMP7, IRF5, TGFβ, and PDPN were observed among the groups. Interpretation — Histological and immunohistochemical analysis of native tendon tissue after patch augmentation in rotator cuff repair raises some concerns about a lack of benefit and potential for harm from these materials. © 2020, © 2020 The Author(s). Published by Taylor & Francis on behalf of the Nordic Orthopedic Federation.

Long term comparative evaluation of two types of absorbable meshes in partial abdominal wall defects: an experimental study in rabbits - Pascual, G.; Rodríguez, M.; Pérez-Köhler, B.; Benito-Martínez, S.; Calvo, B.; García-Moreno, F.; Bellón, J.M. (Hernia, 2020)
Purpose: Synthetic prosthetic materials that are fully absorbable seek to reduce the host foreign body reaction and promote host tissue regeneration. This preclinical trial was designed to analyse, in the long term, the behaviour of two prosthetic meshes, one synthetic and one composed of porcine collagen, in abdominal wall reconstruction. Methods: Partial defects were created in the abdominal walls of New Zealand rabbits and repaired using a synthetic absorbable mesh (Phasix™) or a non-crosslinked collagen bioprosthesis (Protexa™). After 3, 6, 12 and 18 months, specimens were recovered for light microscopy and collagen expression analysis to examine new host tissue incorporation, macrophage response and biomechanical strength. Results: Both materials showed good host tissue incorporation in line with their spatial structure. At 18 months postimplant, Protexa™ was highly reabsorbed while the biodegradation of Phasix™ was still incomplete. Collagenization of both materials was good. Macrophage counts steadily decreased over time in response to Phasix™, yet persisted in the collagen meshes. At 18 months, zones of loose tissue were observed at the implant site in the absence of herniation in both implant types. The stress–stretch behaviour of Phasix™ implants decreased over time, being more pronounced during the period of 12–18 months. Nevertheless, the abdominal wall repaired with Protexa™ became stiffer over time. Conclusion: Eighteen months after the implant both materials showed good compatibility but the biodegradation of Phasix™ and Protexa™ was incomplete. No signs of hernia were observed at 18 months with the stress–stretch relations being similar for both implants, regardless of the more compliant abdominal wall repaired with Protexa™ at short term. © 2020, Springer-Verlag France SAS, part of Springer Nature.
Keywords: Abdominal wall repair; Bioprostheses; Collagen mesh; Hernia repair; Mesh repair; Poly-4-hydroxybutyrate (P4HB)

Development of an abdominal wall abscess caused by fish bone ingestion: A case report - Kuwahara, K.; Mokuno, Y.; Matsubara, H.; Kaneko, H.; Shamoto, M.; Iyomasa, S. (Journal of Medical Case Reports, 2019)
Background: A small percentage of patients with foreign body ingestion develop complications, which have a variety of clinical presentations. Less than 1% of cases require surgical intervention. We present a patient with an abdominal wall abscess resulting from a fish bone that pierced the cecum. The patient was treated laparoscopically. Case presentation: A 55-year-old Japanese man presented to our hospital with a complaint of right lower abdominal pain. A physical examination revealed tenderness, swelling, and redness at the right iliac fossa. Computed tomography showed a low-density area with rim enhancement in his right internal oblique muscle and a hyperdense 20 mm-long pointed object in the wall of the adjacent cecum. Based on the findings we suspected an abdominal wall abscess resulting from a migrating ingested fish bone. He was administered antibiotics as conservative treatment, and the abscess was not seen on subsequent computed tomography. Two months after the initial treatment, he presented with the same symptoms, and a computed tomography scan showed the foreign body in the same location as before with the same low-density area. We diagnosed the low-density area as recurrence of the abdominal wall abscess. He underwent laparoscopic surgery to remove the foreign body. His appendix, and part of his cecum and the parietal peritoneum that included the foreign body, were resected. He had an uneventful postoperative course, and at 1 year after the surgery, the abdominal wall abscess had not recurred. Conclusions: An abdominal wall abscess developed in association with the migration of an ingested fish bone. We suggest that a laparoscopic surgical resection of the portion of the bowel that includes the foreign body is a useful option for selected cases. © 2019 The Author(s).
Keywords: Abdominal wall abscess; Fish bone; Foreign body ingestion; Laparoscopic surgery

Colon stenosis due to acute neonatal appendicitis in a preterm baby: a case report - Naito, T.; Teramen, H.; Hayashi, H.; Takegawa, M.; Sakamoto, H.; Shimada, T.; Ohno, K.; Yoshii, M. (BMC Pediatrics, 2019)
Background: Colon stenosis and acute appendicitis are rare diseases among premature babies. To the best of our knowledge, no study has identified both the conditions in preterm babies. Case presentation: Here we report a case of a preterm Japanese male baby who developed ascending colon stenosis and appendicitis. During his neonatal intensive care unit stay, he developed increasing apnea and vomiting with rapidly worsening abdominal distention. Contrast radiographs indicated colon stenosis. Emergent exploratory laparotomy revealed ascending colon stenosis with appendix adhesion; both the lesions were surgically resected. The pathological findings suggested that he had appendicitis several weeks prior to the surgery; the onset of colon lesion seemed later than that of appendix. The perforated appendix was covered by the ascending colon, and inflammatory reactions led to the narrowing of the intestinal lumen. Conclusions: Neonatal appendicitis and colon stenosis are both challenging for the diagnosis, and early laparotomy is necessary when these conditions are suspected. © 2019 The Author(s).
Keywords: Colon stenosis; Neonatal appendicitis; Preterm

BD-2 and BD-3 increase skin flap survival in a model of ischemia and Pseudomonas aeruginosa infection - Casal, D.; Iria, I.; Ramalho, J.S.; Alves, S.; Mota-Silva, E.; Mascarenhas-Lemos, L.; Pontinha, C.; Guadalupe-Cabral, M.; Ferreira-Silva, J.; Ferraz-Oliveira, M.; Vassilenko, V.; Goyri-O’Neill, J.; et al. (Scientific Reports, 2019)
The main aim of this work was to study the usefulness of human β-defensins 2 (BD-2) and 3 (BD-3), which are part of the innate immune system, in the treatment of infected ischemic skin flaps. We investigated the effect of transducing rat ischemic skin flaps with lentiviral vectors encoding human BD-2, BD-3, or both BD-2 and BD-3, to increase flap survival in the context of a P. aeruginosa infection associated with a foreign body. The secondary endpoints assessed were: bacterial counts, and biofilm formation on the surface of the foreign body. A local ischemic environment was created by producing arterialized venous flaps in the left epigastric region of rats. Flaps were intentionally infected by placing underneath them two catheters with 105 CFU of P. aeruginosa before the surgical wounds were hermetically closed. Flap biopsies were performed 3 and 7 days post-operatively, and the specimens submitted to immunohistochemical analysis for BD-2 and BD-3, as well as to bacterial quantification. Subsequently, the catheter segments were analyzed with scanning electron microscopy (SEM). Flaps transduced with BD-2 and BD-3 showed expression of these defensins and presented increased flap survival. Rats transduced with BD-3 presented a net reduction in the number of P. aeruginosa on the surface of the foreign body and lesser biofilm formation. © 2019, The Author(s).

Clinical observation of bronchoscopy alveolar lavage combined with thoracoscopy in the treatment of empyema in children - Yue, F.; Yang, Z.; Yang, F.; Liu, Y.; Zhao, L.; Chen, Z.; Gao, F. (Medicine (United States), 2019)
The objective of this study was to investigate the therapeutic effects of bronchoscopy alveolar lavage (BAL) combined with thoracoscopy in the treatment of empyema in children.Retrospectively analyzed 174 cases of pediatric empyema treated with thoracoscopy combined with BAL from January 2010 to December 2016 in our hospital. All the cases, according to admission order, were randomly divided into 2 groups, the control group (group A), which contained 89 cases, was treated with thoracoscopy; and the experimental group (group B), which contained 85 cases, was treated with BAL combined with thoracoscopy. The results of BAL treatment, the inflammatory indexes including body temperature, total leukocyte count in peripheral blood and CRP, and the therapeutic effect and prognosis including the days of antibiotic use, hospital stay, the incidence of thoracotomy and lobectomy were compared between the 2 groups.1.There was no significant difference in inflammatory indexes between the 2 groups: body temperature (oC), (39.06±0.047 and 39.08±0.050), P>.855; routine leukocyte count (10^9/L), (25.93±1.035 and 24.76±1.019), P>.425); C-reactive protein (mg/L), (128.7±6.653 and 138.6±7.53), P>.328.2.The results of BAL: hyperemia and edema was detected in trachea intima of all cases, including 32 cases of purulent secretion and ulcer, 21 cases of lumen deformation and 5 cases of foreign body.3.There were statistical significances in the curative effects of the control group and the experimental group: the duration of antibiotic use (days), (21.07±0.342 and 17.07±0.288), P<.0001); the average hospital stay (days), (22.91±0.347 and 18.79±0.287), P<.0001; secondary surgery (thoracotomy), 15 cases in the control group, 5 cases in the experimental group, P<.023; lung lobectomy (disability rate), 13 cases in the control group and 3 cases in the experimental group, P<.011.There was statistical difference in all the therapeutic indexes (P<.05).Bronchoscopy alveolar lavage combined with thoracoscopy has a higher success rate in the treatment of pediatric empyema, and is more comprehensive, safe and effective in controlling inflammation. Copyright © 2019 the Author(s). Published by Wolters Kluwer Health, Inc.
Keywords: bronchoscopy alveolar lavage; pediatric empyema; thoracoscopy; treatment

Acute obstructive cholangitis due to fishbone in the common bile duct: A case report and review of the literature - Yu, M.; Huang, B.; Lin, Y.; Nie, Y.; Zhou, Z.; Liu, S.; Hou, B. (BMC Gastroenterology, 2019)
Background: Choledocholithiasis is an endemic condition in the world. Although rare, foreign body migration with biliary complications needs to be considered in the differential diagnosis for patients presenting with typical symptoms even many years after cholecystectomy, EPCP, war-wound, foreign body ingestion or any other particular history before. It is of great clinical value as the present review may offer some help when dealing with choledocholithiasis caused by foreign bodies. Case presentation: We reported a case of choledocholithiasis caused by fishbone from choledochoduodenal anastomosis regurgitation. Moreover, we showed up all the instances of choledocholithiasis caused by foreign bodies published until June 2018 and wrote the world's first literature review of foreign bodies in the bile duct of 144 cases. The findings from this case suggest that the migration of fishbone can cause various consequences, one of these, as we reported here, is as a core of gallstone and a cause of choledocholithiasis. Conclusion: The literature review declared the choledocholithiasis caused by foreign bodies prefer the wrinkly and mainly comes from three parts: Postoperative complications, foreign body ingestion, and post-war complications such as bullet injury and shrapnel wound. The Jonckheere-Terpstra test indicated the ERCP was currently the treatment of choice. It is a very singular case of choledocholithiasis caused by fishbone, and the present review is the first one concerning choledocholithiasis caused by foreign bodies all over the world. © 2019 The Author(s).
Keywords: Choledocholithiasis; Common bile duct; Fishbone; Foreign body

Accumulations of von Willebrand factor within ECMO oxygenators: Potential indicator of coagulation abnormalities in critically ill patients? - Steiger, T.; Foltan, M.; Philipp, A.; Mueller, T.; Gruber, M.; Bredthauer, A.; Krenkel, L.; Birkenmaier, C.; Lehle, K. (Artificial Organs, 2019)
Clot formation within membrane oxygenators (MOs) remains a critical problem during extracorporeal membrane oxygenation (ECMO). The composition of the clots—in particular, the presence of von Willebrand factor (vWF)—may be an indicator for prevalent nonphysiological flow conditions, foreign body reactions, or coagulation abnormalities in critically ill patients. Mats of interwoven gas exchange fibers from randomly collected MOs (PLS, Maquet, Rastatt, Germany) of 21 patients were stained with antibodies (anti-vWF and anti-P-selectin) and counterstained with 4′,6-diamidino-2-phenylindole. The extent of vWF-loading was correlated with patient and technical data. While 12 MOs showed low vWF-loadings, 9 MOs showed high vWF-loading with highest accumulations close to crossing points of adjacent gas fibers. The presence and the extent of vWF-fibers/“cobwebs,” leukocytes, platelet–leukocyte aggregates (PLAs), and P-selectin-positive platelet aggregates were independent of the extent of vWF-loading. However, the highly loaded MOs were obtained from patients with a significantly elevated SOFA score, severe thrombocytopenia, and persistent liver dysfunction. The coagulation abnormalities of these critically ill patients may cause an accumulation of the highly thrombogenic and elongated high-molecular-weight vWF multimers in the plasma which will be trapped in the MOs during the ECMO therapy. © 2019 The Authors. Artificial Organs published by Wiley Periodicals, Inc. on behalf of International Center for Artificial Organ and Transplantation (ICAOT)
Keywords: extracorporeal membrane oxygenation; liver dysfunction; shear stress; SOFA score; thrombogenesis; von Willebrand factor

Influence of Ceramic Debris on Osteoblast Behaviors: An In Vivo Study - Sun, G.-J.; Yang, S.-F.; Ti, Y.-F.; Guo, G.-D.; Fan, G.-T.; Chen, F.-R.; Xu, S.-G.; Zhao, J.-N. (Orthopaedic Surgery, 2019)
Objective: Wear-induced aseptic loosening has been accepted as one of the main reasons for failure of total hip arthroplasty. Ceramic wear debris is generated following prosthesis implantation and plays an important part in the upregulation of inflammatory factors in total hip arthroplasty. The present study investigates the influence of ceramic debris on osteoblasts and inflammatory factors. Methods: Ceramic debris was prepared by mechanical grinding of an aluminum femoral head and added to cultures of MC3T3-E subclone 14 cells at different concentrations (i.e. 0, 5, 10, and 15 μg/mL). Cell proliferation was evaluated using a Cell Counting Kit (CCK-8), and cell differentiation was assessed by mRNA expression of alkaline phosphatase (ALP), osteocalcin (OCN), and osteopontin (OPN). In addition, cell bio-mineralization was evaluated through alizarin red S staining, and release of tumor necrosis factor alpha (TNF-α), interleukin-1 beta (IL-1β), and interleukin-6 (IL-6) was measured through enzyme-linked immunosorbent assays (ELISA). Furthermore, mRNA expression of Smad1, Smad4, and Smad5 and protein expression of phosphorylated Smad1, Smad4, and Smad5 were measured by reverse transcriptase polymerase chain reaction (RT-PCR) and western blotting. Results: The ceramic debris had irregular shapes and sizes, and analysis of the size distribution using a particle size analyzer indicated that approximately 90% of the ceramic debris was smaller than 3.2 μm (2.0 ± 0.4 μm), which is considered clinically relevant. The results for mRNA expression of ALP, OCN, and OPN and alizarin red S staining indicated that cell differentiation and bio-mineralization were significantly inhibited by the presence of ceramic debris at all tested concentrations (P < 0.05, and the values decreased gradually with the increase of ceramic debris concentration), but the results of the CCK-8 assay showed that cell proliferation was not significantly affected (P > 0.05; there was no significant difference between the groups at 1, 3, and 5 days). In addition, the results of ELISA, RT-PCR, and western blotting demonstrated that ceramic debris significantly promoted the release of inflammatory factors, including TNF-α, IL-β, and IL-6 (P < 0.05, and the values increased gradually with the increase of ceramic debris concentration), and also greatly reduced the mRNA expression of Smad1, Smad4, and Smad5 (the values decreased gradually with the increase of ceramic debris concentration) as well as protein expression of phosphorylated Smad1, Smad4, and Smad5. Conclusion: Ceramic debris may affect differentiation and bio-mineralization of MC3T3-E subclone 14 cells through the bone morphogenetic protein/Smad signaling pathway. © 2019 The Authors. Orthopaedic Surgery published by Chinese Orthopaedic Association and John Wiley & Sons Australia, Ltd
Keywords: BMP/Smads; Osteoblast; Signaling pathway; Total hip arthroplasty; Wear debris

Indications for surgery in non-traumatic spleen disease - Coco, D.; Leanza, S. (Open Access Macedonian Journal of Medical Sciences, 2019)
The spleen is the largest lymphatic organ that acts as a site for filtration of foreign particles from the blood, erythropoiesis and hematopoiesis. Splenectomy represents the first line of treatment for spontaneous splenic rupture, abscesses, cysts, tumours. It is also used to control hereditary, autoimmune, and myeloproliferative disorders alternatively. Numerous diseases have been indicated for surgery in non-traumatic spleen diseases such as non-traumatic spleen rupture, immune thrombocytopenic purpura (ITP), haemolytic anaemias, Felty's syndrome, Hodgkin's and non-Hodgkin's lymphoma among others. This result because the spleen is the most affected lymphoid organ following its overactivity that occurs during sequestration of dead or disrupted RBCs and lymphocytes. Abdominal pain is one of the major manifestations of splenomegaly, and can also designate other associated complications such as liver cirrhosis or bacterial endocarditis. As a secondary lymphoid organ, the spleen is more often an organ for lymphomas. Although splenectomy is a curative alternative in a few diseases, it is a complementary means of treating several other diseases. Splenectomy is a salvage therapy used when other therapeutic alternatives fail. Despite its indication in numerous diseases, controversies are still inbound of its use. © 2019 Danilo Coco, Silvana Leanza.
Keywords: Non-traumatic spleen disease; Spleen; Surgery

Percutaneous Interventional Radiology-Operated Endoscopy for Foreign Body Removal - Khayat, M.; Khayat, A.; Chick, J.F.B.; Healey, T.L.; Srinivasa, R.N. (Techniques in Vascular and Interventional Radiology, 2019)
Image-guided retrieval of endovascular devices such as inferior vena cava filters, guidewires, and stents is well reported, though there is a paucity of published reports on biliary, genitourinary, or gastrointestinal foreign body retrieval utilizing percutaneous endoscopy, particularly when it is performed solely by interventional radiologists. In cases of failed traditional endoscopic techniques or to evade more invasive surgical options, percutaneous endoscopy can be an adjunctive tool employed by interventional radiologists to extract foreign bodies. In this article, clinical evaluation, perioperative management, and procedural techniques for biliary, genitourinary, and gastrointestinal endoscopy for foreign body retrieval are reviewed. © 2019 Elsevier Inc.
Keywords: endobronchial forceps; endoscopic retrieval; foreign body removal; gastroscopy; interventional radiology; Percutaneous endoscopy

Retrieval of 159 magnetic balls from urinary bladder: A case report and literature review - Liu, Z.-H.; Zhu, X.-F.; Zhou, N. (Urology Case Reports, 2019)
Foreign body in urinary bladder is an unusual finding in urology emergency, which has always caused wide attention. In this case report, we presented a 28-year-old unmarried male who was admitted to the emergency room with magnetic balls in his bladder. An abdominal plain X ray showed metallic dense shadow in the pelvic region. The foreign body was removed under modified cystoscopy and 159 magnetic balls were detected. The patient was discharged without any surgical or postsurgical complications. Cystoscopy is a better option for dealing with a large number of magnetic balls in urinary bladder. © 2019
Keywords: Cystoscopy; Foreign body; Magnetic balls; Urinary bladder

Bone Causing Abdominal Groans - Goyal, P.; Gupta, S.; Sapire, J. (Journal of Emergency Medicine, 2019)
Gastrointestinal complications secondary to fish bone ingestion are rare, however important to recognize in timely manner to prevent morbidity and mortality. Diagnosis is often challenging in setting of non-specific and variable symptoms and lack of history of fish bone ingestion. Diagnostic imaging particularly computed tomography is crucial for diagnosis. However, emphasis should be given on identifying underlying cause of abdominal complications because fish bone is often missed unless specifically looked for. Identification of fish bone is essential for extraction of the inciting nidus. Emergency physician should be aware of this entity to identify it and triage the patients in timely manner. We describe here cases of sub-capsular liver abscess and acute cholecystitis caused by fish bone ingestion. The fish bone as a cause of these complication was initially missed in emergency. © 2019 Elsevier Inc.
Keywords: acute cholecystitis; fish bone; liver abscess

Intraperitoneal duodenal perforation secondary to early migration of biliary stent: Closure with through-the-scope clip - Jadallah, K.; Alzubi, B.; Sweidan, A.; Almanasra, A.R. (BMJ Case Reports, 2019)
Endoscopic biliary stenting is a well-recognised method of palliation of malignant biliary obstruction. Distal stent migration causing duodenal perforation is an uncommon complication of this procedure and is usually delayed. Early stent migration resulting in duodenal perforation is extremely rare and can be easily overlooked. We present a case of stent migration and resultant intraperitoneal duodenal perforation that occurred 24 hours following plastic stent insertion for a malignant biliary stricture in a 63-year-old woman. The patient required emergent abdominal laparoscopy with the placement of intraperitoneal drain, followed by endoscopic extraction of the stent and closure of the defect using a through-the-scope clip. This case report addresses intraperitoneal duodenal perforation secondary to early migration of biliary stents. Special emphasis is placed on the importance of prompt diagnosis and the use of endoclips in the management of this serious complication of endoprosthesis. © BMJ Publishing Group Limited 2019. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.
Keywords: Biliary Intervention; Endoscopy; Gastrointestinal Surgery

Delayed onset bioabsorbable screw reaction, intact screw extrusion and Pseudomonas aeruginosa tibial tunnel osteomyelitis years after arthroscopic anterior cruciate ligament reconstruction using hamstring graft - Dumlao, P.E.; Paner, N.; Bathan, L.; Lim, B.A. (BMJ Case Reports, 2019)
Postoperative reaction and infection after anterior cruciate ligament (ACL) reconstruction is a rare complication. We report two cases of bioabsorbable screw extrusion and Pseudomonas aeruginosa tibial tunnel infection in 17/18-year-old men, 2 and 4 years after ACL reconstruction, respectively. They underwent tibial tunnel debridement, removal of the still intact poly-L-D-lactic acid bioabsorbable screw and subsequent wound closure. Physical examination findings confirmed patency of the hamstring graft. Culture guided antibiotics were completed, and wounds healed unremarkably. Both returned to previous level of activity. Successful treatment is achieved through a logical sequence of management, as well as a multidisciplinary approach to prevent unnecessary secondary procedures and morbidity. © 2019 BMJ Publishing Group Limited. No commercial re-use. See rights and permissions. Published by BMJ.
Keywords: bone and joint infections; orthopaedics; unwanted effects/adverse reactions

Complex design of surgical instruments as barrier for cleaning effectiveness, favouring biofilm formation - Lopes, L.K.O.; Costa, D.M.; Tipple, A.F.V.; Watanabe, E.; Castillo, R.B.; Hu, H.; Deva, A.K.; Vickery, K. (Journal of Hospital Infection, 2019)
Background: Inadequately reprocessed reusable surgical instruments (RSIs) may harbour infectious agents which may then be transferred to a suitable site for replication. Aim: To determine the cumulative effect of 20 cycles of contamination, cleaning (manual or manual followed by automated) and steam sterilization on high-complex-design RSIs used for orthopaedic surgery. Methods: New flexible medullary reamers and depth gauges were contaminated by soaking in tryptone soya broth, containing 5% sheep blood and 109 cfu/mL of Staphylococcus aureus (ATCC 25923), for 5 min. To mimic a worse-case scenario, RSIs were dried 7 h and subjected to either (a) rinsing in distilled water, (b) manual cleaning or (c) manual plus automated cleaning (reference standard), and steam sterilization. The contamination, cleaning, and sterilization cycle was repeated 20 times. Adenosine triphosphate (ATP) was measured after cleaning procedures; microbial load and residual protein were measured following the 10th and 20th reprocessing, in triplicate. Scanning electron microscopy (SEM) was used to confirm soil and biofilm presence on the RSIs after the 20th reprocessing. Findings: Manual and manual plus automated cleaning significantly reduced the amount of ATP and protein residues for all RSIs. Viable bacteria were not detected following sterilization. However, SEM detected soil after automated cleaning, and soil, including biofilms, after manual cleaning. Conclusion: Soil and/or biofilms were evident on complex-design RSIs following 20 cycles of contamination and reprocessing, even using the reference standard method of cleaning. Although the depth gauges could be disassembled, biological residues and biofilm accumulated in its lumen. The current design of these RSIs prevents removal of all biological soil and this may have an adverse effect on patient outcome. © 2018 The Healthcare Infection Society
Keywords: Biofilm; Cleaning; Colony count; Microbial; Sterilization; Surgical instrument

Factors Influencing Poor Outcomes in Synthetic Tissue-Engineered Tracheal Replacement - Pepper, V.; Best, C.A.; Buckley, K.; Schwartz, C.; Onwuka, E.; King, N.; White, A.; Dharmadhikari, S.; Reynolds, S.D.; Johnson, J.; Grischkan, J.; Breuer, C.K.; et al. (Otolaryngology - Head and Neck Surgery (United States), 2019)
Objectives: Humans receiving tissue-engineered tracheal grafts have experienced poor outcomes ultimately resulting in death or the need for graft explantation. We assessed the performance of the synthetic scaffolds used in humans with an ovine model of orthotopic tracheal replacement, applying standard postsurgical surveillance and interventions to define the factors that contributed to the complications seen at the bedside. Study Design: Large animal model. Setting: Pediatric academic research institute. Subjects and Methods: Human scaffolds were manufactured with an electrospun blend of polyethylene terephthalate and polyurethane reinforced with polycarbonate rings. They were seeded with autologous bone marrow–derived mononuclear cells and implanted in sheep. Animals were evaluated with routine bronchoscopy and fluoroscopy. Endoscopic dilation and stenting were performed to manage graft stenosis for up to a 4-month time point. Grafts and adjacent native airway were sectioned and evaluated with histology and immunohistochemistry. Results: All animals had signs of graft stenosis. Three of 5 animals (60%) designated for long-term surveillance survived until the 4-month time point. Graft dilation and stent placement resolved respiratory symptoms and prolonged survival. Necropsy demonstrated evidence of infection and graft encapsulation. Granulation tissue with signs of neovascularization was seen at the anastomoses, but epithelialization was never observed. Acute and chronic inflammation of the native airway epithelium was observed at all time points. Architectural changes of the scaffold included posterior wall infolding and scaffold delamination. Conclusions: In our ovine model, clinically applied synthetic tissue-engineered tracheas demonstrated infectious, inflammatory, and mechanical failures with a lack of epithelialization and neovascularization. © American Academy of Otolaryngology–Head and Neck Surgery Foundation 2019.
Keywords: biomaterials; regenerative medicine; stem cells; tissue engineering; trachea

Non-dendritic Langerhans cells: A new entity in normal and malignant buccal mucosa - Mathew, J.K.; Pandian, R.M.K.; Gaikwad, P.; Rabi, S.; Nadu, T. (European Journal of Anatomy, 2019)
Langerhans cells (LCs) are the most effective antigen presenting cells against foreign bodies and carcinogens. Since the oral cavity is a portal of entry for these antigens, the aim of this study was to morphologically classify CD1a+ LCs, quantify them in the normal and malignant buccal mucosa, and evaluate their relation to the age of patients. Healthy buccal mucosal samples collected from 16 patients undergoing reconstructive operation, and malignant samples obtained from 15 patients undergoing radical oncological resection. were processed for immunohistochemistry four- to five-micron thick sections were stained with CD1a antibody (CD1a). At 40X magnification, CD1a+ LCs were morphologically classified and quantified manually for a 25mm length of basement membrane using Cellsens image analysing software and the data was analysed. Two categories of CD1a+ LCs were identified in the normal and malignant buccal mucosa a) typical dendritic LCs and b) non-dendritic LCs (a new entity). Non-dendritic LCs were of significantly higher number compared to the typical dendritic LCs in the normal tissues (p -0.001). In the malignant group, the non-dendritic CD1a+ LCs were significantly fewer in number (p-0.004), when compared to the normal group. Non-dendritic LCs were also significantly fewer (p-0.026) in patients over 60 years of age. This is the first report of non-dendritic Langerhans cells in normal buccal mucosa and malignant buccal mucosa using the CD1a marker. The significantly higher number of these cells in normal tissues and younger individuals supports their role as accessory antigen presenting cells. © 2019 Sociedad Anatomica Espanola. All rights reserved.
Keywords: Accessory antigen presenting cells; Antigen presenting cells; Dendritic; Types of Langerhans cells

A Patient with Abnormal Abdominal CT Scan Findings - Vitello, J.M.; Vitello, D.J.; Bermudez-Allende, M. (JAMA - Journal of the American Medical Association, 2019)

Spontaneous pneumothorax in cocaine users - Ciriaco, P.; Rossetti, F.; Carretta, A.; Sant'Angelo, M.; Arrigoni, G.; Negri, G. (QJM : monthly journal of the Association of Physicians, 2019)
BACKGROUND: Pneumothorax is one of the respiratory toxic effects of cocaine inhalation. The literature counts several cases, some associated to other respiratory conditions such as pneumomediastinum, haemoptysis and others not requiring surgical treatment. AIM: We present a series of nonHIV cocaine-inhaler subjects who underwent video-assisted thoracoscopic surgery (VATS) for isolated spontaneous pneumothorax. DESIGN: Nine subjects, with a mean age of 24 ± 4 years, admitting cocaine inhalation, developed spontaneous pneumothorax and underwent 10 surgical treatments by means of VATS, at our Institution. RESULTS: Previous pneumothorax occurred in six cases episodes ranged from 0 to 5 (mean 1.6 ± 1.6). Chest computed tomography (CT) scan showed abnormalities in seven cases. All subjects underwent lung apicectomy, apical pleurectomy and mechanical pleurodesis. Seven subjects had also bullectomy. In all cases the visceral pleura was partially covered by fibrinous exudate. Histology of the lung showed small foreign body granulomatous inflammation in fibrotic and/or emphysematous pulmonary parenchyma. Relapse of pneumothorax occurred in one subject at 60 days and it was surgically treated. Mean follow-up was 150 ± 38 months (range 120-239). All subjects are now well, with no evidence of pneumothorax. CONCLUSIONS: Spontaneous pneumothorax in cocaine-inhaler subjects is a reality of which physicians need to be aware. Chest CT scan might not reveal abnormalities. Macroscopically the lung might presents bullae and/or peculiar visceral pleura. Foreign body granulomas observed in the specimens suggest that the particulate component of inhaled substances can injure the lung. Surgical treatment of the bullous disease and mechanical pleurodesis can provide a long-term follow-up without relapse of pneumothorax. © The Author(s) 2019. Published by Oxford University Press on behalf of the Association of Physicians. All rights reserved. For permissions, please email: journals.permissions@oup.com.

Biocompatibility of injectable hydrogel from decellularized human adipose tissue in vitro and in vivo - Zhao, Y.; Fan, J.; Bai, S. (Journal of Biomedical Materials Research - Part B Applied Biomaterials, 2019)
Adipose tissue engineering is considered as a promising treatment for repairing soft tissue defects. The decellularized extracellular matrix (ECM) is becoming the research focus in tissue engineering for its tissue specificity. In this study, the human adipose tissue liposucted from healthy people were decellularized by a series of mechanical, chemical, and enzymatic methods. The components of cell and lipid were effectively removed, whereas the collagens and other ingredients in adipose tissue were retained in the human decellularized adipose tissue (hDAT). Then the extracted hDAT was further fabricated into injectable hydrogel, which could be self-assembled to form gel under certain condition. The hDAT hydrogel was nontoxic to human adipose-derived stem cells (ADSCs) and could spontaneously induce adipogenic differentiation in vitro. It was highly biocompatible and could not cause inflammation and rejection after being implanted subcutaneously. The hDAT hydrogel developed in this study will be one of the available choices for soft tissue enlargement and cosmetic fillers because of its noninvasive in collection and implantation process. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1684–1694, 2019. © 2018 Wiley Periodicals, Inc.
Keywords: decellularized adipose tissue; extracellular matrix; hydrogel; scaffolds; tissue engineering

Severe subacromial-subdeltoid inflammation with rice bodies associated with implantation of a bio-inductive collagen scaffold after rotator cuff repair - Barad, S.J. (Journal of Shoulder and Elbow Surgery, 2019)
Keywords: acute bursitis; Bio-inductive implant; foreign body reaction; rice body; rotator cuff tear; subacromial-subdeltoid bursa

Man With Finger Pain and Swelling - Lee, A.S.; Jackson, B.S. (Annals of Emergency Medicine, 2019)

Breast abscess in a competitive high school swimmer: A case of toxic shock syndrome - Taylor, G.M.; Vieder, S.J.; Cooley, C.N.; Fan, W.C.; Alper, M.E. (Oxford Medical Case Reports, 2019)
Toxic shock syndrome (TSS) is a severe, acute, toxin-mediated disease process characterized by fever, diffuse erythroderma, hypotension, multisystem organ dysfunction and desquamation of skin. TSS represents the most severe form of disease caused by exotoxin-producing strains of Streptococcus pyogenes and Staphylococcus aureus. Menstrual and non-menstrual TSS become significant causes of morbidity and mortality. As a result of public awareness and various campaigns, the majority of TSS cases tend to be non-menstrual related. The clinical course is fulminant and can result in abrupt decompensation and death. Management within the emergency department (ED) includes removal of the potential foreign body, fluid resuscitation, appropriate antibiotics, potential vasopressor support and possible surgical intervention. We present the unique case of a 16-year-old female competitive swimmer who presented to the ED twice, demonstrating the fulminant course of TSS. She initially presented with non-specific symptoms with an unremarkable evaluation. She returned within hours of discharge with an abrupt onset of diffuse macular erythroderma, placed on norepinephrine and was diagnosed with TSS secondary to a breast abscess. © 2019 The Author(s) 2019. Published by Oxford University Press.

Pericardial Effusion in a Dog with Pericardial Hemangiosarcoma - Gunasekaran, T.; Olivier, N.B.; Smedley, R.C.; Sanders, R.A. (Journal of Veterinary Cardiology, 2019)
An adult Jack Russel terrier dog presented for evaluation of large-volume peritoneal and pleural effusion. Echocardiography revealed scant pericardial effusion and abnormally thickened pericardium. Electrocardiography revealed complete atrioventricular block with junctional and ventricular escape beats and occasional ventricular premature complexes. Computed tomography of the thorax confirmed diffuse abnormal thickening of the pericardium, and a tentative diagnosis of constrictive-effusive pericarditis was made. The dog underwent subtotal pericardiectomy to remove the parietal pericardium and permanent epicardial pacemaker implantation to manage bradycardia. Based on pericardial histopathology and immunohistochemistry, a diagnosis of pericardial hemangiosarcoma was made. Systemic chemotherapy was initiated with doxorubicin 1 month after surgery. Despite initial improvement with chemotherapy, the dog was euthanized 4 months after surgery because of development of recurrent pleural effusion. To the author's knowledge, this is the first case report in dogs to describe isolated pericardial location of hemangiosarcoma resulting in constrictive-effusive pericarditis. © 2019 Elsevier B.V.
Keywords: Constrictive-effusive; Pericardiectomy; Pericarditis

Acupuncture gone awry: a case report of a patient who required surgical removal of two single-use filament needles following acupuncture treatment - Snyder, D.D. (Journal of Manual and Manipulative Therapy, 2019)
Background: Acupuncture and dry needling are increasingly popular treatment modalities used to treat pain around the world. This case report documents the clinical history of a patient who presented to an outpatient physical therapy clinic following surgical removal of two single-use filament needles that fractured in the patient’s neck during acupuncture treatment. Case Description: The purpose of this case report was to highlight a rare adverse event following acupuncture treatment. The patient received the acupuncture treatment from a practitioner licensed in acupuncture, while on an international business trip. Following the acupuncture treatment, the practitioner realized that a needle had fractured and remained in the patient’s neck. After failing to retrieve the needle, the patient was sent for imaging. Radiograph revealed that the patient had two needle fragments located in his cervical tissue. After determining that the needles did not pose an immediate threat, the patient boarded a flight home to the United States. Following his flight, the patient presented to an American hospital where it was discovered that the needle fragments had migrated during the flight, with one needle now located 2 mm from the patient’s vertebral artery. Surgical intervention was required to retrieve the needles, resulting in the patient needing physical therapy to increase cervical range of motion and mediate pain relief. Outcomes: The patient suffered a setback in his treatment of chronic neck pain that resulted in decreased cervical range of motion and increased pain. Discussion: Clinicians utilizing single-use filiform needles in their practice, whether for acupuncture or dry needling, should be aware of the potential for this type of adverse event. Further, to minimize the risk of similar adverse events occurring in the future, clinicians should make sure that they are using high quality needles and make a habit of counting in and counting out the needles that they use to verify that all needles are accounted for. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Acupuncture; acupuncturist; adverse events; chronic neck pain; complications; dry needling; filiform needles; physical therapy

Leaving a foreign object in the body of a patient during abdominal surgery: still a current problem - Szymocha, M.; Pacan, M.; Anufrowicz, M.; Jurek, T.; Rorat, M. (Polski przeglad chirurgiczny, 2019)
INTRODUCTION: Leaving a foreign object (retained surgical item, or RSI) during surgery involving the abdominal cavity and pelvis minor is a relatively frequent, underestimated phenomenon which is dangerous to the health of the patient and the legal security of the medical personnel. These adverse events are easy to avoid through the use of appropriate means of prevention. The aim of the present paper is the collection of epidemiological data and determination of risk factors, symptomatology, health effects, and prevention methods associated with RSIs. MATERIAL AND METHODS: Analysis of global scientific publications in the databases PubMed, ClinicalKey, Google Scholar, ScienceDirect, and Scopus related to the subject of RSIs. RESULTS: The frequency of RSI incidents ranges from 1 to 10 in 10,000 surgeries, which results in at least one case in an average multispeciality hospital on a yearly basis. The items most frequently left behind include soft foreign objects, such as swabs and bandages (90%). Risk factors include emergency surgical procedures, high patient BMI, significant loss of blood during surgery, and neglect in counting the material and surgical tools. The postoperative course, although in many cases asymptomatic, may be complicated by inflammation, bleeding, or perforation, leading to the necessity of a second operation and, in 2 to 4% of cases, even ending in death. Imaging tests are effective diagnostic tools. Effective methods of preventing RSIs are based on checklists and systems for counting and monitoring the location of material and tools. CONCLUSIONS: The globally occurring problem of RSIs requires education of the operating block personnel regarding risk factors and identification with elimination of adverse events of this type. Diagnostics based on imaging should take into account non-specific complaints resulting from a possible oligosymptomatic course. An RSI should not be regarded as a medical error. Changes in the perception of the phenomenon aim aimed at minimising the legal liability of the staff in the event of leaving a foreign object in a patient's body.
Keywords: adverse event; foreign object; gossypiboma; never event; retained foreign object

Elderly Woman With Flank Pain - Hong, C.-W.; Fan, H.-L.; Tsai, S.-H.; Chen, S.-J.; Wang, J.-C. (Annals of Emergency Medicine, 2019)

A very persistent chicken bone: Two separate perforations from the same foreign object 2 months apart - Brown, A.J.; Whitehead-Clarke, T.; Tudyka, V. (BMJ Case Reports, 2019)
A 56-year-old man presented acutely with abdominal pain and raised inflammatory markers. Initial CT images demonstrated acute inflammation in the right upper quadrant surrounding a high-density linear structure. The appearance was of a chicken bone causing a contained small bowel perforation. This was managed conservatively with intravenous antibiotics and the patient was discharged 10 days later. The same patient returned to the hospital 2 months later, once again with an acute abdomen. CT imaging on this occasion showed distal migration of the chicken bone as well as free gas and fluid indicative of a new small bowel perforation. The patient underwent an emergency laparotomy, washout and small bowel resection. No foreign body was found at laparotomy or in the histopathology specimen. The postoperative course was complicated by an anastomotic leak. A further CT on that admission demonstrated that the chicken bone had migrated to the rectum! © BMJ Publishing Group Limited 2019. No commercial re-use. See rights and permissions. Published by BMJ.
Keywords: gastrointestinal surgery; general surgery

Preliminary Studies of the Impact of CXCL12 on the Foreign Body Reaction to Pancreatic Islets Microencapsulated in Alginate in Nonhuman Primates - Sremac, M.; Lei, J.; Penson, M.F.E.; Schuetz, C.; Lakey, J.R.T.; Papas, K.K.; Varde, P.S.; Hering, B.; De Vos, P.; Brauns, T.; Markmann, J.; Poznansky, M.C. (Transplantation Direct, 2019)
Background. We previously demonstrated that the incorporation of the chemokine CXCL12 into alginate microbeads supported long-term survival of microencapsulated auto-, allo-, and xenogeneic islets in murine models of diabetes without systemic immune suppression. The purpose of this study was to test whether CXCL12 could abrogate foreign body responses (FBRs) against alginate microbeads which were empty or contained autologous islets in healthy nonhuman primates (NHPs; n = 4). Methods. Two NHPs received intraperitoneal implants of 400 000 alginate microbeads with or without CXCL12, and postimplantation immunological and histopathological changes were evaluated up to 6 months postimplantation. A similar evaluation of autologous islets in CXCL12-containing alginate microbeads was performed in NHPs (n = 2). Results. CXCL12-containing alginate microbeads were associated with a markedly reduced FBR to microbeads. Host responses to microbead implants were minimal, as assessed by clinical observations, blood counts, and chemistry. Evaluation of encapsulated islets was limited by the development of necrotizing pancreatitis after hemipancreatectomy in 1 NHP. A limited number of functioning islets were detectable at 6 months posttransplantation in the second NHP. In general, empty microbeads or islet-containing beads were found to be evenly distributed through the intraperitoneal cavity and did not accumulate in the Pouch of Douglas. Conclusions. Inclusion of CXCL12 in alginate microbeads minimized localized FBR. The NHP autologous islet implant model had limited utility for excluding inflammatory/immune responses to implanted islets because of the complexity of pancreatic surgery (hemipancreatectomy) before transplantation and the need to microencapsulate and transplant encapsulated autologous islets immediately after pancreatectomy and islet isolation. © 2019 The Author(s).

Squamous cell carcinoma of skin due to prolonged indwelling percutaneous nephrostomy catheter - Sharma, A.; Singh, V.; Sinha, R.J.; Agarwal, S. (BMJ Case Reports, 2019)
Percutaneous nephrostomy (PCN) catheter placement is a commonly performed procedure in the urological practice for various indications like percutaneous nephrolithotomy, pyonephrosis, infected hydronephrosis and after failed attempt of ureteric stenting. The nephrostomy catheter is usually associated with low complication and morbidity rate, but prolonged indwelling nephrostomy tube may be hazardous in some cases. We hereby report a case of squamous cell carcinoma of skin around the PCN, which was attributed to chronic inflammation and persistent irritation from a long-term neglected indwelling nephrostomy catheter for last 3 years. The patient was managed with wide local excision of skin carcinoma and ureterocalicostomy for pelviureteric junction stricture. The authors report the first documented case with aforementioned presentation. © BMJ Publishing Group Limited 2019.
Keywords: catheter care; catheterisation; skin cancer; surgical oncology; unwanted effects / adverse reactions

Nanofiber-hydrogel composite–mediated angiogenesis for soft tissue reconstruction - Li, X.; Cho, B.; Martin, R.; Seu, M.; Zhang, C.; Zhou, Z.; Choi, J.S.; Jiang, X.; Chen, L.; Walia, G.; Yan, J.; Callanan, M.; et al. (Science Translational Medicine, 2019)
Soft tissue losses from tumor removal, trauma, aging, and congenital malformation affect millions of people each year. Existing options for soft tissue restoration have several drawbacks: Surgical options such as the use of autologous tissue flaps lead to donor site defects, prosthetic implants are prone to foreign body response leading to fibrosis, and fat grafting and dermal fillers are limited to small-volume defects and only provide transient volume restoration. In addition, large-volume fat grafting and other tissue-engineering attempts are hampered by poor vascular ingrowth. Currently, there are no off-the-shelf materials that can fill the volume lost in soft tissue defects while promoting early angiogenesis. Here, we report a nanofiber-hydrogel composite that addresses these issues. By incorporating interfacial bonding between electrospun poly(-caprolactone) fibers and a hyaluronic acid hydrogel network, we generated a composite that mimics the microarchitecture and mechanical properties of soft tissue extracellular matrix. Upon subcutaneous injection in a rat model, this composite permitted infiltration of host macrophages and conditioned them into the pro-regenerative phenotype. By secreting pro-angiogenic cytokines and growth factors, these polarized macrophages enabled gradual remodeling and replacement of the composite with vascularized soft tissue. Such host cell infiltration and angiogenesis were also observed in a rabbit model for repairing a soft tissue defect filled with the composite. This injectable nanofiber-hydrogel composite augments native tissue regenerative responses, thus enabling durable soft tissue restoration outcomes. Copyright © 2019 The Authors,

‘Lost in Nasal Space’: Staphylococcus aureus sepsis associated with Nasal Handkerchief Packing - Koehler, P.; Jung, N.; Kochanek, M.; Lohneis, P.; Shimabukuro-Vornhagen, A.; Böll, B. (Infection, 2019)
Introduction: Staphylococcus aureus frequently causes infections in outpatient and hospital settings and can present as a highly variable entity. Typical manifestations are endocarditis, osteoarticular infections or infection of implanted prostheses, intravascular devices or foreign bodies. A thorough diagnostic evaluation with early focus identification is mandatory to improve patient outcome. Case report: We report a case of a 68-year old patient with a history of double allogeneic stem cell transplant for acute myeloid leukemia who developed a S. aureus bacteremia with dissemination, severe sepsis and lethal outcome due to nasal handkerchief packing after nose bleeding. Conclusion: A thorough medical examination with further diagnostic work-up is most important in S. aureus blood stream infection to identify and eradicate the portal(s) of entry, to rule out endocarditis, to search for spinal abscesses, osteomyelitis or spondylodiscitis. Adherence to management guides for clinicians must be of major importance to achieve optimal quality of clinical care, and thus improve patient outcome. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Dissemination; Infectious disease consulting; Intensive care medicine; Superantigen

The sucked surgical sponge: Rare case of Gossypiboma after vaginal hysterectomy - Oehme, F.; Rühle, A.; Stickel, M.; Metzger, J.; Gass, J.-M. (Clinical Case Reports, 2019)
Retained surgical material needs to be a possible differential diagnosis for patients presenting with unspecific abdominal pain after especially cavitary emergency surgery. Even though international standard checklists concerning sponge handling and counting exist, RSM could never be ruled out completely. © 2019 The Authors. Clinical Case Reports published by John Wiley & Sons Ltd.
Keywords: Gossypiboma; remained surgical material; small bowel obstruction; vaginal hysterectomy

Biocompatibility of n-butyl-2-cyanoacrylate (Histoacryl) in cervical structures of rats: Prospective in vivo study - Suh, Y.J.; Yu, H.W.; Kim, S.-J.; Choe, J.-Y.; Park, H.J.; Choi, J.Y.; Lee, K.E. (Annals of Surgical Treatment and Research, 2019)
Purpose: We investigated the biocompatibility of n-butyl-2-cyanoacrylate (NBCA) in the cervical deep tissues of rats to assess its biocompatibility. Methods: A total of 30 Sprague-Dawley rats were injected with NBCA. After 30, 90, 180, and 360 days, cubes of tissue (1 cm × 1 cm × 1 cm) surrounding the NBCA and normal tissue from the other side of the neck were excised from each rat. The adhesion of NBCA to adjacent structures was examined histologically. Cells were counted per high-power field (HPF), and fibrosis was graded with the measurement of fibrotic thickening. Results: All animals displayed normal behavior without any symptoms of distress throughout the study. There was no recognizable inflammatory reaction, foreign body reaction, or fibrosis in the 30 control samples. The analyses of experimental samples showed significantly decreased inflammatory cell counts over time (lymphoplasma cell count decreased from 100 (range, 70–100) to 30 (range, 30–50) per HPF, P = 0.010; neutrophil count decreased from 2 (range, 2–30) to 0 (range, 0–2) per HPF, P = 0.017). However, there was no significant difference in the number of multinuclear giant cells throughout the study period (a decrease from 22 [range, 16–34] to 16 [range, 12–22] per HPF, P = 0.287). The level of fibrosis was Common Toxicity Criteria ver. 4.0 Grade 1 without further thickening (P = 0.600). However, maturation of fibrosis progressed gradually. Conclusion: NBCA was biologically tolerable in the cervical deep tissues of rats. However, precautions are needed with respect to preventing a sustained foreign body reaction and fibrosis. Copyright 2019, the Korean Surgical Society
Keywords: Biocompatible materials; Chyle; Cyanoacrylate; Neck dissection

Granulomatosis with polyangiitis: Potentially lethal gingival lesions presenting to the dentist - Patrick, A.; Altman, K. (BMJ Case Reports, 2019)
Gingival pathology is a daily presentation, however a small number of systemic conditions can manifest similar to a common gingival condition and have fatal results. Dentist referred 56-year-old woman to Oral and Maxillofacial Surgery department with a 2-week medical history of gingival bleeding not responding to local measures. Biopsy showed eosinophilic infiltrate and vasculitis, and blood tests showed positive markers including cytoplasmic antineutrophil cytoplasmatic antibodies. Granulomatosis with polyangiitis is a rare disease affecting the respiratory tract, blood vessels and kidneys. Oral lesions are rarely the primary presenting feature. When left untreated, most cases are fatal within a year of diagnosis. The diagnosis can only be made when certain criteria are found, including granular oral lesions exhibiting an eosinophilic inflammatory infiltrate on biopsy. With 5% of cases showing intraoral lesions as the primary feature, it is essential that dentists have the knowledge of this rare disease to refer and not to treat as a common gingival condition. © BMJ Publishing Group Limited 2019. No commercial re-use. See rights and permissions. Published by BMJ.
Keywords: Dentistry and oral medicine; Mouth; Pathology; Vasculitis

Twenty years later… A story of intra-thoracic textiloma - Lebas, L.; Dupuis, M.; Solovei, L.; Jaffro, M.; Grunenwald, E.; Pontier-Marchandise, S.; Dahan, M.; Didier, A. (Revue des Maladies Respiratoires, 2019)
Introduction: Intrathoracic textiloma is a rare complication possibly leading to misdiagnosis. It could present as haemoptysis, lung abscess, pseudo-tumour or a chronic cough. Case report: A 65-year-old patient with a history of multiple cardiac problems and needing long-term anticoagulation, complained since 2007 of recurrent haemoptysis of increasing abundance, the etiological investigation of which was negative. A thoracic CT-scan revealed a lesion in the lingula in contact with the pericardial plates of an implanted automatic defibrillator dating from 1989. In 2016, after two failures of arterial embolization, a diagnostic and therapeutic surgical exploration was undertaken on this patient who was a high operative risk. A segmental resection revealed an intra-pulmonary textiloma on pathological examination. Conclusion: The diagnosis of intrathoracic textiloma remains rare and its late presentation is non specific. Radiological imaging with a CT-scan and/or MRI could lead to the diagnosis. Surgery remains the reference treatment for the diagnosis and cure of intrathoracic textiloma with pathological examination, essential for confirmation. A means of prevention has to be developed because swab count is not totally reliable. © 2018 SPLF
Keywords: Bronchial artery embolization; Foreign body; Haemoptysis; Implantable defibrillator; Textiloma; Thoracic surgery

Activity of fixed direct electrical current in experimental Staphylococcus aureus foreign-body osteomyelitis - Schmidt-Malan, S.M.; Brinkman, C.L.; Greenwood-Quaintance, K.E.; Karau, M.J.; Mandrekar, J.N.; Patel, R. (Diagnostic Microbiology and Infectious Disease, 2019)
Fixed DC was compared to ceftriaxone, ceftriaxone with 200 μA fixed DC, or no treatment in a rat model of methicillin-susceptible Staphylococcus aureus foreign-body osteomyelitis. After 3 weeks, fewer bacteria were present in bones of the ceftriaxone group (5.71 log 10 cfu/g [P = 0.0004]) and the ceftriaxone/DC group (3.53 log 10 cfu/g [P = 0.0002]) than untreated controls (6.70 log 10 cfu/g). Fewer bacteria were present in the ceftriaxone/DC group than in the ceftriaxone-alone and DC-alone groups (P = 0.0012 and 0.0008, respectively). There were also fewer bacteria on the implanted wires in the groups treated with ceftriaxone (5.47 log 10 cfu/cm 2 ) or ceftriaxone/DC (2.82 log 10 cfu/cm 2 ) than in the untreated controls (6.44 log 10 cfu/cm 2 [P = 0.0003 and 0.0002, respectively]). There were fewer bacteria in the ceftriaxone/DC rats than in the ceftriaxone-alone– and fixed DC-alone–treated rats (P = 0.0017 and 0.0016, respectively). Fixed DC with an antibiotic may be useful for treating foreign-body infections caused by S. aureus. © 2018 Elsevier Inc.
Keywords: Prosthetic joint infection; Staphylococcus aureus; Treatment

Epistaxis - Krulewitz, N.A.; Fix, M.L. (Emergency Medicine Clinics of North America, 2019)
Most anterior epistaxis originates primarily from the Kiesselbach plexus, whereas posterior epistaxis is less common and originates from branches of the sphenopalatine artery. Risk factors include local trauma, foreign body insertion, substance abuse, neoplasms, inherited bleeding diatheses, or acquired coagulopathies. Assessment of airway, breathing, and circulation precedes identification of bleeding source, pain control, and achieving hemostasis. Management options include topical vasoconstrictors, direct pressure, cautery, tranexamic acid, nasal tampons, Foley catheters, or surgical intervention. Specialty consultation may be pursued if interventions fail. Disposition is typically to home unless posterior epistaxis or significant comorbidities exist that warrant admission. © 2018 Elsevier Inc.
Keywords: Anterior epistaxis; ENT emergencies; Epistaxis; Posterior epistaxis; TXA

Specificity of the female's local cellular immune response in genital plug producing scorpion species - Oviedo-Diego, M.A.; Mattoni, C.I.; Peretti, A.V. (PLoS ONE, 2019)
Immune defense is a key feature in the life history of organisms, expensive to maintain, highly regulated by individuals and exposed to physiological and evolutionary trade-offs. In chelicerates, relatively scarce are the studies that relate postcopulatory mechanisms and immune response parameters. This work makes an approximation to the female's immunological consequences produced after the placement of a foreign body in the genitalia of three scorpions species, two species that normally receive genital plugs during mating (Urophonius brachycentrus and U. achalensis) and one that does not (Zabius fuscus). Here we performed the first morphological description of the natural plugs of the two Urophonius species. We described complex three zoned structure anchored to the female genital atrium and based on this information we placed implants in the genitalia (for eliciting the local immune response) of virgin females of the three species and measured the immune encapsulation response to this foreign body. We found a greater and heterogeneous response in different zones of the implants in the plug producing species. To corroborate the specificity of this immune response, we compared the local genital reaction with the triggered response at a systemic level by inserting implants into the female body cavity of U. brachycentrus and Zabius fuscus. We found that the systemic response did not differ between species and that only in the plug producing species the local response in the genitalia was higher than the systemic one. We also compared the total hemocyte load before and after the genital implantation to see if this parameter was compromised by the immunological challenge. We confirmed that in Urophonius species the presence of a strange body in the genitalia caused a decrease in the hemocyte load. Besides, we find correlations between the body weight and the immunological parameters, as well as between different immunological parameters with each other. Complementarily, we characterized the hemocytes of the three scorpion species for the first time. This comparative study can help to provide a wider framework of the immunological characteristics of the species, their differences and their relationship with the particular postcopulatory mechanism such as the genital plugs. © 2019 Oviedo-Diego et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Tissue reaction after subcutaneous implants of a new material composed of ethylene-vinyl acetate and starch for future use as a biomaterial - Froes, B.; Holgado, L.A.; Simões, R.D.; Velasco Nieto, D.; Angel Rodriguez Perez, M.; Kinoshita, A. (Journal of Biomedical Materials Research - Part B Applied Biomaterials, 2019)
This study aimed to evaluate the tissue reaction of ethylene-vinyl acetate (EVA) in 4 different compositions and processing: EVA foamed at high pressure with ultrasound (EVACU); EVA with 15% starch foamed at high pressure with ultrasound (EVAMCU); EVA with 15% starch foamed at high pressure without ultrasound and EVA foamed at high pressure without ultrasound as future use as a porous scaffold. Scanning electron microscopy images showed the influence of starch, reducing the diameter of pores. The number of open pores was also reduced with the addition of starch. The ultrasound applied during the manufacturing of composites does not affect these characteristics. Eighteen rats were used to test the tissue reaction of materials and PTFE (polytetrafluoroethylene), proven biocompatible material. After 7, 15, and 60 days of surgery, the materials were removed and processed for microscopic evaluation and counting of the inflammatory infiltrate. The data shows inflammatory reaction similar to PTFE. However, in the quantitative analysis at 60 days, the EVACU and EVAMCU showed less quantity of mononuclear cells (p < 0.05). Thus, the results suggest that the use of ultrasound in the production method (EVA) seems to have improved cell behavior regarding the reduction of infiltration over the period, with tissue response equivalent to the PTFE. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 107B: 400–407, 2019. © 2018 Wiley Periodicals, Inc.
Keywords: biocompatibility; biomaterial; ethylene-vinyl acetate; porous scaffolds; tissue reaction

Intraabdominal gossypibomas with variable ct appearance: A case report - Fatima, K. (Journal of the Pakistan Medical Association, 2019)
A retained surgical sponge or gossypiboma is a rare and an underreported complication occurring most commonly after abdominal surgeries. The clinical presentation as well as the time of presentation is variable with about one third of patients being asymptomatic. The diagnosis is challenging because of marked variation in the presentation and imaging plays a crucial role in diagnosis. We report a 30-year old Asian woman with prior history of Caesarean section who presented with persistent abdominal pain since surgery and underwent imaging in December 2012. The case is interesting as she had two intraabdominal gossypibomas with different appearances on computerized tomography. One was suggested to be a retained foreign body while the other was initially misinterpreted as a solid ovarian mass. However, on ultrasound, both lesions showed similar appearance and the left lower abdominal solid mass was also suggested to be a retained foreign body which was then confirmed on laparotomy. © 2019, Pakistan Medical Association. All rights reserved.
Keywords: Computerized tomography; Gossypiboma; Intraabdominal; Surgical sponge; Ultrasound

Gossypiboma (Textiloma) in the Abdominal Preperitoneal Space Following Cesarean Section: A Case Report with Literature Review - Dhar, H.; Sashidharan, P.; Razek, Y.A. (Journal of SAFOG, 2019)
Retention of surgical items is a preventable complication. The foreign body may be symptomless or migrate in and around the abdomen causing fistula formation, bowel obstruction and perforation. Some major causes responsible for this complication are emergency, prolonged, difficult surgeries associated with obesity, poor communication with an error in sponge and instrument counting. Frequency being 1/1000 to 1/32672 surgeries in the recent review of the literature. Definitive treatment for this condition is surgical removal either by laparotomy or laparoscopically. We report a case whose cesarean section was done in a secondary care hospital for brow presentation and later referred to us after two months with complaints of pain and swelling in the abdomen. Entrapment of a surgical sponge in the preperitoneal space of the abdomen was noted and later removed surgically. This case highlights the need for all health care professionals to be vigilant and cautious intraoperatively as any lapse in mop and instrument counting may be disastrous for both the patient as well as the healthcare team. There is a growing need for patient safety hospital initiation to avoid such errors by surgical teams. The aim of presenting and reporting this case is to increase awareness among healthcare workers to avoid such lapses causing great medical morbidity with medicolegal complications. © 2019 Journal of South Asian Federation of Obstetrics and Gynaecology. All rights reserved.
Keywords: Cesarean; Fistula; Gossypiboma; Migrating sponge; Retained foreign body; Textiloma

A new search algorithm for reducing the incidence of missing cottonoids in the operating theater - Reddy, A.; Mahajan, R.; Rustagi, T.; Goel, S.A.; Bansal, M.L.; Chhabra, H.S. (Asian Spine Journal, 2019)
Study Design: Retrospective study. Purpose: Missing cottonoids during and after spinal surgery is a persistent problem and account for the most commonly retained surgical instruments (RSIs) noticed during a final cottonoid count. The aim of this study was to enumerate risk factors and describe the sequence to look out for misplaced cottonoids during spinal surgery and provide an algorithm for resolving the problem. Overview of Literature: There are only a few case reports on RSIs among various surgical branches. The data is inconclusive and there is little evidence in the literature that relates to spinal surgery. Methods: This retrospective study was conducted at Indian Spinal Injuries Centre. The data was collected from hospital records ranging from January 2013 to December 2017. The surgical cases in which cottonoid counts were inconsistent during or after the procedure were included in the study. The case files along with operating theater records were thoroughly screened for selecting those in which there was confirmed evidence of such an event. Results: There were 7,059 spinal surgeries performed during the study period. Fifteen cases of miscounts were recorded with an incidence of one in every 471 cases. Cottonoids were most commonly lost under the shoes of the surgeon or assistants. In two instances, cottonoids were found in the surgical field and trapped in the interbody cage site. Based on these locations, a systematic search algorithm was created Conclusions: This study enumerates RSI risk factors in spinal surgical procedures and describes steps that can be followed to account for any missing cottonoids. The incidence of missing cottonoids can be decreased using a goal-oriented approach and ensuring that surgical teams work in collaboration. © 2019 by Korean Society of Spine Surgery.
Keywords: Algorithms; Cottonoids; Re-exploration; Retained foreign body; Spine; Surgical sponges

Ingested metallic foreign body impacted in the vermiform appendix presenting as acute appendicitis: Case report - Mohammed, A.A.; Ghazi, D.Y.; Arif, S.H. (International Journal of Surgery Case Reports, 2019)
Introduction: Ingestion of foreign bodies and their impaction at the lumen of the appendix is a very rare finding and only few cases have been reported all over the world. A variety of metallic foreign bodies when ingested may be lodged in the lumen of the appendix such as screws, bird shots, and needles. This is called in most literatures as foreign body appendicitis. Case presentation: A 4-year-old boy with history of an accidental ingestion of a metallic nail presented to the emergency department one week later with right iliac fossa pain and one attack of vomiting. During abdominal examination there was tenderness and rebound tenderness at the right iliac fossa. Plain abdominal X-ray showed the metallic nail in the region of the right iliac fossa. Ultrasound examination was normal apart from tenderness of putting the probe on the right lilac fossa. The white blood cell counts were 14,000 cell per microliter. During surgery the nail was found to be impacted inside the lumen of the vermiform appendix causing inflammation of the appendix. Appendicectomy done and the patient discharged on the third day in a good general condition. Conclusion: Acute appendicitis may be caused by a variety of causes including ingested foreign bodies if impacted in its lumen. When the patient has signs of generalized peritonitis it is important to exclude bowel perforation. The surgery can be done by the open surgery or laparoscopically. © 2019 The Authors
Keywords: Appendicectomy; Appendicitis; Foreign body appendicitis; Vermiform appendix

The Effect of Radiofrequency Technology on Time Spent Searching for Surgical Sponges and Associated Costs - Steelman, V.M.; Schaapveld, A.G.; Storm, H.E.; Perkhounkova, Y.; Shane, D.M. (AORN Journal, 2019)
Retained surgical items (eg, sponges, instruments) remain the most frequently reported sentinel events. The primary strategy for preventing retained sponges is the sponge count. Reconciling sponge counts is time consuming and can extend the duration of operative and other invasive procedures. The primary objective of this observational study was to evaluate the effect of a radiofrequency (RF) surgical-sponge detection system on time spent searching for surgical sponges. The study included 27,637 procedures during nine months before and after implementing an RF surgical-sponge detection system. After implementation of the system, time spent searching for sponges was reduced by 79.58%, the percentage of unreconciled counts was reduced by 71.28%, and time spent using radiography to rule out a retained sponge was reduced by 46.31%. This resulted in a reduction of costs. These findings should be used as part of a comprehensive cost analysis of alternative methods when evaluating RF sponge detection technology. © AORN, Inc, 2019
Keywords: radiofrequency; retained surgical item; sponge count; sponge detection; unreconciled count

The practice of ‘urethral sounding’ complicated by retained magnetic beads within the Bladder and Urethra: Diagnosis and review of management - Lindsay, J.S. (American Journal of Case Reports, 2019)
Objective: Background: Case Report: Conclusions: Rare disease The emergency treatment of a retained foreign body within the urethra and bladder is an uncommon clinical scenario within adult urology. Beyond the medical field, the placement of an object/s into the urethra is known as ‘urethral sounding’ and encompasses a sexual practice performed to heighten arousal and pleasure. The medical literature highlights the morbidity associated with this practice, most commonly when the sounding device can no longer be retrieved by the participant. A case report involving an 18-year-old male requiring endoscopic retrieval of 60 magnetic metal beads intended for the purpose of urethral sounding. The management was uncomplicated and the patient suffered no longterm complications at follow-up. A brief review of the literature reveals 9 reports since 2013 of magnetic beads retained within the bladder following this autoerotic practice in adults. The insertion of multiple small magnetic beads into the urethra is an inadvisable method for use in the practice of urethral sounding due to the lack of non-operative management options. This is due to the high risk of the magnetic beads forming a magnetized cluster once the chain enters the bladder. All cases assessed report successful management with both minimally invasive and open approaches. © Am J Case Rep, 2019.
Keywords: Foreign bodies; Urologic surgical procedures; Urology

Endoscopic management of gastric perforation secondary to chicken bone: A report of 2 cases - Sidiqi, M.M.; Sharma, S.; Muhammed, A.H. (International Journal of Surgery Case Reports, 2019)
Introduction: Ingested foreign bodies (IFB) can uncommonly cause perforation of the gastrointestinal tract. The traditional management is surgical exploration via laparotomy or laparoscopy, although endoscopic options are now gaining prominence. Presentation of case: We present two patients with almost identical clinical presentations of post-prandial abdominal pain and anorexia. On examination they were haemodynamically stable with localised epigastric tenderness. Both patients underwent CT scan of the abdomen, with one scan revealing a foreign body in the stomach penetrating the full thickness of the gastric wall with the tip lying extraluminally. They subsequently underwent endoscopy where a chicken bone was found perforating the wall of the stomach. This was removed via snare and endoscopic clips were used to close the site of perforation. Discussion: The majority of ingested foreign bodies pass through the gastrointestinal tract harmlessly. However some IFBs can cause significant complications like bowel obstruction, bleeding, abscess formation, migration to other organs, and in our case perforation. The diagnosis may be delayed due to an insidious clinical presentation especially if the patient does not recall ingesting anything untoward. Our patients managed to avoid surgery by undergoing successful endoscopic therapy. Conclusion: In selected cases, endoscopic management is more cost-effective, minimally invasive, has less post-operative complications, and leads to a more expeditious recovery. Therefore, the role of therapeutic endoscopy for gastric perforations secondary to foreign bodies should always be considered. © 2019 The Author(s)
Keywords: Complication; Endoscopy; Foreign-body; Gastric; Perforation

Treatment of penetrating trauma to the buttock assisted by spinal endoscopy - Long, Z.-S.; Nie, X.-Y.; Zhang, Y.-W. (Journal of International Medical Research, 2019)
Objective: Penetrating trauma to the buttock is relatively common. Because of the location of the trauma and complicated peripheral anatomical structures, surgery to the area can be difficult. We report the cases of 2 patients who sustained penetrating trauma to the buttock and underwent operative treatment assisted by spinal endoscopy. Methods: With the rapid development of minimally invasive spine surgery techniques in recent years, especially the wide application of endoscopy, we treated 2 cases of penetrating trauma with endoscopic probing within the wound channel, followed by hemostasis and postoperative irrigation and drainage. Results: Drainage tubes were removed from the 2 patients within 7 days after the surgery. Their wounds were healing well and they were discharged from the hospital within 12 days. Conclusions: If there is no injury to the large blood vessels, intestines, or urinary system, satisfactory clinical results can be obtained using spinal endoscopy to probe, irrigate, and identify foreign objects, when combined with hemostasis, postoperative short-term irrigation and debridement, and the use of antibiotics. © The Author(s) 2019.
Keywords: buttock; minimally invasive; open injury; penetrating trauma; soft tissues; Spinal endoscopy

Intralenticular foreign body: A case report and literature review - Lin, Y.-C.; Kuo, C.-L.; Chen, Y.-M. (Taiwan Journal of Ophthalmology, 2019)
The purpose of this manuscript was to provide a better understanding of patients with intralenticular foreign bodies (FBs) and also to review the reported cases, including clinical presentation, diagnosis, management, and visual outcome. A 50-year-old male was referred to our clinic with suspected intraocular FB. Under slit-lamp examination, a full-thickness corneal wound with localized corneal edema at the temporal lower peri-limbal area was revealed. Seidel test did not indicate any wound leakage. The corresponding iris was depigmented, but there was no penetrating hole. The anterior chamber was deep with cells, but the lens, vitreous, and fundus were normal. B-scan ultrasonography and orbital computed tomography were performed, but no intraocular FB was detected. On the 2 nd day, a zonal cortical cataract and posterior subcapsular cataract formed rapidly. Left-eye bare vision dramatically decreased from 20/100 to counting fingers. One month later, the patient received elective extracapsular cataract extraction. A fine metal thread was completely embedded in the lens; the lens and FB were removed together during the operation. The posterior capsule was not injured; an intraocular lens was implanted in the capsular bag. Two months postoperatively, left-eye vision had returned to 20/25. No adverse events were noted during the follow-up period. In addition to the case report, some 28 previously reported cases of intralenticular FB are reviewed here. Patient demographics, time and course of management, and visual outcome are all summarized and compared. © 2019 Wolters Kluwer Medknow Publications. All Rights Reserved.
Keywords: Intralenticular foreign body; intraocular foreign body; metal foreign body

Endoscopic ultrasound-guided drainage of a mediastinal abscess caused by an ingested fish bone - Shibuya, H.; Ikehara, H.; Andoh, K.; Horii, T.; Moriyama, M.; Yamao, K.; Gotoda, T. (Internal Medicine, 2019)
Cases of foreign body ingestion are encountered relatively often in clinical settings; however, serious complications are rare. In such cases, mediastinal abscess due to esophageal perforation can become a life-threatening complication. Although highly invasive, surgery is often used as the first-line treatment. We herein report the case of a 65-year-old woman who presented with complaints of progressive odynophagia and dysphagia for 2 weeks following a fish meal. Enhanced cervicothoracic computed tomography demonstrated an enhanced round mass with peripheral contrasted margins. The mass was diagnosed as a mediastinal abscess resulting from esophageal perforation caused by a fish bone. Endoscopic ultrasound-guided abscess drainage (EUS-AD) was performed using a nasobiliary drainage tube (NDT). Two weeks later, the abscess had completely disappeared. EUS-AD was safe and effective in this case; furthermore, external drainage using NDT was suitable for this abscess located very close to the upper esophageal sphincter. © 2019 The Japanese Society of Internal Medicine.
Keywords: Endoscopic ultrasound-guided abscess drainage; Fish bone; Mediastinal abscess

An unusual mimic of intermittent bowel obstruction - Mohseni, M.; Kruse, B. (American Journal of Case Reports, 2019)
Objective: Background: Case Report: Conclusions: Rare disease Indigestible foreign material in the bowel can develop into bezoars. Intestinal obstruction can occur secondary to these bezoars. Phytobezoars specifically refer to those which accumulate as a result of undigested plant or other food material. A 42-year-old woman presented to the Emergency Department with a several-month history of right-sided abdominal pain associated with bouts of vomiting. She had no other significant medical history. Labs and computed tomography were unrevealing. Gastroenterology was consulted and performed endoscopy. A foreign body resembling an undigested mini bell pepper was found near the terminal ileum. This was removed, and the patient later reported significant improvement in her symptoms. Phytobezoars can lead to symptoms consistent with intestinal obstruction. The underlying pathology (e.g., masses, gastritis, adhesions, or dysmotility) can precipitate obstructions in the setting of bezoar formation. Surgical removal if often necessary for small-bowel obstructions secondary to bezoars, but in our case, fortunately, the foreign body was successfully removed during endoscopy. © 2019, International Scientific Information, Inc. All rights reserved.
Keywords: Bezoars; Endoscopy; Gastroenterology; Intestinal Pseudo-Obstruction

Infected chronic sinus secondary to a retained fragment of radial artery introducer sheath following percutaneous coronary intervention (PCI) - Ghazala, C.G.; Marrow, B.A.; Kearney, D.; Harrison, J.W.K. (BMJ Case Reports, 2019)
Coronary angiography and percutaneous coronary intervention (PCI) are frequently performed procedures in the UK and the developed world, with the radial artery becoming the preferred route of access. A chronically retained macroscopic fragment of radial artery introducer sheath is a very rare complication that has not, to our knowledge, been reported. We report the case of a 62-year-old woman who underwent PCI and developed a persisting infected sinus and abscess at the cannulation site despite multiple courses of antibiotics. Surgical exploration of the forearm recovered a foreign body that was found in the brachioradialis muscle and resembled a fragment of hydrophilic sheath. In conclusion, this case highlights that it is possible to leave macroscopic fragments of hydrophilic sheaths in situ. This is likely to be encountered during difficult access, especially during arterial spasm, and it is advised that the sheath and any other vascular access device is thoroughly inspected following removal. © 2019 BMJ Publishing Group Limited. No commercial re-use. See rights and permissions. Published by BMJ.
Keywords: cardiovascular medicine; interventional cardiology; interventional radiology; orthopaedic and trauma surgery; orthopaedics

Biliary Fascioliasis in Chronic Calcific Pancreatitis Presenting with Ascending Cholangitis and Biliary Stricture - Pattarapuntakul, T.; Ovartlarnporn, B.; Rojsanga, W.; Yungyoo, T. (Case Reports in Gastroenterology, 2019)
Biliary fascioliasis is a rare infection of the hepatobiliary system. In human, it is known to present with two main phases; acute phase (hepatic phase) presenting with abdominal pain or abnormal liver biochemistry then chronic phase (biliary phase) presenting with biliary obstruction or cholangitis. Optimal treatment of biliary fascioliasis consists of endoscopic retrograde cholangiography with removal of the parasite and single oral dose of triclabendazole. We report a rare case of biliary fascioliasis in chronic calcified pancreatitis who presented with ascending cholangitis and biliary stricture. A 63-years-old Thai man was referred to our hospital for treatment of clinical symptoms severe cholangitis. Magnetic resonance cholangiopancreatography showed evidence of distal common bile duct stricture associated with chronic calcific pancreatitis. ERCP was performed, that found a few amorphous filling defects in the common bile duct and distal biliary stricture. After removal of the foreign body of what seems to be a fluke parasite followed with single oral dose triclabendazole thereafter, the clinical symptom was improved dramatically. © 2019 S. Karger AG. All rights reserved.

Biomechanical Analysis of Fixation Devices for Basicervical Femoral Neck Fractures - Johnson, J.; Deren, M.; Chambers, A.; Cassidy, D.; Koruprolu, S.; Born, C. (Journal of the American Academy of Orthopaedic Surgeons, 2019)
Introduction:Basicervical femoral neck fractures are challenging fractures in geriatric populations. The goal of this study was to determine whether compression hip screw (CHS) constructs are superior to cephalomedullary constructs for the treatment of basicervical femoral neck fractures.Methods:Thirty cadaver femurs were osteotomized and received a CHS with derotation screw, a long cephalomedullary nail (long Gamma nail), or a short cephalomedullary nail (short Gamma nail). All constructs were loaded dynamically in compression until dynamic failure.Results:All failed CHS constructs demonstrated superior femoral head cutout. In the long Gamma nail and short Gamma nail groups, constructs failed by nail cutout through the medial wall of the trochanter or rotationally. Normalized fluoroscopic distance was found to increase markedly with an increasing cycle count when considering all treatment groups.Conclusions:Given our results and those of previous studies, we could not determine superiority of one implant and recommend that surgeons select fixation constructs based on the individual patient's anatomy and the surgeon's comfort with the implant. © American Academy of Orthopaedic Surgeons.

Wire bezoar - Unique presentation with duedenojejunal flexure perforation - Roy, A.K.; Lyngdoh, T.S. (JMS - Journal of Medical Society, 2019)
Bezoars are commonly found in the stomach, which are usually trichobezoar or phytobezoar. Signs and symptoms depend on the location and type of bezoars. Small intestinal perforation following wire bezoar has not been reported earlier. We report a 26-year-old schizophrenic male presented to us with features of perforation peritonitis. Preoperative abdominal radiograph was suggestive of unexpected intraoperative findings. Celiotomy with gastrostomy, feeding jejunostomy, and primary closure of perforation over a large bore T-tube was done. The patient was discharged after prolonged hospitalization. Wire bezoar presenting with jejunal perforation has not been reported earlier although every high possibility of perforation exists when the wires are pointed and long, where negotiation at the duodenojejunal flexure may be difficult. © 2019 Journal of Medical Society.
Keywords: Jejunal perforation; Schizophrenia; Wire bezoar

Bladder calculus causing large bowel obstruction - Bellomo, A.; Kwati, M.; Monzon, J.; Ogunrombi, B. (Annals of African Surgery, 2019)
Urinary tract calculi are fairly common, though bladder calculi are less common, accounting for only 5% of urinary tract calculi. Bladder calculi, particularly large bladder calculi, are usually associated with pathology in the urinary tract. Such pathologies include urethral strictures, bladder neck contractures, benign prostatic hypertrophy, neurogenic bladder and foreign bodies in the bladder. Bladder calculi are more common in men than in women. Bladder calculi causing bowel obstruction have been documented in the literature before but they remain very rare. © 2019 Author. This work is licensed under the Creative Commons Attribution 4.0 International License.
Keywords: Bladder calculus; Large bowel obstruction

Repeated lumps and infections: A case report on breast augmentation complications - Zhang, M.-X.; Li, S.-Y.; Xu, L.-L.; Zhao, B.-W.; Cai, X.-Y.; Wang, G.-L. (World Journal of Clinical Cases, 2019)
BACKGROUND Polyacrylamide hydrogel (PAAG) injections were once common in breast augmentation and have been prohibited for augmentation mammaplasty in China since a large number of patients who underwent breast augmentation with PAAG injections have continued to seek medical advice as a result of related complications. Among all these complications, distant migration is relatively rare. CASE SUMMARY A 49-year-old female presented at the hospital with a one-year history of a vulvar lump. The sonography of the lump showed several subcutaneous fluid-filled regions from the left vulva to the pubic symphysis, which suggested possible fat liquefaction. An enhanced magnetic resonance imaging (MRI) revealed a cystic area, which was considered a benign lesion. Intraoperative observations showed that the mass did not have an obvious capsule, the subcutaneous tissue presented as a cavity, and some yellow material came out of this cavity. A culture of the drainage did not show bacterial contamination. Histopathology revealed a foreign body granuloma. After resection and closed drainage, lumps were successively observed in the left lower abdomen and the bilateral hypochondriac region with infections. Sonography found that the hypoechoic areas in the bilateral hypochondriac region seemed continuous with deep in the breasts. The patient reported that she had undergone surgery with PAAG injections 20 years ago after she was repeatedly asked about her past history. Finally, a diagnosis of distant migration of PAAG was made. CONCLUSION PAAG gel can migrate after long periods of time. A diagnosis should not be limited to the area where the symptom develops. © The Author(s) 2019.
Keywords: Breast augmentation; Case report; Distant migration; Repeated infection; Repeated lump

In vitro and in vivo evaluation of a dextran-graft-polybutylmethacrylate copolymer coated on CoCr metallic stent - Delattre, C.; Velasquez, D.; Roques, C.; Pavon-Djavid, G.; Ollivier, V.; Lokajczyk, A.; Avramoglou, T.; Gueguen, V.; Louedec, L.; Caligiuri, G.; Jandrot-Perrus, M.; Boisson-Vidal, C.; et al. (BioImpacts, 2019)
Introduction: The major complications of stent implantation are restenosis and late stent thrombosis. PBMA polymers are used for stent coating because of their mechanical properties. We previously synthesized and characterized Dextran-graft-polybutylmethacrylate copolymer (Dex-PBMA) as a potential stent coating. In this study, we evaluated the haemocompatibility and biocompatibility properties of Dex-PBMA in vitro and in vivo. Methods: Here, we investigated: (1) the effectiveness of polymer coating under physiological conditions and its ability to release Tacrolimus®, (2) the capacity of Dex-PBMA to inhibit Staphylococcus aureus adhesion, (3) the thrombin generation and the human platelet adhesion in static and dynamic conditions, (4) the biocompatibility properties in vitro on human endothelial colony forming cells (ECFC) and on mesenchymal stem cells (MSC) and in vivo in rat models, and (5) we implanted Dex-PBMA and Dex-PBMA TAC coated stents in neointimal hyperplasia restenosis rabbit model. Results: Dex-PBMA coating efficiently prevented bacterial adhesion and release Tacrolimus®. Dex-PBMA exhibit haemocompatibility properties under flow and ECFC and MSC compatibility. In vivo, no pathological foreign body reaction was observed neither after intramuscular nor intravascular aortic implantation. After Dex-PBMA and Dex-PBMA TAC coated stents 30 days implantation in a restenosis rabbit model, an endothelial cell coverage was observed and the lumen patency was preserved. Conclusion: Based on our findings, Dex-PBMA exhibited vascular compatibility and can potentially be used as a coating for metallic coronary stents. © 2019 The Author(s).
Keywords: Animal model; Biocompatibility; Dextran; Haemocompatibility; In vitro; Stent

Management of Anterior Chamber Dislocation of a Dexamethasone Implant - Nguyen, T.L.; Wolfensberger, T.J. (Klinische Monatsblatter fur Augenheilkunde, 2019)
Purpose To characterise the surgical removal technique of a dislocated dexamethasone implant in the anterior chamber and to gauge its success by analysing corneal transparency and subsequent visual acuity recovery in the postoperative phase. Methods Description of a patient who presented with an anterior chamber dexamethasone implant migration through an inferior iridotomy performed previously for a silicone oil fill in aphakia. Visual acuity had dropped to counting fingers due to marked corneal oedema. Results The implant was removed using a 23-g needle aligned with the axis of the implant through a paracentesis. After the clinical follow-up at 2 months, best-corrected visual acuity had returned to 0.2, which remained stable at the last follow-up at 14 months with an intraocular pressure of 10 mmHg. The corneal oedema resolved completely. Conclusion This novel surgical management of a dexamethasone implant dislocation into the anterior chamber was successful and resulted in no long-term corneal damage when the implant was removed without delay. A repeated Ozurdex injection in patients with previous inferior iridotomy may require prior suturing of the iridotomy. © Georg Thieme Verlag KG Stuttgart. New York.
Keywords: anterior chamber migration; corneal oedema; dexamethasone implant

The effect of fibroblast growth factors in grafted fascia into the vocal fold of rabbits - Carvalho, E.G.B.; Machado-Júnior, A.J.; Pauna, H.F.; Nicola, E.M.D.; Altemani, A.M.A.M.; Crespo, A.N. (International Archives of Otorhinolaryngology, 2019)
Introduction The human larynx is a very important organ for communication. Many conditions lead to scarring of the vocal folds, decreasing voice quality. Objective We aimed to determine whether fibroblast growth factors (FGFs) may influence tissue integration of grafted fascia into the vocal folds of an animal model. Methods This is an experimental animal study with 12 adult rabbits that were submitted to a grafting fragment obtained from superficial cervical fascia into the vocal fold lamina propria, bilaterally. The right vocal fold was injected with FGFs. The animals were sacrificed after 1 month or 12 months, depending on the group they were assigned to, and a histological analysis of their vocal folds was performed. We analyzed the histological changes (such as the presence of fibrosis and neovascularization) induced by the acute or chronic inflammatory reactions. Results The FGFs induced acute inflammatory changes in all animals after 1 month of the initial experiment. The presence of FGFs triggered more fibrosis than the expected due to the surgical procedure itself when compared with the control side of all animals after 12 months of the initial experiment. Conclusions Fibroblast growth factors alone do not represent a good therapeutic option in phonosurgery, since we observed higher levels of fibrosis in the vocal fold lamina propria. Further studies combining more substances may be necessary to elucidate the best option to be used in this kind of surgery. Copyright © 2019 by Thieme Revinter Publicações Ltda, Rio de Janeiro, Brazil.
Keywords: Fascia; FGFs; Fibroblasts; Grafting; Rabbits; vocal folds

Refinement of estimates of mortality risk using the Radiologic Severity Index in hematologic malignancy patients with respiratory syncytial virus infection - Sheshadri, A.; Karimipour, M.; Vakil, E.; Bashoura, L.; Godoy, M.; Arain, M.H.; Evans, S.E.; Dickey, B.F.; Ost, D.E.; Chemaly, R.F.; Faiz, S.A. (Transplant Infectious Disease, 2019)
Background: Immunocompromised hematologic malignancy (HM) patients experience high mortality after respiratory syncytial virus (RSV) lower respiratory tract infection (LRTI). We measured radiologic severity to determine whether it could improve the performance of 60-day mortality models based only upon immunodeficiency severity. Methods: We studied 155 HM patients, including 84 hematopoietic cell transplant recipients, who developed RSV LRTI from 2001 to 2013. We measured immunodeficiency using lymphopenia (lymphocyte count <200 cells/mm3), Immunodeficiency Severity Index (ISI), and Severe Immunodeficiency (SID) criteria. Radiologic severity was measured by the Radiologic Severity Index (RSI, range 0-72) at time of LRTI (baseline-RSI) and peak severity (peak-RSI). Delta-RSI was defined as the difference between baseline-RSI and peak-RSI. We used logistic regression models to measure the association of immunodeficiency and RSI with 60-day all-cause mortality, and measured model discrimination using areas under the receiver-operating characteristics curves, calibration using Brier scores, and explained variance using pseudo-R2 values. Results: Forty-one patients died within 60 days of RSV LRTI. Severe immunodeficiency was associated with higher mortality. Peak-RSI (odds ratio [OR] 1.06/point, 95% confidence interval [CI] 1.04-1.08), and delta-RSI (OR 1.07/point, 95% CI 1.05-1.10) were associated with 60-day mortality after RSV LRTI, but not baseline-RSI. Addition of peak-RSI or delta-RSI to baseline immunodeficiency improved the discrimination, calibration, and explained variance (P < 0.001) of 60-day mortality models. Conclusions: Although baseline immunodeficiency in HM patients helps predict 60-day mortality after RSV LRTI, mortality risk estimates can be further refined by also measuring LRTI progression using RSI. RSI is well-suited as a marker of LRTI severity in RSV infection. © 2019 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd

A comparative study on patient safety attitude between nurses and doctors in operating rooms - Kwon, E.; Kim, Y.W.; Kim, S.W.; Jeon, S.; Lee, E.; Kang, H.-Y.; Nam, S.; Kim, M. (Journal of International Medical Research, 2019)
Objective: To investigate and compare the attitudes of operating room nurses and doctors regarding patient safety, performance of surgical time-out and recognition of count error. Methods: This cross-sectional study recruited operating room nurses, surgeons and anaesthesiologists between 1 August 2015 and 5 February 2016. A Safety Attitude Questionnaire was used to analyse the three elements in both groups of operating room staff (nurses and doctors). Results: The study analysed the questionnaires from 171 participants; 95 nurses (55.6%) and 76 doctors (44.4%). Differences exist between doctors and nurses regarding teamwork climate, working conditions, perception of management and the recognition of stress. On the performance of surgical time-out, nurses showed higher scores on way of counting, while doctors showed higher scores on the time-out procedure itself. Also, doctors believed they actively cooperated with the nurses, while nurses believed they did not receive cooperation. Scores for the recognition of count error were higher in nurses than in doctors. More experienced operating room staff showed higher scores than younger less experienced staff. Conclusions: Perceptual differences among doctors and nurses need to be minimized for the safety of the patient in the operating room. © The Author(s) 2019.
Keywords: nurse; operating rooms; retained surgical items; Surgical safety; surgical time-out

Feasible advantage of bioactive/bioresorbable devices made of forged composites of hydroxyapatite particles and poly-L-lactide in alveolar bone augmentation: A preliminary study - Sukegawa, S.; Kawai, H.; Nakano, K.; Kanno, T.; Takabatake, K.; Nagatsuka, H.; Furuki, Y. (International Journal of Medical Sciences, 2019)
Purpose: We aimed to document the clinical usefulness of uncalcined and unsintered hydroxyapatite (u-HA) particles and poly-L-lactide (PLLA) composite materials and their advantageous properties. Methods: Between April 2016 and March 2018, five patients required anterior maxillary alveolar ridge augmentation using fixation with u-HA/PLLA screws for an onlay block bone graft harvested from the mandibular ramus at our institute. Bone biopsies were obtained from the dental implantation site following bone healing for histomorphometric and immunohistochemical (IHC) measurements. Results: Many stromal cells were positive for Osterix, RUNX2, and SOX9 but were negative for CD68. On cell counting, based on IHC staining for Osterix, RUNX2, SOX9 and CD68 from peripheral u-HA/PLLA screw or bone areas, both areas consistently showed no significant difference in terms of Osterix, RUNX2, and SOX9. Hematoxylin-eosin staining revealed direct bone connection to the biomaterials, and no inflammatory cells infiltrated the areas surrounding the bone or artificial material. Area between the bone and u-HA/PLLA screw was seamless with no boundary. Round small cells and immature fibroblasts were noted. The new bone showed the presence of bone lamellae, normal osteocytes, and osteoblasts. Conclusion: The u-HA/PLLA materials showed excellent biodegradability and bioactive osteoconductivity. In addition, this material induced no apparent inflammatory or foreign body reactions following implantation, and it directly bonded to the human bone. Therefore, this u-HA/PLLA material seems ideal and most suitable for use as a substitute for osteosynthesis. © Ivyspring International Publisher.
Keywords: Biodegradability; Bone regeneration; Osteoconductivity; Poly-L-lactide; Uncalcined and unsintered hydroxyapatite

Suture wear particles cause a significant inflammatory response in a murine synovial airpouch model - Lovric, V.; Goldberg, M.J.; Heuberer, P.R.; Oliver, R.A.; Stone, D.; Laky, B.; Page, R.S.; Walsh, W.R. (Journal of Orthopaedic Surgery and Research, 2018)
Background: Commonly used contemporary orthopaedic sutures have been identified as a potential causative factor in the development of post-arthroscopic glenohumeral chondrolysis. Currently, little is known about the body's immune response to these materials. The aim of this study was to examine the biological response of synovial tissue to three commonly used orthopaedic sutures, using a murine airpouch model. Methods: Fifty rats were used in this study (ten per group). An airpouch was created in each rat, and test materials were implanted. Test materials consisted of an intact polyethylene terephthalate suture with a polybutilate coating (suture A), an intact polyethylene suture braided around a central polydiaxannone core (suture B), an intact polyethylene/polyester cobraid suture with a silicone coating (suture C), and particles of suture C (particles C). Rats were sacrificed at 1 or 4weeks following implantation. Histological (multinucleated giant cell count) and immunohistochemical (expression of matrix metalloproteinases MMP-1,-2,-3,-9,-13) markers of inflammation were examined. Results: Multinucleated giant cells were present in all specimens containing suture material but not in the control specimens. No significant differences were found in the number of giant cells between the intact suture groups at either time point. Significantly higher numbers of giant cells were noted in the particles C group compared to the intact suture C group at both time points (p=0.021 at 1week, p=0.003 at 4weeks). Quantitative analysis of immunohistochemical staining expression at 4weeks showed that significantly more MMP (-1,-2,-9,-13) was expressed in the particles C group than the intact suture C group (p=0.024, p=0.009, p=0.002, and p=0.007 for MMP-1, MMP-2, MMP-9, and MMP-13, respectively). No significant difference was seen in the expression of MMP-3 (p=0.058). Conclusions: There were no differences observed between the biological reactivity of commonly used intact orthopaedic sutures A, B, and C. However, wear particles of suture C elicited a significantly greater inflammatory response than intact suture alone. This was confirmed by increased numbers of multinucleated giant cells as well as MMP (-1,-2,-9,-13) expression. Further studies are needed to determine whether this inflammatory response may play a role in the development of post-arthroscopic glenohumeral chondrolysis or interfere with biological healing. These findings have important clinical implications relating to surgical technique and surgical implant design. © 2018 The Author(s).
Keywords: Foreign body reaction; Inflammatory response; Matrix metalloproteinase; Post-arthroscopic glenohumeral chondrolysis; Suture; Suture wear particles

Buried bumper syndrome presenting with bleeding - Bamakhrama, K.; Aldaham, T.A.; Alassaf, O. (BMJ Case Reports, 2018)
Buried bumper syndrome (BBS) is a relatively rare complication of percutaneous endoscopic gastrostomy (PEG) feeding. In this paper, we report the case of a 74-year-old man who attended the emergency department with bleeding from the PEG tube site that was later confirmed by endoscopy to be BBS. The treatment consisted of a PEG tube replacement with a 10-day course of antibiotics. Furthermore, this report discusses possible signs, symptoms and physical examination signs suggesting BBS. It can cause serious complications that might sometimes be fatal. Therefore, the diagnosis needs to be done swiftly and the patient treatment to start without delay. BBS should always top the differentials of physicians once suspected. © 2018 BMJ Publishing Group Limited.
Keywords: endoscopy; gastrointestinal system; parenteral/enteral feeding

Case series: Use of stromal lenticule as patch graft - Song, Y.J.; Kim, S.; Yoon, G.J. (American Journal of Ophthalmology Case Reports, 2018)
Purpose: To introduce cases of the use, as patch grafts, of stromal lenticules obtained by small incision lenticule extraction (SMILE) surgery. Observations: Case 1 was a 79-year-old man who presented with Ahmed-valve-tube exposure in his left eye. His uncorrected visual acuity (UCVA) was 20/40, best-corrected visual acuity (BCVA) 20/32, and intraocular pressure (IOP) 11 mmHg. He was treated with stromal lenticule patch that had been extracted by SMILE surgery. The patch was positioned underneath of the conjunctiva and sutured to it. At postoperative 8 months, the graft site was well maintained without Ahmed valve-tube exposure, the UCVA was 20/32, BCVA 20/20, and IOP 12 mmHg. Case 2 was a 60-year-old man who presented with Ahmed-valve-tube exposure in his right eye. His UCVA was finger-count (FC) 30 cm, his BCVA 20/125, and his IOP 14 mmHg. He was treated with stromal lenticule patch by the same method as employed in case 1. At postoperative 10 days, tube re-exposure and displacement of the Ahmed valve external plate toward the limbus area occurred due to loosening of the anchoring suture. So, we removed the Ahmed valve device, which had been implanted in the supero-temporal area, and performed new Ahmed valve implantation, with a stromal lenticule flap instead of a partial scleral flap, in the supero-nasal area. As of 6 months post-reoperation, the patient was stable, with UCVA 20/200, BCVA 20/40 and IOP 13 mmHg. Case 3 was a 74-year-old man who presented with bullous keratopathy in his right eye, which was blind. Due to severe adhesions, his conjunctiva could not cover the entire cornea. Therefore, we performed a stromal lenticule patch graft with conjunctival advance flap. At postoperative 3 months, the patient's right eye was stable, without displacement or melting of the lenticule graft. Conclusions & importance: It is suggested that the stromal lenticule, with its biocompatibility, sufficient strength, ease of handling and low cost, is a useful patch graft for various therapeutic purposes in the ophthalmic field. © 2018 The Authors
Keywords: Ahmed valve tube exposure; Bullous keratopathy; Patch graft; Stromal lenticule

Current Indications for Transnasal Esophagoscopy: An American Broncho-Esophagological Association Survey - Best, A.R.; Halum, S.L.; Parker, N.P. (Annals of Otology, Rhinology and Laryngology, 2018)
Introduction: The aim of this study was to evaluate the current indications for and clinical factors influencing the use of transnasal esophagoscopy (TNE). Methods: An online survey was sent to American Broncho-Esophagological Association members, including questions on demographics, indications, and factors influencing the use of TNE. Results: Sixty of 251 members (24%) completed the survey. Ninety-three percent of respondents reported academic practices, while 98% practice in medium to large urban settings. Thirty-five (58%) completed laryngology fellowships. Mean monthly TNE procedure count was 7.15 (range, <1-35). The most common indications were dysphagia (82%), biopsy (50%), and laryngopharyngeal reflux (47%). Chronic cough, head and neck cancer screening, gastroesophageal reflux (GER), and tracheoesophageal puncture were also commonly reported indications (44% each). For laryngopharyngeal reflux and GER, most respondents perform TNE for recalcitrant disease following a medical trial of at least 3 months. Long-standing GER symptoms, documentation of GER on pH and impedance testing, and abnormal findings on previous esophagoscopy lead to greater TNE use. Specific dysphagia indications included abnormal esophagographic findings (70%), history or examination localizing to the esophagus (60%), solid dysphagia only (53%), and solid and/or liquid dysphagia (40%). The primary sites most likely to prompt TNE use for head and neck cancer surveillance were the esophagus (92.3%) and hypopharynx (84.6%). Balloon dilation was the most common indication for which respondents do not currently perform TNE but would like to (n = 8). Conclusions: TNE indications have not been well established. According to respondents from the American Broncho-Esophagological Association, TNE is most commonly used for dysphagia and laryngopharyngeal reflux and slightly less so for GER and head and neck cancer screening and surveillance. Several clinical indicators were identified that influence the decision to perform TNE. © The Author(s) 2018.
Keywords: dysphagia; esophagoscopy; globus; office-based; reflux; transnasal

The inflammatory response to ventricular assist devices - Radley, G.; Pieper, I.L.; Ali, S.; Bhatti, F.; Thornton, C.A. (Frontiers in Immunology, 2018)
The therapeutic use of ventricular assist devices (VADs) for end-stage heart failure (HF) patients who are ineligible for transplant has increased steadily in the last decade. In parallel, improvements in VAD design have reduced device size, cost, and device-related complications. These complications include infection and thrombosis which share underpinning contribution from the inflammatory response and remain common risks from VAD implantation. An added and underappreciated difficulty in designing a VAD that supports heart function and AIDS the repair of damaged myocardium is that different types of HF are accompanied by different inflammatory profiles that can affect the response to the implanted device. Circulating inflammatory markers and changes in leukocyte phenotypes receive much attention as biomarkers for mortality and disease progression. However, they are seldom used to monitor progress during and outcomes from VAD therapy or during the design phase for new devices. Even the partial reversal of heart damage associated with heart failure is a desirable outcome from VAD use. Therefore, improved understanding of the interplay between VADs and the recipient's inflammatory response would potentially increase their uptake, improve patient lives, and fuel research related to other blood-contacting medical devices. Here we provide a review of what is currently known about inflammation in heart failure and how this inflammatory profile is altered in heart failure patients receiving VAD therapy. © 2007 - 2018 Frontiers Media S.A.
Keywords: cytokines; heart failure; inflammation; leukocytes; ventricular assist devices

Recurrent epibulbar dermoid cyst treated with amniotic membrane implant a case report 11 Medical and Health Sciences 1113 Ophthalmology and Optometry - Villalón, M.L.; Leal, M.D.L.Á.; Chávez, J.R.; Santillán, E.M.; Lares-Asseff, I.; Loera, V.; Valencia, L.; Camacho, B.; Alvarado, B.; Cervantes, V.; Patrón, L.; Almanza, H. (BMC Surgery, 2018)
Background: The dermoid cyst considered a cystic teratoma derived from embryonic germinal epithelium is a slow-growing benign tumour. Dermoid cysts may occur in the orbital and periorbital region in paediatric patients and are often recurrent. The surgical approach depends upon the site of the lesion, superficial or deep. To our knowledge, this is the first described case of a patient with resection of dermoid cyst treated with human amniotic membrane implant and topical application of 0.02% mitomycin C. Case presentation: We present a case of a 12-year-old male with a tumour in the superotemporal region of the right eye (RE). Symptoms included decreased visual acuity (VA), burning eye, foreign body sensation, and photophobia of the affected eye. A physical examination detected blepharospasm. Ophthalmic examination of his RE, fingers count from a 1-2 m distance, showed no improvement with pinhole. Visual acuity was 20/20 on the left eye (LE). The bio-microscopic examination confirmed the presence of a tumour mass (15 mm × 12 mm) on the surface of the RE, invading the superotemporal sector. The tumour had a lobulated appearance, a shiny and vascularized surface covered by conjunctiva, a pearlescent-pink colour, a medium consistency, was renitent and painless. An ultrasound scan revealed atrophy of the pigmented retinal epithelium with scleral indentation of the RE. A computed tomography (CT) scan revealed a recurrent lesion consistent with an epibulbar dermoid cyst. Surgical excision of the lesion was performed and a human amniotic membrane (HAM) graft and topical 0.02% mitomycin C (MMC) were applied. Histopathological analysis confirmed the diagnosis of recurrent dermoid cyst. Conclusion: In this case report, we describe a case of recurrent epibulbar dermoid cyst treated with complete resection; topical MMC and HAM implant with good clinical outcome of the lesion and implant adhesion. Resection of a cyst of the ocular surface is not recommended when a large epibulbar dermoid tissue needs to be resected and no HAM graft is available. © 2018 The Author(s).
Keywords: Amniotic membrane; Dermoid cyst; Mitomycin c

Pulmonary artery embolism by a metal fragment after a booby trap explosion in a combat patient injured in the armed conflict in East Ukraine: A case report and review of the literature 11 Medical and Health Sciences 1103 Clinical Sciences - Khomenko, I.; Tsema, I.; Shklyarevych, P.; Kravchenko, K.; Holinko, V.; Nikolaienko, S.; Shypilov, S.; Gerasimenko, O.; Dinets, A.; Mishalov, V. (Journal of Medical Case Reports, 2018)
Background: Pulmonary artery embolization due to projectile embolus is a rare complication in combat patients. Such embolization is rare for combat patients in the ongoing armed conflict, in East Ukraine since 2014. Case presentation: We report a clinical case of a 34-year-old Caucasian combat patient who was injured after an explosion of a booby trap hand grenade. This soldier was diagnosed with severe abdominal and skeletal trauma: damage of the duodenum and transverse colon, internal bleeding due to inferior vena cava damage and fractures of both lower extremities. The patient was treated at a highly specialized surgical center within the "golden hour" time. Whole-body computed tomography scan was performed as a routine screening method for hemodynamically stable patients, at which we identified a projectile embolus due to the explosion of a booby trap hand grenade in the right midlobar pulmonary artery. Our patient had no clinical manifestation of pulmonary artery embolism. At follow-up, our patient was diagnosed with the following complications: multiple necrosis and perforations of the transverse colon leading to a fecal peritonitis; duodenum suture line leakage caused the formation of a duodenal fistula; postoperative wound infection. These complications required multiple secondary operations, and in accordance to the principles of damage-control tactics, the extraction of projectile-embolus was postponed. Open surgery retrieval of the metal fragment was successfully performed on the 80th day after injury. Our patient was discharged from the hospital on day 168th after injury. Conclusions: Literature analysis shows a significant difference of clinical management for patient with projectile embolism in hybrid war settings as compared to previously described cases of combat and civil gunshot injuries. Damage control tactics and the concept of the "golden hour" are highly effective for those injured in a hybrid war. A whole-body computed tomography scan is an effective screening method for asymptomatic patients with projectile-embolism of the great vessels. The investigation of a greater cohort of combat patients with severe injuries and projectile-embolism should be performed in order to develop a better guideline for these patients and to save more lives. © 2018 The Author(s).
Keywords: Armed conflict in Ukraine; Combat trauma; Damage control; Hybrid warfare; Projectile-embolus

Retained surgical needle and gauze after cesarean section and adnexectomy: A case report and literature review - Lovrec, V.G.; Cokan, A.; Lukman, L.; Arko, D.; Takač, I. (Journal of International Medical Research, 2018)
Although the incidence of retained surgical items (RSIs) is low, it is nevertheless an important preventable cause of patient injury that can ultimately lead to the patient’s death and to subsequent high medical and legal costs. Unintentional RSI is the cause of 70% of re-interventions, with a morbidity of 80% and mortality of 35%. The most common RSIs are sponges or gauze (gossypiboma or textiloma), while retained surgical instruments and needles are rare. Perioperative counting of equipment and materials is the most common method of screening for RSIs, while a diagnosis can later be confirmed by the clinical appearance and by imaging studies. We present a rare case of a 43-year-old patient who was admitted to our hospital because of two retained needles following a cesarean section, despite several subsequent laparotomies. One needle had been removed previously, but in addition to the remaining needle, we also removed a retained gauze. The diagnosis of RSIs is extremely important, and safe surgical practices including the addition of new imaging technologies should be encouraged to detect RSIs. © The Author(s) 2018.
Keywords: Cesarean section; Gauze; Imaging; Needle; Retained surgical item; Surgery; Surgical count

Endoscopic Retrieval of Flanged Ventricular Catheters - Babadagli, M.E.; Cooke, D.; Walling, S.A.; McNeely, P.D. (Canadian Journal of Neurological Sciences, 2018)
Flanged ventricular catheters are now used infrequently. Many patients with longstanding hydrocephalus still harbor these catheters, either as their current ventricular catheter, or as a retained catheter from a prior implant. The removal of flanged ventricular catheters is sometimes necessary, and may be challenging due to intraventricular adhesions. We describe the use of an endoscopic technique for the successful retrieval of flanged ventricular catheters in two patients. The technique described in this report may be helpful for patients that have flanged ventricular catheters that must be removed. © Copyright 2018 The Canadian Journal of Neurological Sciences Inc.
Keywords: Cerebrospinal Fluid Shunts; Hydrocephalus; Neuroendoscopy

The use of a skin-stretching device combined with vacuum sealing drainage for closure of a large skin defect: A case report - Lei, Y.; Liu, L.; Du, S.-H.; Zong, Z.-W.; Zhang, L.-Y.; Guo, Q.-S. (Journal of Medical Case Reports, 2018)
Background: This case report presents the treatment of a large infected skin defect, which was caused by an accidental explosion, through a skin-stretching device combined with vacuum sealing drainage. To the best of our knowledge, the area of the wound that we treated may currently be the largest. Case presentation: A 41-year-old Asian man was transferred to the Center of Trauma Surgery of our hospital for the closure of an open infected wound with a large skin defect in his right lower limb caused by an accidental explosion of 100 pieces of blasting cap. The wounds located in his right gluteal were approximately 40 cm × 35 cm. On admission, the wounds had hemorrhaged, exhibiting a darkened appearance, and included scattered metallic foreign bodies. Debridement of his right gluteal area was conducted 6 hours after injury. Subsequently, a skin-stretching device combined with vacuum sealing drainage was applied to reduce the skin defect. This treatment proved to be valuable for the closure of the skin defect and to attain successful functional rehabilitation without sciatic nerve entrapment or amputation in this case. Conclusions: It is difficult to close large skin defects, especially when they are infected. The application of a skin-stretching device combined with vacuum sealing drainage should be commonly applied to treat infected wounds because it is a safe and easy operative technique. © 2018 The Author(s).
Keywords: Blast injury; Skin defect; Skin stretching; Vacuum sealing drainage

Growth of Cutibacterium acnes is common on osteosynthesis material of the shoulder in patients without signs of infection - Both, A.; Klatte, T.O.; Lübke, A.; Büttner, H.; Hartel, M.J.; Grossterlinden, L.G.; Rohde, H. (Acta Orthopaedica, 2018)
Background and purpose — Cutibacterium acnes, formerly known as Propionibacterium acnes, is often isolated from deep tissues of the shoulder. It is recognized as an important causative agent of foreign-material associated infections. However, the incidence and significance of its detection in tissues from patients without clinical evidence for infection is unclear. We assessed the incidence of C. acnes colonization of osteosynthesis material in asymptomatic patients, and evaluated the short-term outcome in relation to the microbiological findings. Patients and methods — We microbiologically analyzed osteosynthesis material of 34 asymptomatic patients after surgery on the clavicle. Material obtained from 19 asymptomatic patients after osteosynthesis of the fibula served as a control group. Patients were clinically followed up for 3–24 months after removal of the osteosynthesis material. Results — Bacteria were recovered from devices in 29 of 34 patients from the clavicle group. 27 of 29 positive samples grew C. acnes. Isolation of C. acnes was more common in male than in female patients. No bacterial growth was observed on foreign material from patients in the fibula group. All patients remained asymptomatic at follow-up. Interpretation — Growth of C. acnes is common on osteosynthesis material of the shoulder, especially in males. Samples were positive irrespective of clinical signs of infection. Therefore, detection of C. acnes in this clinical setting is of questionable clinical significance. The high positivity rate in asymptomatic patients discourages routine sampling of material in cases without clinical evidence for infection. © 2018, © 2018 The Author(s). Published by Taylor & Francis on behalf of the Nordic Orthopedic Federation.

Pulse Granulomas in Interval Appendectomy Specimens: Histochemical Identification of Cellulose Matter - Ban, S.; Fujii, A.; Takimoto, T.; Kikuchi, K.; Kang, W.; Namiki, Y.; Koyatsu, J.; Ueda, Y. (Case Reports in Gastroenterology, 2018)
Pulse granuloma is a rare pathologic condition considered to be a benign inflammatory reaction to foreign materials originated from ingested legume matter. As for pulse granulomas of the gastrointestinal tract, association with diverticular diseases is relatively common, but only a few pulse granuloma cases associated with appendicitis have been reported. This report presents histopathologic findings of pulse granuloma lesions observed in two appendectomy cases, with some histochemical examinations of cellulose matter which is reportedly a major component to provoke pulse granuloma reaction. Our patients in both cases were girls in their teens, and they underwent interval appendectomy for acute appendicitis. Both appendectomy specimens revealed ruptured walls with inflammatory granulation tissue with marked foreign body reaction including characteristic collections of ring-like, curled ribbon-like, and/or lobulated nephrosclerosis-like hyaline structures and various foreign bodies, in which microorganisms or amyloid deposition were not identified. The presence of cellulose matter was suggested by Sirius red stain, the IKI (iodine potassium iodide)-H 2 SO 4 method, and birefringence by polarized light. Appendectomy materials due to acute appendicitis would include pulse granuloma reaction provoked by ingested materials with cellulose. Pathologists should be familiar with the concept and histopathologic features of pulse granulomas to avoid misinterpreting them as vascular lesions and/or amyloid deposition, or any infectious organisms. © 2018 The Author(s). Published by S. Karger AG, Basel.
Keywords: Appendicitis; Appendix; Cellulose; Interval appendectomy; Pulse granuloma

Nocardia nova Tenosynovitis and Abscess after a Remote Gunshot Wound - Linder, K.A.; Herc, E.S.; Kauffman, C.A. (Infectious Diseases in Clinical Practice, 2018)
Nocardia nova is a less commonly isolated Nocardia species that was formerly classified as belonging to the Nocardia asteroides complex. This organism is a rare cause of primary cutaneous nocardiosis. We report a case of N. nova flexor tenosynovitis and abscess involving the right forearm after a remote inoculation injury. © 2018 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: cutaneous nocardiosis; Nocardia nova; retained foreign body

Mycobacterial granuloma on the staple line after pulmonary resection - Matsuoka, K.; Ueda, M.; Miyamoto, Y. (Asian Cardiovascular and Thoracic Annals, 2018)
Objective: It has been reported previously that granulomas can occur around nonabsorbable sutures, but that granuloma formation around the staple line is very rare. However, the increased use of thoracoscopic surgery is creating more opportunities to use automatic mechanical suturing equipment for pulmonary surgery, and it is expected that the incidence of granuloma around the staple line will increase. Methods: We retrospectively investigated the clinical records of 6 patients who developed nontuberculous mycobacterial granuloma on the staple line after pulmonary resection. We investigated their clinical characteristics and compared them with data in 16 cases of cancer recurrence. Results: Fluorodeoxyglucose uptake was detected in all 6 patients. Laboratory data including white blood cell counts and C-reactive protein levels were within normal ranges in all patients. There was no evident tendency in terms of age, sex, maximal standardized uptake value, or radiological findings. However, compared to cancer recurrence, mycobacterial granuloma around the staple line appeared after a longer period of time, and the proportion of patients who had a segmentectomy as the initial surgery was significantly higher. Conclusion: When growing shadows are observed near the staple line, it is difficult to differentiate between cancer recurrence and nontuberculous mycobacterial granuloma from computed tomography and laboratory findings. However, if a mass shadow around the staple line appears 2, 3, or more years after segmentectomy, it could be considered likely to be a granuloma. “Post-segmentectomy” and “late occurrence” are important attributes for distinguishing staple line granuloma from cancer recurrence. © The Author(s) 2018.
Keywords: foreign-body; Granuloma; Lung neoplasms; Mycobacterium; Pneumonectomy; Surgical staplers; Thoracic surgery; video-assisted

Perioperative outcomes in human immunodeficiency virus-infected patients – the PRO HIV study - Shanthamurthy, D.; Manesh, A.; Zacchaeus, N.G.P.; Roy, L.R.; Rupali, P. (International Journal of STD and AIDS, 2018)
It is estimated that a quarter of patients with HIV/AIDS undergo at least one surgical procedure in their life time. Surgical outcomes in these patients from developing countries are poorly characterized and surgeons are often concerned about poor surgical outcomes, especially when their CD4 cell counts are less than 200 cells/µl. This study evaluated the surgical outcomes of HIV-infected patients undergoing various surgical procedures over a six-year period in a large tertiary care hospital from South India. Two hundred and ninety-three patients underwent 374 surgical procedures during the study period. The median duration of HIV prior to surgery was 1.9 years (range 0–18.8 years). Two-thirds (58%) were on highly active antiretroviral therapy (HAART) at the time of surgery with the median duration of this treatment being 38 months (n = 194). About one-third (35%) of surgical procedures were performed as an emergency. Abdomino-pelvic surgeries were the most common (225, 60%). Adverse surgical outcome defined as death or post-operative infection was seen in 25 (6.6%). The post-operative infection rate was 5% (20/374). The most common of these was surgical site infection observed in nine (60%) followed by pneumonia in five patients (33%) and urinary tract infection in one patient. Day 30 mortality was 2% (n = 8) and a quarter of these were reported to be related to post-operative infectious complications. On multivariate analysis, only preoperative haemoglobin of less than 10 g/dl was significantly associated with a poor surgical outcome. HIV-related parameters such as CD4 cell counts, duration of HIV infection and HAART regimen did not seem to contribute towards an adverse surgical outcome. © The Author(s) 2018.
Keywords: Perioperative outcomes; post-operative infections; post-operative mortality; surgery in HIV

Intrabiliary Migrated Clips and Coils as a Nidus for Biliary Stone Formation: A Rare Complication following Laparoscopic Cholecystectomy - Schreuder, A.M.; Van Gulik, T.M.; Rauws, E.A.J. (Case Reports in Gastroenterology, 2018)
Clips inserted during laparoscopic cholecystectomy (LC) may migrate into the biliary system and function as a nidus for the formation of gallstones. Here, we present a series of 4 patients who presented with this rare complication 5-17 years after LC. All 4 patients presented with symptomatic choledocholithiasis with biochemical and radiological signs of biliary obstruction. Three patients also had fever and infectious parameters, compatible with concurrent cholangitis. All patients successfully underwent endoscopic retrograde cholangiopancreatography (ERCP) with papillotomy and stone extraction. Patients with cholangitis also had antibiotic treatment. In 3 patients, obstruction of the common bile duct was caused by a single, relatively large stone that had formed around a clip (supposedly the cystic duct clip). In 1 patient, multiple stones had formed around an intrabiliary migrated cluster of coils that had been used for arterial embolization of a pseudo-aneurysm of the right hepatic artery. In conclusion, surgical clips and coils can migrate into the biliary tract and serve as a nidus for the formation of bile duct stones. Although rare, this complication should caution surgeons not to place clips "at random" during cholecystectomy. Patients with this rare complication are best managed by ERCP in combination with sphincterotomy and stone extraction. © 2018 The Author(s). Published by S. Karger AG, Basel.
Keywords: Bile duct injury; Cholecystectomy; Clip migration; Endoscopic retrograde cholangiopancreatography; Foreign body migration

Ocular complications from retained intraocular ointment discovered 33 months after cataract surgery - Sanders, R.N.; Warner, D.B.; Adams, L.R.; Sallam, A.A.; Uwaydat, S.H. (Case Reports in Ophthalmology, 2018)
Topical antibiotic and steroid ointments are sometimes used topically at the conclusion of intraocular surgery, and inadvertent entry into the eye has been reported. Dispersed ointment droplets or consolidated globules in the anterior chamber (AC) can sometimes be visualized on exam. Occasionally, intraocular ointment is found incidentally without apparent toxic effect, but retained ointment usually presents with early or delayed intraocular inflammation, pressure rise, macular edema, or corneal edema. The usual treatment for toxicity from retained ointment is removal of the ointment. While the complication of ointment-induced cystoid macular edema has been reported, there is paucity of literature on the anatomical response and eventual visual outcome of patients who have been treated for long-standing edema from retained ointment. We present a case of a patient who presented with history of poor vision since the time of cataract surgery 33 months prior, who had cystoid macular edema, reduced endothelial cell count, and apparent Maxitrol ointment (neomycin, polymyxin B sulfate, and dexamethasone in paraffin vehicle; Novartis Pharmaceuticals UK) floating in the AC. The patient was treated with AC washout and sub-Tenon injection of triamcinolone. His vision, retinal architecture by optical coherence tomography, endothelial cell count, and pachymetry has been followed for 9 months following this treatment. © 2018 The Author(s). Published by S. Karger AG, Basel.
Keywords: Cystoid macular edema; Endothelial cell loss; Intraocular ointment; Optical coherence tomography; Specular microscopy

Small-Bowel Obstruction Secondary to Ileal Trichobezoar in a Patient with Rapunzel Syndrome - García-Ramírez, B.E.; Nuno-Guzman, C.M.; Zaragoza-Carrillo, R.E.; Salado-Rentería, H.; Gómez-Abarca, A.; Corona, J.L. (Case Reports in Gastroenterology, 2018)
Bezoars are conglomerations of undigested foreign material retained in the gastrointestinal tract. Trichobezoar is a compact conglomeration of swallowed hair and constitutes less than 6% of all bezoars. Their most frequent location is in the stomach but they may extend through the pylorus into the small bowel. This condition is known as Rapunzel syndrome. Many patients may remain asymptomatic or present a mild form of the disease characterized by abdominal pain, early satiety, nausea, and vomiting. Complications may manifest as gastric outlet obstruction or bleeding, and intestinal obstruction. A 15-year-old female patient presented with clinical findings of intestinal obstruction. The patient suffered from depressive and anxiety disorders and trichotillomania, although trichophagy could not be assured. Alopecia circumscripta and irregular hair length on the scalp were identified. A computed tomography (CT) scan showed two images highly suggestive of trichobezoars, one in the stomach and the second one causing obstruction at the ileocecal valve. At laparotomy, both a mobile gastric trichobezoar with a tail extending to the duodenum and a trichobezoar causing obstruction at the ileocecal valve were removed. The postoperative course was uneventful. The passage of a detached trichobezoar fragment in a patient with Rapunzel syndrome may cause intestinal obstruction. CT is the preferred image modality for the evaluation of suspected trichobezoars in order to characterize their size and locations, the presence and level of obstruction, and complications such as ischemia or perforation. A case of small-bowel obstruction secondary to ileal trichobezoar in a patient with Rapunzel syndrome is herein reported. © 2018 The Author(s). Published by S. Karger AG, Basel.
Keywords: Case report; Gastric trichobezoar; Intestinal obstruction; Rapunzel syndrome; Small-bowel trichobezoar; Trichobezoar

Infections After Cranial Neurosurgery: Prospective Cohort of 103 Episodes Treated According to a Standardized Algorithm - Renz, N.; Özdirik, B.; Finger, T.; Vajkoczy, P.; Trampuz, A. (World Neurosurgery, 2018)
Objective: The optimal surgical and antimicrobial treatment for intracranial infections after neurosurgery is unknown. We investigated the clinical, laboratory, and microbiological characteristics of intracranial infections after neurosurgery. In addition, treatment outcome in patients treated according to a standardized algorithm was evaluated. Methods: Consecutive patients with extradural, intradural, and device-related infections after cranial neurosurgery were included prospectively. A standardized antimicrobial and surgical treatment regimen was applied. The probability of infection-free survival was estimated by using the Kaplan–Meier survival method. Survival curves between groups were compared by using log-rank Mantel–Cox test. Results: Of 103 infections, 58 (56%) were extradural, 33 (32%) intradural, and 12 (12%) device-associated. Foreign material was involved in 98 infections (95%), including 78 bone flaps or fixation devices, 41 duraplasties, 17 external drains, and 15 functional devices. The median duration from primary surgery until infection diagnosis was 33 days (range, 6–1132 days). In total, 69 infections (67%) were monomicrobial, 26 (25%) polymicrobial, and 8 (8%) culture-negative. Ninety of 103 patients (90%) underwent surgical intervention, of whom foreign material was retained in 24 (23%). The probability of infection-free survival was 87% after 12 months (95% confidence interval 77%–93%). Nonadequate antimicrobial therapy was associated with treatment failure (5% vs. 70%, P < 0.001), which remained significant in the multiple logistic regression model (P = 0.01). Conclusions: Most (95%) intracranial infections were associated with foreign material and required surgical intervention and biofilm-active treatment. Via a standardized treatment approach, the infection-free survival after 12 months was good (87%), independent of the infection site or type of micro-organism. © 2018 Elsevier Inc.
Keywords: Craniotomy; Neurosurgery; Outcome; Surgical-site infection; Treatment

Deciding to remove or leave a peritoneal loose body: A case report and review of literature - Obaid, M.; Gehani, S. (American Journal of Case Reports, 2018)
Objective: Unusual clinical course Background: Peritoneal loose bodies, also known as peritoneal mice, are rare findings and they present either with nonspe-cific symptoms or are found incidentally during exploration and autopsy. Usually, they have no clinical significance and require no specific treatment. We report a case of a giant peritoneal loose body found incidentally in the abdominal cavity of a patient who presented with abdominal pain and hematuria. Case Report: Our patient was a 58-year-old man who presented with abdominal pain and hematuria. Abdominal non-con-trast computed tomography (CT) and subsequent CT abdomen and pelvis with intravenous and oral rectal contrast were performed preoperatively, showing a well-circumscribed and calcified lesion of undetermined etiology in the abdominal cavity. The lesion was removed laparoscopically with no complications. Histopathologically, the lesion was reported as calcified tissue with fat necrosis, most likely an infarcted appendix epiploicae. Conclusions: Loose peritoneal bodies can present a challenging diagnostic problem to the surgeon, with confusing findings that can point towards malignancy. It often requires a number of investigations; however even with these investigations, operative exploration, either open or laparoscopic, can be the ultimate diagnostic and therapeutic modality, and the mobility of these calcified lesions may give a preoperative clue to the etiology. It is important to distinguish peritoneal loose bodies from neoplastic or metastatic lesions and to consider it in the differential diagnosis of a calcified mobile pelvic mass. Laparoscopic surgery is safe and effective in the retrieval of symptomatic peritoneal loose bodies. © Am J Case Rep, 2018.
Keywords: Appendices epiploicae; Boiled egg; Hematuria; Laparoscopic surgery; Peritoneal loose body

Cranially migrated ventriculoperitoneal shunt in patient with bilateral subdural empyema - Rafiq, M.F.A. (Journal of the College of Physicians and Surgeons Pakistan, 2018)
A right-sided ventriculoperitoneal (VP) shunt was placed in patient with congenital hydrocephalous in the first month of life. Three-month review visit showed no improvement and after evaluation and computerised tomogram (CT) scan brain, another VP shunt was placed on the left side without handling the previous right sided VP shunt. Patient did not improve and again presented with fever and fits. CT scan brain with and without contrast was repeated, which showed bilateral subdural empyema and right-sided cranially migrated VP shunt. Cerebrospinal fluid (CSF) analysis demonstrated infection. Bilateral burr hole drainage of subdural empyema with subsequent removal of right-sided migrated VP shunt was done. Cranial end of left-sided VP shunt was converted into external ventricular drain (EVD) and its abdominal end removed. Patient was placed on intravenous as well as intraventricular antibiotics through the EVD. Later, right-sided VP shunt was placed after clearance of infection. Regular follow-up showed that the patient is doing well. © 2015 College of Physicians & Surgeons Pakistan.
Keywords: Congenital hydrocephalus; Infection; Subdural empyema; Ventriculoperitoneal shunt migration

Orbital Inflammatory Syndrome Secondary to Flea Bite - Prospero Ponce, C.M.; Malik, A.I.; Vickers, A.; Chevez-Barrios, P.; Lee, A.G. (Ophthalmic Plastic and Reconstructive Surgery, 2018)
A 34-year-old previously healthy Hispanic male presented to the emergency room complaining of progressive left upper eyelid swelling and pain for more than 2 weeks. He was previously diagnosed and treated for a "pink eye" but failed to improve. He reported a previous "bug bite" around the left lateral canthus a few weeks prior to admission. Computer tomography orbit with contrast showed left exophthalmos, an enhancing left lacrimal gland and orbital inflammatory signs suggestive of possible intraorbital abscess. Intravenous antibiotics did not improve his symptoms. Surgical debridement showed no abscess but inflamed soft tissues and lacrimal gland. Intravenous steroids failed to improve his symptoms. On postoperative day 3, the patient reported that an insect had "jumped" out from his left orbit. Identification of the specimen proved to be a mature flea. Biopsy of the lacrimal gland showed degranulation of eosinophils and foreign body material consistent with probable insect leg parts. Copyright © 2018 The American Society of Ophthalmic Plastic and Reconstructive Surgery, Inc.

Retained surgical sponges: A descriptive study of 319 occurrences and contributing factors from 2012 to 2017 - Steelman, V.M.; Shaw, C.; Shine, L.; Hardy-Fairbanks, A.J. (Patient Safety in Surgery, 2018)
Background: Unintended retention of foreign bodies remain the most frequently reported sentinel events. Surgical sponges account for the majority of these retained items. The purpose of this study was to describe reports of unintentionally retained surgical sponges (RSS): the types of sponges, anatomic locations, accuracy of sponge counts, contributing factors, and harm, in order to make recommendations to improve perioperative safety. Methods: A retrospective review was undertaken of unintentionally RSS voluntarily reported to The Joint Commission Sentinel Event Database by healthcare facilities over a 5-year period (October 1, 2012- September 30, 2017). Event reports involving surgical sponges were reviewed for patients undergoing surgery, invasive procedures, or child birth. Results: A total of 319 events involving RSS were reported. Sponges were most frequently retained in the abdomen or pelvis (50.2%) and the vagina (23.9%). Events occurred in the Operating Room (64.1%), Labor and Delivery (32.7%) and other procedural areas (3.3%). Of the events reported, 318 involved 1 to 12 contributing factors totaling 1430 in 13 different categories, most frequently in human factors and leadership. In 69.6% of reports, the harm was an unexpected additional care or extended stay. Severe temporary harm was associated with 14.7% of the events. One patient died as a result of the retained sponge. Conclusions: Because of the complexity of perioperative patient care, the multitude of contributing factors that are difficult to control, and the potential benefit of radiofrequency sponge detection, we recommend that this technology be considered in areas where surgery is performed and in Labor and Delivery. © 2018 The Author(s).
Keywords: Adverse event; Gossypiboma; Labor and delivery; Obstetrics; Patient safety; Sponges; Surgery

Postoperative kinetics of common inflammatory biomarkers after congenital heart defect procedures with extracorporeal circulation in children - Haponiuk, I.; Jaworski, R.; Paczkowski, K.; Chojnicki, M.; Steffens, M.; Szofer-Sendrowska, A.; Gierat-Haponiuk, K.; Kwaśniak, E.; Paśko-Majewska, M.; Leszczyñska, K.; Zieliñski, J.; Szymanowicz, W. (Kardiologia Polska, 2018)
Background: Extracorporeal circulation is associated with systemic inflammatory response syndrome. Therefore, the diagnosis of infection should be differentiated from a typical postoperative course. Aim: The aim of the study was to evaluate the kinetics of inflammatory biomarkers in children in the first days after cardiac surgery with extracorporeal circulation. Methods: Prospective data were collected from 51 consecutive children referred for surgical treatment in Department of Paediatric Cardiac Surgery, St. Adalbertus Hospital in Gdañsk, between February and August 2015. Blood samples were collected on the first, second, and third postoperative days and sent to the institutional laboratory for routine investigations: White blood cell count, serum C-reactive protein (CRP) and procalcitonin concentrations. Results: The highest levels of procalcitonin were on the first postoperative day (median 3.53 ng/mL), although the peak values of CRP concentration and white blood cell count were on the second postoperative day (96 mg/L and 17.3 G/L). In the group of patients with foreign material implantation (Contegra(r) or Gore-Tex(r)), the higher values of procalcitonin concentration and white blood cell count were measured in the subsequent postoperative days. Conclusions: The kinetics of analysed inflammatory biomarkers on the first days after cardiac surgery for congenital heart disease in children have different characteristics. The knowledge about the kinetics of inflammatory biomarkers could be useful in determining the possibility of evolving infections in the early postoperative period. © Polish Cardiac Society 2018.
Keywords: Congenital heart defects; Diagnostics; Infections; Paediatric cardiac surgery; Postoperative care; Procalcitonin

Retained foreign body in the nasal cavity after oral maxillofacial surgery - Tsukamoto, M.; Hirokawa, J.; Yokoyama, T. (Anesthesia Progress, 2018)
Retained foreign bodies sometimes occur in various surgical procedures and can lead to severe complications. Foreign bodies in the oral and maxillofacial region are not rare because of the use of many small items and the natural communication with the outside environment in some areas. We experienced a case of foreign body in the nasal cavity, which was discovered 1 year later at a second operation for hardware removal after maxillofacial surgery. A small, soft material is usually placed between the nasal endotracheal tube and nostril to avoid nasal pressure ulcer at the ala of nose after prolonged anesthesia after our group’s experiencing some cases of this complication. The foreign body was found in the pharynx during induction of a second anesthesia. Attention should be directed to not leaving any materials in the patient after surgery. In addition to the normal counts of sponges, needles, etc, other small nonsurgical materials used should be recorded by medical staff to help ensure nothing is retained in the patient. © 2018 by the American Dental Society of Anesthesiology.
Keywords: Foreign body; General anesthesia; Nose; Oral surgery

Button battery lodged in Meckel's diverticulum - Farber, B.A.; Shaul, E.; LaQuaglia, M.J.; Janofsky, E.; Statter, M.B.; Jan, D.M.; Borenstein, S.H.; Rudolph, B. (Journal of Pediatric Surgery Case Reports, 2018)
Meckel's diverticulum is the most common congenital anomaly of the gastrointestinal tract. It is relatively uncommon, however, for patients to become symptomatic and rarer still for foreign bodies to become lodged within a Meckel's diverticulum. Here we present one such case in which a button battery was lodged in a Meckel's diverticulum, along with the patient's subsequent interdisciplinary management and review of the relevant literature. © 2018
Keywords: Button battery; Foreign body ingestion; Meckel's diverticulum

Developing Process Maps as a Tool for a Surgical Infection Prevention Quality Improvement Initiative in Resource-Constrained Settings - Forrester, J.A.; Koritsanszky, L.A.; Amenu, D.; Haynes, A.B.; Berry, W.R.; Alemu, S.; Jiru, F.; Weiser, T.G. (Journal of the American College of Surgeons, 2018)
Background: Surgical infections cause substantial morbidity and mortality in low-and middle-income countries (LMICs). To improve adherence to critical perioperative infection prevention standards, we developed Clean Cut, a checklist-based quality improvement program to improve compliance with best practices. We hypothesized that process mapping infection prevention activities can help clinicians identify strategies for improving surgical safety. Study design: We introduced Clean Cut at a tertiary hospital in Ethiopia. Infection prevention standards included skin antisepsis, ensuring a sterile field, instrument decontamination/sterilization, prophylactic antibiotic administration, routine swab/gauze counting, and use of a surgical safety checklist. Processes were mapped by a visiting surgical fellow and local operating theater staff to facilitate the development of contextually relevant solutions; processes were reassessed for improvements. Results: Process mapping helped identify barriers to using alcohol-based hand solution due to skin irritation, inconsistent administration of prophylactic antibiotics due to variable delivery outside of the operating theater, inefficiencies in assuring sterility of surgical instruments through lack of confirmatory measures, and occurrences of retained surgical items through inappropriate guidelines, staffing, and training in proper routine gauze counting. Compliance with most processes improved significantly following organizational changes to align tasks with specific process goals. Conclusions: Enumerating the steps involved in surgical infection prevention using a process mapping technique helped identify opportunities for improving adherence and plotting contextually relevant solutions, resulting in superior compliance with antiseptic standards. Simplifying these process maps into an adaptable tool could be a powerful strategy for improving safe surgery delivery in LMICs. © 2018 American College of Surgeons

1,300 Days and Counting: A Risk Model Approach to Preventing Retained Foreign Objects (RFOs) - Duggan, E.G.; Fernandez, J.; Saulan, M.M.; Mayers, D.L.; Nikolaj, M.; Strah, T.M.; Swift, L.M.; Temple, L. (Joint Commission Journal on Quality and Patient Safety, 2018)
Background: A retained foreign object (RFO) is a devastating surgical complication that typically results in additional surgeries, increased length of stay, and risk of infections and is potentially fatal. Memorial Sloan Kettering Cancer Center (MSKCC) convened a multidisciplinary task force to undertake an improvement initiative to reduce the frequency of RFO incidents. Methods: A needs assessment was undertaken using focus group interviews, review of past RFOs, and operating room (OR) observations, and a comprehensive intervention plan was initiated. Items at risk of retention were reclassified and new tracking sheets were developed. A probabilistic risk model was developed based on aviation industry methodology, an RFO risk projection, and the retention risk classification of surgical items. Training initiatives were launched to shift organizational culture and staff behaviors toward greater awareness of RFO risk and proactive prevention. Results: Since the implementation of our task force's recommendations on March 24, 2014, there have been no RFO incidents at our institution to this day. The last RFO occurred in August 2013—more than 1,300 days ago (as of March 28, 2017). The RFO incident frequency was reduced from 1.69 per year to a risk model estimate of 1 in 22 years. Ongoing training maintains the staff's behavioral changes as well as the improved OR and organizational culture. Conclusion: Implementation of a multidisciplinary approach to preventing RFOs was successful at MSKCC. The use of an RFO risk model enabled the creation of a robust system for RFO prevention. Support from leadership, participation by all stakeholders, education, training, and cooperation from frontline staff are all important contributors to RFO prevention success. © 2018 The Joint Commission

Evaluating complication rates and outcomes among infants less than 5 kg undergoing traditional percutaneous endoscopic gastrostomy insertion: A retrospective chart review - Fernandes, A.R.; Elliott, T.; McInnis, C.; Easterbrook, B.; Walton, J.M. (Journal of Pediatric Surgery, 2018)
Purpose: Percutaneous endoscopic gastrostomy (PEG) enables enteral nutrition for patients with inadequate oral intake. Laparoscopic guidance of PEG insertion is used for high-risk populations, including in infants less than 5 kg at insertion. This study aimed to assess complication rates with traditional PEG tube insertion in infants less than 5 kg at a single tertiary care center. Methods: A retrospective review of patients less than 5 kg who underwent PEG insertion was conducted. PEG insertion-related complications, up to four years following insertion, were collected. Outcomes were reported as counts and percentages, or median with minimum and maximum values. Results: 480 pediatric gastrostomy procedures between January 1, 2009 and February 1, 2017, were screened, with 129 included for analysis. Median weight at PEG insertion was 3800 g. Superficial surgical site infection (SSI) occurred in 6 (4.7%) patients, and 1 (0.8%) required readmission for intravenous antibiotics. One (0.8%) required endoscopic management for retained foreign body, 1 (0.8%) required operative management for gastrocolic fistula, and 1 (0.8%) for persistent gastrocutaneous fistula. No deep space SSI, procedure-related hemorrhage requiring readmission or transfusion, buried bumper syndrome, or procedure-related mortality occurred. Conclusion: Traditional PEG tube insertion in infants less than 5 kg results in complication rates comparable to pediatric literature standards. Level of Evidence: Level II, retrospective prognosis study. © 2018
Keywords: Complications; Infant; Laparoscopic; Neonate; Percutaneous endoscopic gastrostomy; Pull technique

Effect of red propolis on hamster cheek pouch angiogenesis in a new sponge implant model - Melo, N.O.R.; Juanes, C.C.; Alves, M.F.A.; Silva, E.T.M.; Jamacaru, F.V.F.; de Lemos, T.L.G.; Dornelas, C.A. (Acta Cirurgica Brasileira, 2018)
Purpose: To evaluate the effects of red propolis on cheek pouch angiogenesis in a hamster new model sponge implant. Methods: Forty eight animals divided into eight groups. (Groups I-IV), the animals were treated for 15 days before and 10 days after sponge implantation. (Groups V-VIII), the animals were treated for 10 days after sponge implantation (GI and GV: red propolis 100 mg/kg, GII and GVI: celecoxib 20 mg/kg, GIII and GVII: 1% gum arabic 5 mL/kg, GIV and GVIII: distilled water 5 mL/kg). On the 11th day of implantation, the animals were anesthetized for stereoscopic microscopic imaging and morphometric quantification of angiogenesis (SQAN), followed by histopathological evaluation (H&E). Results: In the SQAN analysis, no significant difference was found between the groups. However, on histology, propolis was found reduce the population of mastocytes in the qualitative analyses (p = 0,013) in the quantitative analyses to reduce the number of blood vessels (p = 0,007), and increase the macrophage count (p = 0,001). Conclusion: Red propolis inhibited inflammatory angiogenesis when administered before andcontinuously after sponge implant, and was shown to have immunomodulating effects on inflammatory cells (mastocytes and macrophages) in a new sponge implant hamster model. © 2018, Sociedade Brasileira para o Desenvolvimento de Pesquisa em Cirurgia. All rights reserved.
Keywords: Angiogenesis Inhibitors; Cricetinae; Inflammation; Mesocricetus; Propolis

A Bile Duct Stone Formation around a Fish Bone as a Nidus after Pancreatoduodenectomy - Sakakida, T.; Sato, H.; Doi, T.; Kawakami, T.; Nakatsugawa, Y.; Nishimura, K.; Yamada, S.; Fujii, H.; Tomatsuri, N.; Okuyama, Y.; Kimura, H.; Yoshida, N. (Case Reports in Gastroenterology, 2018)
We report a rare case of bile duct stone formation around an ingested fish bone as a nidus after pancreatoduodenectomy. A 78-year-old woman was admitted to our department for fever and epigastric pain. Abdominal computed tomography revealed an elongated bile duct stone containing a linearly shaped foreign body of bone density. Enteroscopic lithotomy was performed using single balloon enteroscopy to safely remove the stone and foreign body from the bile duct. The foreign body was determined to be a fish bone by pathological examination and component analysis. © 2018 The Author(s). Published by S. Karger AG, Basel.
Keywords: Bile duct stone; Fish bone; Foreign body; Pancreatoduodenectomy

Neutrophils at the Biological-Material Interface - Jhunjhunwala, S. (ACS Biomaterials Science and Engineering, 2018)
Integral to the development of new biomaterials is the characterization of immune responses to biomaterial implants, and formulating methods to overcome or utilize these actions for therapeutic benefit. Neutrophils are an essential component of the immune response against biomaterials, but studies on the neutrophil-biomaterial interaction have been largely limited to characterizing their role in establishing an inflammatory microenvironment and antimicrobial activity at implant surfaces. Recent advances in neutrophil biology, especially recognition of their cellular heterogeneity, ability to suppress immune responses, the identification of a new process of cell death, and crosstalk with other immune cell types, have brought about a fundamental change in our perception regarding the activities of neutrophils. Herein, in the context of the progress in our comprehension of neutrophil function, potential avenues for effectively employing neutrophil activity to develop the next generation of regenerative biomaterials are discussed. © 2017 American Chemical Society.
Keywords: fibrosis; foreign body response; polymorphonuclear cells; tissue engineering

The significance of routine computer tomography in evaluation of asymptomatic postoperative war trauma patients transferred from Syria for further treatment - Kakiashvili, E.; Mansour, M.; Weiss, M.; Barhoum, M.; Khatib, K.; Bickel, A. (Israel Medical Association Journal, 2018)
Keywords: Emergency surgery; Laparotomy; Retained foreign body; Syrian civil war; Wartime casualty

Photorefractive intrastromal corneal crosslinking for treatment of myopic refractive error: Findings from 12-month prospective study using an epithelium-off protocol - Elling, M.; Kersten-Gomez, I.; Dick, H.B. (Journal of Cataract and Refractive Surgery, 2018)
Purpose: To assess the long-term effectiveness and safety of photorefractive intrastromal corneal crosslinking (CXL) in patients with low myopia. Setting: Ruhr University Eye Hospital, Bochum, Germany. Design: Prospective case series. Methods: Healthy eyes with myopia were treated with photorefractive intrastromal CXL using the Mosaic System. Riboflavin 0.1% solution (VibeX Rapid) was topically administered, followed by 365 nm ultraviolet-A (30 mW/cm2) irradiance. Efficacy was assessed by the uncorrected distance visual acuity (UDVA), manifest refraction spherical equivalent (MRSE), and keratometry. Safety was assessed by corrected distance visual acuity (CDVA), slitlamp biomicroscopy, endothelial cell count, and adverse event rates. Results: Fourteen patients (24 eyes) with a mean age of 35.7 years were included. At all follow-ups, a statistically significant improvement in UDVA was observed (all P <.001). The CDVA progressively improved from 1 month postoperatively and a statistically significant improvement was achieved at 12 months (P <.001). The average reduction in manifest sphere was 0.90 diopter (D) ± 0.40 (SD) by 12 months. There were no significant differences in mean manifest sphere and MRSE at 3, 6, or 12 months. Compared with baseline, significant reductions in corneal curvature were also observed at all follow-ups (all P <.05). There were no significant changes in endothelial cell density (P = 1.00) or number of cells (P =.95) at 12 months postoperatively, and no adverse events were reported. Conclusion: Photorefractive intrastromal CXL was a safe and efficacious treatment of refractive error in patients with low myopia. © 2018 ASCRS and ESCRS

Retained surgical sponge: Medicolegal aspects - Gualniera, P.; Serena, S. (Legal Medicine, 2018)
Retained surgical sponge events continue to occur despite the implementation of preventive surgical count policies, procedures, and adjunct technologies to manual counting. Such intraoperative mistakes can cause chronic nonspecific symptoms during the early postoperative period. When discovered years after surgery, they raise thorny medicolegal questions. We describe two cases from our practice that illustrate the need to identify the responsibility of the surgical team, as delineated in ministerial directives and the current legal framework, as well as the difficulty in evaluating clinical actions taken at different times and in different settings, with regard to the permanent health damage incurred by sponge retention. Finally, we discuss prevention actions operating room staff should take to reduce the risk of retained surgical sponges. © 2018 Elsevier B.V.
Keywords: Clinical risk management; Damage; Prevention; Professional liability; Retained sponge; Surgery

Hidden Malefactor: Occult Foreign Body in Diabetic Foot - Schattner, A.; Dubin, I. (American Journal of Medicine, 2018)

Spontaneous rupture of lacrimal gland pleomorphic adenoma: Pivotal role in masquerading orbital cellulitis - Pakdel, F.; Pirmarzdashti, N.; Soltani, S.; Nozarian, Z.; Amoli, F.A.; Kassaee, A. (Ophthalmic Plastic and Reconstructive Surgery, 2018)
The authors aim to report a 68-year-old patient presenting with acute swelling and redness of orbital area diagnosed initially as orbital cellulitis. Surgical excision was decided based on clinical and imaging findings with the diagnosis of pleomorphic adenoma of the lacrimal gland. Lacrimal gland pleomorphic adenoma usually presents with painless gradual swelling of upper eyelid. In an exceptionally rare circumstance, this case showed acute orbital inflammation, and imaging findings of orbital inflammation mostly focused around the cystic space of the lacrimal gland tumor. Histologic evaluation confirmed a ruptured cystic space of pleomorphic adenoma with foreign body–type inflammatory reaction. The authors propose spontaneous rupture of cystic space in the lacrimal gland pleomorphic adenoma as underlying mechanism for acute presentation of this tumor. Imaging and clinical characteristics and also prognostic implication of this phenomenon are discussed. Copyright © 2017 The American Society of Ophthalmic Plastic and Reconstructive Surgery, Inc.

A Case of Child Physical Abuse with a Rolling Pin Insertion, Resulting in Bladder and Rectal Perforation - Kondolot, M.; Doganay, S.; Turan, C.; Asil, H.; Oztop, D.B.; Ozdemir, C. (Pediatric Emergency Care, 2018)
Visceral injuries are not uncommon in nonaccidental trauma and often require emergent operative intervention. However, sometimes it can be difficult to assess the extent of injury. In this report, we present a case of child physical abuse resulting in bladder and rectal perforations, which was initially referred to our hospital as acute abdomen with intraperitoneal free fluid on ultrasonography. An exploratory laparotomy revealed the perforations and surgical repair was performed. The patient was evaluated by the Hospital Child Protective team and it was revealed that bladder and rectum perforations were due to insertion of rolling pin into the rectum by the stepmother. The child was discharged home uneventfully with a temporary colostomy. We believe that this is the first reported case in the English literature of inflicted perforation of the rectum and bladder through insertion of a rolling pin. © 2018 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: acute abdomen; bladder perforation; child abuse; rectal injury; rolling pin

Trans-nasal flexible bronchoscopy in wheezing children: Diagnostic yield, impact on therapy, and prevalence of laryngeal cleft - Boesch, R.P.; Baughn, J.M.; Cofer, S.A.; Balakrishnan, K. (Pediatric Pulmonology, 2018)
Aim: Persistent or recurrent wheezing is a common indication for flexible bronchoscopy, as anatomic and infectious or inflammatory changes are highly prevalent. We sought to evaluate the prevalence of anatomic, infectious, and inflammatory disease in a cohort of children undergoing flexible bronchoscopy for wheezing or poorly controlled asthma. Methods: We retrospectively reviewed all children <18 years old who underwent flexible bronchoscopy at our center from October 29, 2012-December 31, 2016 for the primary or secondary indication of wheezing (persistent, frequently recurring, or atypical) or poorly controlled asthma. Results: A total of 101 procedures were identified in 94 patients, aged 3 months to 18 years. Potential anatomic causes for wheezing identified in 45.7% of patients and inflammatory changes in 49.5% of procedures. This included the identification of a laryngeal cleft in 17% for which half required medical or surgical management. Tracheobronchomalacia was the most commonly identified anatomic lesion. Thirty children from this cohort had poorly controlled asthma. Among this subgroup, 54% had increased neutrophils on BAL and 30% had an anatomic contributor to wheezing, including one with a laryngeal cleft. Based on findings from flexible bronchoscopy, management changes made in 63.8% of patients. This included medication changes in 54 and surgical intervention in 9. Discussion: We conclude that transnasal flexible bronchoscopy has high yield in children with recurrent, persistent, or atypical wheezing and those with poorly controlled asthma. Laryngeal cleft has a reasonably high prevalence that warrants specific evaluation in this population. © 2017 Wiley Periodicals, Inc.
Keywords: asthma; flexible bronchoscopy; laryngeal cleft; wheezing; yield

Late Presentation of Infected Silicone Granulomas in the Lower Limb - Jessop, Z.M.; Welck, M.; Zinser, E.; Garlick, N.; Hopkins, S. (Clinical Medicine Insights: Arthritis and Musculoskeletal Disorders, 2018)
Introduction: Dermal fillers are used for multiple cosmetic indications including gluteal and thigh augmentation. Complications, although infrequent, are increasing due to the dramatic growth of dermal filler use. Our aim was to describe how the complication of infected silicone granulomas can present following lower limb augmentation. Methods: Two cases presented with pain, oedema, and erythema at the site of previous silicone filler injection, following a considerable delay after the last injection (range 4-7 years). We collected data on their biochemistry, haematology, histology, microbiology, and imaging at the time of presentation. Results: Complications included prolonged cellulitis with recurrent abscesses at sites of previous silicone dermal filler injection. Histology revealed infiltration of chronic inflammatory cells suggestive of silicone granuloma in both cases. Patients were reluctant to divulge use of cosmetic fillers or failed to recognise their significance given the time delay making diagnosis difficult. Delayed or recurring infections can suggest the presence of atypical organisms and we present the first reported case of silicone granuloma infection with Propionibacterium acnes. Conclusions: Microorganisms can induce immune-mediated hypersensitivity and are believed to be the trigger for delayed activation of a quiescent foreign body to a granulomatous reaction. The substantial time delay between injection and reaction must be recognised and may be attributable to atypical microorganisms or biofilm formation. Previous antibiotic use can affect expedient microbiological diagnosis and treatment requires close collaboration with microbiologists. It is important that clinicians are aware of these important complications which are becoming more common with increased use of filler augmentation. © The Author(s) 2018.
Keywords: dermal filler; lower limb augmentation; Silicone granuloma

Ureterovaginal fistula: A complication of a vaginal foreign body - Lo, T.-S.; Jaili, S.B.; Ibrahim, R.; Kao, C.C.; Uy-Patrimonio, M.C. (Taiwanese Journal of Obstetrics and Gynecology, 2018)
Objective: To know the diagnostic tools and proper management of ureterovaginal fistula following neglected vaginal foreign body in order to achieve optimal outcome. Case report: A case of ureterovaginal fistula associated with a neglected vaginal foreign body. The patient was complaining of a foul-smelling vaginal discharge and lower abdominal pain. On vaginal examination, a hard and large foreign body was found. Examination under anesthesia was performed, and an aerosol cap was removed from her vagina. The patient developed urinary incontinence after removal of the foreign body. Subsequent work-up demonstrated the presence of a right ureterovaginal fistula. The patient underwent an abdominal ureteroneocystostomy. At one year follow up, the patient had fully recovered. Conclusion: Ureterovaginal fistula following neglected vaginal foreign body is a serious condition. Early diagnosis, treatment of infection and proper surgical management can improve the outcome and decrease complications. © 2018
Keywords: Ureteroneocystostomy; Ureterovaginal fistula; Vagina foreign body

Concurrent partial small bowel obstruction and acute appendicitis secondary to play-dough ingestion - Zubair, O.N.; Carroll, D.; Goodall, K. (Journal of Pediatric Surgery Case Reports, 2018)
Keywords: Appendicitis; Partial small bowel obstruction; Play-dough

Gossypiboma: A ghastly find - De Gea Rico, A.; Krishna, P.; Devlin, H.L.; Rohatgi, A. (BMJ Case Reports, 2018)
A gossypiboma is a mass within a patient's body comprising a cotton matrix surrounded by a foreign body granuloma. We describe an unusual presentation of a gossypiboma presenting in a 32-year-old man with acute epigastric pain and haematemesis. His surgical history revealed an emergency laparotomy following a road traffic accident 16 years ago. Initial gastroscopy showed extrinsic stomach compression. An abdominal ultrasound scan followed by a CT scan evidenced a large, well-defined, predominantly cystic mass with some solid areas occupying the left hypochondrium. Conservative management with insertion of a percutaneous drain proved to be inefficient. A laparotomy was performed; intraoperatively, the cyst was found to be ruptured and within it, a large surgical gauze was found. This was removed but required a distal pancreatectomy and gastrectomy for complete excision. He was discharged on day 74 of admission with outpatient follow-up. © BMJ Publishing Group Limited 2018.
Keywords: Gastrointestinal surgery; Surgery

Intrapericardial gossypiboma: Rare cause of intrathoracic mass - Kumar, A.; Paswan, S.S.; Prashad, R.; Kumari, R.; Kumar, B. (International Journal of Surgery Case Reports, 2018)
Introduction: Gossypiboma is a retained surgical sponge inside our body after surgical intervention. It is most commonly found in abdominal cavity. Its occurrence in thoracic cavity as intrapericardial gossypiboma is extremely rare. Presentation of case: We present a 25 year old male with complaint of chest pain for 1 year. He had a history of total correction of Tetralogy of fallot 14 years back, at another hospital. On clinical examination and investigations including contrast enhanced computed tomography (CECT) of thorax; diagnosis of right anterior mediastinal mass of germ cell tumor was made and planned for thoracotomy. On exploration, the gauze piece of 31 cm was removed from the pericardial mass and a final diagnosis of gossypiboma was made. Discussion: Although gossypibomas are commonly reported in abdominal and pelvic surgery but a prolonged operative time, untrained staff, poor communication in sponge count may favour the occurrence in thoracic cavity. A patient with intrathoracic gossypiboma usually presents with chest pain, dyspnoea, thoracic mass or fever. CECT and Magnetic resonance Imaging (MRI) are useful imaging modality in such cases. Surgical exploration with histopathological examination confirms the diagnosis of gossypiboma. Conclusion: In a postoperative patient who presents with chest pain and intrathoracic mass, gossypiboma should be a differential diagnosis even it is rare to occur in thorax. © 2018 The Authors
Keywords: Gauze piece; Gossypiboma; Intrapericardial; Intrathoracic; TOF

Evaluation of radiofrequency electronic system in intraoperative monitoring of surgical textiles - Antonio, A.M.; Vieira, C.A.P. (Einstein (Sao Paulo, Brazil), 2018)
Objective To test performance of SurgiSafe®, a radiofrequency electronic device to detect surgical textiles during operations as compared to manual counting. Methods Surgical sponges with radiofrequency TAGs were placed in the abdominal cavity of a pig submitted to laparotomy, in randomly distributed sites. The TAGs were counted manually and also using SurgiSafe®. Positive and negative predictive values, sensitivity, specificity and time required for counting were analyzed for both methods. Results Through the analysis of 35 surgical cycles, SurgiSafe® immediately identified all sponges, with specificity, sensitivity, positive and negative predictive values of 100%. Although not statistically significant, the manual count had sensitivity of 99.72% and specificity of 99.90%. Conclusion SurgiSafe® proved to be an effective device to identify surgical sponges in vivo, in real time; and its use as an adjuvant to manual counting is very helpful to increase patient's safety.

Material-associated bone resorption - Bonartsev, A.P.; Muraev, A.A.; Deyev, R.V.; Volkov, A.V. (Sovremennye Tehnologii v Medicine, 2018)
A number of similar macrophage responses to the implantation of various osteoplastic materials into bone defects in humans and laboratory animals have been demonstrated in the present article based on the retrospective analysis of the archival histological material (2008–2016). The presence of osteoplastic materials in a bone regenerate has led to the emergence of giant cells of foreign bodies and osteoclastogenic cells both on the surface of the material and neoformed bone with its subsequent resorption. It was suggested to name this phenomenon “material-associated bone resorption”. © 2019, Privolzhsky Research Medical University. All rights reserved.
Keywords: Bone resorption; Bone tissue; Giant cells of foreign bodies; Osteoclasts; Osteoplastic materials; Regenerative medicine; Tissue engineering

Pyogenic liver abscess secondary to foreign body (Fish bone) treated by laparoscopy: A case report - Bandeira-De-Mello, R.G.; Bondar, G.; Schneider, E.; Wiener-Stensmann, I.C.; Gressler, J.B.; Kruel, C.R.P. (Annals of Hepatology, 2018)
Liver abscess due to perforation of the gastrointestinal tract by a foreign body is a rare and possibly fatal event. Diagnosing this pathology is complicated by the lack of specific symptoms and unfamiliarity of ingestion by the patient and low clinical suspicion of this disease. In the case of liver abscess unresponsive to aspiration and administration of antibiotics, this hypothesis must be made, despite its low incidence. This case report describes and illustrates a case of liver abscess secondary to fish bone ingestion with consequent piercing of the lesser gastric curvature, diagnosed by computed tomography and specific anamnesis. Laparoscopy was performed to extract the foreign body, without complications; the patient is currently asymptomatic and does not present any abnormal physical examination findings. We believe this represents the first case report of a successful laparoscopic treatment in South America for the removal of an ingested foreign body associated with pyogenic liver abscess. © 2018, Fundacion Clinica Medica Sur. All rights reserved.
Keywords: CT; Foreign body penetration; Hepatic abscess; Perforation; Videolaparoscopy

Current perspectives on diagnosis and management of sternal wound infections - Yusuf, E.; Chan, M.; Renz, N.; Trampuz, A. (Infection and Drug Resistance, 2018)
Deep sternal wound infection (DSWI), also known as mediastinitis, is a serious and potentially fatal condition. The diagnosis and treatment of DSWI are challenging. In this current narrative review, the epidemiology, risk factors, diagnosis, and surgical and antimicrobial management of DSWI are discussed. Ideally, the management of DSWI requires early and sufficient surgical debridement and appropriate antibiotic therapy. When foreign material is present, biofilm-active antibiotic therapy is also needed. Because DSWI is often complex, the management requires the involvement of a multidisciplinary team consisting of cardiothoracic surgeons, plastic surgeons, intensivists, infectious disease specialists, and clinical microbiologists. © 2018 Yusuf et al.
Keywords: Antibiotic; Deep sternal wound infection; Diagnosis; Surgical treatment

Angry bird's revenge: Hepatic abscesses secondary to colonic perforation - Sivandzadeh, G.; Banazadeh, A.; Anushiravani, A. (Acta Medica Iranica, 2018)
Foreign bodies are commonly ingested and usually pass through the gastrointestinal tract, but in less than 1% complications can be seen. We aimed to report a very rare case of multiple hepatic abscesses caused by perforation of the sigmoid colon due to a chicken bone. An 82-year-old man presented with a 5-day history of abdominal pain, fever, and coffee ground vomiting. He was febrile and tachycardic and had a mild localized abdominal tenderness in the left lower quadrant. Laboratory findings revealed a lymphocyte dominant leukocytosis with an elevated erythrocyte sedimentation rate. Multiple abscesses were shown in the right lobe of the liver in abdominal computed tomography. Colonoscopy showed a chicken bone perforating both walls of the sigmoid colon. He received broad-spectrum antibiotics and underwent surgery for a complete recovery. Chronic lymphocytic leukemia was diagnosed by flow cytometry phenotyping. Mortality and morbidity of hepatic sepsis caused by foreign body-induced colon perforation depend on a rapid diagnosis. We presented a very rare condition that should always be kept in mind when dealing with a case of liver abscess and even while confronting septic shock with an unknown origin. © 2018 Tehran University of Medical Sciences. All rights reserved.
Keywords: Chicken bone; Liver abscess; Perforation

Dislodged bonded molar tube into wound during orthognathic surgery - Shaeran, T.A.Te.; Samsudin, A.R. (Case Reports in Dentistry, 2018)
Introduction. Dislodgement of orthodontic appliance into operation wounds may occur while performing orthognathic surgery. Its occurrence is commonly associated with bonded upper molar tube. Case Report. A 25-year-old gentleman presented with recurrent upper right vestibular abscess three months following a bimaxillary orthognathic surgery. A bonded molar orthodontic tube had dislodged into the wound during the operation. The clinical presentation initially mimics an odontogenic infection until our investigations revealed that it originated from the dislodged appliance. The abscess was drained, the wound site was explored, and the molar tube and neighbouring rigid fixation plates and screws were removed. The patient recovered well following the procedure. Conclusion. Dislodged metal orthodontic appliance in oral wound acts as a foreign body that may exert allergic reactions, infection, or inflammation. Pre- and postoperative intraoral examination of fixed orthodontic appliances including its count should be recorded in orthognathic surgery protocol. Copyright 2018 Tengku Aszraf Tengku Shaeran and A. R. Samsudin.

A rare complication in a liver transplant patient: Meckel diverticulum perforation due to biliary stent - Topal, U.; Ülkü, A.; Sarıtaş, A.G.; Akçam, A.T. (International Journal of Surgery Case Reports, 2018)
Introduction: Meckel's diverticulum is the most common congenital lesion of the small intestine. The incidence varies between 0.5% and 2% Biliary stents can be used for the treatment of patients with bile duct complications. Intestinal perforation due migrated stents is a very rare and life threatening complication. “Perforation of the Meckel diverticulum due to stent” and no case was found in the literature. For this reason, our case has been identified as the first case seen in the literature. Case presentation: A 20 year old male patient liver transplantation was performed from a live donor. 3 years ago The patient presented at our clinic with abdominal pain, nausea and vomiting that has been present for 2 days. Abdominal computed tomography showed a foreign body in the small intestines Patient was operated in emergency conditions. Meckel Diverticulum 40 cm proximal to the ileocecal valve and a biliary drainage catheter perforating the diverticule was seen Meckel's diverticulum was excised, primary repair was performed, Postoperative recovery was uneventful. Discussion: Complication rates due to a biliary stent range between 8–10% with a mortality below 1% (Konstantinidis et al. [1]). The most feared complication due to a biliary stent is stent migration. The perforation rate due to stent migration is below 1%. It most commonly occurs in the duodenum. Patients with stent related perforations are surgically managed as other GIS perforations. Conclusions: Perforation due to stent migration should also be considered in differential diagnosis in patients with a biliary stent and Acute Abdomen. © 2018
Keywords: Biliary stent migration; Liver transplantation; Meckel diverticule

Peritonitis with small intestinal perforation caused by a plastic bread bag clip: A case report - Mitsui, E.; Inaba, M.; Mimura, T. (International Journal of Surgery Case Reports, 2018)
Introduction: Cases of a foreign body ingestion often require surgical treatment due to perforation or penetration. There is a possibility that plastic bread bag clips also cause serious adverse events when they are ingested. Presentation of a case: We report a rare case of peritonitis with small intestinal perforation caused by a plastic bread bag clip that needed surgical treatment. A 47-year-old man was taken to our hospital because of abdominal distension and vomiting. A computed tomography test demonstrated findings of small intestinal perforation, and a high-density object was seen in the jejunum. During emergency surgery, it was discovered that a plastic bread bag clip had caused the perforation. Discussion: Some cases of gastrointestinal tract perforation or bleeding due to the ingestion of bread bag clips have been reported overseas. Because bread bag clips are normally radiolucent, they are impossible to discover when accidentally ingested, so diagnosis is difficult unless the patient remembers the incident. The shape of plastic bread bag clips is unique and can result in a trap-like effect, which prevents easy removal once ingested. Conclusion: Bread bag clips need caution in handling, and in cases of accidental ingestion, careful observations should be made to allow for removal within reach of upper GI endoscopy. The following case report has been reported in line with the SCARE criteria [1]. © 2018 The Authors
Keywords: Bread bag clip; Foreign body; Small intestinal perforation

Polymicrobial bacterial pericarditis and cardiac tamponade caused by pericardial penetration of an adjustable gastric band - De Jong, Y.; Van Loenhout, R.B.; Swank, D.J.; Jansen, C.L.; Sorgdrager, B.J. (BMJ Case Reports, 2018)
We describe a case of polymicrobial bacterial pericarditis with Klebsiella pneumoniae and Proteus mirabilis, caused by pericardial penetration of the tip of the catheter of a laparoscopic adjustable gastric band (LAGB). The patient developed a cardiac tamponade, and subsequently emergency pericardiocentesis was performed. Analysis of earlier CT scans showed that the tip of the catheter had migrated through the liver and through the diaphragm into the pericardium, and was in contact with the myocardium. After stabilisation he was operated to remove the LAGB. In this case report, we describe the chain of events that led to the polymicrobial pericarditis - a complication of LAGB placement that to our knowledge has thus far never been reported. We furthermore present a detailed literature review of all published cases of polymicrobial pericarditis and its causes. © 2018 BMJ Publishing Group Ltd. All rights reserved.
Keywords: emergency medicine; gastroenterology; gastrointestinal surgery; interventional cardiology

Intentional cyanoacrylate ingestion: A rare cause of delayed gastric perforation requiring gastric wedge resection - Lee, S.H.; Yun, S.J.; Ryu, S.; Choi, S.W.; Kim, H.J.; Kang, T.K.; Oh, S.C.; Cho, S.J. (American Journal of Emergency Medicine, 2018)
Cyanoacrylate (LOCTITE® 401™) is a fast-acting adhesive available nationwide, with medical and household uses. Most cases of cyanoacrylate exposure are accidental and occur in children less than 5 years old. Various routes of exposure have been reported including the dermal, oral, ocular, otic, nasal, and urethral routes; however, very few result in serious complication and mortality. Although a few cases of airway obstruction related to cyanoacrylate ingestion have been reported, intentional cyanoacrylate ingestion-induced gastrointestinal tract injury has scarcely been reported. In addition, there have been no reports of serious complications following intentional cyanoacrylate ingestion requiring surgical intervention. Herein, we report a case of intentional ingestion of cyanoacrylate in a 70-year-old man who required gastric wedge resection due to delayed gastric perforation. © 2017 Elsevier Inc.
Keywords: Cyanoacrylate; Gastric perforation; Intentional ingestion; Surgical treatment; Toxicology

Critical evaluation of colon submucosal microdialysis in awake, mobile rats - Cibicek, N.; Ehrmann, J.; Proskova, J.; Vecera, R. (PLoS ONE, 2018)
Sensors able to record large bowel physiology and biochemistry in situ in awake rodents are lacking. Microdialysis is a mini-invasive technique that may be utilized to continuously deliver or recover low-molecular substances from various tissues. In this experiment we evaluated the feasibility of in vivo microdialysis to monitor extracellular fluid chemistry in the descending colon submucosa of conscious, freely moving rodents. Following surgical implantation of a microdialysis probe, male Wistar rats were housed in metabolic cages where they were analgized and clinically followed for four days with free access to standard diet and water. To assess local microcirculation and probe function, glucose, lactate, glucose-to-lactate ratio and urea clearance were determined in the dialysates from the three postoperative days with focus on the final 24-h period. In an attempt to mitigate the expected tissue inflammatory response, one group of animals had the catheters perfused with 5-ami-nosalicylic acid-enriched medium with final concentration 1 ?mol/L. For verification of probe position and the assessment of the surrounding foreign body reaction, standard histological and immunohistochemical methods were employed. Microdialysis of rat gut is associated with considerable technical challenges that may lead to the loss of probe function and high drop-out rate. In this setting, limited data did not allow to draw any firm conclusion regarding local anti-inflammatory effectiveness of 5-aminosalicylic acid perfusion. Although intestinal microdialysis may be suitable for larger anesthetized animals, low reproducibility of the presented method compromises its routine experimental use in awake and freely moving small-sized rodents. © 2018 Cibicek et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Novel diagnostics in revision arthroplasty: Implant sonication and multiplex polymerase chain reaction - Hischebeth, G.T.R.; Gravius, S.; Buhr, J.K.; Molitor, E.; Wimmer, M.D.; Hoerauf, A.; Bekeredjian-Ding, I.; Randau, T.M. (Journal of Visualized Experiments, 2017)
In orthopedic patients, foreign body-associated infections, especially periprosthetic joint infections (PJIs), are a devastating complication of arthroplasty. Infection requires complex treatment, may result in long hospitalization and causes considerable costs. Multiple surgical revisions can be necessary in these patients, with a loss in function as well as in quality of life. The routine preoperative diagnostics include blood examination for C-reactive protein (CRP) and other biomarkers, as well as joint aspirate analysis for cell count, differentiation, and culture. Intraoperative specimens for histology and microbiology are also standard procedure. The microbiological examination of removed implants with sonication, in combination with the implementation of molecular biology techniques in microbiology, represent two novel techniques currently employed to enhance the differential diagnostics of PJI. We present here the step-wise procedure of analyzing joint aspirate and sonication fluid, using a cartridge-based multiplex polymerase chain reaction (PCR) system. Results were matched against conventional cultures and consensus criteria for PJI. Conventional microbiological cultures from tissue biopsies, joint aspirate and sonication fluid showed a sensitivity of 66.7%, 66.7%, and 88.9%, respectively, and a specificity of 82.3%, 54.6%, and 61.5%, respectively. The PCR diagnostic of the sonication fluid and the joint fluid showed a sensitivity of 50.0% and 55.6%, respectively, and both a specificity of 100.0%. Both PCR diagnostics combined had a sensitivity of 66.7% and a specificity of 100.0%. The multiplex PCR therefore presents a rapid diagnostic tool with moderate sensitivity but high specificity in diagnosing PJI. © 2017, Journal of Visualized Experiments. All rights reserved.
Keywords: Arthroplasty; Hip; Issue 130; Knee; Medicine; Periprosthetic joint infection; Polymerase chain reaction; Revision surgery; Sonication

Retained fragment of surgical gauze in hip arthroplasty - Case report and literature review - Wui, N.B.; Ariff, M.A.M.; Rani, R.A.; Yahaya, N.H.M. (Brunei International Medical Journal, 2017)
Cases of retained foreign body are rarely reported due to its medico-legal implications. We present a case of retained surgical gauze fragments after bipolar hemiarthroplasty of hip in a patient who sustained left neck of femur fracture. This complication occurred despite strict adherence to standard operating theater protocols which includes meticulous swab and instrument count. We propose an additional operating room processes and surgical technique in preventing such complications in future hip arthroplasties in our centre.
Keywords: Femur neck fracture; Foreign body; Gossypiboma; Hemiarthroplasty; Medico-legal

A case of renal gossypibomas mimicking tumor pathological discovery - Doh, K.; Thiam, I.; Takin, R.C.A.; Bissirou, I.; Gaye, G.W. (African Journal of Urology, 2017)
Introduction The gossypibomas is an inflammatory granuloma centered by textile fibers forgotten during surgery. Renal gossypibomas is a rare post-operative complication. The authors report a case of gossypibomas simulating kidney tumor pathological discovery. Observation The patient A. G. 53 years old, with a history of left nephrolithotomy by lumbotomy 5 years earlier was admitted for left lumbar pain lasting for 4 months. The uro-scan was consistent with an upper polar cyst Bosniack III. Macroscopic examination of the nephrectomy piece noted, a cystic cavity 7x6 cm containing gauze surrounded by a gelatinous substance. The histological sections showed a thickened wall, including calcification foci and granulomatous reaction to foreign bodies. The diagnosis of a pseudo-tumor gossypibomas left kidney was retained. Conclusion The textile fibers may trigger an acute inflammatory reaction with formation of a perirenal abcess if aseptic resulting in the formation of fibrotic foci, encystment and calcification. Renal gossypibomas pose diagnostic difficulties in the absence of pathognomonic clinical and radiological signs. The presence of a renal mass associated with a history of kidney surgery on the same side should suggest first a gossypibomas. The treatment is surgical. Partial nephrectomy is the treatment of choice. The best treatment remains prevention by careful gauze counts, and surgical drapes in the beginning and end of intervention. © 2017 Pan African Urological Surgeons’ Association
Keywords: gauze; Gossypibomas; kidney; pseudo-tumor; Senegal.; Thies

Duodenal perforation due to ingested partial denture - Siddiq, M.; Qureshi, A.U.; Farooq, M.S.; Ali, A.A. (Journal of the College of Physicians and Surgeons Pakistan, 2017)
Ingestion of foreign bodies including dentures can be a cause of morbidity and mortality. We report a case of poor-fit denture in an elderly male with pulmonary and musculoskeletal comorbidities, who presented as an acute abdomen. The pin attached to the denture caused perforation of first part of duodenum. The only positive finding prior to surgery was a radiopaque density in the abdominal radiograph of the patient and air under the diaphragm. It is important for all the surgeons dealing with acute care patients to be aware of different designs and constructions of dentures.
Keywords: Denture design; Geriatric pop; Ingested foreign bodies; Partial denture

Anterior segment optical coherence tomography and retained vegetal intraocular foreign body masquerading as chronic anterior uveitis - Mahmoud, A.; Messaoud, R.; Abid, F.; Ksiaa, I.; Bouzayene, M.; Khairallah, M. (Journal of Ophthalmic Inflammation and Infection, 2017)
Background: The purpose of this single case report was to report the use of anterior segment optical coherence tomography for the diagnosis and management of a retained vegetal intraocular foreign body. Results: A 23-year-old otherwise healthy male presented with a progressive vision loss in the right eye (RE). He reported a mild ocular trauma with a tree leaf 1 year ago followed by recurrent episodes of redness and pain in the RE that partially resolved after a self-medication with topical steroids. Visual acuity of the RE was limited to light perception. Slit-lamp examination of the RE showed an iris granuloma with overlying exudate and associated anterior chamber inflammatory reaction. Film X-rays, contact B-scan ultrasonography, and CT scan showed no abnormalities. Anterior segment optical coherence tomography revealed an enclaved iris foreign body. The foreign body was removed after a short course of local antibio-corticosteroid therapy. This was followed 2 months later by cataract surgery with intraocular lens implantation, with subsequent improvement of visual acuity to 20/40. Conclusions: A missed intraocular foreign body can lead to sight-threatening complications. Anterior segment optical coherence tomography may be useful for detecting non-clinically evident intraocular foreign body involving the anterior segment masquerading as chronic anterior uveitis. © 2017, The Author(s).
Keywords: Anterior segment optical coherence tomography; Masquerade syndrome; Vegetal intraocular foreign body

Mature cystic teratoma of mediastinum compressing the right atrium in a child: A rare case report - AlHarbi, K.M.; Sairafi, M.H.; Almuzaini, S.A. (Journal of Taibah University Medical Sciences, 2017)
Teratomas or Germ cell tumours (GCTs) are interesting because of their obscure origin, bizarre microscopic appearance and unpredictable behaviour. Mediastinal teratoma is a slowly growing and rare tumour found in children that is diagnosed incidentally in asymptomatic patients. Most of the symptoms are related to mass compression effects such as chest pain, cough, respiratory distress and dysphagia. We report a 5-year-old male child who presented with a history of foreign body ingestion, sternal and left upper quadrant pain and vomiting without respiratory distress. The patient was incidentally found to have an anterior mediastinal mass compressing the right atrium and was diagnosed by histopathological examination as having a mature cystic teratoma of the mediastinum. The patient was successfully treated by the surgical resection of the tumour. © 2017 The Authors
Keywords: Anterior mediastinum; Children; Histopathology; Surgical treatment; Teratoma

A missed diagnosis of multiple intraocular foreign bodies for 21 years - Yang, X.; Liu, C.; Liu, L.; Zhang, L. (Contact Lens and Anterior Eye, 2017)
A 30-year-old patient went to the emergency department because of a chemical burn to the left eye more than 10 days ago by toilet cleanser. Surprisingly, a small piece of glass was found in the inferior anterior chamber in the same eye. The visual acuity was counting fingers. There was conjunctival congestion, corneal oedema and Descemet's membrane striae. And there was also a corneal leukoma around 4 to 5 o'clock. Through repeated questioning he recalled that he was injured by an exploded light bulb around 21 years ago. He was asymptomatic until he saw “something moving” in front of the left eye one month ago. Computed tomography (CT) scanning, ultrasonography, ultrasound biomicroscopy (UBM), anterior segment optical coherence tomography (AS-OCT) verified the presence of multiple intraocular foreign bodies (IOFBs) in the anterior chamber and vitreous cavity. B-scan verified the IOFB in the vitreous cavity. Thus, he was diagnosed with corneal chemical burn, IOFBs and corneal leukoma of the left eye. The IOFB in the anterior chamber was removed through surgery. An attempt was made to remove the IOFB in the vitreous cavity with electromagnet, but it was not successful. Vitrectomy could not be performed as it was hindered by the opacity of cornea. After surgery, the visual acuity remained counting fingers and the corneal oedema still existed. This case is a reminder that a detailed history taking, a thorough physical examination and modern imaging techniques are beneficial for establishing the diagnosis and treatment of IOFBs. © 2017 British Contact Lens Association
Keywords: Asymptomatic; Glass; Intraocular foreign body; Ocular trauma

Effect of hand hygiene and glove use on cleanliness of reusable surgical instruments - Costa, D.M.; Lopes, L.K.O.; Tipple, A.F.V.; Castillo, R.B.; Hu, H.; Deva, A.K.; Vickery, K. (Journal of Hospital Infection, 2017)
Background During functionality testing and packaging of reusable surgical instruments (RSI) for sterilization, instruments are frequently touched. There is a lack of standards relating to hand hygiene frequency and use of gloves in the sterilizing service unit packing area. Aim To determine the effect of hand hygiene and glove use on maintenance of RSI cleanliness. Methods Following manual and automated cleaning, Halsted-mosquito forceps were assessed for adenosine triphosphate (ATP), protein and microbial contamination after handling with gloved and ungloved but washed hands using an ATP surface swab test, bicinchoninic acid assay, and standard culture plate/broth, respectively. Gram's stain was used to classify the isolates. RSI contamination was assessed immediately following and 1, 2, and 4 h after washing hands. Findings Packing instruments with hands that had been unwashed for 2 or 4 h resulted in a significant increase in contaminating ATP when compared with all other treatment groups (P < 0.05). There was a significant correlation between the time since washing hands, the amount of ATP (r = 0.93; P ≤ 0.001), and the microbial load (r = 0.83; P ≤ 0.001) contaminating the forceps, where the longer the time the hands remained unwashed the higher the contamination. Significantly more contaminating protein was found on forceps handled with ungloved hands that had not been washed for 2 or 4 h (P < 0.001). Conclusion Critical RSI inspection, assembling, lubricating and packing should be performed using either gloves or within 1 h of washing hands. © 2017 The Healthcare Infection Society
Keywords: Colony count; Gloves; Hand hygiene; Microbial; Sterilization; Surgical instruments

Pancreatitis and cholangitis following intraductal migration of a metal clip 5 years after laparoscopic cholecystectomy - Antunes, A.G.; Peixe, B.; Guerreiro, H. (Gastroenterologia y Hepatologia, 2017)

Removal of Entrapped Transoesophageal Echocardiography Probe Under the Guidance of Fluoroscopic Imaging - Kim, K.-H.; Seol, S.-H.; Song, Y.-S.; Kim, D.-K.; Kim, D.-I. (Heart Lung and Circulation, 2017)

Radioactive seed migration following parotid gland interstitial brachytherapy - Fan, Y.; Huang, M.-W.; Zhao, Y.-J.; Gao, H.; Zhang, J.-G. (Brachytherapy, 2017)
Purpose To evaluate the incidence and associated factors of pulmonary seed migration after parotid brachytherapy using a novel migrated seed detection technique. Methods and Materials Patients diagnosed with parotid cancer who underwent permanent parotid brachytherapy from January 2006 to December 2011 were reviewed retrospectively. Head and neck CT scans and chest X-rays were evaluated during routine follow-up. Mimics software and Geomagic Studio software were used for seed reconstruction and migrated seed detection from the original implanted region, respectively. Postimplant dosimetry analysis was performed after seeds migration if the seeds were still in their emitting count. Adverse clinical sequelae from seed embolization to the lung were documented. Results The radioactive seed implants were identified on chest X-rays in 6 patients. The incidence rate of seed migration in 321 parotid brachytherapy patients was 1.87% (6/321) and that of individual seed migration was 0.04% (6/15218 seeds). All migrated seeds were originally from the retromandibular region. No adverse dosimetric consequences were found in the target region. Pulmonary symptoms were not reported by any patient in this study. Conclusions In our patient set, migration of radioactive seeds with an initial radioactivity of 0.6–0.7 mCi to the chest following parotid brachytherapy was rare. Late migration of a single seed from the central target region did not affect the dosimetry significantly, and patients did not have severe short-term complications. This study proposed a novel technique to localize the anatomical origin of the migrated seeds during brachytherapy. Our evidence suggested that placement of seeds adjacent to blood vessels was associated with an increased likelihood of seed migration to the lungs. © 2017 American Brachytherapy Society
Keywords: 3D reconstruction; Brachytherapy; Parotid; Seed migration

Incidence, root cause, and outcomes of unintentionally retained intraabdominal surgical sponges: A retrospective case series from two hospitals in Togo - Tchangai, B.; Tchaou, M.; Kassegne, I.; Simlawo, K. (Patient Safety in Surgery, 2017)
Background: The term gossypiboma refers to a sponge that has been forgotten in the surgical field. It is the most common retained surgical item, and constitutes a continuing problem for surgical safety. We performed a hospital-based study to examine their incidence, root cause, and outcomes, as an effort toward improving prevention. Methods: This retrospective study covered 10 years (2006-2015) and included surgically confirmed cases of abdominal gossypibomas occurring after 45,011 abdominal and gynaecological operations in 2 public hospitals in Lome (Togo). Age, diagnosis, initial surgical procedure, evidence of textile count, and data related to the revision procedure were collected for descriptive analysis. Results: Fifteen cases of gossypibomas (11 women and 4 men) were recorded. The mean age of the patients was 27 (range 21-55) years. Initial procedures were gynaecological in 11 patients and 5 cases involved an emergency surgery. Evidence of sponge counting was found in 6cases. Gossypiboma was an incidental finding in 1 patient. The average time to onset of symptoms after the initial procedure was 2 months. The gossypiboma was removed within 7 days to 4 years after the initial procedure. Postoperative complications included enterocutaneous fistula in 2 patients, incisional hernia in 2 patients, and wound sepsis in 1 patient. Death occurred in 2 patients (13.3%). Conclusions: Although rare, the incidence of gossypibomas is still unacceptably high and reveals failures regarding patient safety standards. The associated morbidity and mortality are significant, yet can be reduced by an early diagnosis in the immediate postoperative period. A systematic methodical count of sponges is the cornerstone of prevention, and introducing surgical safety protocols, such as the WHO Safe Surgery Saves Lives checklist, can enhance effectiveness. There is a crucial need for safety-focused policies, which may include a never event reporting system, elaboration of prevention strategies, interventions, and evaluation. © 2017 The Author(s).
Keywords: Complications; CT scan; Foreign body reaction; Gossypiboma; Laparotomy; Prevention

First identification of Gordonia sputi in a post-traumatic endophthalmitis patient - A case report and literatures review - Fang, W.; Li, J.; Cui, H.-S.; Jin, X.; Zhai, J.; Dai, Y.; Li, Y. (BMC Ophthalmology, 2017)
Background: We present a case of post-traumatic endophthalmitis with relatively good prognosis caused by Gordonia sputi, which, to our knowledge is the first case in the literature. Case presentation: A 24 year old man, who underwent an intraocular foreign body extraction half a month before presentation in the left eye, was referred to us complaining of blurred vision and slight pain for 5 days. His first presentation showed moderate intracameral and intravitreous purulent inflammation with a best corrected vision of counting fingers. After gram staining of the intravitreous samples revealed a gram-positive bacilli infection, a combination of amikacin and vancomycin was initially injected intravitreously. The left eye kept stable for three days but deteriorated on the 4th day. On the 5th day after presentation conventional culture characterized the bacterium as an Actinomyces sp. while 16S ribosomal RNA gene sequencing confirmed it as Gordonia sputi. Thereby a complete pars plana vitrectomy combined with lensectomy and silicone oil tamponade was performed. During the surgery an intraocular irrigation with penicillin G was adopted, followed by administration of intravenous penicillin G twice one day for a week. A relatively normal fundus with slight intracameral inflammation was observed a week after the operation, and the best corrected vision recovered to 0.15. One year later his vision remained 0.1. Conclusion: Gordonia sputi should be taken into consideration in patients with post-traumatic endophthalmitis especially due to foreign body penetration. Compared to conventional laboratories, molecular methods are recommended for an accurate diagnosis. A comprehensive strategy of antimicrobial agents and vitrectomy may render a satisfactory result. © 2017 The Author(s).
Keywords: Actinomyces; Case report; Endophthalmitis; Gordonia sputi; Traumatic

Complete transmural migration of a retained surgical sponge: An atypical case in image mimicking intussusception - Zhou, Y.; Chen, P.; Qiao, T.; Chen, Y.-F.; Zong, L. (Medicine (United States), 2017)
Rationale: Intraluminal migration of a retained surgical sponge causing intestinal obstruction and fistula is extremely rare occurrence. Patient concerns: A case of a 35-year-old male, who complaining a diffuse abdominal pain beginning three days earlier. He also complained of occasional vomiting, nonspecific abdominal pain, and an unintentional 15 kg weight loss during the past 2 years. However, there were no clear findings in previous laboratory work. He had received an open appendectomy approximately 4 years earlier. Diagnoses: Retained surgical sponge. Interventions: A contrast-enhanced CT of the abdomen showed a clear invagination of the small intestine. However, intraoperatively, we could not find an intestinal segment with intussusception. After the adhesive intestine was detached, a jejunal-ileal cross-linked fistula was found. More surprisingly, a retained surgical sponge was found inside the ileal fistula when the cross-linked fistula was detached. Outcomes: The patient was discharged 7 days after surgery. Lessons: This is the first report showing an atypical image of a complete transmural migration of a retained surgical sponge mimicking intussusception. © 2017 the Author(s). Published by Wolters Kluwer Health, Inc.
Keywords: abdomen; intussusception; retained surgical sponge; transmural migration

Late Dacron Patch Inflammatory Reaction after Carotid Endarterectomy - Alawy, M.; Tawfick, W.; ElKassaby, M.; Shalaby, A.; Zaki, M.; Hynes, N.; Sultan, S. (European Journal of Vascular and Endovascular Surgery, 2017)
Objective The aim was to analyse the incidence and presentation of carotid patch inflammatory reactions following carotid endarterectomy (CEA). Methods This was a cohort study using a prospectively maintained database. All patients who underwent elective CEA at a tertiary vascular centre between 2002 and 2016 were included. Computed tomography scan angiogram, duplex scan, and leucocyte scintigraphy were used to assess patients with suspected inflammatory patch complications. Re-intervention procedures and outcomes were noted. Histopathology and organisms cultured from the harvested material during re-intervention were assessed. Results During the study period, 633 patients underwent elective CEA. Fifty-one underwent eversion endarterectomy: 111 did not require a patch, whereas 471 patients had a patch repair. Four hundred and twenty eight had a Dacron patch repair and 43 a biological patch. Eight patients returned with late Dacron patch inflammatory complications (1.3% of all CEA and 1.9% of Dacron patch closures) after a period ranging from 18 months to 7 years (mean 4.1 ± 2.1 years). Seven of the eight patients underwent surgical re-intervention, and the eighth patient was deemed high surgical risk. One patient underwent a vein bypass, three had vein patch repair, one required internal carotid artery (ICA) ligation after patch excision, and two were managed by debridement, with omohyoid and sternomastoid muscle covering of the patch. The patient who required ICA ligation suffered a fatal stroke. The remaining patients had a satisfactory outcome. All patients showed evidence of foreign body reaction in pathological examination with no pathological organism cultured from swabs or tissue harvested during surgery. Conclusion Late wound complications after CEA may be related to inflammatory reaction of the Dacron patch rather than infection. Infection should be excluded first. Reconstruction with vein is effective. However, debridement with sternomastoid and omohyoid muscle covering of the patch may be considered in high risk patients after exclusion of infection with regular follow-up. © 2017 European Society for Vascular Surgery
Keywords: Carotid endarterectomy; Dacron; Foreign body reaction; Infection; Patch

Periprosthetic knee infection: Two stage revision surgery - Bonanzinga, T.; Tanzi, P.; Iacono, F.; Ferrari, M.C.; Marcacci, M. (Acta Biomedica, 2017)
Periprosthetic joint infection (PJI) remains a serious complication following a total joint replacement. Diagnosis and management of PJI is challenging for surgeons since there is no “gold standard”. This challenging condition requires a coordinated management approach to achieve good patient outcomes. Further difficulties involve choosing the optimal method to treat the periprosthetic joint infection. In this article, it is stressed the role of the two-stage revision: implant removal, debridement and placement of an antibiotic spacer, and antibiotic therapy with cessation prior to reimplantation. Published literature shows that two stage revision is a valid treatment option for periprosthetic joint infection. (www.actabiomedica.it) © Mattioli 1885.
Keywords: Infection; Knee; Periprosthetic joint infection; Revision; Two stage

Endovascular stent-graft treatment in aortoesophageal fistula caused by foreign bodies - Lu, C.; Gong, J.; Shen, Z.; Yu, C.; Li, Y. (International Journal of Clinical and Experimental Medicine, 2017)
Background: Aortoesophageal fistula (AEF) caused by the ingestion of foreignbodiesis rare and often life threatening. We aim to summarize effective measures to improve the curative effect and survival rate. Case Reports: Between January 2010 and September 2015, three patients with AEF received endovascular stent-graft treatment in our hospital. Through the effective prevention of hemorrhage by stent-grafting, surgical repair of the esophageal rupture was performed successfully. All three cases were treated successfully and survived up to the day that this article was written. Comments: It may be safer to first perform an endovascular stent-graft to prevent hemorrhage in AEF. © 2017, E-Century Publishing Corporation. All rights reserved.
Keywords: Aortoesophageal fistula; Foreign body; Stent-graft

How many people work in your operating room? An assessment of factors associated with instrument recounts within plastic surgery - Reformat, D.D.; David, J.A.; Diaz-Siso, J.R.; Plana, N.M.; Wang, A.; Brownstone, N.D.; Ceradini, D.J. (Journal of Plastic, Reconstructive and Aesthetic Surgery, 2017)
Background Intraoperative instrument recounts are performed to avoid retained foreign surgical items. These additional counts, however, beget risks of their own, including prolonged operative times, exposure to radiation, and increased cost. Our study aimed to identify factors that increase the likelihood of instrument recounts during plastic surgery procedures, and use our findings to guide potential solutions for preventing unnecessary recounts across all surgical fields. Study design This is a retrospective review of all plastic surgical cases in the main operating setting at New York University Langone Medical Center (NYULMC) between March 2014 and February 2015. Results Of 1285 plastic surgery cases, 35 (2.7%) reported a missing instrument necessitating a recount. Of all subspecialties within plastic surgery, only microsurgery conferred an increased risk of a recount event. We identified multiple factors that increased the odds of a recount event, including increased operative time, number of surgical sites, and intraoperative instrument handoffs. Conclusion Instrument recounts, although designed to prevent inadvertently retained surgical items, present inherent risks of their own. In a large retrospective review of plastic surgery cases at our medical center, we identified many factors that increased the likelihood of an instrument recount. On the basis of our findings and prior literature, we recommend limiting the number of staff handling instrument, the number of handoffs, and a heightened awareness by surgeons and perioperative staff of specific procedures and factors that increase the risk of a miscount event. © 2017
Keywords: Miscount; Patient safety; Recount; Retained surgical items; Risk factors; Surgical instruments

Right ventricular outflow tract endocarditis caused by brucellosis - Sabzi, F.; Heidari, A.; Faraji, R. (Journal of Infection and Public Health, 2017)
Right-ventricular outflow tract (RVOT) endocarditis is a very rare presentation of right-sided infective endocarditis (RSIE) by brucellosis. RSIE occurs most commonly in immune-suppressed cases and illicit drug abuser. The patients with RSIE and an incompetent immune system usually have a prosthetic foreign body in blood circulation such as catheter, pacemakers, or central venous lines and may be accompanied with tricuspid or pulmonary valve dysfunction. The most common site for RSIE is the tricuspid valve. We describe an exceedingly rare condition of RVOT endocarditis in a patient with brucellosis in which vegetation is attached to a muscle bundle of the RVOT. Despite appropriate antibiotic therapy, the general condition of the patient deteriorated and was finally scheduled for open-heart surgery. The mass was resected and the patient recovered uneventfully and was discharged on the 9th day of surgery with appropriate oral antibiotics. © 2016 King Saud Bin Abdulaziz University for Health Sciences
Keywords: Endocarditis; Outflow tract; Right cardiac chambers

Keeping count: With the Surgicount Safety-Sponge System, Stryker aims to help healthcare facilities put an end to retained surgical sponges - Seeger, D. (Surgical Products, 2017)

Leaks in fixed-ring banded sleeve gastrectomies: a management approach - Foo, J.W.; Balshaw, J.; Tan, M.H.L.; Tan, J.T.H. (Surgery for Obesity and Related Diseases, 2017)
Background The use of a Fobi ring to prevent pouch dilation is sometimes used in Roux-en-Y gastric bypass (RYGB). Recently, it has been extrapolated to laparoscopic sleeve gastrectomy (LSG) procedures by placing a fixed-ring band a few centimeters below the gastroesophageal junction (GEJ). Objectives What is the consequence if a patient develops a leak? Setting Tertiary metropolitan referral center, Australia. Methods Over 18 months, all patients with either a conventional LSG or a fixed-ring banded sleeve gastrectomy (BLSG) who presented with a proven leak complication were included. The management approaches along with the surgical, endoscopic, and percutaneous procedures used were examined. Results Six patients had a BLSG leak and 6 had a LSG leak. All patients had leak resolution. There was no significant difference in body mass index (BMI), time to leak, initial white cell count (WCC), and C-reactive protein (CRP) levels between the 2 groups. LSG patients required a median of 2 endoscopic procedures (range: 1–3). Stents were deployed in 3 patients. All BLSG patients required a single surgical intervention with laparoscopic washout, drainage, removal of band±feeding jejunostomy. One stent was deployed in 1 BLSG patient. BLSG leak resolution was found at 34±12 days versus 85±12 days in the LSG group (P<.05). Conclusion The BLSG is a new modification of the sleeve gastrectomy procedure. This study presents a management strategy for leak resolution employed in BLSG patients. The presence of a foreign body as a persistent nidus of infection mandates band removal. © 2017 American Society for Bariatric Surgery
Keywords: Banded sleeve gastrectomy; Bariatric surgery; Complications; Fixed-ring sleeve gastrectomy; Gastric leak; Minimizer ring; Sleeve gastrectomy; Sleeve gastrectomy leak

Ball Valve Syndrome Caused by the Migration of Gastrostomy Catheter Tip - Toh Yoon, E.W.; Nishihara, K. (Clinical Gastroenterology and Hepatology, 2017)

Establishment of novel meniscal scaffold structures using polyglycolic and poly- l -lactic acids - Murakami, T.; Otsuki, S.; Nakagawa, K.; Okamoto, Y.; Inoue, T.; Sakamoto, Y.; Sato, H.; Neo, M. (Journal of Biomaterials Applications, 2017)
The purpose of this study was to evaluate various types of meniscus scaffolds that mimic the meniscus structure, and to establish a novel cell-free meniscus scaffold with polyglycolic acid or poly-l-lactic acid. Four types of scaffolds were implanted into Japanese white rabbits: poly-l-lactic acid sponge poly-l-lactic acid, PGA-coated PLLA sponge, PGA lamination, and film-coated PGA lamination. Samples were harvested at 8 and 12 weeks after implantation, and a compression stress test was performed. The meniscus size and Ishida scores were evaluated for regenerated tissue. Immunohistochemistry was analyzed by anti-type I, II and X collagen antibodies to investigate the structure of the regenerated tissue, and by anti-iNOS antibody to investigate the inflammatory tissue of the meniscus. The cell nuclei of lymphocytes and foreign body multinucleated giant cells were counted in hematoxylin and eosin staining. Modified Mankin scores for cartilage degeneration were used for assessment after Safranin-O/Fast Green staining. The biomechanical test showed that l- and film-coated PGA lamination exhibited greater strength than s- and PGA-coated PLLA sponge. At 12 weeks, the size of meniscus and the Ishida score in implanted film-coated PGA lamination were improved significantly compared with the defect groups. The type II collagen staining intensity in the PGA lamination lamination is significantly higher than the defect at eight weeks. The staining intensity of iNOS and number of lymphocytes significantly increased in sponge poly-l-lactic acid at eight weeks, and increased in p-PLLA at 12 weeks. Foreign body multinucleated giant cells in implantation groups appeared, especially at eight weeks. The Mankin score for film-coated PGA lamination was significantly lower than for the defect at 12 weeks. Novel meniscal scaffolds especially PGA should possess not only biological but also biomechanical functions. In conclusions, film-coated PGA lamination was the beneficial property for meniscus scaffold from the points of better biomechanical function, good regeneration, and less inflammation with chondroprotective effects. © The Author(s) 2017.
Keywords: Meniscectomy; meniscus repair; meniscus scaffold; poly- l -lactic acid; polyglycolic acid

Adenoviral nephritis in a renal transplant recipient: Case report and literature review - Veer, M.; Abdulmassih, R.; Como, J.; Min, Z.; Bhanot, N. (Transplant Infectious Disease, 2017)
Adenovirus (AdV) infections in transplant recipients may cause invasive disease. We present a case of granulomatous interstitial nephritis secondary to AdV infection in a renal transplant recipient that was initially interpreted as acute graft rejection on histopathology. Specific testing based on clinical suspicion, however, aided in making an accurate diagnosis. We present a retrospective review of all cases of AdV infection in renal transplant recipients to date, and analyze outcomes based on different treatment modalities for this disease. © 2017 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd
Keywords: adenovirus; nephritis; rejection; transplantation

Radiological, histological, and hematological evaluation of hydroxyapatite-coated resorbable magnesium alloy screws placed in rabbit tibia - Lim, H.-K.; Byun, S.-H.; Lee, J.-Y.; Lee, J.-W.; Kim, S.-M.; Lee, S.-M.; Kim, H.-E.; Lee, J.-H. (Journal of Biomedical Materials Research - Part B Applied Biomaterials, 2017)
Titanium (Ti) screw has excellent mechanical property, and osseointegration capacity. However, they require surgery for removal. In contrast, polymer screws are resorbable, but they have poor mechanical properties. In this research, magnesium alloy screws (WE43: Mg-Y-Nd-Zr) that have advantages of titanium and polymer were manufactured. In addition, to increase biocompatibility and control degradation rate, the Mg alloy was coated with hydroxyapatite (HA). Torsion test and corrosion test were performed in vitro. For clinical, radiological and histological evaluation, on the eight rabbits, two HA-coated screws were installed in left tibia, and two noncoated screws were installed in right tibia. Each four rabbits were sacrificed 6 and 12 weeks postoperatively. For hematological evaluation, the same type of screws were installed on both legs. Complete blood count (CBC), Mg2+ concentrate were sampled from the ear central artery on the operation day for a control point, and at 1, 2, 4, 6, 8, and 12 weeks. Mg alloy screws have no differences of biocompatibility according to the HA coating. However, resorption of screw was slower in case of the HA coating. The hematological problem related releasing of Mg was not found. The results suggest that Mg alloy screws have feasibility for clinical application. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1636–1644, 2017. © 2016 Wiley Periodicals, Inc.
Keywords: biocompatibility; bioresorbable screw; HA coating; magnesium; magnesium alloy (WE43)

Omental actinomycosis imitating a foreign body infection - Choi, Y.S.; Park, Y.G. (Zeitschrift fur Gastroenterologie, 2017)
Actinomycosis is a rare chronic disease caused by a group of anaerobic Gram-positive bacteria that colonize the mouth, colon, and urogenital tract. Infection involving the cervicofacial area is the most common clinical presentation, followed by that of the pelvic and thoracic areas. The preoperative diagnosis of abdominal actinomycosis is difficult because the condition can be easily confused with malignancy, tuberculosis, or other inflammatory diseases. We report a case of omental actinomycosis mimicking a foreign body. Actinomycosis is diagnosed based on the histopathologic demonstration of sulfur granules in a tissue or organ that was surgically removed. Following confirmative diagnosis by surgical intervention, the patient was treated with oral doxycycline 100mg twice daily for 6 months. A follow-up abdominopelvic computed tomography after 16 months showed no evidence of inflammation. Moreover, the patient no longer had disease-associated symptoms and exhibited normal laboratory findings.
Keywords: actinomycosis; foreign body; omentum

Team Training in the Perioperative Arena: A Methodology for Implementation and Auditing Behavior - Rhee, A.J.; Valentin-Salgado, Y.; Eshak, D.; Feldman, D.; Kischak, P.; Reich, D.L.; LoPachin, V.; Brodman, M. (American Journal of Medical Quality, 2017)
Preventable medical errors in the operating room are most often caused by ineffective communication and suboptimal team dynamics. TeamSTEPPS is a government-funded, evidence-based program that provides tools and education to improve teamwork in medicine. The study hospital implemented TeamSTEPPS in the operating room and merged the program with a surgical safety checklist. Audits were performed to collect both quantitative and qualitative information on time out (brief) and debrief conversations, using a standardized audit tool. A total of 1610 audits over 6 months were performed by live auditors. Performance was sustained at desired levels or improved for all qualitative metrics using χ2 and linear regression analyses. Additionally, the absolute number of wrong site/side/person surgery and unintentionally retained foreign body counts decreased after TeamSTEPPS implementation. © 2016, © The Author(s) 2016.
Keywords: checklist; communication; perioperative; TeamSTEPPS; teamwork

Clinical Issues—July 2017 - Ogg, M.J.; Johnstone, E.M. (AORN Journal, 2017)
Operation of fluoroscopy equipment Key words: fluoroscopy, mini C-arm, scope of practice, radiologic device. Patient education after radionuclide implantation Key words: radionuclides, brachytherapy, prostate cancer, radiation safety. Personal protective equipment Key words: clean, decontamination, instruments, PPE, tray assembly. Safe staffing patterns Key words: on-call staffing, schedules, safe staffing levels. Counting instruments when laparoscopy procedures convert to open procedures Key words: counts, instrument, laparoscopy, retained surgical items. © 2017 AORN, Inc

Toothpick meningitis - Zhou, Q.; Singh, N.; Monteforte, B. (Radiology Case Reports, 2017)
A 66-year-old male with a history of hypertension, back pain, diverticulosis and anal fistula presents with acute onset syncopal episodes, worsening back pain, and altered mental status. The patient exhibited considerable leukocytosis but was hemodynamically stable. CT imaging of the head revealed a gas pattern in the posterior fossa and velum interpositum. CT imaging of the abdomen and pelvis revealed a needle-like foreign body traversing the left sacrum to the sigmoid colon. A lumbar puncture revealed meningitis. Flexible sigmoidoscopies were performed without successful visualization of the foreign body. An explorative laparoscopy was successfully performed, enabling retrieval of what was determined to be a wooden toothpick. The patient remained hemodynamically stable with persistent altered mental status and was eventually discharged after completion of antibiotics on day 47 of hospitalization. This case illustrates a rare complication of ingesting a sharp foreign body that was identified by CT of the brain and abdomen/pelvis with successful surgical repair. © 2016 The Authors
Keywords: Foreign object; Ingestion; Meningitis; Perforation

Infarcted neuroendocrine tumor following endobronchial ultrasound guided fine needle aspiration of a pulmonary nodule: Typical versus atypical carcinoid a pathological diagnostic dilemma - Jassim, S.H.; Temes, R.T.; Tomashefski, J., Jr. (Human Pathology: Case Reports, 2017)
Introduction Pulmonary Neuroendocrine tumors have been categorized into high, intermediate and low grade. The distinction between low grade typical carcinoid from atypical carcinoid depends on mitotic count and presence of punctate necrosis. Case presentation The patient is a 60 year old female with past medical history of diabetes mellitus, hyperlipidemia, gastrointestinal reflux disease and cervical myelopathy. An incidental right upper lobe nodule was discovered during hospitalization for post-total knee arthroplasty sepsis. Follow-up CT and PET scans demonstrated size stability with mild hypermetabolic activity. The tumor was excised by a robotic thoracoscopic right upper lobectomy and mediastinal lymph node dissection. A lobulated, tan-yellow, well demarcated firm mass, measuring 1.2 × 1 × 1 cm was grossly identified. Microscopically, the well circumscribed mass demonstrated near complete infarct-like central necrosis with a peripheral viable cellular rim consisting of nests of tumor cells that stained positively with TTF-1, Synaptophysin, Chromogranin, and CD56; and was negative for calcitonin and monoclonal CEA. The mitotic figure count was negligible and met the WHO criteria for typical carcinoid. The proliferative index (Ki-67) was slightly high at 9.29%. Discussion The unusual central necrosis seen in the tumor and the relatively high proliferative index created a pathological diagnostic dilemma discussed in this report. © 2017 The Authors
Keywords: Carcinoid; Lung; Neuroendocrine tumors

SURGICAL COUNTING: A PERIOPERATIVE NURSE'S PERSPECTIVE - Warwick, V.; Gillespie, B. (Australian nursing & midwifery journal, 2017)
The Australian College of Perioperative Nurses (ACORN) have developed a set of standards to guide clinical practice within the perioperative setting. The ACORN standard 'Management of accountable items used during surgery and procedures' (ACORN 2016) details a process for perioperative nurses to follow when undertaking a surgical count.

Mycobacterium avium complex septic arthritis presenting as osteonecrosis of the femoral head in a patient with systemic lupus erythematosus - Christ, A.B.; Zininberg, E.V.; Jules-Elysee, K.M.; Parks, M.L. (Orthopedics, 2017)
Mycobacterium avium complex is a rare cause of musculoskeletal infection, usually occurring in patients with compromised immune systems. Obtaining the diagnosis requires a high index of suspicion, and treatment can be delayed because of difficulty with isolating the organism. Treatment involves prolonged, targeted combination antibiotic therapy, and it is unclear whether eradication of the infection can occur in the presence of a foreign body, such as antibiotic spacers. The authors report a case of M avium infection presenting as presumed osteonecrosis of the femoral head in a young woman with systemic lupus erythematosus. She presented with collapse of her femoral head coinciding with several months of progressive, debilitating hip pain. She had mild fevers during that time, but results from multiple infectious workups, including hip aspiration, were negative. Purulent fluid was found in the operating room, but diagnosis was delayed for 5 weeks while waiting for cultures. The patient required 3 subsequent operations, eventually being left with a resection arthroplasty. Pertinent issues concerning diagnosis, therapy, and treatment challenges in M avium infections of the musculoskeletal system are discussed in this case report. © SLACK Incorporated.

Appendiceal foreign body in an infant - Lee, M.; Kim, S.C. (Medicine (United States), 2017)
Rationale for this case report: Many children are hospitalized because of foreign body ingestion. In such circumstances, the gastroenterologist must consider the timing of ingestion; the size, type, and location of the object ingested; and the patient's symptoms. But appendiceal foreign body in infant is very rare. Patient concerns: A 12-month-old boy visited because of swallowing small objects 2 weeks ago. Three small beads were found in the right lower quadrant on abdominal radiography. A 7-year-old boy was admitted for treatment of appendiceal foreign body, which was detected by accident 3 months ago. Diagnoses, interventions, and outcomes: A 7-year-old boy had abdominal pain and underwent immediate appendectomy. However, the 12-month-old child was asymptomatic, which led to deliberation in regard to wait time for an appendectomy in younger children with asymptomatic appendiceal foreign body. He underwent prophylactic appendectomy after 2 months. Main lessons: An appendiceal foreign body is very rare in infant and there are currently no treatment guidelines. We report 2 cases of appendiceal foreign body including infant who gave us difficult decisions. Copyright © 2017 the Author(s).
Keywords: Appendectomy; Appendicitis; Foreign body

Forgotten Kirschner wire passing across the sigmoid colon - Matsumoto, H.; Yo, S.; Fukushima, S.; Osawa, M.; Murao, T.; Ishii, M.; Fujita, M.; Shiotani, A. (Clinical Journal of Gastroenterology, 2017)
The Kirschner wire (K-wire) is used in the treatment of hip fractures, and migration of a K-wire into the pelvis with resultant colon injury is a very rare complication. We report a case in which a forgotten K-wire passing across the sigmoid colon was accidentally found by screening colonoscopy in a patient with no abdominal symptoms. Surgery was performed to remove the K-wire. Although the migration of a K-wire is extremely rare, it is important for it to be considered in patients with a history of orthopedic surgery. © 2017, Japanese Society of Gastroenterology.
Keywords: Colon; Foreign body ingestion; Kirschner wire

Aseptic Lymphocytic-Dominated Vasculitis-Associated Lesions Scores Do Not Correlate With Metal Ion Levels or Unreadable Synovial Fluid White Blood Cell Counts - Plummer, D.R.; Yi, P.H.; Jacobs, J.J.; Urban, R.M.; Moric, M.M.; Della Valle, C.J. (Journal of Arthroplasty, 2017)
Background Failed metal-on-metal (MoM) bearings are being increasingly encountered with little information to guide evaluation for aseptic lymphocytic-dominated vasculitis-associated lesions (ALVAL). It is often assumed that elevated metal ion levels correlate with the occurrence of ALVAL. Our purpose was to determine the utility of the erythrocyte sedimentation rate, C-reactive protein, synovial white blood cell count, differential (%PMN), and serum metal ion levels in diagnosing ALVAL. Methods We identified 80-failed MoM total hip arthroplasties. Tissue was examined under light microscopy and graded on a scale of ALVAL severity. Mean laboratory values were compared between groups and receiver operating curves generated with an area under the curve to determine test performance and optimal cutoffs. Results ALVAL scores were graded as low in 30 (37.5%), moderate in 39 (49%), and severe in 8 (10%), with 3 being unreadable. No clear cutoff values for erythrocyte sedimentation rate, C-reactive protein, or synovial white blood cell count could be determined to reliably diagnose moderate or severe ALVAL. Furthermore, serum metal levels had no correlation with ALVAL score. The best test to diagnose ALVAL was the synovial fluid monocyte percentage with an optimal cutoff value of 39% and area under the curve of 69% (moderate testing performance). Conclusion The diagnosis of ALVAL remains challenging, with most of the screening tests being unreliable. Although serum metal ion levels are typically elevated in failed MoM bearings, higher levels do not appear to correlate with ALVAL grade. Elevated synovial fluid monocytes may provide diagnostic utility for ALVAL, suggesting a possible delayed-type hypersensitivity reaction. © 2016 Elsevier Inc.
Keywords: adverse local tissue reaction; ALVAL; aseptic lymphocytic-dominated vasculitis-associated lesions; failed metal-on-metal bearing; metal ion levels

Three years evaluation of retained foreign bodies after surgery in Iran - Zarenezhad, M.; Gholamzadeh, S.; Hedjazi, A.; Soltani, K.; Gharehdaghi, J.; Ghadipasha, M.; Hosseini, S.M.V.; Zare, A. (Annals of Medicine and Surgery, 2017)
Background Medical errors such as retained foreign bodies (RFB) during surgery are not well studied. To define risk factors associated with this type of error, we performed retrospective study. Methods We reviewed medical records for unintentional foreign object remaining in the body during surgery such as gender, age, surgery ward, and incident reports referred to several forensic medicine administrations as well as adverse effects of retained foreign bodies and methods for detection of them over a 3-years period from January 2008 through May 2011. Results Thirty eight patients were involved in the study to have retained foreign bodies (73% sponges and 27% other instruments including 7 (18.42%) cases of other bandages, 2 cases (5.26%) of scissor and 1 case (2.63%) of forceps). The general surgery ward was most commonly involved (47%) followed by the gynecology surgery ward (34%). Men (58%) were more involved with RFB than women (42%). Conclusion Considering the most frequent type of retained foreign bodies and also more frequent involved surgery wards besides detection methods for RFB, a mixed of preventing protocols such as regular counting of devices, post-operative X-ray with radiopaque markers and exact evaluation of surgery site should be employed to reduce the occurrence of retained foreign bodies and its complications. © 2017
Keywords: Medical error; Retained foreign body; Surgery

Penetrating palpebral grass awn in a dog: Unusual case of a penetrating grass awn in an eyelid - Marchegiani, A.; Fruganti, A.; Cerquetella, M.; Cassarani, M.P.; Laus, F.; Spaterna, A. (Journal of Ultrasound, 2017)
An unusual case of a penetrating grass awn in an eyelid of a dog is reported. A 6-month-old mixed breed dog was referred to the Ophthalmology Unit of the Veterinary Teaching Hospital of Camerino University for anorexia, lethargy, left monolateral ocular swelling and pain to the left eye, present from 1 month. Ophthalmic examination of the left eye showed copious and purulent discharge, and ultrasonography revealed the presence of an abscess containing a grass foreign body. The grass awn was surgically removed. Three days after surgery, the dog showed a marked improvement, with a total resolution obtained in 7 days. To the authors’ knowledge, penetrating foreign bodies such as the one of this paper have never been described before in literature. © 2017, Società Italiana di Ultrasonologia in Medicina e Biologia (SIUMB).
Keywords: Dog; Foreign body; Grass awn; Lid abscess; Swollen eyelid; Ultrasonography

Surgical count process: evidence for patient safety - Freitas, P.S.; Mendes, K.D.; Galvão, C.M. (Revista gaucha de enfermagem, 2017)
Objective: To analyze the surgical count process according to reports of nurses working in surgical centers of a city in the state of São Paulo. Methods: Cross-sectional study with a sample of 55 nurses. Data collection occurred from August to December 2013, with application of an instrument submitted to face and content validation, composed of data on variables regarding characteristics of nurses, hospital, and surgical count process. Results: Fifty-two (94.5%) nurses reported that the surgical count process was carried out in their workplaces. A statistically significant association was found between the surgical count process and the type of institution (P=0.046), and between the presence of a surgical technologist and the processes for counting surgical instruments (P<0.001) and sponges (P=0.016). Conclusion: The results found contributed to understand how, by whom, and when the surgical count process was carried out in the studied hospital.

Preserving brain function in a comatose patient with septic hyperpyrexia (41.6 °C): A case report - Sterkel, S.; Akinyemi, A.; Sanchez-Gonzalez, M.A.; Michel, G. (Journal of Medical Case Reports, 2017)
Background: Pyrexia is a physiological response through which the immune system responds to infectious processes. Hyperpyrexia is known to be neurodegenerative leading to brain damage. Some of the neurotoxic effects of hyperpyrexia on the brain include seizures, decreased cognitive speed, mental status changes, coma, and even death. In the clinical management of hyperpyrexia, the goal is to treat the underlying cause of elevated temperature and prevent end organ damage. Case presentation: This case illustrates a 39-year-old white American man referred from another medical facility where he had undergone an upper gastrointestinal tract diagnostic procedure which became complicated by blood aspiration and respiratory distress. During hospitalization, he developed a core body temperature of 41.6 °C (106.9 °F) leading to cognitive decline and coma with a Glasgow Coma Score of 3. Levetiracetam and amantadine were utilized effectively for preserving and restoring neurocognitive function. Prior studies have shown that glutamate levels can increase during an infectious process. Glutamate is an excitatory neurotransmitter that is utilized by the organum vasculosum laminae terminalis through the neuronal excitatory system and causes an increase in body temperature which can lead to hyperpyrexia. Similar to neurogenic fevers, hyperpyrexia can lead to neurological decline and irreversible cognitive dysfunction. Inhibition of the glutamate aids a decrease in excitatory states, and improves the brain's regulatory mechanism, including temperature control. To further improve cognitive function, dopamine levels were increased with a dopamine agonist. Conclusions: We propose that a combination of levetiracetam and amantadine may provide neuroprotective and neurorestorative properties when administered during a period of hyperpyrexia accompanied by any form of mental status changes, particularly if there is a decline in Glasgow Coma Score. © 2017 The Author(s).
Keywords: Amantadine; Glasgow Coma Score; Glutamate; Hyperpyrexia; Levetiracetam; Neuroprotection; Organum vasculosum laminae terminalis

Near-death Thoracic Trauma Caused by a Stingray in the Indian Ocean - Mahjoubi, L.; Joyeux, A.; Delambre, J.-F.; Rind, A. (Seminars in Thoracic and Cardiovascular Surgery, 2017)
Stingray injuries are frequent, and although mostly benign, some can be life-threatening. We present the case of a 24-year-old man who suffered from a stingray attack in the Indian Ocean with a thoracic penetrating trauma, and its management. © 2017 Elsevier Inc.
Keywords: penetrating chest injuries; stingray injuries; thoracic trauma; video-assisted thoracoscopy surgery

An unusual cause of intestinal perforation - Pernar, L.I.M.; Mongiu, A.; Sheu, E.G. (JAMA Surgery, 2017)

Gossypiboma with bleeding from fistula to the colon observed by colonoscopy - Nishimura, N.; Mizuno, M.; Shimodate, Y.; Doi, A.; Mouri, H.; Matsueda, K.; Yamamoto, H. (Clinical Journal of Gastroenterology, 2017)
A gossypiboma is a mass of cotton sponge left in the body postoperatively. Here, we report a case of gossypiboma with bleeding through a fistula to the colon, which became clinically evident 24 years after gynecological surgery, and resembled a bleeding diverticulum at colonoscopy. A 67-year-old woman presented with anemia and hematochezia. She had undergone a hysterectomy for myoma uteri 24 years earlier. Colonoscopy showed a deep depressed lesion mimicking a diverticulum with bleeding in the transverse colon. A contrast-enhanced computed tomography was interpreted as revealing a 6-cm thick-walled tumor, containing an air bubble, and a fistula between the mass and the transverse colon. The patient underwent laparotomy, with the preoperative expectation that the mass was a penetrating submucosal tumor. Pathological findings revealed denatured cotton tissues surrounded by reactive tissues to the foreign body. Despite its rarity, gossypiboma should be considered in patients with an intra-abdominal mass who have a history of laparotomy. Gossypiboma can cause fistula to the colon and bleeding. Imaging studies and the clinical course may mimic a malignant tumor. © 2016, Japanese Society of Gastroenterology.
Keywords: Bleeding; Colonoscopy; Fistula; Gossypiboma

Image-guided percutaneous transhepatic removal of fish bone from liver abscess - Lau, C.W.; Wong, K.M.; Gogna, A. (Journal of Radiology Case Reports, 2017)
We present a case of a woman who was diagnosed with a hepatic abscess secondary to a migrated fish bone. As the patient did not improve after percutaneous drainage of the abscess, image-guided percutaneous transhepatic removal of the fish bone was performed. Fish bones in hepatic abscesses are typically removed surgically, with the fish bone left in situ in a number of cases. There has been only another reported case of percutaneous transhepatic fish bone removal. We conclude that in the rare case of a hepatic abscess complicating fish bone migration, image-guided percutaneous transhepatic removal of the offending foreign body is a feasible alternative to surgery, especially in high surgical risk patients. © 2017, EduRad. All rights reserved.
Keywords: Fish bone; Foreign body migration; Hepatic abscess; Intervention; Percutaneous removal

Eventual Endothelial Failure after Initial Corneal Clearing after a Detached Endothelial Graft in Fuchs Dystrophy - Lee, H.J.; Munir, W.M. (Cornea, 2017)
Purpose: To report a case of eventual corneal endothelial cell failure after spontaneous resolution of corneal edema after failed Descemet membrane endothelial keratoplasty (DMEK). Methods: Retrospective case report. Results: A 56-year-old man with Fuchs endothelial corneal dystrophy underwent cataract and DMEK surgery in the left eye. The transplanted DMEK graft detached in the early postoperative period and formed a peripheral scroll. Despite graft detachment, corneal edema resolved with endothelial cell repopulation of the central cornea. The patient's uncorrected visual acuity 5 months after surgery was 20/25. However, by 7 months after this spontaneous improvement, the patient started to complain of worsening vision. At 2.5 years, recurrent corneal edema became clinically apparent, and no endothelial cells were visible by specular microscopy in the central cornea. Conclusions: This case suggests that spontaneous healing of a large central Descemet membrane defect significantly diminishes the peripheral endothelial cell reserves and can lead to imminent bullous keratopathy. If there is any potential of corneal endothelial cells to regenerate after surgical removal of central Descemet membrane in Fuchs dystrophy, it is likely very limited. Copyright © 2016 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: corneal edema; Descemet stripping; descemetorhexis; DMEK; Fuchs' endothelial dystrophy

A foreign body (Toothbrush) in the Esophagus of a Patient with Hiatal Hernia - Klancnik, M.; Grgec, M.; Perković, N.; Ivanišević, P.; Poljak, N.K. (Case Reports in Gastroenterology, 2017)
Toothbrush ingestion is rare and most commonly seen in patients with psychiatric comorbidities and in young women with a medical history of eating disorders who try to induce emesis. Long ingested objects, such as a toothbrush, cannot pass the gastrointestinal tract spontaneously and require endoscopic removal or even a surgical approach in cases of unsuccessful endoscopic removal or complication development. We present a case of a 71-year-old male with hiatal hernia without psychiatric or neurological comorbidity who accidentally ingested a toothbrush during oral hygiene routine. After X-ray confirmation, the toothbrush was removed endoscopically. © 2017 The Author(s). Published by S. Karger AG, Basel.
Keywords: Endoscopy; Esophageal foreign body; Hiatal hernia; Toothbrush

Detection of Retained Foreign Objects in Upper Extremity Surgical Procedures With Incisions of Two Centimeters or Smaller - Tofte, J.N.; Caldwell, L.S. (The Iowa orthopaedic journal, 2017)
BACKGROUND: While the true incidence of retained foreign bodies after surgery is unknown, it has been approximated at 1:5,500 operations overall, with substantially less frequency in hand and upper extremity procedures. Despite the rarity of foreign body retention in hand and upper extremity surgery, universal radiofrequency scanning for electronically-tagged sponges and automatic radiographic evaluation for incorrect sponge counts are employed for all surgical procedures at our institution. We demonstrate the infeasibility of retaining an operative sponge of a standard size in commonly performed hand and upper extremity procedures with incision sizes of two centimeters or less, and establish that visual detection of sponges in these cases is adequate. METHODS: Eighteen trigger finger releases, five carpal tunnel releases, three trigger thumb releases, and three de Quervain's tenosynovitis releases were successfully performed upon five cadaveric specimens by residents under supervision of fellowship-trained hand surgeons for a total of 29 two-centimeter or smaller incisions. Randomized surgical sponge placement was evaluated by a blinded observer at two distances and incision sizes were quantified. Kappa values were calculated to determine the acuity of visual detection versus the actual presence of a sponge. RESULTS: The maximum length of the standard surgical sponge that could be contained within an incision was three centimeters. When compared with the gold standard (whether the sponge had been placed or not by the operating resident), the placement of a standard surgical sponge could be detected correctly in 100% of cases at both "across the room" and "at the table" distances, for kappa values of 1.0 and 1.0 respectively. This did not vary with incision size or surgical procedure. CONCLUSIONS: The added cost and time from radiofrequency detection of retained sponges and radiographic evaluation in the event of incorrect sponge counts can be safely eliminated if sponges can be reliably visually detected. CLINICAL RELEVANCE: This cadaveric study informs patient safety practices by demonstrating that visual detection of surgical sponges is adequate for certain upper extremity procedures.
Keywords: hand; patient safety; quality improvement; radiofrequency; retained foreign body; retained foreign object; upper extremity

Gossypibomas in India - A systematic literature review - Patial, T.; Thakur, V.; Ganesun, N.K.V.; Sharma, M. (Journal of Postgraduate Medicine, 2017)
Purpose of Review: Gossypibomas remain a dreaded and unwanted complication of surgical practice. Despite significant interest and numerous guidelines, the number of reported cases remains sparse due to various factors, including potential legal implications. Herein, we review related data from India to ascertain if the problem is better or worse than that reported in world literature. Materials and Methods: A literature search was performed on PubMed and Google Scholar, to collect and analyze all case reports and case reviews regarding the condition in India. Results: On analysis of the results, there were 100 publications reporting a total of 126 events. The average patient age was 38.65 years. Average time to discovery was 1225.62 days. Forty-nine percent of reported cases were discovered within the 1 st year. The most common clinical features were pain (73.8%), palpable mass (47.6%), vomiting (35%), abdominal distention (26%), and fever (12.6%). Spontaneous expulsion of the gossypiboma was noted in five cases (3.96%). Transmural migration was seen in 36 cases (28.57%). Conclusions: Despite advancements in surgical approaches and preventive measures, gossypibomas continue to be a cause of significant morbidity. A safe working culture, open communication, teamwork, and an accurate sponge count remain our best defence against this often unpredictable complication of surgery. © 2016 Journal of Postgraduate Medicine | Published by Wolters Kluwer - Medknow.
Keywords: Cottonoma; gauzoma; gossypiboma; pathogenesis; retained foreign body; retained surgical item; retained surgical sponge; systematic review; textiloma

Penetrating chest trauma with massive hemothorax by a small stone - Huang, H.-P.; Ning, C.-D.; Lu, B.; Huo, Q.-L. (Biomedical Research (India), 2017)
A patient who presented with penetrating chest trauma and massive hemothorax by a small stone required tube insertion as part of his therapy. In contrast, hemodynamically unstable patients require emergency department thoracotomy to stop the bleeding and evacuate the pleural space. This is treated with an intercoastal chest drain. The management of the traumatic hemothorax by closed thoracic drainage is an effective treatment for traumatic hemothorax induced by a small foreign body, since tube drainage can avoid the incidence of thoracotomy related complications. © 2018, Scientific Publishers of India. All rights reserved.
Keywords: Closed thoracic drainage; Emergency treatment; Foreign body; Haemothorax; Penetrating chest trauma

Huge rectovesical fistula due to long-term retention of a rectal foreign body: A case report and review of the literature - Kiyasu, Y.; Kano, N. (International Journal of Surgery Case Reports, 2017)
Introduction Most patients with foreign bodies in their rectums present to medical institutions within a few days. In this report, we describe a foreign body in the rectum in situ for 5 months that resulted in a huge rectovesical fistula 4 cm in diameter, requiring emergency laparotomy. Presentation of case A 59-year-old man, who had undergone rectal foreign body extraction via the anal canal without any complications 7 years previously, presented with abdominal pain and diarrhea. Computed tomography revealed a cup-shaped rectal foreign body and huge rectovesical fistula. We performed an emergency laparotomy. There was no contaminated ascites. The adhesion around the fistula was too stiff to be dissected. We incised the rectal wall, excised the ceramic cup-shaped foreign body, and detected a fistula approximately 4 cm in diameter. We performed sigmoid colostomy, and the incised rectal wall and the bladder wall were sutured, and the residual rectum was supposed to function as a part of the bladder. After the surgery, no severe complications occurred. The patient told us that he inserted the foreign body himself 5 months earlier, and urine had appeared in the stool in the previous month. Discussion A long-term retained rectal foreign body is very rare and could create an abnormal huge fistula between the pelvic organs because of prolonged pressure on the walls of the pelvic organs. Conclusion In patients with a long-term retained rectal foreign body, we should prepare for surgical treatment of not only the rectum but also the other pelvic organs. © 2017 The Author(s)
Keywords: Large rectovesical fistula; Pelvic surgery; Rectal foreign body; Sigmoid colostomy

Perforation of the gallbladder due to a swallowed sewing needle: Case report - Doğan, H.; çağlayan, K.; Işler, B.F.; Arslan, H.; Özüçelik, D.N. (Akademik Acil Tip Olgu Sunumlari Dergisi, 2017)
Introduction: Ingestion of foreign bodies is a common problem, particularly among the elderly, pediatric, and psychiatric populations. Most of the foreign bodies pass spontaneously and uneventfully within a week. Perforation of the gallbladder by an ingested sewing needle is extremely rare, and a single case has been reported in the literature. Case Report: We report a rare case of 30-year-old woman who accidentally ingested a sewing needle, which silently perforated the stomach and migrated to the gallbladder. Conclusion: For foreign bodies in the stomach and duodenum, the general management is usually conservative. In situations such as those in our presented case, if there is a history of foreign body ingestion and failure of its progress as well as the presence of acute abdomen, there may be an indication for surgery. © 2017 by Emergency Physicians Association of Turkey.
Keywords: Foreign bodies; Gallbladder; Perforation; Sewing needle

Radiofrequency-Based Identification Medical Device: An Evaluable Solution for Surgical Sponge Retrieval? - Lazzaro, A.; Corona, A.; Iezzi, L.; Quaresima, S.; Armisi, L.; Piccolo, I.; Medaglia, C.M.; Sbrenni, S.; Sileri, P.; Rosato, N.; Gaspari, A.L.; Di Lorenzo, N. (Surgical Innovation, 2017)
Background. A retained surgical item in patients (gossypiboma) is a persisting problem, despite consistent improvements and existing guidelines in counting instruments and sponges. Previous experiences with radiofrequency identification technology (RFID) tracking sponges show that it could represent an innovation, in order to reduce the criticism and increase the effectiveness during surgical procedures. We present an automated system that allows reduction of errors and improves safety in the operating room. Methods. The system consists of 3 antennas, surgical sponges containing RFID tags, and dedicated software applications, with Wi-Fi real-time communication between devices. The first antenna provides the initial count of gauzes; the second a real-time counting during surgery, including the sponges thrown into the kick-bucket; and the third can be used in the event of uneven sponge count. The software allows management at all stages of the process. Results. In vitro and in vivo tests were performed: the system provided excellent results in detecting sponges in patients' body. Hundred percent retained sponges were detected correctly, even when they were overlapped. No false positive or false negative was recorded. The counting procedure turned out to be more streamlined and efficient and it could save time in a standard procedure. Conclusions. The RFID system for sponge tracking was shown to be experimentally a reliable and feasible method to track sponges with a full detection accuracy in the operating room. The results indicate the system to be safe and effective with acceptable cost-effective parameters. © The Author(s) 2017.
Keywords: biomedical engineering; image-guided surgery; simulation

Transanal removal of a broken drinking glass self-inserted and retained in the rectum - Lazzari, V.; Siboni, S.; Asti, E.; Bonavina, L. (BMJ Case Reports, 2017)
Retained rectal foreign bodies are increasingly reported in current clinical practice, and there is no clear consensus in the literature as to whether transanal extraction should be performed in the emergency or in the operating room. A 47-year-old presented to the hospital for a retained drinking glass in the rectum that was broken after an attempt at self-extraction. Physical examination showed no evidence of abdominal guarding nor bleeding from the rectum; abdominal and pelvic X-rays confirmed the presence of a broken glass, 8×6 cm in size and no signs of perforation. Initial anoscopy performed in the emergency room confirmed the partial fracture of the glass. The patient was transferred to the operating room and transanal extraction was carried out under general anaesthesia without complications. © BMJ Publishing Group Ltd (unless otherwise stated in the text of the article) 2017. All rights reserved.
Keywords: Anxiety disorders (including OCD and PTSD); Endoscopy; Gastrointestinal surgery; General surgery; Sexual and gender disorders

A retained resectoscope beak: are we missing the point of surgical checklists? - Smith, S.F.; Miakhil, S.I.; Johnston, T.J.; Lockett, C. (Journal of Clinical Urology, 2017)
We present an unusual case of a retained resectoscope beak detected 10 months following transurethral resection of a bladder tumour. We describe this rare complication after transurethral surgery and present a safe method for removing a resectoscope beak from the urethra. This case prompted several improvements in our local surgical checklists to prevent such an event from recurring. It is important to check the integrity of surgical equipment in addition to counting equipment in and out during theatre; without checking, as exemplified by the resectoscope in this case, we risk missing the point. © 2016, © British Association of Urological Surgeons 2016.
Keywords: Cystoscopy; patient safety; resectoscope; retained surgical instrument; surgical checklists

Complications of dysgerminoma: Meeting the health needs of patients in conflict zones - Hayari, L.; On, E.S.; Fedorenko, A.; Sergio, S.; Zidan, J.; Solomonov, E. (BMJ Case Reports, 2017)
A symptom of prolonged conflict is the destruction of infrastructure and healthcare systems. While the need for acute trauma services is obvious in conflict zones, patients with chronic diseases also require care. This report describes the clinical course of a young teenage girl with a large mid pelvic tumour originating from the left ovary and reaching the umbilicus. She presented with acute abdominal pain and underwent surgery in a healthcare facility within a conflict zone. She was then transferred to a neighbouring country for continuing care. The tumour is malignant. After further surgery, she required chemotherapy and will need ongoing surveillance. She has since returned to her home country. It is doubtful that she will be able to access all the care she needs. We describe her healthcare needs and discuss the disastrous effects of conflict on meeting the health needs of civilian populations in war zones. © 2017 BMJ Publishing Group. All rights reserved.

Sigmoid colon perforation due to a jujube pit - Chen, J.; Lin, W. (Biomedical Research (India), 2017)
Jujube is a common fruit in Chinese diet, jujube pit is sharp but has rarely been reported to cause digestive tract perforation. Here we presented a rare case of sigmoid colon perforation by a jujube pit in an 88 year-old toothless woman. The evidence of peritoneal irritation was acquired by physical examination and CT scan. Then perforation peritonitis was diagnosed, and emergency operation was performed accordingly. The patient recovered smoothly and was discharged after 10 days of hospital stay. © 2017, Scientific Publishers of India. All rights reserved.
Keywords: Foreign body; Jujube; Perforation; Peritonitis

A rare cause for Hartmann's procedure due to biliary stent migration: A case report - Siaperas, P.; Ioannidis, A.; Skarpas, A.; Angelopoulos, A.; Drikos, I.; Karanikas, I. (International Journal of Surgery Case Reports, 2017)
Introduction Biliary stent migration (proximal or distal) occurs in 6% of all cases. The majority of these migrating stents are passing through the intestine, without causing any complications. Usually when a stent migration occurs, endoscopic retrieval is the proper treatment option, except in case of complications when surgical removal is the only treatment option. This report presents a case of a biliary stent which migrated and caused a sigmoid colon perforation. Presentation of case A 75 years old female patient presented to the emergency department with diffuse abdominal pain, nausea and vomiting. Clinical examination showed distended abdomen and signs of peritoneal irritation. CT scan of the abdomen revealed free gas and fluid in the left iliac fossa, as well as a foreign body penetrating the sigmoid colon. Emergency laparotomy was performed. A plastic stent was found perforating the sigmoid colon through a diverticulum. The rest of the sigmoid colon was intact presenting only uncomplicated diverticula. Hartmann's operation was performed, involving the diseased segment, together with part of the descending colon due to profound diverticulosis. Patient's post-surgical course was uneventful and was discharged on postoperative day 10. Discussion Migration of a biliary stent can cause life-threatening complications such as perforation of the intestine and peritonitis. The migration of the stent from the biliary tree may be mostly asymptomatic except in cases of intestinal perforation that immediate surgery is the proper treatment option. On the other hand, even in cases of benign lesions of the bile duct, the stent should be removed immediately after dislocation in order to reduce the risk of secondary complications such as obstruction, infection or perforation. Conclusion In cases of non-complicated stent migration endoscopic retrieval is the indicated treatment. In patients who suffer serious complications due to stent dislocation, emergency surgery may be the proper treatment option. © 2017 The Author(s)
Keywords: Biliary stents; Hartmann's procedure; Intestinal perforation; Stent migration

Efficacy of oxidized regenerated cellulose, SurgiGuard®, in Porcine surgery - Kim, S.H.; Kim, S.H.; Yoon, H.S.; Kim, H.K.; Kim, K.S. (Yonsei Medical Journal, 2017)
Purpose: Adequate hemostasis is important for postoperative outcomes of abdominal surgery. This study evaluated the hemostatic effects and accompanying histopathological changes of a novel oxidized regenerated cellulose, SurgiGuard®, during abdominal surgery. Materials and Methods: Ten pigs underwent wedge resection of the spleen (1×1 cm) and liver (1.5×1.5 cm). The resected surface was covered with Surgicel® fabric or fibril type (Group A) or SurgiGuard® fabric or fibril type (Group B). Surgicel® and SurgiGuard® were randomized for attachment to the resected surface by fabric type (n=5) or fibril type (n=5). Blood loss was measured 5, 7, and 9 min after resection. Pigs were necropsied 6 weeks postoperatively to evaluate gross and histopathological changes. Results: There was no significant difference in total blood loss between groups [spleen fabric: Group A vs. Group B, 4.38 g (2.74-6.43) vs. 3.41 g (2.46-4.65), p=0.436; spleen fibril: Group A vs. Group B, 3.44 g (2.82-6.07) vs. 3.60 g (2.03-6.09), p=0.971; liver fabric: Group A vs. Group B, 4.51 g (2.67-10.61) vs. 6.93 g (3.09-9.95), p=0.796; liver fibril: Group A vs. Group B, 3.32 g (2.50-8.78) vs. 3.70 g (2.32-5.84), p=0.971]. Histopathological analysis revealed no significant difference in toxicities related to Surgicel® or Surgi-Guard® [inflammation, fibrosis, foreign bodies, and hemorrhage (spleen: p=0.333, 0.127, 0.751, and 1.000; liver: p=0.155, 0.751, 1.000, and 1.000, respectively)]. Conclusion: SurgiGuard® is as effective and non-toxic as Surgicel® in achieving hemostasis after porcine abdominal surgery. © Yonsei University College of Medicine 2017.
Keywords: Animal model; Blood loss; Hemostatics; Histopathology; Oxidized regenerated cellulose

Liver abscess and portal vein thrombosis due to ileal diverticulitis mediated by barium fluoroscopy - Kubo, H.; Asai, G.; Haraguchi, K.; Shibahara, Y.; Kihara, T.; Yamakawa, G.; Kira, F.; Higashi, H.; Morishita, S.; Fujie, H.; Matsumoto, M.; Shimura, W. (Internal Medicine, 2017)
We report a case of liver abscess and portal vein thrombosis, which occurred due to diverticulitis at the terminal ileum in a 59-year-old man. The patient underwent a barium fluoroscopic examination 1 month before presenting to our hospital. He also showed liver dysfunction due to thrombosis at the superior mesenteric and portal veins. His inflammation gradually subsided after the initiation of treatment, but the recovery was not sufficient. Thus, surgery was performed. The patient condition improved after surgery and he was discharged. Barium examinations are relatively safe, but can sometimes cause severe adverse effects in patients with certain risk factors, and an appropriate diagnosis and treatment are necessary when symptoms appear. © 2017 The Japanese Society of Internal Medicine.
Keywords: Barium; Diverticulitis; Liver abscess; Portal vein thrombosis; Superior mesenteric vein thrombosis

DEBS - a unification theory for dry eye and blepharitis - Rynerson, J.M.; Perry, H.D. (Clinical Ophthalmology, 2016)
For many years, blepharitis and dry eye disease have been thought to be two distinct diseases, and evaporative dry eye distinct from aqueous insufficiency. In this treatise, we propose a new way of looking at dry eye, both evaporative and insufficiency, as the natural sequelae of decades of chronic blepharitis. Dry eye is simply the late form and late manifestation of one disease, blepharitis. We suggest the use of a new term in describing this one chronic disease, namely dry eye blepharitis syndrome (DEBS). Bacteria colonize the lid margin within a structure known as a biofilm. The biofilm allows for population densities that initiate quorum-sensing gene activation. These newly activated gene products consist of inflammatory virulence factors, such as exotoxins, cytolytic toxins, and super-antigens, which are then present for the rest of the patient’s life. The biofilm never goes away; it only thickens with age, producing increasing quantities of bacterial virulence factors, and thus, increasing inflammation. These virulence factors are likely the culprits that first cause follicular inflammation, then meibomian gland dysfunction, aqueous insufficiency, and finally, after many decades, lid destruction. We suggest that there are four stages of DEBS which correlate with the clinical manifestations of folliculitis, meibomitis, lacrimalitis, and finally lid structure damage evidenced by entropion, ectropion, and floppy eyelid syndrome. When one fully understands the structure and location of the glands within the lid, it becomes easy to understand this staged disease process. The longer a gland can resist the relentless encroachment of the invading biofilm, the longer it can maintain normal function. The stages depend purely on anatomy and years of biofilm presence. Dry eye now becomes a very easy disease to understand. We feel that dry eye should be treated and prevented by early and routine biofilm removal through electromechanical lid margin debridement. © 2016 Rynerson and Perry.
Keywords: Aqueous insufficiency; Biofilm; Demodex; Meibomian gland disease; MGD; Quorum-sensing gene activation

Clinical Issues—December 2016 - Spruce, L.; Wood, A. (AORN Journal, 2016)
Head coverings Key words: head cover, bouffant, skull cap, hair, scalp. Skin preps Key words: skin preps, antiseptics, cesarean delivery, surgical site infections, abdomen. Pediatric surgical counts Key words: pediatrics, counts, surgical, retained surgical items, policy. Sterile set up Key words: sterile table, sterile set up, covering, monitoring, contamination. Surgical hand antisepsis Key words: surgical hand rub, application, surgical scrub, scrubbed areas. © 2016 AORN, Inc

A Very Unusual Cause of Hemoptysis - Loarte, P.; Holguín, G.; Cohen, R. (International Journal of Angiology, 2016)
The use of Lucite balls or spheres played a role in the management of tuberculosis during the first decade of the 20th century. Several complications have been reported with the use of this surgical technique, but are rarely seen nowadays. The availability of effective oral regimens has forced to abandon this approach. Calcification of these spheres within the lung cavity produced a series of late complications result of the migration of these foreign bodies to adjacent structures, causing erosion of blood vessels and nerves. Herein, we present a case where the aforementioned complication caused significant bleeding with hemodynamic instability. The source of the profuse hemoptysis was identified and was resolved with the combined use of noninvasive approaches such as bronchoscopy and angiographic embolization. Copyright © 2016 by Thieme Medical Publishers, Inc.
Keywords: embolization; hemoptysis; Lucite spheres; tuberculosis

99mTc-Labeled ubiquicidin accumulation in a retained surgical gauze - Ghahremani, S.; Sadeghi, R.; Kakhki, V.R.D.; Massoudi, T.; Aryana, K. (Clinical Nuclear Medicine, 2016)
A 31-year-old woman underwent99mTc-labeled UBI scanning for diagnosis of possible prosthesis infection evaluation in our department. The scan showed an area of increased tracer uptake in the mid-lateral portion of the left thigh. This was proven to be due to a retained surgical gauze in her left thigh. Copyright © 2016 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: Foreign body; Hip; Scintigraphy; UBI; Ubiquicidin

Laparoscopic resection and intracorporeal anastomosis of perforated small bowel caused by fish bone ingestion - Dural, A.C.; Çelik, M.F.; Yiğitbaş, H.; Akarsu, C.; Doğan, M.; Alış, H. (Ulusal Travma ve Acil Cerrahi Dergisi, 2016)
Presently described is case of a 52-year-old man who was admitted to the emergency department with 3-day history of epigastric pain. Abdominal examination revealed diffuse tenderness and muscle guarding. Plain abdominal X-ray showed free subdiaphragmatic air. The patient underwent diagnostic laparoscopy with presumptive diagnosis of peptic ulcer perforation. Laparoscopy showed several inflamed, edematous jejunal loops with proximal obstruction and perforation by an impacted fish bone. Completely intracorporeal resection and anastomosis using laparoscopic linear stapler was performed and segment of resected bowel was removed through trocar site. Postoperative period was uneventful, and the patient was discharged on fourth day. © 2016 TJTES.
Keywords: Fish bone; Foreign body ingestion; Perforation; Small bowel

Endoscopic removal of a duodenal-perforating leg of glasses with dormia basket - Wang, L.; Wen, W.; Huang, J.; Hu, W.; Zhou, R.; Li, X.; Wang, X. (Case Reports in Gastroenterology, 2016)
Ingestion of foreign bodies is common in clinical practice. Most ingested foreign bodies will pass through the gastrointestinal (GI) tract without any problems. While GI tract injury due to the ingested foreign body such as a toothpick, a fishbone, a date pit, or a chicken bone, is common, duodenal perforation is rare. In this report, our experience with this rare entity is shared. We present a 38-year-old male patient with GI tract perforation in the bulbus of the duodenum due to a leg of glasses. The patient was admitted to our hospital with severe abdominal pain. Right upper quadrant tenderness was detected at physical examination, and leukocytosis on the laboratory test results. Plain X-ray and computerized tomography showed an ingested foreign body in the bulbus of the duodenum. A leg of glasses perforating the duodenum was removed with endoscopy. The patient was managed nonoperatively, and discharged without any complications on the eighth day after endoscopy. Endoscopic removal and nonoperative management may be feasible in carefully selected patients with duodenal-perforating foreign bodies. © 2016 The Author(s) Published by S. Karger AG, Basel.
Keywords: Duodenal perforation; Endoscopic removal; Foreign body

Successful treatment through single-port laparoscopy for a gastrojejunal fistula caused by an accidentally ingested toothpick - Chen, C.-C.; Ting, C.-T.; Hsu, Y.-H.; Chen, P.-C.; Lee, M.-D.; Liu, M.-H. (Formosan Journal of Surgery, 2016)
The causes of gastrojejunal fistula are unclear. The ingestion of foreign bodies should be considered. We report the case of a 46-year-old man who visited the emergency department with a 3-day history of dysuria, left upper abdominal pain, left flank soreness, and high fever. Physical examination revealed tenderness in the left upper abdominal quadrant and left costovertebral angle. Abdominal computed tomography and gastroduodenoscopy were inconclusive for gastrojejunal fistula with regional peritonitis caused by an ingested toothpick. A 7-cm toothpick was successfully removed through single-port laparoscopy. Toothpick ingestion is a medical emergency because it can lead to acute abdomen and gut perforation. Single-port laparoscopy is a minimally invasive strategy for treating this condition. © 2016
Keywords: laparoscopy; peritonitis; single-port; toothpick

An unusual respiratory tract foreign body: A case report of pediatric broncholithiasis - Feng, S.; Liu, D.; Huang, Z.; Zhong, J.; Zhong, J. (International Journal of Pediatric Otorhinolaryngology Extra, 2016)
Tracheobronchial foreign body aspiration is one of the most life-threatening diseases in children. Its symptom is non-specific sometimes; therefore the distinction with some similar clinical presentation pulmonary disease should be performed. Here, we reported a 5-year-old girl who was misdiagnosed with foreign body aspiration twice based on the broncho-obstructive symptom and radiologic finding. Finally, the diagnosis of broncholithiasis was confirmed by finding broncholiths in the respiratory tract through bronchoscopy. It is replied that bronchoscopy should be performed in the children with unexplained airway obstruction symptom. Furthermore, it is the first report about the broncholiths located at the upper main trachea. © 2016 Elsevier Ltd
Keywords: Broncholithiasis; Bronchoscopy; Foreign body

Left subclavian artery-esophageal fistula induced by a paper star: A case report - Lin, C.-S.; Lin, C.-W. (BioMedicine (Netherlands), 2016)
A subclavian artery-esophageal fistula usually occurs on the right side of an aberrant subclavian artery. It also rarely appears in the site between a non-aberrant subclavian artery and the esophagus due to the ingestion of a foreign body. Upper gastrointestinal bleeding in the case of a subclavian artery-esophageal fistula is rare but often fatal. Here, we report on a 62-year-old male patient with a left subclavian artery-esophageal fistula complicated by hemorrhagic shock. He swallowed a foreign body at a birthday party. An upper gastrointestinal endoscopy indicated a paper star lodged at 20 cm from the incisors, inducing a kissing esophageal ulcer around the esophageal sphincter. One month later, he suffered an unusually strong episode of hematemesis. Subsequently, a computed tomography angiography was performed and demonstrated a left subclavian artery-esophageal fistula. Finally, the fistula induced by the ingestion of a paper star was successfully treated by endovascular stent grafting. © Author(s) 2016.
Keywords: Gastrointestinal bleeding; Hemorrhagic shock; Subclavian artery-esophageal fistula

Correlation between word recognition score and intracochlear new bone and fibrous tissue after cochlear implantation in the human - Kamakura, T.; Nadol, J.B., Jr. (Hearing Research, 2016)
Cochlear implantation is an effective, established procedure for patients with profound deafness. Although implant electrodes have been considered as biocompatible prostheses, surgical insertion of the electrode induces various changes within the cochlea. Immediate changes include insertional trauma to the cochlea. Delayed changes include a tissue response consisting of inflammation, fibrosis and neo-osteogenesis induced by trauma and an immunologic reaction to a foreign body. The goal of this study was to evaluate the effect of these delayed changes on the word recognition scores achieved post-operatively. Seventeen temporal bones from patients who in life had undergone cochlear implantation were prepared for light microscopy. We digitally calculated the volume of fibrous tissue and new bone within the cochlea using Amira® three-dimensional reconstruction software and assessed the correlations of various clinical and histologic factors. The postoperative CNC word score was positively correlated with total spiral ganglion cell count. Fibrous tissue and new bone were found within the cochlea of all seventeen specimens. The postoperative CNC word score was negatively correlated with the % volume of new bone within the scala tympani, scala media/vestibuli and the cochlea, but not with the % volume of fibrous tissue. The % volume of new bone in the scala media/vestibuli was positively correlated with the degree of intracochlear insertional trauma, especially trauma to the basilar membrane. Our results revealed that the % volume of new bone as well as residual total spiral ganglion cell count are important factors influencing post-implant hearing performance. New bone formation may be reduced by limiting insertional trauma and increasing the biocompatibility of the electrodes. © 2016 Elsevier B.V.
Keywords: Cochlear implant; Fibrous tissue; Human inner ear; Insertional trauma; New bone; Word recognition score

De Novo Belatacept in a Human Immunodeficiency Virus–Positive Kidney Transplant Recipient - Cohen, E.A.; Mulligan, D.; Kulkarni, S.; Tichy, E.M. (American Journal of Transplantation, 2016)
Benefits of belatacept-based immunosuppressive regimens in human immunodeficiency virus (HIV)–positive renal transplant recipients include avoidance of drug interactions between calcineurin inhibitors and highly active antiretroviral agents and decreased likelihood or severity of nonimmune toxicities such as new-onset diabetes after transplant, hyperlipidemia and hypertension. We report a successful case of de novo belatacept at >18 mo from transplant in an HIV-positive black man aged 50 years who received his first transplant from a living related kidney donor. To our knowledge, this case is the first reported of belatacept use in an HIV-positive renal transplant recipient. © Copyright 2016 The American Society of Transplantation and the American Society of Transplant Surgeons
Keywords: clinical research/practice; fusion proteins and monoclonal antibodies: belatacept; immunosuppressant; immunosuppression/immune modulation; infection and infectious agents; kidney transplantation/nephrology; viral: human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS)

Unilateral recurrent anterior uveitis as the presenting sign of bladder carcinoma - Şatırtav, G.; Donbaloğlu, M.; Oltulu, R.; Oltulu, P.; Kerimoğlu, H.; Özkağnıcı, A. (Turk Oftalmoloiji Dergisi, 2016)
A 79-year-old male patient was followed for unilateral uveitis with 3 attacks in 10 months, despite initial improvement with steroid therapy. The patient had visual acuity (VA) of counting fingers in right eye, hypopyon and vitritis with no chorioretinal lesions. The left eye was normal. The patient was evaluated for intraocular foreign body, intraocular lymphoma and associated systemic disease and malignancy. Computed tomography of the abdomen showed a mass in the bladder. Biopsy confirmed bladder carcinoma. After resection of the mass, intraocular inflammation improved completely and no attack was noted in the follow-up. In his last examination, two years after the operation, VA was light perception; seclusio pupilla and mature cataracts were seen on biomicroscopy. There was no sign of vitritis on ocular ultrasonography. Evidence is discussed that suggests a link and potential etiology between refractory uveitis with hypopyon and bladder carcinoma. This is the first case of unilateral recurrent uveitis with hypopyon as the initial presenting sign of bladder carcinoma. © 2016, Turkish Ophthalmology Society. All rights reserved.
Keywords: Anterior uveitis; Bladder carcinoma; Paraneoplastic syndrome

Clinical Issues—July 2016 - Burlingame, B.L. (AORN Journal, 2016)
Wearing ring dosimeters Key words: dosimeter, ring dosimeters, finger dosimeters. Reporting a retained surgical item (RSI) Key words: reportable event, retained surgical item, RSI, retained foreign object, counts. Definition of an implant Key words: implant, implant documentation. Determining whether RN first assistants (RNFAs) must maintain CNOR certification to practice Key words: CNOR, CRNFA, RNFA, first assistant, RN first assistant. Definition of personal protective equipment (PPE) Key words: personal protective equipment, PPE, surgical attire, removing PPE. © 2016 AORN, Inc

Guideline Implementation: Prevention of Retained Surgical Items - Fencl, J.L. (AORN Journal, 2016)
A surgical item unintentionally retained in a patient after an operative or other invasive procedure is a serious, preventable medical error with the potential to cause the patient great harm. Perioperative RNs play a key role in preventing retained surgical items (RSIs). The updated AORN “Guideline for prevention of retained surgical items” provides guidance for implementing a consistent, multidisciplinary approach to RSI prevention; accounting for surgical items; preventing retention of device fragments; reconciling count discrepancies; and using adjunct technologies to supplement manual count procedures. This article focuses on key points of the guideline to help perioperative personnel provide optimal care during a procedure. Key points addressed include taking responsibility for RSI prevention as a team; minimizing distractions, noise, and interruptions during counts; using consistent counting methods; reconciling discrepancies; and participating in performance-improvement activities. Perioperative RNs should review the complete guideline for additional information and for guidance in writing and updating policies and procedures. © 2016 AORN, Inc
Keywords: count reconciliation; incorrect count; never event; retained surgical item

Surgical count process for prevention of retained surgical items: An integrative review - Freitas, P.S.; Silveira, R.C.C.P.; Clark, A.M.; Galvão, C.M. (Journal of Clinical Nursing, 2016)
Aims and objectives: To analyse the evidence reported in the literature concerning the surgical count process for surgical sponges, surgical instruments and sharps and to identify knowledge gaps for future research on the surgical count process. Background: The surgical count process stands out among the practices advocated by the World Health Organization to ensure surgical safety. The literature indicates that this practice should be performed in all surgical processes. However, surgical items are still retained. Design: Integrative review. Methods: The literature search was conducted in the PubMed, CINAHL and LILACS databases and included studies on the surgical count process published in English, Spanish and Portuguese from January 2003-December 2013. Results: A total of 28 primary studies were included in the sample, allowing the knowledge on the surgical count process to be summarised and grouped into three categories: risk factors for retained surgical items, how the surgical count process should be performed in the intraoperative period and the accompanying technologies that collaborate to improving the manual count process. Conclusions: The correct implementation of the surgical count process by the perioperative nurse may contribute to preventing retained surgical items, thereby improving surgical patient safety. Relevance to clinical practice: Nurses can use this review to assist in decision-making directed towards preparing, updating and implementing a reliable system for the surgical count process based on recent evidence because the perioperative nurse plays a key role in the implementation of this practice in health services. © 2016 John Wiley & Sons Ltd.
Keywords: Brazil; Evidence-based practice; Integrative review; Patient safety; Perioperative nursing; Retained surgical items; Sharps; Surgical count process; Surgical instruments; Surgical sponges

(1→3)-β-D-glucan and galactomannan for differentiating chemical “Black particles” and fungal particles inside peritoneal dialysis tubing - Leelahavanichkul, A.; Pongpirul, K.; Thongbor, N.; Worasilchai, N.; Petphuak, K.; Thongsawang, B.; Towannang, P.; Lorvinitnun, P.; Sukhontasing, K.; Katavetin, P.; Praditpornsilpa, K.; Eiam-Ong, S.; et al. (Peritoneal Dialysis International, 2016)
Background: Aseptic, sheet-like foreign bodies observed inside Tenckhoff(TK) catheter lumens (referred to as “black particles”) are, on gross morphology, hardly distinguishable from fungal colonization because these contaminants adhere tightly to the catheter. Detection of fungal cell wall components using (1→3)-β-d-glucan (BG) and galactomannan index (GMI) might be an alternative method for differentiating the particles. Methods: Foreign particles retrieved from TK catheters in 19 peritoneal dialysis patients were examined microscopically and cultured for fungi and bacteria. Simultaneously, a Fungitell test (Associates of Cape Cod, Falmouth, MA, USA) and a Platelia Aspergillus ELISA assay (Bio-Rad Laboratories, Marnes-La-Coquette, France) were used to test the spent dialysate for BG and GMI respectively. Results: Of the 19 patients, 9 had aseptic black particles and 10 had fungal particles in their tubing. The fungal particles looked grainy, were tightly bound to the catheter, and appeared more “colorful” than the black particles, which looked sheet-like and could easily be removed by milking the tubing. Compared with effluent from patients having aseptic particles, effluent from patients with fungal particles had significantly higher levels of BG (501 ± 70 pg/mL vs. 46 ± 10 pg/mL) and GMI (10.98 ± 2.17 vs. 0.25 ± 0.05). Most of the fungi that formed colonies inside the catheter lumen were molds not usually found in clinical practice, but likely from water or soil, suggesting environmental contamination. Interestingly, in all 10 patients with fungal colonization, visualization of black particles preceded a peritonitis episode and TK catheter removal by approximately 1-3 weeks; in patients with aseptic particles, a 17-week onset to peritonitis was observed. Conclusions: In all patients with particle-coated peritoneal dialysis tubing, spent dialysate should be screened for BG and GMI. Manipulation of the TK catheter by squeezing, hard flushing, or even brushing to dislodge black particles should be avoided. Replacement of the TK catheter should be suspended until a cause for the particles is determined. © 2016 International Society for Peritoneal Dialysis.
Keywords: (1→3)-β-d-glucan; Black particles; CAPD; Fungal colonization; Fungal peritonitis; Galactomannan

Pediatric open-globe injuries: clinical characteristics and factors associated with poor visual and anatomical success - Sul, S.; Gurelik, G.; Korkmaz, S.; Ozdek, S.; Hasanreisoglu, B. (Graefe's Archive for Clinical and Experimental Ophthalmology, 2016)
Purpose: We determine the clinical characteristics, visual and anatomical outcomes, and factors associated with poor visual outcome and anatomical success in pediatric open-globe injuries (OGI). Methods: The records of patients aged 17 years and younger who had undergone surgical intervention after OGI between January 2000 and June 2010 were reviewed retrospectively. Results: In total, 182 patients were enrolled in the study (70.9 % males, 29.1 % females; mean age: 8.6 ± 4.5 years [range 1–17 years]). Injuries occurred mostly at home (45.1 %). Objects most often causing the ocular trauma were sharp objects (74.1 %). Over one-third of the eyes (39.7 %) had final visual acuities of 20/200 or better. Anatomical success was achieved in 76.9 % of eyes. Time between primary globe repair and secondary surgical intervention was 61.4 ± 144 days. Visual outcomes were poor in eyes with initial visual acuity less than for counting fingers, retinal detachment, proliferative vitreoretinopathy, and endophthalmitis. Anatomical success rates were low with retinal detachment. Conclusion: Visual outcomes seem to be poor in more than half of the patients despite advanced microsurgical techniques. © 2015, Springer-Verlag Berlin Heidelberg.
Keywords: Endophthalmitis; Open globe injury; Retinal detachment

Case of unrecognised food bone ingestion with dual site intestinal perforations - Coyte, A.; Aïssa, J.T.; Koh, H.C.; Mackay, G. (BMJ Case Reports, 2016)
Food bone perforation of the bowel is a relatively rare diagnosis. Its presentation is non-specific and often misdiagnosed. We present a case where a food bone perforation in both the large and small bowel was diagnosed on CT scan. A successful outcome was achieved with surgical treatment. © 2016 BMJ Publishing Group. All rights reserved.

Small bowel perforation due to glass particle in a patient without history of swallowed foreign body - Kaymak, Ş.; Şenocak, R.; Kılbaş, Z. (Journal of Clinical and Analytical Medicine, 2016)

The pathogenesis of implant-related reactive lesions: A clinical, histologic and polarized light microscopy study - Halperin-Sternfeld, M.; Sabo, E.; Akrish, S. (Journal of Periodontology, 2016)
Background: Peri-implant soft tissue reactive lesions (I-RLs) may jeopardize implant success and survival. To the best of the authors' knowledge, its pathogenesis is unknown. The objective of this study is to conduct a clinicopathologic and polarized light microscopy (PLM) analysis of 14 new I-RLs and compare them with comparable tooth-associated cases (T-RLs) to better understand I-RL pathogenesis. Methods: Fifty-eight new cases of I-RL and T-RL were retrieved from the pathology department archives of Rambam Health Care Campus, Haifa, Israel. Retrospective analysis of histopathologic and clinical features was conducted, documented, and then compared for: 1) I-RL (n = 14), 2) peri-implant pyogenic granuloma (I-PG) (n = 5), 3) peri-implant peripheral giant cell granuloma (I-PGCG) (n = 9), 4) T-RL (n = 44), 5) tooth-associated pyogenic granuloma (T-PG) (n = 21), and 6) tooth-associated peripheral giant cell granuloma (T-PGCG) (n = 23). Presence of foreign bodies was assessed using PLM. Results: Foreign bodies were found more commonly in I-RLs (n = 13/14; 93%) when compared with T-RLs (n = 18/44; 41%), which was a statistically significant difference (P = 0.01) with an odds ratio of 7.9. Microscopically, I-PGCG was associated with: 1) lower multinucleated giant cell count (P = 0.04); 2) lower density of mesenchymal cells (P = 0.05); and 3) more diffuse, nonlobulated stromal morphology (P = 0.001). Clinically, I-RLs were found in patients who were older, and all cases were located in the posterior region: mandible (n = 12/14; 86%) and maxilla (n = 2/14; 14%). Conclusions: In cases of implant failure, implantation of foreign bodies may play a role with subsequent development of I-PG and I-PGCG-like lesions. Clinicians should be aware of this risk so they can implement measures to minimize adverse implant outcomes.
Keywords: Dental implants; Foreign-body reaction; Granuloma giant cell; Granuloma pyogenic

Surviving penetrating brainstem injury by bamboo sticks: Rare case reports and a brief review of literature - Mzimbiri, J.M.; Li, J.; Xia, Y.; Yuan, J.; Liu, J.; Liu, Q. (Neurosurgery, 2016)
BACKGROUND AND IMPORTANCE: Chopsticks are common utensils used in many Asian cultures. However, they sometimes can be used as weapons or can cause accidents, particularly in children. Penetrating transorbital/transpharyngeal intracranial injuries with bamboo sticks are peculiar accidents and are relatively rare. Because of their rarity, the management of such injuries is often complex. We discuss 3 cases of penetration of the brainstem by bamboo sticks, 1 case through the foramen magnum, which, to the best of our knowledge, is the first reported case of such an injury. CLINICAL PRESENTATION: The case of a 50-year-old man who was stabbed with a pair of chopsticks in his left eye is presented. The chopsticks passed through the cavernous sinus, and the patient sustained superior orbital fissure syndrome. The other 2 cases were those of a 4-year-old girl having a similar pattern but different mechanism of injury and a 2-year-old boy who sustained transpharyngeal intracranial injury via the foramen magnum. Computed tomography, magnetic resonance imaging, and computed tomographic angiography (CTA) are the key imaging modalities frequently used to determine the course and extent of brain injury. CONCLUSION: Early surgical exploration by a multidisciplinary team approach is essential for attaining a favorable outcome. All cases demonstrated good postoperative recovery and were successfully managed by removing the foreign body through its trajectory. We discuss and briefly review the literature on patterns, complications, and management issues of these less common injuries. ABBREVIATIONS: CN, cranial nerve CTA, computed tomographic angiography GCS, Glasgow Coma Scale PHI, penetrating head injury SOF, superior orbital fissure. © 2016 by the Congress of Neurological Surgeons.
Keywords: Bamboo; Brainstem; Chopstick; Foramen magnum; Superior orbital fissure syndrome; Transorbital; Transpharyngeal

A case report - Kim, S.C.; Kim, S.H.; Kim, S.J. (Medicine (United States), 2016)
Rapunzel syndrome is very rare gastric foreign bodies that occur in children. It is a severe condition of a gastric trichobezoar with a long tail that passes into the small intestine. Here, we present the case of an 8-year-old girl with Rapunzel syndrome due to a very large (7 × 7 × 30cm) gastric trichobezoar. The patient had trichotillomania and trichophagia for 1 year prior to presentation. Ideally, small bezoars are removed through a minimally invasive method, such as endoscopic fragmentation. However, large trichobezoars, including those in Rapunzel syndrome, can only be managed with open surgical extraction, despite the large scars that may result. We report a case of Rapunzel syndrome with a large bezoar that was surgically removed after it was endoscopically cauterized with argon plasma. Endoscopic precutting was used to effectively reduce the size of the bezoar. © 2016 Wolters Kluwer Health, Inc.

Host inflammatory response to polypropylene implants: Insights from a quantitative immunohistochemical and birefringence analysis in a rat subcutaneous model - Prudente, A.; Fávaro, W.J.; Filho, P.L.; Riccetto, C.L.Z. (International Braz J Urol, 2016)
Objectives: To describe acute and sub acute aspects of histological and immunohistochemical response to PP implant in a rat subcutaneous model based on objective methods. Materials and Methods: Thirty rats had a PP mesh subcutaneously implanted and the same dissection on the other side of abdomen but without mesh (sham). The animals were euthanized after 4 and 30 days. Six slides were prepared using the tissue removed: one stained with hematoxylin-eosin (inflammation assessment); one unstained (birefringence evaluation) and four slides for immunohistochemical processing: IL-1 and TNF-α (pro-inflammatory cytokines), MMP-2 (collagen metabolism) and CD-31 (angiogenesis). The area of inflammation, the birefringence index, the area of immunoreactivity and the number of vessels were objectively measured. Results: A larger area of inflammatory reaction was observed in PP compared to sham on the 4th and on the 30th day (p=0.0002). After 4 days, PP presented higher TNF (p=0.0001) immunoreactivity than sham and no differences were observed in MMP- 2 (p=0.06) and IL-1 (p=0.08). After 30 days, a reduction of IL-1 (p=0.010) and TNF (p=0.016) for PP and of IL-1 (p=0.010) for sham were observed. Moreover, area of MMP-2 immunoreactivity decreased over time for PP group (p=0.018). Birefringence index and vessel counting showed no differences between PP and sham (p=0.27 and p=0.58, respectively). Conclusions: The implantation of monofilament and macroporous polypropylene in the subcutaneous of rats resulted in increased inflammatory activity and higher TNF production in the early post implant phase. After 30 days, PP has similar cytokines immunoreactivity, vessel density and extracellular matrix organization.
Keywords: Foreign body reaction; Graft versus host reaction; Immunohistochemistry; Pelvic organ prolapse; Polypropylenes; Urinary incontinence

Weekly injections of Hylan G-F 20 delay cartilage degeneration in partial meniscectomized rat knees - Yanagisawa, K.; Muneta, T.; Ozeki, N.; Nakagawa, Y.; Udo, M.; Saito, R.; Koga, H.; Tsuji, K.; Sekiya, I. (BMC Musculoskeletal Disorders, 2016)
Background: Cross-linked hyaluronan - also called Hylan G-F 20 - is a medical device developed to treat osteoarthritis of the knee. However, it is still controversial whether Hylan G-F 20 has a cartilage protective effect in trauma-induced osteoarthritis. We investigated whether Hylan G-F 20 delayed osteoarthritis progression in a partial meniscectomized rat model. Methods: Lewis rats were used for the experiments. The anterior medial meniscus was resected at the level of the medial collateral ligament in both knees. From 1 week after the surgery, 50 μl of Hylan G-F 20 was injected weekly into the left knee and phosphate buffered saline was injected into the right knee. Cartilage was evaluated for macroscopic findings, histology with safranin-o, and expression of type II collagen at 2, 4, and 8 weeks. Synovitis was also evaluated, and immunohistochemical analysis was performed for ED1. Results: Macroscopic findings demonstrated that India ink positive area, representing fibrillated cartilage, was significantly smaller in the Hylan G-F 20 group than in the control group at 2, 4, and 8 weeks (n = 5). There were no significant differences in osteophyte score between the Hylan G-F 20 group and the control group at 2, 4, and 8 weeks. Histologically, the cartilage in the medial tibial plateau was destroyed at 8 weeks in the control group, while type II collagen expression was still observed at 8 weeks in the Hylan G-F 20 group. OARSI score for cartilage histology was significantly lower in the Hylan G-F 20 group than in the control group at 4 and 8 weeks (n = 5). There were no significant differences in synovial cell number or modified synovitis score between the Hylan G-F 20 group and the control group at 2, 4, and 8 weeks (n = 5). In the Hylan G-F 20 group, foreign bodies surrounded by ED1 positive macrophages were observed in the synovium. Conclusion: Weekly injections of Hylan G-F 20 starting 1 week after surgery delayed cartilage degeneration after meniscectomy in a rat model. Synovitis induced by meniscectomy was not alleviated by Hylan G-F 20. Insoluble gels were observed in the synovium after the Hylan G-F 20 injection. © 2016 Yanagisawa et al.
Keywords: Hyaluronan; Hylan G-F 20; Osteoarthritis; Partial meniscectomy; Rat

In Vivo Microcomputed Tomography of Nanocrystal-Doped Tissue Engineered Scaffolds - Forton, S.M.; Latourette, M.T.; Parys, M.; Kiupel, M.; Shahriari, D.; Sakamoto, J.S.; Shapiro, E.M. (ACS Biomaterials Science and Engineering, 2016)
Tissue engineered scaffolds (TES) hold promise for improving the outcome of cell-based therapeutic strategies for a variety of biomedical scenarios, including musculoskeletal injuries, soft tissue repair, and spinal cord injury. Key to TES research and development, and clinical use, is the ability to longitudinally monitor TES location, orientation, integrity, and microstructure following implantation. Here, we describe a strategy for using microcomputed tomography (microCT) to visualize TES following implantation into mice. TES were doped with highly radiopaque gadolinium oxide nanocrystals and were implanted into the hind limbs of mice. Mice underwent serial microCT over 23 weeks. TES were clearly visible over the entire time course. Alginate scaffolds underwent a 20% volume reduction over the first 6 weeks, stabilizing over the next 17 weeks. Agarose scaffold volumes were unchanged. TES attenuation was also unchanged over the entire time course, indicating a lack of nanocrystal dissolution or leakage. Histology at the implant site showed the presence of very mild inflammation, typical for a mild foreign body reaction. Blood work indicated marked elevation in liver enzymes, and hematology measured significant reduction in white blood cell counts. While extrapolation of the X-ray induced effects on hematopoiesis in these mice to humans is not straightforward, clearly this is an area for careful monitoring. Taken together, these data lend strong support that doping TES with radiopaque nanocrystals and performing microCT imaging, represents a possible strategy for enabling serial in vivo monitoring of TES. © 2016 American Chemical Society.
Keywords: agarose; alginate; biomedical imaging; bismuth; gadolinium oxide; Hounsfield units; microCT; tissue engineered scaffold; X-ray

Management of ureteral stenting for postrenal failure during pregnancy after ureteral reimplantation: A case report - Yoneoka, Y.; Kaku, S.; Tsuji, S.; Yamashita, H.; Inoue, T.; Kimura, F.; Murakami, T. (BMC Pregnancy and Childbirth, 2016)
Background: Vesicoureteral reflux is thought to predispose to urinary tract infection and renal scarring, and ureteral reimplantation in childhood remains the gold standard for its treatment. It has been reported that the risk of postrenal failure during pregnancy is increased among women with Politano-Leadbetter ureteral reimplantation. In previous case reports on patients with progressive hydronephrosis and renal failure during pregnancy after ureteral reimplantation, percutaneous nephrostomy was always required, so there has been no information about the clinical management of such patients by ureteral stenting. Here we report a patient with a history of bilateral ureteral reimplantation, in whom severe hydronephrosis during pregnancy was managed with ureteral stents. Case presentation: A primigravida with severe hydronephrosis was referred to us at 29 weeks of gestation. Bilateral Politano-Leadbetter ureteral reimplantation had been performed at the age of 3 years. She was hospitalized immediately, and bilateral ureteral stents were successfully inserted. Post-obstructive diuresis occurred after the stents were placed. Urinary tract infection developed after removal of the urethral catheter 1 week later, but responded to antibiotic therapy and catheter replacement. Labor was induced at 39 weeks of gestation, with vaginal delivery of a healthy male infant. Both stents were found to have spontaneously migrated into the urethra after delivery. Repeat stenting under spinal anesthesia was required to improve postpartum symptoms of back pain and fever. Right distal ureteral obstruction persisted at 6 months after delivery and repeat ureteral reimplantation is planned. Conclusions: General obstetricians will not necessarily pay attention to a history of Politano-Leadbetter ureteral reimplantation, but these patients should undergo careful monitoring of renal function and urinary tract morphology during perinatal care. In the present case, ureteral stenting was effective for postrenal failure during pregnancy after ureteral reimplantation. If ureteral stenting is selected, attention should be paid to post-obstructive diuresis, infection, and stent migration. © 2016 Yoneoka et al.
Keywords: Postrenal failure; Pregnancy; Ureteral reimplantation; Ureteral stenting

Back to Basics: Counting Soft Surgical Goods - Spruce, L. (AORN Journal, 2016)
Retained surgical items (RSIs) pose serious consequences for patients and are a significant threat to patient safety. Perioperative team members are morally and ethically responsible for the prevention of RSIs and should understand how to reduce the risk of occurrence. The prevention of RSIs does not rest in the hands of one individual. It is a multidisciplinary endeavor that aims to reduce the risk of RSIs, and team members should hold each other accountable. This Back to Basics article focuses on the process of counting soft surgical goods, which are the most common RSIs. © 2016 AORN, Inc.
Keywords: Counting; Patient safety; Retained surgical items; Surgical sponge

Histologic assessment of drug-eluting grafts related to implantation site - Tille, J.-C.; de Valence, S.; Mandracchia, D.; Nottelet, B.; Innocente, F.; Gurny, R.; Möller, M.; Walpoth, B.H. (Journal of Developmental Biology, 2016)
Drug-eluting vascular prostheses represent a new direction in vascular surgery to reduce early thrombosis and late intimal hyperplasia for small calibre grafts. Subcutaneous implantation in rats is a rapid and cost-effective screening model to assess the drug-elution effect and could, to some extent, be useful to forecast results for vascular prostheses. We compared biological and histological responses to scaffolds in different implantation sites. Polycaprolactone (PCL), paclitaxel-loaded PCL (PCL-PTX) and dexamethasone-loaded PCL (PCL-DXM) electrospun scaffolds were implanted subcutaneously and in an infrarenal abdominal aortic model in rats for up to 12 weeks. At the conclusion of the study, a histological analysis was performed. Cellular graft invasion revealed differences in the progression of cellular infiltration between PCL-PTX and PCL/PCL-DXM groups in both models. Cell infiltration increased over time in the aortic model compared to the subcutaneous model for all groups. Cell counting revealed major differences in fibroblast, macrophage and giant cell graft colonisation in all groups and models over time. Macrophages and giant cells increased in the PCL aortic model; whereas in the subcutaneous model these cell types increased only after three weeks or even decreased in the drug-eluting PCL groups. Other major findings were observed only in the aortic replacement such as extracellular matrix deposition and neo-angiogenesis. The subcutaneous implant model can be used for screening, especially when drug-eluting effects are studied. However, major histological differences were observed in cell type reaction and depth of cell penetration compared to the aortic model. Our results demonstrate that the implantation site is a critical determinant of the biological response. © 2016 by the authors; licensee MDPI, Basel, Switzerland. All rights reserved.
Keywords: Biodegradable polymers; Drug release; Extracellular matrix; Foreign body reaction; Pathology; Tissue engineering; Vascular prosthesis

Thorn injury osteomyelitis - Shastri, N.; Pham, T. (Journal of Emergency Medicine, 2016)

Heterogeneity of biomaterial-induced multinucleated giant cells: Possible importance for the regeneration process? - Barbeck, M.; Motta, A.; Migliaresi, C.; Sader, R.; Kirkpatrick, C.J.; Ghanaati, S. (Journal of Biomedical Materials Research - Part A, 2016)
Biomaterial-associated multinucleated giant cells (BMGCs) have been found within the implantation beds of many different biomaterials. However, their exact differentiation and their involvement in the inflammatory and healing events of the foreign body response still remain mostly unclear. Silk fibroin (SF) scaffolds, which induces a tissue reaction involving both macrophages and BMGCs, was implanted in the subcutaneous connective tissue of four CD-1 mice for 15 days using an established subcutaneous implantation model. Analysis of macrophage polarization and BMGCs was performed by immunohistochemcial detection of pro- (cyclooxygenase-2 (COX-2), C-C chemokine receptor type 7 (CCR7), nuclear factor "kappa-light-chain-enhancer" (NF-κB)) and anti-(heme oxygenase-1 (HO-1) and mannose receptor (MR, also known as CD206)). Furthermore, histochemical detection of tartrate-resistant acid phosphatase (TRAP) was conducted to test its predictive efficiency for the pro-inflammatory differentiation of cells. An established system for histomorphometrical analysis was used for counting of BMGCs expressing these molecules. The results show that BMGCs express both pro- and anti-inflammatory molecules within the implantation beds of SF scaffolds in comparable numbers, while only statistically significantly lower numbers of TRAP-positive BMGCs were measured in comparison to the BMGCs expressing the above-mentioned molecules. As these data substantiate the heterogeneity of BMGCs, the question arises to what extent BMGCs can "support" the process of tissue regeneration. Furthermore, the data prompt the question to what extent TRAP-expression within a biomaterial implantation bed can be seen as a predictive marker for an inflammatory condition, as in this study no obvious correlation between TRAP-expression and other pro-inflammatory markers could be observed. © 2015 Wiley Periodicals, Inc.
Keywords: biomaterial; foreign body reaction; heterogeneity; inflammation; macrophages; multinucleated giant cells

Suppression of scarring in peripheral nerve implants by drug elution - Fitzgerald, J.J. (Journal of Neural Engineering, 2016)
Objective. Medical implants made of non-biological materials provoke a chronic inflammatory response, resulting in the deposition of a collagenous scar tissue (ST) layer on their surface, that gradually thickens over time. This is a critical problem for neural interfaces. Scar build-up on electrodes results in a progressive decline in signal level because the scar tissue gradually separates axons away from the recording contacts. In regenerative sieves and microchannel electrodes, progressive scar deposition will constrict and may eventually choke off the sieve hole or channel lumen. Interface designs need to address this issue if they are to be fit for long term use. This study examines a novel method of inhibiting the formation and thickening of the fibrous scar. Approach. Research to date has mainly focused on methods of preventing stimulation of the foreign body response by implant surface modification. In this paper a pharmacological approach using drug elution to suppress chronic inflammation is introduced. Microchannel implants made of silicone doped with the steroid drug dexamethasone were implanted in the rat sciatic nerve for periods of up to a year. Tissue from within the microchannels was compared to that from control devices that did not release any drug. Main results. In the drug eluting implants the scar layer was significantly thinner at all timepoints, and unlike the controls it did not continue to thicken after 6 months. Control implants supported axon regeneration well initially, but axon counts fell rapidly at later timepoints as scar thickened. Axon counts in drug eluting devices were initially much lower, but increased rather than declined and by one year were significantly higher than in controls. Significance. Drug elution offers a potential long term solution to the problem of performance degradation due to scarring around neural implants. © 2016 IOP Publishing Ltd.
Keywords: bioengineering; drug release; neural interfacing

Silver ion doped ceramic nano-powder coated nails prevent infection in open fractures: In vivo study - Kose, N.; Çaylak, R.; Pekşen, C.; Kiremitçi, A.; Burukoglu, D.; Koparal, S.; Doʇan, A. (Injury, 2016)
Background Despite improvement in operative techniques and antibiotic therapy, septic complications still occur in open fractures. We developed silver ion containing ceramic nano powder for implant coating to provide not only biocompatibility but also antibacterial activity to the orthopaedic implants. Questions/purposes We hypothesised silver ion doped calcium phosphate based ceramic nano-powder coated titanium nails may prevents bacterial colonisation and infection in open fractures as compared with uncoated nails. Methods 33 rabbits divided into three groups. In the first group uncoated, in the second group hydroxyapatite coated, and in the third group silver doped hydroxyapatite coated titanium nails were inserted left femurs of animals from knee regions with retrograde fashion. Before implantation of nails 50 μl solution containing 106 CFU/ml methicillin resistance Staphylococcus aureus (MRSA) injected intramedullary canal. Rabbits were monitored for 10 weeks. Blood was taken from rabbits before surgery and on 2nd, 6th and 10th weeks. Blood was analysed for biochemical parameters, blood count, C-reactive protein and silver levels. At the end of the 10 weeks animals were sacrificed and rods were extracted in a sterile fashion. Swab cultures were taken from intramedullary canal. Bacteria on titanium rods were counted. Liver, heart, spleen, kidney and central nervous tissues samples were taken for determining silver levels. Histopathological evaluation of bone surrounding implants was also performed. Results No significant difference was detected between the groups from hematologic, biochemical, and toxicological aspect. Microbiological results showed that less bacterial growth was detected with the use of silver doped ceramic coated implants compared to the other two groups (p = 0.003). Accumulation of silver was not detected. No cellular inflammation was observed around the silver coated prostheses. No toxic effect of silver on bone cells was seen. Conclusion Silver ion doped calcium phosphate based ceramic nano powder coating to orthopaedic implants may prevents bacterial colonisation and infection in open fractures compared with those for implants without any coating. © 2015 Elsevier Ltd. All rights reserved.
Keywords: Bacterial colonisation; Calcium phosphate ceramic; Silver ion

Violence-related periorbital trauma with a retained foreign body: A case report - Dell'Aversana, G.; Marenzi, G.; Piombino, P.; Testa, D.; De Riu, G.; Abbate, V.; Califano, L.; Sammartino, G. (Journal of Medical Case Reports, 2016)
Background: Orbital fracture usually occurs as a result of blunt orbital and facial trauma and may involve ocular injuries. International studies on orbital floor fracture show several differences in epidemiology, diagnostic criteria, surgical treatment modalities, and complication rates; therefore, any comparison should be made with caution. Here we describe an unusual case involving a 19-year-old man with violence-related periorbital trauma, wherein a foreign body (a plastic pen cap) traversed the median wall of the maxillary sinus and penetrated the lower turbinate. Case presentation: A 19-year-old Caucasian man was referred to our department with localized pain and swelling in the left suborbital region following a physical fight in May 2014. A clinical examination revealed no abnormalities in his eyeballs or eye movement, palpation of the orbital contour revealed no fractures, and ophthalmological evaluation showed no evidence of diplopia. A computed tomography scan revealed fractures in the left orbital floor, periorbital tissue herniation without muscular entrapment and left maxillary hemosinus were observed. A hypodense soft tissue mass was lodged in the left orbital floor, which extended to the median wall of the maxillary sinus and penetrated the left lower turbinate. Surgical exploration of the foreign body was conducted, revealing the foreign body to be a pen cap. Conclusions: History or clinical examination alone may be inadequate to raise the suspicion of a retained periorbital foreign body in a situation of orbital region trauma. Computed tomography is important for the evaluation of periorbital injuries, especially because it could reveal the presence of a foreign body. Periorbital foreign bodies can be observed distinctly on computed tomography, which remains the most sensitive study and should be the first imaging modality in such cases. © 2016 Dell'Aversana et al.
Keywords: Blunt trauma; Computed tomography; Foreign body; Hemosinus; Orbital floor fracture

Gossypiboma mimicking a mesenchymal tumor: A report of a rare case - Eken, H.; Soyturk, M.; Balci, G.; Firat, D.; Cimen, O.; Karakose, O.; Somuncu, E. (American Journal of Case Reports, 2016)
Objective: Challenging differential diagnosis Background: Gossypiboma is the term for a surgical complication resulting from foreign materials such as a surgical sponge or gauze that was accidentally left inside a patient’s body. Case Report: Here, we report the case of a 62-year-old woman with gossypiboma. She underwent surgery due to an abdominal mass that was preoperatively considered a tumor. Intra-postoperatively, it was diagnosed as gossypiboma. Conclusions: For the prevention of gossypiboma during the pre-operative and post-operative periods, counting sponges and surgical equipment must be done very carefully. If there is any doubt postoperatively, direct abdominal imaging may be helpful. © Am J Case Rep 2016.
Keywords: Abdomen; Diagnostic errors; Gossypium

Gossypiboma revisited: A never ending issue - Rabie, M.E.; Hosni, M.H.; Al Safty, A.; Al Jarallah, M.; Ghaleb, F.H. (International Journal of Surgery Case Reports, 2016)
Introduction Leaving a surgical item inside the patient at the end of surgery, is one of the most dreadful complications. The item is frequently a surgical sponge and the resultant morbidity is usually severe. Additionally, the event poses considerable psychic strain to the operating team, notably the surgeon. Presentation of cases Here we describe the clinical course of three patients in whom a surgical sponge was missed, despite a seemingly correct count at the end of difficult caesarean sections. In two patients, who presented shortly after surgery, the pad was extracted with no bowel resection. In the third patient, who presented several years after surgery, colectomy was performed. Discussion Gossypiboma is under reported and the true incidence is largely unknown. Depending on the body reaction and the characters of the retained sponge, the patient may present within months to years after surgery. Risk factors for retained foreign objects include emergency surgery, an unplanned change in the surgical procedure, higher body mass index, multiple surgical teams, greater number of major procedures done at the same time and incorrect count recording. The surgical procedure needed to extract the retained sponge may be a simple one, as in the first case, or it may be more complex, as seen in the other two cases. Although holding the correct count at the end of surgery is the gold standard safeguard against this mishap, human errors continue to occur, as happened in our patients. For that reason, the correct count should be supplemented by employing one of the several new technologies currently available. Conclusion Gossypiboma continues to occur, despite precautionary measures. As its consequences might cost the patient his life and the surgeon his professional reputation, extra preventive measures should be sought and implemented. New advances in technology should be incorporated in the theatre protocol as additional safeguard against human error. When encountered, a direct incision over the encapsulated swelling, in contrast to a formal laparotomy incision, might simplify the surgical procedure. © 2015 Published by Elsevier Ltd.
Keywords: Gossypiboma; Prevention; Retained object

Surgical sponge forgotten for nine years in the abdomen: A case report - Susmallian, S.; Raskin, B.; Barnea, R. (International Journal of Surgery Case Reports, 2016)
Introduction Retained surgical sponge or other items in patients’ bodies happens more frequently than is reported. Healthcare personnel can forget to remove textile material or instruments during complicated, extended, or emergency surgery. In addition, changes in the operating team can influence the occurrence of such errors. Presentation of case We present a case with a symptomatic gossypiboma nine years after a previous cesarean section. A 34-year-old woman was admitted to the emergency room having experienced abdominal pain and fever for the previous month. An abdominal computed tomography revealed an abscess in the lower abdomen. A laparotomy was performed, and a resection and block were carried out. A surgical sponge was extracted from an omental abscess. Discussion Surgical sponges are the most common foreign materials retained (70%) in the abdominal cavity because of their frequent usage and small size. Moreover, a blood-soaked sponge in a hemorrhagic abdomen can be difficult to distinguish from blood. Conclusion Whenever the accounting for material depends on humans, mistakes will continue to be committed. A falsely correct sponge count was reported in 71.42% of cases [14]; therefore, a new count system must be developed for post-surgical situations. © 2016 The Authors
Keywords: Abdomen; Bowel; Patient safety; Retained foreign body; Surgery

Unintentionally retained Foreign bodies after surgical procedures. Analysis of 4547 cases - Birolini, D.V.; Rasslan, S.; Utiyama, E.M. (Revista do Colegio Brasileiro de Cirurgioes, 2016)
Objective: this study aims to explore the experience of Brazilian surgeons on Unintentionally Retained Foreign Bodies (RFB) after surgical procedures. Methods: A questionnaire was sent to surgeons by electronic mail, between March and July 2012. The questions analyzed their experience with foreign bodies (FB), foreign bodies’ types, clinical manifestations, diagnoses, risk factors and legal implications. Results: in the 2872 eligible questionnaires, 43% of the surgeons asserted that they had already left FB and 73% had removed FB in one or more occasions, totalizing 4547. Of these foreign bodies, 90% were textiles, 78% were discovered in the first year and 14% remained asymptomatic. Among doctors with less than five years after graduation, 36% had already left a FB. The most frequently surgical procedures mentioned were the elective (57%) and routine (85%) ones. Emergency (26%), lack of counting (25%) and inadequate conditions of work contributed (12.5%) to the occurrence. In 46% of the cases patients were alerted about the FB, and 26% of them sued the doctors or the institution. Conclusions: challenging medical situations, omission of security protocols and inadequate work conditions contributed to RFB. However, RFB occurs mostly in routine procedures such as cesarean or cholecystectomy, and at the beginning of the professional career, highlighting, particularly in poorest countries, the need for primary prevention. Textiles predominated causing clinical repercussions and they were diagnosed in the first postoperative months. Surgeons were sued in 11.3% of the RFB cases. © 2016, Colegio Brasileiro de Cirurgioes, All rights reserved.
Keywords: Foreign Bodies; Postoperative Complications; Surgical Instruments

Supra-aural gossypiboma: Case report of a retained textile surgical sponge in an unusual location - Chawla, N.; Gupta, N.; Dhawan, N. (Annals of the Royal College of Surgeons of England, 2016)
Gossypiboma or retained surgical sponge is an infrequently encountered surgical complication, more so in the head and neck region. A literature search did not reveal a previously reported case of retained or concealed surgical sponge after microscopic ear surgery. We present a unique and previously unreported case of a 25-year-old male who presented with a cystic swelling in the right supra-aural region 5 months post-modified radical mastoidectomy of the right ear. Surgical excision of the swelling revealed a retained surgical sponge. We emphasise the importance of counting surgical sponges after every surgical step to minimise the incidence of such retained surgical items.
Keywords: Gossypiboma; Retained surgical item; Supra-aural; Surgical sponge

Splenic abscess with portal venous gas caused by intrasplenic migration of an endoscopic double pigtail drain as a treatment of post-sleeve gastrectomy fistula - Genser, L.; Pattou, F.; Caiazzo, R. (Surgery for Obesity and Related Diseases, 2016)
Keywords: Aeroportia; Endoscopic internal drainage; Hepatic portal splenic venous gas; Leak; Migration; Pigtail; Sleeve

Foreign body reaction after implantation of a device for intervertebral assisted motion - Seo, J.-Y.; Ha, K.-Y.; Kim, Y.-H.; Ahn, J.-H. (Journal of Korean Neurosurgical Society, 2016)
The device for intervertebral assisted motion (DIAM) is a dynamic implant that consists of a silicone bumper enveloped by a polyethylene terephthalate (PET) fiber sack. Silicone and PET were used because of their biological inertness, but repetitive motion of the spine can cause wear on the implant nonetheless. The purpose of this study is to report a case of foreign body reaction (FBR) against a DIAM. A 72-year-old female patient presented with lower back pain and both legs radiating pain. She had undergone DIAM implantation at L4–5 for spinal stenosis 5 years previously. The intervertebral disc space of L4–5, where the DIAM was inserted, had collapsed and degenerative scoliosis had developed due to left-side collapse. MRI showed L3–4 thecal sac compression and left L4–5 foraminal stenosis. The patient underwent removal of the DIAM and instrumented fusion from L3 to L5. During surgery, fluid and granulation tissue were evident around the DIAM. Histopathology showed scattered wear debris from the DIAM causing chronic inflammation due to the resulting FBR. A FBR due to wear debris of a DIAM can induce a hypersensitivity reaction and bone resorption around the implant, causing it to loosen. © 2016 The Korean Neurosurgical Society.
Keywords: Device for intervertebral assisted motion; Foreign body reaction; Polyethylene terephthalate; Silicone

Gastric Perforation by Ingested Rabbit Bone Fragment - Gambaracci, G.; Mecarini, E.; Franceschini, M.S.; Scialpi, M. (Case Reports in Gastroenterology, 2016)
The majority of accidentally ingested foreign bodies is excreted from the gastrointestinal (GI) tract without any complications. Sometimes sharp foreign bodies - like chicken and fish bones - can lead to intestinal perforation and may present insidiously with a wide range of symptoms and, consequently, different diagnoses. We report the case of a 59-year-old woman presenting with fever and a 1-month history of vague abdominal pain. Computed tomography (CT) showed the presence of a hyperdense linear image close to the gastric antrum surrounded by a fluid collection and free peritoneal air. At laparotomy, a 4-cm rabbit bone fragment covered in inflamed tissue was detected next to a gastric wall perforation. Rabbit bone fragment ingestion, even if rarely reported, should not be underestimated as a possible cause of GI tract perforation. © 2016 The Author(s). Published by S. Karger AG, Basel.
Keywords: Bone fragment; Foreign body; Ingestion; Perforation; Rabbit; Stomach

Penetrating ocular trauma with retained intraocular foreign body: Management, follow-up and medico-legal evaluation - Sorrentino, S.; Marsella, L.T.; Feola, A.; Marino, V.; Billi, B. (West Indian Medical Journal, 2016)
Ocular trauma is the leading cause of acquired monocular blindness, accounting for 1.97-6% of such cases. Particularly, penetrating ocular injuries are among the most common eye injuries with this kind of outcome. Early diagnosis and prompt management are crucial to avoid complications, and the especially dreaded enucleation. In this article, the authors describe the clinical management, and evaluate the visual and anatomical results obtained in a case of ocular injury with retained intraocular foreign body (IOFB) in a 20-year old female patient. The course of treatment involved a combination of penetrating keratoplasty with a temporary keratoprosthesis, phacoemulsification with intraocular lens implantation and pars plana vitrectomy. At three years from the initial injury, the patient was able to count fingers at 30 centimetres and anatomical restitutio ad integrum of the globe had been achieved.
Keywords: Intraocular foreign body; Keratoprosthesis; Vitrectomy

Repeated small bowel obstruction caused by chestnut ingestion without the formation of phytobezoars - Satake, R.; Chinda, D.; Shimoyama, T.; Satake, M.; Oota, R.; Sato, S.; Yamai, K.; Hachimori, H.; Okamoto, Y.; Yamada, K.; Matsuura, O.; Hashizume, T.; et al. (Internal Medicine, 2016)
A small number of cases of small bowel obstruction caused by foods without the formation of phytobezoars have been reported. Repeated small bowel obstruction due to the ingestion of the same food is extremely rare. We present the case of 63-year-old woman who developed small bowel obstruction twice due to the ingestion of chestnuts without the formation of phytobezoars. This is the first reported case of repeated small bowel obstruction caused by chestnut ingestion. Careful interviews are necessary to determine the meal history of elderly patients and psychiatric patients. © 2016 The Japanese Society of Internal Medicine.
Keywords: Chestnut; Repeated small bowel obstruction

Symptomatic giant peritoneal loose body in the pelvic cavity: A case report - Elsner, A.; Walensi, M.; Fuenfschilling, M.; Rosenberg, R.; Robert, M. (International Journal of Surgery Case Reports, 2016)
Introduction Giant peritoneal loose bodies (gPLB) occur rarely and therefore only few have been described. Often they are found incidentally and have no clinical relevance, whereas symptomatic forms may require surgical removal. Presentation of case We report the case of a male patient suffering from abdominal discomfort with alternating localizations for several years, actually presenting with a proctitis. With elevated inflammatory markers, a conspicuous resistance in the lower abdomen and in order to evaluate further affection of the colon, an abdominal CT-scan was performed. It revealed a spherical mass in the lesser pelvis. A colonoscopy confirmed the proctitis, showing no further pathologies. Due to the symptoms and the uncertain entity of the mass, a diagnostic laparoscopy was performed and a boiled egg-like structure (diameter 5.2 cm) was removed. The patient recovered well and was free of symptoms. Discussion The patient had two potential reasons for his symptoms, one of them being a suspected leftover foreign body years after an appendectomy. The proctitis was treated conservatively but without complete remission of the abdominal discomfort. Therefore, a diagnostic laparoscopy was performed and the mass turned out to be a gPLB. Conclusion To obtain a fast diagnosis and to perform an adequate conservative or surgical therapy, the knowledge about the rare entity of a gPLB is necessary. An exact anamnesis, clinical examination and the knowledge about the diagnostic values of radiological and endoscopic investigations are crucial. © 2016 The Authors.
Keywords: Abbreviations PLB peritoneal loose body; gPLB giant peritoneal loose body

Outcomes of retinal detachment repair after posterior open globe injury - Reed, D.C.; Juhn, A.T.; Rayess, N.; Hsu, J.; Chiang, A. (Retina, 2016)
Purpose: To report outcomes of retinal detachment (RD) repair following posterior open globe injury. Methods: This retrospective, consecutive case series examined patients who underwent RD repair following Zone II and/or III open globe injury repair between January 1, 2007 and October 31, 2013. Patients with<3 months of follow-up since their last vitreoretinal surgery, and those who underwent pars plana vitrectomy (e.g., for intraocular foreign body) during their initial open globe injury repair were excluded. Results: Of 30 patients who met inclusion criteria, reattachment of the retina was achieved in 25 (83%) during the first vitreoretinal surgical procedure and 5 (17%) were deemed inoperable intraoperatively. Ten patients (30%) developed recurrent RD, and 8 underwent additional surgery. At last follow-up, reattachment was observed in 4 of these 8. The overall rate of final reattachment was 63% (19 patients). The mean number of surgeries for RD was 1.5 (range, 1-3). Fifteen patients (50%) achieved final visual acuity of counting fingers or better. Mean follow-up from the last vitreoretinal surgery was 23 months (range, 3-52). Conclusion: Although RD following posterior open globe injury confers a grave prognosis, successful anatomic reattachment of the retina was achieved in the majority of patients in this series, with half achieving ambulatory vision.
Keywords: open globe injury; pars plana vitrectomy; retinal detachment; ruptured globe

Biocompatibility and potential of decellularized porcine small intestine to support cellular attachment and growth - Nowocin, A.K.; Southgate, A.; Gabe, S.M.; Ansari, T. (Journal of Tissue Engineering and Regenerative Medicine, 2016)
The aim of this study was to decellularize a 30cm long segment of porcine small intestine, determine its in vivo behaviour and assess the type of immunological reaction it induces in a quantitative manner. A segment of porcine ileum up to 30cm long, together with its attached vasculature, was decellularized via its mesenteric arcade as a single entity. The quality of the acellular scaffold was assessed histologically and using molecular tools. The host response to the scaffold was evaluated in a rodent model. Stereological techniques were incorporated into quantitative analysis of the phenotype of the macrophages infiltrating the scaffold in vivo. Lengths of ileal scaffold, together with its attached vasculature, were successfully decellularized, with no evidence of intact cells and DNA or collagen and GAGs overdegradation. Analysis of explants harvested over 2months postimplantation revealed full-thickness recellularization and no signs of foreign body or immune reactions. Macrophage profiling proved that between weeks 4 and 8 in vivo there was a switch from an M1 (pro-inflammatory) to an M2 (pro-remodelling) type of response. We show here that the decellularization process results in a biocompatible and non-toxic matrix that upon implantation triggers cellular infiltration and angiogenesis, primarily characterized by a pro-remodelling type of mononuclear response, without inducing foreign body reaction or fibrosis. © 2016 John Wiley & Sons, Ltd.
Keywords: Bicompatibility; Decellularization; ECM scaffold; Host response; Macrophage responses; Subcutaneous implantation; Tissue remodelling

Penicillium keratitis in a HIV-infected patient - Anutarapongpan, O.; Thanathanee, O.; Suwan-Apichon, O. (BMJ Case Reports, 2016)
36-year-old HIV-positive man presented with symptoms of redness, blurred vision and foreign body sensation in his right eye for 3 months. The slit lamp examination revealed deep stromal infiltration with a feathery margin in an otherwise minimal anterior chamber reaction. A corneal scraping was negative. Confocal microscopy demonstrated an abnormal large hyper-reflective oval shape in the corneal stroma. Corneal infiltration did not show improvement after topical, intrastromal and intracameral antifungal treatment. Therapeutic penetrating keratoplasty was performed to eradicate the infection. Corneal button culture and histopathological results confirmed the diagnosis of Penicillium marneffei keratitis. No recurrent infection occurred after corneal transplantation. This appears to be the first report of P. marneffei keratitis in an HIV-infected patient. Although it is an uncommon condition, it should be one of the differential diagnoses in an HIV-infected patient presenting with keratitis.

Diagnosis and Management of Adverse Local Tissue Reactions Secondary to Corrosion at the Head-Neck Junction in Patients With Metal on Polyethylene Bearings - Plummer, D.R.; Berger, R.A.; Paprosky, W.G.; Sporer, S.M.; Jacobs, J.J.; Della Valle, C.J. (Journal of Arthroplasty, 2016)
We reviewed 27 patients who underwent revision for an adverse local tissue reaction (ALTR) secondary to corrosion at the head-neck junction with MoP bearings. Serum cobalt and chromium levels were elevated in all cases, with a mean cobalt of 11.2 ppb and chromium of 2.2 ppb. Patients underwent modular bearing exchange, including a ceramic head with a titanium sleeve in 23 of 27 cases with only one recurrence of ALTR in one of the four patients not treated with a ceramic head. The diagnosis of ALTR secondary to corrosion is associated with cobalt levels of >1 ppb with cobalt levels elevated above chromium. Retention of a well-fixed stem and modular exchange to a ceramic head leads to resolution of symptoms and decreases in metal levels. © 2016 Elsevier Inc.
Keywords: Adverse local tissue reaction; Bearing surfaces; Modular taper corrosion; Revision total hip arthroplasty; Total hip arthroplasty

Epidemiology of Wire-Bristle Grill Brush Injury in the United States, 2002-2014 - Baugh, T.P.; Hadley, J.B.; David Chang, C.W. (Otolaryngology - Head and Neck Surgery (United States), 2016)
Objectives The purpose of this study was to investigate the epidemiology of wire-bristle grill brush injury. Study Design and Setting Cross-sectional analysis of national databases; literature review. Subjects and Methods The Consumer Product Safety Commission's National Electronic Injury Surveillance System (NEISS) was used to derive a national weighted estimate of emergency department visits for wire bristle injury from 2002 to 2014. Date, location of injury, demographics, and outcomes were analyzed. A literature search and a consumer-reported injury database (SaferProducts.gov) were interrogated to provide ancillary sources of data. Results A total of 43 cases were found within the NEISS database, which extrapolated to an estimated 1698 (95% confidence interval, 1468-1927) emergency department visits nationwide. In the NEISS database, the mean age was 30 years, and the sex distribution of the patients was similar (21 males vs 22 females). The most common location of injury was the oropharynx in both the NEISS database (23 of 43, 53.4%) and the literature review (11 of 36, 30.5%). However, the oral cavity was the most frequent site in the consumer-reported SaferProducts.gov database (9 of 24, 37.5%). The majority of patients in the NEISS were treated in the emergency department (31 of 43, 69.7%). Raw case counts were highest in June, July, and August, with the highest number of events in the month of July. Conclusion Injury from wire-bristle grill brush is uncommon but prevalent during certain seasons. Otolaryngologists play an important in the diagnosis and treatment of these injuries. Awareness among consumers and product manufacturers is necessary to promote safety. © American Academy of Otolaryngology-Head and Neck Surgery Foundation 2016.
Keywords: grill brush; ingestion; NEISS; swallow; wire bristle

Two cases of small bowel obstruction secondary to a swallowed potato - Castren, E.; Hakeem, A.; Mahmood, N.S.; Aryal, K. (BMJ Case Reports, 2015)
Bowel obstruction due to bezoars (compaction of ingested material within the gastrointestinal tract) is a rare, but well documented occurrence. In this paper, we present two cases of potato-induced small bowel obstruction. Both patients were approximately 50 years old and had cerebral palsy and learning disabilities, respectively. They presented with abdominal pain and bilious vomiting, with no medical or surgical history. Diagnosis of small bowel obstruction was confirmed by CT prior to taking the patients to the operating theatre, where whole potatoes were found to be obstructing each patient's bowel lumen. Both patients underwent laparotomy with enterotomy and removal of the potato. They both made a good recovery. Through a literature review of bezoar-induced bowel obstruction, these cases highlight important diagnostic and management principles. Copyright 2015 BMJ Publishing Group. All rights reserved.

Beyond the “B”: a new concept of the surgical staple enabling miniature staplers - Demertzis, S.; Beslac, O.; Mettler, D.; Zalokar, D.; Spangler, T.; Hausen, B.; Swanstrom, L. (Surgical Endoscopy, 2015)
Background: Surgical staplers currently all rely on the same staple form—the “B” which necessitates a high delivery profile (12 mm). A novel “D” shape staple allows for an extremely low profile of the applicator. The acute and long-term efficacy of a D-shaped staple (Cardica, Redwood City, CA, USA) was compared to conventional B-form staples (Covidien, Norwalk, CN, USA) in an animal model for intestinal transections and anastomoses. Methods: Jejunojejunal anastomoses (JJ) were performed via mini-laparotomy in a swine model. White & blue D- and B-shaped staples were studied in three groups (planned survival 14–84 days). Intraoperative assessment included completeness of staple line, hemostasis, and need for intervention. Postoperatively, animals were evaluated for complications. At the time of sacrifice, gross pathological and histological assessments were performed. Results: Twenty-three animals had 40 anastomoses (23 “D” and 17 “B” staple anastomoses) with no intraoperative mortalities. One “D” staple application required a manual extension of the cut. Acute hemostasis was 100 %. Group 1 (n = 5) compared white staples in JJs (D staple n = 5; B staple n = 5; 14-day survival = 100 %). Group 2 (n = 12) compared white staples in JJs (D staple n = 12; B staple n = 6; 34-day survival = 92 %). One animal died on day 4 for a non-staple related cause. Group 3 (n = 6) compared blue staples in JJs (D staple n = 6; B staple n = 6; 84 day survival = 84 %). One animal died on day 18 due to an obstruction at the B staple JJ caused by stricture. There were no other bleeding, leaks or strictures in any of the groups. Gross pathology and histology were unremarkable in all JJs. Conclusions: This study showed no difference in intraoperative performance and the chronic healing response in JJs between D- and B-shaped staples. Based on these findings, the D-shaped staple elicits a normal healing response in jejunostomies and offers the possibility of clinical use of this advance in staple design. © 2015, The Author(s).
Keywords: Anastomosis; Laparoscopy; Staples; Surgical staplers

Severe neck infections that require wide external drainage: clinical analysis of 17 consecutive cases - Horváth, T.; Horváth, B.; Varga, Z.; Liktor, B., Jr.; Szabadka, H.; Csákó, L.; Liktor, B. (European Archives of Oto-Rhino-Laryngology, 2015)
Infections in the neck layers and spaces are potentially life-threatening diseases causing further complications, like mediastinitis, airway obstruction, or sepsis. Despite of the need for a conservative approach, they still regularly require surgical intervention. Records of 17 patients with severe neck infections that were treated by wide external incision and open wound management were retrospectively analyzed. The aim of the study was to clinically characterize these most serious neck infections. The most common presenting symptoms were neck pain and tense neck mass (94-94 %) regularly with fever (65 %), always accompanied by a marked elevation of C reactive protein level (average 192 uG/l). These findings were constant and very similar among both the deep neck infection and necrotizing fasciitis cases. More than half of the patients (53 %) had at least one systemic co-morbidity. The parapharyngeal space was most commonly affected (83 %), but extended disease involving more than two major neck regions was found in 13 cases (76 %). Dental (29 %) was the most common primary infection, followed by peritonsillar abscess (23 %), Microbiological results showed a wide variety of corresponding bacteria. Mediastinitis was developed in three cases (18 %), and airway obstruction requiring tracheostomy in two cases (12 %). All the patients survived. Severe neck infections are a heterogenous group of diseases regarding to the primary site of infection, microbiology, localisation and host reaction. However, rapidly developed, painful, tense neck mass with a highly elevated CRP level should always alert for an extended or phlegmonous process in the layers or spaces of the neck. © 2014, Springer-Verlag Berlin Heidelberg.
Keywords: Deep neck infection; External drainage; Necrotizing fasciitis; Surgery

A Surprising Cause for Corneal Edema after Cataract Surgery: A Missed Posterior Chamber Intraocular Lens Haptic Remnant - Elyashiv, S.; Barequet, I. (Seminars in Ophthalmology, 2015)
We present a case of retained intraocular lens (IOL) haptic segment in the anterior chamber, diagnosed seven months following a reportedly uneventful cataract surgery due to manifestation of inferior corneal edema. Specular microscopy revealed low endothelial counts of 513/mm2. Upon diagnosis, prompt surgical removal of the IOL haptic segment resulted in rapid resolution of the corneal edema within a week. Despite the clearing of the cornea, no improvement in the visual acuity occurred and cystoid macular edema was diagnosed and treated with topical anti-inflammatory agents and two intra-vitreal anti-VEGF injections, followed by complete resolution of ocular findings and improvement of the visual acuity. © 2014 Taylor & Francis.
Keywords: Cornea; edema; haptic; retained

Menarche? a case of abdominal pain and vaginal bleeding in a preadolescent girl - Riney, L.C.; Reed, J.L.; Kruger, L.L.; Brody, A.J.; Pomerantz, W.J. (Annals of Emergency Medicine, 2015)
Abdominal pain is one of the most common complaints in the pediatric ED. Because of the broad range of potential diagnoses, it can pose challenges in diagnosis and therapy in the preadolescent girl. An 11-year-old previously healthy girl presented to our pediatric ED with fever, decreased appetite, vaginal bleeding, and abdominal pain. Initial evaluation yielded elevated creatinine levels, leukocytosis with bandemia, elevated inflammatory markers, and urine concerning for a urinary tract infection. She began receiving antibiotics for presumed pyelonephritis and was admitted to the hospital. After worsening respiratory status and continued abdominal pain, a computed tomography scan was obtained and a pelvic foreign body and abscess were identified. Adolescent gynecology was consulted for examination under anesthesia for abscess drainage and foreign body removal. A foreign body in the vagina or uterus can present as vaginal discharge, vaginal bleeding, abdominal pain, dysuria, or hematuria. Because symptoms can be diverse, an intravaginal or uterine foreign body should be considered in the preteen female patient presenting to the ED with abdominal pain. © 2015 American College of Emergency Physicians.

Inattention blindness in surgery - Hughes-Hallett, A.; Mayer, E.K.; Marcus, H.J.; Pratt, P.; Mason, S.; Darzi, A.W.; Vale, J.A. (Surgical Endoscopy, 2015)
Background: Inattention blindness (IB) can be defined as the failure to perceive an unexpected object when attention is focussed on another object or task. The principal aim of this study was to determine the effect of cognitive load and surgical image guidance on operative IB. Methods: Using a randomised control study design, participants were allocated to a high or low cognitive load group and subsequently to one of three augmented reality (AR) image guidance groups (no guidance, wireframe overlay and solid overlay). Randomised participants watched a segment of video from a robotic partial nephrectomy. Those in the high cognitive load groups were asked to keep a count of instrument movements, while those in the low cognitive load groups were only asked to watch the video. Two foreign bodies were visible within the operative scene: a swab, within the periphery of vision; and a suture, in the centre of the operative scene. Once the participants had finished watching the video, they were asked to report whether they had observed a swab or suture. Results: The overall level of prompted inattention blindness was 74 and 10 % for the swab and suture, respectively. Significantly higher levels of IB for the swab were seen in the high versus the low cognitive load groups, but not for the suture (8 vs. 47 %, p < 0.001 and 90 vs. 91 %, p = 1.000, for swab and suture, respectively). No significant difference was seen between image guidance groups for attention of the swab or suture (29 vs. 20 %, p = 0.520 and 22 vs. 22 %, p = 1.000, respectively). Conclusions: The overall effect of IB on operative practice appeared to be significant, within the context of this study. When examining for the effects of AR image guidance and cognitive load on IB, only the latter was found to have significance. © 2015, Springer Science+Business Media New York.
Keywords: Augmented reality; Cognitive load; Inattention blindness; Laparoscopic; Safety; Surgery

Spondylodiscitis associated with button battery ingestion: Prompt evaluation with MRI - Young, A.; Tekes, A.; Huisman, T.A.G.M.; Bosemani, T. (Neuroradiology Journal, 2015)
Spondylodiscitis is a rare complication of unwitnessed button battery ingestion in children. We report a case of a 20-month-old girl who presented to the emergency room 2 weeks after endoscopic removal of unwitnessed, impacted esophageal battery. Delayed presentation of spondylodiscitis after foreign body removal is related to local injury, pressure necrosis, and perforation. The bilaminar shape of an unknown ingested foreign body should alert the treating physician that it might be a battery rather than a coin. Prompt evaluation with magnetic resonance imaging is essential to prevent neurological deficit and/or spinal deformities. © The Author(s) 2015.
Keywords: button battery ingestion; children; magnetic resonance imaging; Spondylodiscitis

Ingested cylindrical batteries in an incarcerated male: A caustic tale! - Dunphy, L.; Maatouk, M.; Raja, M.; O'Hara, R. (BMJ Case Reports, 2015)
A 37-year-old incarcerated man presented to the accident and emergency department following the deliberate ingestion of eight cylindrical batteries. He also admitted to inserting a razor blade wrapped in cling-film into his rectum; in addition, he sustained a self-inflicted laceration to his left antecubital fossa, using the metal casing from a battery. His medical history included a borderline and emotionally unstable personality disorder. He had ingested several batteries 12 months previously and required an emergency laparotomy to retrieve them. On the present admission, as there was no clinical evidence of small bowel obstruction, he was treated conservatively with serial radiographs. Following conservative management, the batteries failed to progress through the gastrointestinal tract, hence a laparotomy was performed and all the batteries were extricated. This paper discusses the management and associated sequelae of patients presenting following the intentional ingestion of a battery. Copyright © 2015 BMJ Publishing Group.

Neutrophil responses to sterile implant materials - Jhunjhunwala, S.; Aresta-DaSilva, S.; Tang, K.; Alvarez, D.; Webber, M.J.; Tang, B.C.; Lavin, D.M.; Veiseh, O.; Doloff, J.C.; Bose, S.; Vegas, A.; Ma, M.; et al. (PLoS ONE, 2015)
In vivo implantation of sterile materials and devices results in a foreign body immune response leading to fibrosis of implanted material. Neutrophils, one of the first immune cells to be recruited to implantation sites, have been suggested to contribute to the establishment of the inflammatory microenvironment that initiates the fibrotic response. However, the precise numbers and roles of neutrophils in response to implanted devices remains unclear. Using a mouse model of peritoneal microcapsule implantation, we show 30-500 fold increased neutrophil presence in the peritoneal exudates in response to implants. We demonstrate that these neutrophils secrete increased amounts of a variety of inflammatory cytokines and chemokines. Further, we observe that they participate in the foreign body response through the formation of neutrophil extracellular traps (NETs) on implant surfaces. Our results provide new insight into neutrophil function during a foreign body response to peritoneal implants which has implications for the development of biologically compatible medical devices. © 2015 Jhunjhunwala et al.

Large Urethro-Vesico-Vaginal Fistula due to a Vaginal Foreign Body in a 22-Year-Old Woman: Case Report and Literature Review - D'Elia, C.; Curti, P.; Cerruto, M.A.; Monaco, C.; Artibani, W. (Urologia Internationalis, 2015)
In the non-industrialized countries of Africa and Asia obstetric fistulas are more frequently caused by prolonged labour, whereas in countries with developed healthcare systems they are generally the result of complications of gynaecological surgery or, rarely, benign pathologies like inflammation or foreign bodies. A 22-year-old woman was brought to the gynaecology clinic because of foul-smelling vaginal discharge. On pelvic examination a ring-like foreign body was impacted between the anterior and posterior vaginal wall. MRI scan confirmed the presence of a cylindrical foreign body in the vagina and the patient revealed that she had involuntarily' inserted a plastic bubble bath cap into the vagina. At surgery removal of the cap was difficult and at the end of the manoeuver evidence of a huge urethro-vesicovaginal fistula occurred. The patient was discharged with bilateral ureteral stents and suprapubic catheter. After 3 months we performed an end-to-end anastomotic urethroplasty to repair the urethral avulsion and restored the bladder/ trigonal and vaginal/cervical defects with 3 layers of sutures; 3 months later the patient had no complaints. Complex genital fistulas represent an extremely debilitating morbidity. In our case, a vaginal approach was successful, but the choice between an abdominal or vaginal approach depends on the surgeon's experience and training. © 2015 S. Karger AG, Basel.
Keywords: Foreign body; Genital fistula; Incontinence; Urethro-vaginal fistula; Vesico-vaginal fistula

Invading of intrauterine contraceptive device into the sigmoid colon through uterine perforation caused by a blunt trauma - Davoodabadi, A.; Mohammadzadeh, M.; Amirbeigi, M.; Jazayeri, H. (Chinese Journal of Traumatology - English Edition, 2015)
Intrauterine contraceptive device (IUCD) is relatively safe but still with some serious risks. Uterus perforation is rare and would be fatal. A case of Cu-7 IUCD invading into the sigmoid colon through uterine perforation caused by a pelvic blunt trauma was presented. Our case showed that uterus perforation by an IUCD could induce utero-sigmoid fistula which is likely to be missed. Imaging is required when the patients with IUCD present abdominal pain, particularly with a history of trauma. © 2015 Production and hosting by Elsevier B.V. on behalf of Daping Hospital and the Research Institute of Surgery of the Third Military Medical University.
Keywords: Colon; Intrauterine devices; Sigmoid; Uterine perforation

Adverse local tissue reactions in metal-onpolyethylene total hip arthroplasty due to trunnion corrosion: The risk of misdiagnosis - Whitehouse, M.R.; Endo, M.; Zachara, S.; Nielsen, T.O.; Greidanus, N.V.; Masri, B.A.; Garbuz, D.S.; Duncan, C.P. (Bone and Joint Journal, 2015)
Adverse reaction to wear and corrosion debris is a cause for concern in total hip arthroplasty (THA). Modular junctions are a potential source of such wear products and are associated with secondary pseudotumour formation. We present a consecutive series of 17 patients treated at our unit for this complication following metal-on-highly cross-linked polyethylene (MoP) THA. We emphasise the risk of misdiagnosis as infection, and present the aggregate laboratory results and pathological findings in this series. The clinical presentation was pain, swelling or instability. Solid, cystic and mixed softtissue lesions were noted on imaging and confirmed intra-operatively. Corrosion at the head-neck junction was noted in all cases. No bacteria were isolated on multiple pre- and intra-operative samples yet the mean erythrocyte sedimentation rate was 49 (9 to 100) and C-reactive protein 32 (0.6 to 106) and stromal polymorphonuclear cell counts were noted in nine cases. Adverse soft-tissue reactions can occur in MoP THA owing to corrosion products released from the head-neck junction. The diagnosis should be carefully considered when investigating pain after THA. This may avoid the misdiagnosis of periprosthetic infection with an unidentified organism and mitigate the unnecessary management of these cases with complete single- or two-stage exchange. © 2015 The British Editorial Society of Bone & Joint Surgery.

Biocompatibility and biodegradation of protein microparticle and film scaffolds made from kafirin (sorghum prolamin protein) subcutaneously implanted in rodent models - Taylor, J.; Anyango, J.O.; Potgieter, M.; Kallmeyer, K.; Naidoo, V.; Pepper, M.S.; Taylor, J.R.N. (Journal of Biomedical Materials Research - Part A, 2015)
Kafirin, the sorghum prolamin protein, like its maize homologue zein, can be made into microparticles and films and potentially used as a biomaterial. Zein has good bio- and cyto-compatibility. Kafirin could be advantageous as it is more hydrophobic, more crosslinked, more slowly digested by mammalian proteases than zein and is non-allergenic. The safety and biocompatibility of kafirin implants in two forms was determined in rodent models. One week post subcutaneous injection of kafirin microparticles (size 5-μm diameter) in mice, chronic inflammation, abnormal red blood cells, and gross fibrin formation were observed. This chronic inflammatory response was possibly caused by the release of hydrolysis products such as glutamate during the degradation of the kafirin microparticles. In contrast, films made from kafirin microparticles (50-μm thick, folded into 1 cm3) implanted in rats showed no abnormal inflammatory reactions and were only partially degraded by day 28. The slower degradation of the kafirin films was probably due to their far smaller surface area when compared to kafirin microparticles. Thus, kafirin films appear to have potential as a biomaterial. This study also raises awareness that the form of prolamin based biomaterials, (kafirin and zein) should be considered when assessing the safety of such materials. © 2014 Wiley Periodicals, Inc.
Keywords: biocompatibility; film; histology; kafirin; microparticle

Bacterial endophthalmitis associated with a broken and retained small-gauge vitrectomy cannula - Wong, R.W. (Retinal Cases and Brief Reports, 2015)
Purpose: To report a case of bacterial endophthalmitis associated with a retained smallgauge vitrectomy trocar. Methods: Retrospective case report of a 66-year-old woman who underwent 25-gauge vitrectomy surgery for an epiretinal membrane who presented with postoperative bacterial endophthalmitis and hand motions vision 3 weeks later. Results: Aqueous and vitreous biopsy revealed Corynebacterium species sensitive to vancomycin. The patient was initially treated with intravitreal and subconjunctival injections of vancomycin, ceftazidime, and dexamethasone. Surgical exploration during a subsequent vitrectomy surgery revealed a retained, transscleral 25-gauge cannula beneath a subconjunctival abscess. The cannula was removed, and the patient was treated with vitrectomy, debridement and closure of the transscleral wound, and injection of intravitreal antibiotics. Fifteen months of follow-up revealed no recurrence of infection and improvement of vision to 20/150. Conclusion: Although rare, retained small-gauge vitrectomy cannulas may lead to vision threatening ocular infection. Care should be taken to inspect both the wound and the removed trocar system to ensure complete removal of this surgical device. Detailed counts of all surgical equipment should be routinely performed at the conclusion of vitrectomy surgery. © 2015 by Ophthalmic Communications Society, Inc.
Keywords: 25-gauge; Corynebacterium; postvitrectomy complications

Comparative activities of vancomycin, tigecycline and rifampin in a rat model of methicillin-resistant Staphylococcus aureus osteomyelitis - Vergidis, P.; Schmidt-Malan, S.M.; Mandrekar, J.N.; Steckelberg, J.M.; Patel, R. (Journal of Infection, 2015)
Objectives: Implant-associated methicillin-resistant Staphylococcus aureus (MRSA) infections are challenging to treat. We compared antimicrobial activities in a rat model of chronic osteomyelitis in the context of retention of the foreign body without débridement. Methods: MRSA was inoculated into the proximal tibia and a wire implanted. Four weeks after infection, treatment with vancomycin 50mg/kg every 12h, tigecycline 14mg/kg every 12h, rifampin 25mg/kg every 12h, or the combination of vancomycin or tigecycline plus rifampin was administered intraperitoneally for 21 days. Results: MRSA was cultured from all tibias in the control group (median, 6.06 log 10 CFU/g bone). Median bacterial counts (log 10 CFU/g) at 48h post-treatment were 6.16 for vancomycin (p=0.753), 2.29 for vancomycin plus rifampin (p<0.001), 5.90 for tigecycline (p=0.270), 0.10 for tigecycline plus rifampin (p<0.001), and 0.91 for rifampin (p=0.044) treatment. Three deaths were observed in the tigecycline plus rifampin group. Median bacterial counts (log 10 CFU/g) at two weeks post-treatment were 5.65 for vancomycin (p = 0.6), 4.05 for vancomycin plus rifampin (p = 0.105), 5.68 for tigecycline (p = 0.401), 4.05 for tigecycline plus rifampin (p = 0.028), and 5.98 for rifampin (p = 0.297) treatment. Conclusions: Tigecycline plus rifampin resulted in a significant bacterial count decrease, an effect more prominent at 48 h than two weeks after treatment completion. Tigecycline was not well tolerated at the dose studied. © 2015 The British Infection Association.
Keywords: Osteomyelitis; Rifampin; Staphylococcus aureus; Tigecycline; Vancomycin

Surgical Counts in the Delivery Room - Hurley, T.T.; Meyer, A. (JOGNN - Journal of Obstetric, Gynecologic, and Neonatal Nursing, 2015)
Purpose for the Program: An opportunity existed to reduce or eliminate the risk of retained surgical items (RSIs) in response to the Joint Commission's October Sentinel Event Alert regarding RSIs. Within perinatal nursing there is a keen awareness that a discrepancy exists between the approaches to surgical counts in the perioperative suite versus the vaginal delivery room. It is very likely that during vaginal births, the surgical count error rate is greater than the overall 10% to 15% error rate noted by The Joint Commission. Proposed Change: To implement a highly reliable and standardized count process during all vaginal births that was more in line with structured counts of the perioperative suites. Implementation, Outcomes, and Evaluation: Although limited, the literature demonstrated the need to first revise the facility wide count policy and specifically address the count process for vaginal births. Next, informal staff surveys indicated that the existing process lacked clear expectations, identified significant gaps in the process, and confirmed breaks in communication between nursing and provider staff. These surveys also revealed that the team approached the counts for vaginal births in a less formal manner than the surgical counts in the perioperative suite. Based on this information we implemented a standardized counting system that included a defined interdisciplinary communication requisite, streamlined the documentation, and provided global team education. Within 2 months of the completion of phase one training (hands on training) and the policy revision, the count sheet audits demonstrated greater than 95% adherence. After Phase 2 training, which included video demonstration and eLearning, greater than 98% adherence was demonstrated using 100% count sheet and random observed audits. In the 3rd and 4th month of observed audits, 100% adherence was noted, demonstrating normalization of the new process. Implications for Nursing Practice: Primary outcomes included improved communication between health care providers and nurses, count diligence, and standardization of the count culture within the vaginal delivery room. In addition, the process change enhanced patient safety by minimizing the risk of the RSI in the vaginal delivery room. Finally, although not utilized in this process change, there is clearly a need to evaluate the effect of assistive safe count technology during vaginal births. © 2015 AWHONN, the Association of Women's Health, Obstetric and Neonatal Nurses
Keywords: retained surgical items; surgical counts; vaginal birth

Case 15-2015: A 27-year-old man with a nail in the eye - Gupta, R.; Vavvas, D.; Asaad, W.F. (New England Journal of Medicine, 2015)

Invasive Propionibacterium acnes infections in a non-selective patient cohort: clinical manifestations, management and outcome - Tebruegge, M.; Jones, C.; de Graaf, H.; Sukhtankar, P.; Allan, R.N.; Howlin, R.P.; Browning, D.; Schuster, H.; Pallett, A.; Patel, S.; Faust, S.N. (European Journal of Clinical Microbiology and Infectious Diseases, 2015)
An increasing number of reports suggest that Propionibacterium acnes can cause serious invasive infections. Currently, only limited data exist regarding the spectrum of invasive P. acnes infections. We conducted a non-selective cohort study at a tertiary hospital in the UK over a 9-year-period (2003–2012) investigating clinical manifestations, risk factors, management, and outcome of invasive P. acnes infections. Forty-nine cases were identified; the majority were neurosurgical infections and orthopaedic infections (n = 28 and n = 15 respectively). Only 2 cases had no predisposing factors; all neurosurgical and 93.3 % of orthopaedic cases had a history of previous surgery and/or trauma. Foreign material was in situ at the infection site in 59.3 % and 80.0 % of neurosurgical and orthopaedic cases respectively. All neurosurgical and orthopaedic cases required one or more surgical interventions to treat P. acnes infection, with or without concomitant antibiotic therapy; the duration of antibiotic therapy was significantly longer in the group of orthopaedic cases (median 53 vs 19 days; p = 0.0025). All tested P. acnes isolates were susceptible to penicillin, ampicillin and chloramphenicol; only 1 was clindamycin-resistant. Neurosurgical and orthopaedic infections account for the majority of invasive P. acnes infections. Most cases have predisposing factors, including previous surgery and/or trauma; spontaneous infections are rare. Foreign material is commonly present at the site of infection, indicating that the pathogenesis of invasive P. acnes infections likely involves biofilm formation. Since invasive P. acnes infections are associated with considerable morbidity, further studies are needed to establish effective prevention and optimal treatment strategies. © 2014, Springer-Verlag Berlin Heidelberg.

An unusual presentation of hydrochloric acid ingestion: A mystery unraveled - Ganapathy, V.P.; Das, R.R.; Chinnakkannan, S.; Panda, S.S. (Pediatric Emergency Care, 2015)
Background: Unintentional acid ingestion is less commonly encountered than alkali ingestion. The injury develops for hours to days after ingestion and often results in progressively increasing difficulty in airway management. However, gastric perforation is rare. Case: A 3-year-old boy presented to us with an orotonsillopharyngeal membrane and severe upper airway obstruction. Subsequently, he was diagnosed with a case of gastric perforation due to unintentional hydrochloric acid ingestion. He was treated with partial gastrectomy and feeding jejunostomy, and the recovery was good. Conclusions: Unintentional hydrochloric acid ingestion is rare in children. The manifestations masquerade many other clinical conditions, and the diagnosis is difficult in cases in which history of ingestion is not available. Treatment is symptomatic, and emergency surgery is indicated in case of gastrointestinal perforation. Copyright © 2015 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: Gastric perforation; Hydrochloric acid; Tonsillopharyngitis; White membrane

Esophagus perforation and myocardial penetration caused by swallowing of a foreign body leading to a misdiagnosis of acute coronary syndrome: A case report - Erdal, U.; Mehmet, D.; Turkay, K.; Mehmet, I.A.; Ibrahim, N.; Hasan, B. (Journal of Medical Case Reports, 2015)
Introduction: Here we present our clinical experience in a case of esophagus perforation due to the swallowing of a bone piece causing acute angina pectoris and leading to misdiagnosis of acute coronary syndrome. Case presentation: A 73-year-old Caucasian man underwent urgent coronary angiography with possible diagnosis of acute coronary syndrome. His coronary arteries were found to be normal. A computed tomography examination revealed esophagus perforation by a foreign body (a piece of bone), and he underwent urgent left thoracotomy and the foreign body was removed. Conclusions: Sometimes, even a piece of bone within a meal can lead to esophagus perforation, and injure the pericardium and myocardium. The symptoms of esophagus perforation may be confused with acute coronary syndrome due to their similarities and lack of knowledge about the detailed clinical history as shown in our case. Thus, careful consideration of detailed clinical history as well as choosing an appropriate medical imaging modality, such as computed tomography, should always be kept in mind in order to promptly diagnose and start early treatment to reduce mortality. © 2015 Erdal et al.; licensee BioMed Central.
Keywords: Acute coronary syndrome; Esophagus perforation; Foreign body

Extracorporeal laparoscopically assisted resection of a perforated Meckel's diverticulum due to a chicken bone - Nikolopoulos, I.; Ntakomyti, E.; El-Gaddal, A.; Corry, D. (BMJ Case Reports, 2015)
Meckel's diverticulum is the commonest congenital anomaly of the small intestine. It can, however, present acutely relating to a number of complications that may require emergency surgery and possible bowel resection. Perforation is a rare complication and there are only seven cases reported of an inflamed Meckel's diverticulum due to a chicken bone. Laparoscopic repair of Meckel's diverticulum-associated complications has gained popularity over the recent years. We present a case of chicken bone perforation that was treated with laparoscopic-assisted extracorporeal resection of the affected small bowel segment. Copyright 2015 BMJ Publishing Group. All rights reserved.

Laparoscopically detected and nonsurgically managed ileal perforation by an ingested fish bone: A case report - Chandrasinghe, P.C.; Pathirana, C.K. (Journal of Medical Case Reports, 2015)
Introduction: Ileal perforation due to fish bone is a rare event. The condition is difficult to diagnose due to lack of specific clinical features and low sensitivity of imaging techniques. We report a case of ileal perforation by a fish bone that was detected laparoscopically and managed nonsurgically. Case presentation: A 45-year-old Sinhalese man presented with acute onset right iliac fossa pain and fever for three days. On examination, he had significant right iliac fossa tenderness and guarding. His white cell count and C-reactive protein level were elevated and an ultrasound scan was indicative of a bowel mass formation. A clinical diagnosis of acute appendicitis was made and laparoscopic appendicectomy was scheduled. At initial survey, a thin spike-like structure was retrieved from the bowel mass, which was revealed to be a fish bone. Our patient was managed with antibiotics only and did not develop any complications. Conclusions: Ileal perforation due to fish bone is a rare condition that can mimic common conditions like appendicitis. Preoperative diagnosis is rarely made. The slow process of fish bone migration results in concomitant sealing of the perforation, reducing contamination. Use of laparoscopy may be useful in diagnosing this condition and preventing the morbidity of laparotomy in these patients. © 2015 Chandrasinghe and Pathirana; licensee BioMed Central.
Keywords: Ileal perforation; Ingested fish bone; Laparoscopy

Traumatic ocular emergencies: The difficulties associated with their care at the university hospital of brazzaville - Atipo-Tsiba, P.W. (East African Medical Journal, 2015)
Background: In black Africa, the severity of traumatic ocular emergencies (TOE) is increased by a lack of ophthalmologists and often inadequate or even the inexistence of surgical equipment. Objective: To make an inventory of the difficulties associated with the management of TOE at the ophthalmology department of the University Hospital of Brazzaville (UHB). Design: A retrospective study. Setting: The University Hospital of Brazzaville. Subjects: Records selected were those of patients seen for traumatic pathologies that could compromise the visual prognosis and require immediate surgical treatment. The patients seen for injuries of related structures of the eye were excluded. Types of lesion, consultation period, time of surgical treatment, clinical appearance of the eye and visual acuity (VA) at three months were analysed. Results: The frequency of TOE was 1.8%. The average age was 35 ± 4 years old. The average time for consultation and treatment were 35 ± 10 days and 74 ± 5.5 hours. These TOE were: Corneoscleral rupture (63.2%), vitreoretinal iron foreign body (16.8%), retinal detachment (15%), and macula hole (5%). At three months 73.2% of eyes did not see the light, 19.2% had a VA waving from light perception and counting fingers, and for 7.6% the best VA did not exceed three out of ten. Conclusion: In the UHB, the rate of blindness associated with TOE is high. Training of ophthalmologists and adapted surgical equipment should be a priority. © 2015, East African Medical Association. All rights reserved.

Retained foreign body: "Needle in a haystack" - O'Brien, L.; Eyster, K.M.; Hansen, K.A. (Journal of Patient Safety, 2015)
Retained foreign bodies remain an area of potential patient harm. This case describes a retained needle from distant surgery discovered at the time of the needle count after myomectomy. Copyright © 2014 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: Fluoroscopy; Retained foreign bodies; Retained needle

Intraoperative Radiography for Evaluation of Surgical Miscounts - Walter, W.R.; Amis, E.S., Jr.; Sprayregen, S.; Haramati, L.B. (Journal of the American College of Radiology, 2015)
Purpose Retained surgical items result in substantial morbidity, health care-related expense, and legal liability. This study determines the performance of a protocol for locating surgical items after a miscount, in which intraoperative radiography included a radiograph of the unaccounted for item. Methods Institutional review board approval was obtained. In 20,820 operations performed between January 1, 2011 and April 1, 2013, a total of 183 consecutive surgical miscounts occurred, involving 180 patients (97 male, 83 female; median age: 55 years). Departmental protocol mandated that a radiograph of an example of the potentially retained item be taken simultaneously with each patient intraoperative radiograph. Three board-certified radiologists retrospectively reviewed these radiographs and follow-up imaging, achieving consensus on interpretation. Adherence to institutional protocol was assessed. Demographic data, surgical documentation, and clinical follow-up data were recorded. Results The incidence of surgical miscounts was 0.9% (183 of 20,820). Only 9% (17 of 183) were resolved by discovery: outside the patient (8 cases); on intraoperative radiographs (5 cases); incidentally on follow-up radiographs (2 cases); and on retrospective review (2 cases). The false-negative rate was 44% (4 of 9). Neither of the 2 retained needles discovered postoperatively was removed. The procedures most prone to miscounts were: esophagogastrectomy (33%; 2 of 6); liver transplant (18%; 12 of 66); and Whipple procedure (16%; 7 of 44). Needles (65%) and sponges (9%) were the items that were overlooked most often. Adherence to the protocol of imaging an example of a potentially retained item was 91% (167 of 183). Conclusions Despite good adherence to a protocol of imaging the potentially retained items, small needles often were not visualized on intraoperative radiographs and were not subsequently removed, without known adverse events. This finding suggests that intraoperative radiography for small needles may be unnecessary, but further study is required. © 2015 American College of Radiology.
Keywords: Intraoperative radiograph; OR miscount; retained surgical item

Retained foreign body in transplanted liver - Kayaalp, C.; Kirmizi, S.; Kutlu, R.; Yagci, M.A.; Isik, B.; Yilmaz, S. (International Journal of Organ Transplantation Medicine, 2015)
Liver transplantation is a technically complex and long surgical procedure. A large quantity of various materials such as catheters, sutures, needles and clips are frequently used during the procedure. These materials may enter in the liver from the vascular or biliary orifices inadvertently. A 50-year-old patient who had hepatic failure due to HBV underwent a deceased-donor liver transplantation. The deceased donor was a 75-year-old HbsAg+ man. The recipient had subfebrile fever and leukocytosis post-operatively. A control computed tomography revealed a cuneiform ischemic area, and a foreign body inside the right anterior portal vein branch proximal to this ischemic region. A 10-F Nelaton catheter, 5-cm long, was removed from the portal vein by surgery. Retrospectively, we understood that the portal vein was cut during the backtable procedure and the portal vein catheter was replaced with a larger one for better irrigation. Most probably, the original catheter was cut together with the portal vein, and the tip of the catheter was retained in the portal system and migrated into the liver. As far as we know, such a complication of liver transplantation has never been described previously.
Keywords: Foreign body; Liver transplantation; Portal vein; Post-operative complication

Isolated primary amyloidosis of the epiglottis presenting as a long-standing foreign body sensation in throat: A case report - Swain, S.K.; Sahu, M.C. (Journal of Taibah University Medical Sciences, 2015)
Primary amyloidosis of the larynx is a rare benign disease of unknown aetiology. Isolated epiglottic involvement with amyloidosis is an extremely uncommon benign laryngeal pathology and can present with a foreign body sensation in the throat. This lesion should be kept in mind in cases with a long-standing foreign body sensation in the throat. Observation and endoscopic carbon dioxide laser excision are the main methods of treatment. Long-term follow-up is also required because of the slow progressive nature of this disease. © 2015 The Authors. Production and hosting by Elsevier Ltd on behalf of Taibah University.
Keywords: Amyloidosis; Epiglottis; Foreign body sensation in throat

The Hidden Costs of Reconciling Surgical Sponge Counts - Steelman, V.M.; Schaapveld, A.G.; Perkhounkova, Y.; Storm, H.E.; Mathias, M. (AORN Journal, 2015)
Retained surgical sponges are serious adverse events that can result in negative patient outcomes. The primary method of prevention is the sponge count. Searching for sponges to reconcile counts can result in inefficient use of OR time. The purpose of this descriptive study was to estimate the cost of nonproductive OR time (ie, time spent not moving forward with the surgical procedure) spent reconciling surgical sponge counts and the cost of using radiography to rule out the presence of retained sponges. We included 13,322 patient surgeries during a nine-month period. Perioperative personnel required from one to 90 minutes of additional time to reconcile each of 212 incorrect/unresolved counts. The total annualized cost of OR time spent searching for sponges and ruling out the presence of potentially retained sponges using radiography was $219,056. These costs should be included in comprehensive cost analyses when considering alternatives to supplement the surgical count. © 2015 AORN, Inc.
Keywords: Cost; Medical/surgical errors; Patient safety; Retained surgical item; Retained surgical sponge

Successful endoscopic management of gastric perforation caused by ingesting a sharp chicken bone - Shaheen, M.F.; Barrette, P. (International Journal of Surgery Case Reports, 2015)
Introduction Gastrointestinal perforation related to foreign body ingestion is uncommon. Surgical interventions aiming at removal of the offending agent and restoration of bowel continuity are sought when perforations occur. Presentation of case A 68 year old male presented with epigastric abdominal pain and anorexia for 2 days. On examination, he was febrile and had localized epigastric tenderness. Laboratory investigations revealed marked leucocytosis with no other abnormalities. Computed tomography revealed the presence of a foreign body penetrating through the full thickness of the gastric wall with its tip lying adjacent to the pancreatic head. Endoscopic trial to extract the foreign body was successfully carried out. The gastric defect was sealed by applying an endoscopic metallic clip. Discussion Gastric perforations secondary to foreign body ingestion usually follow an elusive clinical course and are rarely diagnosed early in its course. Early diagnosis allows for the utilization of minimally invasive management. Unfortunately, Most reported cases were diagnosed after intra-abdominal processes, such as abscesses, have ensued. Conclusion This case illustrates the importance of early diagnosis of foreign body related gastrointestinal perforations and emphasizes the role of therapeutic endoscopy. © 2015 Published by Elsevier Ltd. on behalf of Surgical Associates Ltd. This is an openaccess article under the CC BY-NC-ND license.
Keywords: Endoscopy; Foreign body; Gastric perforation; Minimally invasive

Foreign body reaction to implantable biosensors: Effects of tissue trauma and implant size - Wang, Y.; Vaddiraju, S.; Gu, B.; Papadimitrakopoulos, F.; Burgess, D.J. (Journal of Diabetes Science and Technology, 2015)
Background: Implantable biosensors for continuous glucose monitoring can greatly improve diabetes management. However, their applications are still associated with some challenges and one of these is the gradual functionality loss postimplantation as a consequence of the foreign body response (FBR). Sensor miniaturization in combination with drug-eluting biocompatible coatings is a promising strategy to enhance in vivo performance. However, limited study has been performed to understand the effect of initial trauma and implant size on foreign body reaction as well as in vivo performance of implantable glucose sensors. Methods: Different initial trauma was induced by implanting composite coated dummy sensors into rats using various sized needles and 3 different-sized dummy sensors were implanted to examine the size effect. Histological evaluation was performed to relate the inflammatory cell counts and foreign body capsule thickness with the implantation needle size and sensor size respectively. The effect of biocompatible coating on the performance of implantable glucose sensors was determined using both coated amperometric glucose sensors and microdialysis probes. Results: The results revealed that the degree of acute inflammation was mainly controlled by the extent of the initial trauma: the greater the trauma, the greater the acute inflammatory response. Implant size did not affect the acute inflammatory phase. However, the extent of chronic inflammation and fibrous encapsulation were affected by sensor size: the smaller the size the less the extent of chronic inflammation and fibrous encapsulation. Glucose sensors implanted using 14 gauge needles showed significantly lower initial in vivo response compared to those implanted using 16 gauge needles. This was not observed for sensors with dexamethasone-eluting biocompatible coatings since inflammation was suppressed. Conclusions: The results of the current study indicate that the extent of the inflammatory response post-sensor implantation varies as a function of the initial tissue trauma as well as the sensor size. Accordingly, miniaturization of implantable biosensors together with the utilization of a drug-eluting biocompatible composite coating may be a promising strategy to achieve longterm reliable continuous glucose monitoring. © 2015 Diabetes Technology Society.
Keywords: Composite coatings; Foreign body response; Implantable glucose biosensors

Radiographic Detectability of Retained Neuropatties in a Cadaver Model - Luo, W.T.; Almack, R.; Mawson, J.B.; Cochrane, D.D. (World Neurosurgery, 2015)
Background Counts are the commonest method used to ensure that all sponges and neuropatties are removed from a surgical site before closure. When the count is not reconciled, plain radiographs of the operative site are taken to determine whether the missing patty has been left in the wound. The purpose of this study was to describe the detectability of commonly used neuropatties in the clinical setting using digital technologies. Methods Neuropatties were implanted into the anterior and posterior cranial fossae and the thoracolumbar extradural space of a mature male cadaver. Four neuropatty sizes were used: 3 × 1 in, 2 × 1/2 in, 1/2 × 1/2 in, and 1/4 × 1/4 in. Neuropatties, with size and location chosen at random, were placed in the surgical sites and anteroposterior/posterior-anterior and lateral radiographs were taken using standard portable digital radiographic equipment. Six clinicians reviewed the digital images for the presence or absence of neuropatties. The readers were not aware of the number and size of the patties that were included in each image. Results The detectability of neuropatties is dependent on the size of the neuropatty's radiopaque marker and the operative site. Neuropatties measuring 2 × 1/2 in and 3 × 1 in were detected reliably regardless of the operative site. 1/4 × 1/4 in neuropatties were poorly detected by neurosurgeons and radiologists in all three operative sites. Readers of various experience and background were similar in their ability to detect neuropatties under these conditions. Conclusions Under simulated operating room conditions and using currently available neuropatties and plain radiograph imaging technology, small 1/4-in and 1/2-in neuropatties are poorly visible/detectable on digital images. © 2015 Elsevier Inc.
Keywords: Cadaver model; Foreign body; Imaging; Neuropatty; Radiopaque; Retained

Literature review and clinical presentation of pelvic impalement by steel bar causing cauda equina syndrome - Ye, J.; Kong, Q.; Yang, T. (Neurosurgery Quarterly, 2015)
Pelvic-penetrating injuries are rare but often spectacular and constitute formidable management problems. Most of the patients suffered from organ or vascular damages; however, neurological lesion in combination with pelvic impalement was seldom reported. This paper highlights a unique case of pelvic impalement through the sacrum with cauda equina injury. A 50-year-old construction worker was impaled in the pelvis because of an accidental fall on a steel bar. The surgical treatment of the injury and the medical management of complications are described in detail. The patient made a good recovery, although he has functional deficits related to the concomitant cauda equina injury. Our case emphasizes the importance of appropriate neurological diagnosis when providing no magnetic resonance imaging but a fuzzy x-ray computed tomography because of a metal object in situ and of individualized surgical management during therapeutic process. © 2013 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: accidental fall; cauda equina syndrome; Penetrating pelvic injury; steel bar; transsacral impalement

Do We Need Heparin Coating for Extracorporeal Membrane Oxygenation? New Concepts and Controversial Positions About Coating Surfaces of Extracorporeal Circuits - Silvetti, S.; Koster, A.; Pappalardo, F. (Artificial Organs, 2015)
Blood contact with surfaces of the extracorporeal circuit provokes the activation of the coagulation system. To improve biocompatibility of the extracorporeal circuit without increasing the risk of bleeding, coatings of artificial surfaces were designed; many of them involve the use of heparin. Data in the literature show that heparin-induced thrombocytopenia is a major issue in the extracorporeal membrane oxygenation scenario, and no relevant benefits have been shown comparing heparin and no-heparin coating. © 2014 International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: Blood coagulation-Extracorporeal membrane; Oxygenation-Heparin-Circuit coating

Allergy to prolene sutures in a dural graft for chiari decompression - Cajigas, I.; Burks, S.S.; Gernsback, J.; Fine, L.; Moshiree, B.; Levi, A.D. (Case Reports in Medicine, 2015)
Allergy to Prolene suture is exceedingly rare with only 5 cases reported in the literature. There have been no such cases associated with neurosurgical procedures. Diagnosis is nearly always delayed in spite of persistent symptomatology. A 27-year-old girl with suspected Ehlers-Danlos, connective tissue disorder, underwent posterior fossa decompression for Chiari Type 1 malformation. One year later, the patient presented with urticarial rash from the neck to chest. Cerebrospinal fluid and blood testing, magnetic resonance imaging, and intraoperative exploration did not suggest allergic reaction. Eventually skin testing proved specific Prolene allergy. After suture material was removed, the patient no longer complained of pruritus or rash. This single case highlights the important entity of allergic reaction to suture material, namely, Prolene, which can present in a delayed basis. Symptomatology can be vague but has typical allergic characteristics. Multidisciplinary approach is helpful with confirmatory skin testing as a vital part of the workup. © 2015 Iahn Cajigas et al.

Wrong-site surgery, retained surgical items, and surgical fires a systematic review of surgical never events - Hempel, S.; Maggard-Gibbons, M.; Nguyen, D.K.; Dawes, A.J.; Miake-Lye, I.; Beroes, J.M.; Booth, M.J.; Miles, J.N.V.; Shanman, R.; Shekelle, P.G. (JAMA Surgery, 2015)
IMPORTANCE Serious, preventable surgical events, termed never events, continue to occur despite considerable patient safety efforts. OBJECTIVE To examine the incidence and root causes of and interventions to prevent wrong-site surgery, retained surgical items, and surgical fires in the era after the implementation of the Universal Protocol in 2004. DATA SOURCES We searched 9 electronic databases for entries from 2004 through June 30, 2014, screened references, and consulted experts. STUDY SELECTION Two independent reviewers identified relevant publications in June 2014. DATA EXTRACTION AND SYNTHESIS One reviewer used a standardized form to extract data and a second reviewer checked the data. Strength of evidence was established by the review team. Data extraction was completed in January 2015. MAIN OUTCOMES AND MEASURES Incidence of wrong-site surgery, retained surgical items, and surgical fires. RESULTS We found 138 empirical studies that met our inclusion criteria. Incidence estimates for wrong-site surgery in US settings varied by data source and procedure (median estimate, 0.09 events per 10 000 surgical procedures). The median estimate for retained surgical items was 1.32 events per 10 000 procedures, but estimates varied by item and procedure. The per-procedure surgical fire incidence is unknown. A frequently reported root cause was inadequate communication. Methodologic challenges associated with investigating changes in rare events limit the conclusions of 78 intervention evaluations. Limited evidence supported the Universal Protocol (5 studies), education (4 studies), and team training (4 studies) interventions to prevent wrong-site surgery. Limited evidence exists to prevent retained surgical items by using data-matrix-coded sponge-counting systems (5 pertinent studies). Evidence for preventing surgical fires was insufficient, and intervention effects were not estimable. CONCLUSIONS AND RELEVANCE Current estimates for wrong-site surgery and retained surgical items are 1 event per 100 000 and 1 event per 10 000 procedures, respectively, but the precision is uncertain, and the per-procedure prevalence of surgical fires is not known. Root-cause analyses suggest the need for improved communication. Despite promising approaches and global Universal Protocol evaluations, empirical evidence for interventions is limited. © 2015 American Medical Association. All rights reserved.

Staphylococcal biofilm formation on the surface of three different calcium phosphate bone grafts: a qualitative and quantitative in vivo analysis - Furustrand Tafin, U.; Betrisey, B.; Bohner, M.; Ilchmann, T.; Trampuz, A.; Clauss, M. (Journal of Materials Science: Materials in Medicine, 2015)
Differences in physico-chemical characteristics of bone grafts to fill bone defects have been demonstrated to influence in vitro bacterial biofilm formation. Aim of the study was to investigate in vivo staphylococcal biofilm formation on different calcium phosphate bone substitutes. A foreign-body guinea-pig infection model was used. Teflon cages prefilled with β-tricalcium phosphate, calcium-deficient hydroxyapatite, or dicalcium phosphate (DCP) scaffold were implanted subcutaneously. Scaffolds were infected with 2 × 103 colony-forming unit of Staphylococcus aureus (two strains) or S. epidermidis and explanted after 3, 24 or 72 h of biofilm formation. Quantitative and qualitative biofilm analysis was performed by sonication followed by viable counts, and microcalorimetry, respectively. Independently of the material, S. aureus formed increasing amounts of biofilm on the surface of all scaffolds over time as determined by both methods. For S. epidermidis, the biofilm amount decreased over time, and no biofilm was detected by microcalorimetry on the DCP scaffolds after 72 h of infection. However, when using a higher S. epidermidis inoculum, increasing amounts of biofilm were formed on all scaffolds as determined by microcalorimetry. No significant variation in staphylococcal in vivo biofilm formation was observed between the different materials tested. This study highlights the importance of in vivo studies, in addition to in vitro studies, when investigating biofilm formation of bone grafts. © 2015, The Author(s).

Bronchiolitis obliterans complicating a pneumothorax after Stevens-Johnson syndrome induced by lamotrigine - Wang, W.-P.; Ni, Y.-F.; Wei, Y.-N.; Li, X.-F.; Cheng, Q.-S.; Lu, Q. (Journal of the Formosan Medical Association, 2015)
Bronchiolitis obliterans (BO) was defined as a nonreversible obstructive lung disease in which the bronchioles are always compressed and narrowed by fibrosis or inflammation. In the severe event of lung collapse after BO, surgical intervention is often recommended, and conservative therapy is thought to be ineffective. Here, we report the case of a 9-year old girl clinically diagnosed as having bronchiolitis obliterans with abrupt occlusion of the right B4b bronchus. After a lamotrigine-induced Stevens-Johnson syndrome (SJS) occurred, she presented with total collapse of the right lung on admission, which was subsequently complicated by a pneumothorax during conservative treatment, but with the re-expansion of the right upper lobe after intervention. The case indicates the possibility of reversing pulmonary atelectasis in BO. Thus, surgery may not be necessary. © 2012.
Keywords: Bronchiolitis obliterans; Lamotrigine; Stevens-Johnson syndrome

Dirofilaria Repens infection in a TEN-year-old boy from the Istria Peninsula: Case report - Glavan, N.; Pećanić, S.; Bosak, A.; Gačanin, L.; Abram, M.; Jonjić, N. (Acta Clinica Croatica, 2015)
Dirofilariasis is a zoonotic infection caused by worms belonging to the genus Dirofilaria. The disease is transmitted by mosquitoes and the hosts are usually dogs. Infections in humans are rare and they usually manifest as a subcutaneous nodule or a conjunctival form. We present a 10-year-old boy with a subcutaneous nodule on his left forearm, who was admitted to the hospital. On examination, the only significant findings were high levels of eosinophils. The pediatrician suspected dirofilariasis and the boy was referred to pediatric surgery. The whole lesion was surgically removed and histopathologic examination confirmed parasitic infection by Dirofilaria repens. Although human dirofilariasis is a rare disease, the number of reported cases has recently increased worldwide. The disease mainly occurs in southern European countries, but has also been described in eastern Europe, Central Asia and Sri Lanka. Croatia is one of the endemic areas for dirofilariasis, especially in the region of the Istria Peninsula. The case presented highlights the requirement for further monitoring of endemic areas in order to establish effective preventive measures.
Keywords: Case report; Croatia; Dirofilaria repens; Dirofilariasis; Zoonoses

Potential use of gallium-doped phosphate-based glass material for periodontitis treatment - Sahdev, R.; Ansari, T.I.; Higham, S.M.; Valappil, S.P. (Journal of Biomaterials Applications, 2015)
This study aimed at evaluating the potential effect of gallium-incorporated phosphate-based glasses towards periodontitis-associated bacteria, Porphyromonas gingivalis, and matrix metalloproteinase-13. Periodontitis describes a group of inflammatory diseases of the gingiva and supporting structures of the periodontium. They are initiated by the accumulation of plaque bacteria, such as the putative periodontal pathogen Porphyromonas gingivalis, but the host immune response such as elevated matrix metalloproteinases are the major contributing factor for destruction of periodontal tissues. Antibacterial assays of gallium-incorporated phosphate-based glasses were conducted on Porphyromonas gingivalis ATCC 33277 using disc diffusion assay on fastidious anaerobe agar and liquid broth assay in a modified tryptic soy broth. In vitro study investigated the effect of gallium on purified recombinant human matrix metalloproteinase-13 activity using matrix metalloproteinase assay kit. In vivo biocompatibility of gallium-incorporated phosphate-based glass was evaluated in rats as subcutaneous implants. Antibacterial assay of gallium displayed activity against Porphyromonas gingivalis (inhibition zone of 22±0.5mm compared with 0mm for control glass, c-PBG). Gallium in the glass contributed to growth inhibitory effect on Porphyromonas gingivalis (up to 1.30 reductions in log10 values of the viable counts compared with control) in a modified tryptic soy broth. In vitro study showed gallium-incorporated phosphate-based glasses inhibited matrix metalloproteinase activity significantly (pâ‰0.01) compared with c-PBG. Evaluation of in vivo biocompatibility of gallium-incorporated phosphate-based glasses in rats showed a non-toxic and foreign body response after 2 weeks of implantation. The results indicate that gallium ions might act on multiple targets of biological mechanisms underlying periodontal disease. Moreover, gallium-incorporated phosphate-based glasses are biocompatible in a rat model. The findings warrant further investigation and will have important clinical implications in the future treatment and management of periodontitis. © 2015 The Author(s).
Keywords: Gallium; matrix metalloproteinase; periodontitis; phosphate-based glasses; Porphyromonas gingivalis

Tympanic membrane gangrene - Surya Prakash, D.R.; Hussain, A. (Indian Journal of Otology, 2015)
Necrosis of tympanic membrane (TM) can be due to infections, drugs, radiation, and foreign body. Strain of group A Streptococcus is associated with acute otitis media or in immunocompromised individuals resulting in TM necrosis. Gangrene of lower limb has been described, but the selective loss of TM due to emboli is an uncommon finding. A 62-year-old female presented with sudden behavioral changes and irrelevant talk. After 2 days, she noticed a discharge from left ear. There was perforation of left TM in posterior superior and inferior quadrant with areas of the black patch around the perforation suggesting a loss of blood supply. Patient was recently detected retrovirus positive with multiple lung shadows. Patient is not on any anti-retroviral medications or other medications. The discharge started 2 days after an episode of left middle cerebral artery infarct due to emboli with no previous history of ear symptoms. Culture of discharge showed no growth. This suggests that TM might have gone for gangrene due to emboli affecting deep auricular artery branch or posterior tympanic branch, which is a branch of the stylomastoid artery.
Keywords: Blood supply; Gangrene; Necrosis; Stylomastoid artery; Tympanic membrane

Deep neck infections in cervical injection drug users - Tamir, S.O.; Marom, T.; Len, A.; Gluck, O.; Goldfarb, A.; Roth, Y. (Laryngoscope, 2015)
Objectives/Hypothesis To characterize deep neck infections (DNI) in adult intravenous drug users (IDUs) who injected illicit substances to their neck, in comparison to DNI in non-IDUs. Study Design Retrospective, cohort study. Methods Data were retrieved from medical charts of adult DNI patients in a secondary hospital during 2000-2013. Clinical, radiologic, and microbial data were extracted and tabulated following categorization into 2 patient groups: IDUs and non-IDUs. Results Of the 136 patients identified with DNI, 20 (15%) were IDUs; of them 80% were males. IDUs were significantly younger than non-IDUs (mean age, 35-‰±-‰10 vs. 44-‰±-‰16 years, P-‰=-‰.01). All IDUs had multiple comorbidities. IDUs presented for medical examination and hospitalization later in the course of their disease, and the most common involved neck spaces were consistent with areas where cervical injections are commonly performed. Abscess formation was more common in IDUs than non-IDUs (16 [80%] vs. 79 [68%], respectively, P-‰=-‰.04). Despite later presentation of IDUs and their higher rate of comorbidities, laboratory data, microbiology cultures, and disease course were similar to non-IDUs. Conclusions Although IDU and non-IDU differ in DNI presentation, both groups had good outcomes. DNI in IDUs frequently evolved into abscesses, and most were found in the anterior triangle deep to sternocleidomastoid (SCM), posterior triangle, and anterior triangle superficial to SCM, in concordance with the injection sites. © 2014 The American Laryngological, Rhinological and Otological Society, Inc.
Keywords: complication; Deep neck infection; foreign body; hepatitis C virus; intravenous drugs users

Deep neck infection: A review of 130 cases in southern China - Yang, W.; Hu, L.; Wang, Z.; Nie, G.; Li, X.; Lin, D.; Luo, J.; Qin, H.; Wu, J.; Wen, W.; Lei, W. (Medicine (United States), 2015)
The study aims to present our experience of the clinical course and management of deep neck infection and try to determine if the characteristics of this kind of infection were similar between the children and adults in southern China. Patients diagnosed with deep neck infection in the Division of Otolaryngology in the First Affiliated Hospital of Sun Yat-sen University between January 2002 and December 2011 were screened retrospectively for demographic characteristics, presenting symptoms, antibiotic therapy before admission, the history of antibiotics abuse, leucocyte count, etiology, bacteriology, disease comorbidity, imaging, treatment, complications, and outcomes. One hundred thirty patients were included and 44 (33.8%) were younger than 18 years old (the children group), 86 patients (66.2%) were older than 18 years old (the adults group). Fever, trismus, neck pain, and odynophagia were the most common symptoms in both groups. Forty children (90.9%) and 49 adults (57.0%) had been treated with broad-spectrum antibiotic therapy before admission. Thirty one children (70.5%) and 24 adults (27.9%) had a history of antibiotics abuse. In children group, the site most commonly involved was the parapharyngeal space (18 patients, 40.9%). In adults group, the site most commonly involved was multispace (30 patients, 34.9%). In children group, the most common cause was branchial cleft cyst (5 patients, 11.4%) and the cause remained unknown in 31 patients (70.5%). In adults group, the most common cause was pharyngeal infection (19 patients, 22.2%). All of the 27 patients with associated disease comorbidity were adults and 17 were diabetes mellitus (DM). Streptococcus viridans was the most common pathogen in both children and adults groups. Eighty six (66.2%) underwent surgical drainage and complications were found in 31 patients (4 children, 27 adults). Deep neck infection in adults is easier to have multispace involvement and lead to complications and appears to be more serious than that in children. Understanding the different characteristics between the children and adults with deep neck infection may be helpful in accurate evaluation and proper management. © 2015 Wolters Kluwer Health, Inc.

Retained surgical needle post myomectomy, an uncommon mishap - Obajimi, G.O.; Oranye, B.C. (African journal of medicine and medical sciences, 2014)
BACKGROUND: Retained foreign bodies are relatively uncommon and probably underreported in the tropics. Largely preventable errors, they cause harm to both the patient and the medical practitioner. CASE PRESENTATION AND MANAGEMENT: A 32 year old primigravida with recurrent lower abdominal pain in pregnancy. She had myomectomy a year earlier at a private hospital in which the endometrium was inadvertently breached. She subsequently had an elective caesarean section at 38 weeks and 2 days gestational age. Intra-operative findings were adhesive bands between the uterus and loops of bowel and a round bodied surgical needle attached by adhesions anteriorly to the lower segment. Her post operative care was uneventful and she was discharged home on the 3rd day post operation. CONCLUSION: Retained surgical foreign body (RSFB) could pose a diagnostic dilemma as in the case of this patient with recurrent lower abdominal pain in pregnancy. Meticulous instrument count should include sutures and needles.

Foreign body response to subcutaneous implants in diabetic rats - Oviedo Socarrás, T.; Vasconcelos, A.C.; Campos, P.P.; Pereira, N.B.; Souza, J.P.C.; Andrade, S.P. (PLoS ONE, 2014)
Implantation of synthetic matrices and biomedical devices in diabetic individuals has become a common procedure to repair and/or replace biological tissues. However, an adverse foreign body reaction that invariably occurs adjacent to implant devices impairing their function is poorly characterized in the diabetic environment. We investigated the influence of this condition on the abnormal tissue healing response in implants placed subcutaneously in normoglycemic and streptozotocin-induced diabetes in rats. In polyether-polyurethane sponge discs removed 10 days after implantation, the components of the fibrovascular tissue (angiogenesis, inflammation, fibrogenesis, and apoptosis) were assessed. Intraimplant levels of hemoglobin and vascular endothelial growth factor were not different after diabetes when compared with normoglycemic counterparts. However, there were a lower number of vessels in the fibrovascular tissue from diabetic rats when compared with vessel numbers in implants from non-diabetic animals. Overall, the inflammatory parameters (neutrophil accumulation - myeloperoxidase activity, tumor necrosis factor alpha, and monocyte chemotactic protein-1 llevels and mast cell counting) increased in subcutaneous implants after diabetes induction. However, macrophage activation (N-acetyl-β-D-glucosaminidase activity) was lower in implants from diabetic rats when compared with those from normoglycemic animals. All fibrogenic markers (transforming growth factor beta 1 levels, collagen deposition, fibrous capsule thickness, and foreign body giant cells) decreased after diabetes, whereas apoptosis (TUNEL) increased. Our results showing that hyperglycemia down regulates the main features of the foreign body reaction induced by subcutaneous implants in rats may be relevant in understanding biomaterial integration and performance in diabetes. ©2014 Socarrás et al.

The prevention effect of poly (l-glutamic acid)/chitosan on spinal epidural fibrosis and peridural adhesion in the post-laminectomy rabbit model - Li, C.; Wang, H.; Liu, H.; Yin, J.; Cui, L.; Chen, Z. (European Spine Journal, 2014)
Purpose: Spinal epidural fibrosis and adhesion are implicated as one of the key factors of failed back surgery syndrome, which may cause dura mater compression or peridural tethering, resulting in persistent backache and leg pain. Various materials or drugs have been used to inhibit formation of epidural fibrosis and reduce the compressive effect on neural structures. Nevertheless, the effects are not satisfied. In this study, we investigated the prevention effect of poly (l-glutamic acid)/chitosan (PLGA/CS) barrier on epidural fibrosis developing post-laminectomy in a rabbit model. Methods: Sixteen rabbits were divided randomly into two equal groups: group A (experimental group, n = 8) and group B (non-treatment group, n = 8). In both groups, total L5–6 laminectomy was performed; further both ligamentum flavum and epidural fat were removed gently. In experimental group, the laminectomy sites were treated with PLGA/CS barriers, while no additional treatment was received in non-treatment group. At 1, 12 and 24 weeks post-surgery, the animals were subjected to magnetic resonance imaging (MRI) evaluation. Following last MRI examination, all rabbits were sacrificed and their spinal columns were totally removed for further macroscopic and histological evaluation. Results: MRI showed that rabbits treated with PLGA/CS barrier at 12 and 24 weeks post-surgery had less epidural fibrosis or scar tissue, peridural adhesion, foreign body reaction and low pressure of spinal cord in comparison with the non-treatment group. In consistence with the radiographic results, macroscopic analysis and histological examination showed that the amount of scar tissue and the extent of epidural adhesion decreased significantly in experimental groups. Concerning the fibroblast density evaluated, the scores were significantly lower in experimental group compared with those in non-treatment group. Conclusion: The results of our study demonstrate that PLGA/CS barrier is effective in inhibiting epidural fibrosis and peridural adhesions in post-laminectomy rabbit model. © 2014, Springer-Verlag Berlin Heidelberg.
Keywords: Epidural fibrosis; Failed back surgery syndrome; Laminectomy; MRI; Poly (l-glutamic acid)/chitosan

Acute appendicitis resulting from rectosigmoid foreign body - Gupta, R.; Mala, T.A.; Gupta, A.; Gupta, A.K.; Paul, R. (Formosan Journal of Surgery, 2014)
A case is presented of a rectosigmoid foreign body causing perforation of the rectosigmoid colon and ulcerating the base of the appendix that resulted in acute appendicitis in a 9-year-old boy, which was initially misdiagnosed. A preoperative diagnosis of acute appendicitis was made after clinical evaluation and abdominal ultrasound, suggestive of the same. An upright abdominal X-ray was also performed to rule out suspected perforation, which showed a radio-opaque shadow in the right iliac region, misdiagnosed as a fecalith. The abdomen was opened for appendectomy and the tip of a pen was immediately observed perforating the sigmoid colon, touching the base of the appendix and ulcerating it, resulting in appendicitis. Subsequently, the pen was removed from the perforation site. Sigmoid colon perforation was repaired and appendectomy was performed. There were no postoperative complications, and the patient was referred for psychiatric evaluation. Histopathology of the specimen confirmed acute appendicitis. © 2014.
Keywords: Acute appendicitis; Foreign body; Pen; Perforation; Rectosigmoid

Behavioral and cellular consequences of high-electrode count Utah Arrays chronically implanted in rat sciatic nerve - Wark, H.A.C.; Mathews, K.S.; Normann, R.A.; Fernandez, E. (Journal of Neural Engineering, 2014)
Objective. Before peripheral nerve electrodes can be used for the restoration of sensory and motor functions in patients with neurological disorders, the behavioral and histological consequences of these devices must be investigated. These indices of biocompatibility can be defined in terms of desired functional outcomes; for example, a device may be considered for use as a therapeutic intervention if the implanted subject retains functional neurons post-implantation even in the presence of a foreign body response. The consequences of an indwelling device may remain localized to cellular responses at the device-tissue interface, such as fibrotic encapsulation of the device, or they may affect the animal more globally, such as impacting behavioral or sensorimotor functions. The objective of this study was to investigate the overall consequences of implantation of high-electrode count intrafascicular peripheral nerve arrays, High Density Utah Slanted Electrode Arrays (HD-USEAs; 25 electrodes mm-2). Approach. HD-USEAs were implanted in rat sciatic nerves for one and two month periods. We monitored wheel running, noxious sensory paw withdrawal reflexes, footprints, nerve morphology and macrophage presence at the tissue-device interface. In addition, we used a novel approach to contain the arrays in actively behaving animals that consisted of an organic nerve wrap. A total of 500 electrodes were implanted across all ten animals. Main results. The results demonstrated that chronic implantation (≤8 weeks) of HD-USEAs into peripheral nerves can evoke behavioral deficits that recover over time. Morphology of the nerve distal to the implantation site showed variable signs of nerve fiber degeneration and regeneration. Cytology adjacent to the device-tissue interface also showed a variable response, with some electrodes having many macrophages surrounding the electrodes, while other electrodes had few or no macrophages present. This variability was also seen along the length of the electrodes. Axons remained within the proximity of the electrode tips at the distances required for theoretically effective stimulation and recording (≤100 μm). Significance. We conclude from these studies that HD-USEAs do not cause overall global effects on the animals, at least up to the two-month period investigated here. These results demonstrate for the first time that the consequences of high-electrode count intrafascicular arrays compare with other peripheral nerve electrodes currently available for clinical or investigational neuromodulation. © 2014 IOP Publishing Ltd.
Keywords: biocompatibility; microelectrodes; nerve electrodes; neural prosthesis; peripheral nerve

Unusual implant-related soft tissue reaction presenting as a swollen leg: A case report - Ozkanli, S.; Soylemez, M.S.; Sahin, A.; Senol, S.; Bilsel, K.; Ceylan, H.H. (Journal of Medical Case Reports, 2014)
Introduction. There are several causes of peri-implant edema, pain, and swelling around implants after orthopedic fixation device application for fracture repair. The most common and well-known reason is infection, however, granulomas associated with foreign body reactions are rarely seen. In this report we present a case of a granulomatous reaction mimicking a hydatid cyst and sarcoma. We emphasize the importance of differential diagnosis in triggering appropriate management of the patient. Our case was unusual; to the best of our knowledge no similar clinical or pathological findings have been reported in current literature. Case presentation. A 56-year-old Turkish man who had been treated for a right femoral fracture via a plate fixation 10 years prior underwent an operation to treat pain and swelling around the plate. A hydatid cyst-like mass was observed during surgery, but subsequent examination revealed that no hydatid cyst was present; both malignancy and infection were also absent. Conclusions: Although infection is generally the first possibility that should be considered in a patient complaining of pain and swelling in the vicinity of an implant, malignancies, hydatid cysts, and (finally) foreign body reactions should also be kept in mind as differential diagnoses. A soft-tissue reaction around a previously implanted plate should be managed carefully. Pre-operative radiological assessment, and biopsy to allow pathological and microbiological examination, should be considered in all suspected cases. © 2014 Ozkanli et al.; licensee BioMed Central Ltd.
Keywords: Granuloma; Malignancy; Orthopedic hardware; Soft-tissue reaction

Influence of weight and structure on biological behavior of polypropylene mesh prostheses placed at the esophageal hiatus - Senft, J.; Gehrig, T.; Lasitschka, F.; Linke, G.R.; Shevchenko, M.; Bruckner, T.; Kenngott, H.G.; Fischer, L.; Müller-Stich, B.P. (Journal of Laparoendoscopic and Advanced Surgical Techniques, 2014)
Background: Experimental knowledge about mesh behavior at the esophageal hiatus is rare, but such information is essential in order to find a safe and effective method of mesh reinforcement. This study aimed to investigate the influence of mesh structure on the biological behavior of polypropylene prostheses placed at the hiatus. Materials and Methods: Twenty-four pigs in three groups of eight underwent implantation of heavyweight small-porous (HW-SP), heavyweight large-porous (HW-LP), or lightweight large-porous (LW-LP) circular polypropylene mesh at the hiatus. Eight weeks later, the meshes were explanted. Macroscopic analysis was performed evaluating mesh deformation, adhesions, and position relative to the hiatal margin. Histological analysis comprised evaluation of foreign body reaction and tissue integration by mononuclear cell count and immunostaining of Ki-67, collagen type I, and collagen type III. Results: No mesh-related complications occurred. Mesh shrinkage was observed within all groups and was the lowest for HW-LP, higher for HW-SP, and highest for LW-LP (13.8% versus 19.5% versus 25.5%; P<.001). The adhesion score was highest for HW-SP, lower for HW-LP, and lowest for LW-LP (11.0 versus 8.0 versus 6.0; P<.001). The collagen type I/III ratio was higher for HW-SP compared with HW-LP and LW-LP (3.1 versus 2.2 versus 1.8; P=.014). Conclusions: Heavyweight polypropylene meshes may be advantageous for application at the hiatus. They provide a solid fixation of the esophagogastric junction by adhesions, which may contribute to a reduction of hernia recurrence. In heavyweight meshes, the large-porous structure is associated with superior form stability, and small-porous meshes are superior with regard to solidity of tissue integration, which may prevent mesh migration. © 2014, Mary Ann Liebert, Inc.

Retropharyngeal abscess complicating 'innocent' foreign body ingestion - Vourexakis, Z.; Konu, P. (BMJ Case Reports, 2014)
An adult patient presented to the emergency department with pharyngeal discomfort on swallowing, persisting several hours after lunch. Transnasal fibre-optic endoscopy performed by an otolaryngologist identified a hypopharyngeal foreign body, and the stalk of a dry leaf partially penetrating the mucosa was easily removed under general anaesthesia. Symptoms regressed completely and the patient was discharged. Two days later he presented again, reporting slight dysphagia without odynophagia or other associated symptoms. Meticulous physical examination by the same otolaryngologist revealed this time a slight asymmetry of the posterior pharyngeal wall. A history of recent pharyngeal trauma and findings on clinical examination raised clinical suspicion of retropharyngeal abscess which was supported by CT scan findings. The diagnosis was confirmed in the operating theatre where a purulent collection was drained under new general anaesthesia. Copyright 2014 BMJ Publishing Group. All rights reserved.

Retained foreign body after chest stab wound - Apiliogullari, B.; Duzgun, N.; Kurtipek, E.; Esme, H. (BMJ Case Reports, 2014)
Foreign bodies may occur after a thoracic trauma, but foreign bodies retained after stab wounds are rare. This paper reports the case of a 20-year-old man who was admitted with the diagnosis of haemothorax following a single stab wound on the chest. One month later, he was referred to the authors' clinic with symptoms of pain and swelling under the left scapula due to a previously overlooked foreign body on the chest wall. Copyright 2014 BMJ Publishing Group. All rights reserved.

Optical imaging of fibrin deposition to elucidate participation of mast cells in foreign body responses - Tsai, Y.-T.; Zhou, J.; Weng, H.; Tang, E.N.; Baker, D.W.; Tang, L. (Biomaterials, 2014)
Mast cell activation has been shown to be an initiator and a key determinant of foreign body reactions. However, there is no non-invasive method that can quantify the degree of implant-associated mast cell activation. Taking advantage of the fact that fibrin deposition is a hallmark of mast cell activation around biomaterial implants, a near infrared probe was fabricated to have high affinity to fibrin. Subsequent invitro testing confirmed that this probe has high affinity to fibrin. Using a subcutaneous particle implantation model, we found significant accumulation of fibrin-affinity probes at the implant sites as early as 15min following particle implantation. The accumulation of fibrin-affinity probes at the implantation sites could also be substantially reduced if anti-coagulant - heparinwas administered at the implant sites. Further studies have shown that subcutaneous administration of mast cell activator - compound 48/80 - prompted the accumulation of fibrin-affinity probes. However, implant-associated fibrin-affinity probe accumulation was substantially reduced in mice with mast cell deficiency. The results show that our fibrin-affinity probes may serve as a powerful tool to monitor and measure the extent of biomaterial-mediated fibrin deposition and mast cell activation invivo. © 2013 Elsevier Ltd.
Keywords: Biocompatibility; Biomaterial; Fibrin; Inflammation; Invivo imaging; Near infrared fluorescence

Intrathoracic gossypiboma - Hameed, A.; Naeem, A.; Azhar, M.; Fatimi, S.H. (BMJ Case Reports, 2014)
Gossypiboma refers to retained sponge or swab in any body cavity after surgery. Although it is a rare occurence, it can lead to various complications which include adhesions, abscess formation and subsequent infections. Gossypiboma occurs as a result of not using radioopaque sponges, poorly performed sponge counts, inadequate wound explorations on suspicion and misread intraoperative radiographs. Therefore, this event can be avoided if strict preventive measures are taken. Moreover, further complications can be avoided following the correct and early diagnosis of gossypiboma. Gossypiboma is an important topic as it carries great medicolegal consequences for the surgeon. We have presented three cases of intrathoracic gossipiboma following previous cardiothoracic surgeries. They presented years after their surgeries, with features varying from patient to patient, ranging from cough and fever to no sypmtoms at all. CT scan only showed a mass lesion in all cases, therefore we proceeded for CT-guided biopsy which was also found to be inconclusive. It was only after entering the thoracic cavity via video-assisted thoracoscopy/ thoracotomy that the diagnosis was made and sponges were taken out successfully. All our cases recovered with no further complications.

Fish bone migration to the urinary bladder after rectosigmoid colon perforation - Cho, M.-K.; Lee, M.-S.; Han, H.-Y.; Woo, S.H. (World Journal of Gastroenterology, 2014)
Fish bones are the most common foreign objects leading to bowel perforation. Most cases are confined to the extraluminal space without penetration of an adjacent organ. However, abscess formation due to the perforation of the rectosigmoid colon by a fish bone can lead to the penetration of the urinary bladder and may subsequently cause the fish bone to migrate into the urinary bladder. In the presented case, a 42-yearold female was admitted for lower abdominal pain. The computed tomography (CT) demonstrated a 5cm pelvic abscess containing a thin and curvilinear foreign body. After conservative management, the patient was discharged. After 1 mo, the subject developed a mechanical ileus. Surgery had to be delayed due to her hyperthyroidism. Migration of the foreign body to the urinary bladder was shown on additional CT. A Yellowish fish bone 3.5 cm in size was removed through intraoperative cystoscopy. The patient was discharged 8 d after the operation without any unexpected event. © 2014 Baishideng Publishing Group Inc. All rights reserved.
Keywords: Fish bone; Foreign body induced bowel perforation; Foreign body ingestion; Rectosigmoid colon perforation; Urinary bladder

An unusual destination for magnetic foreign bodies - Robey, T.E.; Kaimakliotis, H.Z.; Hittelman, A.B.; Walsh, S.A. (Pediatric Emergency Care, 2014)
Rare earth metal magnets (Buckyballs and similar products) remain an important public health risk for children.We report the presentation, course, and treatment of a boy who inserted a string of 30 magnets through his urethra into his bladder and review the diagnostic as well as the therapeutic options for foreign bodies inserted into the pediatric urogenital tract.. Copyright © 2014 by Lippincott Williams &Wilkins.
Keywords: adolescent; foreign bodies; magnets

Carotid-esophageal fistula due to a retained foreign body - Behesthirouy, S.; Kakaei, F. (Asian Cardiovascular and Thoracic Annals, 2014)
We describe a case of carotid-esophageal fistula due to retention of an ingested foreign body in a 65-year-old woman. Late diagnosis resulted in severe hemorrhage and postoperative cerebrovascular accident because of the impossibility of repairing the carotid artery due to severe local inflammation. © The Author(s) 2013 Reprints and permissions: sagepub.co.uk/journalsPermissions.nav.
Keywords: Carotid artery injuries; Esophageal fistula; Foreign bodies; Hematemesis; Hemorrhage; Stroke

Risk factors for retained surgical items: A meta-analysis and proposed risk stratification system - Moffatt-Bruce, S.D.; Cook, C.H.; Steinberg, S.M.; Stawicki, S.P. (Journal of Surgical Research, 2014)
Background Retained surgical items (RSI) are designated as completely preventable "never events". Despite numerous case reports, clinical series, and expert opinions few studies provide quantitative insight into RSI risk factors and their relative contributions to the overall RSI risk profile. Existing case-control studies lack the ability to reliably detect clinically important differences within the long list of proposed risks. This meta-analysis examines the best available data for RSI risk factors, seeking to provide a clinically relevant risk stratification system. Methods Nineteen candidate studies were considered for this meta-analysis. Three retrospective, case-control studies of RSI-related risk factors contained suitable group comparisons between patients with and without RSI, thus qualifying for further analysis. Comprehensive Meta-Analysis 2.0 (BioStat, Inc, Englewood, NJ) software was used to analyze the following "common factor" variables compiled from the above studies: body-mass index, emergency procedure, estimated operative blood loss >500 mL, incorrect surgical count, lack of surgical count, >1 subprocedure, >1 surgical team, nursing staff shift change, operation "afterhours" (i.e., between 5 PM and 7 AM), operative time, trainee presence, and unexpected intraoperative factors. We further stratified resulting RSI risk factors into low, intermediate, and high risk. Results Despite the fact that only between three and six risk factors were associated with increased RSI risk across the three studies, our analysis of pooled data demonstrates that seven risk factors are significantly associated with increased RSI risk. Variables found to elevate the RSI risk include intraoperative blood loss >500 mL (odds ratio [OR] 1.6); duration of operation (OR 1.7); >1 subprocedure (OR 2.1); lack of surgical counts (OR 2.5); >1 surgical team (OR 3.0); unexpected intraoperative factors (OR 3.4); and incorrect surgical count (OR 6.1). Changes in nursing staff, emergency surgery, body-mass index, and operation "afterhours" were not significantly associated with increased RSI risk. Conclusions Among the "common risk factors" reported by all three case-control studies, seven synergistically show elevated RSI risk across the pooled data. Based on these results, we propose a risk stratification scheme and issue a call to arms for large, prospective, and multicenter studies evaluating effects of specific changes at the institutional level (i.e., universal surgical counts, radiographic verification of the absence of RSI, and radiofrequency labeling of surgical instruments and sponges) on the risk of RSI. Overall, our findings provide a meaningful foundation for future patient safety initiatives and clinical studies of RSI occurrence and prevention. © 2014 Elsevier Inc. All rights reserved.
Keywords: Meta-analysis; Retained foreign body; Risk stratification

Primary omental abscess with increased concentrations of carcinoembryonic antigen - Chatzoulis, G.; Pappas, D.; Karagiozopoulos, T.; Moschos, J.; Karapiperis, D.; Barpagiannis, A.; Pantelidou, V.; Makrakis, V.; Pachiadakis, I. (Surgical Infections, 2014)

Flip-flop lung. An unusual etiology of bronchiectasis - Liptzin, D.R.; Fan, L.L.; Stillwell, P.C.; Dannull, K.A.; Fadell, M.F.; Partrick, D.A.; Dishop, M.K. (American Journal of Respiratory and Critical Care Medicine, 2014)

Laparoscopic adjustable gastric band erosion and migration into the proximal jejunum - Creedon, L.; Leeder, P.; Awan, A. (Surgery for Obesity and Related Diseases, 2014)

The best treatment option in colorectal foreign bodies; simplicity: Experience of two centers - Ünver, M.; Öztürk, S.; Ölmez, M.; Kumkumoǧlu, Y.; Zalluhoǧlu, N.; Bozbiyik, O.; Kebapçi, E.; Erol, V.; Doǧan, S.M.; Uǧurlu, L.; Turgut, E.; Karaca, C.; et al. (Acta Medica Mediterranea, 2014)
Introduction: Rectal foreign bodies often cause a serious challenge on the clinician. Objects can be inserted for diagnostic or therapeutic purposes, or self-treatment of anorectal disease, by criminal assault and accident but most commonly, for sexual purposes. We aimed to evaluate patients with foreign bodies in rectum and review the management strategy of these patients in this paper. Materials and methods: The data of all the patients who were treated in Tepecik Education and Research Hospital and Atatürk Education and Research Hospital, General Surgery Departments during a 7 years period between 2006 and 2013 were retrospectively analysed. Results: A total of 36 patients, 33 men and 3 women, were admitted with retained rectal foreign body or associated complications. The age range was from 14 to 71 years. The time to presentation and extraction of the foreign body is a range of 4 hours to 15 days. 8 of 36 patients underwent surgery. Discussion: Colorectal foreign bodies are usually inserted for sexual activity. Physical and rectal examination, rectosigmoidoscopy and plain radiograms should be routinezed for diagnosis and localisation. The first principle in treatment is simplicity. At least 24 hours of observation while eliminating perforation with repeated physical examinations and plain abdominal x rays is necessary for cases whom the extraction of the object achieved via anus.
Keywords: Colorectal; Foreign body; Simplicity

Surgical swab counting: a qualitative analysis from the perspective of the scrub nurse. - D'Lima, D.; Sacks, M.; Blackman, W.; Benn, J. (Journal of perioperative practice, 2014)
The aim of the study was to conduct a qualitative exploration of the sociotechnical processes underlying retained surgical swabs, and to explore the fundamental reasons why the swab count procedure and related protocols fail in practice. Data was collected through a set of 27 semistructured qualitative interviews with scrub nurses from a large, multi-site teaching hospital. Interview transcripts were analysed using established constant comparative methods, moving between inductive and deductive reasoning. Key findings were associated with interprofessional perspectives, team processes and climate and responsibility for the swab count. The analysis of risk factors revealed that perceived social and interprofessional issues played a significant role in the reliability of measures to prevent retained swabs. This work highlights the human, psychological and organisational factors that impact upon the reliability of the process and gives rise to recommendations to address contextual factors and improve perioperative practice and training.

Every wound counts: A case of undiscovered wound in mons pubis resulting in a chronic foreign body granuloma of the abdominal wall - Ramman, S.; Al-Rubayee, H. (International Wound Journal, 2014)
A 33-year-old male patient presented to clinic with a tender, discharging wound at mons pubis area. Three months before, he was a victim in a blast injury and received lifesaving emergency laparotomy at a field hospital in Baghdad, where shrapnel was removed from the abdomen and he was subsequently discharged. We present this unusual case of chronic wound from an undiscovered injury that was not formally explored at initial treatment, highlighting the importance of systematic exploration of all wounds particularly in sensitive body areas, despite cultural barriers both for the assessing clinicians and for the patients in that part of the world. © 2014 Medicalhelplines.com Inc and John Wiley & Sons Ltd.
Keywords: Blast injury; Foreign body reaction; Granuloma; Shrapnel

Intra-abdominal abscess formation from the ingestion of a fish bone - Mannu, G.S.; Pawelec, K. (BMJ Case Reports, 2014)

Retained surgical sponges: Findings from incident reports and a cost-benefit analysis of radiofrequency technology - Williams, T.L.; Tung, D.K.; Steelman, V.M.; Chang, P.K.; Szekendi, M.K. (Journal of the American College of Surgeons, 2014)
Background Retained surgical items (RSIs) are serious events with a high potential to harm patients. It is estimated that as many as 1 in 5,500 operations result in an RSI, and sponges are most commonly involved. The adverse outcomes, additional medical care needed, and medico-legal costs associated with these events are substantial. The objective of this analysis was to advance our understanding of the occurrence of RSIs, the methods of prevention, and the costs involved. Study Design Incident reports entered into the University HealthSystem Consortium (UHC) Safety Intelligence database on incorrect surgical counts and RSIs were analyzed. Reported cases of retained surgical sponges at organizations that use radiofrequency (RF) technology and those that do not were compared. A cost-benefit analysis on adopting RF technology was conducted. Results Five organizations that implemented RF technology between 2008 and 2012 collectively demonstrated a 93% reduction in the rate of reported retained surgical sponges. By comparison, there was a 77% reduction in the rate of retained sponges at 5 organizations that do not use RF technology. The UHC cost-benefit analysis showed that the savings in x-rays and time spent in the operating room and in the medical and legal costs that were avoided outweighed the expenses involved in using RF technology. Conclusions Current standards for manual counting of sponges and the use of radiographs are not sufficient to prevent the occurrence of retained surgical sponges; our data support the use of adjunct technology. We recommend that hospitals evaluate and consider the use of an adjunct technology. © 2014 by the American College of Surgeons.
Keywords: Abbreviations and Acronyms; Centers for Medicare and Medicaid Services; CMS; operating room; OR; Patient Safety Organization; PSO; radiofrequency; radiofrequency identification systems; retained surgical item; retained surgical sponge; RF; RFID; RSI; RSS

Identification of the cause of severe skin infection by Fournier transform infrared spectroscopy: A case of Fournier's gangrene caused by fish bone - Shimizu, T.; Harada, K.; Akazawa, S.; Yamaguchi, M.; Inozume, T.; Kawamura, T.; Shibagaki, N.; Momosawa, A.; Shimada, S. (Journal of Dermatology, 2014)
Fournier's gangrene (FG) is an infrequent but highly lethal infection. Here we report a 74-year-old man who presented with genital swelling and severe malaise. Based on the physical and imaging examination results, the diagnosis of FG was confirmed. Intraoperative findings showed dirty necrosis of soft tissue, and a splinter-shaped foreign body was found in the perirectal region. The foreign body was thought to be the cause of the condition, and it was analyzed using Fourier transform infrared spectroscopy. We found that the foreign body was a mixture of calcium phosphate and protein, suggesting that the splinter was a bone. Moreover, during the medical interview, the patient mentioned about intake of fish around the time of onset of symptoms. Therefore, to confirm the results of the analysis, DNA was extracted from the foreign body, and genomic PCR with subsequent sequence analysis was performed. The DNA sequence was identical to that of Oncorhynchus kisutch, a salmon that is a very popular food in Japan. On the basis of these findings, we concluded that FG in this case was caused by the penetration into the rectum of an accidentally ingested fish bone. Although some cases of intra-abdominal abscess due to accidental ingestion of fish bone have been reported, FG caused by fish bone is extremely rare. © 2014 Japanese Dermatological Association.
Keywords: bacterial infection; fish bone; foreign body; Fourier transform infrared spectroscopy; Fournier's gangrene

Swab and instrument count practice: Ways to enhance patient safety - Smith, Y.; Burke, L. (British Journal of Nursing, 2014)
This article presents the results of an audit of swab and instrument count practices in the operating department of a large hospital NHS Trust in South East England. A literature review of the subject is presented followed by the methodology used including questionnaires and observation of practice. Findings are discussed in terms of compliance with the department's swab and instrument count policy and observed practice mapped against the recommendations for best practice in the literature. The findings show that audit of practice is still treated with suspicion by many and that a number of practices of scrub and circulating personnel in operating theatres need to be improved. Recommendations are made related to improving staff development in the department and introducing clinical supervision as one way to provide support for colleagues to reflect on their practice and change to more evidence-based practices in the operating department. © 2014 MA Healthcare Ltd.
Keywords: Clinical audit; Clinical supervision; Evidence-based practice; Operating department; Swab counts

Esophageal rupture complicated by acute pericarditis - Duman, H.; Bakirci, E.M.; Karadaʇ, Z.; Uʇurlu, Y. (Turk Kardiyoloji Dernegi Arsivi, 2014)
Esophageal perforation is a serious condition with a high mortality rate. Delayed detection of esophageal perforation may result in devastating complications such as mediastinitis and pericarditis. Esophageal perforation is rarely due to aspiration of foreign bodies. Here we report the case of a 59-year-old male patient with complicated esophageal perforation due to ingestion of a chicken bone, whose first signs are considered to be acute non-specific pericarditis. © 2014 Turkish Society of Cardiology.
Keywords: Esophageal perforation; Pericarditis

Temporary epicardial pacing wire migrating to and exiting from the jaw - Kondo, T.; Hirota, M.; Hoshino, J.; Takahashi, Y.; Notomi, Y.; Isomura, T. (Annals of Thoracic Surgery, 2014)
A 63-year-old woman underwent cardiac surgery, with atrial and ventricular temporary epicardial pacing wires being placed at the end of the procedure. Four months after the operation, the patient experienced tooth decay and underwent a tooth extraction. Thereafter, the patient developed an infected, swollen neck; computed tomography revealed that one of the temporary pacing wires had migrated into her neck. The patient was readmitted for removal of the wire, but it spontaneously exited through the skin of the lower jaw; the infection was resolved with intravenous antibiotic therapy. © 2014 The Society of Thoracic Surgeons.

Gastric perforation by a foreign body presenting as a pancreatic pseudotumour - Williams, H.E.; Khokhar, A.A.; Rizvi, M.; Gould, S. (International Journal of Surgery Case Reports, 2014)
INTRODUCTION Foreign body ingestion rarely causes complications, though it can pose a significant diagnostic challenge. Perforation, particularly of more muscular viscera, can present insidiously with a wide range of differential diagnoses. PRESENTATION OF CASE Here we present a case of 75 year-old woman presenting with chest and epigastric pain. Initial imaging suggested a pancreatic lesion. Despite appropriate treatment she deteriorated clinically, and following urgent laparotomy a duck bone fragment was found to have perforated the lesser curvature of the stomach and embedded within the liver causing subhepatic abscess formation and associated inflammation. DISCUSSION There are a number of examples of insidious presentations of gastrointestinal perforation. However, we have found only one other case of a perforation presenting as a pancreatic pseudotumour, and ours is the first to have been successfully managed by removal of the foreign body and drainage of the abscess alone. CONCLUSION A high level of suspicion is required to make the correct diagnosis in cases such as these where the symptoms are not clear-cut. Thorough review and discussion of imaging prior to surgical treatment is essential to prevent unnecessary intervention. © 2014 The Authors.
Keywords: Foreign body; Perforation

Inadvertent intravesicular placement of a vaginal contraceptive ring: A case report and review of literature - Baker, K.S.; Barish, M. (Journal of Radiology Case Reports, 2014)
The NuvaRing® is a deformable, ring-shaped hormonal contraceptive device which is typically vaginally self-inserted by the patient. While there are several potential side effects of usage, essentially all of them result from hormone delivery. Complications from incorrect placement are rare. We present the case of a 31 year old female who presented to our emergency department after being unable to retrieve a NuvaRing® for its scheduled removal. CT scan showed a hypodense intravesicular NuvaRing® which the patient had inadvertently placed transurethrally 3 weeks prior. Cystoscopy was performed and retrieval using a 3-pronged grasper was eventually successful after several failed attempts with an alligator grasper. Our purpose in presenting this case is to introduce the reader to a rare complication of incorrect NuvaRing® placement, explain how this complication may occur as a result of NuvaRing® construction/functionality, describe how alternative cystoscopic instruments may aid in cystoscopic retrieval, and review the 3 other case reports of intravesicular NuvaRing® placement to discuss the utility of various imaging modalities when clinical suspicion of the complication is high. © 2014, EduRad. All rights reserved.
Keywords: Contraception radiology; Contraceptive ring; CT imaging; Foreign body; Intravesicular foreign body; NuvaRing

Haptic breakage after transscleral fixation of a single-piece acrylic intraocular lens - Tanaka, H.; Fujinami, K.; Watanabe, K.; Noda, T.; Akiyama, K. (Case Reports in Ophthalmology, 2014)
Purpose: To report the case of a patient with a damaged haptic of an acrylic intraocular lens (IOL) after transscleral IOL fixation. Methods: This is a retrospective and descriptive case report. Results: A 40-year-old man presented with sudden visual loss in the left eye. He had undergone phacoemulsification/aspiration and IOL implantation 3 years previously and IOL repositioning with transscleral fixation 2 years before the initial visit. His visual acuity was 0.3 in the left eye due to corneal edema caused by a foreign body, i.e., the severed haptic tip of the single-piece acrylic IOL, which was surgically removed. The IOL itself was tilted and therefore explanted. The surface of the tip of the haptic suggested that the monofilament suture thread had exerted continuous force across the haptic. Conclusions: The haptics of acrylic IOLs can be damaged after transscleral fixation. © 2014 S. Karger AG, Basel.
Keywords: Acrylic intraocular lens; Intraocular lens; Intraocular lens damage; Transscleral fixation

Fever after redo Nissen fundoplication with hiatal hernia repair - Sharp, N.E.; Alemayehu, H.; Desai, A.; Holcomb III, G.W.; St. Peter, S.D. (Journal of Surgical Research, 2014)
Background Fevers often arise after redo fundoplication with hiatal hernia repair. We reviewed our experience to evaluate the yield of a fever work-up in this population. Methods We performed a retrospective review of children undergoing redo Nissen fundoplication with hiatal hernia repair between December 2001 and September 2012. Temperatures and fever evaluations of those children receiving a mesh repair were compared with those without mesh. A fever defined as temperature ≥38.4°C. Results Fifty one children received 46 laparoscopic, 4 open, and 1 laparoscopic converted to open procedures. Biosynthetic mesh was used in 25 children whereas 26 underwent repair without mesh. A fever occurred in 56% of those repaired with mesh compared with 23.1% without mesh (P = 0.02). A fever evaluation was conducted in 32% of those with mesh compared with 11.5% without mesh (P = 0.52). A urinary tract infection was identified in one child after mesh use and an infection was identified in two children without mesh, one pneumonia and one wound infection (P = 1). In those repaired with mesh, there was no significant difference in maximum temperature. Conclusions Fever is common after redo Nissen fundoplication with hiatal hernia repair and occurs more frequently, and with higher temperatures in those with mesh. Fever work-up in these patients is unlikely to yield an infectious source and is attributed to the extensive dissection during the redo procedure. © 2014 Elsevier Inc. All rights reserved.
Keywords: Fever; Hiatal hernia; Mesh; Nissen fundoplication; Pediatric

Polypropylene, polyester or polytetrafluoroethylene—is there an ideal material for mesh augmentation at the esophageal hiatus? Results from an experimental study in a porcine model - Müller-Stich, B.P.; Senft, J.D.; Lasitschka, F.; Shevchenko, M.; Billeter, A.T.; Bruckner, T.; Kenngott, H.G.; Fischer, L.; Gehrig, T. (Hernia, 2014)
Purpose: Knowledge about the influence of underlying biomaterial on behavior of surgical meshes at the esophageal hiatus is rare, but essential for safe and effective hiatal hernia surgery. This study aimed to characterize the influence of polymer material on mesh behavior at the hiatus. Methods: 24 pigs in three groups of eight underwent implantation of either polypropylene (PP), polyester (PET) or polytetrafluoroethylene (PTFE) mesh placed circularly at the esophageal hiatus. After 8 weeks, necropsy and measurements were performed evaluating mesh deformation, adhesion formation, fixation of the esophagogastric junction and mesh position. Foreign body reaction was assessed by mononuclear cell count and immunostaining of Ki-67. Tissue integration was evaluated by immunostaining of type I and type III collagen fibers. Results: Mesh shrinkage was the highest for PTFE, lower for PP and the lowest for PET (34.9 vs. 19.8 vs. 12.1 %; p = 0.002). Mesh aperture for the esophagus showed an enlargement within all groups, which was highest for PTFE compared to PP and PET (100.8 vs. 47.0 vs. 35.9 %; p = 0.001). The adhesion score was highest for PP, lower for PTFE and the lowest for PET (11.0 vs. 9.5 vs. 5.0; p = 0.001) and correlated positively with the score of esophagogastric fixation (rs = 0.784, p < 0.001). No mesh migration, erosion or stenosis of the esophagus occurred. Evaluation of foreign body reaction and tissue integration showed no significant differences. Conclusions: In this experimental setting, PP-meshes showed the most appropriate characteristics for augmentation at the hiatus. Due to solid fixation of the esophagogastric junction and low shrinkage tendency, PP-meshes may be effective in preventing hiatal hernia recurrence. The use of PTFE-mesh at the hiatus may be disadvantageous due to high shrinkage rates and correlating enlargement of the aperture for the esophagus. © 2014, Springer-Verlag France.
Keywords: Hiatal hernia; Polyester; Polypropylene; Polytetrafluoroethylene; Surgical mesh

Septic pericarditis and myocardial abscess in an English Springer spaniel - Fraga Veloso, G.; Fraga Manteiga, E.; Trehy, M.; Freeman, A.; McConnell, J.F.; Dukes McEwan, J. (Journal of Veterinary Cardiology, 2014)
Septic pericarditis and myocardial abscess are rare conditions in dogs. They are usually caused by foreign bodies, penetrating wounds, systemic infections or extension of local infections such as endocarditis, pleuritis or pulmonary infections to the myocardial tissue. Here we report a septic pericardial effusion and myocardial abscess in a young English Springer spaniel presenting with a long history of pyrexia and lethargy. No cause could clearly be identified although a penetrating injury or dissolving foreign body was highly suspected. The patient was successfully treated with a surgical approach in combination with broad spectrum antibacterials resulting in resolution of clinical signs without recurrence of the infection. © 2013 Elsevier B.V. All rights reserved.
Keywords: Canine; Myocarditis; Pericardial

Ingestion of multiple magnets: The count does matter - Kim, Y.; Hong, J.; Moon, S.-B. (Journal of Pediatric Surgery Case Reports, 2014)
Ingestion of multiple magnets poses a particular risk for various intraabdominal complications in children. We herein report a case of ingestion of multiple magnets, of which 3 were spontaneously expelled, and the remaining magnets were surgically removed. Since the total amount of ingestion was unknown upon presentation and the remaining intraabdominal magnets failed to pass after 24 h, emergency surgery was performed. Two magnets sandwiched the bowel walls and formed a jejunoileal fistula. There was no peritoneal contamination. We found that not all the ingested multiple magnets attracted each other, and multiple magnets could appear as single material on a plain radiograph. Confirming the exact count of ingested magnets is important; if the count is in doubt or two or more attachments are evident, prompt surgical intervention is warranted. © 2014 The Authors. Published by Elsevier Inc. All rights reserved.
Keywords: Count; Ingestion; Magnets

How do absorbable sutures absorb? A prospective double-blind randomized clinical study of tissue reaction to polyglactin 910 sutures in human skin - Cartmill, B.T.; Parham, D.M.; Strike, P.W.; Griffiths, L.; Parkin, B. (Orbit, 2014)
Objective: To compare the tissue reaction produced by 2 gauges of implanted polyglactin 910(Vicryl) suture material in human skin. Methods: A prospective, double masked, parallel randomized IRB approved clinical trial. Consecutive patients with involutional entropion and horizontal eyelid laxity were randomly allocated to 5/0 or 7/0 gauge test suture groups. Symptoms were alleviated during the wait for definitive surgery by placement of eyelid everting sutures. After 28 days, surgical entropion correction including eyelid wedge excision was achieved. Histological analysis was carried out, masked to the suture gauge used, on the excised eyelid containing one of the temporary everting sutures. Both patient and analyst were masked to the suture group. The four primary outcome measurements were granuloma outer diameter, central cellular diameter, giant cell number and area of fibrous coat and a statistical comparison made between suture gauge groups. Results: 21 patients were allocated to each group, and histological analysis was possible in 36 patients. Significant suture-related granulomatous inflammatory reactions were found in all specimens. Medians of the measurements for 5/0 and 7/0 gauge sutures, respectively, were 0.855mm versus 0.387mm granuloma outer diameter (p=0.0001); 0.464mm versus 0.250mm central cellular element diameter (p=0.0003); 0.194mm2 versus 0.053mm2 fibrous coat area (p=0.0009) and 0.8 versus 1.2 giant cell number (p=0.7511). Conclusions: Polyglycolic acid sutures elicit a significant foreign body inflammatory response proportional to suture gauge. This reaction may be minimized by early suture removal. The study validates a novel and ethical approach to the examination of human skin response to implanted suture material.
Keywords: Human polyglactin response; Polyglactin tissue reaction; Polyglactin-induced scarring; Stitch granuloma; Suture granuloma

Nephron-saving surgery for abscess of renal allograft using radiofrequency bipolar sealer - Yildiz, B.D. (ASAIO Journal, 2014)
Thousands of patients with renal disease are on waiting lists for kidney transplant. Survival and quality of life on hemodialysis are much lower than that after renal transplantation. Renal allografts are extremely valuable and worth saving at all costs. Many complications can be seen after organ transplants on short and long term as rejection, vascular compromise, and infection. There are various reports on partial nephrectomy after renal transplant secondary to de novo masses in the renal allograft. Here, we present a case where we used radiofrequency bipolar sealer for partial nephrectomy for necrotic abscess of the renal allograft. We successfully saved the allograft with partial nephrectomy despite parenchymal infection and necrosis. © 2014 by the American Society for Artificial Internal.
Keywords: Partial nephrectomy; radiofrequency; renal transplantation

Multi drug resistant escherichia coli forming intra-abdominal abscess in a case of gossypiboma: Case report and review of literature - Ansari, M.A.A.; Bhattacharyya, S.; Sarfraz, A.; Jaiswal, N.K.; Kumar, M. (Research Journal of Pharmaceutical, Biological and Chemical Sciences, 2014)
Gossypiboma is a mass-like lesion due to retained cotton swab in abdominal cavity following any operation or exploratory procedure. It is not very uncommon, occurring in about 1 in 1500 operations worldwide. It can either become a fibrotic nodular mass or develop into an abscess. Here we describe abscess formed following gossypiboma development in a young female following Caesarian section which was done in a private hospital.
Keywords: Escherichia coli; Gossypiboma; Multi drug resistant

Colonic basidiobolomycosis in a child: Report of a culture-proven case - Zabolinejad, N.; Naseri, A.; Davoudi, Y.; Joudi, M.; Aelami, M.H. (International Journal of Infectious Diseases, 2014)
Basidiobolomycosis is a rare fungal disease caused by Basidiobolus ranarum, which is endemic in tropical and subtropical regions of Africa, Asia, and Latin America. Gastrointestinal basidiobolomycosis poses diagnostic difficulties due to the non-specific clinical presentation and absence of predisposing factors. Eight pediatric cases of the disease have been reported recently from Iran, but none of these, or most of the other cases reported in the literature, has been proven by culture, which is the gold standard method for diagnosis. We present a case of culture-proven colonic basidiobolomycosis that occurred in a 3-year-old boy. The outcome was successful following surgical excision and antifungal therapy with posaconazole. © 2014 The Authors.
Keywords: Basidiobolomycosis; Child; Gastrointestinal; Posaconazole

When to do paediatric gastrointestinal endoscopy? - Ahmed, M.; Karupaiah, A. (Paediatrics and Child Health (United Kingdom), 2014)
Over the last few decades, paediatric gastroenterology has rapidly developed into a well-established sub-specialty. Improvements in training and equipment have led to enhanced safety with fewer complications following endoscopies. In specialized units, diagnostic and therapeutic upper gastrointestinal endoscopy and proctosigmoidoscopy/colonoscopy are regularly performed under conscious sedation or general anaesthesia. Emerging guidelines and new advances in the diagnostic tools are being incorporated into routine paediatric gastrointestinal endoscopy practice. © 2014 Elsevier Ltd.
Keywords: Children; Colonoscopy; Criteria; Endoscopy; Gastrointestinal tract

Decreased granulomatous reaction by polyurethane-coated stent in the trachea - Matsui, H.; Hiroma, T.; Hasegawa, H.; Ogiso, Y. (Pediatrics International, 2014)
Background Reducing granulomatous reaction for stent implantation is important for the treatment of tracheobronchomalacia because formation of granuloma leads to refractory complication causing further respiratory distress. The purpose of this study was to clarify granulomatous reaction of newly innovated coated stents compared to non-coated metal stents. Methods Materials and animal experiments were performed using the newly invented metallic stent (laser-cut stainless steel with a coating of polyurethane). In the materials experiment, the correlation between the holding force and deformity was tested by a compressor. In the animal examination, coated stents were orally implanted into the trachea in five rabbits, while non-coated stents were implanted in another five rabbits. After 3 weeks' observation, the inner diameter was measured by 3-D computed tomography, and the number of granulation tissues was counted by bronchofiberscope. Histological investigation followed in both groups. Results In the materials experiment, new stents demonstrated a holding force similar to stainless steel stents. In the animal experiment, no difference was found in the inner diameter of the coated and non-coated stent groups (5.70 ± 0.17 vs 5.60 ± 0.27, P = 0.07). However, the number of granulation tissues was higher in non-coated stents than in coated stents (1.60 ± 0.55 vs 0.40 ± 0.55, P < 0.01). Histological investigation showed direct attachment of metal to the tracheal wall around the non-coated stents where epithelial structure was destroyed, while tracheal epithelia were preserved in the group of coated stents. Conclusions The new polyurethane-coated metallic stent maintains enough holding force, and reduces histobiological reaction to foreign bodies in this experiment. © 2014 Japan Pediatric Society.
Keywords: airway; collapse; granulation tissue; stent implantation; tracheobronchomalacia

Intraluminal duodenal diverticulum in a child concomitant with an entrapped coin and a duodenal polyp - Peng, H.-L.; Su, C.-T.; Chang, C.-Y.; Lau, B.-H. (Formosan Journal of Surgery, 2014)
Intraluminal duodenal diverticulum (IDD) is a rare congenital anomaly. We present the report of an 8-year-old girl who had an entrapped coin in an IDD for 3 years that was associated with recurrent pancreatitis. Besides, a duodenoduodenal intussusception was found during the course of investigation and it seemed that a concomitant duodenal polyp contributed to the development of the intussusception. In view of the rarity of each of the aforementioned situations and the improbability of these conditions occurring together, this unusual and possibly unique case is therefore reported here. © 2014 .
Keywords: Coin; Duodenal diverticulum; Intussusception; Pancreatitis; Polyp

Long term behavior of biological prostheses used as abdominal wall substitutes - Pascual, G.; Sotomayor, S.; Pérez-López, P.; Buján, J.; Bellón, J.M. (Histology and Histopathology, 2014)
Background. Despite their degradation in the host organism, the benefits of collagen bioprostheses remain unclear. This study addresses the absorption and long-term host tissue incorporation of several collagen biomeshes. Material and methods. Partial ventral hernial defects created in the abdominal wall of rabbits were repaired using the crosslinked meshes Permacol® or CollaMend®, or the non-crosslinked Surgisis®, Tutomesh® or Strattice®. After 90 and 180 days of implant, morphological studies and morpho-metric analysis of the thickness of the meshes were performed. Immunofluorescence confocal microscopy combined with differential interference contrast (DIC) imaging was used to distinguish newly formed collagen from that comprising the mesh. The macrophage response was examined by immunohisto-chemistry. Results. At 90 days, the thinner non-crosslinked biomeshes Tutomesh and Surgisis were more fully degraded with much of their collagen replaced with loose connective tissue. By 180 days, both implants had been practically fully absorbed. In contrast, in Strattice only the outermost third was infiltrated by neoformed tissue. On both surfaces of the crosslinked meshes, a fibrous capsule with host cells lining its perimeter was observed at both time points, though at 180 days these cells had penetrated the mesh interior. At both implant times, Strattice showed the higher expression of collagen type I while collagen III expression was similar for all the meshes. The non-crosslinked materials elicited lower macrophage counts at both time points, significantly so for Strattice. The macrophage response decreased over time for all the meshes but Surgisis. Conclusions. Strattice, the thicker, more compacted non-crosslinked mesh showed the best balance between tissue incorporation and absorption while eliciting a minimal foreign-body reaction in the long-term.
Keywords: Abdominal wall repair; Bioprosthesis; Collagen mesh; Hernia repair

Platelet function inhibitors and platelet function testing in neurointerventional procedures - Gandhi, C.D.; Bulsara, K.R.; Fifi, J.; Kass-Hout, T.; Grant, R.A.; Almandoz, J.E.D.; English, J.; Meyers, P.M.; Abruzzo, T.; Prestigiacomo, C.J.; Powers, C.J.; Lee, S.-K.; et al. (Journal of NeuroInterventional Surgery, 2014)

Chronic vaginal discharge and left leg edema after a transobturator tape procedure - Kim, T.-H.; Lee, H.-H.; Kim, J.-M. (International Urogynecology Journal and Pelvic Floor Dysfunction, 2014)
We report on a patient who underwent total vaginal hysterectomy for urinary incontinence 8 years previously with a sling operation using transobturator tape (TOT). She was admitted to our hospital after complaints of vaginal discharge, foul odor, and bleeding, left thigh pain, and edema. Magnetic resonance imaging (MRI) and computed tomography (CT) revealed a fistula tract fromthe vagina or urethra with remnant sling tape. We removed the remnant tape using intraoperative ultrasonography. This case exemplifies the rare occurrence of a vaginal fistula extending to the obturator, adductor, and pectineus muscles combined with myositis after TOT placement. It is important that urogynecologists recognize that TOT procedures may result in complications accompanied by common recurrent vaginal symptoms, such as vaginal odor and spotting, which can be identified by MRI or CT. © The International Urogynecological Association 2013.
Keywords: Mesh exposure; Transobturator tape; Vagina fistula

Biomechanics and biocompatibility of woven spider silk meshes during remodeling in a rodent fascia replacement model - Schäfer-Nolte, F.; Hennecke, K.; Reimers, K.; Schnabel, R.; Allmeling, C.; Vogt, P.M.; Kuhbier, J.W.; Mirastschijski, U. (Annals of Surgery, 2014)
OBJECTIVE:: The aim of this study was to investigate biomechanical and immunogenic properties of spider silk meshes implanted as fascia replacement in a rat in vivo model. BACKGROUND:: Meshes for hernia repair require optimal characteristics with regard to strength, elasticity, and cytocompatibility. Spider silk as a biomaterial with outstanding mechanical properties is potentially suitable for this application. METHODS:: Commercially available meshes used for hernia repair (Surgisis and Ultrapro) were compared with handwoven meshes manufactured from native dragline silk of Nephila spp. All meshes were tied onto the paravertebral fascia, whereas sham-operated rats were sutured without mesh implantation. After 4 or 14 days, 4 weeks, and 4 or 8 months, tissue samples were analyzed concerning inflammation and biointegration both by histological and biochemical methods and by biomechanical stability tests. RESULTS:: Histological sections revealed rapid cell migration into the spider silk meshes with increased numbers of giant cells compared with controls with initial decomposition of silk fibers after 4 weeks. Four months postoperatively, spider silk was completely degraded with the formation of a stable scar verified by constant tensile strength values. Surgisis elicited excessive stability loss from day 4 to day 14 (P < 0.001), with distinct inflammatory reaction demonstrated by lymphocyte and neutrophil invasion. Ultrapro also showed decreasing strength and poor elongation behavior, whereas spider silk samples had the highest relative elongation (P < 0.05). CONCLUSIONS:: Hand-manufactured spider silk meshes with good biocompatibility and beneficial mechanical properties seem superior to standard biological and synthetic meshes, implying an innovative alternative to currently used meshes for hernia repair. © 2013 by Lippincott Williams & Wilkins.
Keywords: Biomaterial; degradation; hernia mesh; immune response; spider silk

Bromfenac ophthalmic solution 0.07% dosed once daily for cataract surgery: Results of 2 randomized controlled trials - Walters, T.R.; Goldberg, D.F.; Peace, J.H.; Gow, J.A. (Ophthalmology, 2014)
Purpose To evaluate the efficacy and ocular safety of bromfenac ophthalmic solution 0.07% (Prolensa) dosed once daily for the treatment of ocular inflammation and pain in subjects who underwent cataract surgery with posterior chamber intraocular lens implantation. Design Two phase 3, randomized, double-masked, placebo-controlled, multicenter clinical trials. Participants Four hundred forty subjects (440 study eyes: 222 in the bromfenac group and 218 in the placebo group). Methods Two phase 3, prospective, randomized, double-masked, placebo-controlled clinical trials were conducted at 39 ophthalmology clinics in the United States. Subjects 18 years of age or older were randomized to receive either bromfenac 0.07% or placebo dosed once daily beginning 1 day before cataract surgery, on the day of surgery, and continuing for 14 days after surgery (for a total of 16 days). Subjects were evaluated on days 1, 3, 8, 15, and 22 after surgery. The primary efficacy end point was cleared ocular inflammation, as measured by the summed ocular inflammation score of zero (anterior chamber cell count = 0 and absence of flare) by day 15. Secondary end points included cleared ocular inflammation at day 15 and the number of subjects who were pain free at day 1. The data from the 2 clinical trials were integrated for analyses. Main Outcome Measures Summed ocular inflammation score and ocular pain. Results A significantly higher proportion of subjects treated with bromfenac 0.07% achieved complete clearance of ocular inflammation by day 15 and at day 15 compared with placebo (P < 0.0001). A statistically significantly higher proportion of subjects in the bromfenac 0.07% group were pain free at all study visits compared with those in the placebo group (P < 0.0001). Fewer subjects in the bromfenac group (3.2%) discontinued investigational product early because of a lack of efficacy than in the placebo group (23.9%; P < 0.0001). The incidence of adverse events was significantly lower in the bromfenac 0.07% group compared with the placebo group (P = 0.0041). Conclusions Bromfenac ophthalmic solution 0.07% dosed once daily was clinically safe and effective compared with placebo for the treatment of ocular inflammation and pain in subjects who had undergone cataract surgery and may be a beneficial addition to the current standard of care, which commonly includes ophthalmic antibiotics and corticosteroids. © 2014 by the American Academy of Ophthalmology.

Exogenous bFGF or TGFβ1 accelerates healing of reconstructed dura by CO2 laser soldering in minipigs - Wang, Z.; Zhong, H.; Yang, Z.; Zhao, F.; Wang, B.; Qu, P.; Liu, P. (Lasers in Medical Science, 2014)
This study aims to explore the probable mechanism of better result of dural reconstruction by CO2 laser soldering and the effect of exogenous basic fibroblast growth factor (bFGF) or transforming growth factor-beta1(TGFβ1) on wound healing. In part I of the study, ten minipigs were randomized into two equal groups, and the dural defects were reconstructed by conventional fibrin glue (FG) bonding (group I a) or by CO2 laser soldering (group Ib). In part II, 36 minipigs were randomized into three equal groups, and the dural defect was reconstructed by CO2 laser soldering; then exogenous bFGF or TGFβ1 was administered in group IIb and group II c, respectively, while group IIa served as control group. The dural specimens were harvested at 1st week postoperatively in part I; and at 1st, 2nd, 3rd, and 4th week postoperatively in part II, they were examined for healing condition and subjected to hematoxylin-eosin (HE) staining and immunohistochemical (IHC) staining with antibodies against bFGF and TGFβ1. In part I, group Ib showed higher fibroblast cell density than group Ia (P<0.05). The optical density (OD) for IHC staining with antibodies against bFGF of group Ib was significantly higher than that of group Ia (P<0.05), and for IHC staining with antibodies against TGFβ1, group Ib showed positive staining while group Ia was negative. In part II, administering exogenous bFGF or TGFβ1 made a left shift of fibroblast cell number-time curve compared with control group. For specimens' IHC staining with antibodies against bFGF, the OD of group IIb was higher than that of group IIa in the corresponding time. For specimens' IHC staining with antibodies against TGFβ1, the OD of groups IIb and IIc was both higher than that of group IIa (P<0.05 and P<0.01, respectively). In conclusion, CO 2 laser may trigger fibroblast proliferation through stimulating the secretion of bFGF and TGFβ1. Topically administering exogenous bFGF or TGFβ1 could accelerate the healing of the reconstructed dura by enhancing secretion of bFGF and/or TGFβ1 and promoting the process of fibroblast gathering-degrading. © 2013 Springer-Verlag.
Keywords: Basic fibroblast growth factor; Dura mater; Porcine; Reconstruction; Soldering; Transforming growth factor-beta1; Wound healing

Challenges in linking preclinical anti-microbial research strategies with clinical outcomes for device-associated infections - Moriarty, T.F.; Grainger, D.W.; Richards, R.G. (European Cells and Materials, 2014)
Infections related to implanted medical devices have become a significant health care issue in recent decades. Increasing numbers of medical devices are in use, often in an aging population, and these devices are implanted against a background of increasing antibiotic-resistant bacterial populations. Progressively more antibiotic resistant infections, requiring ever more refined treatment options, are therefore predicted to emerge with greater frequency in the coming decades. Improvements in the prevention, diagnosis and treatment of these deviceassociated infections will remain priority targets both for clinicians and the translational research community charged with addressing these challenges. Preclinical strategies, predictive of ultimate clinical efficacy, should serve as a control point for effective translation of new technologies to clinical applications. The development of new anti-infective medical devices requires a validated preclinical testing protocol; however, reliable validation of experimental and preclinical antimicrobial methodologies currently suffers from a variety of technical limitations. These include the lack of agreement or standardisation of experimental protocols, a general lack of correlation between in vitro and in vivo preclinical results and lack of validation between in vivo preclinical implant infection models and clinical (human) results. Device-associated infections pose additional challenges to practicing clinicians concerning diagnosis and treatment, both of which are complicated by the biofilms formed on the medical device. The critical challenges facing both preclinical research and clinical laboratories in improving both diagnosis and treatment of medical device-associated infections are the focus of this review. © 2014 AO Research Institute. All rights reserved.
Keywords: Antibiotic resistance; Clinical translational research; In vitro-in vivo correlations; Infection strategy; Medical implants

Bioactive nanocomposite for chest-wall replacement: Cellular response in a murine model - Jungraithmayr, W.; Laube, I.; Hild, N.; Stark, W.J.; Mihic-Probst, D.; Weder, W.; Buschmann, J. (Journal of Biomaterials Applications, 2014)
Chest-wall invading malignancies usually necessitate the resection of the respective part of the thoracic wall. Gore-Tex® is the material of choice that is traditionally used to repair thoracic defects. This material is well accepted by the recipient; however, though not rejected, it is an inert material and behaves like a 'foreign body' within the thoracic wall. By contrast, there are materials that have the potential to physiologically integrate into the host, and these materials are currently under in vitro and also in vivo investigation. These materials offer a gradual but complete biodegradation over time, and severe adverse inflammatory responses can be avoided. Here, we present a novel material that is a biodegradable nanocomposite based on poly-lactic-co-glycolic acid and amorphous calcium phosphate nanoparticles in comparison to the traditionally employed Gore-Tex® being the standard for chest-wall replacement. On a mouse model of thoracic wall resection, that resembles the technique and localization applied in humans, poly-lactic-co- glycolic acid and amorphous calcium phosphate nanoparticles and Gore-Tex® were implanted subcutaneously and additionally tested in a separate series as a chest-wall graft. After 1, 2, 4 and 8 weeks cell infiltration into the respective materials, inflammatory reactions as well as neo-vascularization (endothelial cells) were determined in six different zones. While Gore-Tex® allowed for cell infiltration only at the outer surface, electrospun poly-lactic-co-glycolic acid and amorphous calcium phosphate nanoparticles were completely penetrated by infiltrating cells. These cells were composed mainly by macrophages, with only 4% of giant cells and lymphocytes. Total macrophage count increased by time while the number of IL1-β-expressing macrophages decreased, indicating a protective state towards the graft. As such, poly-lactic-co-glycolic acid and amorphous calcium phosphate nanoparticles seem to develop ideal characteristics as a material for chest-wall replacement by (a) having the advantage of full biodegradation, (b) displaying stable chest-wall structures and (c) adapting a physiological and integrating graft compared to Gore-Tex®. © The Author(s) 2013 Reprints and permissions: sagepub.co.uk/journalsPermissions.nav.
Keywords: amorphous calcium phosphate nanoparticle; Chest-wall replacement; degradation kinetics; electrospinning; Gore-Tex®; PLGA/a-CaP

Implementing AORN recommended practices for prevention of retained surgical items - Goldberg, J.L.; Feldman, D.L. (AORN Journal, 2013)
Retention of a surgical item is a preventable event that can result in patient injury. AORN's "Recommended practices for prevention of retained surgical items" emphasizes the importance of using a multidisciplinary approach for prevention. Procedures should include counts of soft goods, needles, miscellaneous items, and instruments, and efforts should be made to prevent retention of fragments of broken devices. If a count discrepancy occurs, the perioperative team should follow procedures to locate the missing item. Perioperative leaders may consider the use of adjunct technologies such as bar-code scanning, radio-frequency detection, and radio-frequency identification. Ambulatory and hospital patient scenarios are included to exemplify appropriate strategies for preventing retained surgical items. © 2013 AORN, Inc.
Keywords: Adjunct technology; Recommended practices; Retained surgical items; Sponge count; Surgical count; Unretrieved device fragments

Comparative study of shrinkage, inflammatory response and fibroplasia in heavyweight and lightweight meshes - Zogbi, L.; Trindade, E.N.; Trindade, M.R.M. (Hernia, 2013)
Purpose: In this manuscript, the authors describe an animal study comparing shrinkage, inflammatory response and fibroplasia in heavyweight (HW-PP) and lightweight polypropylene (LW-PP) meshes. Methods: Both meshes were fixed on abdominal fascia of 25 Wistar rats (epifascial onlay placement). They were killed at 7, 28 and 90 days to measure the prostheses. Histological analysis was performed with hematoxylin-eosin for cellular counting and immunohistochemistry to measure collagen types I and III. Results: The authors found that the LW-PP mesh presented greater median shrinkage than HW-PP mesh at 7 (P =.036), 28 (P =.674) and 90 days (P =.038) postoperatively. There were more neutrophils on LW-PP mesh (P =.008) at 7 days, gradually diminishing in both prostheses. Lymphocytes were similar between the implants at 7 days, diminishing about 50 % on LW-PP mesh (P <.001) at 90 days. Macrophages and giant cells diminished on LW-PP and increased on HW-PP meshes (P <.001). Collagen I/III ratio presented a progressive, almost fivefold rise at 90 days, on both mesh types (P <.001). The collagen I/III ratio was similar between LW-PP and HW-PP meshes at the three times studied. Conclusions: It is concluded that LW-PP showed more shrinkage than HW-PP mesh at 7 and 90 days, despite the fact that HW-PP presented more lately foreign body reaction. The collagen I/III ratio was similar between the prostheses and increased during the postimplant period. © 2013 Springer-Verlag France.
Keywords: Abdominal wall; Animal experimentation; Collagen; Hernia; Shrinkage; Surgical mesh

Prevention of retrosternal adhesion by novel biocompatible glue derived from food additives - Kamitani, T.; Masumoto, H.; Kotani, H.; Ikeda, T.; Hyon, S.-H.; Sakata, R. (Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: Postoperative retrosternal adhesion increases the risk of cardiac injury during cardiac reoperation. We created a novel biodegradable glue called "Lydex" that is derived from food additives. The purpose of this study is to evaluate this new biomaterial's biocompatibility and its preventive effect on retrosternal adhesion. Methods: We performed a median sternotomy and anterior pericardiectomy on Japanese white rabbits, and then closed the chest (control, group 1; n = 12), implanted an expanded polytetrafluoroethylene membrane (group 2; n = 12), or applied Lydex (group 3; n = 12) before closure. After 4 weeks, we evaluated macroscopic adhesion (each group; n = 6) and microscopic findings for fibrosis and macrophage infiltration (each group; n = 6). Results: In group 3, the retrosternal adhesion score was significantly lower than in group 1 (P =.0022). There was no significant difference between groups 2 and 3. The fibrotic area ratio was significantly lower in group 3 than in groups 1 and 2 (P <.001 vs group 1; P <.001 vs group 2). In group 3, the macrophage count was significantly lower than in group 2 (P <.001) and almost equal to that in group 1. Conclusions: Our findings indicate that Lydex reduces retrosternal adhesion and attenuates the progression of fibrosis with excellent biocompatibility. Lydex is a next-generation substance for safer cardiac reoperation, with excellent capability for preventing adhesion, biocompatible and biodegradable properties, and lower potential for viral infections related to human plasma or other animal-derived products. Copyright © 2013 by The American Association for Thoracic Surgery.

Perforation of Meckel's diverticulum by a fish bone presenting as acute appendicitis: A case report - Dimitriou, I.; Evaggelou, N.; Tavaki, E.; Chatzitheoklytos, E. (Journal of Medical Case Reports, 2013)
Introduction. Meckel's diverticulum is the commonest congenital abnormality of the gastrointestinal tract. Most of them are asymptomatic but can rarely present with forms of complications such as bleeding, obstruction, diverticulitis, intussusception and neoplasm. Patients with a perforation of Meckel's diverticulum by a foreign body are rare and may present with right iliac fossa pain, which mimics acute appendicitis. Case presentation. A 64-year-old Greek man presented with an eight-hour history of right iliac fossa pain. On examination, our patient had tenderness in his right iliac fossa. A provisional diagnosis of acute appendicitis was made. He was taken to theatre with the option of an appendicectomy. His appendix was found to have an about normal appearance. An inflamed Meckel's diverticulum that had been perforated by a fish bone was found to be the cause of the abdominal pain. A Meckel's diverticulectomy was performed. Our patient made an uneventful recovery and was discharged after two days. Conclusions: Complications of Meckel's diverticulum can be difficult to diagnose and early recognition and timely operative intervention must occur in order to provide the best outcome for these patients. This is an interesting and unusual case of perforation of Meckel's diverticulum that highlights the importance of considering Meckel's diverticulum as a differential diagnosis in every patient presenting with acute abdomen. © 2013 Dimitriou et al.; licensee BioMed Central Ltd.
Keywords: Acute appendicitis; Meckel's diverticulum; Perforation

Surgicel® (oxidized regenerated cellulose) granuloma mimicking local recurrent gastrointestinal stromal tumor: A case report - Wang, H.; Chen, P. (Oncology Letters, 2013)
Unexpected clinical and/or imaging evidence of the recurrence of gastrointestinal stromal tumors soon after surgical resection may be complicated due to certain biological behavioral features of gastrointestinal stromal tumors. However, local hemostatic materials routinely used in abdominal surgery to achieve hemostasis intraoperatively may cause a foreign-body reaction, which appears to be indistinguishable from recurrent tumors in imaging studies. Thus, a second examination may be necessary to settle the true nature of the findings in such cases. If the resection and examination reveals a recurrent tumor, further proper oncological treatment is warranted, whereas if a foreign-body reaction is observed, radical or potentially harmful therapy may be withheld or cancelled. The present study retrospectively analyzes the case of an 83-year-old male patient who presented with a recurrent gastrointestinal stromal tumor four months after surgical resection, which was later identified as an intra-abdominal foreign-body granuloma caused by retained Surgicel® residue. The present study aimed to demonstrate why foreign-body granuloma induced by local hemostatic materials should be incorporated into the differential diagnosis of recurrent gastrointestinal stromal tumors post--operatively, particularly soon after surgical resection has been performed.
Keywords: Fludeoxyglucose (18F)-positron emission tomography-computed tomography; Foreign-body granuloma; Gastrointestinal stromal tumor recurrence; Surgicelreg; (oxidized regenerated cellulose)

Multiple Drug Resistant Bacterial Biofilms on Implanted Catheters - A Reservoir of Infection - Pradeep Kumar, S.S.; Easwer, H.V.; Maya Nandkumar, A. (Journal of Association of Physicians of India, 2013)
Background: Medical devices are an essential part of modern health-care, but its usage has led to the emergence of medical device associated infections otherwise known as Foreign-Body related infections (FBRIs). This is caused by bacterial adhesion and biofilm formation on their surfaces which act as a nidus of infection. These biofilms are resistant to antibacterial agents and host immune response. The antibiotics which are useful in treating planktonic forms cannot clear the biofilm and the device must usually be removed to resolve the infection. Objective: The main objective of the study was to identify the prevalence of bacterial biofilms on retrieved catheters which included vascular catheters (141) and Foley catheters (86) from patients and understand the nature of antibiotic resistant strains in these biofilms. Materials used: 227 numbers of retrieved catheters which included vascular catheters (141nos) and Foley catheters (86 nos) were used in the study. These retrieved implants were from patients from neurosurgery ward of SCTIMST who had undergone selective neurosurgical procedures. Patients with pre-existing infections including brain abscess were not included in the study. These patients had no clinical infection or pyrexia. Skin swabs were taken from patients using intravascular devices after retrieval of catheter. Results and Conclusions: Among vascular catheters Staphylococcus species were the major isolate and among the isolates many of the strains were Methicillin and some were Vancomycin resistant. Among the Foley catheter isolates E. faecalis was the major isolate followed by E. coli, Staphylococcus species, Klebsiella species, Pseudomonas species, Citrobacter etc. Most of the strains were resistant to multiple antibiotics. Although the patients selected did not have any clinical symptoms of infection, the presence of multiple-drug resistant organisms as biofilm points to this niche which can constitute a threat for HAIs and its resultant complications. This suggests that catheters should be removed as early as possible to prevent Biofilm development on them. © JAPI.

Current surgical instrument labeling techniques may increase the risk of unintentionally retained foreign objects: A hypothesis - Ipaktchi, K.; Kolnik, A.; Messina, M.; Banegas, R.; Livermore, M.; Price, C. (Patient Safety in Surgery, 2013)
Background: Marking of surgical instruments is essential to ensure their proper identification after sterile processing. The National Quality Forum defines unintentionally retained foreign objects in a surgical patient as a serious reportable event also called "never event.". Presentation of the hypothesis: We hypothesize that established practices of surgical instrument identification using unkempt tape labels and plastic tags may expose patients to "never events" from retained disintegrating labels.Testing of the hypothesis: We demonstrate the near miss of a "never event" during a surgical case in which the breakage of an instrument label remained initially unwitnessed. A fragment of the plastic label was accidentally found in the wound upon closing. Further clinical testing of the occurrence of this "never event" appears not feasible. As the name implies a patient should never be exposed to the risk of fragmenting labels.Implication of the hypothesis: Current practice does not mandate verifying intact instrument markers as part of the instrument count. The clinical confirmation of our hypothesis mandates a change in perioperative practice: Mechanical labels need to undergo routine inspection and maintenance. The perioperative count must not only verify the quantity of surgical instruments but also the intactness of labels to ensure that no part of an instrument is left behind. Proactive maintenance of taped and dipped labels should be performed routinely. The implementation of newer labeling technologies - such as laser engraved codes - appears to eliminate risks seen in traditional mechanical labels.This article reviews current instrument marking technologies, highlights shortcomings and recommends safe instrument handling and marking practices implementing newer available technologies. © 2013 Ipaktchi et al.; licensee BioMed Central Ltd.
Keywords: "Never event"; Instrument identification; Surgical instrument marking

Application of an engineering problem-solving methodology to address persistent problems in patient safety: A case study on retained surgical sponges after surgery - Anderson, D.E.; Watts, B.V. (Journal of Patient Safety, 2013)
Despite innumerable attempts to eliminate the postoperative retention of surgical sponges, the medical error persists in operating rooms worldwide and places significant burden on patient safety, quality of care, financial resources, and hospital/physician reputation. The failure of countless solutions, from new sponge counting methods to radio labeled sponges, to truly eliminate the event in the operating room requires that the emerging field of health-care delivery science find innovative ways to approach the problem. Accordingly, the VA National Center for Patient Safety formed a unique collaboration with a team at the Thayer School of Engineering at Dartmouth College to evaluate the retention of surgical sponges after surgery and find a solution. The team used an engineering problem solving methodology to develop the best solution. To make the operating room a safe environment for patients, the team identified a need to make the sponge itself safe for use as opposed to resolving the relatively innocuous counting methods. In evaluation of this case study, the need for systematic engineering evaluation to resolve problems in health-care delivery becomes clear. © 2013 by Lippincott Williams and Wilkins.
Keywords: health-care engineering; patient safety; retained surgical items

Detailed analysis of allergic cutaneous reactions to spinal cord stimulator devices - Chaudhry, Z.A.; Najib, U.; Bajwa, Z.H.; Jacobs, W.C.; Sheikh, J.; Simopoulos, T.T. (Journal of Pain Research, 2013)
The use of spinal cord stimulation (SCS) devices to treat chronic, refractory neuropathic pain continues to expand in application. While device-related complications have been well described, inflammatory reactions to the components of these devices remain underreported. In contrast, hypersensitivity reactions associated with other implanted therapies, such as endovascular and cardiac rhythm devices, have been detailed. The purpose of this case series is to describe the clinical presentation and course of inflammatory reactions as well as the histology of these reactions. All patients required removal of the entire device after developing inflammatory reactions over a time course of 1-3 months. Two patients developed a foreign body reaction in the lead insertion wound as well as at the implantable pulse generator site, with histology positive for giant cells. One patient developed an inflammatory dermatitis on the flank and abdomen that resolved with topical hydrocortisone. "In vivo" testing with a lead extension fragment placed in the buttock resulted in a negative reaction followed by successful reimplantation of an SCS device. Inflammatory reactions to SCS devices can manifest as contact dermatitis, granuloma formation, or foreign body reactions with giant cell formation. Tissue diagnosis is essential, and is helpful to differentiate an inflammatory reaction from infection. The role of skin patch testing for 96 hours may not be suited to detect inflammatory giant cell reactions that manifest several weeks post implantation. © 2013 Chaudhry et al, publisher and licensee Dove Medical Press Ltd.
Keywords: Contact dermatitis; Delayed inflammatory responses; Foreign body giant cell reactions; Spinal cord stimulation

Radiological diagnosis of a small bowel perforation secondary to toothpick ingestion - Mark, D.; Ferris, K.; Martel, G.; Mulholland, K. (BMJ Case Reports, 2013)
A 77-year-old edentulous man presented to the accident and emergency department with a sudden onset of sharp right-sided abdominal pain. The patient reported a change in his bowel habit with constipation over a 6 month period but did not report any significant choking event or ingestion of a foreign body in the preceding months. On examination the patient was maximally tender with guarding over McBurneys point. CT scan showed an abnormal segment of distal ileum with a 3 cm high attenuation focus which had penetrated the bowel wall. At laparotomy the patient was found to have a perforation of his distal ileum caused by an ingested toothpick. Patients wearing dental plates or dentures are at higher risk of toothpick ingestion due to impaired palatal sensation. CT scanning, in the appropriate setting, may aid diagnosis and lower operator risk of sharp related injury at the time of operation.

Right-sided hydronephrosis secondary to swallowing a headscarf pin - Alkan, E.; Ozkanli, O.; Balbay, D. (Urologia Internationalis, 2013)
A majority of foreign objects ingested pass through the gastrointestinal tract without any complications. Sometimes, complications such as perforation and adhesions of the neighboring organs occur and surgical treatment becomes necessary. We report the case of a 22-year-old female who was admitted with right flank pain. Past medical history revealed that the patient had accidentally swallowed a headscarf pin 11 months earlier. A computed tomography scan confirmed the swallowed foreign body posterior to and around the ileocecal region. The headscarf pin, causing stenosis and proximal ureteral dilatation, was removed surgically. To the authors' knowledge there has been no previous report of such ureteral obstruction published in the English literature. © 2013 S. Karger AG, Basel.
Keywords: Foreign body; Hydronephrosis; Ureteral obstruction

The recurring problem of retained swabs and instruments - Mahran, M.A.; Toeima, E.; Morris, E.P. (Best Practice and Research: Clinical Obstetrics and Gynaecology, 2013)
Patient safety is one of the most pressing challenges in health care. The promotion of safety requires that all those involved in healthcare realise that the potential for errors exists, and that teamwork and communication are essential for preventing errors. Incidents compromising patient safety, such as unintended retention of swabs or instruments, are regarded as 'never events'. These incidents are considered 'unacceptable and eminently preventable', as pointed out by the Department of Health 'never events list' 2012/2013. One estimate says that one case of a retained item occurs at least once a year in a major hospital where 8000 to 18,000 major cases are carried out each year. All healthcare organisations should take appropriate measures to prevent retention of foreign bodies by consistent application of reliable and standardised processes of care. In this review, we explore the risks and complications associated with retained swabs and instruments, and different ways to prevent such risks to patients. © 2013 Elsevier Ltd. All rights reserved.
Keywords: gossypiboma; misplaced swab; retained swab; retained swabs and instruments; swab count

Magnetic bead toy ingestion: Uses and disuses in children - Adikibi, B.T.; Arnold, M.; Van Niekerk, G.; Alexander, A.; Numanoglu, A.; Millar, A.J.W. (Pediatric Surgery International, 2013)
A 2-year-old female presented acutely with peritonitis and small bowel obstruction. An abdominal radiograph demonstrated a radiopaque foreign body. At laparotomy she was found to have bowel perforations with entero-enteric fistulae caused by four magnets. The magnets were removed, and debridement and closure of the perforations performed. We review our case and highlight this problem to other medical practitioners as a potential cause of significant morbidity and mortality in the paediatric population. © 2013 Springer-Verlag Berlin Heidelberg.

'Crohn'z meanz Heinz': Foreign body inflammatory mass mimicking Crohn's disease - Visagan, R.; Grossman, R.; Dimitriadis, P.A.; Desai, A. (BMJ Case Reports, 2013)
The authors present a patient with a presumed diagnosis of Crohn's disease for 6 years turning out to be an unusual inflammatory mass caused by ileal perforation due to a foreign body. When surgical intervention became necessary for admissions with recurrent obstruction, laparoscopy revealed an inflammatory mass in the terminal ileum, exposing two pieces of plastic bearing the word 'Heinz'. Resection of the inflammatory mass led to the complete resolution of symptoms. Histology from the operative specimen showed no features of Crohn's disease. There were no granulomas and no fissuring ulcers. This case highlights that an inflammatory mass in the small intestine caused by the perforation of ingested foreign body can mimic Crohn's disease. To our knowledge, this is the first report of a synthetic plastic packaging causing ileo-caecal junctional perforation mimicking Crohn's disease. Copyright 2013 BMJ Publishing Group. All rights reserved.

Lymphoid Aggregates That Resemble Tertiary Lymphoid Organs Define a Specific Pathological Subset in Metal-on-Metal Hip Replacements - Mittal, S.; Revell, M.; Barone, F.; Hardie, D.L.; Matharu, G.S.; Davenport, A.J.; Martin, R.A.; Grant, M.; Mosselmans, F.; Pynsent, P.; Sumathi, V.P.; Addison, O.; et al. (PLoS ONE, 2013)
Aseptic lymphocyte-dominated vasculitis-associated lesion (ALVAL) has been used to describe the histological lesion associated with metal-on-metal (M-M) bearings. We tested the hypothesis that the lymphoid aggregates, associated with ALVAL lesions resemble tertiary lymphoid organs (TLOs). Histopathological changes were examined in the periprosthetic tissue of 62 M-M hip replacements requiring revision surgery, with particular emphasis on the characteristics and pattern of the lymphocytic infiltrate. Immunofluorescence and immunohistochemistry were used to study the classical features of TLOs in cases where large organized lymphoid follicles were present. Synchrotron X-ray fluorescence (XRF) measurements were undertaken to detect localisation of implant derived ions/particles within the samples. Based on type of lymphocytic infiltrates, three different categories were recognised; diffuse aggregates (51%), T cell aggregates (20%), and organised lymphoid aggregates (29%). Further investigation of tissues with organised lymphoid aggregates showed that these tissues recapitulate many of the features of TLOs with T cells and B cells organised into discrete areas, the presence of follicular dendritic cells, acquisition of high endothelial venule like phenotype by blood vessels, expression of lymphoid chemokines and the presence of plasma cells. Co-localisation of implant-derived metals with lymphoid aggregates was observed. These findings suggest that in addition to the well described general foreign body reaction mediated by macrophages and a T cell mediated type IV hypersensitivity response, an under-recognized immunological reaction to metal wear debris involving B cells and the formation of tertiary lymphoid organs occurs in a distinct subset of patients with M-M implants. © 2013 Mittal et al.

Evaluation of the biocompatibility of silicone gel implants - histomorphometric study - França, D.C.C.; de Castro, A.L.; Soubhia, A.M.P.; de Aguiar, S.M.H.C.A.; Goiato, M.C. (Acta Informatica Medica, 2013)
Breast implants are medical devices that are used to augment breast size or to reconstruct the breast following mastectomy or to correct a congenital abnormality. Breast implants consist of a silicone outer shell and a filler (most commonly silicone gel or saline). Approximately 5 to 10 million women worldwide have breast implants. Histomorphometric study to evaluate the biological tissue compatibility of silicone implants suitable for plastic surgery and the adverse effects and risks of this material. Thirty Wistar white rats received subcutaneous implants and the revestiment of silicone gel Silimed ®®, and randomized into six groups of five animals each, according to the type of implanted material and the time of sacrifice. Eight areas of 60.11mm2 corresponding to the obtained surgical pieces were analyzed, counting mesenchymal cells, eosinophils, and foreign body giant cells, observing an acceptable biocompatibility in all implants, for subsequent statistical analysis by Tukey test. Silicone gel showed inflammation slightly greater than for other groups, with tissue reactions varying from light to moderate, whose result was the formation of a fibrous capsule around the material, recognized by the organism as a foreign body. Despite frequent local complications and adverse outcomes, this research showed that the silicone and top layer presented an acceptable chronic inflammatory reaction, which did not significantly differ from the control group. In general, it is possible to affirm that silicone gel had acceptable levels of biocompatibility, confirmed the rare presence of foreign body giant cells, and when of the rupture, formed a fibrous capsule around the material, separating the material of the organism. © AVICENA 2013.
Keywords: Breast Implantation; Materials Testing; Rats; Silicone Gels; Wistar

An impacted denture in the oesophagus- an endoscopic or a surgical emergency-a case report - Singh, P.; Singh, A.; Kant, P.; Zonunsanga, B.; Singh Kuka, A. (Journal of Clinical and Diagnostic Research, 2013)
Accidentally swallowed dentures can lead to severe complications in the gastrointestinal tract. Therefore, an early detection and an effective therapeutic management are important. In the era of advanced endoscopy, though the primary treatment of an impacted foreign body in the oesophagus is an endoscopic removal, a primary surgical treatment is advised for dentures with sharp hooks. Also, a prolonged impaction of dentures with sharp hooks leads to an increase in the complication rates. We are reporting a case of accidentally swallowed denture. After the diagnosis of an impacted denture was made, upper GI endoscopy revealed that an endoscopic removal was not feasible and thus, a late surgical removal was performed in the form of a transhiatal oesophagectomy and reconstruction. This case highlights the importance of an early and preferred treatment in the form of a controlled surgical intervention as compared to an endoscopic extraction for patients with impacted dentures with sharp hooks.
Keywords: Denture with sharp hooks; Impacted denture; Impacted foreign body in the oesophagus; Oesophagectomy

Transoral penetrating craniocerebral injury by a bamboo chopstick in a child - Wang, H.-F.; Li, W.-C.; Xu, N.; Fu, S.-L. (Journal of Clinical Neuroscience, 2013)
We present a 3-year-old girl with a transoral injury by a bamboo chopstick penetrating the middle skull base. The features of imaging are described and the management is discussed. The potential for injury to the cavernous sinus is emphasized, even if no there is no hemorrhage on the initial CT scan. Early intracranial infection in relation to penetrating injuries is a factor in planning treatment by craniotomy. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Chopstick injury; Middle; Mouth; Penetrating craniocerebral injury; Skull base

Candida septic arthritis with rice body formation: A case report and review of literature - Jeong, Y.M.; Cho, H.Y.; Lee, S.-W.; Hwang, Y.M.; Kim, Y.-K. (Korean Journal of Radiology, 2013)
Rice body formation in a joint or bursa is a rare condition, and is usually associated with rheumatoid arthritis or tuberculous arthritis. Here we describe a case of multiple rice body formation in a shoulder joint and in adjacent bursae, which was confirmed to be due to septic arthritis by Candida species. To the best of our knowledge, rice body formation in Candida septic arthritis in an immune-competent patient has not been previously reported.
Keywords: Arthritis; Candida; MRI; Rice bodies

Small bowel perforation by a germanium stone - Jang, J.Y.; Shim, H.; Lee, J.G. (American Surgeon, 2013)

A rare cause of mechanical bowel obstruction: Mesh migration - Yilmaz, I.; Karakaş, D.O.; Sucullu, I.; Ozdemir, Y.; Yucel, E. (Hernia, 2013)
The use of mesh has become the gold standard in hernia operations recently due to advantages such as lower recurrence rates, lower post-surgical pain and earlier return to work. Plug mesh application, first described by Robins and Rutkow [Robbins AW, Rutkow IM (1993) The mesh-plug hernioplasty. Surg Clin North Am 73:501-512], is a popular method of hernia repair. Although rare, there may be complications of surgery using plug mesh. This report presents a case of mechanic bowel obstruction due to mesh migration, 3 years after a left inguinal hernia repair with plug mesh method. © 2011 Springer-Verlag.
Keywords: Inguinal hernia; Mechanical bowel obstruction; Plug mesh

Relations between cochlear histopathology and hearing loss in experimental cochlear implantation - O'Leary, S.J.; Monksfield, P.; Kel, G.; Connolly, T.; Souter, M.A.; Chang, A.; Marovic, P.; O'Leary, J.S.; Richardson, R.; Eastwood, H. (Hearing Research, 2013)
This study reviews the cochlear histology from four hearing preservation cochlear implantation experiments conducted on 73 guinea pigs from our institution, and relates histopathological findings to residual hearing. All guinea pigs had normal hearing prior to surgery and underwent cochlear implantation via a cochleostomy with a silastic-platinum dummy electrode. Pure tone auditory brainstem response (ABR) thresholds from 2 to 32 kHz were recorded prior to surgery, and at one and four weeks postoperatively. The cochleae were then fixed in paraformaldehyde, decalcified, paraffin embedded, and mid-modiolar sections were prepared. The treatment groups were as follows: 1) Systemic dexamethasone, 0.2 mg/kg administered 1 h before implantation, 2) Local dexamethasone, 2% applied topically to the round window for 30 min prior to cochlear implantation, 3) Local n-acetyl cysteine, 200 μg applied topically to the round window for 30 min prior to implantation, 4) inoculation to keyhole-limpet hemocyanin (KLH) prior to implantation, and 5) untreated controls. There was a significant correlation between the extent of the tissue reaction in the cochlea and the presence of foreign body giant cells (FBGCs), new bone formation and injury to the osseous spiral lamina (OSL). The extent of the tissue response, as a percentage of the area of the scala tympani, limited the best hearing that was observed four weeks after cochlear implantation. Poorer hearing at four weeks correlated with a more extensive tissue response, lower outer hair cell (OHC) counts and OSL injury in the basal turn. Progressive hearing loss was also correlated with the extent of tissue response. Hearing at 2 kHz, which corresponds to the region of the second cochlear turn, did not correspond with loco-regional inner hair cell (IHC), OHC or SGC counts. We conclude that cochlear injury is associated with poorer hearing early after implantation. The tissue response is related to indices of cochlear inflammation and injury. An extensive tissue response limits hearing at four weeks, and correlates with progressive hearing loss. These latter effects may be due to inflammation, but would also be consistent with interference of cochlear mechanics. © 2013.

PLDLA/PCL-T scaffold for meniscus tissue engineering - Esposito, A.R.; Moda, M.; Cattani, S.M.D.M.; De Santana, G.M.; Barbieri, J.A.; Munhoz, M.M.; Cardoso, T.P.; Barbo, M.L.P.; Russo, T.; D'Amora, U.; Gloria, A.; Ambrosio, L.; et al. (BioResearch Open Access, 2013)
The inability of the avascular region of the meniscus to regenerate has led to the use of tissue engineering to treat meniscal injuries. The aim of this study was to evaluate the ability of fibrochondrocytes preseeded on PLDLA/PCL-T [poly(L-co-D,L-lactic acid)/poly(caprolactone-triol)] scaffolds to stimulate regeneration of the whole meniscus. Porous PLDLA/PCL-T (90/10) scaffolds were obtained by solvent casting and particulate leaching. Compressive modulus of 9.5±1.0 MPa and maximum stress of 4.7±0.9 MPa were evaluated. Fibrochondrocytes from rabbit menisci were isolated, seeded directly on the scaffolds, and cultured for 21 days. New Zealand rabbits underwent total meniscectomy, after which implants consisting of cell-free scaffolds or cell-seeded scaffolds were introduced into the medial knee meniscus; the negative control group consisted of rabbits that received no implant. Macroscopic and histological evaluations of the neomeniscus were performed 12 and 24 weeks after implantation. The polymer scaffold implants adapted well to surrounding tissues, without apparent rejection, infection, or chronic inflammatory response. Fibrocartilaginous tissue with mature collagen fibers was observed predominantly in implants with seeded scaffolds compared to cell-free implants after 24 weeks. Similar results were not observed in the control group. Articular cartilage was preserved in the polymeric implants and showed higher chondrocyte cell number than the control group. These findings show that the PLDLA/PCL-T 90/10 scaffold has potential for orthopedic applications since this material allowed the formation of fibrocartilaginous tissue, a structure of crucial importance for repairing injuries to joints, including replacement of the meniscus and the protection of articular cartilage from degeneration. © 2013, Mary Ann Liebert, Inc. 2013.
Keywords: fibrochondrocyte culture; meniscus regeneration; PLDLA/PCL-T scaffold

A foreign body masquerading as a tumour - Maempel, J.F.; Nicol, G.; Clement, R.G.E.; Porter, D. (BMJ Case Reports, 2013)
A 29-year-old man presented to his local orthopaedic service with a mass in the medial aspect of his left thigh, present for 1 year. It had not changed in size, although he complained of increasing tightness in the region. He denied any systemic symptoms or history of local trauma. Extensive imaging performed at his local hospital was thought suggestive of a musculoskeletal tumour. The patient was referred to our tertiary centre musculoskeletal tumour clinic. Review of external imaging and further investigations revealed a fluid-filled intramuscular mass containing an echogenic focus consistent with foreign body. Ultrasound-guided aspiration yielded fluid which grew Staphylococcus aureus. Only when presented with this information did the patient vaguely recall sitting on a wooden kebab stick 30 months previously. At surgery, a thick-walled abscess with a central foreign body was identified and drained. At follow-up 1 month later, he was well with no recurrent problems.

Retained surgical sponges, needles and instruments - Hariharan, D.; Lobo, D.N. (Annals of the Royal College of Surgeons of England, 2013)
Introduction Retained sponges and instruments (RSI) due to surgery are a recognised medical 'never event' and have catastrophic implications for patients, healthcare professionals and medical care providers. The aim of this review was to elucidate the extent of the problem of RSI and to identify preventative strategies. Methods A comprehensive literature search was performed on MEDLINE®, Embase™, the Science Citation Index and Google™ Scholar for articles published in English between January 2000 and June 2012. Studies outlining the incidence, risk, management and attempts to prevent RSI following surgical intervention were retrieved. Results The overall incidence of RSI is low although its incidence is substantially higher in operations performed on open cavities. Sponges are the most commonly retained item when compared with needles and instruments. Clinical presentation is varied, leading to avoidable morbidity, and the error is indefensible medicolegally. Risk factors include emergency operations, operations involving unexpected change in procedure, raised body mass index, and a failure to perform accurate sponge and instrument counts. The existing strategy for prevention is manual counting of sponges and instruments undertaken by surgical personnel. This, however, is fallible. Computer assisted counting of sponges using barcodes and gauze sponges tagged with a radiofrequency identification device aiding manual counting have been trialled recently, with success. Conclusions Vigilance among operating theatre personnel is paramount if RSI is to be prevented. Prospective multicentre trials to assess efficacy of new technologies aiding manual counting should be undertaken if this medical error is to be eliminated completely.
Keywords: Counts; Foreign bodies; Instruments; Prevention; Retained; Sponges; Surgery

Fish bone penetration of the duodenum: A rare cause of liver abscess - Chen, M.-H.; Lin, H.-J.; Foo, N.P.; Chen, K.-T. (International Journal of Gerontology, 2013)
We present a case of an elderly patient who visited our emergency department owing to a pyogenic liver abscess. A linear calcified object extending from the stomach to the liver was found on images from a computed tomography scan. The patient underwent laparotomy and a retained fish bone and a hepato-duodenal fistula were discovered during surgery. The bacteriological presentation of foreign-body-related liver abscesses are unique and most of the patients require surgical interventions to remove the foreign bodies. However, it is difficult to obtain a reliable history of accidentally swallowed foreign bodies. Physicians should exam the images carefully for any clues of retained foreign bodies in patients with pyogenic liver abscess. Copyright © 2012, Taiwan Society of Geriatric Emergency & Critical Care Medicine. Published by Elsevier Taiwan LLC. All rights reserved.
Keywords: computed tomography scan; foreign body; geriatric; liver abscess; surgery

Late ventriculo-atrial shunt migration leading to pericardial cerebrospinal fluid effusion and cardiac tamponade - Mastroianni, C.; Chauvet, D.; Ressencourt, O.; Kirsch, M. (Interactive Cardiovascular and Thoracic Surgery, 2013)
We present the case of a patient with cardiac tamponade secondary to late intrapericardial migration of a disrupted ventriculo-atrial shunt (VAS). A 48-year old woman was referred for cardiac tamponade. She had a history of congenital hydrocephalus with implantation of a VAS (Codman®) in 1994. The initial neurological examination was normal. Tomodensitometry showed a discontinuity of the VAS at the cervical level with its distal part floating in the pericardium. Immediate surgery through sternotomy allowed the draining of the pressurized translucid liquid. The distal part of the VAS was extracted and the perforation site on the right ventricle was sutured. The patient showed no neurological trouble 3 months after operation. Surprisingly, cardiac tamponade was not related to bleeding but to the accumulation of translucid liquid whose gross aspect and biochemistry were very suggestive of cerebrospinal fluid (CSF). We hypothesize that a fibrin sheath had developed around the VAS at the time of its disconnection and acted as a fibrous tunnel allowing continued CSF drainage through its distal part. Surgical strategies to prevent late VAS disconnection should be considered at the time of implantation. © 2012 The Author.
Keywords: Cardiac tamponade; Ventriculo-atrial shunt

Stromal rejection after big bubble deep anterior lamellar keratoplasty: Case series and review of literature - Sharma, N.; Kandar, A.K.; Singh Titiyal, J. (Eye and Contact Lens, 2013)
PURPOSE:: The aim of this study was to report three cases of stromal rejection after deep anterior lamellar keratoplasty using big bubble technique in keratoconus. METHODS:: Deep anterior lamellar keratoplasty was performed in 3 cases of keratoconus (11-19 years of age) using the "big bubble" technique. All of them presented 4 to 19 months after uneventful surgeries with variable decrease of vision (1/200-20/200) along with foreign body sensation, mild pain, and corneal edema. Suture infiltrates were present in all eyes. Ultrasound pachymetry showed variable increase in central corneal thickness (711-894 μm). These patients with stromal rejection were administered pulse intravenous methylprednisolone, 500 mg in 150 mL of 5% dextrose and were started on 1% prednisolone acetate eye drops 1 hourly, moxifloxacin hydrochloride 0.5% 4 times a day along with homatropine 2% eye drops 4 times a day. RESULTS:: Complete recovery of the stromal rejections was attained with clear graft and recovery of visual acuity (≥20/40) in all eyes. Central corneal thickness returned to prerejection values in all the eyes after 7 days. There was no significant change in specular count. CONCLUSIONS:: Deep anterior lamellar keratoplasty does not eliminate the risk of stromal rejection. Suture-related factors in the form of suture infiltrates and loose suture are an important risk factor for graft rejection. Graft rejection if treated promptly is reversible. © 2013 Lippincott Williams & Wilkins.

Pitfalls of CT for deep neck abscess imaging assessment: A retrospective review of 162 cases - Chuang, S.-Y.; Lin, H.-T.; Wen, Y.-S.; Hsu, F.-J. (B-ENT, 2013)
Objectives: To investigate the diagnostic value of contrast-enhanced computed tomography (CT) for the prediction of deep neck abscesses in different deep neck spaces and to evaluate the false-positive results. Method: We retrospectively analysed the clinical charts, CT examinations, surgical findings, bacteriology, pathological examinations and complications of hospitalised patients with a diagnosis of deep neck abscess from 2004 to 2010. The positive predictive values (PPV) for the prediction of abscesses by CT scan in different deep neck spaces were calculated individually on the basis of surgical findings. Results: A total of 162 patients were included in this study. All patients received both intravenous antibiotics and surgical drainage. The parapharyngeal space was the most commonly involved space. The overall PPV for the prediction of deep neck abscess with contrast-enhanced CT was 79.6%. The PPV was 91.3% when more than one deep neck space was involved but only 50.0% in patients with isolated retropharyngeal abscesses. In the false-positive group, cellulitis was the most common final result, followed by cystic degeneration of cervical metastases. Five specimens taken intra-operatively revealed malignancy and four of these were not infected. Conclusions: There are some limitations affecting the differentiation of abscesses and cellulitis, particularly in the retropharyngeal space. A central necrotic cervical metastatic lymph node may sometimes also mimic a simple pyogenic deep neck abscess on both clinical pictures and CT images. Routine biopsy of the tissue must be performed during surgical drainage.
Keywords: Computed tomography; Deep neck abscess; Diagnosis; Head and neck cancer; Pseudo-aneurysm

Open globe ocular trauma: Functional outcome of eyes with no light perception at initial presentation - Soni, N.G.; Bauza, A.M.; Son, J.H.; Langer, P.D.; Zarbin, M.A.; Bhagat, N. (Retina, 2013)
PURPOSE:: To evaluate characteristics and prognostic factors for functional success in eyes that present with no light perception (NLP) after open globe trauma. METHODS:: The medical records of all subjects presenting to a single university referral center with visual acuity (VA) of NLP after sustaining an open globe eye injury from January 1, 2001, through June 30, 2010, were retrospectively analyzed to determine epidemiologic and clinical factors associated with visual outcomes. RESULTS:: Of the 73 NLP eyes (73 patients) that underwent primary repair and were included in the study, final VA was 20/100 in 1 eye (1%), counting fingers in 2 eyes (3%), hand motion in 9 eyes (12%), light perception in 5 eyes (7%), and NLP in 56 eyes (77%). Recovery of some vision on postoperative Day 1, pars plana vitrectomy operation, and Zone 2 injury were significantly associated with an improvement in final VA. Zone 3 injuries were the most likely to result in NLP final VA, although this difference was not statistically significant. CONCLUSION:: Visual recovery to light perception or better on postoperative Day 1 increases the likelihood of having a long-term improvement in VA. Pars plana vitrectomy may be beneficial in such eyes if posterior segment abnormalities are noted.
Keywords: anti-VEGF; bevacizumab; macular telangiectasia; ranibizumab; subretinal neovascularization

Inflammatory pseudotumor of liver secondary to migrated fishbone - A rare cause with an unusual presentation - Srinivasan, U.P.; Duraisamy, A.B.; Ilango, S.; Rathinasamy, A.; Chandramohan, S.M. (Annals of Gastroenterology, 2013)
A 35-year-old woman presented with a history of vague epigastric pain which lasted for one day. She had no other gastrointestinal symptoms and had an unremarkable past history and physical examination. An ultrasound scan abdomen showed a 3x3.5 cm mass in the left lobe of liver. A CT scan showed an abnormal hypodense lesion with mild enhancement in the arterial phase, with a central calcification. Complete blood count, liver function test and alpha-fetoprotein were normal. A left lateral segmentectomy was performed after adequate pre-operative assessment. The specimen contained a 3 cm long fishbone. The post-operative period was uneventful. Histopathological examination revealed chronic non-specific inflammation with fibrosis. Inflammatory pseudotumor of liver is a rare benign tumor with uncertain etiopathogenesis. Suggested etiologies include a septic or a viral origin and it can occur after migration of sharp objects, including migrated fishbone. Inflammatory pseudotumor of liver can be a diagnostic challenge and may end up in major resection. © 2013 Hellenic Society of Gastroenterology.
Keywords: Fish bone; Foreign body; Inflammatory pseudotumor

Miscount incidents: A novel approach to exploring risk factors for unintentionally retained surgical items - Judson, T.J.; Howell, M.D.; Guglielmi, C.; Canacari, E.; Sands, K. (Joint Commission Journal on Quality and Patient Safety, 2013)
Background: An estimated 1,500 operations result in retained surgical items (RSIs) each year in the United States, resulting in substantial morbidity. The rarity of these events makes studying them difficult, but miscount incidents may provide a window into understanding risk factors for RSIs. Methods: A cohort study of all consecutive operative cases during a 12-month period was conducted at a large academic medical center to identify risk factors for surgical miscounts. A multidisciplinary electronic miscount reconciliation checklist (necessitating both surgeon and nurse input) was introduced into the internally developed electronic Perioperative Information Management System to build a predictive model for RSI cases. Results: Among 23,955 operations, 84 resulted in miscount incidents (0.35% [95% confidence interval: 0.28% to 0.43%]). Increased case duration was strongly associated with increased risk of a miscount in unadjusted analyses (p <.0001). In the nested case-control analysis, both the case duration and the number of providers present were independently associated with a more than doubling of the odds of a miscount, even after adjustment for one another, the elective/urgent/emergent status of a case, and personnel changes occurring during the case. Conclusions: The finding that both the length of the case and the number of providers involved in the case were independent risk factors for miscount incidents may offer insight into risk-targeted strategies to prevent RSIs, such as postoperative imaging, bar-coded surgical items, and radiofrequency technology. Miscounts trigger use of the Incorrect Count Safety Checklist, which can be used to determine whether a count completed at the procedure's conclusion is consistent across disciplines (circulating nurses, scrub persons, surgeons).

An unusual cause of duodenal perforation due to a lollipop stick - Kim, M.J.; Seo, J.M.; Lee, Y.; Lee, Y.M.; Choe, Y.H. (Korean Journal of Pediatrics, 2013)
Children have a natural tendency to explore objects with their mouths; this can result in the swallowing of foreign objects. Most ingested foreign bodies pass uneventfully through the gastrointestinal tract. However, some foreign bodies cause obstruction or perforation of the gastrointestinal tract, requiring surgical intervention. Perforation of the gastrointestinal tract may be associated with considerable morbidity and mortality. The most common sites of intestinal foreign body perforation are the ileocecal and rectosigmoid regions. Foreign body perforation of the duodenum is relatively uncommon. We report the first Korean case of duodenal perforation by an ingested 8-cm lollipop stick. Lollipops are popular with the children and fairly accessible to them, as most parents are not aware of their potential harm. Pediatric clinicians should be aware of the risks associated with lollipop-stick ingestion. Our report also describes the feasibility and safety of laparoscopic diagnosis and management of pediatric patients with peritonitis induced by the ingestion of foreign bodies. © 2013 by The Korean Pediatric Society.
Keywords: Duodenal perforation; Foreign bodies; Laparoscopy; Lollipop stick

Intentional foreign object ingestions: Need for endoscopy and surgery - Dalal, P.P.; Otey, A.J.; McGonagle, E.A.; Whitmill, M.L.; Levine, E.J.; McKimmie, R.L.; Thomas, A.C.; Cook, C.H.; Papadimos, T.J.; Reilley, T.E.; Bergese, S.D.; Steinberg, S.M.; et al. (Journal of Surgical Research, 2013)
Background: Intentional ingestion of foreign objects (IIFO) is common in the incarcerated population. This study was undertaken in order to better define clinical patterns of IIFO among prisoners. We sought to determine factors associated with the need for endoscopic and surgical therapy for IIFO. Methods: After obtaining permission to conduct IIFO research in incarcerated populations, study patients were identified by ICD-9 codes. Patient charts were reviewed for demographics; past medical history; IIFO characteristics; and diagnostic, endoscopic, and surgical findings. Univariate and multivariate analyses were performed using statistical software. Results: Thirty patients with 141 episodes of IIFO were identified. The mean number of ingested items per episode was 4.60. Endoscopy was performed in 97 of 141 IIFO instances, with failure to retrieve the ingested object in 21 of 97 cases (22%). Eleven instances (7.8%) required surgical intervention. On multivariate analyses, hospital admission was associated with elevated white blood cell count (odds ratio [OR] 1.4, P < 0.05) and number of items ingested (OR 1.3, P < 0.05). The need for endoscopy was independently associated with ingestion of multiple objects (OR 3.3, P < 0.05) and elevated white blood cell count (OR 1.3, P < 0.05). Surgical therapy was significantly associated with elevated white blood cell count (OR 1.6, P < 0.01) and with increasing number of ingested items (OR 1.07 per item, P < 0.05). Endoscopy is associated with significantly lower odds of surgery (OR 0.13, P < 0.01). Conclusions: Intentional ingestion of foreign objects continues to pose a significant human and economic burden. The need for admission or therapy is frequently associated with leukocytosis. Further investigation is warranted into resource-appropriate triage of patients who present with IIFO. © 2013 Elsevier Inc. All rights reserved.
Keywords: Correctional institutions; Endoscopy; Foreign body ingestion; Inmates; Intentional ingestion of foreign; Laparotomy; Objects; Prisoners; Swallowers

Esophageal complications of catheter ablation for atrial fibrillation: A case report - Podgaetz, E.; Deschamps, C. (Journal of Thoracic and Cardiovascular Surgery, 2013)

Acute scrotal pain associated with urethral foreign bodies - Liao, W.-S.; Shen, B.-Y.; Wu, C.-C. (Formosan Journal of Surgery, 2013)
Acute scrotal pain should be treated as a condition that requires immediate medical attention. Herein, we report the case of a 60-year-old male who sought emergency medical care for acute scrotal pain of 2-day duration. Results of an imaging examination revealed an abscess in the scrotum and the presence of foreign bodies in the urethra. The abscess was incised and drained, and the foreign bodies were removed from the urethra. Antibiotic therapy was initiated, and the patient was relieved of scrotal pain. He was discharged from hospital in a stable condition 10 days after the surgery. © 2013, Taiwan Surgical Association.
Keywords: Acute scrotal pain; Urethral foreign bodies

Retained surgical items: A problem yet to be solved - Stawicki, S.P.A.; Moffatt-Bruce, S.D.; Ahmed, H.M.; Anderson III, H.L.; Balija, T.M.; Bernescu, I.; Chan, L.; Chowayou, L.; Cipolla, J.; Coyle, S.M.; Gracias, V.H.; Gunter, O.L.; et al. (Journal of the American College of Surgeons, 2013)
Background: Retained surgical items (RSI) continue to occur. Large RSI studies are few due to low RSI frequency in single institutions and the medicolegal implications. Consequently, RSI risks are not fully defined, with discrepancies persisting among published studies. The goals of this study were to better define risk factors for RSI, to clarify previously discrepant risk factors, and to evaluate other potential contributors to RSI occurrence, such as trainee presence during an operation. Study Design: Multicenter case-match study of RSI risk factors was conducted between January 2003 and December 2009. Cases complicated by RSI were identified at participating centers using clinical quality improvement and adverse event reporting data. Case match controls (non-RSI) were selected from same or similar-type cases performed at each respective institution. Retained surgical item risk factors were evaluated by univariate and multivariate conditional logistic regression. Results: Fifty-nine RSIs and 118 matched controls were analyzed (RSI incidence 1 in 6,975 or 59 in 411,526). Retained surgical items occurred despite use of confirmatory x-rays (13 of 27 instances) and/or radiofrequency tagging (2 of 32 instances). Among previously discrepant results, we confirmed that body mass index, unexpected intraoperative events, and procedure duration were associated with increased RSI risk. The occurrence of any safety variance, and specifically an incorrect count at any time during the procedure, was associated with elevated RSI risk. Trainee presence was associated with 70% lower RSI risk compared with trainee absence. Conclusions: Longer duration of surgery, safety variances, and incorrect counts during the procedure result in elevated RSI risk. The possible positive influence of trainee presence on RSI risk deserves additional study. Our findings highlight the need for zero tolerance for safety omissions, continued study and development of novel approaches to RSI reduction, and establishing anonymous RSI reporting systems to better track both the incidence and risks associated with this problem, which has yet to be solved. © 2013 American College of Surgeons.

Spinal textiloma (gossypiboma): A report of three cases misdiagnosed as tumour - Şahin, S.; Atabey, C.; Şimşek, M.; Naderi, S. (Balkan Medical Journal, 2013)
Background: Textile products commonly used in surgery (e.g., sponges or gauze) have been known to cause complications after spinal surgery. Associated complications usually arise months or even years after the primary surgery. In case of spine surgery, these bodies are often detected during neuroradiological evaluations to investigate reported back pain; however, this complication often remains asymptomatic. Aims: The research is intended to increase awareness among both spinal surgeons and neuroradiologists of this potential complication. Study Design: Retrospective study. Methods: This study is a retrospective case series of three patients with retained surgical textile products who had been misdiagnosed with spinal tumour. The medical records of the patients were reviewed and demographic data, clinical aspects, initial diagnosis, surgical procedures, time interval between previous operation and onset of symptoms, laboratory findings, radiological findings, treatment, and outcome were analysed. Results: The three patients included two women and one man aged between 64 and 67 years. All patients had a previous surgery for lumbar disc herniation. The time from the previous surgical procedures to presentation ranged from 3 to 17 years. All patients presented with non-specific lower back pain and/or radiculopathy without clinical findings of infection. Laboratory parameters were otherwise normal. All three cases had been misdiagnosed as a spinal tumor based on magnetic resonance imaging findings. During new surgical procedures, gauze bandages, i.e., surgical textiles left during a previous operation, were found. Conclusion: Textiloma is an important and rarely mentioned potential neurosurgical complication that may remain asymptomatic for years. They are more common in obese patients, after emergency surgery, and with unplanned changes in surgical procedure such as bleeding and unintended neurosurgical complications. Neuroradiological findings are variable and non-specific; thus, patients could be misdiagnosed with a spinal tumor or abscess. Likewise, in patients with a history of spinal surgery, spinal abscesses, haematomas, hypertrophic scars, fibrosarcomas, rhabdomyosarcomas, and schwannomas should definitely be considered in the differential diagnosis and considered when planning diagnostic procedures. Appropriate antibiotic therapy is recommended when a suppurative complication is present or suspected. Textiloma is a medico-legal complication that can be prevented by the education of surgical staff, the counting method (preoperatively, at closure, and at the end), and use of products with radiopaque barcodes. © Trakya University Faculty of Medicine.
Keywords: Foreign body granuloma; Gauze bandage; Gossypiboma; Lumbar spine; Spinal tumour; Surgical textile products

A Rare Case of Esophageal Submucosal Angiofibroma Resected Completely by Endoscopic Submucosal Dissection - Lin, C.; Lee, W.; Lee, I. (Clinical Gastroenterology and Hepatology, 2013)

Ocular golden galaxy - Naderi, M.; Jadidi, K.; Alishiri, A.; Mosavi, S.A. (JCRS Online Case Reports, 2013)
A 27-year-old man presented to the emergency department with metallic-like foreign-body deposition on the entire aspect of both corneas associated with intense irritation, tearing, and photophobia. The corrected distance visual acuity (CDVA) was counting fingers in the right eye and light perception (LP) in the left eye. Slitlamp examination revealed diffuse, galaxy-like, golden-brown confluent deposits on the cornea, sclera, and conjunctiva of both eyes. The eyes were irrigated several times, followed by foreign-body removal and corneal repair. A penetrating keratoplasty was later performed in the right eye. After 1 year of follow-up, the patient was asymptomatic and the CDVA improved in the right eye but remained LP in the left eye due to macular scar formation secondary to severe tractional macular edema. © 2013 ASCRS and ESCRS.

Costochondritis caused by Aspergillus flavus following cardiac surgery - Mirhosseini, S.J.; Salehi, M.; Ali-Hassan-Sayegh, S.; Forouzannia, S.K.; Karimi-Bondarabadi, A.A. (Acta Medica Iranica, 2013)
Mediastinitis is an infrequent complication after coronary artery bypass graft (CABG) that is associated with prolonged intensive care unit and hospital stay, and increased early and late morbidity and mortality. Patients with mediastinitis have an osteoporotic, fragile, and broken sternum. All foreign bodies as well as infected tissue should be removed. Osteomyelitis of sternum often perseveres after debridement for mediastinitis. In this report, we describe an unusual case of costochondritis caused by aspergillosis following off pump CABG surgery in a male patient in Yazd-Iran. © 2013 Tehran University of Medical Sciences. All rights reserved.
Keywords: Aspergillus flavus; Cardiac surgery; Costochondritis

Sympathetic ophthalmia with sensorineural deafness - report of a case - Venkatesh, R.; Agarwal, M.; Ramesh, V.J.; Singh, S.; Kantha, M.; Biswas, J. (Journal of Ophthalmic Inflammation and Infection, 2013)
Background: The aim of this study is to report a case of sympathetic ophthalmia with sensorineural hearing loss following penetrating trauma. This is an interventional case report. A 23-year-old male presented with bilateral, sudden, profound visual and hearing loss, disorientation, and dizziness. He had a past history of penetrating trauma with an iron rod in the right eye for which he underwent scleral tear repair, vitreo-retinal surgery with intraocular foreign body removal and silicon oil injection. His best corrected visual acuity in the right eye was counting fingers close to the face and was perception of light in the left eye. Clinical evaluation with slit biomicroscopy, indirect ophthalmoscopy, ultrasonography, and pure tone audiometry was suggestive of sympathetic ophthalmia with sensorineural hearing loss. Treatment was started with intravenous methyl prednisolone, oral corticosteroids, and immunosuppressants. Findings: Following treatment, signs of panuveitis showed resolution and improvement in visual, hearing, and neurological symptoms. Conclusions: Sympathetic ophthalmia associated with sensorineural deafness and neurological symptoms is a rare clinical syndrome. Prompt diagnosis and treatment with systemic corticosteroids and immunosuppressant medication may result in clinical improvement. © 2013 Venkatesh et al.
Keywords: Corticosteroids; Deafness; Psychosis; Sympathetic ophthalmia

Internal cardiac defibrillator implant-associated angiosarcoma presenting as suspected implant pouch infection - Smith, S.C.; Bernacki, K.D.; Haft, J.W.; McHugh, J.B. (Cardiovascular Pathology, 2013)
Medical implants have been rarely associated with the development of sarcomas. We report, to our knowledge, the first case of a high-grade epithelioid angiosarcoma developing in the capsule of an internal cardiac defibrillator implanted subcutaneously over the abdomen over 20 years ago. Although the internal cardiac defibrillator generator had been exchanged in the intervening years, recently, the patient showed a year-long history of systemic symptoms suspicious for implant infection, necessitating several internal cardiac defibrillator pocket hematoma evacuations, always with negative microbiologic cultures. Final reexploration identified suspicious tissue with excessive bleeding which was biopsied and proven to be angiosarcoma on histologic examination. Subsequent imaging demonstrated precipitous progression to liver and lung metastases. Though rare, foreign-body-related sarcoma should be considered in the differential diagnosis for presentations suggestive of hemorrhagic or infectious sequelae of medical implants; this case broadens the range of medical devices associated with angiosarcoma to include now very commonly used implantable medical devices. Crown Copyright © 2013 Published by Elsevier Inc. All rights reserved.
Keywords: Angiosarcoma; Cardiac defibrillator; Medical devices

Thiol-ene Michael-type formation of gelatin/poly(ethylene glycol) biomatrices for three-dimensional mesenchymal stromal/stem cell administration to cutaneous wounds - Xu, K.; Cantu, D.A.; Fu, Y.; Kim, J.; Zheng, X.; Hematti, P.; Kao, W.J. (Acta Biomaterialia, 2013)
Mesenchymal stromal/stem cells (MSCs) are considered promising cellular therapeutics in the fields of tissue engineering and regenerative medicine. MSCs secrete high concentrations of immunomodulatory cytokines and growth factors, which exert paracrine effects on infiltrating immune and resident cells in the wound microenvironment that could favorably promote healing after acute injury. However, better spatial delivery and improved retention at the site of injury are two factors that could improve the clinical application of MSCs. In this study, we utilized thiol-ene Michael-type addition for rapid encapsulation of MSCs within a gelatin/poly(ethylene glycol) biomatrix. This biomatrix was also applied as a provisional dressing to full thickness wounds in Sprague-Dawley rats. The three-way interaction of MSCs, gelatin/poly(ethylene glycol) biomatrices, and host immune cells and adjacent resident cells in the wound microenvironment favorably modulated wound progression and host response. In this model we observed attenuated immune cell infiltration, lack of foreign giant cell (FBGC) formation, accelerated wound closure and re-epithelialization, as well as enhanced neovascularization and granulation tissue formation by 7 days. The MSC entrapped in the gelatin/poly(ethylene glycol) biomatrix localized cell presentation adjacent to the wound microenvironment and thus mediated the early resolution of inflammatory events and facilitated the proliferative phases in wound healing. © 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Cell-based therapy; Foreign body response; Inflammation; Macrophages; Mesenchymal stem cells

A study of the bioengineered surgical sponge - Asiyanbola, B. (Technology and Health Care, 2012)
The postoperatively retained foreign body (PORFB) can induce complications leading to the need for follow-up surgery to ensure its removal, to treat or prevent the formation of an abscess, and to minimize the risk of death for the patient and liability for the surgeon and hospital. The most common cause of PORFB complications is the surgical sponge. Previously, PORFB prevention was focused on improved efficiency in RFB counting; however, because of the inability to entirely eliminate human error, cost, and the potentially unproven patient outcome improvement, new approaches have been sought. We examined the use of a novel bioengineered, biodegradable sponge (BSS) to reduce the risk of complications due to PORFBs, thus potentially improving patient outcomes. © 2012-IOS Press and the authors. All rights reserved.
Keywords: automated data identification capture; Biodegradable surgical sponge; retained surgical sponge

A 2-year-old girl with abdominal pain after an action sure to attract attention - Osterhoudt, K.C.; Peranteau, W.H.; Shaw, K.N.; Flake, A.W. (Pediatric Emergency Care, 2012)
Keywords: foreign bodies; intestinal perforation; magnets

Marked infiltration of eosinophils in necrotizing granulomas in the resected hepatic bed after cholecystectomy resulting from gallbladder cancer and metastatic liver cancer is associated with peculiar peripheral eosinophilia - Ohtsuki, Y.; Kimura, M.; Watanabe, R.; Okada, Y.; Teratani, Y.; Kurabayashi, A.; Takeuchi, T.; Lee, G.-H.; Furihata, M. (Medical Molecular Morphology, 2012)
It is known that after transurethral resection of the prostate (TUR-P) or a bladder tumor (TUR-BT), necrotizing granuloma formation associated with massive eosinophil accumulation can be detected at the site of the scar, revealing marked eosinophilia. This condition is called post-TUR prostatitis or cystitis. In the present study, we noticed a similar phenomenon in five patients who underwent cholecystectomy, of whom four had gallbladder adenocarcinoma and one had metastatic liver cancer originating from the rectum. We detected necrotizing granulomas with massive eosinophil accumulation, associated with marked eosinophilia. To induce these phenomena, the interval between the first operation (i.e., cholecystectomy) and the second operation (i.e., resection of the hepatic bed and extrahepatic bile duct) is very important. If the interval was 1 week, no granuloma formation was detected. On the other hand, if it was more than 2 weeks, the resected hepatic bed contained necrotizing granulomas with substantial eosinophil accumulation combined with an increase in peripheral eosinophilia (up to 34% in one case). Secondary resection was necessary to induce eosinophilia after cholecystectomy. In this sense, malignancies possessed a relationship with delayed eosinophilia. In the granulomas, some foreign body-type multinucleated giant cells were positive for both anti-interleukin (IL)-5 and CD68 antibodies. In sharp contrast, no eosinophilia was detected after cholecystectomy, with or without hepatic resection consequent to severe adhesion. Clinicians as well as pathologists should keep in mind that these peculiar phenomena of eosinophil accumulation surrounding the necrotizing granulomas and peripheral eosinophilia after cholecystectomy could occur. © 2012 The Japanese Society for Clinical Molecular Morphology.
Keywords: Cholecystectomy; Eosinophil; Eosinophilia; Gallbladder cancer; Hepatic bed; IL-5; Necrotizing granuloma

Feeding tube placement: Errors and complications - Stayner, J.L.; Bhatnagar, A.; McGinn, A.N.; Fang, J.C. (Nutrition in Clinical Practice, 2012)
Feeding tube placement for enteral nutrition (EN) support is widely used in both critically ill and stable chronically ill patients who are unable to meet their nutrition needs orally. Nasal or oral feeding tubes can be performed blindly at the bedside or with fluoroscopic or endoscopic guidance into the stomach or small bowel. Percutaneous feeding tubes are used when EN support is required for longer periods (>4-6 weeks) and are most commonly placed endoscopically or radiographically. Although generally safe and effective, there is a wide spectrum of known complications associated with feeding tube placement. Errors made at the time of feeding tube placement can result in a number of these procedural and postprocedural complications. In many cases, a single error at the time of placement can result in numerous complications. A thorough knowledge of these errors and avoiding them in practice will decrease iatrogenic complications in a vulnerable population. In addition, early recognition and management of complications will further minimize morbidity and even mortality in enteral feeding tube placement. This article reviews the common errors leading to complications of enteral feeding tube placement and their prevention and management. © 2012 American Society for Parenteral and Enteral Nutrition.
Keywords: enteral nutrition; gastrostomy; jejunostomy; nutritional support

Inflammatory reaction and neotissue maturation in the early host tissue incorporation of polypropylene prostheses - Pascual, G.; Rodríguez, M.; Sotomayor, S.; Pérez-Köhler, B.; Bellón, J.M. (Hernia, 2012)
Purpose: The use prosthetic materials for the surgical repair of abdominal wall defects has become almost standard practice. This study was designed to assess the expression of different growth factors (VEGF/TGF-β1) and macrophages during the early host tissue incorporation of several polypropylene lightweight (PP-LW) - including one partially absorbable - and heavyweight (PP-HW) prosthetic meshes. Methods: Ventral defects were created in the anterior abdominal wall of New Zealand rabbits and repaired by fixing PP-LW meshes of different pore size and a low porosity PP-HW mesh to the edges of the defect. Following killing 14 days after implant, specimens were taken to examine TGF-β1/VEGF gene and protein expression by qRT-PCR and immunohistochemistry. The macrophage response was also assessed. Results: All the materials showed good host tissue incorporation, with a more severe inflammatory reaction and greater numbers of macrophages recorded in the partially absorbable LW implants. Relative amounts of VEGF mRNA were significantly lower for the LW partially absorbable implants compared with the remaining LW meshes. Protein expression of VEGF showed undetectable or minimum staining in the different groups. TGF-β1 mRNA levels were also lower in the partially absorbable group compared with one of PP-LW type of mesh. Gene expression patterns were consistent with the TGF-β1 protein levels detected. Conclusions: The results suggest that VEGF and TGF-β1 expression were independent of mesh pore size. The expression of both growth factors and the macrophage response were correlated with the presence of biodegradable material in the mesh. The presence of absorbable material in the LW mesh gave rise to a more intense inflammatory reaction and the reduced synthesis of growth factors known to contribute to neotissue maturation. © 2012 Springer-Verlag.
Keywords: Abdominal meshes; Foreign body reaction; Growth factor; Wound healing

Interview with a quality leader: Dr. Verna Gibbs on surgical safety. Interview by Susan V. White. - Gibbs, V. (Journal for healthcare quality : official publication of the National Association for Healthcare Quality, 2012)
Dr. Verna Gibbs describes the "NoThing Left Behind" Program designed to eliminate retained devices from surgical procedures. She explains the genesis of the program along with adjuncts to counting including computer-assisted sponge count, radiofrequency detection system, radiofrequency identification system, and the Sponge ACCOUNTing system. She provides comments on the use of these adjuncts with responses on their effectiveness on improving safety. © 2011 National Association for Healthcare Quality.

Foreign body-induced abscess resembling pancreatic neoplasia - Garment, A.R.; Schwartz, M.B.; Axsom, K.M. (Journal of General Internal Medicine, 2012)
We report the case of a 44-year-old man presenting with abdominal pain and leukocytosis. His initial computed tomography demonstrated a pancreatic head mass concerning for pancreatic adenocarcinoma. However, on further review of the patient's imaging, the mass was determined to be an abscess caused by foreign body ingestion and gastric perforation rather than cancer. This report describes the clinical and radiographic distinctions between pancreatic neoplasia and abscess. It also reviews the pertinent medical literature on how such viscus perforations affect subsequent prognostication and clinical management. © Society of General Internal Medicine 2012.
Keywords: Abscess; Foreign body; Pancreatic cancer; Pancreatic neoplasia

Autologous fascia graft as a biological barrier to silicone application in rabbits - Tuncel, N.; Tuncel, H.; Bayrak, I.; Gunes, P.; Uzunismail, M.A. (Journal of the College of Physicians and Surgeons Pakistan, 2012)
Objective: To determine the cellular effects of providing a fascial interface around subcutaneously-placed silicone implants, in terms of capsule thickness, myofibroblast/fibroblast cell count and inflammatory cell count. Study Design: Interventional, comparative study. Place and Duration of Study: Istanbul University Cerrahpasa Medical Faculty, Laboratory of Experimental Animals, Istanbul, Turkey, from May to September 2008. Methodology: A total of 16 adult New Zealand male rabbits with mean weight of 2508 ± 360 g were used in the study. Animals were divided into two groups as experiment and control groups with equal number of rabbits in each. Fascia injection was applied on silicone implant in the experiment group and compared with the control group in terms of capsule thickness, myofibroblast/fibroblast cell count and inflammatory cell count. At the end of the experiment, tissue samples were examined macroscopically and microscopically for the above. Statistical analysis of data was performed using student's t-test. Results: A statistically significant difference was found between experiment group and control group in terms of mean capsule thickness, mean myofibroblast and fibroblast cell counts and cell density (p < 0.05, each). Conclusion: Fascia tissue barrier prevent silicone rod reaction and foreign body reaction developing against silicone prosthesis in the studied animal model.
Keywords: Fascia. Silicone implant. Rabbit. Silicone rod reaction. Foreign body reaction

Spontaneous gastric perforation in an 11-year-old boy with anorexia nervosa: Rare presentation with right iliac fossa pain - Hashmi, K.S.; Ellul, T.; Leopard, D.C.; Woodward, A. (BMJ Case Reports, 2012)
Spontaneous gastric perforation is rare in children. It is usually associated with prematurity, foreign bodies and trauma. Anorexia nervosa (AN) can be an underlying condition although no cases are reported in the literature. We are reporting a rare case of 1- year-old boy with AN who presented with right iliac fossa (RIF) pain mimicking acute appendicitis. Intraoperative findings proved a gastric perforation. Pathophysiology of this condition in AN is poorly understood. Gastric smooth muscle atrophy and ischaemia can be the possible underlying mechanisms. The case discussed here highlights the fact that any abdominal pain in patients with underlying eating disorders (EDs) should raise suspicion of perforation as diagnosis can be far more complicated. Copyright 2012 BMJ Publishing Group. All rights reserved.

Effectiveness of a radiofrequency detection system as an adjunct to manual counting protocols for tracking surgical sponges: A prospective trial of 2,285 patients - Rupp, C.C.; Kagarise, M.J.; Nelson, S.M.; Deal, A.M.; Phillips, S.; Chadwick, J.; Petty, T.; Meyer, A.A.; Kim, H.J. (Journal of the American College of Surgeons, 2012)
Background: Despite rigorous manual counting protocols and the classification of retained surgical items (RSIs) as potential "never events," RSIs continue to occur in approximately 1 per 1,000 to 18,000 operations. This study's goals were to evaluate the incorporation of a radiofrequency detection system (RFDS) into existing laparotomy sponge- and Raytec-counting protocols for the detection of RSIs and define associated risk factors. Study Design: All patients undergoing surgery at the University of North Carolina Hospitals from September 2009 to August 2010 were enrolled consecutively. The performance of an RFDS-incorporated accounting protocol for detecting RSIs was prospectively evaluated. Several operative metrics were recorded to identify risk factors for miscounts. Results: A total of 2,285 patients were enrolled. One near miss was detected by the RFDS. Thirty-five miscounts occurred, for a rate of 1.53%. The ultimate locations of miscounted items were surgical site (n = 11), within operative suite (n = 10), surgical drapes (n = 2), and emergency protocol deviations (n = 12). Perioperative variables associated with miscounts were higher estimated volume of blood lost, longer operations, higher number of laparotomy sponges used, open surgical approach, "after hours" operations, change of surgical team during operation, weekend or holiday operations, unanticipated changes in operative plan during surgery, and emergency operations. Body mass index was not associated with miscounts. Surveys completed by participating surgical staff suggested high confidence in the RFDS for prevention of RSIs. Conclusions: The incorporation of the RFDS assisted in the resolution of a near-miss event (1 of 2,285) not detected by manual counting protocols and assisted in the resolution of 35 surgical-sponge miscounts. No known RSIs occurred during the study period. Risk factors for miscounts were identified and can help identify at-risk surgical populations. © 2012 American College of Surgeons.

Assessment of radiofrequency device sensitivity for the detection of retained surgical sponges in patients with morbid obesity - Steelman, V.M.; Alasagheirin, M.H. (Archives of Surgery, 2012)
Hypothesis: Retained surgical sponges are serious medical errors that result in negative patient outcomes.Aradiofrequency( RF)matfor the operatingroombedhas recently been introduced to detect the presence of a retained surgical sponge. The study objectives were to evaluate the sensitivity and specificity of the RF mat for the detection of surgical sponges through the torso of individuals with varying body habitus and to compare the sensitivity of the RF mat with that of the RF wand. We hypothesized that the sensitivity and specificity of the RF technology would be comparable to published findings of themanual sponge count by operating room personnel. Design: Aprospective, crossover, double-blinded study design was used. Participants served as theirowncontrols. Setting: Large Midwestern academic medical center. Participants: In total, the first phase of the study enrolled 203 participants, including 129 (63.5%)with morbid obesity. One hundred seventeen of 203 participants were also enrolled in the second phase of the study. Main Outcome Measures: The study participants reclined in a supine position on top of an RF mat. Four surgical sponges were sequentially placed on top of the torso in locations approximating the abdominal quadrants. The torso was scanned for sponges. In a subset of participants, 4 surgical sponges were sequentially placed underneath the torso, and an RF wand was passed over the abdomen. Results: Overall, 812 readings were obtained with the RF mat, and 468 readings were obtained with the RF wand. Twelve false-negative readings were obtained with the RF mat, exclusively in participants with super morbid obesity (body mass index [calculated as weight in kilograms divided by height in meters squared] >50.0). Overall, the sensitivity of the RF mat was 98.1%, and the specificity of the RF mat was 100.0%. In the subset of 117 participants in whom the RF wand was also used, the sensitivity and specificity of the wand were each 100.0%. Conclusions: The sensitivity and specificity of RF device technology are much higher than those of surgical sponge counts or published findings on the use of intraoperative radiographs to identify retained surgical sponges. The RF wand is more sensitive than the RF mat in individuals with morbid obesity. ©2012 American Medical Association. All rights reserved.

Risk factors associated with incorrect surgical counts - Rowlands, A. (AORN Journal, 2012)
Incorrect surgical counts after surgery are a perplexing problem for nurses working in the perioperative environment. To determine factors associated with an incorrect surgical count, this cross-sectional, correlational study examined explanatory variables (eg, patient and nurse characteristics, intraoperative circumstances, staff involvement) by using data abstracted from perioperative medical records and primary data collected from perioperative nurses. In the final multivariate analysis, six variables were significantly associated with an incorrect surgical count: a higher surgical risk, a lower body mass index, a complicated procedure, an unplanned procedure, an increased number of perioperative personnel involved, and an increased number of specialty teams involved. © 2012 AORN, Inc.
Keywords: Incorrect surgical counts; Patient safety; Perioperative nursing; Retained foreign bodies; Retained surgical items

An unusual case of small bowel obstruction in a child caused by ingestion of water-storing gel beads - Moon, J.S.; Bliss, D.; Hunter, C.J. (Journal of Pediatric Surgery, 2012)
Foreign body ingestion occurs most commonly in the pediatric population. Small bowel obstruction is a rare complication that can occur, and surgical intervention is required. We present the first report of a case of an 18-month-old child with a jejunal obstruction caused by ingestion of water-storing gel beads used for botanical arrangements. The child presented with obstipation and nonbloody, nonbilious emesis. Symptoms resolved after a large bead 3 cm in diameter was retrieved via laparoscopic-assisted excision. This case suggests that water-storing gel beads are particularly dangerous foreign bodies and should be kept out of the reach of children. © 2012 Elsevier Inc. All rights reserved.
Keywords: Foreign body; Intestine obstruction; Pediatric

The prolonged presence of a fish bone in the neck - Watanabe, K.; Amano, M.; Nakanome, A.; Saito, D.; Hashimoto, S. (Tohoku Journal of Experimental Medicine, 2012)
Fish bones are one of the most frequently observed ingested foreign bodies in the pharynx-esophagus. Fish bones have a tendency to stick and penetrate the mucosa, which can occasionally lead to severe or lethal complications. The extraluminal migration of fish bones in the upper digestive tract is a rare event, and it is even more unlikely that the foreign body will remain in the neck for a prolonged period. We report the unique case of a 69-year-old woman who remained asymptomatic, while a fish bone was lodged in her neck for 9 months. Finally, after her anterior neck had become swollen, she underwent neck exploration, which revealed that the fish bone was embedded in the scar tissue running from within the thyroid gland to outside of the thyroid. Treatment proceeded without complications, and the foreign body was removed successfully. The length of the fish bone was 34 mm. Intraoperative ultrasonography was able to identify the fish bone in situ using real-time imaging; therefore, we recommend this technique for locating migrated foreign bodies in the neck. © 2012 Tohoku University Medical Press.
Keywords: Complication; Fish bone; Migration; Prolonged presence; Ultrasonography

Small bowel adenocarcinoma: A case of atypical CT scan appearance - Eltweri, A.M.; Bowrey, D.; Taylor, M. (BMJ Case Reports, 2012)
A 73-year-old man presented to the surgical assessment unit with recurrent episodes of central abdominal pain and vomiting for 18 months. He has the past medical history (PMH) of hypertension and has been using his denture for 35 years; he had no past surgical history; he drinks alcohol socially and not a smoker. This patient was investigated for iron defi ciency anaemia with upper and lower gastrointestional endoscopy, as the patient had positive faecal occult blood; rectal biopsy showed no sign of inflammation and no evidence of malignancy; blood investigation showed Hb 9.8 g/dl, white cell count 14.8, mean cell volume 86.3, mean cell haemoglobin 26.9 and C reactive protein 13. This patient underwent a CT scan of the chest, abdomen and pelvis; the latest one showed that there is a short segment of the middle part of the small bowel that looks thickened and within which there is a high-density calcified shadow which is reported as an ingested foreign body or a tooth fragment; the patient underwent laparotomy and the histology results revealed 30 mm well differentiated/moderately differentiated adenocarcinoma.

Gossypiboma - Liu, Y.-C.; Huang, C.-M. (Digestive and Liver Disease, 2012)

Vitalization of porous polyethylene (Medpor®) with chondrocytes promotes early implant vascularization and incorporation into the host tissue - Ehrmantraut, S.; Naumann, A.; Willnecker, V.; Akinyemi, S.; Körbel, C.; Scheuer, C.; Meyer-Lindenberg, A.; Menger, M.D.; Laschke, M.W. (Tissue Engineering - Part A, 2012)
Porous polyethylene (Medpor®) is frequently used in craniofacial reconstructive surgery. The successful incorporation of this alloplastic biomaterial depends on adequate vascularization. Here, we analyzed whether the early vascularization of porous polyethylene can be accelerated by vitalization with human chondrocytes. For this purpose, small polyethylene samples were coated with platelet-rich plasma (PRP) or a suspension of PRP and human chondrocytes. Uncoated polyethylene samples served as controls. Subsequently, the samples were implanted into the dorsal skinfold chamber of CD-1 nude mice to repetitively analyze their vascularization and biocompatibility by means of intravital fluorescence microscopy. PRP-chondrocyte-coated polyethylene exhibited an accelerated and improved vascularization when compared with the other two groups. This was indicated by a significantly higher functional capillary density of the microvascular network developing around the implants. Moreover, a leukocyte-endothelial cell interaction was found in a physiological range at the implantation site of all three groups, demonstrating that the vitalization with PRP and chondrocytes did not affect the good biocompatibility of the alloplastic material. Additional histological, immunohistochemical, and in situ hybridization analyses revealed that the chondrocytes formed a bioprotective tissue layer, which prevented the accumulation of macrophages and foreign body giant cells on the polyethylene surface. These findings clearly indicate that vitalization of polyethylene with chondrocytes promotes early implant vascularization and incorporation into the host tissue and, thus, may be a promising approach that prevents postoperative complications such as implant extrusion, migration, and infection. © 2012 Copyright, Mary Ann Liebert, Inc.

Succinylcholine-induced hyperkalemia in a patient with multiple sclerosis - Levine, M.; Brown, D.F.M. (Journal of Emergency Medicine, 2012)
Background: Succinylcholine administration is associated with hyperkalemia in patients with a variety of medical conditions, including many neuromuscular disorders. Nonetheless, there is a paucity of literature describing hyperkalemia after the administration of succinylcholine to patients with multiple sclerosis. Case Report: This case report describes a 38-year-old woman with multiple sclerosis who developed life-threatening hyperkalemia after the administration of succinylcholine during rapid sequence intubation. Conclusion: This case highlights the potential for iatrogenic hyperkalemia after succinylcholine in patients with neurologic diseases, including multiple sclerosis.
Keywords: hyperkalemia; intubation; multiple sclerosis; RSI; succinylcholine

Incidence and outcome after infection of megaprostheses - Pilge, H.; Gradl, G.; von Eisenhart-Rothe, R.; Gollwitzer, H. (HIP International, 2012)
Recent advances in chemotherapy and radiation therapy in the treatment of malignant bone tumours as well as the consistent increase of revision arthroplasties have been followed by an increased use of megaprostheses. These large foreign bodies make infection a common and feared complication. Infection rates of 3 - 31% have been reported (average approx. 15%), often in conjunction with risk factors, e.g. the anatomic region (pelvis implants in particular), implant alloy, and underlying reason for implantation of a megaprosthesis. Apart from the basic principles of septic revision arthroplasty, special patient and implant factors have to be considered in infected megaprosthesis, which we have summarised in our paper (e.g. life expectancy, implant design, spacers and external stabilisation). This article further analyses the current literature available for these cases and summarises outcome after treatment of periprosthetic infections. © 2012 Wichtig Editore.
Keywords: Infection; Megaprosthesis; Modular arthroplasty; Periprosthetic infection; Revision arthroplasty; Tumor arthroplasty

Transmyocardial voyage of a temporary epicardial lead: An unusual long-term complication - Sheikh, M.; Bruhl, S.R.; Omer, S.; Schwaan, T.; Grubb, B.; Cooper, C.; Kanjwal, Y. (PACE - Pacing and Clinical Electrophysiology, 2012)
Although the majority of temporary epicardial leads used during cardiac surgery are removed in the perioperative period, occasionally, the wires are cut and allowed to retract into the subcutaneous tissue. Complications arising from such retained epicardial wires are rare. We present a case of transmyocardial migration of a retained epicardial wire through the right ventricular myocardium into the pulmonary artery in a patient who had undergone coronary artery bypass graft surgery 13 years ago. We describe the presentation and successful management of this case. © 2011 Wiley Periodicals, Inc.
Keywords: congestive heart failure; pacing

A persisting puzzling pneumonia in a young man - Baker, J.; McClelland, D.; Dempsey, O.J. (BMJ (Online), 2012)

Comparative economic analyses of patient safety improvement strategies in acute care: A systematic review - Etchells, E.; Koo, M.; Daneman, N.; McDonald, A.; Baker, M.; Matlow, A.; Krahn, M.; Mittmann, N. (BMJ Quality and Safety, 2012)
Background: The objective was to systematically review comparative economic analyses of patient safety improvements in the acute care setting. Methods: A systematic review of 15 patient safety target conditions and six improvement strategies was conducted. The authors searched the published literature through Medline (2000eNovember 2011) using the following search terms for costs: 'costs and cost analysis', 'cost-effectiveness', 'cost' and 'financial management, hospital'. The methodological quality of potentially relevant studies was appraised using Cochrane rules of evidence for clinical effectiveness in quality improvement, and standard economic methods. Results: The authors screened 2151 abstracts, reviewed 212 potentially eligible studies, and identified five comparative economic analyses that reported a total of seven comparisons based on at least one clinical effectiveness study of adequate methodological quality. Pharmacist-led medication reconciliation to prevent potential adverse drug events dominated (lower costs, better safety) a strategy of no reconciliation. Chlorhexidine for vascular catheter site care to prevent catheter-related bloodstream infections dominated a strategy of povidone-iodine for catheter site care. The Keystone ICU initiative to prevent central line-associated bloodstream infections was economically dominant over usual care. Detecting surgical foreign bodies using standard counting compared with a strategy of no counting had an incremental cost of US$1500 (CAN$1676) for each surgical foreign body detected. Several safety improvement strategies were less economically attractive, such as bar-coded sponges for reducing retained surgical sponges compared with standard surgical counting, and giving erythropoietin to reduce transfusion requirements in critically ill patients to avoid one transfusion-related adverse event. Conclusions: Five comparative economic analyses were found that reported a total of seven comparisons based on at least one effectiveness study of adequate methodological quality. On the basis of these limited studies, pharmacist-led medication reconciliation, the Keystone ICU intervention for central line-associated bloodstream infections, chlorhexidine for vascular catheter site care, and standard surgical sponge counts were economically attractive strategies for improving patient safety. More comparative economic analyses of such strategies are needed.

Healthcare-associated vs. hospital-acquired Staphylococcus aureus bacteremia - Bishara, J.; Goldberg, E.; Leibovici, L.; Samra, Z.; Shaked, H.; Mansur, N.; Paul, M. (International Journal of Infectious Diseases, 2012)
Objective: To analyze clinical features and outcomes of patients with hospital-acquired (HA) and healthcare-associated (HCA) Staphylococcus aureus bacteremia. Methods: A retrospective cohort study was conducted from 1988 to 2007. We compared patients with clinically significant HA with those with HCA S. aureus bacteremia. Risk factors for 30-day all-cause mortality were assessed using multivariable logistic regression analysis. Cox regression analysis was used to estimate the hazard ratio (HR) for 5-year mortality with 95% confidence intervals (CI). Results: Of 1261 episodes, 735 (58.3%) were HA and 526 (41.7%) were HCA. The percentage of MRSA was 48.2% (354/735) in HA vs. 42.2% (222/526) in HCA bacteremia; p= 0.04. The percentages of HCA S. aureus bacteremia and MRSA bacteremia did not vary throughout the study period. Mortality at 30 days was 40.2% (507/1261) and at 1 year was 63.4% (800/1261); this was comparable for HA and HCA bacteremia. Five-year survival curves in both settings followed very similar patterns (HR 1.01, 95% CI 0.89-1.15). Risk factors for 30-day mortality were similar, except for primary bacteremia and pre-existing heart valve disease in the HA group. Conclusions: HCA S. aureus bacteremia shares many similarities with HA bacteremia with respect to the prevalence of MRSA strains, mortality rates, and risk factors for death, and should be managed similarly. © 2012 International Society for Infectious Diseases.
Keywords: Healthcare; Mortality; MRSA; Nosocomial; Staphylococcus aureus

In vitro and in vivo characteristics of gentamicin-supplemented polyvinylidenfluoride mesh materials - Klink, C.D.; Binnebösel, M.; Lambertz, A.; Alizai, H.P.; Roeth, A.; Otto, J.; Klinge, U.; Neumann, U.P.; Junge, K. (Journal of Biomedical Materials Research - Part A, 2012)
To reduce infection rates after mesh implantation antibiotic-coated meshes were designed. The aim of the study was to analyze biocompatibility and in vitro efficiency of a modified gentamicin-supplemented polyvinylidenfluoride mesh. Twenty rats were randomized to two groups (PVDF group and Genta group). Mesh material was implanted subcutaneously. Blood samples were taken to determine the gentamicin serum concentration. Seven and 90 days after mesh implantation, animals were euthanized. The inflammatory tissue response was characterized by analyzing the foreign body granuloma. Cellular immune response was analyzed by immunohistochemical investigations. The collagen type I/III ratio was estimated by crosspolarization microscopy. In vitro agar diffusion test, suspension test, and gentamicin release were characterized. Agar diffusion and suspension test showed efficient antibiotic effects of the mesh in vitro. Serum concentrations of gentamicin showed a peak value 1 h postoperatively with a decline within the next day. The total size of the granuloma was significantly smaller in the Genta group compared to the PVDF group at both points of time. Except of a short period of increased expression of CD68 in the Genta group after 7 days, no further difference was found analyzing cellular immune response. The collagen type I/III ratio was widely constant analyzing the two mesh types without significant differences comparing both mesh materials. A significantly decreased foreign body granuloma formation compared to the pure PVDF mesh group was found. In vitro analysis showed efficient antibiotic effects of the Gentamicin supplementation compared to the pure PVDF mesh. © 2012 WILEY PERIODICALS, INC.
Keywords: abdominal wall hernia; antibiotic coating; collagen type I/III ratio; gentamicin; mesh repair; PVDF

Biocompatibility of a novel poly(butyl succinate) and polylactic acid blend - Kun, H.; Wei, Z.; Xuan, L.; Xiubin, Y. (ASAIO Journal, 2012)
A novel poly(butyl succinate) (PBS) and polylactic acid (PLA) blend with the favorable mechanical and degradable properties may be applied in the field of biomedicine. The purpose of this study was to investigate the in vitro and in vivo biocompatibilities of the PBS/PLA blend for future application. For in vitro analysis, the L929 fibroblasts and bone marrow stem cells (BMSCs) had been chosen to assess the cytocompatibility. The extract of PBS/PLA blend did not show any cytotoxicity to the L929 and BMSCs by Cell Counting Kit-8 and lactate dehydrogenase assays. Meanwhile, the results of the cytocompatibility showed no difference between the PBA/PLA blend and pure PLA and PBS. Subsequently, they were implanted into rats subcutaneously for in vivo study. It was found that similar with pure PLA and PBS, PBS/PLA blend caused the mild inflammation and foreign body reaction in rats during the consecutive 9 month implantation. However, the status of fibrosis surrounding PBS/PLA blend was superior to the pure PLA and PBS. In all, it was demonstrated that the novel PBS/PLA blend had excellent biocompatibilities in vitro and in vivo. Copyright © 2012 by the American Society for Artificial Internal.

Rhizobium radiobacter wound infection in a patient with diabetes-fact, factitious or just plain unlucky? - Dhatariya, K.; Gooday, C.; Morrow, D.; Murchison, R.; Turner, J.; Hutchinson, R.; Williams, H. (QJM, 2012)

Peritoneal catheter implantation elicits IL-10-producing immune-suppressor macrophages through a MyD88-dependent pathway - Min, S.-Y.; Fu, Y.; Hutcheson, J.; Wu, T.; Khobahy, E.; Zhu, J.; Vanarsa, K.; Du, Y.; Park, M.-J.; Park, H.-S.; Saxena, R.; Kim, H.-Y.; et al. (Clinical Immunology, 2012)
Catheters are implanted into the peritoneal cavity during the process of peritoneal dialysis. Though these catheters may be effective and beneficial, the impact of catheters on the immune system is poorly understood. Catheters and other devices implanted in the peritoneal cavity elicit a foreign body reaction. However, the immunological consequences of this remain uncharacterized. To model this, catheters were implanted into the peritoneal cavity of healthy mice. Catheter implantation induced rapid cellular changes within the peritoneal cavity. Whereas B-cells and T-cells were reduced, catheter implantation was associated with the rapid expansion of F4/80-low-positive, CD11b-positive macrophages that elaborated IL-10, and suppressed T-cell division and Th1 skewing in co-culture assays. Peritoneal catheter elicited macrophages had increased Jmjd3 but reduced NF-κB activation, and their emergence was MyD88-dependent. Collectively, these studies indicate that foreign body implantation into the peritoneal cavity is associated with the expansion of suppressor macrophages. Whether peritoneal cavity catheter implantation may have systemic immunoregulatory roles remains to be explored. © 2012 Elsevier Inc.
Keywords: Foreign body reaction; IL-10; Immune regulation; Macrophages; Peritoneal dialysis

Fatal pulmonary embolism: When the cause is not a thrombus - Franco, E.; Frea, S.; Solaro, C.; Conti, V.; Pinneri, F. (Spine, 2012)
Study Design.: We report a case of pulmonary embolism of polymethylmethacrylate material after percutaneous vertebroplasty. Objective.: To describe a severe vertebroplasty complication, the pulmonary embolism, which proved to be fatal in a patient with many chronic disabilities. Summary of Background Data.: Until 2007, the literature noted that the risk of embolism of polymethylmethacrylate after a percutaneous vertebroplasty counted a small number of pulmonary cement embolism and a smaller number of fatal consequences. The most recent research revealed that the risk of a pulmonary cement embolism ranges from 3.5% to 23% for osteoporotic compression fractures. Methods.: This study is a case report of an 80-year-old patient with multiple medical comorbid factors, chronic obstructive pulmonary disease, mild renal failure, osteoporosis, and hepatic cirrhosis. Symptoms of pulmonary embolism developed 1 month after a percutaneous vertebroplasty. An echocardiography report suggested that the cement infiltrated the right atrium and the right pulmonary artery, and this was confirmed by a computed tomographic scan. As the therapy with oxygen and low-molecular-weight heparin failed to solve the thrombus, the patient required a surgical tricuspid annuloplasty and the extirpation of the right atrial and right pulmonary masses. Results.: The course of the operation was complicated by pulmonary infection, and the patient ultimately succumbed to infection/respiratory failure. Conclusion.: The presence of intravascular/ intracardiac foreign bodies is underreported in literature, but it is quite common in clinical practice. We need to discuss the choice of some non-risk-free interventions such as vertebroplasty in older patients already affected by multiple main disabilities. © 2012 Lippincott Williams and Wilkins.
Keywords: intracardiac foreign body; pulmonary embolism; vertebroplasty

A serious medicolegal problem after surgery: Gossypiboma - Gümüş, M.; Gümüş, H.; Kapan, M.; Önder, A.; Tekbaş, G.; Baç, B. (American Journal of Forensic Medicine and Pathology, 2012)
After surgery, the most common foreign bodies retained in the abdominal cavity are the surgical sponges. The aim of the present study was to emphasize the importance of gossypiboma, which is a serious and medicolegal problem. The records of 12 patients with a confirmed diagnosis of gossypiboma after abdominal surgery at Dicle University Hospital were retrospectively reviewed between January 1994 and December 2009. Eight of the 12 patients were females, and 4 were males. Previously, 7 patients had been operated on electively, and 5 had undergone operations on an emergency basis. Abdominal ultrasonography clearly demonstrated gossypibomas in 5 patients, and computed tomography demonstrated a more precise image of retained surgical sponges in 3 patients. One patient died because of ventricular fibrillation; the other 11 patients were discharged in good health. To eliminate the risk of gossypibomas, all sponges should be counted at least twice (once preoperatively and once postoperatively); use of small sponges should be avoided during laparotomy, and only sponges with radiopaque markers should be used. The surgeon should explore the abdomen before closure. In cases in which the sponge count is uncertain, an abdominal x-ray should be performed before closure. Copyright © 2012 Lippincott Williams & Wilkins.
Keywords: gossypiboma; intra-abdominal; surgical sponges

Open Versus Endovascular Stent Graft Repair for Abdominal Aortic Aneurysms: An Historical View - Rutherford, R.B. (Seminars in Vascular Surgery, 2012)
Development of endovascular abdominal aortic aneurysms repair (EVAR), now in its 4th decade, has involved at least 16 different devices, not counting major modifications of some, only 4 of which have emerged from clinical trials and gained US Food and Drug Administration approval. The main impetus behind EVAR has been its potential for significantly reducing procedural mortality and morbidity, but it was also expected to speed recovery and reduce costs through decreased use of hospital resources. At the outset, EVAR was touted as a better alternative to OPEN in high-risk patients with large abdominal aortic aneurysms, and to "watchful waiting" (periodic ultrasound surveillance) for those with small abdominal aortic aneurysms. This new technology has evoked a mixed response with enthusiasts and detractors debating its pros and cons. Bias and conflict of interest exist on both sides. This review will attempt to present a balanced review of the development and current status of this controversial competition between EVAR and OPEN, comparing them in terms of the following key considerations: mortality and morbidity, complications, failure modes and durability, and costs. © 2012 Elsevier Inc.

Intercollegiate exam - viva in paediatric otolaryngology - paediatric emergencies - Bajaj, Y.; Kapoor, K.; Jephson, C.G.; Albert, D.M. (Otorhinolaryngologist, 2012)

Imaging and clinical findings of a gossypiboma migrated into the stomach - Erbay, G.; Koç, Z.; Çalişkan, K.; Araz, F.; Ulusan, Ş. (Turkish Journal of Gastroenterology, 2012)
In the presented case, the radiologic, endoscopic and surgical findings of a gossypiboma that migrated into the stomach are presented. A 63-year-old woman presented with epigastric pain, and her clinical and laboratory findings were compatible with pancreatitis. Upper gastrointestinal endoscopy revealed a foreign body at the greater curvature of the stomach. Computed tomography and magnetic resonance imaging showed a mass consistent with a gossypiboma that had migrated into the stomach transmurally. This is a first case of a gossypiboma diagnosed endoscopically.
Keywords: Computed tomography; Magnetic resonance imaging; Transmural migration of gossypiboma

Implementing AORN recommended practices for prevention of retained Surgical Items - Goldberg, J.L.; Feldman, D.L. (AORN Journal, 2012)
Retention of a surgical item is a preventable event that can result in patient injury. AORN's "Recommended practices for prevention of retained surgical items" emphasizes the importance of using a multidisciplinary approach for prevention. Procedures should include counts of soft goods, needles, miscellaneous items, and instruments, and efforts should be made to prevent retention of fragments of broken devices. If a count discrepancy occurs, the perioperative team should follow procedures to locate the missing item. Perioperative leaders may consider the use of adjunct technologies such as bar-code scanning, radio-frequency detection, and radio-frequency identification. Ambulatory and hospital patient scenarios are included to exemplify appropriate strategies for preventing retained surgical items. © 2012 AORN, Inc.
Keywords: Adjunct technology; Recommended practices; Retained surgical items; Sponge count; Surgical count; Unretrieved device fragments

Surgical Count Practice Variability and the Potential for Retained Surgical Items - Edel, E.M. (AORN Journal, 2012)
Validating existing count practices and reducing individual practice variance are necessary to decrease the risk for retained surgical items. A quality improvement project was undertaken at one large city hospital to identify best practice and eliminate variability in count practices. The project included an analysis of 20 surgical count policies from hospitals across the country and a review of count practices among nurses and surgical technologists at the facility. Assessment of the policies and practices indicated that clinical practice requirements in the policies varied greatly, and there was a high degree of count practice variability among staff members. The facility OR manager and OR quality coordinator collaborated with staff nurses and surgical technologists to identify practices that created variability and then addressed each one to create a new count policy and reduce the risk of retained surgical items. © 2012 AORN, Inc.
Keywords: Perioperative counts; Policies and procedures for counts; Retained surgical items; Surgical counts

A Nurse-led Approach to Developing and Implementing a Collaborative Count Policy - Norton, E.K.; Micheli, A.J.; Gedney, J.; Felkerson, T.M. (AORN Journal, 2012)
During the 2007 meeting of the Child Health Corporation of America Operating Room Director's Forum, members identified two major discrepancies in surgical count policies among the member hospitals: variations for instrument counts in pediatrics and exceptions to radiographic verification when needle counts were incorrect. The group agreed to collaboratively develop a pediatric count policy based on directors' expertise and current literature to help improve count practices. The task force members reviewed the literature as well as count policies from 30 member hospitals to identify and combine best practices and to create a single, standardized count policy. The project exemplifies a successful nurse-led, national group effort. The outcome is a policy that represents best practice in pediatrics and is a first step toward future opportunities to improve patient safety. © 2012 AORN, Inc.
Keywords: Collaboration; Count policy; Pediatrics; Prevention of retained surgical items; Surgical counts

Paraspinal textiloma after posterior lumbar surgery: A wolf in sheep's clothing - Akhaddar, A.; Boulahroud, O.; Naama, O.; Al-Bouzidi, A.; Boucetta, M. (World Neurosurgery, 2012)
Objective: Paraspinal textiloma (ParaTex) is a well-known complication after posterior lumbar surgery. However, there are few articles on this topic, probably because of medicolegal concerns. In addition, patients with ParaTex can remain asymptomatic for months or even years unless it causes complications. The purpose of this study is to review our experience on this "undesirable" topic to increase awareness among spinal surgeons and radiologists and avoid unnecessary morbidity, which is still being encountered. Methods: This study is a retrospective case series of six patients with ParaTex who underwent posterior lumbar spinal surgery in our neurosurgical department between January 2000 and December 2010. The medical records of each patient were reviewed and demographic data, clinical characteristics, initial diagnosis, surgical procedures, time interval between operation and onset of symptoms, biological and radiologic findings, treatment, and outcome were analyzed. Results: The six patients included four women and two men with a mean age of 48 years. Four patients had a history of lumbar disc herniation, one had undergone a laminectomy for a lumbar spinal stenosis, and a Gill's procedure was performed in one patient with a lumbar spondylolisthesis. The time from the causative operation to presentation ranged from 2 months to 6 years. All patients presented with nonspecific lower back pain and/or surgical site infection without fever or neurological symptoms. Laboratory parameters showed increased blood sedimentation rates and/or C-reactive protein level in four patients. Bacteria were isolated in only one patient. Five patients were evaluated with computed tomography scan, and this showed the spongiform pattern with gas bubbles in three cases. Magnetic resonance imaging was performed in two patients. The signal intensity varies according to stage and fluid content of the lesion. The ParaTex was removed surgically in all patients with a good outcome. Conclusions: ParaTexs are more common in obese patients, after emergency surgery, and with unplanned changes in surgical procedure. On computed tomography scan, the classic spongiform appearance is highly suggestive. Magnetic resonance imaging findings are variable and less specific, but confrontation of imaging data with the surgical history helps with the preoperative diagnosis. In the early postoperative period symptoms are related to the exudative response; at later times symptoms may be linked to pseudotumor formation clinically and radiologically. Appropriate antibiotic therapy is recommended when a septic complication is present or suspected. Strict measures must be taken to prevent this complication. Surgical sponges should always be counted at least three times (preoperatively, at closure, and at the end), radiopaque markers should be used, and if there is doubt, intraoperative radiography must be performed. © 2012 Elsevier Inc.
Keywords: Foreign body granuloma; Gossypiboma; Infection; Lumbar spine; Sponge; Surgical complication; Textiloma

Late presentation of massive pleural effusion from intrathoracic migration of a ventriculoperitoneal shunt catheter: Case report and review of the literature - Glatstein, M.M.; Roth, J.; Scolnik, D.; Haham, A.; Rimon, A.; Koren, L.; Constantini, S. (Pediatric Emergency Care, 2012)
We report an unusual case of ventriculoperitoneal (VP) shunt intrathoracic migration, associated with massive symptomatic hydrothorax. The VP shunt was inserted 10 years before presentation, after hemorrhagic hydrocephalus caused by prenatal intraventricular hemorrhage. The pleural fluid was drained via tube thoracostomy and the shunt was externalized, with full resolution of symptoms and signs. The patient was subsequently managed with shunt revision with drainage into the abdominal cavity. We review the 10 pediatric cases of cerebrospinal fluid hydrothorax reported in the literature and discuss the mechanism of shunt tip migration. Pleural effusion secondary to VP shunt insertion is a rare and potentially life-threatening occurrence, and it should be suspected in any patient with a VP shunt and respiratory distress. © 2012 by Lippincott Williams & Wilkins.
Keywords: cerebrospinal fluid; hydrothorax; pleural effusion; respiratory distress; ventriculoperitoneal shunt

Adverse Events: Root Causes and Latent Factors - Karl, R.; Karl, M.C. (Surgical Clinics of North America, 2012)
This article describes the process of root cause analysis (RCA), the theories of error that underlie the concept of systemic or latent factors that allow errors to occur or to be propagated without correction; the difference between the process in health care and those found in high-reliability organizations; and suggests some ways to augment the standard health care RCA into a more robust and helpful process. © 2012 Elsevier Inc.
Keywords: Latent factors; Root cause analysis; Systemic factors; Theories of error

Transepithelial corneal collagen crosslinking: Bilateral study - Filippello, M.; Stagni, E.; O'Brart, D. (Journal of Cataract and Refractive Surgery, 2012)
Purpose: To evaluate the efficacy of transepithelial collagen crosslinking (CXL) in patients with bilateral progressive keratoconus. Setting: Outpatient ophthalmic clinic. Design: Cohort study. Methods: Patients with a history of bilateral progressive keratoconus were recruited. The worst eye was treated with transepithelial CXL, while the fellow eye was left untreated as a control. Transepithelial CXL was performed by applying an enhanced riboflavin solution (riboflavin 0.1%, dextrane T500 with trometamol [Tris-hydroxymethyl aminomethane] and EDTA [ethylenediaminetetraacetic] sodium salt) on the intact corneal epithelium for 30 minutes before irradiation with ultraviolet A (370 nm at 3 mW/cm 2) for 30 minutes. Follow-up was 18 months in all eyes. Results: The study enrolled 20 patients. Transient hyperemia and mild foreign-body sensation occurred in 8 eyes (40%) after treatment; both resolved after 24 hours. In treated eyes, there were statistically significant improvements in uncorrected and corrected visual acuity and topography-derived keratometry, cone apex power, and higher-order aberrations (P<.05). In untreated control eyes, there was a general trend toward worsening of these parameters. No complications were reported. Conclusions: Transepithelial CXL treatment appeared to halt keratoconus progression, with a statistically significant improvement in visual and topographic parameters. The treatment was safe and well tolerated. Its noninvasive nature makes it potentially useful in cases in which epithelial debridement is ideally avoided, such as pediatric cases, uncooperative patients, and thin corneas with thicknesses nearing 380 μm. Financial Disclosure: No author has a financial or proprietary interest in any material or method mentioned. © 2011 ASCRS and ESCRS Published by Elsevier Inc.

Hydrophobic polycationic coatings that inhibit biofilms and support bone healing during infection - Schaer, T.P.; Stewart, S.; Hsu, B.B.; Klibanov, A.M. (Biomaterials, 2012)
Adhesion of microorganisms to biomaterials with subsequent formation of biofilms on such foreign bodies as orthopedic trauma hardware is a critical factor in implant-associated infections; once a biofilm has been established, its microorganisms become recalcitrant to the host's immune surveillance and markedly resistant to drugs. We have previously reported that painting with the hydrophobic polycation N,N-dodecyl,methyl-PEI (PEI = polyethylenimine) renders solid surfaces bactericidal in vitro. Herein we observe that N,N-dodecyl,methyl-PEI-derivatized titanium and stainless steel surfaces resist biofilm formation by Staphylococcus aureus compared to the untreated ones. Using imaging, microbiology-, histopathology-, and scanning electron microscopy (SEM) experiments in a clinically relevant large-animal (sheep) trauma model, we subsequently demonstrate in vivo that orthopedic fracture hardware painted with N,N-dodecyl,methyl-PEI not only prevents implant colonization with biofilm but also promotes bone healing. Functionalizing orthopedic hardware with hydrophobic polycations thus holds promise in supporting bone healing in the presence of infection in veterinary and human orthopedic patients. © 2011 Elsevier Ltd.
Keywords: Animal model; Bactericidal; Hardware; Infection; Orthopedics

Patients Count on It: An Initiative to Reduce Incorrect Counts and Prevent Retained Surgical Items - Norton, E.K.; Martin, C.; Micheli, A.J. (AORN Journal, 2012)
Retained surgical items were the most frequently reported sentinel event in 2010, according to The Joint Commission. Perioperative nurse leaders at Children's Hospital Boston, a pediatric teaching hospital, conducted a quality improvement initiative to reduce or eliminate incorrect counts and count discrepancies, which increase the risk of an item being unintentionally retained after surgery. Work included educating the perioperative staff members, standardizing count practices, formally reviewing every reported count discrepancy with the nursing team, and reviewing and revising the count policy for prevention of retained surgical items. The initiative reduced the number of incorrect counts and count discrepancies by 50% between 2009 to 2010. These initiatives continue to be expanded, and the results have been sustained on an ongoing basis. © 2012 AORN, Inc.
Keywords: Count discrepancies; Incorrect counts; Retained surgical items

Sigmoid colon perforation due to a foreign body ingestion - Alonso-Gómez, S.; Rubio-González, E.; Donat-Garrido, M.; Lomas-Espadas, M.; Solís-Herruzo, J.A.; Moreno-González, E. (Revista Espanola de Enfermedades Digestivas, 2012)

Counting matters: Lessons from the root cause analysis of a retained surgical item - Agrawal, A. (Joint Commission Journal on Quality and Patient Safety, 2012)
Background: Retained surgical items (RSIs), such as a sponge, instrument, or needle, after a surgery or invasive procedure is an uncommon but potentially serious event associated with significant morbidity and mortality. A 27-yearold woman was discovered to have a retained vaginal sponge a week after she underwent the repair of a vaginal tear following normal vaginal delivery. The retained sponge was removed with no further complications. Root Cause Analysis: The fundamental error involved the obstetric team's failure to perform the standard protocol of counting sponges before, as well as after, the procedure. This was attributed to a lack of reminders to perform the count, relatively recent implementation of the sponge-count policy, and a breakdown in teamwork and communication between physicians and nurses. Corrective Actions: The corrective actions focused on systems improvement, as opposed to the human error of the memory lapse. The sponge-counting process was reinforced by incorporating a sign-out at the end of obstetric procedures to ensure that the counts have been done and any discrepancies addressed. A specialized delivery note with mandatory field to document sponge count was implemented in the electronic health record as an additional reminder. All staff participated in a teamwork and com munication training program. Tracking Compliance: Since the incident's occurrence in 2010, the staff has demonstrated 100% compliance with the corrective actions, and a retained surgical item complication has not recurred. Conclusion: Individual accountability must be balanced with systems improvement, given that most medical errors are a result of fallible humans working in chaotic, unpredictable, and complex clinical environment.

A fish bone causing ileal perforation in the terminal ileum - Mutlu, A.; Uysal, E.; Ulusoy, L.; Duran, C.; Selamoǧlu, D. (Ulusal Travma ve Acil Cerrahi Dergisi, 2012)
Foreign body perforation of the gastrointestinal (GI) tract has diverse clinical manifestations, and the correct preoperative diagnosis is seldom made. We report the case of a 69-year-old woman who experienced severe pain in the right iliac fossa. The presumptive diagnosis was acute purulent appendicitis or diverticulitis. Multidetector computed tomography (MDCT) imaging showed the fish bone perforation of the terminal ileum. A high index of suspicion should always be maintained in order for the correct diagnosis to be made.
Keywords: Bowel perforation; Fishbone; Multidetector computed tomography

Policy for prevention of a retained sponge after vaginal delivery - Garry, D.J.; Asanjarani, S.; Geiss, D.M. (Case Reports in Medicine, 2012)
Background. Policies for sponge count are not routine practice in most labor and delivery rooms. Ignored or hidden retained vaginal foreign bodies has potentially significant health care morbidity. Case. This was a case of a retained vaginal sponge following an uncomplicated spontaneous vaginal delivery. Delivery room policy resulted in the discovery of the sponge on X-ray when an incorrect sponge count occurred and physical exam did not find the sponge. Conclusion. This emphasizes the use of protocols to enhance patient safety and prevent medical error. © Copyright 2012 David J. Garry et al.

Stent migration to the ileum-A potentially lethal complication after montgomery salivary bypass tube placement for hypopharyngeal stenosis after laryngectomy - Bitter, T.; Pantel, M.; Dittmar, Y.; Guntinas-Lichius, O.; Wittekindt, C. (Head and Neck, 2012)
Background. Montgomery salivary bypass tubes (MSBTs) have been used for decades in the treatment of stenoses and fistulae of the hypopharynx and the cervical esophagus. Generally, MSBT use is not associated with serious complications. Only a small number of cases with severe MSBT-associated complications have been reported in the literature. Methods. and Results. We report for the first time an MSBT migration to the ileum in a laryngectomized patient who underwent surgical pharyngocutaneous fistula closure with MSBT placement. The MSBT was removed surgically via laparotomy. The patient died 15 days later due to sepsis associated with peritonitis. Conclusion. To avoid potentially lethal complications associated with MSBT migration into the intestinal tract, we recommend secure fixation of the MSBT to a nasogastric tube. © 2010 Wiley Periodicals, Inc.
Keywords: complication; dislocation; migration; pharyngocutaneous fistula; salivary bypass tube

Irritable bowel syndrome: A "mesh" of a situation - Barnes, M.G. (Journal of the American Board of Family Medicine, 2012)
The diagnosis of irritable bowel syndrome (IBS) frequently is made after the exclusion of a mechanical etiology for a patient's symptoms. This case demonstrates that IBS symptoms can be caused by a rare complication of a common surgery: mesh herniorrhaphy repair. The patient is a 50-year-old woman who underwent periumbilical Marlex mesh herniorrhaphy 13 years before presentation. After her operation, the patient developed constipation (approximately one bowel movement per week) alternating with diarrhea for approximately 10 years. An abdominal radiograph showed large amounts of stool, and after a normal colonoscopy the patient was diagnosed with IBS. The patient was treated with tegaserod (Zelnorm) and polyethylene glycol (MiraLAX), which did not palliate her symptoms. The patient presented with obstructive symptoms and physical findings of an incarcerated umbilical hernia. A computed tomography (CT) scan of the abdomen confirmed an umbilical hernia involving a segment of small bowel with surrounding fecalization of enteric contents. During operative repair, the patient was found to have Marlex mesh fully eroded into the lumen of the small bowel, causing a partial obstruction. The involved section of small bowel was resected, and during serial follow-up the patient had complete resolution of her IBS-like symptoms. A discussion follows regarding the implications of mesh migration, and questions are posed for future research.
Keywords: Case report; Hernioplasty; Herniorrhaphy; Irritable bowel syndrome; Polypropylene; Surgical mesh

Replacement gastrostomy tube causing acute pancreatitis:Case series with review of literature - Shah, A.M.; Shah, N.; Depasquale, J.R. (Journal of the Pancreas, 2012)
Context Percutaneous endoscopic gastrostomy (PEG) feedings are generally considered safe with few serious complications. Acute pancreatitis is a rare complication associated with replacement percutaneous endoscopic gastrostomy tubes. Case report We report two cases of acute pancreatitis induced by migrated replacement percutaneous endoscopic gastrostomy tubes. Conclusions Migration of a balloon into the duodenum can result in external manipulation of the ampulla of Vater thereby disturbing the flow of pancreatic secretions leading to acute pancreatitis. Recognition of this complication is important and should be included as potential etiology of acute pancreatitis in patients receiving percutaneous endoscopic gastrostomy feedings. Periodic examination and documentation of the distance of the balloon from the skin should be performed to document the position of the tubes or any inadvertent migration of the tubes. The use of Foley catheters as permanent replacement tubes should be considered medically inappropriate.
Keywords: Acute necrotizing abbreviations peg percutaneous endoscopic gastrostomy; Enteral nutrition; Gastrostomy; Pancreatitis

Laparoscopic mesh explantation and drainage of sacral abscess remote from transvaginal excision of exposed sacral colpopexy mesh - Roth, T.M.; Reight, I. (International Urogynecology Journal, 2012)
Sacral colpopexy may be complicated by mesh exposure, and the surgical treatment of mesh exposure typically results in minor postoperative morbidity and few delayed complications. A 75-year-old woman presented 7 years after a laparoscopic sacral colpopexy, with Mersilene mesh, with an apical mesh exposure. She underwent an uncomplicated transvaginal excision and was asymptomatic until 8 months later when she presented with vaginal drainage and a sacral abscess. This was successfully treated with laparoscopic enterolysis, drainage of the abscess, and explantation of the remaining mesh. Incomplete excision of exposed colpopexy mesh can lead to ascending infection and sacral abscess. Laparoscopic drainage and mesh removal may be considered in these patients. been reported to have only minor postoperative complications and abdominal excisions are more likely to have more serious complications [2]. Atlas et al. reported the safe laparoscopic removal of mesh after a failed transvaginal excision but without an associated sacral abscess [3]. We describe the laparoscopic drainage of a sacral abscess and the removal of the associated mesh at the promontory, 8 months after a transvaginal excision of a mesh exposure. © The International Urogynecological Association 2012.
Keywords: Abscess; Mesh; Sacral colpopexy

Intraabdominal abscessus of unknown etiology - Radoje, C.; Nikica, G.; Stojan, L.; Nataša, C. (Srpski Arhiv za Celokupno Lekarstvo, 2012)
Introduction. Intraabdominal abscesses are in 98-99% cases the result of secondary and only in 1-2% of primary peritonitis. They are easy and successfully diagnosed. Abdominal abscesses of unknown cause are extremely rare. Case Outline. The authors present a 68-year-old man, without significant data in past history, who suddenly developed epigastric pain, nausea, vomiting and leukocytosis which was treated with antibiotics resulting in the alleviation of complaints and reduction of white blood cells count. After five days ultrasonography showed incapsulated collection of dense fluid in the epigastrium confirmed by CT scan two days later. Upper endoscopy excluded ulcer and/or perforation of the stomach and duodenum. Under local anesthesia, through the upper part of the left rectal muscle, puncture followed by incision was done, and about 50 ml of dense pus was removed. Finger exploration of the cavity showed no foreign body within the cavity. Using drainage, the recovery was quick and uneventful. By preoperative and postoperative abdominal investigations no cause of the abscess was found. Two and a half years after surgery the patient remained symptom-free with normal clinical, laboratory and ultrasonographic findings. Conclusion. The authors presented an intraabdominal abscess of unknown cause that was successfully treated with antibiotics, percutaneous puncture and drainage under local anaesthesia. In spite of all diagnostic methods the cause of the abscess could not be found. Thus, such a possibility, although being rare, should be taken into account. © 2012. Centre for Evaluation in Education and Science.
Keywords: Abdomen; Abscess; Drainage; Incision; Local anaesthesia; Puncture

Increased connective tissue attachment to silicone implants by a water vapor plasma treatment - Jensen, C.; Gurevich, L.; Patriciu, A.; Struijk, J.J.; Zachar, V.; Pennisi, C.P. (Journal of Biomedical Materials Research - Part A, 2012)
Polydimethylsiloxane (PDMS) is the most common type of silicone polymer for the fabrication of implantable medical devices. Because of its inherent hydrophobic nature, the PDMS surface does not readily promote cellular adhesion, which leads to diverse clinical issues. Previously, we reported a simple water vapor plasma treatment of PDMS surfaces that resulted in stable long-term wettability and excellent in vitro cell compatibility. In this work, we report investigation of the in vivo local responses to PDMS implants treated by water vapor plasma using a subcutaneous rat model. The local tissue responses were assessed after 2 and 4 weeks of implantation by means of macroscopic and histomorphometric analysis. After 2 weeks of implantation, the plasma-treated implants elicited the formation of fibrous tissue capsules that were significantly thinner, more adherent, and vascularized than the control counterparts. The improved cell adhesion was correlated with an increased amount of cells attached to the implant surface after retrieval. There was no difference in the inflammatory response between untreated and treated samples. This study provides a rational approach to optimize the long-term performance of silicone implants, which is likely to have a significant impact in clinical applications demanding enhanced tissue integration of the implants. © 2012 Wiley Periodicals, Inc.
Keywords: Cell adhesion; Foreign body response; Polydimethylsiloxane; Surface modification; Water vapor plasma

Unusual spine anatomy contributing to wrong level spine surgery: A case report and recommendations for decreasing the risk of preventable 'never events' - Lindley, E.M.; Botolin, S.; Burger, E.L.; Patel, V.V. (Patient Safety in Surgery, 2011)
Background: Wrong site surgery is one of five surgical "Never Events," which include performing surgery on the incorrect side or incorrect site, performing the wrong procedure, performing surgery on the wrong patient, unintended retention of a foreign object in a patient, and intraoperative/immediate postoperative death in an ASA Class I patient. In the spine, wrong site surgery occurs when a procedure is performed on an unintended vertebral level. Despite the efforts of national safety protocols, literature suggests that the risk for wrong level spine surgery remains problematic.Case Presentation: A 34-year-old male was referred to us to evaluate his persistent thoracic pain following right-sided microdiscectomy at T7-8 at an outside institution. Postoperative imaging showed the continued presence of a herniated disc at T7-8 and evidence of a microdiscectomy at the level immediately above. The possibility that wrong level surgery had occurred was discussed with the patient and revision surgery was planned. During surgery, the site of the previous laminectomy was clearly visualized; however, we also experienced confusion when verifying the level of the previous surgery. We ultimately used the previous laminectomy site as a landmark for identifying and treating the correct pathologic level. Postoperative consultation with Musculoskeletal Radiology revealed the patient had two abnormalities in his spinal anatomy that made intraoperative counting of levels inaccurate, including a pair of cervical ribs at C7 and the absence of a pair of thoracic ribs.Conclusion: This case highlights the importance of strict adherence to a preoperative method of vertebral labeling that focuses on the landmarks used to label a pathologic disc space, rather than simply relying on the reference to a particular level. That is, by designating the pathological level as the disc space associated with the fourth rib up from the last rib-bearing vertebrae, rather than calling it "T7-8", then the correct level can be found intraoperatively even in the case of abnormal segmentation. We recommend working closely with radiology during preoperative planning to identify unusual anatomy that may have been overlooked. We also recommend that radiology colleagues use the same system of identifying pathological levels when dictating their reports. Together, these strategies can reduce the risk of wrong level surgery and increase patient safety. © 2011 Lindley et al; licensee BioMed Central Ltd.
Keywords: Abnormal segmentation; Cervical ribs; Never event; Wrong level spine surgery; Wrong site surgery

Septic arthritis due to cellulosimicrobium cellulans - Magro-Checa, C.; Chaves-Chaparro, L.; Parra-Ruiz, J.; Peña-Monje, A.; Rosales-Alexander, J.L.; Salvatierra, J.; Raya, E. (Journal of Clinical Microbiology, 2011)
Cellulosimicrobium cellulans has been reported as a rare cause of human pathogenesis. Infections mainly occur in immunocompromised patients and very often are associated with a foreign body. We report the first case of septic arthritis caused by C. cellulans in an immunocompetent patient. Our patient suffered a penetrating palm tree thorn injury to his left knee 8 weeks before admission. Although no foreign objects were found, they were suspected because previous reports suggest a frequent association with this microorganism, and open debridament was performed. Removal of foreign bodies related to this organism must be considered a high-priority treatment in these patients to achieve a complete recovery. Copyright © 2011, American Society for Microbiology. All Rights Reserved.

Percutaneous retrieval of a misplaced guidewire from the sigmoid dural venous sinus - Perdikakis, E.; Kehagias, E.; Tsetis, D. (Chirurgia, 2011)
Minimally invasive and interventional techniques are increasingly being used in manipulating malpositioned or dislocated intravascular foreign bodies. There is a wide range of available endovascular techniques either for correcting the position of an incorrectly placed endovascular device or for its percutaneous retrieval. We report a case of successful retrieval of a misplaced central venous guiding wire from the left sigmoid dural venous sinus.
Keywords: Cranial sinus; Foreign bodies; Surgical procedures, minimally invasive

Comparisons of mouse models for hair follicle reconstitution - Liang, Y.; Silva, K.A.; Kennedy, V.; Sundberg, J.P. (Experimental Dermatology, 2011)
Three methods are currently available to reconstitute hair follicles in mice. Direct comparisons have yet to be made to determine which method is most efficient. In this study, mouse epithelial cells (MECs) and mouse dermal cells (MDCs) were grafted onto the dorsal skin of nude mice using the chamber, flap or patch assays. Comparisons were made based on gross, scanning electron microscopic and histological observations. MDCs alone induced hair follicle reconstitution with the production of hairs yielding false-positive results caused by contamination by hair follicle remnants. Neither primary MECs nor cultured MDCs alone formed hair follicles but did result in hair follicle formation when mixed together. Frozen MECs or MDCs resulted in decreased hair follicle-inductive activity but could still regenerate hairs. The hair patch assay was the quickest model (20±3days) to determine whether cell mixtures would reconstitute hair follicles that produce hairs; however, the hair follicles were randomly orientated and often associated with foreign body granulomas. The flap assay took the longest time (29±2days) to produce follicles and hairs to develop with a clinically natural appearance, but an epidermal sheet was needed. The chamber assay was the most labour-intensive and cell number-dependent procedure but follicles developed in a dense, clinically normal manner. © 2011 John Wiley & Sons A/S.
Keywords: Chamber; Flap; Hair follicle; Patch; Reconstitution

Aseptic polyurethane carotid patch rejection: Complication, allergy or miraculous healing? - Tshomba, Y.; De Dominicis, D.; Marone, E.M.; Mascia, D.; Sanvito, F.; Chiesa, R. (Journal of Cardiovascular Surgery, 2011)
Carotid endarterectomy plays an important role in the prevention of ischemic stroke; patching could reduce the risk of intra- and postoperative complications and late restenosis among primary closure. Materials actually available for the patch tailoring are synthetic or biological: which is the best is still debated. We present the case of a polyurethane (PU) carotid patch rejection three years after its implant, with no evident arterial discontinuity and no sign of infection. Histopathological analysis on hematoxylin-eosin stained sections of the regenerated arterial wall tissue removed revealed plasma cell infiltration and clusters of foreign body giant cells. PU patch rejection has been seldom described in literature. This is an unusual late complication that should be considered at long-term follow-up evaluation of these patients.
Keywords: Endarterectomy, carotid; Rejection; Stroke

Surgical intervention for swallowed gastrointestinal foreign bodies in adults - Jarbou, S.M. (Rawal Medical Journal, 2011)
Objective The aim of our study was to present our experience in dealing with a group of complicated accidentally swallowed foreign bodies (FBs) that need surgical treatment. Methods From 2003-2008 we treated five adult patients who presented with complications after FB ingestion. These cases were dealt with in the hospitals of The Royal Medical Services in Jordan and in field. Results The complications treated were perforation of bowel in two cases, intestinal obstruction two cases and migration of FB (needle) to the liver one case. The preoperative diagnosis was achieved only in the last case. Conclusion The complications of the ingested FBs increased when they were sharp, pointed or large, and because it usually happened unnoticed by the patient. Thus, preoperative diagnosis is difficult, despite the wide range of imaging methods used. Complications are usually dealt with during operation especially when the FB is radiolucent.
Keywords: Foreign body ingestion; Intestinal perforation

Prevention of retained surgical items - Feldman, D.L. (Mount Sinai Journal of Medicine, 2011)
Reduction in retained surgical items is an important part of any operating room patient-safety effort. Any item used in an operation can result in a retained surgical item, but sponges are the most frequent and the abdomen is the most common location. Retained sponges can cause significant morbidity, and the costs associated with both prevention and treatment of retained surgical items, including legal costs, can be considerable. This review will examine counting, teamwork, radiography, and new technology as methods used to prevent retained surgical items. Even though none of these techniques individually is likely to completely prevent retained surgical items, when used together the numbers can be reduced. Mt Sinai J Med 78:865-871, 2011. © 2011 Mount Sinai School of Medicine.
Keywords: patient safety; retained foreign bodies; retained sponges; retained surgical items; surgical safety

Schistosoma japonicum: Treatment of different developmental stages in mice with long-acting praziquantel implants - Cheng, L.; Lei, L.; Guo, S.; Zhu, C.; Rong, H.; Guo, D.; Zhang, L.; Jiang, Y.; Lin, J. (Experimental Parasitology, 2011)
This paper reports the effective treatment of Schistosoma japonicum in a mouse model with long-acting praziquantel (PZQ)-loaded poly(ε-caprolactone) implants. The implants yielded stable, high plasma PZQ concentrations ranging 100-1600. ng/mL during the 40-day investigation period. For assessment of efficacy, the implants were implanted into mice immediately after infection and at 1, 2, 3 and 4. weeks after infection to treat the schistosomes at different developmental stages. All the mice were sacrificed at 6. weeks after infection for worm and egg recovery, worm morphology examination, and histopathological analysis of implantation site tissues. The worm burdens, egg burdens, and numbers of miracidia hatched from the retrieved eggs for all the implant-treated groups (except groups T2-A, T4 and T5) were reduced by 100% when compared with the control group. From groups T2-A, T4 and T5, some schistosome debris was recovered. Eggs were found in only group T5 for which the time between infection and implantation was 4. weeks, which enabled the maturation of juvenile female schistosomes into adult ones that lay eggs. Histopathological observations of implantation tissue showed no evidence of granulomatous foreign-body or lymphoid cell aggregation, demonstrating good biocompatibility of the PZQ implants. These results demonstrate that the long-acting PZQ implants can kill schistosomes at any developmental stages and attenuate/avoid the associated liver damage. © 2011 Elsevier Inc.
Keywords: Implant; Praziquantel; Schistosoma japonicum; Schistosomiasis; Sustained release formulation

Textiloma as a complication of transsphenoidal surgery - Hsieh, C.-T.; Chung, T.-T.; Chen, Y.-H.; Li, Y.-F.; Liu, M.-Y. (Neurosciences, 2011)
Transsphenoidal surgery is the mainstream in the management of sellar and anterior fossa diseases. However, textiloma, as known as cotton left behind during an operation, is rarely reported as a complication of transsphenoidal surgery. In this paper, we present a case of textiloma after transsphenoidal surgery. The patient had been suffering progressive blurred vision and she received transsphenoidal surgery for the diagnosis of pituitary tumor. However, the intermittent headaches persisted for half a year after the surgery. The subsequent images revealed a rim-like enhanced tumor in the sellar region. The retained cotton material was found when she underwent transcranial surgery. The etiology and management of textiloma are discussed, and the relevant literature also reviewed.

A system-wide initiative to prevent retained vaginal sponges - Chagolla, B.A.; Gibbs, V.C.; Keats, J.P.; Pelletreau, B. (MCN The American Journal of Maternal/Child Nursing, 2011)
As any perinatal nurse knows, retained vaginal sponges are an obstetrical and postpartum patient safety problem. As surgical sponge counts are not routine in some obstetrical units for vaginal births, our healthcare system chose to institute a rigorous process to eliminate retained sponges in all vaginal births. This article describes this process, along with the lessons learned, when Catholic Healthcare West implemented the Sponge ACCOUNTing System in its 32 hospitals in California, Arizona, and Nevada. Implementation of this process involved the standardization of practice for obstetricians, certified nurse midwives, nurses, obstetric technicians, radiologists, and radiology technicians in the management and accounting of surgical sponges. Copyright © 2011 Lippincott Williams & Wilkins.
Keywords: Labor and delivery; Perinatal patient safety; Retained vaginal sponge; Vaginal birth

The breast: A clean-contaminated surgical site - Bartsich, S.; Ascherman, J.A.; Whittier, S.; Yao, C.A.; Rohde, C. (Aesthetic Surgery Journal, 2011)
Background: Capsular contracture is one of the most common complications associated with breast implants. While the cause of this process has not yet been elucidated, subclinical infection is a likely culprit. Objectives: The authors assess the hypothesis that a probable source of contamination is endogenous breast bacteria, likely originating in the ducts themselves and most concentrated near the nipple. Methods: Twenty-five healthy patients presenting for routine reduction mammaplasty were recruited as study participants. Tissue samples were taken intraoperatively from the periareolar, inframammary, and axillary regions of each sampled breast. Specimens were then processed in the microbiology laboratory, and quantitative bacterial counts were obtained. Results: Of the 50 breasts sampled, 19 yielded positive culture results, for a rate of 38%. There was a significant difference in the positive culture rate among all three sites, with increasing quantitative bacterial counts in the axillary, inframammary, and periareolar regions, respectively. The most commonly-identified organisms in this study included various species of Staphylococcus and Propionibacterium acnes, with S. epidermidis being the most common. Conclusions: The breast harbors significant endogenous bacteria that can become the source of spontaneous or postoperative infection. Positive intraoperative cultures with high quantitative counts suggest that breast tissue harbors more bacteria than normal skin flora. Routine perioperative antibiotic prophylaxis may be suboptimal for the prevention of foreign body seeding in this setting. Furthermore, bacterial concentrations are highest in areas with the most ductal tissue, namely the periareolar region. These findings may be helpful when considering which incision site to select for augmentation mammaplasty. © 2011 The American Society for Aesthetic Plastic Surgery, Inc.
Keywords: Antibiotic irrigation; Breast enhancement; Breast enlargement; Capsular contracture; Infection; Periareolar; Primary or secondary or revision breast augmentation; Risks with implants

Incidental finding of a splenic hamartoma with tumour-like extramedullary erythropoiesis - Dolcet, C.; Kornprat, P.; Lindenmann, J.; Beham-Schmid, C.; Mischinger, H.-J. (Wiener Medizinische Wochenschrift, 2011)
Hamartomas of the spleen are rare benign tumourlike lesions that tend to be asymptomatic incidental findings. Splenic hamartomas with tumour-like extramedullary erythropoiesis are extremely rare. A 70-year-old male patient with dyspnoea and a nodular intrapulmonary lesion morphologically verified by CT underwent fibre bronchoscopy, which showed a pea-shaped foreign body that was retrieved without complication. As a secondary finding, the CT showed a splenic lesion of about 8 cmin size. An MR study showed an expansive process in the center of the spleen. The patient was completely free of clinical symptoms. Because of the unknown nature and the high risk for spontaneous rupture of the lesion, a splenectomy was performed. The histological analyses revealed tumour-like extramedullary erythropoiesis of the spleen. The patient was discharged in good condition ten days postoperatively. A hamartoma of the spleen with extramedullary tumor-like erythropoiesis should be considered in the differential diagnosis of a splenic lesion. © 2011 Springer-Verlag.
Keywords: Extramedullary erythropoiesis; Hamartoma; Spleen; Splenadenoma; Splenoma

Designing a Safer Process to Prevent Retained Surgical Sponges: A Healthcare Failure Mode and Effect Analysis - Steelman, V.M.; Cullen, J.J. (AORN Journal, 2011)
A retained surgical sponge is a sentinel event that can result in serious negative outcomes for the patient. Current standards rely on manual counting, the accuracy of which may be suspect, yet little is known about why counting fails to prevent retained sponges. The objectives of this project were to describe perioperative processes to prevent retained sponges after elective abdominal surgery; to identify potential failures; and to rate the causes, probability, and severity of these failures. A total of 57 potential failures were identified, associated with room preparation, the initial count, adding sponges, removing sponges, the first closing count, and the final closing count. The most frequently identified causes of failures included distraction, multitasking, not following procedure, and time pressure. Most of the failures are not likely to be affected by an educational intervention, so additional technological controls should be considered in efforts to improve safety. © 2011 AORN, Inc.
Keywords: Operating room safety; Retained surgical items; Sponge counts; Surgical sponge

Effectiveness of the biophysical barriers on the peridural fibrosis of a postlaminectomy rat model: An experimental research - Kasimcan, M.O.; Bakar, B.; Akta, S.; Alhan, A.; Yilmaz, M. (Injury, 2011)
Purpose: Long term results after surgical treatment of disc herniation have shown that epidural and/or peridural fibrosis formed during the healing process after surgical intervention. We conducted this experimental study to evaluation of the effectiveness of the bioresorbable barriers (ADCON-L and Seprafilm ® Adhesion Barrier) on formation of the peridural fibrosis in rat model performed laminectomy. Methods: Thirty-two male Wistar albino rats 250-350 g body weight were distributed into three groups (CONTROL, AL group received ADCON-L; SAB group received Seprafilm ® Adhesion Barrier). A dorsal laminectomy at L3, L4, L5 was performed, and then except those of the CONTROL group, the experimental material was left on the dura mater. Six weeks later spinal column of all rats was totally removed between the T10 and L5 levels, and peridural fibrosis, and dural adhesions were evaluated histologically and graded. The results were compared statistically by using the chi-square (χ 2) test. Also three random regions were examined, and the fibroblast cells were counted. The fibroblast count results were statistically analysed by using the One-Way ANOVA test. Results: The variation of histopathological grades was statistically significant regarding the comparison of the all groups obtained from the χ 2 test (χ 2 = 16.40; p = 0.003). However, the variation in the mean values of the fibroblast count result was not statistically significant obtained from the One-Way ANOVA test (F = 2.114; p > 0.05). Conclusion: Our study results suggest that Seprafilm ® Adhesion Barrier and ADCON-L can be effective in reducing the prevalence of the postoperative peridural adhesions in rat laminectomy model. On the other hand, the fibroblast densities of the experimental groups were not different between groups. So, we could say that these materials can act as a foreign body in long term period in rat. © 2010 Elsevier Ltd.
Keywords: Adhesion barrier; Fibroblast; Peridural fibrosis; Spine

Ketorolac 0.45% ophthalmic solution - McCormack, P.L. (Drugs and Aging, 2011)
Ketorolac 0.45 ophthalmic solution is a topical NSAID indicated in the US for the treatment of ocular pain and inflammation following cataract surgery.In animal studies, the ocular relative bioavailability of single-dose topical ketorolac 0.45 ophthalmic solution was 2- to 3-fold higher than that of ketorolac 0.4 ophthalmic solution.In two identically designed, randomized, double-masked, multicentre trials in adult patients undergoing cataract extraction, the proportions of patients with a summed ocular inflammation score of zero for anterior chamber cell count plus anterior chamber flare on day 14 after surgery were significantly greater in those treated with topical ketorolac 0.45 ophthalmic solution than in those treated with vehicle placebo.Compared with placebo, topical ketorolac 0.45 ophthalmic solution significantly increased the proportion of patients who were pain-free on the day after surgery in both trials.Ketorolac 0.45 ophthalmic solution was generally well tolerated in clinical trials with lower overall incidences of treatment-emergent and treatment-related adverse events than placebo, and with no single treatment-related adverse event having a higher incidence than with placebo. © 2011 Adis Data Information BV. All rights reserved.
Keywords: Adis-Drug-Profiles; Ketorolac; Ocular-inflammation; Ocular-pain; Ophthalmic

Migration of a fish bone into the right renal vein - Iwai, T.; Yoshida, H.; Yokoyama, T.; Maruyama, H.; Suzuki, S.; Matsutani, T.; Matsushita, A.; Hirakata, A.; Sasajima, K.; Uchida, E. (Journal of Nippon Medical School, 2011)
We describe a patient in whom a fish bone penetrated the duodenum and migrated into the right renal vein. The bone was successfully removed with surgery. The 75-year-old man was admitted to Nippon Medical School Tama Nagayama Hospital because of right upper abdominal pain persisting for 7 days. The patient's medical history was not relevant to the current disorder. Plain radiography showed no abnormalities. Computed tomography revealed a linear object of high intensity that had penetrated the duodenum and migrated into the right renal vein with thrombus. The object was surrounded by a low-density area, suggesting severe inflammation. The patient had eaten fish 1 day before the onset of abdominal pain. We diagnosed duodenal penetration caused by an ingested fish bone. Endoscopic examination showed erosion, but no fish bone or ulceration was detected in the duodenum. The patient was treated conservatively with fasting, peripheral parental nutrition, and intravenous antibiotics. Three days after admission, non-contrast-enhanced computed tomography showed no movement of the foreign body. The patient continued to have pain, and the decision was made to surgically explore the abdomen. Intraoperative ultrasonography showed that the foreign body had migrated completely into the right renal vein with thrombus. Severe inflammation of the right renal vein was observed. Because we could not remove the foreign body without seriously injuring the right renal vein, right nephrectomy was performed. Macroscopic examination of the surgical specimen confirmed the presence of a fish bone with thrombus in the right renal vein. The patient was discharged 9 days after operation, with no complications.
Keywords: Fish bone; Migration; Renal vein

Cell adhesion on explanted intraocular lenses: Part 1: Analysis of explanted IOLs - Ishikawa, N.; Miyamoto, T.; Okada, Y.; Saika, S. (Journal of Cataract and Refractive Surgery, 2011)
Purpose: To determine whether cell adhesion on an intraocular lens (IOL) in Japanese patients is affected by the optic material. Setting: Department of Ophthalmology, Wakayama Medical University, Wakayama, Japan. Design: Experimental study. Methods: Intraocular lenses of various materials explanted from Japanese patients were histologically examined under light microscopy. Specimens included 271 poly(methyl methacrylate) (PMMA) IOLs, 117 hydrophobic soft acrylic IOLs, and 48 silicone IOLs. The mean cell adhesion on the central area of the anterior surface of each IOL material (referred to as cell number) was evaluated. Results: The cell number in the PMMA group was significantly higher than that in the silicone group in the periods of 1 to 5, 6 to 11, and more than 24 months. Although the cell number in the silicone group was less than one-third and one-twentieth the cell number in the hydrophobic soft acrylic group in the periods 1 to 5 months and 6 to 11 months, respectively, the difference was not statistically significant. Conclusion: In Japanese patients, the cell adhesion on silicone IOLs was less than that on PMMA IOLs. © 2011 ASCRS and ESCRS.

Effects of NasoPore packing in the middle ear cavity of the guinea pig - Huang, G.; Chen, X.; Jiang, H. (Otolaryngology - Head and Neck Surgery, 2011)
Objective. To evaluate the effects of NasoPore after packing of the middle ear in guinea pigs. Study Design. A randomized, prospective, controlled animal study. Setting. University laboratory. Subjects and Methods. Forty-one guinea pigs were divided into 3 groups. In group 1 (n = 12), the middle ears of animals were unilaterally implanted with NasoPore, leaving the contralateral middle ears packed with absorbable gelatin sponge soaked in a solution containing kanamycin and furosemide as an ototoxicity-positive control; group 2 (n = 17) underwent the same experimental protocol as group 1, except the gelatin sponge was unsoaked; in group 3 (n = 12), NasoPore was inserted unilaterally and no packing material was placed into the contralateral ear. Auditory brainstem responses (ABRs) were performed preoperatively and 3 months after the procedure. The surface preparation and scanning electron microscopy (SEM) were assessed 3 months postoperatively, whereas pathology of middle ear was analyzed in 5 samples of group 2. Results. ABR thresholds of the contralateral ear significantly increased in group 1 and were slightly shifted in group 2 compared with the NasoPore-packed and nonpacked ears 3 months postoperatively. The NasoPore-packed middle ears were found to have less fibrosis and inflammation and less thickened bone and tympanic membranes than Gelfoam-packed ears. Surface preparations and SEM showed no ototoxicity in the inner ear of NasoPore-packed ears. Conclusion. NasoPore appears to be effective for use in otosurgery. It caused less fibrosis in the middle ear than conventional packing agents and no ototoxicity to the inner ear. © American Academy of Otolaryngology - Head and Neck Surgery Foundation 2011.
Keywords: Guinea pig; Inner ear; Middle ear; NasoPore; Ototoxicity

Cell adhesion on explanted intraocular lenses: Part 2: Experimental study of a surface-modified IOL in rabbits - Ishikawa, N.; Miyamoto, T.; Okada, Y.; Saika, S. (Journal of Cataract and Refractive Surgery, 2011)
Purpose: To develop a hydrophobic acrylic IOL with a hydrophilic, anti-cell adhesive surface characteristic. Setting: Department of Ophthalmology, Wakayama Medical University, Wakayama, Japan. Design: Experimental study. Methods: Hydrophobic acrylic IOLs were coated with hydrophilic 2-methacryloyloxyethyl phosphorylcholine (MPC) polymer and implanted in rabbit eyes following lens extraction. Cell adhesion on the IOL surface was histologically compared with that on an uncoated IOL under light microscopy. Specimens were also observed under scanning electron microscopy to examine the effects of MPC coating on cell morphology. Results: Hydrophilic MPC coating reduced cell adhesion on acrylic IOLs at 1 month postoperatively. Conclusion: Coating an acrylic IOL with a hydrophilic polymer inhibited cell adhesion on the IOL surface. © 2011 ASCRS and ESCRS.

From cylindrical battery ingestion to right hemicolectomy - Ribakovs, A.; Uzoigwe, C. (American Surgeon, 2011)

Detecting patient safety indicators: How valid is "foreign body left during procedure" in the Veterans Health Administration? - Chen, Q.; Rosen, A.K.; Cevasco, M.; Shin, M.; Itani, K.M.F.; Borzecki, A.M. (Journal of the American College of Surgeons, 2011)
Background: The Agency for Healthcare Research and Quality (AHRQ) developed patient safety indicator (PSI) 5, "Foreign body left during procedure," to flag accidental foreign bodies in surgical and medical procedures. This study examined how well this indicator identifies true foreign body events in the Veterans Health Administration (VA). Study Design: This was a retrospective study within 28 selected VA hospitals from fiscal year 2003 to 2007. Trained abstractors reviewed medical charts flagged by PSI 5 and determined true foreign body cases. We calculated the positive predictive value (PPV) of this indicator and performed descriptive analyses of true positive and false positive cases. Results: Of the 652,093 eligible cases, 93 were flagged by PSI 5 (0.14 per 1,000). Forty-two were true positives, yielding a PPV of 45% (95% CI 35% to 56%). False positives were due to a foreign body that was present on admission (57%) or coding errors (43%). True foreign bodies were associated with surgical (n = 23) and medical (n = 19) procedures. The most common type of surgical foreign body was a sponge (52%). Overall, approximately 40% of foreign bodies were related to a device failure or malfunction (30% surgical vs 53% medical foreign bodies). Postoperative complications included pain (24%), infection (12%), adhesions (5%), and bowel obstruction (5%). Conclusions: The reported rate of foreign body events as detected by PSI 5 is low in the VA, but occurs in both surgical and medical procedures. Despite widespread implementation of surgical counts, quality improvement efforts should focus on novel ways to eliminate this "never event" from operations. Future studies are needed to better understand the preventability of medical procedure-associated foreign bodies and particularly, device failure-related foreign bodies. © 2011 by the American College of Surgeons.

The tissue response to photopolymerized PEG-p(HPMAm-lactate)-based hydrogels - Censi, R.; Van Putten, S.; Vermonden, T.; Di Martino, P.; Van Nostrum, C.F.; Harmsen, M.C.; Bank, R.A.; Hennink, W.E. (Journal of Biomedical Materials Research - Part A, 2011)
Hydrogels are three-dimensional networks of crosslinked hydrophilic polymers widely used for protein delivery and tissue engineering. To be eligible for in vivo applications, the hydrogels should not evoke an adverse tissue response. In this study the angiogenic and inflammatory responses in vivo after implantation of photopolymerized thermosensitive poly(hydroxypropyl methacrylamide lactate)-poly(ethyl copolymer hydrogels are investigated. Hydrogels consisting of polymers with different crosslink densities were subcutaneously implanted in Balb/c mice and histological evaluation of the tissue response was performed. The implants showed an acute and localized inflammatory reaction upon implantation, mainly characterized by a strong infiltration of granulocytes. The acute inflammatory reaction was followed by a milder chronic inflammation which was characterized by infiltration of macrophages and persistent but decreasing levels of granulocytes. The number of macrophages and blood vessels was associated with the biodegradation and resorption of the biomaterial and increased in time as the degradation of the materials progressed. The observed degradation rates in vivo correlated well with previously observed in vitro degradation rates, which suggests that hydrolysis is the main mechanism governing the degradation. © 2011 Wiley Periodicals, Inc.
Keywords: angiogenesis; biodegradation; granulocytes; macrophages; photopolymerized thermosensitive hydrogels

Penetrating injury of rectum and vertebral body by steel bar causing cauda equina syndrome - Zhou, Z.; Song, Y.; Cai, Q.; Li, T.; Liu, H. (Spine, 2011)
Study Design.: Case report. Objective.: To report an extremely rare case of combined penetrating injury to rectum and vertebral body by steel bar causing cauda equina syndrome. Summary of Background Data.: Only one similar case has been reported. Our case was more severe and posed more challenges to physicians. Methods.: A 37-year-old male had a penetrating rectal injury by a long steel bar as a result of a falling accident. He was firstly treated with removal of the bar, debridement, and fecal diversion. Spine and cauda equina injuries were found the second day by lumbar and sacral CT. Because of infection after the first surgery, decompressive surgery was performed 2 months from injury. Cerebrospinal fluid fistula happened on the 12th day after surgery which was managed by debridement, irrigation and drainage, suture of the leaking skin and combined use of antibiotics. Results.: When being discharged, he could ambulate independently but could not control his voiding. The colostomy and urinary canal was preserved during the follow-up. Conclusion.: Steel bar penetrating injury of rectum and vertebral body can be severe and cause complex injuries. Complications included infection and cerebrospinal fluid fistula. Thorough history and physical examination and CT and MRI inspection are very important for timely diagnosis and early treatment of spine and cauda equina injuries. Dural tear should be carefully inspected and repaired during posterior lumbar decompression surgery. Cooperation of experienced surgeons from orthopedics and gastrointestinal department is needed to give the patient the most appropriate treatment and improve prognosis. Copyright © 2011 Lippincott Williams & Wilkins.
Keywords: cauda equina syndrome; cerebrospinal fluid fistula; penetrating injury; rectum; steel bar; vertebral body

Silicone granulomas after soft-tissue augmentation of the buttocks: A case report and review of management - Lopiccolo, M.C.; Workman, B.J.; Chaffins, M.L.; Kerr, H.A. (Dermatologic Surgery, 2011)

Clinical experience with a new vascular graft free from biodegradable material - Tamura, A.; Yamaguchi, A.; Yuri, K.; Noguchi, K.; Naito, K.; Nagano, H.; Takahashi, M.; Adachi, H. (Interactive Cardiovascular and Thoracic Surgery, 2011)
Triplex (Terumo Co., Tokyo, Japan), a newly developed large diameter vascular graft sealed with a non-biodegradable material, is expected to reduce inflammatory reaction. We confirmed its safe implantation and assessed inflammatory reaction after thoracic aortic surgery. Between January 2009 and February 2010, 101 consecutive patients underwent thoracic aortic replacement. Triplex grafts were implanted in 40 patients, and bovine-collagen coated grafts (Hemashield, Boston Scientific, Boston, MA, USA) were implanted in 61 patients. During the postoperative course, body temperature and laboratory findings including inflammatory markers were examined. The mean operation time and amount of bleeding during operation were equivalent in the two groups. The mean body temperature and Creactive protein in patients implanted with Triplex were significantly lower than those in patients implanted with Hemashield grafts. The mean white blood cell count tended to be at lower levels in patients implanted with Triplex grafts. No patients in both groups suffered postoperative complications associated with the prosthetic grafts. Triplex was confirmed to be safely applied for thoracic aortic surgery as well as the conventional vascular grafts and to reduce postoperative inflammatory reaction. © 2011 Published by European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: Inflammatory reaction; Non-biodegradable material; Triplex graft

Biocompatibility evaluation of 3 facial silicone elastomers - França, D.C.C.; De Castro, A.L.; Soubhia, A.M.P.; Tucci, R.; De Aguiar, S.M.H.C.A.; Goiato, M.C. (Journal of Craniofacial Surgery, 2011)
The failure of facial prostheses is caused by limitations in the properties of existing materials, especially the biocompatibility. This study aimed to evaluate the biocompatibility of maxillofacial silicones in subcutaneous tissue of rats. Thirty Wistar rats received subcutaneous implants of 3 maxillofacial silicone elastomers (LIM 6050, MDX 4-4210, and industrial Silastic 732 RTV). A histomorphometric evaluation was conducted to analyze the biocompatibility of the implants. Eight areas of 60.11 mm from the surgical pieces were analyzed. Mesenchymal cells, eosinophils, and foreign-body giant cells were counted. Data were submitted to analysis of variance and Tukey test. Initially, all implanted materials exhibited an acceptable tissue inflammatory response, with tissue reactions varying from light to moderate. Afterward, a fibrous capsule around the silicone was observed. The silicones used in the current study presented biocompatibility and can be used for implantation in both medical and dental areas. Their prosthetic indication is conditioned to their physical properties. Solid silicone is easier to adapt and does not suffer apparent modifications inside the tissues. Copyright © 2011 by Mutaz B. Habal, MD.
Keywords: biocompatibility; connective tissue; Facial silicone; inflammation

Clinical presentation and outcome of perforating ocular injuries due to BB guns: A case series - Nili Ahmadabadi, M.; Karkhaneh, R.; Kord Valeshabad, A.; Tabatabai, A.; Jager, M.J.; Nili Ahmadabadi, E. (Injury, 2011)
Purpose: To describe the clinical presentations and treatment modalities of a series of BB gun-related perforating ocular injuries. Methods: Clinical records of all consecutive cases of perforating BB gun injuries to the globe seen between September 2004 and September 2008 were reviewed retrospectively. At the time of the trauma and after final treatment, all patients underwent a complete ocular examination, including visual acuity, applanation tonometry for intraocular pressure, slit lamp biomicroscopy, indirect ophthalmoscopy and fundus photography, if possible. In all cases, primary globe repair was performed in the first session, and then appropriate surgery took place based on the individual situation. Results: In this study, 13 patients (11 males and 2 females) with a mean age of 20.8 years (range 9-50 years) were enrolled. The mean follow-up period was 7.2 ± 4.3 months (range 1-25 months). Initial visual acuity (VA) ranged from no-light perception (NLP) to finger counting (CF). Vitreous haemorrhage and retinal detachment were present in all involved eyes. Hyphema (30.76%), uveal and retinal prolapse (30.8%), retinal incarceration (30.8%) and retinal haemorrhage (53.8%) were other ocular findings. VA remained stable in 46.2% of the patients (6 cases). The best achieved final VA was CF at 2 m in one case after 6 months follow-up. After several surgical procedures, enucleation was necessary in only 2/13 (15.4%) cases. Conclusion: Despite several surgical procedures which decreased the number of enucleations, BB gun-perforating ocular injuries still lead to a grim visual outcome. This implies the importance of political strategies targeting on education of parents and restriction for children to access to these guns. © 2010 Elsevier Ltd. All rights reserved.
Keywords: Airgun; BB; Perforating ocular injury; Visual outcome

Esophageal Foreign Body: A Case Report - Chen, W.-C.; Lee, F.-P.; Lee, C.-M.; Chen, C.-M. (Journal of Experimental and Clinical Medicine, 2011)
Foreign body ingestion is a commonly seen medical emergency in children. Retropharyngeal abscess and mediastinitis are well-documented complications from foreign body ingestion, which reflects the importance of early diagnosis. The neck radiograph is the most significant radiographic examination performed in a child with a suspected pharyngeal lesion. We report a case where the initial malpositioned lateral view neck radiograph failed to detect a potentially serious esophageal foreign body. A second lateral view neck radiograph discovered a mass of foreign body in the upper esophagus, which was found to be a chicken bone during surgery. The case suggests that a properly positioned neck radiograph is the most important examination in the initial evaluation of a child with suspected foreign body ingestion. © 2011.
Keywords: Foreign body ingestion; Neck radiograph; Retropharyngeal abscess

Gastro-duodenal phytobezoar causing choleducho-duodenal fistula-A rare case - Akhtar, J.M.; Nerker, E.N.; Reddy, S.P.; Tiwari, S.; Chauhan, M.K.; Shahapurkar, V.V. (Pravara Medical Review, 2011)
Bezoars (BZ) are the most common foreign bodies of gastrointestinal tract. Clinical manifestations vary depending on the location and dimension of BZ from no symptoms to acute abdominal syndrome. Hereby we report the case of gastric bezoar which was perforating through first part of duodenum into common hepatic duct. There are no certain data about the therapy of choice of bezoars. The ultimate goal of the treatment of BZs is their removal and prevention of recurrence. Here gastrostomy was done and BZ was removed in piece meal.
Keywords: Common hepatic duct; Fistula; Phytobezoar

Diagnosis and treatment of 32 cases with aortoesophageal fistula due to esophageal foreign body - Zhang, X.; Liu, J.; Li, J.; Hu, J.; Yu, F.; Li, S.; Yang, X. (Laryngoscope, 2011)
Objectives/Hypothesis: Aortoesophageal fistula is a rare but life-threatening complication of foreign body ingestion. In spite of several strategies for treatment, there is little consensus regarding the optimal management of the entity. In this article, we present our experience in the diagnosis and treatment of patients with aortoesophageal fistula. Study Design: Retrospective study. Methods: A total of 3,209 admissions due to esophageal foreign body impaction were recorded in Second Xiangya Hospital between 1963 and 2010. Of these, 32 cases were complicated with aortoesophageal fistula. In these 32 patients, 19 were treated by open surgery and 13 were managed with nonsurgical measures. We compared different treatments of the patients and their clinical outcomes. Results: Foreign body and aortoesophageal fistula were found in all of these 32 cases in imaging examination and/or surgery. Three patients were completely cured and 16 patients died of fatal hemorrhage from the group of patients with surgical management. All 13 nonsurgically treated cases died. Conclusions: Early diagnosis and an aggressive surgical treatment without delay is the only form of effective therapy for the condition of aortoesophageal fistula. Imaging examination is helpful in diagnosis. In particular, three-dimensional computerized tomography is a safe, simple, and noninvasive examination method that has high sensitivity and specificity for the early diagnosis of aortoesophageal fistula. © 2011 The American Laryngological, Rhinological, and Otological Society, Inc.
Keywords: aortic disease; aortoesophageal fistula; Esophageal foreign body; Level of Evidence: 4

Interferon-γ-loaded collagen scaffolds reduce myofibroblast numbers in rat palatal mucosa - Jansen, R.G.; Van Kuppevelt, T.H.; Daamen, W.F.; Kuijpers-Jagtman, A.M.; Von Den Hoff, J.W. (European Journal of Orthodontics, 2011)
Wound contraction and scar formation after cleft palate repair lead to growth impairment of the maxilla and midface. Myofibroblasts play a key role in these processes. The application of an interferon-γ (IFN-γ)-loaded collagen scaffold after surgery might reduce the differentiation of myofibroblasts. In this study, the tissue response to IFN-γ-loaded collagen scaffolds was evaluated after implantation in the palate of rats.Scaffolds, with or without IFN-γ, were implanted submucoperiosteally in the palate of two groups of 25 five-week-old male Wistar rats. Groups of five rats were sacrificed at 1, 2, 4, 8, and 16 weeks post-implantation and processed for histological analyses. On haematoxylin and eosin-stained sections, the cell density and number of giant cells within the scaffolds were determined. Blood vessels, inflammatory cells, and myofibroblasts were detected by immunohistochemistry. The data for cell density, blood vessels, and giant cells were compared with a two-way analysis of variance. The scores for myofibroblasts and inflammation were compared by a rank sum test.A mild and rapidly subsiding inflammatory and foreign body response was found in both groups. Angiogenesis had already begun after 1 week, showed a peak after 4 weeks, and declined thereafter. IFN-γ induced a faster influx of host cells and a major reduction in myofibroblast numbers. The scaffolds might be suitable for future applications in oral surgery. © The Author 2010. Published by Oxford University Press on behalf of the European Orthodontic Society. All rights reserved.

Sensitivity of detection of radiofrequency surgical sponges: A prospective, cross-over study - Steelman, V.M. (American Journal of Surgery, 2011)
Background: A retained surgical sponge is a serious medical error that results in negative patient outcomes. Radiofrequency (RF) technology has recently been introduced to evaluate for the presence of a retained sponge. The aim of this study was to evaluate the sensitivity and specificity of the detection of surgical sponges embedded with an RF chip through the torsos of subjects of varying body habitus, including the morbidly obese. Methods: A prospective, crossover, and observer blinded study design was used. Subjects served as their own controls. With the subject supine, 4 surgical sponges were sequentially placed behind the subject's torso in locations approximating abdominal quadrants. Results: Two hundred ten subjects were enrolled in the study. Nearly half (n = 101) were morbidly obese. Eight hundred forty readings were taken. There were no false-positive or false-negative readings. The sensitivity and specificity of detection of the RF sponges through the torsos of subjects of varying body habitus were 100%. Conclusions: The sensitivity and specificity of RF sponge technology are much higher than published reports of surgical counts or published findings of intraoperative radiographs for retained sponges. Copyright © 2011 Published by Elsevier Inc.
Keywords: Morbid obesity; Operating room; Radio waves; Safety; Safety management; Surgical sponge

Using a data-matrix-coded sponge counting system across a surgical practice: Impact after 18 months - Cima, R.R.; Kollengode, A.; Clark, J.; Pool, S.; Weisbrod, C.; Amstutz, G.J.; Deschamps, C. (Joint Commission Journal on Quality and Patient Safety, 2011)
Background: Retained surgical items (RSIs), most commonly sponges, are infrequent. Yet despite sponge-counting standards, failure to maintain an accurate count is a common error. To improve counting performance, technology solutions have been developed. A data-matrix-coded sponge (DMS) system was evaluated and implemented in a highvolume academic surgical practice at Mayo Clinic Rochester (MCR). The primary end point was prevention of sponge RSIs after 18 months. Methods: Two trials were conducted before implementation. A randomized-controlled trial assessed the system's function, efficiency, and ergonomics. The second, larger trial was conducted to validate the prior findings and test product improvements. After the trials, the system was implemented in all 128 operating/procedure rooms across the MCR campus on February 2, 2009. The institutionwide implementation was intended to avoid the possibility of having standard unmarked sponges and DMSs in the operating room suite concurrently. Results: Before implementation, a retained sponge occurred on average every 64 days. Between February 2009 and July 2010, 87,404 procedures were performed, and 1,862,373 DMSs were used without an RSI (p < .001). After four cases, the average time to count a DMS decreased from 11 to 4 seconds. Total sponge counting time/operation in creased without any increase in overall operative time. Conclusions: After 18 months, a DMS system eliminated sponge RSIs from a high-volume surgical practice. The DMS system caused no work-flow disruption or increases in case duration. Staff satisfaction was acceptable, with a high degree of trust in the system. The DMS system is a reliable and cost-effective technology that improves patient safety. Copyright 2011 © The Joint Commission.

Large foreign body reaction to tension-free vaginal tape masquerading as inguinal hernia - Von Roon, A.C.; Letchworth, P.; Stafford, M. (International Urogynecology Journal, 2011)
We report a case of a 73-year-old woman who presented to general surgery with a tender lump in the groin 5 years after insertion of a tension-free vaginal tape. The lesion was thought to be an incarcerated inguinal hernia. Emergency surgical exploration revealed a 7×5×4 cm soft tissue mass which was adherent to the external inguinal ring, emanating from the end of the tension-free vaginal tape at the level of the symphysis pubis. Resection and histological examination revealed a central track of granulation tissue with a surrounding foreign body inflammatory response. The surgery was complicated by an infected seroma requiring surgical drainage and antibiotic therapy, following which the patient made a full recovery. Large foreign body reaction is a rare but an important complication of tension-free vaginal tapes and may be mistaken for a groin hernia or lymphadenopathy. © 2011 The International Urogynecological Association.
Keywords: Complications; Foreign body reaction; Tension-free vaginal tape

Implementation of a protocol to reduce occurrence of retained sponges after vaginal delivery - Lutgendorf, M.A.; Schindler, L.L.; Hill, J.B.; Magann, E.F.; O'Boyle, J.D. (Military Medicine, 2011)
Background: Retained sponges (gossypiboma) following vaginal delivery are an uncommon occurrence. Although signifi cant morbidity from such an event is unlikely, there are many reported adverse effects, including symptoms of malodorous discharge, loss of confi dence in providers and the medical system, and legal claims. Objective: To report a protocol intended to reduce the occurrence of retained sponges following vaginal delivery. Methods: After identifi - cation of limitations with existing delivery room protocols, we developed a sponge count protocol to reduce occurrence of retained vaginal sponges. We report our experience at Naval Medical Center Portsmouth, a large tertiary care military treatment facility with our efforts to implement a sponge count protocol to reduce retained sponges following vaginal delivery. Conclusions: With appropriate pre-implementation training, protocols which incorporate post-delivery vaginal sweep and sponge counts are well accepted by the health care team and can be incorporated into the delivery room routine.

Right hip necrotizing fasciitis - Lee, I.-H.; Chiu, Y.-H.; How, C.-K.; Chen, J.-D.; Yen, D.H.-T. (American Journal of the Medical Sciences, 2011)

Retroperitoneal Migration of a Septically Loose Femoral Component - Yagdi, S.; Kazimoglu, C.; Dirim, B.; Bulut, T.; Sener, M. (Journal of Arthroplasty, 2011)
Migration of total hip arthroplasty components is generally associated with a medial acetabular wall defect and may cause various intrapelvic complications. This is often a result of the destructive bone loss that takes place with infection. To our knowledge, this is the first report that presents complete intrapelvic migration of a femoral stem of total hip arthroplasty due to septic loosening with an intact medial acetabular wall. © 2011 Elsevier Inc..
Keywords: Postoperative complications; Prosthesis-related infection; Total hip arthroplasty

A prolonged buried fish bone mimicking Ludwig angina - Hsu, C.-L.; Chen, C.-W. (American Journal of Otolaryngology - Head and Neck Medicine and Surgery, 2011)
Most migrated foreign bodies in the neck were removed immediately in patients with persistent symptoms. It is a rare condition that a fish bone was buried for a prolonged time in the tongue with little discomfort. We report a unique case of an ingested fish bone lodged in the tongue for 16 months until infection ensued. Ludwig angina was considered first because the patient had fever, odynophagia, swelling of the tongue, and mouth floor. The fish bone buried in the tongue was incidentally found on the computed tomography scan and successfully removed by surgical exploration. Although dental infection is the most common underlying cause in Ludwig angina, embedded foreign body should be considered as one of the pathogenesis. On the other hand, computed tomography scan can be useful in identifying extraluminal migration of fish bones in the neck. © 2011 Elsevier Inc.

Case report on textiloma of uterus - Begum, R.; Khanum, S. (Bangladesh Journal of Obstetrics and Gynecology, 2011)
A 30years of old hypothyroid lady, presented with foul smelling excessive whitish per vaginal discharge, associated with itching in vulva & pain in the lower abdomen following caesarean section 3 months back. Her uterus was palpably enlarged and firm. USG revealed bulky uterus with wall echo shadow sign. A CT scan of whole abdomen was done that revealed intra-uterine textiloma. During laparotomy huge amount of pus came out through wound and a mob was found within uterine cavity. Textiloma is a rare problem of surgery arising from retained gauze during operation. Careful counting of surgical gauze before closure and identification by newer techniques is required to prevent this iatrogenic complication.

An unusual complication 4 years after laparoscopic adjustable banding: Jejunal obstruction due to the connecting tube - Van De Water, W.; Vogelaar, F.J.; Willems, J.M. (Obesity Surgery, 2011)
Laparoscopic adjustable gastric banding (LAGB) is an often performed bariatric procedure for morbid obesity. Several complications are known, including surgery and port-side-associated complications. As rare but serious late complication of LAGB, we describe a 50-year-old patient with periodic incomplete intestinal constriction due to the silicone connecting tube, 4 years after laparoscopic adjustable gastric banding was performed. Abdominal CT scan showed an obstructive ileus due to a loop in the connecting tube. After surgical removal of the connecting tube, the patient recovered without sequelae. © 2009 Springer Science + Business Media, LLC.
Keywords: Bariatric surgery; Jejunal obstruction; Morbid obesity; Postoperative complication

Transoralgastric gastroscopic debridement for peripancreatic abscess: A special case report - Wang, X.-W.; Fan, C.-Q.; Wang, L.; Guo, H.; Xie, X.; Zhao, G.-C.; Zhao, X.-Y. (Hepato-Gastroenterology, 2011)
Transoralgastric debridement for pancreatic abscess is one of the successful applications of NOTES in clinical practice. We present a case report as follows: a 71-year-old female was hospitalized due to acute biliary pancreatitis. Three weeks after onset, the secondary abdominal CT showed a peripancreatic abscess. A passageway between the gastric wall and the abscess was made with a high-frequency puncher under the guidance of an ultrasonic gastroscope and then a gastroscope was directly inserted into the abscess, and a large amount of solid necrotic tissue was taken out with foreign body forceps and snare under the direct vision of a gastroscope. Then a 8.5F double-J stent and a nasobiliary drainage tube were inserted. After three times of intra-abdominal abscess debridement and repeated rinsing with an antibiotic solution, abdominal CT revealed the intra-abdominal abscess nearly disappeared and the patient discharged from hospital. © H.G.E. Update Medical Publishing S.A.
Keywords: Peripancreatic abscess; Transoralgastric gastroscopic

Deep neck infection caused by fish bone migration and huge fish bone migration observed by chance: Two unusual cases of fish bone migration - Park, J.; Kim, B.; Jung, S.; Do, N. (American Journal of Case Reports, 2011)
Background: Case Report: Conclusions: key words: A fsh bone lodged in the oral cavity is in most cases removed simply; but, if it migrates, surgical intervention is necessary. We report a case of deep neck infection caused by the migration of a fsh bone which was not removed initially, as well as a case of a huge fsh bone migration found by chance along with complaints about mild symptoms. As there was no specifc fnding in simple X-ray examination and endoscopy, both of the 2 cases were diagnosed with neck CT. The fsh bones were removed with surgical exploration through lateral neck incision and the patients were discharged without any signifcant sequela. For patients swallowing a fsh bone, even though there is no abnormality in physical examination, simple X-ray and endoscopy, diagnosis should be made early through neck CT by considering the possibility of fsh bone migration. A surgical approach is needed to avoid any damage to the major structures. © The American Journal of Case Reports.
Keywords: Deep neck infections; Fish bone; Migrations

Retained foreign bodies after abdominal surgery - Ahmed, H.A.H. (New Iraqi Journal of Medicine, 2010)
Background and Objectives: To look into clinical presentations of intra-abdominal foreign bodies, identify risk factors for incorrect sponge and towel counts. Describe complications that can occur from retained sponges and towels, to see measures for prevention. Patient and method: The records of twelve patients with a confirmed diagnosis of gossypiboma after abdominal surgery at AL - Kadhimyia teaching hospital and private hospital, in Baghdad, between January 2007 and January 2010, were retrospectively reviewed Results: Nine of the twelve patients were female and three male. Previously, of the patients, three underwent elective operations and nine were operated on for emergency. Among retained surgical foreign bodies, sponges accounted for 66.6% of patients, gauze were found in 33.3% of patients.. Operated in emergency 75% and elective 25%. Clinical presentations were intestinal obstruction 25%., abdomen Mass 25%, Discharging Sinus 16.6%, Intra abdominal abscessl6.6%, Persistent abdominal pain 16.6%. Conclusions: Retained foreign bodies commonly occur during an emergent procedure when the surgical team's efforts are completely focused on saving the patient's life. In that scenario, speed is essential and taking the time to perform a surgical count may not be an option. Other situations or factors that may lead to a retained foreign body include unplanned changes in the surgical procedure, patients with increased body mass, and procedures involving increased blood loss.
Keywords: Gossypiboma; Retained abdominal

Myofibroblasts and capsular tissue tension in breast capsular contracture - Hwang, K.; Sim, H.B.; Huan, F.; Kim, D.J. (Aesthetic Plastic Surgery, 2010)
Background: This study aimed to observe the relationship between the number of myofibroblasts, the tensile strength of the breast implant capsule, and the degree of breast capsular contracture. Methods: The study enrolled 21 women with 31 capsular contractures after aesthetic breast augmentation. The capsular tissue specimens were obtained during capsulectomy, open capsulotomy, and other revisional procedures. The tensile strength of capsular tissues (1 × 3 cm) was measured by tensiometer. The capsular tissues were immunostained by alpha smooth muscle actin, and the immunostained myofibroblasts all were counted on a 2.5-mm length of the capsule. Results: Myofibroblasts were detected in 22 (71%) of 31 specimens. The myofibroblasts were on the outer layer of the capsule and made up 7.3% to 50% (average, 26.9% ± 12.7%) of the capsule thickness. The number of myofibroblasts varied according to the degree of capsular contracture, but grades 2, 3, and 4 contracture did not differ significantly (p = 0.102). The average tensile strength of the capsule was 44 ± 38 N. Tensile strength was the lowest for grade 2 (27.0 ± 22.2 N), increased for grade 3 (38.0 ± 22.6 N), and was highest for grade 4 (66.5 ± 55.4 N; p = 0.044) contracture. The tensile strength of the capsule correlated positively with the degree of capsular contracture (p = 0.029). Conclusion: The tensile strength of breast capsules correlated with the degree of capsular contracture. The authors think myofibroblasts appear during an active phase of wound contraction and diminish when the wound has matured. © 2010 Springer Science+Business Media, LLC and International Society of Aesthetic Plastic Surgery.
Keywords: Breast implantation; Contracture; Fibroblasts; Tensile strength

Infective endocarditis of native aortic valve: Destruction of leaflet with an aorto-cavitary fistula to the right ventricle - Velicki, L.; Susak, S.; Srdanovic, I.; Kovacevic, M. (Chirurgia, 2010)
Infective endocarditis is an endovascular microbial infection of cardiovascular structures, including large intrathoracic vessels and intracardiac foreign bodies. In case of periannular tissue involvement results could be catastrophic. Periannular abscess rupture leads to aorto-cavitary fistula formation with subsequent intracardiac shunting which furthermore overloads the heart progressively leading to heart failure. This complication must be timely recognized and surgically treated. Transesophageal echocardiography presents highly accurate imaging tool capable of detecting endocarditis and its complications even in the absence of positive blood cultures. Staphylococcus aureus, Streptococcus viridians groups A, C and G and Enterococcus species are the most common microorganisms that cause infective endocarditis. Several surgical techniques have been proposed for treating native valve endocarditis including valve repair or replacement, drainage of abscess cavities, the excision of necrotic tissue and the closure of aorto-cavitary fistula. We present a case of native valve endocarditis caused by Enterococcus spp. with a partial disruption of right coronary valve, two large periannular abscesses and aorto-cavitary fistula to the right ventricle.
Keywords: Aortic valve; Heart failure; Infective endocarditis; Surgery

IgG4-related meningeal disease: Clinico-pathological features and proposal for diagnostic criteria - Lindstrom, K.M.; Cousar, J.B.; Lopes, M.B.S. (Acta Neuropathologica, 2010)
IgG4-related disease has evolved from originally being recognized as a form of pancreatitis to encompass diseases of numerous organs including the hypophysis and one reported case of dural involvement. A search of the University of Virginia, Division of Neuropathology files for 10 years identified ten cases of unexplained lymphoplasmacytic meningeal inflammation that we then evaluated using immunohistochemical stains for IgG4 and IgG. Ten control cases including sarcoidosis (4), tuberculosis (1), bacterial abscess (2), Langerhans cell histiocytosis (2), and foreign body reaction (1) were also examined. The number of IgG4-positive plasma cells was counted in five high power fields (HPFs) and an average per HPF was calculated. Cases that contained greater than ten IgG4-positive cells/HPF were considered to be IgG4- related. Five of the study cases met these criteria, including one case of leptomeningeal inflammation. All cases exhibited the typical histological features of IgG4-related disease including lymphoplasmacytic inflammation, fibrosis, and phlebitis. The dural-based lesions appear to represent a subset of the cases historically diagnosed as idiopathic hypertrophic pachymeningitis. While the leptomeningeal process most closely resembles non-vasculitic autoimmune inflammatory meningoencephalitis. Given these findings, IgG4-related meningitis should be considered in the differential diagnosis of meningeal inflammatory lesions after stringent clinical and histologic criteria are used to rule out other possible diagnoses. © Springer-Verlag 2010.
Keywords: Central nervous system; Idiopathic hypertrophic pachymeningitis; IgG4-related pachymeningitis; IgG4-related sclerosing disease; Non-vasculitic autoimmune inflammatory meningoencephalitis

In vivo behavior of trimethylene carbonate and ε-caprolactone-based (co)polymer networks: Degradation and tissue response - Bat, E.; Plantinga, J.A.; Harmsen, M.C.; Van Luyn, M.J.A.; Feijen, J.; Grijpma, D.W. (Journal of Biomedical Materials Research - Part A, 2010)
The in vivo erosion behavior of crosslinked (co)polymers based on trimethylene carbonate (TMC) and ε-caprolactone (CL) was investigated. High molecular weight poly(trimethylene carbonate) (PTMC) homopolymer-and copolymer films were crosslinked by gamma irradiation. To adjust the in vivo erosion rate of the (co)polymer films, both the irradiation dose (25, 50, or 100 kGy) for PTMC and composition (100-70 mol % TMC) at a constant irradiation dose of 25 kGy were varied. After subcutaneous implantation of irradiated films in rats, their in vivo behavior was evaluated qualitatively and quantitatively. When the irradiation dose for PTMC was increased from 25 to 100 kGy, the erosion rate of nonextracted PTMC films (determined at day 5) decreased from 39.7 ± 16.0 μm day-1 to 15.1 ± 2.5 μm day-1, and the number of lymphocytes in the tissue surrounding the films decreased from 235 ± 114 cells mm-2 to 64 ± 33 cells mm-2. The number of macrophages and giant cells at the tissue-polymer interface also decreased with increasing irradiation dose. All (co)polymer films eroded completely within 28 days of implantation. Variation of the TMC content of gamma irradiated (co)polymer films did not affect the tissue response to the gamma irradiated (co)polymer films and their in vivo erosion behavior much. © 2010 Wiley Periodicals, Inc.
Keywords: Crosslinking by gamma irradiation; In vivo erosion; Poly(trimethylene carbonate); Tissue response; Trimethylene carbonate and ε-caprolactone copolymers

Decreased recent thymus emigrant number in rheumatoid factor-negative polyarticular juvenile idiopathic arthritis - Horvath, D.; Kayser, C.; Silva, C.A.A.; Terreri, M.T.; Hilário, M.O.E.; Andrade, L.E.C. (Clinical and Experimental Rheumatology, 2010)
Objectives: To determine TCR excision circle (TREC) levels, a marker of recent thymic emigrants, in the peripheral lymphocyte pool of rheumatoid factor-negative (RFØ) polyarticular juvenile idiopathic arthritis (JIA) children. Materials and methods: We studied TREC levels in peripheral blood mononuclear cells (PBMC) in 30 RFØ polyarticular JIA children with active disease and in 30 age- and gender-matched healthy controls. Signal-joint TREC concentration was determined by real-time quantitative-PCR as the number of TREC copies/μg PBMC DNA gauged by a standard curve with known number of TREC-containing plasmids. Results: TREC levels in PBMC were significantly lower in JIA (4.90±3.86 × 104 TRECs/μg DNA) as compared to controls (10.45±8.45 × 104 TRECs/μg DNA, p=0.001). There was an inverse correlation between age and TREC levels in healthy children (r=-0.438, p=0.016) but not in JIA. No clinical association was observed between TREC levels and disease activity and use of oral steroids and methotrexate. Conclusions: The finding of decreased PBMC TREC levels in RFØ polyarticular JIA children is consistent with a low proportion of recent thymus emigrants. This may interfere with the equilibrium between populations of polyclonal and naïve T cells versus oligoclonal memory auto-reactive T cells and, therefore, may hinder the maintenance of immune tolerance in this disease. © Copyright Clinical and Experimental Rheumatology 2010.
Keywords: Juvenile idiopathic arthritis; Recent thymus emigrants; T lymphocyte; Thymus; TREC

Retained foreign bodies after cardiovascular surgery - Leitz, K.H.; Neu, J. (Zeitschrift fur Herz-, Thorax- und Gefasschirurgie, 2010)
Six cases of retained foreign bodies [sternal wire, two pieces of catheters, sponge (surgical gauze), surgical towel, and an instrument] after cardiovascular surgery are presented. All six cases were submitted to the north German arbitration board with the reproach of medical malpractice. In four cases, the allegations were found to be true. How often foreign bodies are forgotten and how retainment may be prevented by count control are discussed using data from a literature search. © 2010 Springer-Verlag.
Keywords: Compensation; Count control; Foreign bodies; Malpractice; Surgical sponges

Incorrect surgical counts: A qualitative analysis - Rowlands, A.; Steeves, R. (AORN Journal, 2010)
Ensuring that patients remain free of unintended retained foreign bodies is a primary responsibility of perioperative nurses and surgical technologists. However, these incidents continue to occur despite hospital policies and AORN recommended practice guidelines for their prevention. To provide insight into how incorrect surgical counts occur, researchers conducted a qualitative analysis of the tasks and challenges faced by perioperative nurses and surgical technologists in an academic medical center and a community hospital. Using hermeneutic phenomenological methodology, we identified bad behavior, general chaos, and communication difficulties as problems associated with incorrect surgical counts. As point-of-care providers, perioperative RNs are well poised to identify problematic areas and design systems and processes that protect patients. Perioperative RNs should consider using red rules or a code of conduct as tools for improving the manual counting process. These strategies could be developed in the shared governance council or a perioperative staff-led committee to ensure adherence to AORN standards. © 2010 AORN, Inc.
Keywords: Code of conduct; Incorrect surgical counts; Patient safety; Red rules; Retained foreign bodies

Increasing patient safety and surgical team communication by using a count/time out board - Edel, E.M. (AORN Journal, 2010)
Communication and collaboration in patient care settings is vital for promoting the best possible patient outcomes. The counting of sponges, sharps, and instruments, and the surgical time out before the start of any surgical procedure are opportunities for the surgical team to address patient safety risks. Personnel in the surgical services department at St Luke's Episcopal Hospital, Houston, Texas, implemented the use of a hanging, magnetic, dry-erase board that includes the elements of a time out (eg, patient name and identifiers, procedure, site, allergies) and provides a means to document countable items. The board promotes team awareness of this time out and count information at all times during a procedure. Specific magnets on the count board identify items intentionally packed inside the patient to remind the team of the location of these items when the count is reconciled at the end of the procedure. In addition, a process of obtaining an radiograph of items similar to any missing items assists radiologists in identifying the location of retained surgical items. As a result of implementing both changes, our ability to locate missing items has significantly increased. © 2010 AORN, Inc.
Keywords: Count verification; Retained surgical items; Surgical counts; Time out

A bizarre abdominal cystic lesion - Zucchini, G.; Pezzilli, R.; Ricci, C.; Casadei, R.; Santini, D.; Calculli, L.; Corinaldesi, R. (Journal of the Pancreas, 2010)
In spite of careful intraoperative precautions and gauze counts, mistakes can still occur during surgery. In the case reported, a retained gauze leaved during a surgical approach for removing a solid-cystic papillary tumor localized in the pancreatic tail, caused both persistent abdominal discomfort and the presence of an abdominal cystic lesion at imaging techniques. When a previous operative history is present, a foreign body should be taken into account in the differential diagnosis of a patient with an intraabdominal cystic mass. Finally, radio-opaque marker should be routinely used by surgeons in order to reach a correct diagnosis in operated patients having retained gauze.
Keywords: Abdominal abscess; Abdominal pain; Spiral computed; Surgical sponges; Tomography

Nail puncture wound through a rubber-soled shoe: A retrospective study of 96 adult patients - Rubin, G.; Chezar, A.; Raz, R.; Rozen, N. (Journal of Foot and Ankle Surgery, 2010)
Nail punctures through rubber-soled shoes expose the foot to the possibility of deep infection and foreign body retention. In this article, we describe characteristics of adult patients who sustained nail puncture wounds through a rubber-soled shoe and were treated at our institution from January 1, 2000, to January 8, 2008. Of the 96 patients, 36 (37.5%) were treated conservatively and 60 (62.5%) were treated surgically in the operating room. Of those treated surgically, 15 (25%) had a foreign body extracted during the operation. The operated group had a longer duration of time from injury to hospital admission than did the nonoperated group (5.0 ± 6.8 days versus 2.7 ± 3.8 days, P < .05). Treatment success was observed in 91 (94.8%) of the patients, and the median lag time before admission for the less successfully treated group was longer than that for the successfully treated group (10 days versus 2 days, P < .002); and, the less successfully treated group was more likely to receive antibiotics in the community before hospitalization (100.0% versus 47.2%, P < .06), and was more likely to be diabetic (40.0% versus 9.9%, P < .10). Fever, white blood cell count, and erythrocyte sedimentation rate were not significantly associated with treatment outcome. Success of the treatment did not depend on white blood cell count, erythrocyte sedimentation rate, or fever. Ultrasonography was useful in detecting the presence of a foreign body. © 2010 American College of Foot and Ankle Surgeons.
Keywords: Foreign body; Sole; Surgery; Trauma; Ultrasonography

Impact of heavy polypropylene mesh and composite light polypropylene and polyglactin 910 on the inflammatory response - Di Vita, G.; Patti, R.; Barrera, T.; Arcoleo, F.; Ferlazzo, V.; Cillari, E. (Surgical Innovation, 2010)
The aim of the study was to analyze the acute inflammatory response after implantation of a heavyweight mesh of polypropylene (PP) compared with a composite mesh of light PP and polyglactin 910 (PG) in patients undergoing inguinal hernioplasty. A total of 30 male patients with inguinal hernia were included in the study and divided into 2 groups (PP and PP-PG) according to the mesh used. Changes of leukocytes, cytokines, growth factors, and acute phase proteins were evaluated in the sera. Leukocytes and acute phase proteins were significantly increased postoperatively in both groups, and the values were slightly higher in the PP group. Cytokine levels were significantly increased postoperatively in both groups; a slight increase was observed in the PP-PG group, especially for the proinflammatory cytokine. Growth factors decreased significantly in both groups immediately after surgery. The authors found that the use of the mesh is a stimulator of inflammatory response, and the 2 types of mesh induce a similar inflammatory response. © The Author(s) 2010.
Keywords: hernioplasty; inflammatory response; inguinal hernia; mesh; polyglactin 910; polypropylene

Rhinolithiasis: An unusual cause of sinusitis complicated with frontal osteomyelitis and epidural abscess - Atmaca, S.; Belet, N.; Şensoy, G.; Belet, U. (Turkish Journal of Pediatrics, 2010)
Rhinoliths are rare foreign bodies of the nose formed by in situ mineralization of endogenous or exogenous foreign material. They are often asymptomatic but may have various clinical presentations, with purulent rhinorrhea and nasal obstruction being the most common. They may go unnoticed for a long period and be diagnosed accidentally during a routine examination. We report a 6.5-year-old girl with rhinolithiasis complicated with sinusitis, frontal osteomyelitis and epidural abscess; she had a history dating back four years.
Keywords: Epidural abscess; Frontal osteomyelitis; Rhinolithiasis; Sinusitis

Courts rejected RIL: did nurses botch sponge count? Baxter v. Ash Samaritan Hospital, LLC, 2008-CA-000541-MR KYCA (1/15/2010)-KY. (Nursing law's Regan report, 2010)

Endoscopic lower esophageal sphincter bulking for the treatment of GERD: Safety evaluation of injectable polymethylmethacrylate microspheres in miniature swine - Kamler, J.P.; Lemperle, G.; Lemperle, S.; Lehman, G.A. (Gastrointestinal Endoscopy, 2010)
Background: Endoscopic therapy for GERD is an appealing, minimally invasive alternative to medical treatment and surgery. Various materials have been tested to augment the lower esophageal sphincter (LES), with limited success. To our knowledge, safety and migration of polymethylmethacrylate (PMMA) microspheres has never been evaluated. Objective: To assess the safety, migration, inflammatory reaction, and durability of PMMA injected into the LES of miniature swine to create a reflux barrier. Design: Animal study. Setting: Approved animal research facilities. Intervention: Injection of the LES of miniature swine with PMMA. Histopathology of the injected site at certain intervals and postnecropsy microsphere counts of various organs. Main Outcome Measurements: Minimal inflammatory reaction at the injection site, persistent bulking effect of the material, and no migration of microspheres. Results: Injection of LES with PMMA caused a mild inflammatory reaction. The bulking effect of the injected material was persistent. Migration of microspheres was eliminated with the use of larger-sized microspheres. Limitations: Animal model. Conclusion: Our phase I study documented that 40-μm polymethylmethacrylate microspheres are biocompatible and that PMMA microspheres are resistant to degradation when injected submucosally into the wall of the esophagus. The detection of 40-μm PMMA microspheres in local lymph nodes, liver, and lungs of some animals in the phase I study clearly documented transport of PMMA away from the injection site. This finding was eliminated by increasing the size of microspheres to 125 μm. The potential therapeutic effects of these larger microspheres for humans with GERD remains to be evaluated. Copyright © 2010 by the American Society for Gastrointestinal Endoscopy.

The effect of liposome-delivered prednisolone on collagen density, myofibroblasts, and fibrous capsule thickness around silicone breast implants in rats - Moreira, M.; Fagundes, D.J.; De Jesus Simoes, M.; Taha, M.O.; Perez, L.M.N.; Bazotte, R.B. (Wound Repair and Regeneration, 2010)
Capsular contracture is a potential adverse effect of breast implants. An inflammatory reaction is most likely the origin of fibrosis around the implant. It is possible that some substances may act to prevent this inflammatory reaction. Thus, our goal was to evaluate the effectiveness of local depot prednisolone phosphateliposomes (PPL) on fibrous capsule formation around textured silicone breast implants. Shell prostheses (2 mL) were implanted in the right (plus PPL group) and left (plus saline solution, saline group) subcutaneous dorsum of 18 rats. In another 18 rats, the implants were positioned in the left of the back without any drug instillation (control group). In the PPL group, the capsule thickness (mm) and density (%) of collagen were significantly (p < 0.0001) lower compared with the control group on days 35 and 90 postsurgery. Furthermore, in the PPL group, a significant reduction in myofibroblast count was observed on day 90 postsurgery (p < 0.0001). In conclusion, a single dose of depot liposome-delivered prednisolone was effective at impairing capsule formation around the silicone implant. The results suggest a strong local and weak systemic effect of PPL on the fibrous tissue around silicone implants. To our knowledge, no study has yet assessed the effect of PPL on silicone breast implants. © 2010 by the Wound Healing Society.

Transanal Repair of Colonic Perforation due to Ventriculoperitoneal Shunt-Case Report and Review of the Literature - Chiang, L.-L.; Kuo, M.-F.; Fan, B.-J.; Hsu, W.-M. (Journal of the Formosan Medical Association, 2010)
Colonic perforation is an extremely rare complication following ventriculoperitoneal (VP) shunting. Laparotomy to repair the perforation site is usually required for patients with peritonitis. Here we report colonic perforation due to VP shunt in a 4-year-old girl, presenting with a distal catheter protruding out of the anus as well as symptoms and signs of peritonitis. The distal catheter was removed and the perforation site was repaired successfully via the anus. Postoperative course was uneventful. Trans-anal repair of the colonic perforation after removal of the distal shunt may be considered an alternative choice for managing this kind of complication. © 2010 Formosan Medical Association & Elsevier.
Keywords: bowel perforation; transanal repair; ventriculoperitoneal shunt

Characterization of the in vitro macrophage response and in vivo host response to poly(ethylene glycol)-based hydrogels - Lynn, A.D.; Kyriakides, T.R.; Bryant, S.J. (Journal of Biomedical Materials Research - Part A, 2010)
Photopolymerizable poly(ethylene glycol) (PEG)-based hydrogels have great potential as in vivo cell delivery vehicles for tissue engineering. However, their success in vivo will be dependent on the host response. The objectives for this study were to explore the in vivo host response and in vitro macrophage response to commonly used PEG-based hydrogels, PEG and PEG containing RGD. Acellular hydrogels were implanted subcutaneously into c57bl/6 mice and the foreign body response (FBR) was compared to medical grade silicone. Our findings demonstrated PEG-RGD hydrogels resulted in a FBR similar to silicone, while PEG-only hydrogels resulted in a robust inflammatory reaction characterized by a thick layer of macrophages at the material surface with evidence of gel degradation. In vitro, bone marrow-derived primary macrophages adhered well and similarly to PEG-based hydrogels, silicone, and tissue culture polystyrene when cultured for 4 days. Significantly higher gene expressions of the proinflammatory cytokines, TNF-a and Il-1b, were found in macrophages seeded onto PEG compared to PEG-RGD and silicone at 1 and 2 days. PEG hydrogels were also shown to be susceptible to oxidative biodegradation. Our findings indicate that PEG-only hydrogels are proinflammatory while RGD attenuates this negative reaction leading to a moderate FBR. © 2009 Wiley Periodicals, Inc.
Keywords: In vivo; Inflammation; Macrophage; Murine; Poly(ethylene glycol)

Penetrating injury to the pharynx by scissors leading to retropharyngeal abscess in a depressed man - Lin, C.-H.; Chu, Y.-S.; Liao, C.-F.; Chen, Y.-L.; Hsu, K.-C. (Journal of Medical Sciences, 2010)
Retropharyngeal abscess caused by pharyngeal penetrating injury is a rare but life threatening condition with extensive fasciitis and possible gas accumulating in the prevertebral fascia. Pharyngeal penetrating injuries are uncommon, except for those with a definite history of foreign body swallowing or external traumatic injury. We described a 24-year-old man, who sustained retropharyngeal abscess with gas formation in the retropharyngeal soft tissue after swallowing and vomiting a pair of scissors. In the emergency department (ED), an early computed tomography scan helped with the diagnosis and showed the extent of the ailment, which was promptly treated with surgical debridement and drainage. Broad-spec-trum antibiotics were started as soon as possible, while the clinical suspicion was initially made. The patient was treated promptly and discharged without serious complications. © 2010 JMS.
Keywords: Depression; Penetrating injury; Prevertebral soft tissue; Retropharyngeal abscess

Late extrusion of pulmonary plombage outside the thoracic cavity - Yadav, S.; Sharma, H.; Iyer, A. (Interactive Cardiovascular and Thoracic Surgery, 2010)
Plombage, a variant of collapse therapy for patients with pulmonary tuberculosis that uses a variety of foreign materials, was undertaken until the 1950s before the invention of effective antimicrobial therapy. Complications related to previous plombage procedures are not uncommon. Management of these complications can be challenging. We report a patient presenting with extrusion of plombage 59 years later and managed successfully with removal of the plomb and pectoral muscle flap transposition. © 2010 Published by European Association for Cardio-Thoracic Surgery.
Keywords: Pectoral muscle flap; Plombage; Tuberculosis

The effect of incorporation of SDF-1α into PLGA scaffolds on stem cell recruitment and the inflammatory response - Thevenot, P.T.; Nair, A.M.; Shen, J.; Lotfi, P.; Ko, C.-Y.; Tang, L. (Biomaterials, 2010)
Despite significant advances in the understanding of tissue responses to biomaterials, most implants are still plagued by inflammatory responses which can lead to fibrotic encapsulation. This is of dire consequence in tissue engineering, where seeded cells and bioactive components are separated from the native tissue, limiting the regenerative potential of the design. Additionally, these interactions prevent desired tissue integration and angiogenesis, preventing functionality of the design. Recent evidence supports that mesenchymal stem cells (MSC) and hematopoietic stem cells (HSC) can have beneficial effects which alter the inflammatory responses and improve healing. The purpose of this study was to examine whether stem cells could be targeted to the site of biomaterial implantation and whether increasing local stem cell responses could improve the tissue response to PLGA scaffold implants. Through incorporation of SDF-1α through factor adsorption and mini-osmotic pump delivery, the host-derived stem cell response can be improved resulting in 3X increase in stem cell populations at the interface for up to 2 weeks. These interactions were found to significantly alter the acute mast cell responses, reducing the number of mast cells and degranulated mast cells near the scaffold implants. This led to subsequent downstream reduction in the inflammatory cell responses, and through altered mast cell activation and stem cell participation, increased angiogenesis and decreased fibrotic responses to the scaffold implants. These results support that enhanced recruitment of autologous stem cells can improve the tissue responses to biomaterial implants through modifying/bypassing inflammatory cell responses and jumpstarting stem cell participation in healing at the implant interface. © 2010 Elsevier Ltd.
Keywords: Angiogenesis; Biocompatibility; Hematopoietic stem cells; Inflammation; Mesenchymal stem cell; Scaffold

Gossypiboma: A lesson to learn: Case report - Ilter, E.; Manukyan, M.N.; Haliloǧlu, B.; Çelik, A.; Özden, S. (Turkiye Klinikleri Jinekoloji Obstetrik, 2010)
The term "gossypiboma" denotes foreign bodies retained after surgery. The most common gossypiboma is the iatrogenic surgical sponge. Usually, hysterectomy, appendectomy and cholecystectomy operations are associated with these retained sponges. They may be misdiagnosed as incisional endometriosis. We present a patient who had a caesarean section operation eleven years ago with a mass at the abdominal wall between the umbilicus and the caesarean section scar on the left paramedian region approximately 5 x 2 cm in diameter. We must keep in mind that prevention is more important for cure. As we knew that most reported cases occur in the presence of a normal pack count, we think that the surgical team must be very careful in the operation room.
Keywords: Endometriosis; Foreign bodies

Intra vaginal wooden foreign body causing multiple internal fistulae and bladder stone in a 12 years girl - Jan, I.A.; Arif, K.; Anwar-ul-Haq; Gondal, M.; Orakzai, H. (Pakistan Journal of Medical Sciences, 2010)
Vaginal foreign bodies in girls may be accidental, self-inflicted or secondary to child abuse. These may causes a number of complications like Infections, abscess formation, intestinal perforation, vaginal discharge and internal fistulae. We are presenting a case of a 13 years old girl who presented with a supra-pubic mass and dysuria. X-ray showed a radio-opaque shadow in pelvis. The child was admitted in medical ward with the diagnosis of bladder stone and UTI. She was pouring frank pus from the vagina. On rectal digital examination a hard foreign body was felt in the rectum. Investigations revealed that she had a large pelvic collection, a sharp wooden Foreign Body (FB) extending from the rectum through the vagina in to the urinary bladder forming a bladder stone. Patient also developed recto-vaginal and vesico-vaginal fistulae. Foreign body was removed along with the bladder stone, pelvic abscess drained and colostomy was performed. Later repair of vesico-vaginal fistula were performed, recto-vaginal fistula closed spontaneously and colostomy closed. Patient became fully continent for urine and feces after completion of surgical procedures. A careful history from the child revealed that she had inserted the foreign body herself as a self-exploring practice.
Keywords: Complications; Internal fistula; Vaginal foreign body; Wooden

Peritonitis due to Mycobacterium fortuitum following gastric banding - Al Majid, F.M. (Saudi Journal of Gastroenterology, 2010)
Mycobacterium fortuitum is a rapid growing nontuberculous organism that has rarely been associated with peritonitis in an otherwise healthy host. We describe a patient who developed peritonitis due to the organism after gastric banding operation, which resolved after removal of the gastric band and institution of appropriate antibiotic therapy.
Keywords: Hospital acquired; Mycobacterium fortuitum; Peritonitis

Poly(3-hydroxybutyrate) multifunctional composite scaffolds for tissue engineering applications - Misra, S.K.; Ansari, T.I.; Valappil, S.P.; Mohn, D.; Philip, S.E.; Stark, W.J.; Roy, I.; Knowles, J.C.; Salih, V.; Boccaccini, A.R. (Biomaterials, 2010)
Poly(3-hydroxybutyrate) (P(3HB)) foams exhibiting highly interconnected porosity (85% porosity) were prepared using a unique combination of solvent casting and particulate leaching techniques by employing commercially available sugar cubes as porogen. Bioactive glass (BG) particles of 45S5 Bioglass® grade were introduced in the scaffold microstructure, both in micrometer ((m-BG), <5 μm) and nanometer ((n-BG), 30 nm) sizes. The in vitro bioactivity of the P(3HB)/BG foams was confirmed within 10 days of immersion in simulated body fluid and the foams showed high level of protein adsorption. The foams interconnected porous microstructure proved to be suitable for MG-63 osteoblast cell attachment and proliferation. The foams implanted in rats as subcutaneous implants resulted in a non-toxic and foreign body response after one week of implantation. In addition to showing bioactivity and biocompatibility, the P(3HB)/BG composite foams also exhibited bactericidal properties, which was tested on the growth of Staphylococcus aureus. An attempt was made at developing multifunctional scaffolds by incorporating, in addition to BG, selected concentrations of Vitamin E or/and carbon nanotubes. P(3HB) scaffolds with multifunctionalities (viz. bactericidal, bioactive, electrically conductive, antioxidative behaviour) were thus produced, which paves the way for next generation of advanced scaffolds for bone tissue engineering. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Bioactive glass; Bone tissue engineering; Carbon nanotubes; Composite materials; Poly(3-hydroxybutyrate); Scaffolds

Efficacy of antimicrobial polymer coatings in an animal model of bacterial infection associated with foreign body implants - Hart, E.; Azzopardi, K.; Taing, H.; Graichen, F.; Jeffery, J.; Mayadunne, R.; Wickramaratna, M.; O'Shea, M.; Nijagal, B.; Watkinson, R.; O'Leary, S.; Finnin, B.; et al. (Journal of Antimicrobial Chemotherapy, 2010)
Objectives: To assess support discs, comprising polyethylene terephthalate (PET), coated with different polymer/levofloxacin combinations for antimicrobial activity in an animal model of infection, in order to explore the use of specific polymer coatings incorporating levofloxacin as a means of reducing device-related infections. Methods: Aliphatic polyester-polyurethanes containing different ratios of poly(lactic acid) diol and poly(caprolactone) diol were prepared, blended with levofloxacin and then used to coat support discs. The in vitro levofloxacin release profiles from these discs were measured in aqueous solution. Mice were surgically implanted with the coated discs placed subcutaneously and infection was initiated by injection of 106 cfu of Staphylococcus aureus into the subcutaneous pocket containing the implant. After 5, 10, 20 and 30 days, the discs were removed, and the number of bacteria adhering to the implant and the residual antimicrobial activity of the discs were determined. Results: In vitro, the release of levofloxacin from the coated discs occurred at a constant rate and then reached a plateau at different timepoints, depending on the polymer preparation used. In vivo, none of the discs coated with polymer blends containing levofloxacin was colonized by S. aureus, whereas 94% of the discs coated with polymer alone were infected. All discs coated with levofloxacin-blended polymers displayed residual antimicrobial activity for at least 20 days post-implantation. Conclusions: Bioerodable polyester-polyurethane polymer coatings containing levofloxacin can prevent bacterial colonization of implants in an intra-operative model of device-related infections. © The Author 2010. Published by Oxford University Press on behalf of the British Society for Antimicrobial Chemotherapy. All rights reserved.
Keywords: Implant-associated infections; Levofloxacin; Staphylococcus aureus

Surprise Finding at Endoscopic Retrograde Cholangiopancreatography - Taylor, K.M.; Foxton, M.; McNair, A. (Clinical Gastroenterology and Hepatology, 2010)

Review of Best Practices and Literature on Instrument Counts - Halvorson, C.K. (Perioperative Nursing Clinics, 2010)
With a heightened emphasis on patient safety and a lowered tolerance for the occurrence of "never events" there is a need for improved practices. Evidence-based knowledge bridges this gap by providing direction for best practices that ensure consistent and sustained safe patient care and optimal outcomes. Perioperative nursing has a long-standing and well-respected position of advocating for safe patient care. With intimate knowledge of the counting process, perioperative nurses, as key stakeholders in the multidisciplinary approach, must contribute to the body of evidence regarding best practices for effective surgical counts. © 2010 Elsevier Inc. All rights reserved.
Keywords: Best practices; Evidence-based practice; Never-events; Retained foreign objects; Sharp/needle; Sponge/swab; Surgical instrument counts

Retroperitoneal abscess with consecutive acute renal failure caused by a lost gallstone 2 years after laparoscopic cholecystectomy - Justinger, C.; Sperling, J.; Katoh, M.; Kollmar, O.; Schilling, M.K.; Schuld, J. (Langenbeck's Archives of Surgery, 2010)
A 70-year-old male patient presented with abdominal pain, acute renal failure, and fever 2 years after laparoscopic cholecystectomy. During the surgical drainage of the abscess formation on the patient́s right flank, a huge gallstone was found in the retroperitoneum. The patient was dismissed from the hospital 11 days after admission with normal lab panel and restored renal function. © Springer-Verlag 2010.
Keywords: Acute renal failure; Laparoscopic cholecystectomy; Lost gallstone; Retroperitoneal abscess

Biocompatibility and safety evaluation of a ricinoleic acid-based poly(ester-anhydride) copolymer after implantation in rats - Vaisman, B.; Motiei, M.; Nyska, A.; Domb, A.J. (Journal of Biomedical Materials Research - Part A, 2010)
The aim of this study was to evaluate the safety and tissue compatibility of an injectable biodegradable poly(ester-anhydride) copolymer of ricinoleic acid (RA) and sebacic acid (SA) in rats. The absorbable biomaterial containing 70% w/w of RA and 30% w/w of SA [P(SA-RA) 3:7] was implanted in rats in two separate studies: (1) at high doses subcutaneously (SC) and intramuscularly (IM) simultaneously into the same animal and (2) intracranially (IC). The safety was established in the highdose administration experiment. No systemic tissue damage, polymer-related lesions, or abnormalities could be detected in the animals. The histopathological evaluation of the SC and IM P(SA-RA) 3:7 implanted sites suggested a typical foreign body reaction (FBR) to biomaterials, and was characterized by excellent tissue repair and good tissue tolerance. In the second experiment, no neurological deficits or behavior changes suggestive of systemic or localized toxicity were observed in the animals implanted IC with the polymer. Only minimal, well-demarcated inflammatory response was observed on days 14 and 21 and consisted of glia cells. No abnormalities were noted in the brain tissue parenchyma located further from the edges of the implant. These results demonstrated that the P(SA-RA) 3:7 copolymer was tolerated well by the animals and compatible with rat subcutaneous, muscle and brain tissues. The biodegradable polymeric system described here could be used as a scaffold for varied applications in localized and sustained delivery of therapeutic agents. © 2009 Wiley Periodicals, Inc.
Keywords: Biocompatibility; Biodegradable polymer; Implant; Injectable drug-delivery scaffold; Poly(ester-anhydride) copolymer; Ricinoleic acid-based polymer

Surgical treatment of severely traumatized eyes with no light perception - Heidari, E.; Taheri, N. (Retina, 2010)
Purpose: The purpose of this study was to evaluate the anatomical and functional outcomes of surgical intervention in severely traumatized eyes with no light perception (NLP). Methods: In this prospective interventional case series, 18 eyes of 18 patients with severe ocular trauma whose vision was documented as NLP and with relative afferent pupillary defect of 3 to 4+ underwent deep vitrectomy and other appropriate procedures 1 to 3 times. Results: Vision was NLP in all eyes at the time of surgery, which was performed 3 days to 14 days after the initial trauma. During a mean follow-up period of 20.5 ± 5.2 months (range, 11-36 months), except for 1 case of phthisis, other eyes achieved acceptable anatomical and functional outcomes. Postoperative vision was NLP in 2 eyes (11.1%), light perception in 3 eyes (16.7%), hand motions in 4 eyes (22.2%), counting fingers in 3 eyes (16.7%), and 20/200 or better in 6 eyes (33.4%). Conclusion: After eye trauma, NLP vision and relative afferent pupillary defect of 3 to 4+ alone may not be an indication for enucleation. Performing exploratory surgery within 14 days after the injury may salvage the globe and improve vision; this approach also entails positive psychologic effects for patients and relatives. Copyright © by Ophthalmic Communications Society, Inc.
Keywords: No light perception; Surgical treatment; Traumatized eye

Immunological response to tissue-engineered cartilage derived from auricular chondrocytes and a PLLA scaffold in transgenic mice - Fujihara, Y.; Takato, T.; Hoshi, K. (Biomaterials, 2010)
The immune response against biomaterials in tissue-engineered constructs could potentially worsen the outcome of tissue regeneration, but immunological reactions between host and donor in tissue-engineered constructs remain to be clarified. In the present study, we syngenically transplanted tissue-engineered cartilage constructs consisting of C57BL/6 mice auricular chondrocytes and poly-l-lactic acid scaffolds (MW:200,000) into EGFP transgenic mice of C57BL/6 background, and evaluated the response by the localization of donor-derived and host-derived cells, the latter of which were distinguished by the presence of EGFP. While donor-derived cells constituted the areas of regenerated cartilage, host-derived cells were increased in number for the initial two weeks, and then decreased and excluded to non-cartilage areas thereafter. Furthermore, EGFP positivity was mostly co-localized with that of F4/80, suggesting most of the host-derived cells in the tissue-engineered constructs could be macrophages. Immunohistochemical staining of the tissue-engineered cartilage constructs revealed expression of factors related to immune privilege in chondrocytes, such as macrophage migration inhibitory factor (MIF), fas ligand (FasL) and others. Co-culture of chondrocytes and macrophages in vitro increased the expression of MIF and FasL in the chondrocytes, suggesting that chondrocytes in tissue-engineered cartilage constructs could regulate the actions of host-derived macrophages by expressing factors related to immune privilege. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Cartilage tissue engineering; Foreign body response; Immune response; Immunomodulation; Polylactic acid; Scaffold

Retained surgical foreign bodies: Can these be prevented? - Sushel, C.; Khanzada, T.W.; Samad, A. (Pakistan Journal of Medical Sciences, 2010)
Objectives: To determine the frequency and modes of presentation of retained surgical foreign bodies. Methodology: This study was carried out mainly at a private teaching hospital i.e. Isra University Hospital and four other non-teaching private hospitals of Hyderabad city over a period of five years from June 2004 to May 2009. Results: A total of 15 patients with retained surgical foreign body were found during the above mentioned study period. Female patients were more common than male patients. Gynaecological procedures were more frequently associated with surgical retained foreign bodies. Most (60%) of the causative procedures were performed as emergency procedures. Retained sponge was the most frequent foreign body (60%) followed by gauze piece. Discharging sinuses and abdominal masses (33.3% each) were the most frequent presentations followed by intestinal obstruction (20%). Conclusion: Retained surgical foreign body is a rare but well known iatrogenic complication of surgery mostly seen in procedures done as emergency. Discharging sinuses, abdominal mass and intestinal obstruction are the most common modes of presentation. Proper frequent double sponge count and use of radioopaque markers are the major preventive measures to safeguard against this dangerous complication.
Keywords: Gossypiboma; Retained sponge; Retained surgical foreign body

Textiloma, migration of retained long gauze from abdominal cavity to intestine - Govarjin, H.M.; Talebianfar, M.; Fattahi, F.; Akbari, M.E. (Journal of Research in Medical Sciences, 2010)
Retaining of gauzes and surgical sponges in the abdomen is one of the most frequent medical errors usually manifesting as abscess or abdomino-cutaneus fistulas with no definite symptoms during lifetime. Here, we introduce a 35 year old woman with symptoms and signs of partial bowel obstruction and enterocutaneous fistulas caused by migration of retained gauze from abdominal cavity to terminal ileum, 9 months after cesarean section. This is called "Textiloma". There are several reports of gossypiboma worldwide but migration of retained gauze into intestine causing an enterocutaneous fistula is rare.
Keywords: Foreign body; Gossypiboma; Retained surgical towel; Surgical error

Retained surgical sponges: What the practicing clinician should know - Sakorafas, G.H.; Sampanis, D.; Lappas, C.; Papantoni, E.; Christodoulou, S.; Mastoraki, A.; Safioleas, M. (Langenbeck's Archives of Surgery, 2010)
Retained surgical sponges (RSS) are an avoidable complication following surgical operations. RSS can elicit either an early exudative-type reaction or a late aseptic fibrous tissue reaction. They may remain asymptomatic for long time; when present, symptomatology varies substantially and includes septic complications (abscess formation, peritonitis) or fibrous reaction resulting in adhesion formation or fistulation into adjacent hollow organs or externally. Plain radiograph may be useful for the diagnosis; however, computed tomography is the method of choice to establish correct diagnosis preoperatively. Removal of RSS is always indicated to prevent further complications. This is usually accomplished by open surgery; rarely, endoscopic or laparoscopic removal may be successful. Prevention is of key importance to avoid not only morbidity and even mortality but also medicolegal consequences. Preventive measures include careful counting, use of sponges marked with a radiopaque marker, avoidance of use of small sponges during abdominal procedures, careful examination of the abdomen by the operating surgeon before closure, radiograph in the operating theater (either routinely or selectively), and recently, usage of barcode and radiofrequency identification technology. © Springer-Verlag 2010.
Keywords: Complications; Fistula; Foreign bodies; Instruments; Morbidity; Retained; Sponges; Surgery

Toothpick ingestion causing duodenal perforation - Ragazzi, M.; Delcò, F.; Rodoni-Cassis, P.; Brenna, M.; Lavanchy, L.; Bianchetti, M.G. (Pediatric Emergency Care, 2010)
In childhood, almost all swallowed objects that successfully navigate the esophagus pass through the gut without complications. In a 15-year-old male adolescent with the initial working diagnosis of acalculous cholecystitis, computed tomography revealed a thickened wall of the second duodenal portion, some infiltration of the periduodenal tissue, and a hyperdense needle-shape structure probably passing through the duodenal wall. Endoscopy revealed a wooden toothpick perforating the duodenum that was carefully retracted. An uneventful recovery followed the endoscopic removal of the foreign body. A computer-based search of the literature to examine the injuries caused by ingested toothpicks since 1960 found only 4 reports in 5 children. © 2010 by Lippincott Williams & Wilkins.
Keywords: duodenal perforation; foreign bodies ingestion; toothpick

Retained intraabdominal gossypiboma, five years after bilateral orchiopexy - Moslemi, M.K.; Abedinzadeh, M. (Case Reports in Medicine, 2010)
Introduction. Gossypiboma or textiloma is used to describe a retained surgical swab in the body after an operation. Intraabdominal surgical sponge is an uncommon surgical error. The incidence of gossypiboma has been reported as high as 1 in 1000 to 15,000 intraabdominal operations. Gossypiboma may cause serious morbidity and may lead to mortality. Case presentation. Herein, we report a 24 years-old man who was admitted due to the intraabdominal mass after evaluation of primary infertility. He had a surgical history of bilateral abdominal orchiopexy 5 years previously, performed at another hospital. Hydatid cyst was suspected by abdominal computed tomography. After laparotomy excision, the cyst wall opened incidentally, and draining of a large amount of thick pus with retained surgical gauze within the cyst was found, with final diagnosis of gossypiboma. Conclusion. The policy that prevention is far more important than cure is highly appreciated. Accurate sponge and instrument counts, along with radiologic evaluation when a discrepancy is found, can be helpful. Although human errors cannot be completely avoided, continuousmedical training and strict adherence to rules of the operation room should reduce the incidence of gossypiboma to a minimum. Surgical sponges should be counted once at the start and twice at the end of all surgical operations. Copyright © 2010 M. K. Moslemi and M. Abedinzadeh.

Conjunctival scrape cytology findings in patients with chronic graft-versus-host disease following allogeneic bone marrow transplantation - Hosseini, H.; Kumar, P.V.; Geramizadeh, B.; Nowroozizadeh, B.; Ramzi, M. (Acta Cytologica, 2010)
Objective: To describe the conjunctival scrape cytology findings in patients with chronic graft-versus-host disease (GVHD). Study Design: Conjunctival scrape cytology was performed to find the cause of conjunctivitis in 20 patients with chronic conjunctival GVHD. All patients had chronic ocular symptoms such as foreign body sensation, burning, tearing and red eye. Twenty age-matched bone marrow transplant recipients without GVHD were included as a control group. Results: Scraping yielded a sufficient number of cells. Cytologic findings included atypical epithelial cells; loss of goblet cells; epithelial cells with vacuolated or coarse, granular cytoplasm; squamous metaplasia; and a prominent inflammatory background. Conclusion: Conjunctival scrape cytology yields a sufficient number of cells in conjunctival GVHD. This method is useful for the diagnosis of complications associated with conjunctival GVHD and may be helpful in evaluating the response to treatment options. © The International Academy of Cytology.
Keywords: Bone marrow transplantation; Conjunctival disease; Graft-versus-host disease; Scrape cytology

Microvascular response to calcium phosphate bone substitutes: An intravital microscopy analysis - Roetman, B.; Ring, A.; Langer, S.; Schildhauer, T.A.; Muhr, G.; Köller, M. (Langenbeck's Archives of Surgery, 2010)
Objectives: The purpose was to evaluate inflammatory and microcirculatory reactions after implantation of various calcium phosphate bone substitutes in an in vivo model. Methods: Calcium phosphate-based bone substitutes were implanted in dorsal skinfold chambers of mice. Intravital fluorescence microscopy was performed to measure inflammatory and microcirculatory reactions based on functional vessel density (FVD), capillary leakage, and relative white blood cell velocity (rWBCV). Results: An increase of FVD was observed in all groups and the capillary leakage grew with a level of significance (p<0.001). The fraction of rolling and sticking leukocytes (rWBCV) was highest at the beginning of the trial and decreased during the course. Conclusions: There are differences in microvascular soft tissue reactions between various calcium phosphate bone substitutes, but inflammatory reactions were moderate, and the results revealed no reasons which explain the sporadic failure of the tested substances under clinical conditions. © Springer-Verlag 2010.
Keywords: Dorsal skinfold chamber; Fluorescence microscopy; Inflammatory reaction; Microvascular response; Resorbable bone substitutes

Conductive keratoplasty for the treatment of astigmatism induced by corneal trauma or incision - Xu, W.; Ye, P.; Yao, K.; Ma, J.; Xu, H. (Journal of Refractive Surgery, 2010)
PURPOSE: To assess the efficacy, safety, and predictability of conductive keratoplasty for the treatment of corneal trauma/incision-induced hyperopic or compound astigmatism. METHODS: Thirteen eyes with corneal trauma/incision- induced astigmatism underwent conductive keratoplasty in this prospective study. The main outcome measures included distance uncorrected visual acuity (UCVA), near UCVA, best spectacle-corrected visual acuity (BSCVA), manifest refraction cylinder, keratometric astigmatism, manifest refraction spherical equivalent (MRSE), contrast sensitivity, glare sensitivity, intraocular pressure, tear break-up time, endothelial cell count, and pachymetry. Patients were followed 1 week and 1, 3, and 6 months postoperatively. RESULTS: Mean logMAR scores for distance UCVA, near UCVA, and BSCVA significantly improved from 0.87±0.31, 1.32±0.41, and 0.18±0.18, respectively, to 0.32±0.21, 0.59±0.21, and 0.08±0.11 (P≤.05), respectively, 6 months after conductive keratoplasty. Mean manifest refraction cylinder, keratometric astigmatism, and MRSE significantly reduced from 4.12±2.86 diopters (D), 4.15±2.40 D, and 0.73±2.56 D, respectively, to 1.46±1.35 D, 1.66±1.44 D, and -0.52±0.99 D (P≤.05), respectively, at 6 months postoperatively. Contrast sensitivity and glare sensitivity showed significant improvement at spatial frequencies of 1, 1.6, 2.5, 4, and 6.3 cycles per degree (P≤.05). Surgically induced astigmatism calculated by vector analysis highly correlated to target induced astigmatism (P≤.05). No severe complications occurred postoperatively. CONCLUSIONS: This study suggests that conductive keratoplasty is an effective and safe treatment for hyperopic or compound astigmatism after corneal trauma or incision. Copyright ©SLACK Incorporated.

Endoscopy after bariatric surgery (with videos) - Obstein, K.L.; Thompson, C.C. (Gastrointestinal Endoscopy, 2009)

Migrating foreign body of the neck as a cause of recurrent febrile lymphadenopathy - Pignataro, L.; Laguardia, M.; Esposito, S.; Bosis, S.; Torretta, S.; Principi, N.; Capaccio, P. (International Journal of Pediatric Otorhinolaryngology Extra, 2009)
A 15-year-old girl was referred to our Pediatric Emergency Unit because of recurrent fever associated with a painful right laterocervical mass over the previous four months, which was unresponsive to various antimicrobial therapies. During surgery, performed to obtain a biopsy, an unexpected vegetable thin fibre, about 1.2 cm long, was found among the laterocervical lymph nodes. The patient subsequently experienced complete clinical remission and told us that about one month before the development of symptoms she had felt a punctory sensation in the floor of her mouth after she had been playing with a blade of grass between her lips. © 2009.
Keywords: Cervical lymphadenopathy; Foreign body; Migration

Transmural migration of a surgical compress into the stomach after splenectomy: A case report - Akbulut, S.; Sevinc, M.M.; Basak, F.; Aksoy, S.; Cakabay, B. (Cases Journal, 2009)
A surgical compress retained in the abdominal cavity following surgery is a serious problem. Here, we describe a 33-year-old female who was admitted with abdominal pain, vomiting, no passage of gas or feces, and abdominal distension for 3 days. She had a splenectomy at another medical center 4 years previously. An upright plain abdominal film revealed small bowel obstruction with marked small bowel air-fluid levels. The physical examination revealed muscular guarding and rebound tenderness in the periumbilical region. Therefore, a laparotomy was performed. A surgical compress was removed at enterotomy and the final diagnosis was gossypiboma. Because a retained surgical compress may lead to medicolegal problems, it is important to count the material used before and after a surgical procedure to reduce the risk of this problem. © 2009 Akbulut et al.; licensee Cases Network Ltd.

Clinical, pathological and radiological features of paraspinal textiloma: Report of two cases and review of the literature - Hakan, T.; Aydoseli, A.; Demir, K.; Aker, F. (Neurologia i Neurochirurgia Polska, 2009)
Textiloma is a term used for retained cottonoid or surgical sponge in the operation field. Although they occur mostly after thoracic or abdominal operation, they can also be encountered after surgery of extremities or the spine. There are few reports of spinal cases in which MR and CT imaging findings of textilomas have been described. In this report, two additional cases with MR, CT and pathological features of paraspinal textilomas are described. CT image demonstrated a paraspinal mass simulating a malignant tumour. While T1-weighted MR images showed the masses with low signal intensity, T2-weighted MR images showed heterogeneous masses with low and high signal intensities.
Keywords: Foreign body; Gauzoma; Gossypiboma; Textiloma

Biologic response to orthopedic sutures: A histologic study in a rabbit model - Carr, B.J.; Ochoa, L.; Rankin, D.; Owens, B.D. (Orthopedics, 2009)
Biologic reactivity to suture materials can have an effect on patient outcomes. The goal of this study was to determine the histologic response to 8 commonly used orthopedic sutures-Ethibond (Ethicon, Somerville, New Jersey), Ticron (Tyco, Waltham, Massachusetts), HiFi (Linvatec, Largo, Florida), Ultrabraid (Smith & Nephew, Memphis, Tennessee), MaxBraid (Biomet, Warsaw, Indiana), Orthocord (Mitek, Raynham, Massachusetts), MagnumWire (Opus Medical, San Juan Capistrano, California), and FiberWire (Arthrex, Naples, Florida)-using a rabbit model. The suture granuloms were evaluated at 30, 60, and 120 days with measurement of the fibrous capsule, the number of giant cells in and near the capsule, and the overall inflammatory grade: 1 (mild), 2 (moderate), and 3 (severe). MagnumWire and Ticron sutures initiated a more intense inflammatory reaction when compared to the other sutures. By 120 days, MagnumWire (P=.0297) and Ticron (P=.1855) had fewer giant cells at the soft tissue-suture interface, fewer giant cells within the capsule (P=.0074 and P=.0377, respectively), and the greatest capsular thickness of all suture types (P<.0001 and P=.1378, respectively). Differences exist between the biologic reactivity of commonly used orthopedic sutures that may be attributable to their material composition and/or braid characteristics. In comparison to other high-strength sutures, MagnumWire and Ticron stimulated a more intense foreign body inflammatory response. Copyright © 2009 SLACK Incorporated. All rights reserved.

Consultation section. Cataract surgical problem. (Journal of cataract and refractive surgery, 2009)

Silicone spaghetti - Sinnadurai, M.; Winder, M.J. (Journal of Clinical Neuroscience, 2009)
Migration of ventriculoperitoneal shunt catheters, although infrequent, is well reported. We report the unusual event of a patient who, after having had three shunt revisions over a 15-year period, presented with a per-oral extrusion of her original distal catheter. Crown Copyright © 2009.
Keywords: Migration; Shunt; Transoral; Ventriculoperitoneal

Intrapelvic pin migration - Memişoǧlu, K.; Buluç, L.; Çirpici, Y.; Şarlak, A.Y. (Anatolian Journal of Clinical Investigation, 2009)
We present two cases of pelvic pin migration after operations for Developmental Dysplasia of Hip (DDH). The wire was used for stabilization of the hips after open reduction for neglected unreduced DDH. The pins were protruding towards the bladder and they were all recognized at late follow up. This unusual migration of Kirschner wires into the pelvis has not been reported previously.

Endophthalmitis: Magnitude, treatment and visual outcome in Northwest frontier province of Pakistan - Wade, P.D.; Khan, S.S.; Khan, M.D. (Annals of African Medicine, 2009)
Background: Many cases of post-operative and posttraumatic endophthalmitis are being managed at the Khyber Institute of Ophthalmic Medical Sciences, Peshawar in Pakistan but no study has been done to ascertain the magnitude of the disease and to also evaluate the visual outcome after management. Methods: The case notes of 39 patients diagnosed with posttraumatic and postoperative endophthalmitis between May 2006 and April 2007 were analyzed and clinical characteristics obtained were documented and tabulated. Results: During the study period, 2474 patients were admitted in both the male and female wards. Of these, 39 (1.6%) had endophthalmitis due to surgical and traumatic complications. In all, 6 (12.4%) patients had evisceration, while 21 (53.8%) patients who had topical antibiotics consisting of ofloxacin, 0.1% corticosteroids, fortified cetazoline and 1% atropine along with intravitreal antibiotics, a combination of 0.1mg vancomycin and 0.4mg amikacin, were discharged home with a visual acuity of counting fingers to light perception. Conclusion: Endophthalmitis is a serious ocular complication of open globe injury and intraocular surgery. The frequency in this center has been noted to be very high as compared to other places. Its management is very challenging and often leads to devastating structural and functional damage to the eye; causing severe frustration to both the patient and the attending physician. Efforts must be made to prevent the condition.
Keywords: Endophthalmitis; Magnitude; Visual outcome

Intra-abdominal abscess caused by toothpick injury - Su, Y.-J.; Lai, Y.-C.; Chen, C.-C.; Tang, C. (International Journal of Infectious Diseases, 2009)
We present the case of a 42-year-old female who presented to our emergency department (ED) complaining of epigastric pain for four days. She had been seen in the outpatient department and ED previously for evaluation, but continued to experience epigastric pain with fever. Emergency panendoscopy was performed and a toothpick was discovered impacted in the duodenal bulb. The gastroenterologist was unable to remove the toothpick endoscopically. Computed tomography of the abdomen revealed a long and straight hyperdense foreign body, and intra-abdominal abscess formation. An emergency laparotomy was performed. The patient recovered gradually and was discharged 11 days later. She could not remember when she swallowed the wooden toothpick, but guessed that it was while out drinking. There is an old wives' tale in Taiwan that putting a toothpick in the cup while drinking beer reduces the likelihood of abdominal distention from the carbonation of the beer. © 2008 International Society for Infectious Diseases.
Keywords: Duodenal perforation; Intra-abdominal abscess; Pneumoperitoneum; Toothpick

Bouveret' syndrome: Description of a case - Zippi, M.; Di Stefano, P.; Manetti, G.; Febbraro, I.; Traversa, G.; Mazzone, A.M.; De Felici, I.; Mattei, E.; Occhigrossi, G. (Clinica Terapeutica, 2009)
Bouveret's syndrome is a rare condition usually caused by a single large stone impacted in the duodenum. This is a cause of gastric outlet. Even if endoscopy is the mainstay of diagnosis, the radiographic examinations are also important too. Generally, the stones are too large to be removed endoscopically. Conservative endoscopic treatment should be attempted initially, and if it fails, surgical approach should be performed.
Keywords: Bouveret's syndrome; Endoscopy

Visual outcome and complications after removal of posterior segment intraocular foreign bodies through pars plana approach - Memon, A.A.; Saeed Iqbal, M.; Cheema, A.; Niazi, J.H. (Journal of the College of Physicians and Surgeons Pakistan, 2009)
Objective: To assess the visual outcome and complications after removal of posterior segment retained intraocular foreign bodies through pars plana approach. Study Design: Case series. Place and Duration of Study: Department of Ophthalmology, Jinnah Postgraduate Medical Centre, Karachi, from May 2005 to May 2006. Methodology: Fifty patients with history of ocular foreign body were admitted through outpatient department and emergency. History, visual acuity, ocular and general examination was done. The foreign body was localized with the radiograph of the skull and ultrasonography. Primary repair was done in patients with open wounds. Pars plana vitrectomy, magnetic or forceps extraction of foreign body was done as required visual outcomes and complications were noted. Results: Among the 50 patients, there were 45 (90%) males and 5 (10%) females. Average age of the patients was 31.52 ±9.52 (ranging from 20 to 50) years. The pre-operatively visual acuity finger counting to perception of light was 78% cases. The best corrected final visual acuity was 6/6 in 1 (2%) patient, 6/9 in 5 (10%) patients, 6/12 in 5 (10%) patients, 6/18 in 3 (6%) patients, 6/24 and 6/36 in 4 (8%) patients each, 6/60 in 4 (8%) patients, finger counting in 8 (16%) patients, hand movement in 4 (8%) patients, projection of light in 9 (18%) patients and no projection of light in 3 (6%) patients. The postoperative complications were corneal opacity in 8 (16%) patients, anterior chamber inflammatory reaction in 6 (12%) patients, increased intraocular pressure in 1 (2%) patient, silicone oil in anterior chamber in 1 (2%) patient, macular scar in 7 (14%) patients, cystoid macular edema in 1 (2%) patient, endophthalmitis in 4 (8%) patients, retinal detachment in 11 (22%) patients and phthisis bulbi in 3 (6%) patients. Conclusion: Acceptable visual results were achieved after the removal of posterior segment intraocular foreign bodies by vitrectomy. However, multiple complications can be encountered which require meticulate postoperative care.
Keywords: Complications; Intraocular foreign body; Pars plana; Visual outcome; Vitrectomy

Retained surgical sponges after craniotomies: Imaging appearances and complications - Kim, A.K.; Lee, E.B.; Bagley, L.J.; Loevner, L.A. (American Journal of Neuroradiology, 2009)
Imaging within 24 to 48 hours after most neurosurgical procedures is a routine practice. Nonresorbable surgical sponges have radiopaque filaments readily visible on CT scans and plain film radiographs. However, the proton-poor barium sulfate responsible for this radio-opacity is generally not detectable on MR imaging in the immediate post-operative period. Findings on MR imaging become more evident with elapsing time and when a foreign-body reaction to the sponge manifests as a mass lesion, which can mimic residual or recurrent intracranial tumor or abscess. Although preventive measures by our surgical colleagues to ensure accurate and correct sponge counts before and after wound closure is paramount, even the most fastidious efforts may rarely result in an inadvertently retained surgical sponge. The role of the radiologist is to recognize the imaging findings of this entity and its potential complications so that appropriate and prompt management can be initiated.

Hazardous complications of multiple ingested magnets: Report of four cases - Kabre, R.; Chin, A.; Rowell, E.; Browne, M.; Barsness, K.A.; Luck, S.; Jona, J. (European Journal of Pediatric Surgery, 2009)
Foreign body ingestion is a common occurrence in the pediatric population. Frequent culprits include coins, toys, sharp objects and bones, which most often pass spontaneously. Magnet ingestion, however, can be a serious matter, especially when more than one is taken in. The extremely strong magnetic force between multiple magnets may result in numerous complications including bowel necrosis, perforation, obstruction, fistula formation, volvulus and death. We present the largest series reported to date, with four cases of multiple magnet ingestion at our institution with varied presentations and findings. We review the literature, and discuss the importance of having a high index of suspicion. © Georg Thieme Verlag KG Stuttgart.
Keywords: Bowel obstruction; Foreign body ingestion; Intestinal perforation; Multiple magnet ingestion; Volvulus

Prevention of retained surgical sponges: A decision-analytic model predicting relative cost-effectiveness - Regenbogen, S.E.; Greenberg, C.C.; Resch, S.C.; Kollengode, A.; Cima, R.R.; Zinner, M.J.; Gawande, A.A. (Surgery, 2009)
Background: New technologies are available to reduce or prevent retained surgical sponges (RSS), but their relative cost effectiveness are unknown. We developed an empirically calibrated decision-analytic model comparing standard counting against alternative strategies: universal or selective x-ray, bar-coded sponges (BCS), and radiofrequency-tagged (RF) sponges. Methods: Key model parameters were obtained from field observations during a randomized-controlled BCS trial (n = 298), an observational study of RSS (n = 191,168), and clinical experience with BCS (n ∼ 60,000). Because no comparable data exist for RF, we modeled its performance under 2 alternative assumptions. Only incremental sponge-tracking costs, excluding those common to all strategies, were considered. Main outcomes were RSS incidence and cost-effectiveness ratios for each strategy, from the institutional decision maker's perspective. Results: Standard counting detects 82% of RSS. Bar coding prevents ≥97.5% for an additional $95,000 per RSS averted. If RF were as effective as bar coding, it would cost $720,000 per additional RSS averted (versus standard counting). Universal and selective x-rays for high-risk operations are more costly, but less effective than BCS-$1.1 to 1.4 million per RSS event prevented. In sensitivity analyses, results were robust over the plausible range of effectiveness assumptions, but sensitive to cost. Conclusion: Using currently available data, this analysis provides a useful model for comparing the relative cost effectiveness of existing sponge-tracking strategies. Selecting the best method for an institution depends on its priorities: ease of use, cost reduction, or ensuring RSS are truly "never events." Given medical and liability costs of >$200,000 per incident, novel technologies can substantially reduce the incidence of RSS at an acceptable cost. © 2009 Mosby, Inc. All rights reserved.

Migration of a swallowed toothpick into the liver: The value of multiplanar CT - Liu, H.J.; Liang, C.H.; Huang, B.; Xie, S.F.; Wang, G.Y. (British Journal of Radiology, 2009)
Foreign body ingestion is not an uncommon problem encountered in clinical practice. However, the associated complication of bowel perforation and migration of the foreign body to the liver is rare. We report two cases of hepatic foreign bodies identified intra-operatively as toothpicks, with the alimentary tract being the presumed origin. © 2009 The British Institute of Radiology.

Lung Parasite Ova Granuloma Mimicking Lung Malignancy on FDG PET-CT - Kao, P.-F.; Tsao, T.C.-Y.; Kuo, K.-T.; Yue, C.-T.; Lim, K.-R.; Chou, Y.-H. (Clinical Nuclear Medicine, 2009)
A 60-year-old lady with mild fever, blood tinged sputum, and a left upper lung mass had whole body F-18 2-deoxy-D-glucose (FDG) positron emission tomography (PET)-computer tomography (CT) for cancer staging. The PET-CT imaging revealed FDG accumulation in the left upper lung lesion. The histopathology of the left upper lobe lung resection showed a parasite tunnel with necrosis, parasite ova, and foreign body giant cells. After surgery, eosinophiles in the peripheral blood dropped from 20% of white cell counts before operation to 5.5% at 7 weeks postoperation. © 2009 by Lippincott Williams & Wilkins.
Keywords: F-18 2-deoxy-D-glucose; Granuloma; Lung cancer; Parasite ova; Solitary pulmonary nodule

Improving safety in the operating room: A systematic literature review of retained surgical sponges - Wan, W.; Le, T.; Riskin, L.; Macario, A. (Current Opinion in Anaesthesiology, 2009)
PURPOSE OF REVIEW: Gossypibomas are surgical sponges that are unintentionally left inside a patient during a surgical procedure. To improve this patient safety indicator, anesthesiologists will need to work with operating room personnel. This study's goal was to systematically review the literature on retained sponges to identify body location, time to discovery, methods for detection, and risk factors. RECENT FINDINGS: Two hundred and fifty-four gossypiboma cases (147 reports from the period 1963-2008) were identified via the National Library of Medicine's Medline and the Cochrane Library. Gossypibomas (mean patient age 49 years, range 6-92 years) were most commonly found in the abdomen (56%), pelvis (18%), and thorax (11%). Average discovery time equaled 6.9 years (SD 10.2 years) with a median (quartiles) of 2.2 years (0.3-8.4 years). The most common detection methods were computed tomography (61%), radiography (35%), and ultrasound (34%). Pain/irritation (42%), palpable mass (27%), and fever (12%) were the leading signs and symptoms, but 6% of cases were asymptomatic. Complications included adhesion (31%), abscess (24%), and fistula (20%). Risk factors were case specific (e.g. emergency) or related to the surgical environment (e.g. poor communication). Most gossypibomas occurred when the sponge count was falsely pronounced correct at the end of surgery. SUMMARY: More is being discovered about the patterns leading to a retained sponge. Multidisciplinary approaches and new technologies may help reduce this low frequency but clinically significant event. However, given the complexity of surgical care, eliminating retained sponges may prove elusive. © 2009 Lippincott Williams & Wilkins, Inc.
Keywords: Gossypiboma; Patient safety; Retained sponge; Surgery

Matrix metalloproteinase-9 deficiency leads to prolonged foreign body response in the brain associated with increased IL-1β levels and leakage of the blood-brain barrier - Tian, W.; Kyriakides, T.R. (Matrix Biology, 2009)
Matrix metalloproteinases (MMPs) are enzymes with specificity towards extracellular matrix (ECM) components. MMPs, especially MMP-9, have been shown to degrade components of the basal lamina and disrupt the blood-brain barrier (BBB) and thus, contribute to neuroinflammation. In the present study we examined the role of MMP-9 in the foreign body response in the brain. Millipore filters of mixed cellulose ester were implanted into the brain cortex of wild type and MMP-9-null mice for a period of 2 d to 8 wks and the response was analyzed by histology and immunohistochemistry. We observed enhanced and prolonged neuroinflammation in MMP-9-null mice, evidenced by persistence of neutrophils, macrophages/microglia, and reactive astrocytes up to 8 wks post-implantation. In addition, blood vessel density around implants was increased in MMP-9-null mice and detection of mouse serum albumin (MSA) indicated that vessels were leaky. Immunohistochemical and western blot analyses indicated that this defect was associated with the absence of tight junction proteins zonula occludens-1 (ZO-1) and ZO-2 from vessels in proximity to implants. Analysis of brain sections and brain protein extracts revealed that the levels of the pro-inflammatory cytokine interleukin-1β (IL-1β), which is a substrate for MMP-9, were significantly higher in MMP-9-null mice at 8wks post-implantation. Collectively, our studies suggest that increased levels of IL-1β and the delayed repair of BBB are associated with prolongation of the FBR in MMP-9-null mice. © 2009 Elsevier B.V. All rights reserved.
Keywords: Biomaterials; Blood-brain barrier; Foreign body response; Interleukin; Matrix metalloproteinase; Neuroinflammation

Histological Inflammatory Response to Transvaginal Polypropylene Mesh for Pelvic Reconstructive Surgery - Elmer, C.; Blomgren, B.; Falconer, C.; Zhang, A.; Altman, D. (Journal of Urology, 2009)
Purpose: We prospectively evaluated the histological inflammatory response to the large polypropylene transvaginal mesh used for pelvic organ prolapse surgery. Materials and Methods: Ten patients and 8 controls underwent vaginal punch biopsy sampling before surgery and patients also underwent it 1 year after pelvic reconstructive surgery using polypropylene mesh. Foreign body response to the mesh was assessed using a combination of histological, semiquantitative and computerized image based analysis. Results: Compared to preoperative histology there was a significant postoperative increase in macrophage and mast cell counts (p = 0.03 and 0.01) but no significant changes in the count of cells involved primarily in the infectious cell response or collagen density and the elastin area fraction at the mesh-tissue interface (p = 0.2 and 0.3, respectively). Three cases of mild granuloma formation and 2 of mild erosion were observed. There was no significant change in epithelial thickness when comparing preoperative and postoperative samples. Conclusions: When used for pelvic reconstructive surgery, macroporous monofilament polypropylene mesh induces a mild but persistent foreign body reaction. © 2009 American Urological Association.
Keywords: foreign-body reaction; polypropylenes; prolapse; suburethral slings; urethra

Saved By the Video: Added Value of Recording Surgical Procedures on Video - Hoschtitzky, J.A.; Trivedi, D.B.; Elliott, M.J. (Annals of Thoracic Surgery, 2009)
Intraoperative imaging has immense value for teaching and training surgeons by providing part of a future digital medical record of the patient and supportive evidence of good practice and an open attitude to patient safety. We report a case in which intraoperative video recording of an operation allowed us, after an incorrect count, to confidently assert that there was no equipment left behind in the patient. © 2009 The Society of Thoracic Surgeons.

So who's counting? - Avery, J.K. (Tennessee medicine : journal of the Tennessee Medical Association, 2009)

Synergistic effect of a novel focal hyperthermia on the efficacy of rifampin in staphylococcal experimental foreign-body infection - Zou, G.-Y.; Shen, H.; Jiang, Y.; Zhang, X.-L. (Journal of International Medical Research, 2009)
This study was designed to evaluate the efficacy of focal hyperthermia and rifampin in vitro and in vivo using a rabbit model of foreign-body infection by methicillin-resistant Staphylococcus aureus (MRSA). In vitro studies demonstrated bacterial re-growth and development of rifampin resistance after 24 h with rifampin alone, which was prevented under hyperthermic conditions. For the in vivo studies, rifampin was administered intraperitoneally every 12 h for 7 days to rabbits with MRSA-containing cages implanted into their flanks. When combined with hyperthermia at 39°C, 41°C and 43°C, rifampin significantly reduced in-cage bacterial counts by > 3.0 log10 colony forming units/ml compared with rifampin alone. Eradication of cage-associated infection was achieved more effectively when rifampin was combined with hyperthermia, with cure rates of 70-95% on day 10. Focal hyperthermia combined with rifampin prevented the emergence of rifampin resistance and maintained rifampin efficacy. These findings might have implications for orthopaedic surgery. Copyright © 2009 Field House Publishing LLP.
Keywords: Antibiotics; Focal hyperthermia; Foreign-body infection; Methycillin-resistant staphylococcus aureus; Rifampin

Dental impression material: A rare cause of small-bowel obstruction - Dent, L.; Peterson, A.; Pruett, D.; Beech, D. (Journal of the National Medical Association, 2009)
Small-bowel obstruction due to foreign bodies is unusual in adults. Intestinal obstruction is occasionally caused by pits, bezoars, endoscopy capsules, and gastrostomy tube buttons. We report a rare case of distal small-bowel obstruction due to dental impression material. Avoidance of this potentially life-threatening complication may be achieved by increased vigilance in accounting for all impression material when dental impression trays are removed. Early detection of swallowed dental material may afford endoscopic removal from the stomach, thus preventing intestinal obstruction.
Keywords: Intestines; Obstruction

Transconjunctival 20-gauge vitrectomy: A pilot study - Aguni, J.S.; Meyer, C.H.; Rodrigues, E.B. (Ophthalmologica, 2009)
Purpose: To determine the efficacy of a novel technique for a 'transconjunctival 20-gauge vitrectomy' (T20V). Methods: In total, 12 eyes of 12 consecutive patients were included in a prospective study. The mean age was 58 years (range: 38-74 years); 4 patients were male and 8 were female. The T20V was indicated when short-duration vitrectomy was envisioned: macular surgery for macular hole and epiretinal membrane therapy, moderate vitreous hemorrhage due to retina vein occlusions or diabetic retinopathy, or neurotomy for central retinal vein occlusion. Results: The average time for each procedure was 35 ± 30 min (SD). The preoperative visual acuity ranged from 20/200 to hand motions, while postoperative vision was between 20/30 and counting fingers. The average intraocular pressure changed from 16.1 ± 5.6 mm Hg preoperatively to 15.8 ± 8.1 mm Hg in the first postoperative day, and 17.8 ± 9.4 mm Hg 1 week after surgery - these differences were not statistically significant (p > 0.05). Subjective postoperative pain and foreign body sensation at postoperative day 1 and week 1 were mild to moderate. The chemosis observed 1 h after surgery was minimal, and disappeared quickly during the 1-week follow-up. Conclusion: The T20V is suitable to perform short-duration vitrectomy surgery, and has a low rate of ocular complications, similar to 25- or 23-gauge sutureless vitrectomy systems. Copyright © 2008 S. Karger AG.
Keywords: Macular hole; Retina; Vitrectomy

Safe surgery: reducing the risk of retained items. - Woodhead, K. (Journal of perioperative practice, 2009)
Research from the United States which explores events related to the surgical count has identified that there are opportunities to review our practice in order to reduce risks to surgical patients. The Safe Surgery Saves Lives Campaign highlights this aspect of perioperative patient safety, ensuring that poor processes and poor communication, often the reasons for retained surgical items, become part of the team 'sign-out' at the end of every operation.

Quality and intensity of the tissue response to two synthetic granular hydroxyapatite implanted in critical defects of rat calvaria - de Freitas Costa, N.; Melo, B.R.; Brito, R.T.; de Oliveira Fernandes, M.B.; Bernardo, V.G.; Fonseca, E.C.; Conz, M.B.; Soares, G.A.; Granjeiro, J.M. (Materials Research, 2009)
The objective of the present study was to evaluate the quality and intensity of the tissue response to two synthetic hydroxyapatites implanted in critical defects in the skulls of rats. Sixty animals were divided into three experimental groups: I (control), II (HA-1 = HA with 28% crystallinity) and III (HA-2 = HA with 70% crystallinity). They were sacrificed 1, 3, 6, and 9 months after implantation (n = 5 individuals per group/period). Histomorphometric analysis included i) counting of polymorphonuclear leucocytes, mast cells, macrophages and foreign body multinucleated giant cells stained with anti-lysozyme; ii) microvascular density stained with anti-Factor VIII and iii) degree of cell proliferation stained with anti-PCNA. There were no significant differences between the experimental groups in either the quality or quantity of cells in the inflammatory infiltrate, or the degree of angiogenesis and cell proliferation. We conclude that HA-1 and HA-2 are biocompatible and that the physico-chemical differences of these biomaterials did not affect cellular response.
Keywords: Bone repair; Histomorphometry; Hydroxyapatite; Immunohistochemistry

Difluprednate ophthalmic emulsion 0.05% for postoperative inflammation and pain - Korenfeld, M.S.; Silverstein, S.M.; Cooke, D.L.; Vogel, R.; Crockett, R.S. (Journal of Cataract and Refractive Surgery, 2009)
Purpose: To assess the efficacy and safety of difluprednate ophthalmic emulsion 0.05% (Durezol) 2 or 4 times a day compared with those of a placebo in the treatment of inflammation and pain associated with ocular surgery. Setting: Twenty-six clinics in the United States. Methods: One day after unilateral ocular surgery, patients who had an anterior chamber cell grade of 2 or higher (>10 cells) were treated with 1 drop of difluprednate 2 times or 4 times a day or with a placebo (vehicle) 2 times or 4 times a day in the study eye for 14 days. This was followed by a 14-day tapering period and a 7-day safety evaluation. Outcome measures included cleared anterior chamber inflammation (grade 0, ≤1 cell), absence of pain, and analysis of ocular adverse events. Results: Of the 438 patients, 111 received difluprednate 2 times a day, 107 received difluprednate 4 times a day, and 220 received a placebo 2 or 4 times a day. Both difluprednate dosage regimens reduced postoperative ocular inflammation and pain safely and effectively compared with the placebo. A greater proportion of difluprednate-treated patients had a reduction in inflammation and pain at 8 days and 15 days. Three percent of patients in both difluprednate groups had a clinically significant IOP rise (≥10 mm Hg and ≥21 mm Hg from baseline, respectively) versus 1% in the placebo group. Conclusions: Difluprednate given 2 or 4 times a day cleared postoperative inflammation and reduced pain rapidly and effectively. There were no serious ocular adverse events. Fewer adverse events were reported in the difluprednate-treated groups than in the placebo group. © 2009 ASCRS and ESCRS.

To Count or Not to Count: A Surgical Misadventure - King, C.A. (Perioperative Nursing Clinics, 2008)
An instrument or other surgical item left in the patient is a rare and yet devastating and preventable complication of surgery. Estimates based on claims data suggest the incidence of a retained foreign body to be between 1 in 9000 and 1 in 19,000 operations. The current approach in prevention has been to use the Association of periOperative Registered Nurses' manual counting method. While working at a large academic medical center, a sentinel event occurred where a patient left the operating room with a retained malleable retractor. This article will present the social, cultural, and systems issues that predisposed to that event, the lessons learned, and a summary of evidence concerning these incidents. © 2008 Elsevier Inc. All rights reserved.
Keywords: Counts; Recommended practices; Retained foreign body; Surgery

Removal from the small intestine of a long foreign body (17 cm long pencil) that was introduced per anum - Al-enezi, M.; Fouad, S.; Abul, E. (Kuwait Medical Journal, 2008)
We report a case of a 14-year-old male with a 17 cm long foreign body in his small bowel. The clinical presentation was non-specific and the diagnosis was made only at laparoscopy. This case study emphasizes the possibility of a linear foreign body in the small bowel which has migrated from the large bowel. This type of migration of the foreign body has not been previously reported.
Keywords: Foreign body; Migration; Small bowel

Gossypiboma: A case report and review of the literature - Kiernan, F.; Joyce, M.; Byrnes, C.K.; O'Grady, H.; Keane, F.B.V.; Neary, P. (Irish Journal of Medical Science, 2008)
Introduction: Post-operative complications in surgery may frequently be unavoidable. However, some complications result from human error, both in the intra-operative and post-operative period. One such complication, which is frequently underreported, is the retained swab, or gossypiboma. Case report We report a case from our hospital of a patient who presented with unexplained pyrexia, 4 years post-gynaecological surgery in another institution. A 67- year-old woman from overseas presented to our emergency department with a 2-day-history of pyrexia, collapse and confusion. Following a CT guided biopsy, which was inconclusive, she was scheduled for retroperitoneal biopsy. In theatre, a retained swab was discovered. Conclusion: Prevention of gossypiboma is far better than cure. Strict adherence to swab counts, and the avoidance of change of staff during procedures is important in decreasing the incidence. Perhaps, with the increasing use of minimally invasive procedures, the incidence of gossypiboma will fall dramatically. © Royal Academy of Medicine in Ireland 2007.

Do asymptomatic foreign bodies in the maxillary sinus always need to be removed? - Selvi, F.; Enoz, M.; Yazgin, I.; Cakarer, S.; Keskin, C. (B-ENT, 2008)
Do asymptomatic foreign bodies in the maxillary sinus always need to be removed? Foreign bodies may be displaced into the maxillary sinus as a result of trauma or during dental interventions. They commonly cause chrome sinusitis and/or fungal infections. This paper presents the case of a foreign body lodged in the right maxillary sinus ostium of a 31-year-old female patient. The foreign body was observed incidentally during radiological examination. After careful clinical and radiological examination, it was concluded that the foreign body was a piece of amalgam displaced into the maxillary sinus during a traumatic extraction. It is an uncommon finding to observe an asymptomatic dental foreign body in a position so close to the natural ostium of the maxillary sinus for so many years without any oro-antral fistula formation and/or sinusitis attacks. We describe the non-surgical approach to the case and the need for surgical management will be questioned. The importance of consultation between otolaryngologists and oral and maxillofacial surgeons will also be emphasised.
Keywords: Amalgam; Chronic iatrogenic sinusitis; Computed tomography; Foreign body; Maxillary sinus

Displacement of the Amplatzer occluder device from the mitral paraprosthetic leak - Yuan, S.-M.; Shinfeld, A.; Raanani, E. (Interactive Cardiovascular and Thoracic Surgery, 2008)
A critically ill patient had a major mitral paravalvular leak, failed device closure of the leak, and severe hemolytic anemia after a third mitral valve replacement. Echocardiography showed the Amplatzer occluder device completely displaced and swirled in the left atrial cavity. His condition was greatly improved after a fourth mitral valve replacement. © 2008 Published by European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: Amplatzer occluder device; Complication; Hemolytic anemia; Mitral valve replacement; Paravalvular leak

Radio-opaque marker of a surgical sponge appearing as an intra-articular foreign body after total hip arthroplasty - Takigami, I.; Itoh, Y.; Itokazu, M.; Shimizu, K. (Archives of Orthopaedic and Trauma Surgery, 2008)
We report a 73-year-old female patient who underwent total hip arthroplasty for osteoarthritis of the right hip. An anteroposterior radiograph obtained 1 week after surgery showed an intra-articular striated foreign body. This was subsequently removed and found to be a radio-opaque marker of a surgical sponge that had been used during the operation. The patient made an uneventful recovery. In recent years, cases of retained surgical sponge after surgery have been reported occasionally. Counting surgical sponges and using sponges with radio-opaque markers are methods for preventing them from being accidentally left in situ. However, to our knowledge, there has been no report of retention of a surgical sponge radio-opaque marker at the operation site, appearing as a foreign body on an X-ray film. © Springer-Verlag 2007.
Keywords: Foreign body; Intra-articular foreign body; Radio-opaque marker; Retained surgical sponge; Total hip arthroplasty

Ileal perforation caused by swallowed foreign body, case presentation and review of literature - Albsoul, M.N.; Al-Ardah, M. (Journal of the Bahrain Medical Society, 2008)
This is a case report of a 67 year old female patient who incidentally ingested a chicken bone, and presented to the emergency room with acute abdomen that required exploratory laparotomy later on.

Posttraumatic cellulitis and ulcerative conjunctivitis caused by Yersinia enterocolitica O:8 - Mills, D.M.; Meyer, D.R. (Ophthalmic Plastic and Reconstructive Surgery, 2008)
A 55-year-old white man presented with orbital cellulitis and suspicion of an intraorbital foreign body after ocular trauma. He underwent orbital exploration, but no intraorbital foreign bodies were identified. Intraoperative orbital and conjunctival cultures grew Yersinia enterocolitica O:8. The patient's signs and symptoms resolved with intravenous antibiotic treatment after this exploratory orbitotomy. This is the first case, to our knowledge, of human orbital cellulitis caused by Y. enterocolitica O:8. The single visible interpalpebral conjunctival ulceration was suspected to be an entry wound by the patient's primary physician, the emergency room physician, and the orbital surgeon prior to surgical investigation, at which time all the other ulcerations were identified. Therefore, the physical manifestations of this rare but important infection are presented because they may mislead clinicians in suspecting an intraorbital foreign body. ©2008 The American Society of Opthalmic Plastic and Reconstructive Surgery, Inc.

Exogenous bovine thrombin as a biomarker of exposure and outcome - Crean, S.M.; Michels, S.L.; Reynolds, M.W. (Expert Review of Molecular Diagnostics, 2008)
Bovine thrombin has been used for more than 60 years as a surgical hemostat and sealant. Rare postsurgical events have been attributed to antibovine thrombin immunoglobulins cross-reacting with human homologs. In a literature review of 37 papers reporting safety outcomes in surgical patients, we extracted each paper for a quantitative measurement of bovine thrombin exposure and coagulopathic outcomes. We found that 59.5% of papers documented the commercial source of bovine thrombin and only 19% provided an estimate of exposure in units. Conventional tests for hypocoagulation were common (86%); however, only 9% of papers confirmed this inhibition as an isolated antibody. In addition, only 9% of papers cited a specific biomarker for thrombosis. © 2008 Expert Reviews Ltd.
Keywords: Adverse event; Formulation; Hemostasis; Hemostat; Iatrogenic immunization; Surgery; Thrombin

The effect of a hyaluronan-carboxymethylcellulose membrane vs. polyglactin 910 mesh on intra-abdominal tumor formation in mice - Lee, P.K.; Windsperger, A.P.; Wilson, C.M.; McCarthy, J.B.; Wasiluk, K.R.; Rothenberger, D.A.; Bullard Dunn, K.M. (Diseases of the Colon and Rectum, 2008)
PURPOSE: Hyaluronan mediates growth of SW620 colon cancer cells. Because hyaluronan is the active ingredient in Seprafilm®, we hypothesized that Seprafilm® would affect intraperitoneal tumor growth in a mouse model of peritoneal seeding. METHODS: Immunodeficient mice underwent laparotomy and intraperitoneal inoculation of 105 SW620 cells. Seprafilm® (n = 22), Vicryl mesh (foreign body control; n = 24), or no material (sham; n = 19) was placed under the incision. Mice were killed after four weeks and tumors were dissected, counted, and weighed. RESULTS: Ninety-five percent of mice in the sham group and 96 percent in the Vicryl group developed intraperitoneal tumors. In contrast, only 64 percent of mice in the Seprafilm® group developed tumors (P = 0.024), and these tumors were smaller than those in the sham group; (Seprafilm® = 42 ± 9 mg vs. sham = 82 ± 17 mg; P = 0.05). In contrast, tumors in the Vicryl group were dramatically larger (349 ± 49 mg; P < 0.001 vs. sham or Seprafilm®). CONCLUSIONS: Despite previous data that suggested that hyaluronan increases colon cancer cell growth, we found that Seprafilm® decreased tumor formation and tended to decrease size in this model. In contrast, Vicryl mesh increased tumor formation and size. Our results suggest that Seprafilm® does not promote intraperitoneal tumor growth, especially compared with Vicryl mesh. © 2008 The American Society of Colon and Rectal Surgeons.
Keywords: Colon cancer; Hyaluronan; Polyglactin; Seprafilm®; Vicryl

Surface chemistry influences implant-mediated host tissue responses - Kamath, S.; Bhattacharyya, D.; Padukudru, C.; Timmons, R.B.; Tang, L. (Journal of Biomedical Materials Research - Part A, 2008)
Implant-mediated fibrotic reactions are detrimental to the performance of encapsulated cells, implanted drug release devices, and sensors. To improve the implant function and longevity, recent research has emphasized the need for inducing alterations in cellular responses. Although material surface functional groups have been shown to be potent in affecting cellular activity in vitro and short-term in vivo responses, these groups appear to have little influence on long-term in vivo fibrotic reactions, possibly as a result of insufficient interactions between recruited host cells and functional groups on the implants. To maximize the influence of functionality on cells, and to mimic drug release microspheres, functionalized micronsized particles were created and tested for their ability in modulating tissue responses to biomaterial implants. In this work, the surfaces of polypropylene particles were controllably coated with four different functional groups, specifically -OH, -NH2, -CF x, and -COOH, using a radio frequency glow discharge plasma polymerization technique. The effect of these surface functionalities on host tissue responses were then evaluated using a mice subcutaneous implantation model. Major differences were observed in contrasting tissue response to the different chemistries. Surfaces with -OH and -NH2 surface groups induced the thickest fibrous capsule accompanied with the greatest cellular infiltration into the implants. In contrast, surfaces with -CFx and -COOH exhibited the least inflammatory/fibrotic responses and cellular infiltrations. The present results clearly demonstrate that, by increasing the available functionalized surface area and spatial distribution, the effect of surface chemistry on tissue reactivity can be substantially enhanced. © 2007 Wiley Periodicals, Inc.
Keywords: Fibrosis; Inflammation; Microsphere; Plasma polymerization; Surface modification

The frequency and significance of discrepancies in the surgical count - Greenberg, C.C.; Regenbogen, S.E.; Lipsitz, S.R.; Diaz-Flores, R.; Gawande, A.A. (Annals of Surgery, 2008)
OBJECTIVE:: To prospectively evaluate and accurately describe the rate and type of discrepancies encountered in the surgical count. INTRODUCTION:: Despite near-universal implementation of manual counting protocols for surgical instruments and sponges, incidents of retained sponges and instruments (RSI) persist. Retrospective analyses have shown that RSI are rare and most often involve final counts erroneously thought to be correct, leading some surgeons to question the value of counting. Crucial data regarding how often the surgical count successfully detects meaningful problems before the patient leaves the operating room is lacking. METHODS:: Trained physician-observers documented prospective field observations during 148 elective general surgery operations using standardized intake forms. Data collection focused on the performance of the counting protocols, and the frequency and outcomes of discrepancies (instances in which a subsequent count does not agree with the previous count). RESULTS:: A mean of 16.6 counting episodes occurred per case, occupying 8.6 minutes per case. A total of 29 discrepancies involving sponges (45%), instruments (34%) or needles (21%) were observed among 19 (12.8%) operations. Most discrepancies indicated a misplaced item (59%) as opposed to a miscount (3%) or error in documentation (38%). Each discrepancy took on average 13 minutes to resolve. Counting activities after personnel changes were significantly more likely to involve a discrepancy than those for which the original team was present. CONCLUSIONS:: One in 8 surgical cases involves an intraoperative discrepancy in the count. The majority of these discrepancies detect unaccounted-for sponges and instruments, which represent potential RSI. Thus, despite the recognized limitations of manual surgical counts, discrepancies should always prompt a thorough search and reconciliation process and never be ignored. © 2008 by Lippincott Williams & Wilkins.

Cost-effectiveness of routine radiographs after emergent open cavity operations - Dossett, L.A.; Dittus, R.S.; Speroff, T.; May, A.K.; Cotton, B.A. (Surgery, 2008)
Background: Emergency surgery increases the risk of a retained surgical sponge (RSS) by 9-fold. In most cases, surgical counts are falsely reported as correct. We hypothesized that the institutional costs resulting from a RSS would make routine intraoperative radiography (IOR) more cost-effective than surgical counts in preventing RSS after emergent open cavity cases. Methods: A cost-effectiveness analysis was performed to compare routine IOR with surgical counts after emergent open cavity operations. Parameter estimates were obtained from the literature, expert opinion via a standardized survey, and existing institutional data. Results: Routine IOR was the preferred strategy ($705 vs $1155 per patient) under the assumptions of the base case. The surgical count strategy was dominated by the institutional costs incurred after a RSS. Routine IOR was preferential as long as the sensitivity of surgical counts was less than 98% and the legal fees were more than $44,000 per case of RSS. Conclusions: Routine IOR is a simple, cost-effective option to reduce the occurrence of this preventable medical error. Institutional costs and legal fees associated with RSS dominate the cost of the surgical count strategy, making routine IOR a more cost-effective strategy than surgical counts given the best available parameter estimates. © 2008 Mosby, Inc. All rights reserved.

Giant cell reaction with phagocytosis adjacent to dextranomer-hyaluronic acid (Deflux) implant: Possible reason for Deflux failure - Broderick, K.; Thompson, J.H.; Khan, A.R.; Greenfield, S.P. (Journal of Pediatric Urology, 2008)

Perforation of the esophagus by a fish bone leading to an infected pseudoaneurysm of the thoracic aorta - Kunishige, H.; Myojin, K.; Ishibashi, Y.; Ishii, K.; Kawasaki, M.; Oka, J. (General Thoracic and Cardiovascular Surgery, 2008)
A 79-year-old woman was urgently referred to a district hospital with dull central chest pain after swallowing a fish bone. The bone was removed by esophagoscopy. Eleven days later she presented because of hematemesis. Computed tomography and aortic arch angiography confirmed a diagnosis of esophageal perforation leading to mediastinitis and the presence of an infected pseudoaneurysm. The infected pseudoaneurysm was completely resected, followed by direct aorto-aorta anastomosis and omental coverage in a one-stage operation. She improved and was discharged 2 months later. © 2008 The Japanese Association for Thoracic Surgery.
Keywords: Esophageal perforation; Fish bone; Infected pseudoaneurysm; Omental coverage

Incidence and Characteristics of Potential and Actual Retained Foreign Object Events in Surgical Patients - Cima, R.R.; Kollengode, A.; Garnatz, J.; Storsveen, A.; Weisbrod, C.; Deschamps, C. (Journal of the American College of Surgeons, 2008)
Background: Incidence of retained foreign objects (RFOs) after operations is unknown, as many can go unrecognized for years. We reviewed the incidence and characteristics of surgical RFO events at a tertiary care institution during 4 years. Study Design: All RFO events, near misses and actual, reported on an adverse event line during 2003 to 2006 were reviewed. Results: During 2003 to 2006, there were 191,168 operations performed, with 68 reported events resulting in a potential RFO defect rate of 0.356/1,000 patients. After review, 34 patients had no RFOs (near misses) and 34 were actual RFOs, resulting in a true RFO defect rate of 0.178/1,000 operations or approximately 1:5,500 operations. In the near-miss patient, needles were miscounted 76% of the time. In the 34 actual RFO patients, items retained were 23 sponges (68%), 7 miscellaneous other items (20%), 3 needles (9%), and 1 instrument (3%). The 34 actual RFOs occurred in incidents where the count had been reported as correct in 21 patients (62%). In 18 patients where an RFO was eventually discovered, intraoperative imaging detected only 12 objects (67%). In operations involving a body cavity, our practice is to obtain a high-resolution x-ray survey film, in a dedicated x-ray suite, before entering the recovery room. Twenty RFOs were identified from survey films and all occurred in patients with correct counts. No RFOs occurred during emergency or high blood-loss procedures and none resulted in demonstrable clinical harm. Two patients left the hospital with an RFO. Twenty-two patients (64.8%) underwent reoperation, with 1 object not removed, 6 (17.6%) retrieved without operation, and 6 (17.6%) where the clinical decision was not to remove. Conclusions: RFOs at an institution that routinely performs postprocedure x-rays indicate that RFOs can occur more frequently than expected from the literature. The majority occur in patients with correct counts. Relying on counting as the primary mechanism to avoid RFOs is unreliable, and investigating new technologies designed to achieve reliable counts is warranted. © 2008 American College of Surgeons.

Radio-frequency surgical sponge detection: a new way to lower the odds of leaving sponges (and similar items) in patients. (Health devices, 2008)
Radio-frequency (RF) tags are now being embedded in items such as surgical sponges, towels, and pads to reduce the chances that these objects will be left in patients after a procedure. Find out how--and how well--RF sponge-detection systems work, including our view of the two systems currently on the market: ClearCount Medical's SmartSponge System, which counts sponges in addition to detecting them. RF Surgical's RF Surgical Detection System, which is a detect-only system.

Conjunctival cytologic features in anophthalmic patients wearing an ocular prosthesis - Kim, J.H.; Lee, M.J.; Choung, H.-K.; Kim, N.J.; Hwang, S.-W.; Sung, M.S.; Khwarg, S.I. (Ophthalmic Plastic and Reconstructive Surgery, 2008)
PURPOSE: To evaluate the cytologic features of conjunctival epithelium in anophthalmic sockets with an ocular prosthesis, using an impression cytology technique and to determine the clinical factors associated with these changes. METHODS: In a prospective case-controlled study, 40 consecutive unilateral anophthalmic patients who wore an ocular prosthesis were recruited. A questionnaire on the care of the prosthesis included total wearing period, frequency of cleaning, frequency of polishing, cleaning solution, and eye drop use. The degree of inflammation of the anophthalmic conjunctival socket was evaluated. Impression cytology specimens were taken from the upper tarsal conjunctiva, the bulbar conjunctiva, and the lower tarsal conjunctiva of each socket, and from the contralateral eye (to serve as an internal matched control). The goblet cell density and the nucleus-to-cytoplasm ratio of the epithelial cells were measured. The relevance of these conjunctival cytologic features to the various factors of prosthesis care or conjunctival inflammation was analyzed. RESULTS: In the anophthalmic sockets, the conjunctiva showed squamous metaplasia at all 3 areas sampled. The goblet cell density was significantly decreased and the nucleus-to-cytoplasm ratio of the epithelial cells was significantly increased compared with the control eyes (p < 0.05, on all 3 areas sampled, Wilcoxon signed rank test). These conjunctival cytologic changes were not significantly associated with total wearing time, frequency of polishing, cleaning solution, or eye drops use (p > 0.05, Spearman's correlation test). CONCLUSIONS: Squamous metaplasia with decreased goblet cell density and increased nucleus-to-cytoplasm ratio occurred in anophthalmic conjunctival sockets but was not associated with particular aspects of prosthesis care. © 2008 The American Society of Opthalmic Plastic and Reconstructive Surgery, Inc.

Biocompatibility of an x-shaped zirconium implant in deep sclerectomy in rabbits - Basso, A.; Roy, S.; Mermoud, A. (Graefe's Archive for Clinical and Experimental Ophthalmology, 2008)
Background: The aim of this study was to evaluate the mid-term biocompatibility of a new x-shaped implant made of zirconium in an animal model of glaucoma surgery. Methods: Preoperatively, ultrasound biomicroscopy (UBM), intraocular pressure (IOP) and outflow facility (OF) data were acquired. Upon surgery, one eye was chosen randomly to receive an implant, while the other received none. Ten rabbits went through a 1-, 2-, 3-, 4- and 6-month follow-up. IOP was measured regularly, UBM performed at 1, 3 and 6 months after surgery. At the end of the follow-up, OF was again measured. Histology sections were analyzed. Results: For both groups IOP control was satisfactory, while OF initially increased at month 1 to resume preoperative values thereafter. Eyes with implants had larger filtration blebs which decreased faster than in eyes without the implant. Drainage vessel density, inflammatory cell number and fibrosis were higher in tissues near the implant. Conclusions: The zirconium implant initially promoted the positive effects of the surgery (IOP control, OF increase). Nevertheless, after several months, foreign body reactions and fibrosis had occurred on some implants that restrained the early benefit of such a procedure. Modifications of the zirconium implant geometry could enhance the overall success rate. © Springer-Verlag 2008.
Keywords: Aqueous humour; Drainage device; Filtering surgery; Glaucoma; Tonometry; Ultrasonography

Effect of mitomycin C in pterygium surgery on corneal endothelium - Avisar, R.; Avisar, I.; Bahar, I.; Weinberger, D. (Cornea, 2008)
PURPOSE: To evaluate changes in endothelial cell count after pterygium surgery with 5-minute application of mitomycin C (MMC) 0.02%. METHODS: The study participants included 24 consecutive patients (17 men and 7 women) who underwent pterygium surgery with MMC at a major tertiary center between September and October 2005. The bare sclera technique was used in all cases. After excision of the head and neck of the pterygium, a surgical sponge soaked with MMC 0.02% was placed on the exposed sclera for 5 minutes, with the conjunctival layer draped over the sponge. Thereafter, the sclera was irrigated with balanced salt solution, and surgery was completed. Endothelial images were acquired at the center of the cornea with a specular microscope (average of 3 measurements) before surgery and at 1 week, 1 month, and 3 months after surgery. RESULTS: Mean preoperative endothelial cell count was 2254 ± 128 cells/mm. The percentage of postoperative cell loss was 21.25% ± 2.8% at 1 week, 24.26% ± 1.8% at 1 month, and 21.05% ± 3.2% at 3 months. The difference in cell count from the preoperative value was significant at all time points (P < 0.02). There were no adverse drug effects and no serious operative complications. CONCLUSIONS: A 5-minute application of MMC 0.02% to the bare sclera during pterygium surgery has an immediate and significant effect on endothelial cell density, which remains stable for up to 90 days. Furthermore, longer-term studies are needed of different concentrations and durations of the drug and of procedures wherein MMC is applied before excision of the pterygium head. © 2008 by Lippincott Williams & Wilkins.
Keywords: Corneal endothelium; Mitomycin C; Pterygium

Idiopathic intermediate uveitis in childhood - Arellanes-GarcÍa, L.; Navarro-López, P.; Río, L.E.C.-D.; Unzueta-Medina, J.A. (International Ophthalmology Clinics, 2008)

Sutureless nerve repair with laser-activated chitosan adhesive: A pilot in vivo study - Lauto, A.; Foster, L.J.; Avolio, A.; Sampson, D.; Raston, C.; Sarris, M.; McKenzie, G.; Stoodley, M. (Photomedicine and Laser Surgery, 2008)
Objective: The anastomosis of peripheral nerves is a demanding procedure that has potential complications due to foreign body reactions elicited by sutures. In this study, the sutureless in vivo anastomosis of rat tibial nerves was successfully performed, using for the first time a chitosan-based laser-activated adhesive. The nerve thermal damage caused by the laser irradiation was quantitatively assessed. Materials and Methods: A novel adhesive composed of chitosan, indocyanine green, acetic acid, and water, was fabricated in thin sheets. Its adhesive strength was tested in vitro by bonding strips (surface area ∼20 mm2, thickness ∼20 μm) onto rat sciatic nerves and sheep intestine by laser activation with low fluence (∼50 J/cm2), using a fiber-coupled diode laser (n = 13). The tensile strength of the adhesive/tissue bonds was measured after tissue repair. The chitosan adhesive was then used to perform sutureless anastomosis of tibial nerves in vivo (n = 6). Adhesive strips were also bonded in vivo onto intact rat sciatic nerves (n = 6) in order to quantitatively assess, by counting myelinated axons, the thermal damage induced by the laser. Results: The adhesive bonded well to tissue with a tensile strength of 12.5 ± 2.6 KPa (mean ± SD; n = 13). The in vivo anastomosed nerves were in continuity 3 d after surgery. Axon counting showed the number and morphology of myelinated axons were normal proximally (∼96%) compared with intact nerves (100%). Axon demyelination was observed at the operation site (∼49%) and distally (∼27%), and was attributed to laser-induced thermal damage. Conclusions: Nerve anastomosis, performed by the laser-adhesive procedure, was successful 3 d postoperatively. Proximal myelinated axons were not significantly damaged by the low laser fluence. © 2008 Mary Ann Liebert, Inc.

A rare cause of partial intestinal obstruction in a child: Colonic lithobezoar - Numanoǧlu, K.V.; Tatli, D. (Emergency Medicine Journal, 2008)
The accumulation of undigested foreign bodies or nutrients in the gastrointestinal tract forming a conglomeration is called a bezoar. Bezoars are referred to according to the foreign bodies that constitute their core: phytobezoar (fibres or seeds of vegetables and fruits); trichobezoar (hair); lactobezoar (remnants of milk) and lithobezoar (rock or similar substances). Although they can be found in any part of the gastrointestinal system, the stomach is the most common site. Primary colonic bezoar is an exceptionally rare situation. Up until 2007, only four colonic lithobezoars had been reported in the literature. This report aims to present the clinical and surgical features of a 4-year-old male patient with a previous history of pica and iron deficiency anaemia, who underwent pebble extraction from the colon after being diagnosed with partial intestinal obstruction.

Bar-coding surgical sponges to improve safety: A randomized controlled trial - Greenberg, C.C.; Diaz-Flores, R.; Lipsitz, S.R.; Regenbogen, S.E.; Mulholland, L.; Mearn, F.; Rao, S.; Toidze, T.; Gawande, A.A. (Annals of Surgery, 2008)
OBJECTIVE: A randomized, controlled trial was performed to evaluate a computer-assisted method for counting sponges using a bar-code system. BACKGROUND: Retained sponges are a rare and preventable problem but persist in surgery despite standardized protocols for counting. Technology that improves detection of counting errors could reduce risk to surgical patients. METHODS: We performed a randomized controlled trial comparing a bar-coded sponge system with a traditional counting protocol in 300 general surgery operations. Observers monitored sponge and instrument counts and recorded all incidents of miscounted or misplaced sponges. Surgeons and operating room staff completed postoperative and end-of-study surveys evaluating the bar-code system. RESULTS: The bar-code system detected significantly more counting discrepancies than the traditional protocol (32 vs.13 discrepancies, P = 0.007). These discrepancies involved both misplaced sponges (21 vs. 12 sponges, P = 0.17) and miscounted sponges (11 vs. 1 sponge, P = 0.007). The system introduced new technical difficulties (2.04 per 1000 sponges) and increased the time spent counting sponges (5.3 vs. 2.4 minutes, P < 0.0001). In postoperative surveys, there was no difference in surgical teams' confidence that all sponges were accounted for, but they rated the counting process and team performance lower in operations randomized to the bar-code arm. By the end of the study, however, most providers found the system easy to use, felt confident in its ability to track sponges, and reported a positive effect on the counting process. CONCLUSIONS: Use of automated counting using bar-coded surgical sponges improved detection of miscounted and misplaced sponges and was well tolerated by surgical staff members. © 2008 Lippincott Williams & Wilkins, Inc.

Intra luminal gossypiboma - Agarwal, A.Kr.; Bhattacharya, N.; Mukherjee, R.; Akash Bora, A. (Pakistan Journal of Medical Sciences, 2008)
Intraluminal gossypiboma is a serious but avoidable complication during surgery which can be averted. The whole surgical team has to be vigilant especially during the closure of surgery, the time when fatigue makes every one a bit careless which can be costly both for the surgeon and increases the morbidity and mortality of the patient. Simple precautions like gauze pieces counting and tagging the gauze pieces with markers can prevent this.
Keywords: Gossypiboma

Study examines counts, retained items. (OR manager, 2008)

Coated prostheses are associated with prolonged inflammation in aortic surgery: A cost analysis - Shindo, S.; Motohashi, S.; Katsu, M.; Kaga, S.; Inoue, H.; Matsumoto, M. (Artificial Organs, 2008)
This prospective study was conducted to compare inflammatory responses between patients receiving coated and uncoated vascular prostheses, and to examine their effect on length of stay and cost of patients undergoing abdominal aortic aneurysmectomy. Patients undergoing elective vascular reconstruction of an abdominal aortic aneurysm were assigned randomly to coated-graft or uncoated-graft groups (n = 20, for each group). Interleukin (IL)-6, granulocyte elastase, white blood cell count, C-reactive protein (CRP), and body temperature (BT) were prospectively recorded preoperatively and on postoperative days (PODs) 1, 3, 7, and 14. In-hospital stay and hospitalized costs were also analyzed. IL-6 and CRP concentrations in the coated-graft group were higher than those in the uncoated-graft group (P = 0.01 and 0.05). BT was more frequently elevated >37°C at POD 14 in the coated-graft group than in the uncoated-graft group (P =0.03). Discharge was delayed, and overall hospitalization cost was higher in the coated-graft group than in the uncoated group (17.6 vs. 13.5 days, and 2 010 000 vs. 1 780 000 yen, P = 0.006 and P = 0.002, respectively). Coated vascular prosthesis demonstrated more profound inflammatory reaction than noncoated prosthesis, postoperatively. © 2007, Copyright the Authors.
Keywords: Aortic surgery; Coated graft; Gelatin; Hospitalization cost; Inflammation; Vascular prosthesis

Effect of molecular mobility of polymeric implants on soft tissue reactions: An in vivo study in rats - Andersson, M.; Suska, F.; Johansson, A.; Berglin, M.; Emanuelsson, L.; Elwing, H.; Thomsen, P. (Journal of Biomedical Materials Research - Part A, 2008)
Although numerous different polymers are used as implants or otherwise studied for many other biotechnical applications, there is a lack of basic models that correlate polymer characteristics with foreign body reactions. This study aims at developing one such model by systematically studying surface molecular mobility of polymeric implants in soft tissues in vivo. Changing the length of the alkyl side chain of poly(alkyl methacrylates) (PAMAs), provides an interesting opportunity to study the surface molecular mobility with minimal changes of the hydrophobicity of the surface. Thus, in this study three different PAMAs, with increasingly surface mobility; poly (isobutyl methacrylate) (PIBMA), poly(butyl methacrylate) (PBMA), and poly(lauryl methacralate) (PLMA) along with pure titanium (Ti) substrates were implanted in the dorsum of Sprague-Dawley rats. Inflammatory cell recruitment, cell adhesion, and cytokine release were studied after 1, 3, and 28 days of implantation. Total number of inflammatory cells in the exudate was measured but no correlation between surface mobility and cell recruitment where found. However, the number of surface associated cells where significantly lower on the surfaces with high molecular mobility (PLMA and PBMA). The histological evaluation performed after 28 days revealed thicker fibrous capsule and a higher number of blood vessels on the low molecular mobility surface (PIBMA). After 28 days the cell activity was higher on the high molecular mobility surfaces (PLMA and PBMA) compared with PIBMA, based on the cytokine release. None of the surfaces induced any significant cell-death. On the basis of the results of this study we conclude that there is a significant difference in biological response to surfaces with different in molecular mobility. This might affect the wound healing process and the biocompatibility of biomaterials. © 2007 Wiley Periodicals, Inc.
Keywords: Fibrotic tissue; Inflammatory system; Polymers; Surface molecular mobility; Vascularisation

Acute abdomen: peritonitis - Skipworth, R.J.E.; Fearon, K.C.H. (Surgery, 2008)
Peritonitis is inflammation of the peritoneum and represents an important cause of surgical morbidity and mortality. It may be localized or generalized, and is thought to pass through three phases: firstly, a phase of rapid removal of contaminants from the peritoneal cavity into the systemic circulation; secondly, a phase of synergistic interactions between aerobes and anaerobes; and thirdly, an attempt by host defences to localize infection. Peritonitis is commonly caused by bacteria, but can be chemical (aseptic), biliary, tuberculous, chlamydial, drug-induced or induced by other, rarer causes. Bacterial peritonitis is subclassified into primary or secondary on the basis of whether or not the integrity of the gastrointestinal tract has been compromised. Typically, the patient with peritonitis complains of severe abdominal pain and may exhibit the characteristic Hippocratic facies. Abdominal palpation demonstrates tenderness, guarding and rebound tenderness. Initial laboratory investigations should include urea and electrolytes, full blood count and blood gases. An erect radiograph of the chest demonstrates pneumoperitoneum in about 70-80% of visceral perforations. CT often plays a role in confirming specific diagnoses (e.g. subphrenic abscess). Immediate management should include fluid resuscitation, high-flow oxygen, appropriate antibiotics (i.v.) and analgesia. Definitive management is surgical except for a small group of patients in whom conservative management with fluids (i.v.) and antibiotics (i.v.) is indicated. Surgical management can be via a laparotomy or, in some conditions, laparoscopy. Control of the primary site of sepsis is the main determinant of outcome. Most patients recover quickly. However, major generalized peritonitis is associated with organ dysfunction/failure, and mortality can up to 20-40% in the UK. © 2008 Elsevier Ltd. All rights reserved.
Keywords: antibiotics; bacterial; conservative therapy; emergency surgery; guarding; inflammation; laparotomy; mesothelium; peritonitis; rebound tenderness; relaparotomy; sepsis

Retained large nail with perforating injury of the eye - Chen, K.-J.; Sun, M.-H.; Hou, C.-H.; Chen, T.-L. (Graefe's Archive for Clinical and Experimental Ophthalmology, 2008)
Purpose: To report a case of a mixed open globe injury in which a retained large iron nail and perforating injury of the eye coexisted. Methods: Case report. Results: A 26-year-old construction worker was injured by a nail while using a nail gun at work. The iron nail was inadvertently stabbed into the left eye from the upper eyelid and superonasal sclera to temporal sclera, with lens involvement. His visual acuity was counting fingers in the left eye. Primary suture, removal of a retained iron nail, pars plana vitrectomy and lensectomy, and laser photocoagulation were performed. Three months later, an intraocular lens was implanted in the ciliary sulcus. During postoperative 6-month follow-up, final best-corrected visual acuity was 20/20 without complication. Conclusion: We describe one patient with a mixed open globe injury of a retained nail and perforating injury of the eye resulting from a nail gun. As most eye injuries are preventable, proper training of nail-gun operators and use of safety equipment could reduce the incidence of ocular injuries. Expeditious removal of nails and repair of the lacerations can prevent the complications and achieve good final visual outcomes. © Springer-Verlag 2007.
Keywords: Intraocular foreign body; Nailgun injury; Perforation injury

Managing the prevention of retained surgical instruments: What is the value of counting? - Egorova, N.N.; Moskowitz, A.; Gelijns, A.; Weinberg, A.; Curty, J.; Rabin-Fastman, B.; Kaplan, H.; Cooper, M.; Fowler, D.; Emond, J.C.; Greco, G. (Annals of Surgery, 2008)
OBJECTIVE: Preventing retained foreign bodies is critical for patient safety. However, the value of counting surgical instruments and the reliability of the information provided have never been quantified. This study examines the diagnostic characteristics of counting and its impact on surgical costs. METHODS: We examined data from the Medical Event Reporting System-Total HealthSystem (MERS-TH), administrative hospital, and the New York State Cardiac Surgery Report databases (2000-2004). The cost per count discrepancy was examined by studying a cohort of patients undergoing coronary artery bypass graft (CABG) surgery. Linear and logistic multivariable regression models were used for statistical analysis. RESULTS: Of 153,263 operations, there were 1062 count discrepancies. The rate of retained items was 1 of 7000 surgeries or 1 of 70 discrepancy cases. Final count discrepancies identified 77% and prevented 54% of retained items. The sensitivity of counting was 77.2%, specificity was 99.2%, but the positive predictive value was only 1.6%. Count discrepancies increased with surgery duration, late time procedures, and number of nursing teams. Bypass time, intravenous nitroglycerin injections, or myocardial infarction in the previous 24 hours were independent predictors of count discrepancies in CABG surgery. The incremental OR cost for CABG because of a count discrepancy was $932. Nationally, this would amount to an additional $24 million/yr in OR CABG cost. CONCLUSIONS: This study, for the first time, quantifies the diagnostic accuracy of counting and defines the parameters against which alternative strategies of prevention should be measured, before being adopted in standard practice. © 2008 Lippincott Williams & Wilkins, Inc.

Denture mis-swallowing in the sliding esophageal hiatal hernia mimics esophageal perforation - Chen, C.-Y.; Lee, S.-C.; Chen, C.-W.; Chen, J.-C. (Journal of the Formosan Medical Association, 2008)
Mis-swallowing of a foreign body in the esophagus coexisting with sliding hernia might be misdiagnosed as esophageal perforation with mediastinal abscess. We report an 89-year-old woman, bedridden for a long period in a nursing home after a previous cerebrovascular accident, who was sent to our emergency department in a state of sepsis because she had swallowed a radio-opaque partial denture. The retention of the denture as an esophageal foreign body was complicated with mediastinitis and bilateral pleural effusion. The inability of the patient to give a reliable clinical history delayed the diagnosis. This report highlights the difficulty in precisely locating a partial denture because of conflicting radiologic findings and the coexistence of esophageal sliding hernia, all of which led to a misdiagnosis of possible esophageal perforation. A right posterolateral thoracotomy with gastrostomy was performed to remove the lower esophageal foreign body after esophagoscopy failed. The surgical finding of a coincidental sliding esophageal hiatal hernia correlated well with the clinical presentation. Managing such a complicated esophageal foreign body in this elderly patient was challenging. 2©008 Elsevier & Formosan Medical Association.
Keywords: Esophageal foreign body; Partial denture; Sliding esophageal hiatal hernia

Enteritis cystica profunda: Is trauma the etiology? Interval development in the previously normal ileum: A case report and literature review - Chao, J.C.; Lucha Jr., P.A. (Military Medicine, 2008)
Although well described in the colon, enteritis cystica profunda is an extremely rare lesion of the small intestine with only a few cases documented in English medical literature. It is a benign condition most often associated with Crohn's disease or Peutz-Jeghers syndrome in the adult. It has been described presenting as ileoileal intussusception in the pediatric population. We report a case of enteritis cystica profunda found incidentally on exploratory laparotomy with evidence of interval development over a 5-month period confirming trauma as the etiology.

Perforating Globe Injuries during Operation Iraqi Freedom - Colyer, M.H.; Chun, D.W.; Bower, K.S.; Dick, J.S.B.; Weichel, E.D. (Ophthalmology, 2008)
Objective: To report the injury patterns associated with perforating (through-and-through) injuries of the globe and the visual impact of these injuries on patients with combat ocular trauma (COT) seen at Walter Reed Army Medical Center (WRAMC) from March 2003 through October 2006. Design: Retrospective, noncomparative, interventional case series. Participants: Sixty-five eyes of 61 United States military soldiers deployed during Operation Iraqi Freedom sustaining perforating globe injuries and treated subsequently at WRAMC. Intervention: Principal procedures included enucleation and 20-gauge 3-port pars plana vitrectomy with or without intraocular foreign body removal. Main Outcome Measures: Final visual acuity and rates of proliferative vitreoretinopathy, enucleation, and endophthalmitis. Results: Average patient age was 29 years, with an average of 200 days of postinjury follow-up (median, 97 days; range, 4-1023 days). Nineteen patients confirmed the use of eye protection at the time of injury, whereas 25 patients did not use eye protection. The median presenting visual acuity at WRAMC was no light perception (range, no light perception to hand movements). Twenty-five patients underwent primary enucleation, 1 was eviscerated, and 12 patients underwent secondary enucleation within 2 weeks of surgery. Of 19 patients undergoing pars plana vitrectomy, median visual acuity at presentation was light perception and the median final visual acuity was counting fingers, whereas 4 eyes (21%) achieved final visual acuity of better than 20/200, and in 11 (61%) of 17, proliferative vitreoretinopathy developed over a follow-up of at least 6 months. There were no cases of endophthalmitis or sympathetic ophthalmia. Neither mechanism of injury nor timing of surgery correlated with favorable outcomes. However, entry and exit wounds localized to the anterior half of the globe were associated with favorable anatomic outcome (P<0.005, Fisher exact test, 2-tailed) and visual outcome (P = 0.041, Fisher exact test, 2-tailed). Conclusions: Perforating globe injuries associated with COT generally result in poor visual and anatomic outcomes despite surgical intervention. Prophylactic measures, such as eye protection, are helpful in reducing the likelihood of perforating injuries; however, novel surgical and pharmacologic therapies will be required to improve the functional and anatomic outcomes of these devastating injuries. Financial Disclosure(s): The authors have no proprietary or commercial interest in any materials discussed in this article. © 2008 American Academy of Ophthalmology.

Impact of different texture of polypropylene mesh on the inflammatory response - Di Vita, G.; Patti, R.; Sparacello, M.; Balistreri, C.R.; Candore, G.; Caruso, C. (International Journal of Immunopathology and Pharmacology, 2008)
Over the past decade, hernia surgery has undergone a considerable transformation with the use of prosthetic materials. The most used polypropylene meshes induce a rapid acute inflammatory response followed by chronic foreign body reaction. Many factors influence this response such as density, size, physical characteristics, different texture and porosity of each biomaterial. The aim of this study is to assess whether the implant of monofilament or multifilament meshes, in the inguinal hernioplasty, determine a different inflammatory response. Thirty-two male patients were included in the study and were randomly divided into two groups. In the first group (MO) inguinal hernioplasty was performed using monofilament polypropylene mesh, while in the second one (MU) multifilament prosthesis was used. Peripheral venous blood samples were collected 24 hours before surgery and then 6, 24, 48 and 168 hours posto-peratively. Modifications in leukocyte count, C-reactive protein (CRP), alpha-1 antitrypsin (α1-AT), interleukin (IL)-1, IL-6, IL-1 ra and IL-10 serum levels were recorded at all sampling times. We present evidence that serum levels of CRP, (α1-AT), leukocytes and cytokines were significantly increased post-operatively in both groups, returning to basal values 168 hours afterwards. In particular, the production of all pro-inflammatory mediators was higher in the MU group, whereas the anti-inflammatory cytokine (IL-10, IL-1ra) production was higher in MO patients. Our results indicate that polypropylene multifilament mesh allows a higher intense acute inflammatory response as compared to monofilament mesh implantation. Copyright © by Biolife, s.a.s.
Keywords: Hernioplasty; Mesh; Monofilament polypropylene; Multifilament polypropylene

Case report: Necrotizing fasciitis of odontogenic origin in a subject affected by uncompensated type 2 diabetes mellitus - Pepe, I.; Agrusa, A.; Cusumano, G.; Rinella, M.R.; Fertitta, E.; Scozzari, F.; Adragna, F.; Gaglio, E.C.; Gulotta, P.; Foraci, A.C.; Martorana, U.; Gulotta, G. (Acta Medica Mediterranea, 2008)
Necrotizing Fasciitis (NF) is a highly aggressive infectious process that affects soft tissues, with a high risk of rapid progression through superficial and deep levels of fascia, to the muscle layers. Some forms originate from odontogenous centres with the possibility of rapid evolution into forms of mediastinitis with high mortality rates. Systemic conditions that compromise the immune system of an organism can very easily induce the fatal development of these infectious processes. Prognosis is dependant upon the isolation of the germs that may be responsible in order to start a timely and specific therapeutic treatment; if the isolation is not supported by enough laboratory data to identify the range of action of the pathogens responsible, a wide ranging antibiotic treatment, and possibly surgical drains or treatment in a hyperbaric chamber, should be started. The clinical case that we shall describe is typical and rather complex.
Keywords: Complications; Infections; Necrotizing fasciitis

Comparison of rat bone healing following intra-alveolar grafting with organic or inorganic bovine bone particles - Calixto, R.F.E.; Teófilo, J.M.; Brentegani, L.G.; Lamano, T. (Brazilian Journal of Oral Sciences, 2008)
Aim: This study compared, histometrically, the alveolar bone healing after grafting rats extraction socket with particles of organic or inorganic bovine bone. Method: The volume fraction of grafted materials and bone trabeculae was estimated in histologic images at the end of the 2nd and 9th weeks post-operatively by a differential point-counting method. Results: Particles of both materials were observed partially filling the cervical alveolar third and the volume fraction of inorganic graft was larger than that of organic graft 2 and 9 weeks following implantation. Although evoking neither a foreign body reaction nor a persisting inflammatory response, both materials delayed bone healing. By the 2nd week, the delay was more pronounced in the animals grafted with inorganic than in those grafted with organic bone, but only in the animals whose inorganic graft occupied more than 50% of the cervical third. By the 9th week, despite the greater volume fraction of inorganic graft the percent of bone healing was similar to that observed in the animals grafted with organic bone. Conclusion: The degree of impairment of bone healing resulted from combination of factors such as type of material, its relative amount and the phase of the reparational process.
Keywords: Alveolar healing; Inorganic bovine bone graft; Organic bovine bone graft

Autogenous bone graft associated with enamel matrix proteins in bone repair - Prata, C.A.; Lacerda, S.A.; Brentegani, L.G. (Implant Dentistry, 2007)
PURPOSE: Autogenous bone has been used with success as implants in intrabony defects, because of its biological advantages and osteogenic potential. The objective of this study was to evaluate histological and histometrically the bony repair in intrabony defects after dental extractions in rats with graft of a combination of the enamel matrix protein (EMP) (Emdogain, Strauman USA, LLC, Andover, MA. Headquarters in Basel, Switzerland) and autogenous bone. MATERIALS AND METHODS: Male rats (Rattus norvegicus, Wistar variety) weighing from 250 to 300 g were anesthetized and submitted to the extraction of the superior incisive and divided in (a) group with autogenous bone (fragment of bone of the alveolar ridge was grafted inside the alveolus) and (b) group with autogenous bone associated with EMP. The animals were killed on the 7th, 21st, and 42nd day after the extraction. The maxillae were processed to obtain fine sections (5 μm) stained with hematoxylin-eosin. The percentual volume of bone tissue in contiguous areas of the graft was calculated through a counting point system of image. RESULTS: The results showed that the bone fragments grafted in the cervical third of the alveolus developed a progressive osseointegration without foreign-body reaction. The quantification of the bony repair in the areas adjacent to the graft showed that the autogenous bone associated with EMP produced a greater amount of bone (10%-15% by analysis of variance, P = 0.05) in all the studied periods. CONCLUSIONS: It was concluded that the autogenous bone associated with EMP grafted in bony defects, immediately after the dental extraction in rats, demonstrated biocompatibility and accelerated the repair of bone defect. © 2007 Lippincott Williams & Wilkins, Inc.
Keywords: Autogenous bone; Bony repair; Enamel matrix protein

An unusual abdominal mass: Case report - Saidi, H.; Mohammed, U.; MacHoki, M. (East African Medical Journal, 2007)
The causes of intra-abdominal masses associated with chronic abdominal pain range from the benign to malignant; common to bizarre and some raise major medical-legal issues. We present a case of a 40-year old African lady who presented with chronic right-sided abdominal pain with an associated mass on the right mid-abdomen. She had had a Caesarian section one year prior to presentation. Antecedent history of surgery and typical imaging features enabled a preoperative diagnosis of abdominal mass secondary to retained surgical gauze. The case illustrates the fallibility of the men and women in the operating theatres and the vital role of correct instrument and sponge counts.

Complications of AlphaCor keratoprosthesis: A clinicopathologic report - Chalam, K.V.; Chokshi, A.; Agarwal, S.; Edward, D.P. (Cornea, 2007)
PURPOSE: To describe the clinical and histopathologic features of intractable secondary glaucoma induced by AlphaCor keratoprosthesis. METHODS: An elderly woman with pseudoexfoliation glaucoma and pseudophakic bullous keratopathy in the right eye had graft failures after penetrating keratoplasty. Her best-corrected visual acuity at presentation was counting fingers in the right eye and 20/30 in the left eye. Examination showed severe corneal neovascularization. Chirila keratoprosthesis type II was implanted in 2 stages. Ten months later, the patient developed dense retrocorneal membrane, 360° occlusion of angles, intractable glaucoma, no light perception, and nasal stromal melting associated with partial extrusion of the keratoprosthesis. RESULTS: Histopathology revealed invasion of the porous material of the keratoprosthesis by reactive fibroblasts and multinucleated foreign-body giant cells. In the area of dehiscence, we noted thinning and lysis of the collagen fibers, infiltration of lymphocytes, and plasma cells with a sheet of fibroinflammatory tissue extending into the anterior chamber. CONCLUSIONS: Corneal stromal melting and retrocorneal prosthetic membrane formation after AlphaCor keratoprosthesis implantation led to intractable glaucoma and extrusion of the implant. © 2007 Lippincott Williams & Wilkins, Inc.
Keywords: AlphaCor keratoprosthesis; Complication; Graft failure; Histopathology; Penetrating keratoplasty

Oxidized regenerated cellulose presenting as a postoperative cyst: A case report - Jaspan, D.; Dandolu, V.; Miller, M.; Dunton, C. (Journal of Reproductive Medicine for the Obstetrician and Gynecologist, 2007)
BACKGROUND: Barriers placed intraabdominally may aid in hemostasis and help prevent adhesion formation. CASE: A 17-year-old woman presented with acute pelvic pain and a complex pelvic mass. A laparotomy was performed. To ensure hemostasis, Surgicel (Johnson & Johnson Medical, Arlington, Texas) was placed, and Seprafilm (Genzyme Corp., Cambridge, Massachusetts) was used for adhesion prevention. Within the first postoperative day the patient's status deteriorated, with increasing pain and significant pyrexia. Computed tomography was highly suspicious for a bowel injury. Repeat laparotomy found no injury.the Surgicel was removed and the abdomen irrigated. The remaining postoperative course was uneventful. CONCLUSION: Seprafilm has been associated with acute reactions, and Surgicel has mimicked many radiologic abnormalities. It is imperative to inform the radiologist of the intraoperative use of these agents to allow use of a proper imaging modality in the postoperative period ana to avoid unnecessary repeat surgeries. © Journal of Reproductive Medicine®, Inc.
Keywords: Cellulose; Oxidized; Postoperative complications

Fate of retained capsule: A pathognomonic for surgery - Agaba, E.A.; Shamseddeen, H.; Sasthakonar, V.; Sivalingham, V.; Shah, K.G.; Ravikumar, T.S.; Nadjari, H.; Denoto, G. (American Surgeon, 2007)
Since its introduction in 2001, Wireless Video Capsule enteroscopy is gaining acceptance due to its high diagnostic potential and minimal risk. In some centers, it offers an alternative approach to visualize the small intestine and to evaluate patients with suspected small bowel disease. We present a series of known complications of this procedure and call for a more proactive role in the management of retained capsule.

Retention of silicone oil droplets from ophthalmic viscosurgical devices in the drainage angle of 2 eyes - Lam, P.T.H.; Cheng, A.C.O.; Rao, S.; Lam, D.S.C. (Journal of Cataract and Refractive Surgery, 2007)
We report the outcome in 2 eyes of 2 patients with retained silicone oil droplets in the anterior chamber drainage angle after the use of an ophthalmic viscosurgical device (OVD) during cataract surgery. Silicone oil droplets were observed when the OVD was injected into the anterior chamber during phacoemulsification. Despite removal by irrigation and aspiration, droplets were observed in the anterior chamber during the immediate postoperative period. At 15 months, they were observed in the drainage angle. The retained silicone did not produce untoward side effects in the eyes. Silicone oil is a common contaminant in OVDs but appears to be inert and harmless when retained in small amounts in the anterior chamber drainage angle. © 2007 ASCRS and ESCRS.

Effects of steroids and lubricants on electrical impedance and tissue response following cochlear implantation - Huang, C.Q.; Tykocinski, M.; Stathopoulos, D.; Cowan, R. (Cochlear Implants International, 2007)
The present study examined the effects of steroids and lubricants on electrical impedance and tissue response following cochlear implantation in animal models. Guinea pigs were implanted following either no treatment, or intrascalar injection with dexamethasone, triamcinolone, sodium hyaluronate or saline. Cats were implanted following either no treatment, or intrascalar injection with dexamethasone, triamcinolone or a mixture of triamcinolone with sodium hyaluronate. In guinea pigs, impedance changes and intracochlear tissue response were less for the hyaluronate and saline groups. In cats, impedance in the dexamethasone group increased similar to non-treated cats. Impedance of triamcinolone treated cats remained low for about two months after implantation, before increasing to levels similar to the other groups. Significant fibrous tissue growth was observed histologically. The results of the present study indicate that a single intracochlear application of hyaluronate or triamcinolone may postpone, but will ultimately not prevent the rise in impedance following cochlear implantation. Copyright © 2007 John Wiley & Sons, Ltd.
Keywords: Cochlear implantation; Fibrous tissue growth; Impedance; Intracochlear electrodes

Retained foreign bodies after emergent trauma surgery: Incidence after 2526 cavitary explorations - Teixeira, P.G.R.; Inaba, K.; Salim, A.; Brown, C.; Rhee, P.; Browder, T.; Belzberg, H.; Demetriades, D. (American Surgeon, 2007)
Trauma patients are thought to be at high risk for iatrogenic retained foreign bodies (RFBs). The objective of this study was to evaluate this incidence. All cases of RFB after cavitary trauma surgery were identified by review of Morbidity and Mortality reports at a Level 1 trauma center from January 1998 to December 2005 and confirmed by the Octagon Risk Management System. Over 8 years, 10,053 trauma operations were performed (2075 laparotomies, 377 thoracotomies, and 74 sternotomies). Three cases (0.1%) of RFB (all sponges) occurred during one single-stage and two damage control laparotomies. The counts were correct before definitive closure in two of three cases. No postoperative x-rays were obtained in any of the cases. RFB diagnosis occurred between days 3 and 9, one on a routine chest x-ray and the other two on abdominal computed tomography scans during a septic workup. Four-month to 8-year follow up documented one pleural effusion and one abscess resulting from the RFB. Iatrogenic RFBs after emergent cavitary trauma surgery occur at a rate of 0.12 per cent and are associated with significant morbidity. In addition to standard preventive strategies, in emergent cases with risk factors such as requiring damage control, before final cavity closure, even with a correct sponge count, radiographic evaluation is warranted.

Gentamicin-loaded bioresorbable films for prevention of bacterial infections associated with orthopedic implants - Aviv, M.; Berdicevsky, I.; Zilberman, M. (Journal of Biomedical Materials Research - Part A, 2007)
Adhesion of bacteria to biomaterials and the ability of many microorganisms to form biofilms on foreign bodies are well-established as major contributors to the pathogenesis of implant-associated infections. Treatment of bone infection remains problematic, due to the difficulty of systemically administered antibiotics to locally penetrate bone. The current research addresses this issue by focusing on the development and study of novel gentamicin-loaded bioresorbable films designed to serve as "coatings" for fracture fixation devices and prevent implant-associated infections. Poly(L-lactic acid) and poly (D,L-lactic-co-glycolic acid) films containing gentamicin were developed through solution processing. The effects of polymer type, drug content, and processing conditions on the drug release profile were studied with respect to film morphology. The examined films generally exhibited a burst effect followed by a moderate approximately constant rate of release. The drug contents in the surrounding medium exceeded the required minimal effective concentration. Various gentamicin concentrations that were released from the films with time exhibited efficacy against bacterial species known to be involved in orthopedic infections. The developed systems can be applied on the surface of any metallic or polymeric fracture fixation device, and may therefore comprise a significant contribution to the field of orthopedic implants. © 2007 Wiley Periodicals, Inc.
Keywords: Bioresorbable films; Controlled drug delivery; Gentamicin; Poly(D,L-lactic-co-glycolic acid); Poly(lactic acid)

Histologic analysis of zafirlukast's effect on capsule formation around silicone implants - Bastos, E.M.; Neto, M.S.; Alves, M.T.S.; Garcia, É.B.; Santos, R.A.; Heink, T.; Pereira, J.B.; Ferreira, L.M. (Aesthetic Plastic Surgery, 2007)
Background: The most common complication experienced by patients who have undergone mammary implant surgery is capsular contracture. This matter concerns physicians and patients, but to date, there is no effective way to avoid this complication. Surgical intervention usually is required. In 2002, the use of zafirlukast, a leukotriene inhibitor (a drug used for asthma treatment), was reported for the treatment of capsular contracture, with good results. Methods: For this study, 30 female Wistar rats were used. These animals received two silicone implants each: one with a smooth surface and one with a textured surface. All the animals received daily intraperitoneal injections for 90 days and were divided as follows: control group (C) receiving only saline solution, experimental group 1 (E-I) receiving 1.25 mg/kg/day of zafirlukast, and experimental group 2 (E-II) receiving 5 mg/kg/day of zafirlukast. Histologic analysis used hematoxilin and eosin to verify vessels, capsule thickness, and inflammatory cells. Immunoistochemical analysis with smooth muscle anti-actin antibody was used for myofibroblast verification. Picro-Sirius under polarized light was used for collagen analysis. Results: Textured implant experimental groups presented smaller numbers of vessels, thinner capsules, lower collagen density, and smaller numbers of mastocytes and eosinophils than the control group. No significant differences were found in smooth surface implants, as compared with the control group. Conclusion: Zafirlukast reduced the occurrence of factors directly and indirectly connected with capsular contracture. © 2007 Springer Science+Business Media, LLC.
Keywords: Breast implants; Contracture; Leukotriene antagonists; Therapeutics; Zafirlukast

Grafting of tooth extraction socket with inorganic bovine bone or bioactive glass particles: Comparative histometric study in rats - Calixto, R.F.E.; Teófilo, J.M.; Brentegani, L.G.; Lamano-Carvalho, T.L. (Implant Dentistry, 2007)
PURPOSE:: To compare histometrically, in rats, the bone healing after grafting the incisor extraction sockets with inorganic bovine bone or bioactive glass particles. MATERIAL:: The volume fraction of grafted materials and alveolar healing components was estimated in histologic images at the end of the second and ninth weeks postoperatively by a differential point-counting method. RESULTS:: Both materials were histologically observed partially filling the cervical alveolar third and, although evoking neither a foreign body reaction nor a persisting inflammatory response, delayed new bone formation in trial areas around their particles. By the second week, the delay in bone healing was more pronounced in the animals grafted with inorganic than in those grafted with bioactive glass, and an opposing result was observed during a 9-week period. CONCLUSION:: Both inorganic bovine bone and bioactive glass particles grafted in the incisor extraction sockets of rats delayed new bone formation, and the degree of impairment resulted from a combination of factors such as type of material and phase of the reparation process. Copyright © Lippincott Williams & Wilkins.
Keywords: Alveolar healing; Bioactive glass; Bone healing; Inorganic bovine bone graft

A retained surgical sponge presenting as chronic pelvic pain - Nieves, L.; Schnatz, P.F.; Sahakyan, M.; Sorosky, J.I. (Connecticut Medicine, 2007)
Background: Gossypiboma, the term for a retained sponge, is an underestimated occurrence related to gynecologic surgery. The postoperative presentation can be acute or subacute with symptoms that include pelvic pain. Case: A 39-year-old G7P3043 female presented with chronic pelvic pain. Her only past surgeries were 16 and 21 years prior. After failing to respond to conservative options, she was taken to the operating room for a hysterectomy and possible salpingoophorectomy. During the surgery, a retained sponge was found and removed. Postoperatively, the pain resolved completely. Conclusion: Although gossypiboma is an uncommon cause of chronic pelvic pain, patients can present years later with minimal complications other than discomfort. Accurate sponge and instrument counts, along with radiologic evaluation when a discrepancy is found, can be helpful. Newer technologies are also being developed to help avoid this complication.

Treatment of Candida albicans pericarditis in a heart transplant patient - Puius, Y.A.; Scully, B. (Transplant Infectious Disease, 2007)
Pericarditis due to Candida species is a rare clinical entity, associated with thoracic surgery and immunosuppression. We report here the second case of pericarditis due to Candida albicans in a heart transplant patient, which presented as tamponade approximately 3 weeks post transplant, in the absence of evidence of sternal osteomyelitis. The patient was treated with pericardiocentesis and a combination of caspofungin and fluconazole, but the patient ultimately required the explantation of retained epicardial leads and the creation of a pericardial window. This case illustrates that Candida species must be considered in the differential diagnosis in post-transplant pericarditis, and that foreign body removal is, as always, key in helping to resolve such infections. This case also demonstrates the first use of caspofungin with fluconazole to treat Candida pericarditis. We discuss the conflicting data regarding the use of caspofungin, alone or in combination therapy, in treating infections involving biofilms, such as the infected pericardium. Copyright © Blackwell Munksgaard 2006.
Keywords: Candida albicans; Cardiac transplant; Caspofungin; Pericarditis

Elevation of transforming growth factor beta (TGFβ) and its downstream mediators in subcutaneous foreign body capsule tissue - Li, A.G.; Quinn, M.J.; Siddiqui, Y.; Wood, M.D.; Federiuk, I.F.; Duman, H.M.; Ward, W.K. (Journal of Biomedical Materials Research - Part A, 2007)
Foreign body encapsulation represents a chronic fibrotic response and has been a major obstacle that reduces the useful life of implanted biomedical devices. The precise mechanism underlying such an encapsulation is still unknown. We hypothesized that, considering its central role in many other fibrotic conditions, transforming growth factor β (TGFβ) may play an important role during the formation of foreign body capsule (FBC). In the present study, we implanted mock sensors in rats subcutaneously and excised FBC samples at day 7, 21, and 48-55 postimplantation. The most abundant TGFβ isoform in all tissues was TGFβ1, which was expressed minimally in control tissue. The expression of both TGFβ1 RNA and protein was significantly increased in FBC tissues at all time points, with the highest level in day 7 FBC. The number of cells stained for phosphorylated Smad2, an indication of activated TGFβ signaling, paralleled the expression of TGFβ. A similar dynamic change was also observed in the numbers of FBC myofibroblasts, which in response to TGFβ, differentiate from quiescent fibroblasts and synthesize collagen. Type 1 collagen, the most prominent downstream target of TGFβ in fibrosis, was found in abundance in the FBC, especially during the latter time periods. We suggest that TGFβ plays an important role in the FBC formation. Inhibition of TGFβ signaling could be a promising strategy in the prevention of FBC formation, thereby extending the useful life of subcutaneous implants. © 2007 Wiley Periodicals, Inc.
Keywords: Biosensor; Collagen; Foreign body capsule; Implantation; Smad; Transforming growth factor beta

Idiopathic granulomatous appendicitis treated surgically with long-term follow-up: Report of a case - Mizushima, T.; Ito, T.; Mizuno, H.; Udatsu, Y.; Miyazaki, Y.; Imakita, M.; Iwase, K. (Surgery Today, 2007)
Isolated granulomatous inflammation of the appendix is extremely rare, and its etiology is still unknown. Thus, differentiating between idiopathic granulomatous appendicitis and isolated appendiceal Crohn's disease is difficult. We report a case of idiopathic granulomatous appendicitis with long-term follow-up after surgery. A 26-year-old woman was referred to our hospital for investigation of persistent right lower abdominal pain. Abdominal computed tomography showed a mass, suggesting an inflammatory tumor around the appendix; thus, we suspected subacute appendicitis and performed laparoscopically assisted ileocecal resection. Histological examination of the resected specimen revealed several noncaseous epithelioid granulomas in the wall of the appendix, but no foreign bodies, obstructing lesions, or parasites. Stains for acid-fast bacillus and fungi, and serology for yersinia were all negative. The patient has been followed up for 9 years and remains asymptomatic. This clinical course suggests that her isolated granulomatous appendicitis was idiopathic granulomatous appendicitis unrelated to Crohn's disease. © 2007 Springer-Verlag.
Keywords: Crohn's disease; Idiopathic granulomatous appendicitis; Long-term follow-up

Radio frequency identification (RFID) applied to surgical sponges - Rogers, A.; Jones, E.; Oleynikov, D. (Surgical Endoscopy and Other Interventional Techniques, 2007)
Use of gauze sponges that have been embedded with passive radio frequency identification (RFID) tags presents a high probability of reducing or eliminating instances of gossypiboma, or retained surgical sponge. The use of human counts during surgical operations, especially during instances where unexpected or emergency events occur, can result in errors where surgical instruments, most often gauze sponges, are retained within the patient's body, leading to complications at a later date. Implementation of an automatic inventory record system, for instance, RFID, may greatly reduce these incidences by removing the human factor and would improve patient safety by eliminating the current sponge count protocol. Experiments performed by placing RFID-labeled sponges within an animal and removing them have demonstrated that tags are at least partially readable inside the body cavity and fully readable once removed, suggesting the possibility of an automated sponge count system pending further development of this technology. © 2007 Springer Science+Business Media, LLC.
Keywords: Automated inventory; Gossypiboma; Laparotic sponge; RFID

The brain tissue response to implanted silicon microelectrode arrays is increased when the device is tethered to the skull - Biran, R.; Martin, D.C.; Tresco, P.A. (Journal of Biomedical Materials Research - Part A, 2007)
The influence of tethering silicon microelectrode arrays on the cortical brain tissue reaction was compared with that of untethered implants placed in the same location by identical means using immunoflourescent methods and cell type specific markers over indwelling periods of 1-4 weeks. Compared with untethered, freely floating implants, tethered microelectrodes elicited significantly greater reactivity to antibodies against ED1 and GFAP over time. Regardless of implantation method or indwelling time, retrieved microelectrodes contained a layer of attached macrophages identified by positive immunoreactivity against ED1. In the tethered condition and in cases where the tissue surrounding untethered implants had the highest levels of ED1+ and GFAP+ immunoreactivity, the neuronal markers for neurofilament 160 and NeuN were reduced. Although the precise mechanisms are unclear, the present study indicates that simply tethering silicon microelectrode arrays to the skull increases the cortical brain tissue response in the recording zone immediately surrounding the microelectrode array, which signals the importance of identifying this important variable when evaluating the tissue response of different device designs, and suggests that untethered or wireless devices may elicit less of a foreign body response. © 2007 Wiley Periodicals, Inc.
Keywords: Foreign body response; Implant; Neuroprosthetic; Silicon electrode; Tissue response

Clinical and morphological conditions in capsular contracture formed around silicone breast implants - Prantl, L.; Schreml, S.; Fichtner-Feigl, S.; Pöppl, N.; Eisenmann-Klein, M.; Schwarze, H.; Füchtmeier, B. (Plastic and Reconstructive Surgery, 2007)
BACKGROUND: A study was performed to investigate histological changes in capsules formed around silicone breast implants and their correlation with the clinical classification of capsular contracture defined by the Baker score. For histological classification, the authors used the classification introduced by Wilflingseder, which identifies four grades of contracture. METHODS: The study included 24 female patients (average age, 40 ± 12 years) with capsular contracture after bilateral cosmetic breast augmentation with smooth silicone gel implants (Mentor, Santa Barbara, Calif.). The Baker score was determined preoperatively for each patient. Samples of capsular tissue were obtained from all patients for histologic and immunohistochemical analyses. Capsular thickness, age of the collagen fibers, presence of synovia-like metaplasia on the inner surface of the capsule, number of histiocytes, giant cells, and other inflammatory cells, amount of silicone, foreign body granulomas, and capsule calcification were evaluated. RESULTS: There was a positive correlation between capsular thickness (p < 0.05) and Baker score. Silicone-containing deposits were found in all four histological capsule types. A trend toward greater capsular thickness was documented in patients with severe inflammatory reaction. These patients also had more clinical symptoms. Greater capsular thickness was associated with a higher number of silicone particles and silicone-loaded macrophages in the peri-implant capsule. CONCLUSIONS: The authors demonstrated a positive correlation (p < 0.05) between the clinical classification (Baker score I to IV) and the histological classification introduced by Wilflingseder (Wilflingseder score I to IV). An exact histological classification is needed to describe precisely the morphological changes in capsular contracture. ©2007American Society of Plastic Surgeons.

Partially absorbable meshes for hernia repair offer advantages over nonabsorbable meshes - Bellón, J.M.; Rodríguez, M.; García-Honduvilla, N.; Pascual, G.; Buján, J. (American Journal of Surgery, 2007)
Background: The aim of this study was to establish whether new prosthetic materials with absorbable components, designed to reduce the amount of foreign material in abdominal wall repair, offer advantages over the conventional polypropylene meshes. Methods: Seven × 5 cm defects created in the anterior abdominal wall of New Zealand white rabbits were repaired by using a nonabsorbable polypropylene prosthesis (Surgipro; Tyco, Barcelona, Spain) or 1 of 2 partially absorbable prostheses available on the market (Vypro II and Ultrapro; Johnson & Johnson, St. Stevens-Woluwe, Belgium). At 14 and 90 days after surgery, tissue/prosthesis specimens were subjected to histological studies, biomechanical strength tests, and shrinkage evaluation. Results: At 90 days, the absorbable filaments of Vypro II had been completely reabsorbed, whereas Ultrapro only showed signs of biodegradation in a few zones. Host tissue infiltration and collagen I deposition in the 3 reticular meshes was optimal. Macrophage counts, mesh shrinkage, and biomechanical resistance values were similar. Conclusions: Partially absorbable prostheses perform as well as the standard polypropylene mesh and have the benefit that less foreign material remains in the recipient, without compromising mechanical resistance. © 2007 Excerpta Medica Inc. All rights reserved.
Keywords: Abdominal wall repair; Biomechanical resistance; Macrophages; Partially absorbable meshes; Peritoneum; Polypropylene; Shrinkage

Intra pelvic total migration of sliding screw in intertrochanteric fracture - Bhatti, A.; Abbasi, A. (Journal of the College of Physicians and Surgeons Pakistan, 2007)
A type of fixation failure of Dynamic Hip Screw system (DHS) is presented following a collapse of intertrochanteric fracture fixation. The patient presented three months after DHS fixation with severe lower abdominal pain, painful stiff hip and an uncontrolled diabetes mellitus. The radiographic examination of pelvis revealed intrapelvic presence of DHS sliding screw. The intrapelvic total migration of sliding screw has never been reported so far.
Keywords: Failure; Fixation; Fracture; Intertrochanteric; Screw migration

Influence of hernioplastic implants on male fertility in rats - Kolbe, T.; Lechner, W. (Journal of Biomedical Materials Research - Part B Applied Biomaterials, 2007)
This study explored the vulnerability of the ductus deferens due to mesh induced inflammation and shrinkage after hernia repair in the rodent model. Two commonly used types of hernioplastic implants (Prolene™ and Vypro II™) were surgically wrapped around the ductus deferentes on both sides in 20 juvenile and 20 adult Sprague-Dawley rats. Twenty male rats underwent sham surgeries as controls. After 3 months, each male was mated with 2-3 adult females, which were subsequently sacrificed and oocytes or embryos were flushed and counted. Histochemical investigations of the implants and the ductus recovered surgically 4 weeks after implantation (one side) and after the fertility test (second side) were conducted. All groups exhibited 1-3 males with decreased or restricted fertility but there was no difference between groups. Histochemical analysis of the implants and the ductus recovered 4 weeks and 4 months after implantation revealed some sperm granulomes due to lesions of the spermatic cord caused by the implant in the Prolene™ group. There was no inflammatory reaction in the mucosa or blockage of the spermatic cord visible. Both types of hernioplastic implants tested in this investigation do not give an indication of a negative influence on male fertility in juvenile or adult rats. © 2006 Wiley Periodicals, Inc.
Keywords: Hernia repair; Hernioplastic implant; Male fertility; Rat

Retained Foreign Bodies After Surgery - Lincourt, A.E.; Harrell, A.; Cristiano, J.; Sechrist, C.; Kercher, K.; Heniford, B.T. (Journal of Surgical Research, 2007)
Background: Medical errors during surgery are not well studied. To define risk factors associated with this type of error, we performed a case control analysis. Methods: We retrospectively reviewed medical records involving the ICD-9 code (998.4) for unintentional foreign object remaining in the body during surgery and incident reports gathered by the Department of Risk Management over a 10 year period from 1996 to 2005. Thirty cases were matched with at least four randomly selected controls (131 control patients) that underwent the same type of operation during the same time period. Results: Thirty patients had retained foreign objects (52% sponges and 43% instruments). The abdominal cavity was most commonly involved (46%) followed by the thoracic cavity (23%) although no body cavity remained uninvolved. Eight patients required readmission (30%), 25 patients required reoperation (83%), and there was no mortality. When compared with controls, patients with retained foreign objects were more likely to have had a greater number of major surgical procedures at the same time (2.7 versus 1.8, P = 0.004), to have multiple surgical teams (13% versus 2%, P = 0.02), and more likely to have had an incorrect instrument/sponge count recorded (13% versus 2%, P = 0.01). In multivariate analysis, factors associated with a significantly higher risk of retained foreign objects were the total number of major procedures performed [odds ratio 1.6; 95% confidence interval (CI), 1.1-2.3; P = 0.008] and an incorrect count (odds ratio 16.2; 95% CI, 1.3-197.8; P = 0.02). Conclusion: Retained foreign objects after surgery are associated with multiple major surgical procedures being performed at the same time and an incorrect instrument or sponge count. Identification of these risk factors using case-control analysis should influence operating room policy and reduce these types of errors. © 2007 Elsevier Inc. All rights reserved.
Keywords: medical error; retained foreign body

Delayed Serratia marcescens endocarditis associated with intracardiac foreign body - Yang, L.; Wang, J.-F.; Wu, W. (Chinese Medical Journal, 2007)
Keywords: Echocardiography; Endocarditis; Foreign body

Confocal microscopy imaging of the cornea in patients with silicone oil in the anterior chamber after vitreoretinal surgery - Szaflik, J.P.; Kmera-Muszyńska, M. (Graefe's Archive for Clinical and Experimental Ophthalmology, 2007)
Objective: Evaluation of corneal morphology by confocal microscopy after vitreoretinal surgery complicated by passage of silicone oil into the anterior chamber. Design: Case series (case control study). Methods: Eight patients (eight eyes) who had undergone vitreoretinal surgery and had silicone oil in the anterior chamber but no clinically evident corneal abnormalities made up the patient group. The control group consisted of eight patients (eight eyes) who had undergone vitreoretinal surgery with application of silicone oil tamponade but who had no silicone oil clinically observable in the anterior chamber. In vivo examination of the cornea using a ConfoScan 3 (Nidek Technologies) confocal microscope equipped with the standard 40 immersion lens was performed. Central, upper, and lower parts of the cornea were assessed separately. High-magnification evaluation of the status of corneal layers and endothelial cell density in upper parts of the cornea directly in contact with silicone oil in the anterior chamber and in parts of the cornea not in direct contact with silicone oil was carried out. Results: Alterations in corneal morphology, especially in endothelium and posterior and medium stroma, were observed. In all cases, changes were more advanced in the upper part of the cornea. Endothelial cell density was significantly decreased in upper parts of the cornea. Conclusions: In patients with silicone oil in the anterior chamber, confocal microscopy imaging reveals early morphological alterations of the cornea before their clinical manifestation. © Springer-Verlag 2006.
Keywords: Confocal microscopy; Cornea; Corneal endothelium; Silicone oil; Vitreoretinal surgery

Recurrent fever in patient in a minimally responsive state: An unusual origin of infection - Blazicek, H.; Oder, W. (Brain Injury, 2007)
Embolization of a severed tube of a ventriculo-atrial shunt into the heart is a rare but severe and potentially lethal complication of aresorptive hydrocephalus therapy in patients with severe neurological damage. A rare case is presented of a 53-year-old woman who suffered a severe subarachnoidal haemorrhage. After infection of the first shunting system, the patient underwent an exchange of the system, but repeatedly showed clinical and laboratory signs of infection which failed to improve despite several antibiotic treatments. This case illustrates that, although the patient was in poor neurological and medical condition, it is beneficial to remove the accidentally washed-in foreign body for two reasons. On the one hand to prevent avoidable life-threatening incidents, on the other hand to gain stable medical condition which will allow the patient to participate in neurorehabilitative treatment.
Keywords: Aresorptive hydrocephalus; Medical complication; Ventriculo-atrial shunt

Occurrence and prognosis of nonpenetrating injuries in eyes with Verisyse iris-supported phakic intraocular lens - Moshirfar, M.; Dodd, J.G.; Muir, G.J.; Gagnon, M.R. (Journal of Cataract and Refractive Surgery, 2007)
We report 8 cases of blunt trauma in patients with a Verisyse phakic intraocular lens (pIOL) (AMO). Two cases resulted in dislocation of the pIOL that required repositioning; the other 6 were managed conservatively. In all cases, the outcomes were satisfactory, with no further complications. The cases represent scenarios that patients and physicians might encounter postoperatively and describe ways to manage the complication. © 2007 ASCRS and ESCRS.

Comparison between textured silicone implants and those bonded with expanded polytetrafluoroethylene in rats - Haddad Filho, D.; Zveibel, D.K.; Alonso, N.; Gemperli, R. (Acta Cirurgica Brasileira, 2007)
Purpose: Comparison of the inflammatory reaction promoted by textured silicone implants and that caused by the implant bonded with e-ptfe. Methods: One-hundred and fifty rats were divided into three equal groups (control, silicone, and bonded e-ptfe). These groups were subdivided into five groups, according to the second operation, i.e., 7,30,60,90 and 180 days. Histology of the peri-implant tissue was analyzed by morphometry with blood count (neutrophilos, lymphocytes, macrophages, fibroblasts and capillaries). Results: Comparison of subgroups 7,30,60,90, 180 days: - neutrophils: silicone: > in subgroup 7 days; bonded e-ptfe: > in subgroups 7 and 30 days; - lymphocytes: silicone: > in subgroup 7 and 180 days; bonded e-ptfe: > in subgroup 180 days; - macrophages: silicone: > in subgroup 7 and 60 days; bonded e-ptfe: > in subgroup 7,30 and 60 days; - fibroblasts: silicone: > in subgroup 30 and 60 days;- vascular volume: silicone: in subgroup 7, 60 and 90 days; bonded e-ptfe: > in subgroup 7 days. Comparison of groups: neutrophils : 7 days: > in silicone and bonded e-ptfe; 30 days: > in bonded e-ptfe; - lymphocytes:- 7,30,90 and 180 days: in the control; macrophages:- 7,30 and 60 days: > in silicone & bonded e-ptfe; 180 days > in silicone; fibroblasts: - 7,30 and 90 days: > in silicone and bonded e-ptfe; 180 days: > in bonded e-ptfe; vascular volume - 7,60,90 and 180 days: > in silicone and bonded e-ptfe; 30 days: > in bonded e-ptfe. Conclusions: The acute stage of the inflammatory response was more severe and irregular in the silicone implant; both the silicone implant and the silicone bonded with e-ptfe promoted chronic inflammatory reaction and weak foreign body inflammatory response. These reactions were greater in the silicone implant group.
Keywords: Polytetrafluoroethylene; Rats, wistar; Silicone elastomers; Silicone gels

Treatment of Pseudomonas aeruginosa biofilms with a combination of fluoroquinolones and fosfomycin in a rat urinary tract infection model - Mikuniya, T.; Kato, Y.; Ida, T.; Maebashi, K.; Monden, K.; Kariyama, R.; Kumon, H. (Journal of Infection and Chemotherapy, 2007)
Foreign body-associated infectious disease is currently one of the most problematic hospital-acquired infections. Patients with placement of urinary catheters are especially susceptible to such infection, that is biofilm infection. In this study, we focused on the therapeutic efficacy of prulifloxacin (PUFX) against Pseudomonas aeruginosa OP 14-210, isolated from a patient with complicated urinary tract infection. This microbe formed a biofilm on the surface of a polyethylene tube (PT) placed in a rat bladder without surgical manipulation. In addition, we attempted to eradicate the biofilm by treatment with a combination of PUFX and fosfomycin (FOM). A single oral administration of PUFX at a dose of 20 mg/kg was effective against P. aeruginosa as a biofilm, yielding a significant reduction in CFU per PT of approximately 1 log10 CFU/PT compared with that in untreated controls. A similar therapeutic effect was also observed in levofloxacin-treated rats, and albeit slightly weaker, in ciprofloxacin-treated animals as well. Because 3 days' consecutive treatment with each fluoroquinolone did not further decrease the viable cell counts on the PT, we tested the efficacy of combining PUFX and FOM. These two drugs, administered once a day for 3 days, at doses of 20 and 100 mg/kg, respectively, resulted in significant decreases of viable cell counts on the PT of more than 1.5 log10 CFU/PT compared with PUFX alone (P < 0.05). As seen by scanning electron microscopy, destruction and disappearance of multilayer biofilms occurred after treatment with this drug combination. Such combination therapy with PUFX and FOM may be advantageous for treating biofilm-related infectious diseases. © 2007 Japanese Society of Chemotherapy and The Japanese Association for Infectious Diseases.
Keywords: Biofilm; Fosfomycin; Prulifloxacin; Pseudomonas aeruginosa; Urinary tract infection

Vitreoretinal surgery after childhood ocular trauma - Sheard, R.M.; Mireskandari, K.; Ezra, E.; Sullivan, P.M. (Eye, 2007)
Aim: In adults modern vitreoretinal surgery allows many traumatised eyes to be salvaged. However, one third of serious eye injuries occur in the paediatric age group and trauma is a leading cause of monocular blindness in childhood. This study aims to report the indications, complications and outcomes for vitreoretinal surgical intervention after childhood ocular trauma. Methods: Retrospective case note review of 61 children (age 16 years or less) undergoing vitreoretinal surgical procedures following ocular trauma at a tertiary referral centre. Results: Twenty-eight children (45.9%) had open globe injuries (OGI) and 33 closed globe injuries (CGI, 54.1%). The mean age of children with OGI was 9.5 years and with CGI 12.3 years (P=0.0068). Forty-seven children had traumatic retinal detachments (77.1%), which in 17 cases were treated with conventional scleral buckling surgery and in 30 by vitrectomy. Retinal re-attachment was achieved after one procedure in 70.6% with scleral buckling and 46.7% with vitrectomy. Fourteen children (22.9%) had attached retinas but required vitrectomy for other reasons. After a mean follow-up of 19.6 months, the median visual acuity (VA) of the children improved from counting fingers at presentation to 6/36 at final review (P=0.0031). Traumatic retinal detachment requiring vitrectomy was associated with poor visual outcome (P=0.0003). Conclusion: Vitreoretinal intervention resulted in an improvement in vision in 32 children (57.1%) and stabilised 11 at their presenting acuity (19.6%). Two thirds of the children attained a final VA of 6/60 or better. Proliferative vitreoretinopathy was the cause of redetachment in 68.2% of cases and was significantly associated with a poor outcome (P<0.0001).

In vivo confocal microscopic evaluation of langerhans cell density and distribution in the corneal epithelium of healthy volunteers and contact lens wearers - Zhivov, A.; Stave, J.; Vollmar, B.; Guthoff, R. (Cornea, 2007)
PURPOSE: To examine and compare the density and distribution of Langerhans cells (LCs) in the corneal epithelium of healthy volunteers and contact lens wearers. METHODS: A total of 225 eyes of 130 healthy volunteers (age, 17-81 years) without history of ocular inflammation, trauma, or surgery and 98 eyes of 55 contact lens wearers (age, 13-76 years) were examined in vivo with the combination of the Heidelberg Retina Tomograph II and in-house-invented Rostock Cornea Module. RESULTS: In healthy volunteers, in vivo confocal microscopy revealed LCs in 31% of all volunteers, with 37 of these 43 volunteers presenting LCs both in the center and the periphery of the cornea with densities of 34 ± 3 and 98 ± 8 cells/mm, respectively. In the group of contact lens wearers, 55% of all corneas presented with LCs, and 11 of these 33 corneas revealed LCs at central and peripheral locations. Although LC densities were markedly higher in both the central (78 ± 25 cells/mm) and the peripheral cornea (210 ± 24 cells/mm) of contact lens wearers, the gradient of LC density from peripheral to central cornea was found almost identical in both groups. In the central cornea, LC density decreased with duration of contact lens wear. LCs were located at the depth of 35 to 60 μm (ie, the level of lower intermediate cells, basal cells, and subepithelial nervous plexus). LCs presented as either large cells bearing long processes or smaller cells lacking cell dendrites, most supposedly indicating mature and immature phenotype, respectively. CONCLUSIONS: In vivo confocal microscopy enables evaluation of LC density and distribution in corneal epithelium. LCs were found present both in the center and the periphery of the cornea without difference in distribution between healthy volunteers and contact lens wearers. However, contact lens wearers revealed almost twofold higher LC densities in both locations, implying chronic mechanical irritation of the cornea in response to the contact lens as foreign body. Taken together, analysis of LC using in vivo confocal microscopy provides helpful information for a better understanding of contact lens-disturbed ocular homeostasis. © 2007 Lippincott Williams & Wilkins, Inc.
Keywords: Contact lens; Cornea; Epithelium; In vivo confocal microscopy; Langerhans cells

Correlation of clinical outcome of integra application with microbiologic and pathological biopsies - Muangman, P.; Deubner, H.; Honari, S.; Heimbach, D.M.; Engrav, L.H.; Klein, M.B.; Gibran, N.S. (Journal of Trauma - Injury, Infection and Critical Care, 2006)
BACKGROUND: Integra, a dermal replacement template consisting of bovine collagen, chondroitin-6-sulfate, and a silastic sheet is a postexcisional treatment for deep partial to full thickness burns where autograft is limited. This study correlates Integra histology and quantitative microbiology cultures with clinical outcomes after autografting. METHODS: Charts of 29 burn patients who underwent Integra treatment and neodermis biopsy at the time of ultra thin autografting were reviewed. We analyzed microbial contamination, inflammatory reaction, and autograft take. RESULTS: The mean burn size and age were 43% total body surface area and 39 years old, respectively. In quantitative neodermis cultures, 90% of samples had bacterial growth; nine samples (31%) had >10 colony forming units per gram. The most common organism was Staphylococcus aureus (31%). Patients with quantitative bacterial counts >10 CFU/g received targeted systemic antibiotics. Integra take (83%) and autograft take (92%) were acceptable even in patients with high bacterial counts (78% Integra take; 86% autograft take). More than 50% of biopsies had dermal regeneration similar to normal dermis; foreign body reactions were unusual. Histologic evidence of inflammation, especially polymorphonuclear cells, was increased in biopsies with high bacterial counts. CONCLUSION: Integra and autograft take can be acceptable even with high bacterial counts if wounds are treated with appropriate targeted topical and systemic antibiotics in the presence of microbial contamination. Neodermis biopsies showed fibrous in-growth congruent with existing Integra fibers with minimal foreign body reaction. These data support Integra use as a safe and effective treatment modality in patients with major burns. © 2006 Lippincott Williams & Wilkins, Inc.

Intracolonic multiple pebbles in young adults: Radiographic imaging and conventional approach to a case - Eryilmaz, M.; Ozturk, O.; Mentes, O.; Soylu, K.; Durusu, M.; Oner, K. (World Journal of Gastroenterology, 2006)
Most of the foreign bodies detected in adult gastrointestinal systems are accidentally swallowed pins. In this study, we presented a case with intracolonic multiple pebbles. A 20-year-old man was admitted to emergency surgery policlinic for abdominal pain for 2 d without any alleviation or aggravation. His upright plain abdominal radiographic imaging revealed about 30-40 overt dense opacities in lumen of colonic segments, with oval and well shaped contours, each approximately 1 cm × 1 cm in size. The multiplanar reconstructions and three- dimensional images combined with sectional screening showed that all pebbles had passed completely into the colon and no foreign bodies had remained in the ileal segments. On psychiatric assessment, he was found to have immature personality features, difficulty in over- coming stressors and adaptation disorder. He recovered by conservative management and radiographic monitoring applied during his follow-up. Thus, it can be concluded that, in differential diagnosis of abdominal pain in adult ages, though less frequently seen than in children, gastrointestinal system foreign bodies should always be kept in mind and it should be considered that ingestion of pebbles may be one of the factors contributing to abdominal pain particularly in young adults with psychiatric problems. In such cases suspected of having foreign bodies which cannot be detected by plain films, abdominal tomography can be an alternative for diagnostic imaging. © 2006 The WJG Press. All rights reserved.
Keywords: Current approach; Intracolonic multiple pebbles; Radiographic imaging

Governing the surgical count through communication interactions: Implications for patient safety - Riley, R.; Manias, E.; Polglase, A. (Quality and Safety in Health Care, 2006)
Background: Intermittently, the incidence of retained surgical items after surgery is reported in the healthcare literature, usually in the form of case studies. It is commonly recognised that poor communication practices influence surgical outcomes. Aim: To explore the power relationships in the communication between nurses and surgeons that affect the conduct of the surgical count. Methods: A qualitative, ethnographic study was undertaken. Data were collected in three operating room departments in metropolitan Melbourne, Australia. 11 operating room nurses who worked as anaesthetic, instrument and circulating nurses were individually observed during their interactions with surgeons, anaesthetists, other nurses and patients. Data were generated through 230 h of participant observation, 11 individual and 4 group interviews, and the keeping of a diary by the first author. A deconstructive analysis was undertaken. Results: Results are discussed in terms of the discursive practices in which clinicians engaged to govern and control the surgical count. The three major issues presented in this paper are judging, coping with normalisation and establishing priorities. Conclusions: The findings highlight the power relationships between members of the surgical team and the complexity of striking a balance between organisational policy and professional judgement. Increasing professional accountability may help to deal with the issues of normalisation, whereas greater attention needs to be paid to issues of time management. More sophisticated technological solutions need to be considered to support manual counting techniques.

Percutaneous nephrostomy and antegrade ureteral stenting: Technique - Indications - Complications - Hausegger, K.A.; Portugaller, H.R. (European Radiology, 2006)
In this review the technique, indication for and complications of percutaneous nephrostomy (PCN) and antegrade ureter stent insertion are described. In the majority of the cases PCN is performed to relieve urinary obstruction, which can be of benign or malignant nature. Another indication for PCN is for treatment of urinary fistulas. PCN can be performed under ultrasound and/or fluoroscopic guidance, with a success rate of more than 90%. The complication rate is approximately 10% for major and minor complications together and 4-5% for major complications only. Percutaneous antegrade double-J stent insertion usually is performed if retrograde ureter stenting has not been successful. However, especially in malignant obstructions, the success rate for antegrade stenting is higher than for retrograde transvesical double-J stent insertion. In the case of severe infection and bleeding after PCN JJ-stent insertion may be contraindicated so long as there is no sufficient concomitant drainage via a PCN. Lower urinary tract dysfunction should be excluded before stent placement. The complication rate is 2-4%. Consequent stent surveillance with regular stent exchange is mandatory. © Springer-Verlag 2006.
Keywords: Interventional procedures; Kidney; Percutaneous nephrostomy; Stents; Ureter; Urinary tract obstruction

Counting for patient safety - Watson, D.S. (AORN Journal, 2006)

Delayed presentation of sigmoid colon fistula 2 years after impalement injury - Vuilleumier, H.; Saucy, F.; Halkic, N. (Chirurgia, 2006)
Impalement injuries from falls are rarely seen in emergency unit because many patients die at the scene of the accident. These injuries result in high energy transfer between the impaled foreign object and the patient and demonstrate characteristics of both blunt and penetrating trauma. We present an unusual case of delayed presentation of sigmoid colon fistula and psoas.
Keywords: Abdominal injury; Colon perforation; Fistula; Impalement; Psoas abscess

Global pediatric pulmonology: What is coming to the West - Out of India? - Singh, V. (Paediatric Respiratory Reviews, 2006)
With the increasing globalisation, immigration and travel there are increasing opportunities for the exotic diseases to be seen in different settings. This paper highlights pulmonary diseases seen in the Indian subcontinent. It discusses briefly the clinical features and management of Tropical Pulmonary Eosinophilia, Hydatid disease of the lungs, Malarial lung pathology. In addition, the low cost medical innovations evolved to use the newer medical technologies, in an affordable fashion, in a developing countries context have been detailed. © 2006 Elsevier Ltd. All rights reserved.
Keywords: cystic fibrosis; flexible pediatric bronchoscopy; foreign bodies in the airways; global medicine; hydatid disease of the lungs; inhalation therapy; low cost medical technology; malarial lung; sweat chloride estimation; tropical diseases; tropical pulmonary eosinophilia

No difference in early cellular response of the pseudo-synovial membrane after total hip arthroplasty: Comparison of 3 combinations of bearing materials - Nygaard, M.; Elling, F.; Bastholm, L.; Søballe, K.; Borgwardt, A. (Acta Orthopaedica, 2006)
Background: Wear-resistant bearing materials may hypothetically reduce chronic inflammation in the pseudosynovial membrane as compared to less wear-resistant bearing materials such as polyethylene. We assessed the foreign body response in the pseudosynovial membrane in vivo after total hip replacement. Methods: 37 patients from a larger prospective randomized trial of 225 patients had biopsies taken arthroscopically from the artificial hip joint (i.e. the pseudosynovial membrane) 1 year after insertion of the implant. All patients had an identical hip prosthesis (Bimetric-RingLoc) except for the bearing materials, which consisted of polyethylene on zirconia, CoCr on CoCr, or alumina on alumina. Histological quantification was performed on 2-μm-thick semi-thin plastic sections or paraffin sections by point counting technique to compare the volume fraction of macrophages, granulomas and endothelial cells in biopsies of the pseudosynovial membrane. Results: The median macrophage volume fractions for polyethylene-on-zirconia bearing material (n = 15), CoCr-on-CoCr (n = 9), and alumina-on-alumina (n = 11) were 0.02, 0.04, and 0.004, respectively. The median granuloma volume fractions for polyethylene-on-zirconia (n = 13), CoCr-on-CoCr (n = 9), and alumina-on-alumina (n = 13) were 0.02, 0.04, and 0.02, respectively. The median endothelial cell volume fractions for polyethylene-on-zirconia (n = 15), CoCr-on-CoCr (n = 9), and alumina-on-alumina (n = 11) were 0.03, 0.02, and 0.05, respectively. Statistical analysis showed no significant differences between the three groups with the different bearings with respect to volume fraction of macrophages, granulomas and endothelial cells. Interpretation: Our study demonstrated that a granulomatous inflammation is a common finding in non-loose implants as early as 1 year after the operation not demonstrating a difference in macrophages and granuloma formation with the various bearing materials. Thus a high volume fraction of macrophages was found in the osteoarthritis control group compared to the operated group. Copyright© Taylor & Francis 2006.

The inflammatory cell influx and cytokines changes during transition from acute inflammation to fibrous repair around implanted materials - Gretzer, C.; Emanuelsson, L.; Liljensten, E.; Thomsen, P. (Journal of Biomaterials Science, Polymer Edition, 2006)
The inflammatory and fibrous responses in a subcutaneous rat model were evaluated around degradable polyurethane urea (PUUR; Artelon®), with titanium and tissue culture polystyrene (PS) discs having different surface chemical properties but similar surface topography. Cytokines, viability, cellular response, differentiation of cells and fibrous capsule formation and vascularization was investigated after 1, 7 and 21 days of implantation. The exudates retrieved from the pockets were analysed with respect to the total cell numbers, the proportions of cell types, the differentiation of monocytes/macrophages (ED1, ED2), the DNA content and the viability (LD, Trypan blue). Tumour necrosis factor alpha ((h)TNF-α) and interleukin-10 ((h)IL-10) were quantified by ELISA. The number of blood vessels, blood vessel luminal area, blood vessel distribution and the fibrous capsule thickness were analysed. The highest number of cells in the exudates around all implants was detected during the early phase of healing (1-7 days). The proportion of ED2-positive cells in the exudates increased from 2-8% at 1 day to 43-56% at 21 days. The levels of TNF-α were low with a decrease at 7 days. After 21 days high amounts of IL-10 in the exudates were detected, in particular around PUUR. This study shows that the transition from inflammation to repair (1-21 days) around PUUR, Ti and PS materials was characterized by a decrease in inflammatory cell influx, an increasing proportion of ED2-expressing macrophages, a biphasic TNF-α secretion, an increase of IL-10 and a fibrous capsule formation similar to all materials tested. © VSP 2006.
Keywords: Biocompatibility; Cytokine; Poly(urethane urea); Polystyrene; Titanium; Wound healing

Morphometrical analysis of multinucleated giant cells in subdermal implants of poly-lactic acid in rats - Maluf-Meiken, L.C.V.; Silva, D.R.M.; Duek, E.A.R.; Alberto-Rincon, M.C. (Journal of Materials Science: Materials in Medicine, 2006)
The use of bioabsorbable polymers in (bio)medical applications has increased greatly in recent years, mainly because of their good bioreabsorption and biocompatibility. In this work, we examined the development of foreign body giant cells in intimate contact with porous membranes of poly L-lactic acid containing 7% of plasticizer triethylcitrate implanted in the backs of rats. The membranes were removed 2, 7, 14, 21, 28, 60, 90 and 180 days after implantation, along with a portion of the tissue around the implant. Histological analysis of the implant and tissue revealed the formation of a fibrous capsule from the seventh day of implantation onwards. Foreign body giant cells appeared from the seventh day and increased in number up to the twenty-eighth day and then up to the ninetieth day of implantation, remaining constant up to the end of the study onwards, and increased in number up to the ninetieth day after implantation and then remained constant. The number of nuclei in these cells increased from the seventh day of implantation up to the ninetieth day and then up to the end of the study. © Springer Science + Business Media, LLC 2006.

Long-term complications of iris-claw phakic intraocular lens implantation in Weill-Marchesani syndrome - Burakgazi, A.Z.; Ozbek, Z.; Rapuano, C.J.; Rhee, D.J. (Cornea, 2006)
Purpose: This study was designed to report the long-term complications of iris-claw phakic intraocular lens implantation in a patient with Weill-Marchesani syndrome. Methods: Case report and literature review. Results: A 26-year-old man with a history of glaucoma had bilateral phakic lens implantation for high myopia 10 years previously. Two years later, the left implant dislocated and was repositioned. Slit-lamp examination of both eyes revealed phakic implants of the iris-claw variety. There were moderate iridocorneal adhesions in the areas in which the lens haptics pinched the iris in both eyes and moderate epithelial and stromal edema over the temporal one-third of the left cornea. The crystalline lenses were clear with 3+ phacodonesis OU. Dilated fundus examinations revealed bilateral severe optic nerve cupping. Crystalline lens diameters were measured at 7.5 mm in the right eye and 8 mm in the left. Anterior chamber depths were 2.63 mm OD and 2.40 mm OS. Specular microscopy revealed central endothelial cell counts of 1133 and 587 cells/mm2 OD and OS, respectively. Axial lengths were 23.3 mm OD and 25 mm OS. Gonioscopic examination revealed bilateral angle closure with marked peripheral anterior synechiae. Based on our findings of short stature, shortened and thickened fingers, relatively normal axial length, microspherophakia, high myopia, and glaucoma, we diagnosed the patient with Weill-Marchesani syndrome. Conclusion: Iris claw-lens phakic lenses may be an effective surgical alternative to correct high myopia in select patients; however, it may produce long-term complications in eyes with specific features. Copyright © 2006 by Lippincott Williams & Wilkins.
Keywords: Iris-claw lens; Phakic intraocular lens; Weill-Marchesani syndrome

Antioxidant inhibition of poly(carbonate urethane) in vivo biodegradation - Christenson, E.M.; Anderson, J.M.; Hiltner, A. (Journal of Biomedical Materials Research - Part A, 2006)
This study compared the effect of an antioxidant on the in vivo biodegradation of a poly(carbonate urethane) (PCU) and a poly (ether urethane) (PEU). Unstrained PEU and PCU films with and without Santowhite® were implanted subcutaneously into 3-month-old Sprague-Dawley rats for 3, 6, and 12 months. Characterization of unstabilized PEU and PCU with ATR-FTIR and SEM showed soft-segment and hard-segment degradation consistent with previous studies. In particular, evidence of chain scission and crosslinking of the surface was present in the ATR-FTIR spectra of explanted specimens. Addition of 2.2 wt % antioxidant inhibited the in vivo degradation of both PCU and PEU. Although the antioxidant probably improved polyurethane biostability by decreasing the susceptibility of the polymer to degradation, modulation of the cellular response to prevent the release of degradative agents was also possible. To differentiate the effects, the foreign-body response was investigated with the use of a standard cage implant protocol. Polyurethane films were implanted in wire mesh cages subcutaneously in rats for 4, 7, and 21 days. There were no statistical differences among materials in the inflammatory exudate cell counts, adherent cell densities, or percent fusion of macrophages into foreign-body giant cells (FBGCs). Therefore, it was concluded that the antioxidant inhibited degradation by capturing oxygen radicals that would otherwise cause polyurethane chain scission and crosslinking. © 2005 Wiley Periodicals, Inc.
Keywords: Antioxidant; Biodegradation; Foreign-body response; In vivo; Poly(carbonate urethane); Poly(ether urethane)

Perforation of the gastrointestinal tract secondary to ingestion of foreign bodies - Goh, B.K.P.; Chow, P.K.H.; Quah, H.-M.; Ong, H.-S.; Eu, K.-W.; Ooi, L.L.P.J.; Wong, W.-K. (World Journal of Surgery, 2006)
Introduction: Ingesting a foreign body (FB) is not an uncommon occurrence. Most pass through the gastrointestinal (GI) tract uneventfully, and perforation is rare. The aim of this study was to report our experience with ingested FB perforations of the GI tract treated surgically at our institution. Methods: A total of 62 consecutive patients who underwent surgery for an ingested FB perforation of the GI tract between 1990 and 2005 were retrospectively reviewed. Three patients with no definite FB demonstrated intraoperatively were included. Results: The patients had a median age of 58 years, and 37 (60%) were male. Of the 59 FBs recovered, 55 (93%) were toothpicks and dietary FBs such as fish bones or bone fragments. A definitive preoperative history of FB ingestion was obtained for only two patients, and 36 of 52 patients (69%) wore dentures. Altogether, 18 (29%) perforations occurred in the anus or distal rectum, and 44 perforations were intraabdominal, with the most common abdominal site being the distal ileum (39%). Patients with FB perforations in the stomach, duodenum, and large intestine were significantly more likely to be afebrile (P = 0.043), to have chronic symptoms (> 3 days) (P < 0.001), to have a normal total white blood cell count (P < 0.001), and to be asymptomatic or present with an abdominal mass or abscess (P < 0.001) compared to those with FB perforations in the jejunum and ileum. Conclusions: Ingested FB perforation in the adult population is most commonly secondary to unconscious accidental ingestion and is frequently caused by dietary FBs especially fish bones. A preoperative history of FB ingestion is thus rarely obtained, although wearing dentures is a common risk factor. FB perforations of the stomach, duodenum, and large intestine tend to present with a longer, more innocuous clinical picture than perforations in the jejunum or ileum. © 2006 by the Société Internationale de Chirurgie.

Recommended practices for sponge, sharps, and instrument counts. (AORN journal, 2006)

Perioperative Patient Safety: A Multisite Qualitative Analysis - Chappy, S. (AORN Journal, 2006)
• THIS STUDY WAS UNDERTAKEN to identify specific events that affected patient safety in perioperative service areas during a three-year period. • THE THREE MOST COMMON TYPES of reported incidents were incorrect counts, equipment malfunction, and medication errors. Data revealed significant disparities between health care facilities regarding what types of incidents were reported. • STANDARDIZED LANGUAGE and reporting mechanisms would aid in the consistency and validity of current incident reporting and could help to improve perioperative patient safety. © 2006 AORN, Inc.

Methylene blue for diagnosis of displaced atrial lines - Namachivayam, P.; Tibballs, J. (Anaesthesia and Intensive Care, 2006)
Methylene blue (aniline violet, tetra-methylthionine chloride) has several important uses in clinical medicine, including diagnosis of displaced central lines. After cardiac surgery, three infants with suspected displacement of direct atrial lines were given methylene blue. After injection of the dye into the atrial lines, bluish discolouration was identified in their chest drainage. Use of methylene blue in small amounts appears to be a safe and effective way of diagnosing extravasation of fluid from displaced central lines.
Keywords: Atrial line; Chest drain; Hypoplastic left heart syndrome; Methylene blue

Ulcerated Gastrointestinal Stromal Tumor (GIST) with Ingested Bone Foreign Body Mimicking a Perforation with Abscess - Kriegshauser, J.S.; Hara, A.K. (Radiology Case Reports, 2006)
Gastrointestinal stromal tumors (GIST) have a variety of appearances and can present as an intraluminal, extraluminal, solid or ulcerated mass. We present an unusual case of a patient presenting with pain, elevated white count, and computed topography (CT) findings suggesting an abscess containing bone. CT guided drainage was performed, and resulted in bowel perforation, leading to surgical intervention and the diagnosis of an ulcerated gastrointestinal stromal tumor containing bone. © 2006 The Authors.

A revolutionary advance in skin closure compared to current methods - Piñeros-Fernandez, A.; Salopek, L.S.; Rodeheaver, P.F.; Drake, D.B.; Edlich, R.F.; Rodeheaver, G.T. (Journal of Long-Term Effects of Medical Implants, 2006)
Six pigs were used to evaluate the influence of three separate modalities on contaminated wounds. Full-thickness skin wounds on the abdomen were contaminated with 104 or 105 Staphylococcus aureus and then closed with one of three methods. The three closure modalities included (1) a new absorbable staple (Insorb™) placed in the subcuticular tissue, (2) a braided Vicryl™ suture, and (3) percutaneous metal staples. Any foreign body material implanted in tissue increases the risk of infection at that site. Wound closure always involves the use of a foreign body. Historically, sutures have been the primary material used to close tissue. The newer synthetic sutures are significangly more biodegradable and cause less infection than sutures composed of protein, such as silk and catgut. Metal staples are also associated with a low risk of infection. Recently, Incisive Surgical, Inc. (Plymouth, Minnesota) has developed an absorbable polymer staple specifically for subcuticular skin closure. The purpose of this study was to compare the new Insorb™ staple to both an absorbable polymer suture and a metal staple. Wound infection was assessed 7 days after closure by clinical signs and quantitative bacterial swabs. The results demonstrated that wounds closed with Insorb™ staples had the lowest incidence (33%) of infection, followed by percutaneous metal staples (44%). All wounds (100%) closed with Vicryl™ suture became infected. The incidence of wound infection directly correlated with the level of quantitative bacterial count at analysis. The Insorb™ staple was associated with significantly reduced closure time, less inflammation and infection, and better aesthetic result compared to Vicryl™. Compared to metal staples, the Insorb™ subcuticular staplers demonstrated comparable closure time without the need for later staple removal. In conclusion, the closure of contaminated wounds with the Insorb™ staples is a superior choice to Vicryl™ suture because they have a significantly (p = 0.009) lower incidence of infection. The Insorb™ staple is a revolutionary advance in subcuticular skin stapling. © 2006 by Begell House, Inc.
Keywords: Aesthetic result; Insorb™; Skin staple; Staphylococcus aureus; Staples; Subcuticular; Suture; Vicryl™; Wound closure speed; Wound infection

Patient safety practices in the operating room: Correct-site surgery and nothing left behind - Gibbs, V.C. (Surgical Clinics of North America, 2005)
Attention has turned to issues of surgical patient safety. Essential patient safety practices in the operating room include the application of standard processes of care, the use of protocols and checklists to reduce reliance on memory, the employment of simpler processes as much as possible, the alleviation of conditions that predispose to human error (eg, interruptions, fear, anger, time pressure, anxiety), and the design and use of error-proof devices coupled with frequent training in the use of these devices. These practices can be applied to two issues in surgical patient safety: assurance of correct site surgery and prevention of incidents involving retained foreign bodies. Both of these safety problems involve poor communication between perioperative care personnel and faulty processes of care. Recommendations to ensure that the correct procedure is performed on the correct patient at the correct site have been mandated by the JACHO Universal Protocol. The protocol mandates using a preoperative verification process, marking the operative site, and taking a "time out" immediately before starting the procedure. All health care facilities where invasive procedures that expose patients to harm are performed are required to comply with this protocol. Recommendations to prevent the retention of sponges, sharps, instruments, and other miscellaneous items include consistent application and adherence to standardized counting procedures, performance of a methodical wound exploration before closure of the surgical site, use of radiograph-detectable items in the surgical wound, maintenance of an optimal operating room environment to allow focused performance of operative tasks, and application of radiographs or other technology as indicated to ensure there is no item left by mistake in the operative field. All perioperative care personnel can work together to ensure that these events never happen. Getting to zero is possible.

Comparison of inflammatory response to polyglytone 6211 and polyglecaprone 25 in a rat model - van Heerden, J. (South African Medical Journal, 2005)

Migrating fish bone complicating a deep neck abscess - Yang, S.-W.; Chen, T.-M.; Chen, T.-A. (Chang Gung Medical Journal, 2005)
Deep neck infections are not uncommon; however, a migrating fish bone is seldom a cause of a deep neck abscess. Fish bones are a sharp foreign body and can penetrate the oropharynx or esophagus. However, this rarely occurs. We report a case of deep neck abscess resulting from the intracorporeal migration of a fish bone. Initial radiography and esophagoscopy of the neck were both negative; migration of the bone was ultimately documented by computed tomography. Surgical exploration was performed via a lateral neck incision, and the fish bone was successfully retrieved. Although fish bones are a rare etiology of deep neck abscesses, should be kept in mind when a patient has the history of fish bone ingestion.
Keywords: Abscess; Deep neck infection; Fish bone; Migratory

Septic arthritis - Ross, J.J. (Infectious Disease Clinics of North America, 2005)
Septic arthritis has increased in incidence in the United States in the past two decades, and increasingly affects an older population with a greater burden of chronic illness and a higher risk for drug-resistant organisms. Successful management depends on a high diagnostic suspicion, empiric antibiotic treatment, and joint drainage. A bacteriologic diagnosis is more likely with inoculation into blood culture bottles than plating on solid media. As MRSA increases in prevalence in the community, empiric antibiotic regimens increasingly need to be active against MRSA. © 2005 Elsevier Inc. All rights reserved.

Complete intraluminal migration of a retained surgical lap sponge 4 years after appendicectomy: A case report - Moosavi Naeeni, S.M.; Panahi, F.; Assari, S. (European Surgery - Acta Chirurgica Austriaca, 2005)
Background: Retained foreign bodies after surgery constitute an occasional misadventure in modern surgery and cause returns to the operating room. Approximately, two-thirds of retained objects are sponges. Methods: We report on a 10-year-old boy presenting with a retained surgical sponge that had migrated completely into the lumen of the ileum. Removal was performed by laparotomy and ileotomy. Radiological and intraoperative findings are discussed, and a review of the recent relevant literature is provided. Results: Laparotomy revealed an intraluminal 30 cm long lap sponge (25 cm in the ileum and 5 cm in the cecum) which had completely migrated into the interior of the intestine. Complications, i.e., adhesion bands and fistulae, were treated subsequently. Conclusions: The case highlights the importance of a careful count of sponges before and after surgery and thorough exploration of all quadrants of the abdomen at the termination of surgical cases. © Springer-Verlag 2005.
Keywords: Foreign-body migration; Lap sponge; Retained surgical sponges

The role of osteopontin in foreign body giant cell formation - Tsai, A.T.; Rice, J.; Scatena, M.; Liaw, L.; Ratner, B.D.; Giachelli, C.M. (Biomaterials, 2005)
Foreign body giant cells (FBGCs) are a hallmark of the foreign body reaction caused by biomaterial implantation and are thought to contribute to biomaterial degradation and the duration of the response. Osteopontin (OPN) is a secreted, acidic matricellular protein with multiple phosphorylation sites that is highly expressed at sites of inflammation. OPN wildtype and knockout mice were implanted with poly(vinyl alcohol) sponges and explanted at 14 days. OPN knockout mice had more foreign body giant cells but fewer macrophages surrounding the implants than their wildtype counterparts. In an in vitro human FBGC assay, addition of soluble OPN was found to reduce macrophage fusion to giant cells. These are the first studies to show a direct inhibitory role of OPN in FBGC formation in response to implantation. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Foreign body giant cells; Foreign body reaction; Knockout mice; Macrophages; Osteopontin

Influence of polyglecaprone 25 (Monocryl) supplementation on the biocompatibility of a polypropylene mesh for hernia repair - Junge, K.; Rosch, R.; Krones, C.J.; Klinge, U.; Mertens, P.R.; Lynen, P.; Schumpelick, V.; Klosterhalfen, B. (Hernia, 2005)
Background: Supplementary polyglecaprone 25 (Monocryl) monofilaments were added to a lightweight pure monofilament polypropylene mesh (PP mesh) to improve intraoperative handling (PP+M mesh). This study was designed to evaluate the influence of this additional supplementation on the biocompatibility in a rodent animal model. Methods: Two mesh materials, a composite mesh (PP+M) and the pure polypropylene variant (PP), were compared after subcutaneous implantation in a standardized rat model. Histological analysis of the inflammatory response was performed after 28, 56 and 84 days of implantation. Material absorption, inflammatory tissue reaction, fibrosis and granuloma formation were investigated, as well as the percentage of proliferating and apoptotic cells at the interface. Results: Both mesh materials showed a slight foreign body reaction involving mainly macrophages and foreign body giant cells. Total absorption of the Monocryl filaments of the PP+M mesh occurred between 56 and 84 days of implantation. Both the inflammatory and the fibrotic reaction were decreased (n.s.) in the PP+M mesh group compared to the pure PP mesh. Whereas the percentage of proliferating cells showed no significant difference, the rate of apoptotic cells was significantly decreased in the PP+M mesh group over the whole implantation period. Conclusion: Compared to the pure polypropylene mesh, our data confirm that the use of a polypropylene mesh supplemented with absorbable Monocryl filaments is feasible without additional short-term mesh-related complications in the experimental model or negative side effects on biocompatibility. © Springer-Verlag 2005.
Keywords: Biocompatibility; Mesh; Polyglecaprone 25; Polypropylene

Neuronal cell loss accompanies the brain tissue response to chronically implanted silicon microelectrode arrays - Biran, R.; Martin, D.C.; Tresco, P.A. (Experimental Neurology, 2005)
Implantable silicon microelectrode array technology is a useful technique for obtaining high-density, high-spatial resolution sampling of neuronal activity within the brain and holds promise for a wide range of neuroprosthetic applications. One of the limitations of the current technology is inconsistent performance in long-term applications. Although the brain tissue response is believed to be a major cause of performance degradation, the precise mechanisms that lead to failure of recordings are unknown. We observed persistent ED1 immunoreactivity around implanted silicon microelectrode arrays implanted in adult rat cortex that was accompanied by a significant reduction in nerve fiber density and nerve cell bodies in the tissue immediately surrounding the implanted silicon microelectrode arrays. Persistent ED1 up-regulation and neuronal loss was not observed in microelectrode stab controls indicating that the phenotype did not result from the initial mechanical trauma of electrode implantation, but was associated with the foreign body response. In addition, we found that explanted electrodes were covered with ED1/MAC-1 immunoreactive cells and that the cells released MCP-1 and TNF-α under serum-free conditions in vitro. Our findings suggest a potential new mechanism for chronic recording failure that involves neuronal cell loss, which we speculate is caused by chronic inflammation at the microelectrode brain tissue interface.
Keywords: Brain tissue; Implantation; Neuroinflammation; Neurotoxicity; Silicon

The effect of G-CSF in an experimental MRSA graft infection in mice - Agalar, C.; Eroglu, E.; Sari, M.; Sari, A.; Daphan, C.; Agalar, F. (Journal of Investigative Surgery, 2005)
Wound infection after prosthetic material implantation is a troublesome complication with an incidence of 2% to 10%. The effect of granulocyte colony-stimulating factor (G-CSF) was studied in an experimental methicillin-resistant Staphylococcus aureus (MRSA) graft infection model. Eighty adult mice were used. Under general anesthesia an abdominal incision of 2 cm in length was performed. A subcutaneous cavity of 2 × 2 cm in size was created. Polypropylene mesh pieces of 2 × 1 cm and MRSA solution of 0.1ml of 108 CFU/mL were used. G-CSF was applied systemically or locally in a dosage of 0.02 MU/30 g body weight. There were 8 groups: group I, wound + MRSA; group II, wound + mesh + MRSA; group III, wound + mesh + MRSA + G-CSF (ip, 48 h before operation); group IV, wound + mesh + MRSA + G-CSF (ip, 24 h before operation); group V, wound + mesh + MRSA + G-CSF (locally, into the cavity); group VI, wound + mesh (incubated in G-CSF solution for 4 h) + MRSA; group VII, wound + mesh + MRSA + G-CSF, ip, 24 h from operation; and group VIII (positive control group), wound + mesh + MRSA + Teicoplanin (0.03 mg/30 g body weight, ip, 1/2 h before operation). Three days after, animals were killed and incisions were examined for possible infection or abscess formation and wound failure. Meshes were removed; after vortexing and dilution, samples were incubated with 5% agar media. Results of bacterial incubation were evaluated 24 h and 48 h later. There were symptoms of wound infection and abscess formation in all groups except group VIII. In group VIII, MRSA was isolated in 7 events with a colony count below 103. Bacterial counts were above 106 (106-108) in all other groups. Thus, it was observed that wound infection could be created with this model, but G-CSF could not prevent the development of wound infection, whether it was administered systemically or locally. Teicoplanin decreased the number of colony-forming units of MRSA, and prevents wound infection in this MRSA wound infection model. Copyright © Taylor & Francis Inc.
Keywords: Foreign-body infection; G-CSF; MRSA; Teicoplanin

Effect of dietary supplementation with vitamin E and stocking density on macrophage recruitment and giant cell formation in the teleost fish, Piaractus mesopotamicus - Belo, M.A.A.; Schalch, S.H.C.; Moraes, F.R.; Soares, V.E.; Otoboni, A.M.M.B.; Moraes, J.E.R. (Journal of Comparative Pathology, 2005)
The effect of dietary supplementation with 0, 100 and 450 mg of vitamin E (DL-α tocopheryl acetate)/kg of a dry diet on the kinetics of macrophage recruitment and giant cell formation in the pacu, maintained at different stocking densities (5 kg/m3 and 20 kg/m3), was investigated by insertion of round glass coverslips into the subcutaneous connective tissue. After a feeding period of 18 weeks, the coverslips were implanted and later removed for examination at 2, 7 and 15 days post-implantation. Fish fed diets supplemented with 450 mg of vitamin E showed an increase (P<0.05) in the accumulation of macrophages, foreign body giant cells and Langhans type cells. The kinetics of macrophage recruitment and giant cell formation on the glass coverslips appeared to be strongly influenced by vitamin E supplementation, since fish fed a basal diet and held at high stocking densities showed low numbers of adhering cells on the coverslips, and high concentrations of plasma corticosteroids. On the other hand, fish given a diet supplemented with 450 mg of vitamin E did not show a similar difference in plasma cortisol concentrations related to stocking density. The effect of cortisol concentrations on carbohydrate metabolism, analysed by assessment of plasma glycaemia, was not clear. Blood glucose concentrations did not vary substantially with the different treatments examined. These results suggest that vitamin E may contribute to the efficiency of the fish's inflammatory response by increasing macrophage recruitment and giant cell formation in the foreign body granulomatous reaction. Vitamin E appeared to act on the stress response of pacus by preventing a stress-related immunosuppression. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Alpha-tocopherol; Cortisol; Fish; Piaractus mesopotamicus; Polykaryon macrophage; Vitamin E

Palmar-plantar fibromatosis in children and preadolescents: A clinicopathologic study of 56 cases with newly recognized demographics and extended follow-up information - Fetsch, J.F.; Laskin, W.B.; Miettinen, M. (American Journal of Surgical Pathology, 2005)
Palmar-plantar fibromatosis, the most common type of fibromatosis, is well recognized in the adult population, but many clinicians and pathologists are unfamiliar with the fact that children may also be affected by this process. This report describes the clinicopathologic findings in 56 cases of palmar-plantar fibromatosis in children and preadolescents. Our study group included 19 males and 37 females, ranging from 2 to 12 years of age at the time of their first surgical procedure (median age, 9 years). The patients typically presented with solitary, lobular or multilobular masses in the 0.5- to 2.5-cm size range. The preoperative duration of the lesions ranged from 1 month to 6 years, with 1 patient purportedly having clinical evidence of disease since birth. All but two of the initial lesions occurred on the plantar aspect of the feet, typically in the region of the arch. Only 2 patients presented with palmar disease. The tumors were usually painless, except when pressure was applied. Seven patients had a history of trauma, sometimes involving a foreign body. One patient presented with concurrent disease involving both feet, and 12 additional patients subsequently developed palmar-plantar fibromatosis in another extremity, knuckle pads on the hands, or had other clinical findings linked to this disease. A family history was available for 25 patients, and 11 individuals had relatives with palmar-plantar fibromatosis, and 4 others had relatives with a history that was either suspicious for palmar-plantar disease or positive for other disorders associated with this disease. Histologically, the tumors involved aponeurosis and commonly formed discontinuous, moderately cellular, nodular masses composed of spindled cells with intervening collagen. Mitotic counts for 79 separately submitted tumor specimens ranged from 0 to 31 mitotic figures per 25 wide-field high power fields (mean mitotic count, 3.4 mitotic figures per 25 wide-field high power fields). Eight tumor had ≥ 10 mitoses per 25 wide-field high power fields. All patients were initially managed by local excision, and in most of cases, histologic examination showed tumor extending to the tissue edge. Thirty-two of 38 patients (84.2%) with clinical follow-up, ranging from 4 months to 33 years (mean, 14 years 9 months; median, 16 years 1 month), had one (n = 16) or more (n = 16) local recurrence of their fibromatosis. Copyright © 2005 by Lippincott Williams & Wilkins.
Keywords: Aponeurosis; Clinodactyly; Contracture; Dupuytren's disease; Epilepsy; Fibroma; Fibromatosis; Foot; Hand; Keloid; Ledderhose's disease; Palmar; Plantar; Soft tissue tumor; Superficial fibromatosis

Patient care. The right count. - Dalton, A. (Hospitals & health networks / AHA, 2005)

Inflammatory response to peritoneal implantation of alginate-poly-L-lysine microcapsules - Robitaille, R.; Dusseault, J.; Henley, N.; Desbiens, K.; Labrecque, N.; Hallé, J.-P. (Biomaterials, 2005)
A thorough understanding of the mechanisms involved in the host reaction to alginate-poly-l-lysine microcapsules (HRM) is important to design methods for the evaluation, selection, and development of biocompatible biomaterials and microcapsules or treatments to control this reaction. The objective of this study was to identify those immune cells and cytokines involved in the pathogenesis of the HRM. The total and differential cell counts were evaluated, and the mRNA expression of TNF-α, IL-1β, IL-6 and TGF-β1 was measured in peritoneal washings at 3, 17, 48, 96 and 168 h after saline or microcapsule injections. Neutrophil number and IL-1β and IL-6 m-RNA expression presented an early transient increase, with no differences between saline and microcapsule injections, suggesting a reaction to the procedure. Macrophages, lymphocytes and TNF-α were significantly more activated over a longer period of time, after microcapsule implantation than saline injection. They are likely involved in transforming the reaction into a chronic inflammatory process. TGF-β1 and IL-1β presented a late (day 7) significant increase after microcapsule but not saline injections. They are likely involved in transforming the reaction into a fibrogenic process. These results suggest that macrophages, lymphocytes, TNF-α, IL-1β and TGF-β1 play a role in the pathogenesis of the HRM. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Biocompatibility; Cytokine; Interleukin; Macrophage; Microcapsule; TGF

Healing of PTFE grafts in a pig model recruit neointimal cells from different sources and do not endothelialize - Mellander, S.; Fogelstrand, P.; Enocson, K.; Johansson, B.R.; Mattsson, E. (European Journal of Vascular and Endovascular Surgery, 2005)
Objectives. The aim of this study was to analyze the cellular sources for the neointima and the cell type that is lining the lumen in artificial grafts implanted in pigs. Materials and methods. We used polytetrafluoroethylene grafts as bypasses from the common to the external iliac arteries. The animals were sacrificed after 1, 4, 7, 14, 21, 30, 60 and 90 days. Morphological, immunohistochemical and electron microscope assessments were made. Results. After 7 days a circumferential neoadventitia was formed. At day 14 isolated cellular islets of proliferating cells were observed on the luminal side of the graft without connection to the neoadventitia or the adjacent arteries. In the anastomotic regions at day 14 we observed an isolated neointima in contact with the adjacent artery. The cells lining the lumen had characteristics of both smooth muscle cells and endothelial cells. Conclusions. Our study suggests that in artificial porcine grafts, the perivascular tissue, the blood and the adjacent artery contribute to the formation of the neointima. The luminal surface is covered by a hybrid cell with both smooth muscle cell and endothelial cell properties. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Cellular sources; Hybrid cell; Neointima; Pig; PTFE graft

Tissue reactions of in situ formed dextran hydrogels crosslinked by stereocomplex formation after subcutaneous implantation in rats - Bos, G.W.; Hennink, W.E.; Brouwer, L.A.; Den Otter, W.; Veldhuis, T.F.J.; Van Nostrum, C.F.; Van Luyn, M.J.A. (Biomaterials, 2005)
In this study, the in vivo biocompatibility of physically crosslinked dextran hydrogels was investigated. These hydrogels were obtained by mixing aqueous solutions of dextran grafted with l-lactic acid oligomers and dextran grafted with d-lactic acid oligomers. Gelation occurs due to stereocomplex formation of the lactic acid oligomers of opposite chirality. Since gelation takes some time, in situ gel formation is possible with this system. A number of sterilization methods was evaluated for their effect on the chemical and physical properties of the hydrogel. It was shown that of the investigated options (filtration, gamma irradiation, dry-heat and autoclaving) dry-heat sterilization was the preferred method to prepare sterile gels suitable for in vivo evaluations. Two types of stereocomplex gels were prepared and implanted subcutaneously in rats. The tissue reaction was evaluated over a period of 30 days. A mild ongoing foreign body reaction was observed characterized by infiltration of macrophages. Giant cells were only scarcely formed and the low numbers of lymphocytes showed that priming of the immune system is hardly involved. Importantly, the gels fully degraded in vivo within 15 days, which is in good agreement with the in vitro degradation behaviour of these gels. In conclusion, stereocomplexed dextran-oligolactic gels showed good biocompatibility which makes them suitable candidates for the design of controlled release devices for pharmaceutically active proteins. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Biocompatibility; Dextran; Drug delivery; Hydrogel; In situ gelation; Stereocomplex; Tissue reactions

Embedded weapons-grade tungsten alloy shrapnel rapidly induces metastatic high-grade rhabdomyosarcomas in F344 rats - Kalinich, J.F.; Edmond, C.A.; Dalton, T.K.; Mog, S.R.; Coleman, G.D.; Kordell, J.E.; Miller, A.C.; McClain, D.E. (Environmental Health Perspectives, 2005)
Continuing concern regarding the potential health and environmental effects of depleted uranium and lead has resulted in many countries adding tungsten alloy (WA)-based munitions to their battlefield arsenals as replacements for these metals. Because the alloys used in many munitions are relatively recent additions to the list of militarily relevant metals, very little is known about the health effects of these metals after internalization as embedded shrapnel. Previous work in this laboratory developed a rodent model system that mimicked shrapnel loads seen in wounded personnel from the 1991 Persian Gulf War. In the present study, we used that system and male F344 rats, implanted intramuscularly with pellets (1 mm × 2 mm cylinders) of weapons-grade WA, to simulate shrapnel wounds. Rats were implanted with 4 (low dose) or 20 pellets (high dose) of WA. Tantalum (20 pellets) and nickel (20 pellets) served as negative and positive controls, respectively. The high-dose WA-implanted rats (n = 46) developed extremely aggressive tumors surrounding the pellets within 4-5 months after implantation. The low-dose WA-implanted rats (n = 46) and nickel-implanted rats (n = 36) also developed tumors surrounding the pellets but at a slower rate. Rats implanted with tantalum (n = 46), an inert control metal, did not develop tumors. Tumor yield was 100% in both the low- and high-dose WA groups. The tumors, characterized as high-grade pleomorphic rhabdomyosarcomas by histopathology and immunohistochemical examination, rapidly metastasized to the lung and necessitated euthanasia of the animal. Significant hematologic changes, indicative of polycythemia, were also observed in the high-dose WA-implanted rats. These changes were apparent as early as 1 month postimplantation in the high-dose WA rats, well before any overt signs of tumor development. These results point out the need for further studies investigating the health effects of tungsten and tungsten-based alloys.
Keywords: Cobalt; Embedded fragment; Nickel; Rat; Rhabdomyosarcoma; Tungsten; Tungsten alloy

Encapsulating peritonitis and familial Mediterranean fever - Dabak, R.; Uygur-Bayramiçli, O.; Aydin, D.K.; Dolapçioglu, C.; Gemici, C.; Erginel, T.; Turan, C.; Karadayi, N. (World Journal of Gastroenterology, 2005)
Aim: To investigate the relationship between encapsulating peritonitis and familial Mediterranean fever (FMF). Methods: The patient had a history of type 2 diabetes and laparoscopic cholecystectomy was performed one year ago for cholelithiasis. Eleven months after the operation she developed massive ascites. Biochemical evaluation revealed hyperglycemia, mild Fe deficiency anemia, hypoalbuminemia and a CA-125 level of 2 700 IU. Ascitic evaluation showed characteristics of exudation with a cell count of 580/mm3. Abdominal CT showed omental thickening and massive ascites. At exploratory laparotomy there was generalized thickening of the peritoneum and a laparoscopic clip encapsulated by fibrous tissue was found adherent to the uterus. Biopsies were negative for malignancy and a prophilactic total abdominal hysterectomy and bilateral salpingooophorectomy were performed. Results: The histopathological evaluation was compatible with chronic nonspecific findings and mild mesothelial proliferation and chronic inflammation at the uterine serosa and liver biopsy showed inactive cirrhosis. Conclusion: The patient was evaluated as sclerosing encapsulating peritonitis induced by the laparoscopic clip acting as a foreign body. Due to the fact that the patient had FMF the immune response was probably exaggerated. © 2005 The WJG Press and Elsevier Inc. All rights reserved.
Keywords: Ascites; Encapsulating peritonitis; Familial Mediterranean fever

Small-bowel perforation caused by fish bone - Hsu, S.-D.; Chan, D.-C.; Liu, Y.-C. (World Journal of Gastroenterology, 2005)
A diagnosis of small-bowel perforation, caused by a sharp or pointed foreign body, is rarely made preoperatively because the clinical symptoms are usually nonspecific and can mimic other surgical conditions, such as appendicitis and diverticulitis. We report the case of a 62-year-old woman who experienced severe pain in the right iliac fossa and fever for about five days before arrival at our hospital. The presumptive diagnosis was acute purulent appendicitis and an emergency appendectomy was planned. Swelling and erythema were noted in a segment of the small bowel in the lower right abdomen. A tiny pointed object was found penetrating the inflamed portion of the bowel, which proved to be a sharp fish bone (gray snapper). The bone was removed, followed by segmental resection of the terminal ileum and ascending colon. The postoperative course was uneventful. © 2005 The WJG Press and Elsevier Inc. All rights reserved.
Keywords: Fish bone; Small-bowel perforation

Extraprostatic seed placement and its effect on seed loss - Nedea, E.; Wallner, K.; Reed, D.; Ford, E.; Sutlief, S.; Mueller, A.; Maki, J.; Merrick, G. (Cancer Journal, 2005)
PURPOSE: The purpose of this study was to examine the relationship between extraprostatic seed placement and seed loss in a cohort of patients who had underwent both computed tomographic (CT) and magnetic resonance (MR) scans at day 0 and day 30 following brachytherapy. MATERIALS AND METHODS: Twenty-two patients with 1997 AJC clinical stage T1-T2 prostatic carcinoma were implanted with nonstranded I 125. Patients were selected solely by having a prostate volume between 15 and 60 cc and a willingness to return for 30-day follow-up CT and MR scans. The total number of I-125 sources implanted on day 0 ranged from 50 to 104 (median: 70). Preplan treatment planning methods have been previously described in detail: a modified peripheral loading pattern and treatment margins of 5-10 mm were used. Noncontrast postimplantation CT and MR scans were obtained 1-4 hours after implantation on day 0. The total seed count on days 0 and 30 was verified by plain radiograph. Pelvic MR (T1) images were registered with the CT images in the Varian planning system, using bony landmarks. The number of extracapsular seeds in each quadrant of the circumference was then totaled for each patient. A second set of plain radiographs (for seed counting), as well as CT and MR scans, were obtained 30 days after implantation (day 30) and were similarly analyzed. RESULTS: The number of extraprostatic seeds at day 0 ranged from 13 to 35, making up 17%-48% (median: 34%) of the total number implanted. Of the 22 patients, 10 lost one or more seeds between the implantation day and the 1-month follow-up. The mean number of seeds lost was 1.1 (± 1.7). There was no apparent relationship between the percent of extraprostatic seeds and the number of seeds lost. There was no apparent relationship between seed loss and number of seeds less than 3 mm or greater than 3 mm from the prostatic capsule. CONCLUSIONS: We have shown here that with CT and MR seed localization, extraprostatic seed placement does not appear to substantially increase the likelihood of seed loss after the procedure. Copyright © 2005 Jones and Bartlett Publishers, Inc.
Keywords: Brachytherapy; CT; MR; Prostate cancer

Tuberculosis verrucosa cutis: Antitubercular therapy, a well-conceived diagnostic criterion - Sehgal, V.N.; Sardana, K.; Bajaj, P.; Bhattacharya, S.N. (International Journal of Dermatology, 2005)
A 39-year-old housewife sustained inadvertent trauma to the right index finger about 6 years ago, whilst stitching clothes. A couple of weeks later, the site of trauma became hard and gritty. Ever since, it has progressed slowly, without any appreciable outward sign. It was not associated with any discomfort /pain. Consequent on an opinion from a surgeon, it was decided to operate on the right index finger. During the operation, under local anesthesia, a hard and gritty material was removed. The material was subjected to histopathologic study. Several stitches were applied to the wound. It failed to respond to antimicrobial therapy over a 4-week period, prompting the patient to seek another opinion. Examination of the skin surface revealed a plaque with an irregular configuration on and around the distal interphalangeal joint of the right index finger. It was erythematous and pigmented. The top of the plaque was irregular and had alternating elevations and depressions (Fig. 1). Diascopy was negative for apple jelly nodule. A bacillus Calmette-Guérin (BCG) vaccination scar was identified on the left deltoid. There was no regional lymphadenopathy or systemic abnormality. Mantoux test with intradermal injection of 0.1 mL SPAN's tuberculin (purified protein derivative/5 tuberculin units/0.1 mL) (Span Diagnostic Ltd., Murat, India) was negative after 72 h. Investigations, including total and differential leukocyte count, erythrocyte sedimentation rate, serum biochemistry, and renal and liver function tests, were within the normal range, as was a chest X-ray. Hematoxylin and eosin-stained sections prepared from the biopsy taken from the lesion revealed noteworthy changes in the epidermis and the dermis. The former was marked by the presence of hyperkeratosis, acanthosis, and papillomatosis, whilst the latter contained tubercle granulomas. Each of the granulomas was well formed and consisted of large numbers of lymphocytes, histiocytes, and foreign body (Langerhans') giant cells (Fig. 2). Caseation necrosis and acid-fast bacilli could not be demonstrated. The preceding revelations were fairly conducive to the diagnosis. Accordingly, antitubercular therapy (ATT), comprising 450 mg of rifampicin, 300 mg of isonicotinic acid hydrazide, and 800 mg of ethambutol, was recommended for oral administration each day for 60 days. The outcome of the treatment was satisfactory, resulting in perceptible regression of the skin lesion (Fig. 1b). The patient was advised to continue the treatment for another 30 days, after which 450 mg of rifampicin and 300 mg of isonicotinic acid hydrazide were to be continued for another 6 months. © 2004 The International Society of Dermatology.

Neuroprotective effect of subretinal implants in the RCS rat - Pardue, M.T.; Phillips, M.J.; Yin, H.; Sippy, B.D.; Webb-Wood, S.; Chow, A.Y.; Ball, S.L. (Investigative Ophthalmology and Visual Science, 2005)
PURPOSE. Retinal prosthetics have been designed to interface with the neural retina by electrically stimulating the remaining retinal circuits after photoreceptor degeneration. However, the electrical stimulation provided by the subretinal implant may also stimulate neurotrophic factors that provide neuroprotection to the retina. This study was undertaken to determine whether electrical stimulation from a subretinal photodiode-based implant has a neuroprotective effect on photoreceptors in the. RCS rat, a model of photoreceptor degeneration. METHODS. Eyes of RCS rats were implanted with an active or inactive device or underwent sham surgery before photoreceptor degeneration. Outer retinal function was assessed with electroretinogram (ERG) recordings weekly until 8 weeks after surgery, at which time retinal tissue was collected and processed for morphologic assessment, including photoreceptor cell counts and retinal layer thickness. RESULTS. At 4 to 6 weeks after surgery, the ERG responses in the active-implant eyes were 30% to 70% greater in b-wave amplitude than the response from eyes implanted with inactive devices those undergoing sham surgery, or the nonsurgical control eyes. At 8 weeks after surgery the ERG responses from active-implant eyes were not significantly different from the control groups. However, the number of photoreceptors in eyes implanted with the active or inactive device was significantly greater in the regions over and around the implant versus sham-surgical and non-surgical and nonsurgical control eyes. Conclusions: These results suggest that subretinal electrical stimulation provides temporary preservation of retinal function in the RCS rat. In addition, implantation of an active or inactive device into the subretinal space causes morphologic preservation of photoreceptors in the RCS rat until 8 weeks after surgery. Further studies are needed to determine whether the correlation of neuropreservation with subretinal implantation is due to electrical stimulation and/or a mechanical presence of the implant in the subretinal space.

In vivo cytokine secretion and NF-κB activation around titanium and copper implants - Suska, F.; Gretzer, C.; Esposito, M.; Emanuelsson, L.; Wennerberg, A.; Tengvall, P.; Thomsen, P. (Biomaterials, 2005)
The early biological response at titanium (Ti), copper (Cu)-coated Ti and sham sites was evaluated in an in vivo rat model. Material surface chemical and topographical properties were characterized using Auger electron spectroscopy, energy dispersive X-ray spectroscopy and interferometry, respectively. The number of leukocytes, cell types and cell viability (release of lactate dehydrogenase) were determined in the implant-interface exudate. The contents of activated nuclear transcription factor NF-κB, interleukin-6 (IL-6) and interleukin-10 (IL-10) were determined by enzyme linked immunosorbent assay. An increase in the number of leukocytes, in particular, polymorphonuclear leukocytes, was observed between 12 and 48h around Cu. A marked decrease of exudate cell viability was found around Cu after 48h. The total amounts of activated NF-κB after 12h was highest in Ti exudates whereas after 48h the highest amount of NF-κB was detected around Cu. The levels of cytokine IL-6 were consistently high around Cu at both time periods. No differences in IL-10 contents were detected, irrespective of material/sham and time. The results show that materials with different toxicity grades (titanium with low and copper with high toxicity) exhibit early differences in the activation of NF-κB, extracellular expression and secretion of mediators, causing major differences in inflammatory cell accumulation and death in vivo. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Copper; Cytokine; Inflammation; Titanium

Retained surgical sponges (gossypiboma) - Bani-Hani, K.E.; Gharaibeh, K.A.; Yaghan, R.J. (Asian Journal of Surgery, 2005)
OBJECTIVE: Retained surgical sponges are seldom reported due to medicolegal implications. Awareness of this problem among surgeons and radiologists is essential to avoid unnecessary morbidity. We present our experience with this entity and review the related literature. METHODS: The medical records of 11 patients who were diagnosed as having retained surgical sponges from 1990 to 2003 were reviewed. RESULTS: The incidence was 1:5,027 inpatient operations. There were four males and seven females with a median age of 45 years. The original operations were gynaecological (n = 4), general (n = 4), urological (n = 2) and laminectomy (n = 1). In seven cases, the original operation was performed on an emergency basis. Five patients were obese. A presumed correct sponge count was documented in eight cases. The median time between the original procedure and diagnosis of retained sponges was 12 months. The tentative diagnosis was intestinal obstruction (4 patients), urinary tract infection (1 patient), Crohn's disease (1 patient) and tumour recurrence (1 patient). The correct diagnosis was suggested in the remaining four patients. Surgical removal of the retained sponges was carried out in all cases except one, in which the patient passed the sponge spontaneously through the rectum. CONCLUSION: Retained sponges are more common in obese patients and after emergency surgery. A high degree of suspicion is important for preoperative diagnosis. Despite the use of radio-opaque sponges and thorough sponge counting, this moribund mishap still occurs. Although human errors cannot be completely abolished, continuous medical training and strict adherence to regulations should reduce the incidence to a minimum. © 2005 Elsevier. All rights reserved.
Keywords: Gossypiboma; Retained surgical sponge; Retained surgical swab; Textiloma

Complications of missile craniocerebral injuries during the Croatian Homeland War - Tudor, M.; Tudor, L.; Tudor, K.I. (Military Medicine, 2005)
Objective: Complications of penetrating craniocerebral injuries in war can be early (during the first week after wounding) or late (after that period). Postoperative hematomas, infections, seizures, and cerebrospinal fluid fistulas (CSFFs) are counted among the early complications, whereas foreign bodies migrating intracranially, seizures, infections, and posttraumatic hydrocephalus represent late complications. A total of 176 patients with well-defined head injuries from missiles, sustained during the Croatian Homeland War (1991-1995), developed a total of 61 (34.5%) complications. Methods: A retrospective statistical analysis of the medical records of the patients in our series was performed to determine the risk factors for the onset of complications, which have unfavorable effects on outcomes. Results: There were a total of 28 (15.9%) infections (deep or superficial), 21 (11.9%) cases of CSFFs, 9 (5.11%) cases of early epilepsy, and 3 cases of post-traumatic hydrocephalus. A total of 47.6% of patients with CSFFs developed intracranial infections. Of eight patients with meningoencephalitis, five had CSFFs and four had intracranially retained foreign bodies. Only one patient developed a cerebral abscess. Two patients died because of infectious complications (13.3%). Post-traumatic hydrocephalus (1.7%) required shunt placement. For 60% of patients with deep-seated intracranial infectious complications and 76% of patients with CSFFs, reoperations had to be performed, whereas this was the case for only 8% of patients without infections (χ2 = 43.6, p = 0.00001). Conclusions: Intracranially retained foreign bodies, wound age, wound site, and operations performed outside the neurosurgical services were the main risk factors for the development of complications. Complications themselves exerted a very unfavorable influence on outcomes. The development of complications reflects very reliably the neurosurgical technique applied.

Effects of membrane adhesion barriers on wound healing reaction after glaucoma filtration surgery: A comparative study with Interceed and Seprafilm - Akyol, N.; Aydogan, S.; Akpolat, N. (European Journal of Ophthalmology, 2005)
PURPOSE. To evaluate and compare the effectiveness of two adhesion barriers, Interceed and Seprafilm, on wound healing reaction after glaucoma filtration surgery. MATERIALS AND METHODS. Full-thickness filtration surgery was carried out on three groups, each containing four rabbits. Interceed and Seprafilm prepared in 3x4 mm dimensions was put on and around scleral opening in Groups 1 and 2, respectively. All groups received tobramycin and dexamethasone drops tid for 14 days. Intraocular pressure (IOP), anterior chamber depth, and bleb appearance were checked on the first, third, seventh, and 14th days. The rabbits were killed on the 14th day and the trabeculectomy area with overlying conjunctiva was excised. The samples were fixed with 10% formalin, buried in paraffin, and stained with hematoxylin and eosin. The surgical site and surrounding subconjunctival area were evaluated histopathologically for cell counts (fibroblast, lymphocyte, eosinophil, and macrophage), presence of edema and foreign body reaction, and potency of the fistula tract. RESULTS. Mean IOP at the first and third day examinations was significantly different between groups, but there was no statistically significant difference among the groups with respect to IOP, anterior chamber depth, or bleb appearance at the seventh and 14th days. The groups were similar with respect to number of fibroblasts, eosinophils, and neutrophils. Number of macrophages was significantly increased in Groups 1 and 2 and number of vessels was significantly decreased in Group 1. CONCLUSIONS. Neither of these two adhesion-preventing substances seems to suppress wound healing reaction after glaucoma filtration surgery. However, a diminished wound healing reaction was expected with a decreased number of vessels, such as in Group 1. Increased number of macrophages in both groups may result in a decreased level of some inflammatory mediators. © Wichtig Editore, 2005.
Keywords: Filtration surgery; Interceed; Seprafilm; Wound healing

Histological evaluation of scar tissue inflammatory response: The role of hGH in diabetic rats - García-Esteo, F.; Pascual, G.; García-Honduvilla, N.; Gallardo, A.; San-Román, J.; Bellón, J.M.; Buján, J. (Histology and Histopathology, 2005)
This paper describes a polymer site-specific delivery system containing human growth hormone in an in vivo model of scarring in the diabetic state. Copolymer discs with the hormone were introduced into incisions made in rats previously injected with streptozotocin in order to induce diabetes. Tissue specimens for evaluation were obtained at 3, 7 or 10 days after the procedure. Study groups were healthy rats and diabetic rats untreated or treated with/without the hormone. Histological sections were prepared for light microscopy examination of wound zones. Three and 7 days after surgery, polymer remains could be observed in the subcutaneous tissue. These remnants induced a moderate foreign body reaction. The number of macrophages detected was directly related to neovessel formation and metalloelastase expression. The CD4+/CD8+ ratio was low during the initial follow up stages (3 and 7 days) in untreated diabetic rats, yet an increased ratio corresponding to areas around the polymer remains was noted in the animals treated with copolymer loaded with the growth hormone. Copolymer is biodegradable in vivo and may be used as a vehicle for the slow release of active substances. The presence of the hormone at the site of skin injury induces cell proliferation and enhances the repair process.
Keywords: Diabetes; Drug delivery; Growth factor; Immune response; Wound healing

Successful removal of bovine pericardium by bronchoscope after lung volume reduction surgery - Iwasaki, A.; Yoshinaga, Y.; Shirakusa, T. (Annals of Thoracic Surgery, 2004)
We report on a patient in whom, 10 months after lung volume reduction surgery, bovine material visibly migrated to the bronchial lumen. In this particular case, bronchoscopic treatment was successful. The patient remained well 12 months after such treatment. The report also suggests that the alternative use of absorbable material will reduce later postoperative complications. © 2004 by The Society of Thoracic Surgeons.
Keywords: 11

A case of fish bone perforation of the stomach mimicking a locally advanced pancreatic carcinoma - Goh, B.K.P.; Jeyaraj, P.-R.; Chan, H.-S.; Ong, H.-S.; Agasthian, T.; Chang, K.T.E.; Wong, W.-K. (Digestive Diseases and Sciences, 2004)
Keywords: Fish bone; Pancreas; Pancreatic carcinoma; Pancreatic mass; Perforation

Biocompatibility and tissue interactions of a new filler material for medical use - Zarini, E.; Supino, R.; Pratesi, G.; Laccabue, D.; Tortoreto, M.; Scanziani, E.; Ghisleni, G.; Paltrinieri, S.; Tunesi, G.; Nava, M. (Plastic and Reconstructive Surgery, 2004)
Filler materials for medical use present limits, such as the induction of chronic inflammation and fibrosis. In the search for synthetic materials with improved biocompatible properties, a new polyacrylamide hydrogel, Aquamid (Contura SA, Montreux, Switzerland), has been investigated in preclinical systems. In cell cultures (endothelial cells and fibroblast), no or only transient biological effects were associated with 10% Aquamid exposure. The Aquamid-host interactions were examined in mice (10 mice per group) implanted subcutaneously or in the mammary fat pad with a very large volume (1.5 ml) of the material. Blood analysis, performed after 15 and 94 days (five mice per time for each group) to detect acute or late manifestations of toxicity, did not reveal relevant abnormalities in either group of Aquamid-bearing mice compared with control mice, except for a transient thrombocytopenia and a mild leukocytosis. Histological analysis of the pellet showed the presence of a thin, poorly vascularized cyst wall in implants. Only mild mesenchymal reparative and inflammatory processes were observed, even at longer observation times (more than 400 days). No alterations in any organ were detected. Despite the large volume implanted (approximately 5 percent of mouse body weight), the Aquamid pellet maintained its original size and shape without spreading or sticking to surrounding tissues. In conclusion, the study indicated a good tolerability of the new biopolymer in preclinical systems. The clinical utility of this new compound, if confirmed by clinical randomized trials showing its atoxic properties, could be in the field of aesthetic plastic surgery as a filler material for body contouring and in reconstructive surgery and above all in cancer patients to restore surgical defects.

Failure of acromioclavicular reconstruction using Gore-Tex graft due to aseptic foreign-body reaction and clavicle osteolysis: A case report - Stewart, A.M.; Ahmad, C.S. (Journal of Shoulder and Elbow Surgery, 2004)

The role of implant alignment on stability and particles on periprosthetic osteolysis - A rabbit model of implant failure - Fornasier, V.L.; Goodman, S.B.; Protzner, K.; Kamel, M.; Song, Y.; Shojaci, A. (Journal of Biomedical Materials Research - Part B Applied Biomaterials, 2004)
The study objective was to determine the tissue response to polyethylene and/or titanium particles and the role that these play in peri-prosthetic osteolysis in a rabbit model of implant failure. Twenty-two mature rabbits were used. Unilateral tibial arthroplasty was performed on all of them. The test animals received implants that were intentionally rotationally unstable with reference to the host tibia in order to create a model of failure. The test rabbits were divided into three groups. Group 1 consisted of seven rabbits in which only the carrier was implanted. Group 2 consisted of seven rabbits that received only polyethylene particles suspended in the carrier. Group 3 consisted of eight rabbits that received a mixture of polyethylene and titanium alloy particles suspended in the carrier. The rabbits were sacrificed at 6 months post surgery. The entire knee, together with the immediately surrounding soft tissue, was retrieved. The position of the implant in each rabbit was assessed with reference to its alignment to the tibia. The number of inflammatory, foreign-body reactive cells, the presence of neovascularization, edema, and necrosis in the periprosthetic zones were recorded and assessed in a qualitative and semiquantitative manner. Quantitative histomorphometry was used to determine the proportion of implant surface that interfaced with osseous or fibrous tissue. Also assessed was the thickness and maturity of the fibrous tissue and the endosteal remodeling activity in the peri-implant bone counting both osteoclastic and osteoblastic activity. The results showed that implanted particles and misalignment of the implants combined to produce peri-prosthetic bone resorption. Bone resorption was found to be proportional to the degree of misalignment. The animals that received combined polyethylene/titanium particles had a greater degree of foreign-body and inflammatory response with osteolysis than the other groups. The combination of bio-material particles (polyethylene and titanium alloy) produced a greater degree of bone resorption than the single biomaterial particles (polyethylene). The amount of bone resorption surrounding the implant was directly proportional to the degree of misalignment of the implant. © 2004 Wiley Periodicals, Inc.

A proactive treatment approach for eyes with perforating injury - Kuhn, F.; Mester, V.; Morris, R. (Klinische Monatsblatter fur Augenheilkunde, 2004)
Background: Perforating injuries continue to have a poor prognosis with less than two-thirds of eyes having at least ambulatory final vision, due to proliferation originating from the exit wound. Materials and Methods: We developed a new, proactive treatment method, which is applicable in most eyes with perforating trauma. The strategy involves limited, indirect ophthalmoscopic vitrectomy during the primary repair; heavy topical corticosteroid therapy postoperatively; and complete vitrectomy on day 3, including prophylactic retinectomy around the exit wound, evacuation of subretinal blood, laser retinopexy, and silicone oil implantation. Results: In the five consecutive eyes in which the proactive treatment approach was used, no " enscarceration" of the retina into the exit wound, proliferative vitreoretinopathy, retinal detachment, or retinal folding has occurred. The median visual acuity improved from count fingers to 0.6 in the three eyes without macular involvement. Conclusions: Far-reaching conclusions must not be made based on such a small series, but the proactive treatment approach appears promising in preventing proliferation-related complications such as fractional retinal detachment or retinal fold development. A similar approach should be considered for eyes with deep impact trauma from intraocular foreign bodies and in eyes with incarcerated retina in the rupture wound.
Keywords: Eye injuries; Intraocular foreign bodies; Perforating injury; Prevention; Proliferative vitreoretinopathy; Retinectomy

Biocompatible features of chitosan in brain tissues - Zhou, T.; Zhou, B.; Huang, S.-L. (Chinese Journal of Clinical Rehabilitation, 2004)
Background: The biocompatibility of chitosan in common tissues has already been proved. However, there are few reports on the biocompatible features of it in brain tissues. Objective: To explore the biocompatibility of chitosan in brain tissues in order to provide slow released macromolecule carrier for clinically used chemotherapy. Design: Randomized controlled study. Setting and participants: Experiment site: Operation room of experiment centre, Wuhan University. Thirty-two SD rats were chosen and divided into experimental group and control group by simple random method. Methods: Chitosan and gelfoam were implanted into rats' skull by operation. Then observed the behavior changes and local histologic reaction in the 3rd, 7th, 14th and 30th day (haematoxylin-eosin dye). Main outcome measures: Inflammatory cells counting of different materials in different stages. Results: There was no obvious behavior change of all rats. The histological reactions in the 3rd, 7th, 14th, 30th day were similar with the foreign body reaction caused by gelfoam. There was significant difference on counting of neutrophilic granulocyte and lymphocyte between experimental group and control group within the 3 mm area of implanted materials in the 7th day(t = 6.98, 3.311, P = 0.001, 0.019). There was also significance difference on those cell counting between two groups in the 14th day (t = 6.454, 4.899, P = 0.001, 0.003). In the 30th day, there was difference on counting of lymphocyte and fibrocyte between two groups (t = 3.767, 5.019, P = 0.010, 0.006). Conclusion: There is very good biocompatibility of chitosan with brain tissue. It can be degraded safely.

Decrease in particle-induced osteolysis in obese (ob/ob) mice - Von Knoch, M.; Jewison, D.E.; Sibonga, J.D.; Turner, R.T.; Morrey, B.F.; Loer, F.; Berry, D.J.; Scully, S.P. (Biomaterials, 2004)
There may be variability in the susceptibility of different individuals to osteolysis from wear debris, and it is not clear whether some individuals may have a genetic predisposition for a more marked osteolytic response. The purpose of this study in mice was to determine whether genetically determined obesity can alter the response to particulate debris. Polyethylene particles were implanted onto the calvaria of seven wild-type mice and seven obese mice (ob/ob). Calvaria from unimplanted wild-type and obese mice served as controls. Calvaria were harvested after 7 days, stained with toluidine blue and for tartrate-specific alkaline phosphatase, and analyzed by histomorphometry. The osteoclast number per mm total bone perimeter was 8.000±3.464 in wild-type animals with particles and 2.857±1.676 in ob/ob animals with particles (p=0.0002; Fisher's PLSD). Bone resorption was 1.895±0.713mm/ mm2 in wild-type animals with particles and 1.265±0.494mm/ mm2 in ob/ob animals with particles (p=0.0438; Fisher's PLSD). Particles induced a diminished osteolytic response in genetically determined obese mice, suggesting that obesity may have a protective role against particle-induced bone resorption - similar to obesity and osteoporosis. These important new findings may help to stimulate clinical studies which may define criteria to better identify patients at risk to develop particle-induced osteolysis. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Osteoclast; Osteolysis; Particulates; Polyethylene; Wear debris

Retained IOL fragment and corneal decompensation after pseudophakic IOL exchange - Hoffman, R.S.; Fine, I.H.; Packer, M. (Journal of Cataract and Refractive Surgery, 2004)
A 72-year-old man had exchange of a foldable silicone multifocal intraocular lens (IOL) by transection, removal, and monofocal IOL replacement. One month after the exchange, irreversible corneal edema developed and penetrating keratoplasty was performed. At the time of the corneal transplant, a small silicone fragment was discovered in and removed from the anterior chamber. Histologic evaluation of the patient's cornea demonstrated an absence of corneal endothelium, suggesting the fragment was the etiology of the corneal decompensation. © 2004 ASCRS and ESCRS.

Uveal and capsular biocompatibility of a single-piece, sharp-edged hydrophilic acrylic intraocular lens with collagen (Collamer) 1-year results - Schild, G.; Amon, M.; Abela-Formanek, C.; Schauersberger, J.; Bartl, G.; Kruger, A. (Journal of Cataract and Refractive Surgery, 2004)
Purpose: To analyze uveal and capsular biocompatibility 1 year following implantation of a sharp-edged, hydrophilic, collagen-containing posterior chamber intraocular lens (IOL). Setting: Department of Ophthalmology, University of Vienna Medical School, Vienna, Austria. Method: In a prospective study, a Collamer CC4204BF IOL was implanted in 30 eyes of patients with senile cataract. A standardized surgical technique and postoperative regimen were applied. To assess uveal biocompatibility, cellular inflammation on the anterior IOL surface was evaluated with a specular microscope. Capsular biocompatibility was registered semiquantitatively with a biomicroscope, based on an assessment of fibrosis on the anterior and posterior capsules. Tyndall values were measured with the Kowa FC-1000 laser flare-cell meter. Decentration of the lens was also registered. Results: One year after implantation, the values of flare and cell count in the anterior chamber were lower than preoperatively. Round and spindle-shaped, epithelioid, and foreign-body giant cells were not found on the anterior surface of the IOL. The capsulorhexis rim was moderately fibrosed in 56.6% of cases. Fibrosis of the capsule over the optic was also moderate in 36.6%. The central portion of the posterior capsule was devoid of fibrosis in 43.3% and mildly fibrosed in 50%. Three lenses revealed outgrowth of lens epithelial cells to the anterior surface of the IOL. A neodymium:YAG capsulotomy had to be performed in 1 case. All lenses were well centered in the capsular bag 1 year after implantation. Conclusions: The absence of inflammatory cells on the anterior surface of the IOL indicates the high uveal biocompatibility of the lens. In terms of capsular biocompatibility, the results were satisfactory. © 2004 ASCRS and ESCRS.

Migration of Polyethylene Particles Around Nonloosened Cemented Femoral Components from a Total Hip Arthroplasty - An Autopsy Study - Massin, P.; Chappard, D.; Flautre, B.; Hardouin, P. (Journal of Biomedical Materials Research - Part B Applied Biomaterials, 2004)
Three cemented femoral components from total hip arthroplasties retrieved at autopsy were examined in regard to the migration of birefringent polyethylene particles across the fixation interfaces. They were obtained from two patients who died from unrelated causes. They had been in place, respectively, for 8 and 9 years (first patient) and for 9 years (second patient). Osteolysis was present in the acetabular side only. The femoral components were not loosened. Histologic sections were performed at four levels of the femoral components, and polyethylene particles were counted with the use of a semiautomatic image analyzer. Sections below the tip of the stem were treated by deorganification and the lysate was centrifuged in the attempt to isolate wear debris. Particles were found at both interfaces (bone-cement and metal-cement) and in the cancellous bone between the trabeculae. They were also present in the Haversian canals of the cortical bone. Particles of various sizes were found in the medullary canal beneath the tip of the stem. In scanning electron microscopy, they appeared to have irregular shapes. Wear debris can migrate across the cement-bone interface of nonloosened implants. They appear to progress through the porosity of the cancellous bone. © 2004 Wiley Periodicals, Inc.
Keywords: Foreign body response; Hip replacement prosthesis; Osteolysis; Polyethylene; Wear debris

Long-term complications of bilateral posterior chamber phakic intraocular lens implantation - Mastropasqua, L.; Toto, L.; Nubile, M.; Falconio, G.; Ciancaglini, M. (Journal of Cataract and Refractive Surgery, 2004)
A 34-year-old woman had posterior chamber phakic intraocular lens (PCP IOL) implantation to correct high myopia in both eyes. Five years postoperatively, the patient presented with a decrease in visual acuity from central anterior subcapsular cataract formation in both eyes and IOL dislocation in the left eye. In vivo confocal microscopy of the cornea showed markedly decreased endothelial cell density in both eyes and the presence of bright endothelial microdeposits possibly related to pigmentary dispersion. Gonioscopy showed angle pigmentary deposits with no intraocular pressure increase. The patient was successfully treated by removing the PCP IOLs and performing phacoemulsification with in-the-bag IOL implantation in both eyes. This led to a recovery of visual acuity. This case report presents the rare occurrence and surgical management of cataract formation, IOL dislocation, and severe endothelial cell loss as a late complication of PCP IOL implantation. © 2004 ASCRS and ESCRS.

Study of biocompatibility on implantation of collagen intraocular contact lens in rabbit eyes - Gu, Z.-S.; Sheng, Y.-H.; Zhu, Z.-R.; Gao, J.-B. (Chinese Journal of Clinical Rehabilitation, 2004)
Background: Implantation of intraocular contact lens(ICL) in crystal eyes is a kind of new operation which can correct high myopia. As a kind of new material, collagen has been applied abroad to research and manufacture of ICL, while there is no similar domestic products. Objective: To observe the cellular response after implantation of collagen ICL in rabbit eyes and evaluate biocompatibility of collagen by animal experiments. Design: A randomized and control grouping experiment was designed. Setting and participants: The exporment was carried out in Department of Ophthalmology in the Affiliated Xinhua Hospital of Shanghai second Medical University. Twenty adult New Zealand white rabbits weighing from 2.0 kg to 2.5 kg, were selected without distinction of sex. Intervention: These experimental rabbits were randomly divided into three groups including 1 ICL implantation group; 2 surgical control group; 3 blank control group. On the 14th and 28th days after surgery, the experimental rabbits were killed and their eyeballs were extracted. Then the anterior segment tissue and ICL were taken out. HE stain, light microscopy, transmission and scanning electron microscope were used to observe and photograph. Main outcome measure: The morphological changes of histocytes on the surface of ICL and ocular anterror tissue were observed. Results: In ICL implantation group, the infiltration of plenty of phagocytes was major in ocular anterior segment tissues in the earlier period after operation, and the phagocytes were functionally active. There were only a few fibroblasts. The number of macrophages decreased in the later period, while the number of fibroblasts increased. In surgical control group many macrophages existed in ocular anterior tissue in the earlier period after operation and the number of fibroblasts increased significantly accompanied with fibrous tissue formation in the later period. Conclusion: Changes of inflammatory cells after ICL implantation showed a progress of classic foreign-body granulomatous inflammation. There was excellent ocular biocompatibility in collagen ICL.

Debridement - Steed, D.L. (American Journal of Surgery, 2004)
Debridement is defined as the removal of nonviable material, foreign bodies, and poorly healing tissue from a wound. Although surgeons recognize the importance of debridement, few data have been generated in randomized trials to support its use. Debridement provides for removal of tissue with the highest bacterial count, reliable cultures, and identification of osteomyelitis. The most direct form of debridement is surgical excision. For patients who are poor candidates for surgical debridement or have limited access to a surgeon, other forms of debridement (including mechanical, autolytic, enzymatic, and biologic) can be used. Although operative debridement is best performed by those with surgical training, the other forms of debridement can be accomplished by other allied health care professionals. Debridement remains an important adjunct to good wound care, but questions of what type, how much, and how often it should be performed remain unresolved. © 2004 Excerpta Medica, Inc. All rights reserved.

Surgical counts can be risky business! - Porteous, J. (Canadian operating room nursing journal, 2004)
The surgical count plays a vital role in enabling perioperative nurses to provide a safe environment to surgical patients. Counting errors are preventable. Although national standards of care provide excellent guidelines for developing effective count protocols, counting procedures are often modified according to individual health care policy. This article will discuss the risk factors for retained items, rate of occurrence, what objects are being left in patients, role of x-rays and consequences of leaving an object in a patient. It will also highlight points to be considered when implementing new count policies.

Material Reaction to Suture Anchor - Chow, J.C.Y.; Gu, Y. (Arthroscopy - Journal of Arthroscopic and Related Surgery, 2004)
The authors present a case of material reaction to suture anchor, which is rarely reported. Leukocyte rate, leukocyte differential, multiple cultures, and gram stain test could not prove infection. A second surgery for exploration of the shoulder joint was performed to reconstruct the rotator cuff without using anchors, and the rotator cuff tear healed after the second surgery. During the second surgery, the bone surrounding the anchors was found to be eroded and substituted with necrotic tissue. The anchors protruded outside the bone. The pathological examination of the necrotic tissue showed multinucleated giant cells of foreign body type, some of which had engulfed minute splinters of particulate foreign material. Either metal- or suture-induced bioreaction is suspected in this case.
Keywords: Material reaction; Suture anchor

In vitro degradation and biocompatibility of poly(DL-lactide-ε -caprolactone) nerve guides - Meek, M.F.; Jansen, K.; Steendam, R.; Van Oeveren, W.; Van Wachem, P.B.; Van Luyn, M.J.A. (Journal of Biomedical Materials Research - Part A, 2004)
Bridging nerve gaps by means of autologous nerve grafts involves donor nerve graft harvesting. Recent studies have focused on the use of alternative methods, and one of these is the use of biodegradable nerve guides. After serving their function, nerve guides should degrade to avoid a chronic foreign body reaction. The in vitro degradation, in vitro cytotoxicity, hemocompatibility, and short-term in vivo foreign body reaction of poly(65/35(85/15 L/D) lactide-ε-caprolactone) nerve guides was studied. The in vitro degradation characteristics of poly(DLLA-ε-CL) nerve guides were monitored at 2-week time intervals during a period of 22 weeks. Weight loss, degree of swelling of the tube wall, mechanical strength, thermal properties, and the intrinsic viscosity of the nerve guides were determined. Cytotoxicity was studied by measuring the cell proliferation inhibition index (CPII) on mouse fibroblasts in vitro. Cell growth was evaluated by cell counting, while morphology was assessed by light microscopy. Hemocompatibility was evaluated using a thrombin generation assay and a complement convertase assay. The foreign body reaction against poly(DLLA-ε-CL) nerve guides was investigated by examining toluidine blue stained sections. The in vitro degradation data showed that poly(DLLA-ε-CL) nerve guides do not swell, maintain their mechanical strength and flexibility for a period of about 8-10 weeks, and start to lose mass after about 10 weeks. Poly(DLLA-ε-CL) nerve guides were classified as noncytotoxic, as cytotoxicity tests demonstrated that cell morphology was not affected (CPII 0%). The thrombin generation assay and complement convertase assay indicated that the material is highly hemocompatible. The foreign body reaction against the biomaterial was mild with a light priming of the immunesystem. The results presented in this study demonstrate that poly(65/35(85/15 L/D) lactide-ε-caprolactone) nerve guides are biocompatible, and show good in vitro degradation characteristics, making these biodegradable nerve guides promising candidates for bridging peripheral nerve defects up to several centimeters. © 2003 Wiley Periodicals, Inc.
Keywords: Cytotoxicity; Hemocompatibility; Implantation; In vitro degradation; Peripheral nerve guide

The effect of phosphorylcholine-coated materials on the inflammatory response and fibrous capsule formation: In vitro and in vivo observations - Goreish, H.H.; Lewis, A.L.; Rose, S.; Lloyd, A.W. (Journal of Biomedical Materials Research - Part A, 2004)
Several experiments were performed to compare the in vitro adhesion of human macrophage and granulocyte inflammatory cells to polyethylene terephthalate substrate and the same coated with a phosphorylcholine (PC)-based polymer. The inclusion of various types of serum at different stages in the assay indicated that protein adsorption and passivation of the surface may be responsible for reducing the number of inflammatory cells adhering to the uncoated polyethylene terephthalate controls. In all of the assays performed there was a statistically significant reduction (p < 0.05; analysis of variance) of the number of inflammatory cells adhering to the PC-coated samples, linked to the ability of these surfaces to resist protein adhesion. Implantations of PC-coated stainless steel and high-density polyethylene USP control samples were made in a rabbit intramuscular model. Histological examination of the number of inflammatory cells present around the implant sites 4 weeks postimplantation showed there were 40% less cells associated with the PC-coated samples compared with control, but this was not statistically significant. Fibrous capsule thickness, however, whereas marginally less at 4 weeks, had almost completely regressed for the PC-coated sample at 13 weeks post-implantation and was statistically thinner (p < 0.01; Mann-Whitney U test) than the high-density polyethylene USP control. These findings support the view that low biointeractions observed for PC-based technology in vitro can result in reduced inflammation and foreign body reaction in vivo. © 2003 Wiley Periodicals, Inc.
Keywords: Cellular adhesion; Fibrous capsule formation; Inflammatory response; Phosphorylcholine polymer coating

Image Guided I125 Prostate Brachytherapy with Hybrid Interactive Mick Technique in the Community Setting: How Does it Compare? - Shanahan, T.G.; Mueller, P.W.; Roszhart, D.A.; Severino, W.C.; Bhate, A.D.; Nanavati, P.J.; Madison, J.B.; Dixon, E.J.; Ost, L.B.; Strode, L.L.; Wands, N.S.; Maxey, R.B. (Technology in Cancer Research and Treatment, 2004)
The aim of this study is to evaluate the target coverage, procedural techniques, and merits of Hybrid Interactive Mick (HIM) I125 transperineal permanent implantation (TPPI) of the prostate performed with 10 urologists in a community hospital. Detailed day 0 post-implant dosimetric evaluations of TPPI procedures were performed on 333 consecutive monotherapy patients treated between September 2000 and November 2003 at a single institution. All patients underwent TPPI with HIM. Pelvic and CXR films were obtained for a manual seed count at day 0 and again > day 90 on 175 patients. The HIM-prostate brachytherapy performed in a community hospital provided median D90, V100, and V150 values of 157Gy, 94%, and 42.3%, respectively. 18% of patients had seed migration to the lungs while 2% had seed migration to the bladder. Only 7 patients (4%) had 2 or more seeds migrate to the lungs. Procedure times average 38 minutes and number of needles used averaged 18. The post-implant urinary retention rate was 2.1% Use of HIM-prostate brachytherapy in the community setting with multiple urologists reproducibly maintained excellent and consistent dosimetric coverage. Procedure times and number of needles used were minimized, and with careful attention to image-guided technique, seed migration to bladder and lung was also minimized.
Keywords: Brachytherapy; Dose evaluation; Hybrid interactive brachytherapy; Prostate cancer; Seed migration

The use of URYX for reversible vasectomy in a rabbit model - Naughton, C.K.; Myles, J.; Thomas Jr., A.J. (Journal of Andrology, 2004)
URYX is a biocompatible polymer of ethylene vinyl alcohol dissolved in a dimethyl sulfoxide (DMSO) carrier to allow injection of a very low-viscosity fluid into tissue. Once the material comes into contact with body tissue or fluid, the DMSO rapidly dissipates from the polymer, which results in a precipitate of a coherent solid mass. The purpose of the present study was to determine whether URYX can effectively occlude the vas deferens and whether patency can be restored by redissolving the URYX in vivo using the solvent DMSO. Eight male New Zealand White rabbits (age range, 25-41 weeks; mean age, 33.9 ± 7.5 weeks; mean weight, 4.0 ± 0.2 kg) were used in 2 experiments (E1 and E2). In E1, 3 rabbits underwent unilateral vasectomy, and the contralateral vas was injected with either 0.05 or 0.10 mL of URYX, to determine the amount of URYX required to cause obstruction. Two animals underwent bilateral vasectomy, to serve as controls. In E2, 3 animals underwent bilateral URYX injection and were compared with the bilateral vasectomy control rabbits used in E1. After 1 month of initial bilateral URYX treatment, all animals in E2 underwent attempted unilateral reversal with 1.5 mL of DMSO injected into 1 occluded vas deferens. Two end points were evaluated-a clinical end point assessed by semen analyses and a pathological end point assessed by histological analysis of treated tissues, to assess for safety. A 1.5-cm infrapubic incision was made to expose both vasa in anesthetized rabbits. The vasal injection of URYX was performed with a 30-gauge needle. Vasectomy was performed by excision of a 1-cm segment of the vas deferens and subsequent ligation with a 6-0 prolene suture. Semen was collected using an artificial vagina 2-3 times/wk before and 1 month later, after injection treatments and vasectomy. Manual sperm counts were performed. All animals were sacrificed, and tissues (distal vas, injection site, proximal vas, cauda epididymis, caput epididymis, and testis) were harvested and examined for the presence of URYX. The inflammatory response of the wall and adventitia of the vas deferens was given a score (0-15) based on the sum of grades (0 = none, 1 = mild, 2 = moderate, and 3 = severe) for the following categories: foreign body giant cell reaction, granulation tissue, lymphocytes, eosinophils, and scarring, as evaluated by a single pathologist (J.M.). Vasal injection with 0.05 mL of URYX was not sufficient to cause occlusion. Both animals injected with 0.1 mL of URYX were effectively occluded. The injection of occluded vasa with DMSO did not dissolve the URYX plug in the vas lumen. There was no significant difference in vasal inflammatory response scores between vasal units treated with URYX only and vasal units in the vasectomy model. Vasal units subjected to URYX followed by DMSO demonstrated greater inflammatory response scores than vasal units treated with URYX followed by normal saline, URYX alone, or vasectomy. Epididymal and testicular histology remained unaffected in all vasal units in E1. The vasal units in E2 subjected to URYX followed by normal saline showed no histological abnormalities of the epididymis and testis. However, those vasal units subjected to URYX followed by DMSO in E2 showed evidence of adhesions, necrosis, and degenerating cells in the epididymis and a focal foreign body giant cell reaction in the testis. The bilateral vasal injection of URYX can result in azoospermia in the rabbit model. Reversal with subsequent DMSO injection was not achieved. A minimal inflammatory response of the vas deferens was observed with URYX injection alone; however, DMSO following URYX injection resulted in increased vasal inflammation, in addition to epididymal and testicular changes.
Keywords: DMSO; Epididymis; Testicle; Vas deferens

Treatment of Pseudofolliculitis Barbae Using the Long-Pulse Nd:YAG Laser on Skin Types V and VI - Weaver III, S.M.; Sagaral, E.C. (Dermatologic Surgery, 2003)
BACKGROUND. Pseudofolliculitis barbae (PFB) is a foreign body inflammatory condition that is caused by in-grown hairs of the face and body. An effective treatment to alleviate this condition without the risk of side effects has yet to be found. OBJECTIVE. The objective of this study was to evaluate the Lyra 1064-nm long-pulse ND:YAG laser in the treatment of PFB on skin types V and VI. METHODS. Twenty subjects (12 males and 8 females) were given two treatments approximately 3 to 4 weeks apart and were assessed by objective papule/pustule and hair counts at 1, 2, and 3 months after final treatment. Laser treatments with the Lyra Nd:YAG laser were applied onto 2 × 2-cm regions on the upper and lower mandible and neck regions. Contralateral controls were used to assess overall effectiveness. Subjective evaluations were also obtained from both subjects and investigators. Assessments of any abnormal side effects caused by laser treatment, including dyspigmentation and/or scarring, were also evaluated. RESULTS. A reduction in the quantity of papules/pustules and hairs when compared with baseline data was statistically significant for treatment of PFB in the mandibular and neck regions at the 1-, 2-, and 3-month follow-up evaluations. Subject evaluations ranged from satisfied to very satisfied. Side effects included transient hyperpigmentation, transient hypopigmentation, mild erythema, and itching. CONCLUSIONS. The use of the 1064-nm long-pulse Nd:YAG laser for the treatment and management of PFB on skin types V and VI is both safe and effective, with positive results lasting for up for to 3 months after two treatments.

Vascularizing the tissue surrounding a model biosensor: How localized is the effect of a subcutaneous infusion of vascular endothelial growth factor (VEGF)? - Ward, W.K.; Quinn, M.J.; Wood, M.D.; Tiekotter, K.L.; Pidikiti, S.; Gallagher, J.A. (Biosensors and Bioelectronics, 2003)
Implantable continuous biosensors would improve disease management but long term function of such devices have been limited by a hypovascular foreign body capsule that inhibits influx of analytes. To assess whether capsule vascularity could be increased, we studied the histologic effects of a 28-day continuous infusion of vascular endothelial growth factor (VEGF) (0.45 μg/day) vs. saline from the surface of a model disk biosensor that was implanted subcutaneously in rats. At day 40, tissue was obtained at varying distances from the infusion port and capsular microvessels were counted using two histologic techniques. VEGF treatment led to a marked increase in capillary density. In tissue located 1 mm away from the infusion site, capillary density in VEGF-treated animals was 200-300% higher than in saline controls. Tissue located 13 mm away, but not 25 mm away, also demonstrated neovascularization. Serum obtained from a distant vein during the infusion did not show an elevated concentration of VEGF. These data demonstrate that a subcutaneous infusion of VEGF creates localized neovascularization of the foreign body capsule and suggest that systemic effects of VEGF are avoidable. Vascularization of a foreign body capsule surrounding a subcutaneous biosensor might well extend its useful life. © 2003 Elsevier B.V. All rights reserved.
Keywords: Angiogenesis; Foreign body capsule; Glucose sensor; VEGF

Cellular inflammatory response to porcine collagen membranes - Patino, M.G.; Neiders, M.E.; Andreana, S.; Noble, B.; Cohen, R.E. (Journal of Periodontal Research, 2003)
Objectives: The purpose of this study was to assess local inflammatory changes associated with the implantation of three different porcine collagen membranes having potential use in periodontal regeneration. Methods: Materials were implanted subcutaneously into prepared sites along the dorsal skin surface of 60 female Wistar rats. Saline and turpentine were used as negative and positive controls, respectively. Animals were killed and biopsies obtained after 3 d, and at 1, 2, 4, 6, and 8 weeks after membrane implantation. A panel of six monoclonal antibodies was used to identify circulating monocytes (ED1), resident tissue macrophages (ED2), lymphoid macrophages (ED3), Ia-antigen expression (OX6), T-lymphocytes (OX19), and B-lymphocytes (OX33). Cells identified by each antibody were subjected to quantitative immunocytochemistry to compare any differences present among groups. Sera obtained 8 weeks after grafting were used in immunoblotting assays to detect the presence of systemic antiporcine antibodies. Results: We found that the mononuclear cell subsets associated with implantation of porcine collagen membranes were similar to those obtained with saline administration. On the other hand, the use of turpentine resulted in an inflammatory infiltrate characterized by significantly higher numbers of all six monoclonal cell subsets at all time periods evaluated, compared to either saline or any of the membranes (P < 0.001). Conclusions: The collagen membranes do not appear to be associated with a significant local inflammatory response, nor a systemic immune response, and thus appear to be well tolerated, rendering them useful in periodontal regeneration.
Keywords: Barrier; Collagen; Inflammation; Macrophages; Membranes

An unusual cause of small bowel obstruction: Gossypiboma - Case report - Gencosmanoglu, R.; Inceoglu, R. (BMC Surgery, 2003)
Background: The term "gossypiboma" denotes a mass of cotton that is retained in the body following surgery. Gossypiboma is a medico-legal problem especially for surgeons. To the best of our knowledge, the patient presented herein is the second reported patient in whom the exact site of migration of a retained surgical textile material into the intestinal lumen could be demonstrated by preoperative imaging studies. Case presentation: A 74-year-old woman presented with symptoms of small bowel obstruction due to incomplete intraluminal migration of a laparotomy towel 3 years after open cholecystectomy and umbilical hernia repair. Plain abdominal radiography did not show any sign of a radio-opaque marker in the abdomen. However, contrast enhanced abdominal computerized tomography revealed a round, well-defined soft-tissue mass with a dense, enhanced wall, containing an internal high-density area with air-bubbles in the mid-abdomen. A fistula between the abscess cavity containing the suspicious mass and gastrointestinal tract was identified by upper gastrointestinal series. The presence of a foreign body was considered. It was surgically removed with a partial small bowel resection followed by anastomosis. Conclusions: Although gossypiboma is rarely seen in daily clinical practice, it should be considered in the differential diagnosis of acute mechanical intestinal obstruction in patients who underwent laparotomy previously. The best approach in the prevention of this condition can be achieved by meticulous count of surgical materials in addition to thorough exploration of surgical site at the conclusion of operations and also by routine use of surgical textile materials impregnated with a radio-opaque marker.

Strategic leukocyte depletion reduces pulmonary microvascular pressure and improves pulmonary status post-cardiopulmonary bypass - Olivencia-Yurvati, A.H.; Ferrara, C.A.; Tierney, N.; Wallace, N.; Mallet, R.T. (Perfusion, 2003)
Cardiopulmonary bypass (CPB) precipitates inflammation that causes marked pulmonary dysfunction. Leukocyte filtration has been proposed to reduce these deleterious effects. Other studies show an improvement with aprotinin. We proposed that a combination of these two therapies would synergistically improve pulmonary outcomes. Two hundred and twenty-five patients participated in a randomized prospective study comparing pulmonary microvascular function and pulmonary shunt fraction postcoronary artery bypass grafting (CABG). The study group underwent leukocyte depletion with aprotinin during the procedure. Pulmonary microvascular function was assessed by pulmonary microvascular pressure (PMVP), a measure of pulmonary capillary edema, and pulmonary function was evaluated by comparing pulmonary shunt fractions. Elevated PMVP and increased pulmonary shunting compromise pulmonary performance. The leukocyte-depleted group had significantly reduced PMVP and pulmonary shunt fraction for at least the first 24 hours postbypass. The combination of strategic leukocyte filtration and aprotinin therapy can effectively reduce postoperative decline in pulmonary function. Cardiopulmonary bypass precipitates a variety of inflammatory effects that can cause marked pulmonary dysfunction to the point of respiratory failure, necessitating prolonged mechanical ventilation. Leukocyte filtration has been investigated previously and appears to be beneficial in improving pulmonary outcome by preventing direct neutrophil-induced inflammatory injury. Recent studies of leukocyte reduction profiles suggest that leukoreduction via leukofiltration is short lived with filter saturation occurring 30-45 minutes after onset of filtration. This phenomenon may explain the limited utility observed with higher risk patients. These patients typically require longer pump runs, so leukocyte reduction capability is suboptimal at the time of pulmonary vascular reperfusion. To more effectively protect the lung from reperfusion injury, leukocyte filtration can be delayed so that reduction of activated neutrophils is maximal at the time of pulmonary vascular reperfusion. It is, thus, conceivable that a timely use of arterial line leukoreducing filters may improve, more substantially, pulmonary function postbypass. Two hundred and twenty-five isolated coronary revascularization patients participated in this prospective, randomized trial. The patients received moderately hypothermic CBP alone (control group: n = 110) or combined with leukocyte depletion, initiated 30 minutes before crossclamp release, with filters placed in the bypass circuit (study group: n = 115). All patients also received full Hammersmith aprotinin dosing during the operation. Pulmonary microvascular pressures were lower in the study group at three hours postbypass, and continued to fall until 24 hours postbypass. In contrast, the control group measured a rise in PMVP and a continued plateau throughout 24 hours postbypass (p < 0.028). The calculated pulmonary shunt fraction also was reduced significantly throughout the study interval, with the greatest reduction occurring approximately three to six hours post-CPB (p < 0.002). Shunt fractions eventually converged at 24 hours postbypass. Outcome measures included hospital charges and length of stay, which were also markedly reduced in the treatment group. Increasing PMVPs are a direct reflection of pulmonary capillary edema, which, in conjunction with increased pulmonary shunt ratio, lead to an overall worsening of pulmonary function. Intraoperative strategic leukocyte filtration combined with aprotinin treatment improves post-CPB lung performance by reducing significantly the reperfusion inflammatory response and its sequelae. These benefits are manifested by reductions in ventilator times, hospital stay and patient morbidity.

Lack of biofilm contribution to bacterial colonisation in an experimental model of foreign body infection by Staphylococcus aureus and Staphylococcus epidermidis - Francois, P.; Tu Quoc, P.H.; Bisognano, C.; Kelley, W.L.; Lew, D.P.; Schrenzel, J.; Cramton, S.E.; Götz, F.; Vaudaux, P. (FEMS Immunology and Medical Microbiology, 2003)
The contribution of in vivo biofilm-forming potential of Staphylococcus aureus and Staphylococcus epidermidis was studied in an experimental model of foreign body infections. Increasing inocula (from 102 to 107 organisms) of ica-positive strains of S. aureus and S. epidermidis and their ica-negative isogenic mutants (the ica locus codes for a major polysaccharide component of biofilm) were injected into subcutaneously implanted tissue cages in guinea pigs. Surprisingly, bacterial counts and time-course of tissue cage infection by ica-positive strains of S. aureus or S. epidermidis were equivalent to those of their respective ica-negative mutants, in the locally infected fluids and on tissue-cage-inserted plastic coverslips. © 2003 Federation of European Microbiological Societies. Published by Elsevier Science B.V. All rights reserved.
Keywords: Biofilm; Foreign body infection; ica gene; Staphylococcus aureus; Staphylococcus epidermidis

Hydrogels based on poly(ethylene oxide) and poly(tetramethylene oxide) or poly(dimethyl siloxane). III. In vivo biocompatibility and biostability - Park, J.H.; Bae, Y.H. (Journal of Biomedical Materials Research - Part A, 2003)
To investigate the effects of polymer chemistry and topology (linear or graft copolymer) on in vivo biocompatibility and biostability based on cage implant system, various hydrogels, composed of short hydrophilic [polyethylene oxide (PEO)] and hydrophobic block, were prepared by polycondensation reaction. Poly(tetramethylene oxide) (PTMO) or poly(dimethyl siloxane) (PDMS) was chosen as a hydrophobic block because of their wide utilization as a biomaterial. By using the specimens retrieved from rats killed after 1, 2, 3, 5, and 7 weeks' implantation, cellular and material responses were assessed. Most hydrogels showed a comparable value of macrophage density to Pellethane®, control polymer, whereas they did significantly lower foreign body giant cell (FBGC) density and coverage because of the presence of PEO. However, PEO block length and polymer topology did not affect macrophage adhesion and FBGC formation in our polymer composition. The hydrogel based on PDMS alone showed significantly lower macrophage density and FBGC density than Pellethane®, indicating that PDMS plays a role in inhibiting cellular adhesion. The results obtained from gel permeation chromatography curve and Fourier transform infrared spectra exhibited that all the polymers were susceptible to oxidative degradation in vivo. Although Pellethane® revealed surface degradation by 5 weeks in vivo, hydrogels showed rapid degradation in the bulk within 2 weeks because of the penetration of oxidative chemicals released from phagocytic cells into PEO domain of phase-separated hydrogels. The more significant degradation was observed in the hydrogels with longer PEO block and PTMO as a hydrophobic block instead of PDMS. It was evident that the minor degradation could be achieved by grafting PEO and adopting PDMS as a hydrophobic block in the hydrogel. © 2002 Wiley Periodicals, Inc.
Keywords: Biocompatibility; Biostability; Hydrogel; Poly(dimethyl siloxane); Poly(ethylene oxide); Poly(tetramethylene oxide)

Risk factors for retained instruments and sponges after surgery - Gawande, A.A.; Studdert, D.M.; Orav, E.J.; Brennan, T.A.; Zinner, M.J. (New England Journal of Medicine, 2003)
BACKGROUND: Risk factors for medical errors remain poorly understood. We performed a case-control study of retained foreign bodies in surgical patients in order to identify risk factors for this type of error. METHODS: We reviewed the medical records associated with all claims or incident reports of a retained surgical sponge or instrument filed between 1985 and 2001 with a large malpractice insurer representing one third of the physicians in Massachusetts. For each case, we identified an average of four randomly selected controls who underwent the same type of operation during the same six-month period. RESULTS: Our study included 54 patients with a total of 61 retained foreign bodies (of which 69 percent were sponges and 31 percent instruments) and 235 control patients. Thirty-seven of the patients with retained foreign bodies (69 percent) required reoperation, and one died. Patients with retained foreign bodies were more likely than controls to have had emergency surgery (33 percent vs. 7 percent, P<0.001) or an unexpected change in surgical procedure (34 percent vs. 9 percent, P<0.001). Patients with retained foreign bodies also had a higher mean body-mass index and were less likely to have had counts of sponges and instruments performed. In multivariate analysis, factors associated with a significantly increased risk of retention of a foreign body were emergency surgery (risk ratio, 8.8 [95 percent confidence interval, 2.4 to 31.91]), unplanned change in the operation (risk ratio, 4.1 [95 percent confidence interval, 1.4 to 12.4]), and body-mass index (risk ratio for each one-unit increment, 1.1 [95 percent confidence interval, 1.0 to 1.2]). CONCLUSIONS: The risk of retention of a foreign body after surgery significantly increases in emergencies, with unplanned changes in procedure, and with higher body-mass index. Case-control analysis of medical-malpractice claims may identify and quantify risk factors for specific types of errors.

Projects for improving safety of counts in the OR. (OR manager, 2003)

Counting instruments and sponges. - Beyea, S.C. (AORN journal, 2003)

Gossypiboma simulating huge ovarian mass: a case report. - Fadiora, S.O.; Komolafe, J.O.; Ogunniyi, S.O. (Nigerian journal of medicine : journal of the National Association of Resident Doctors of Nigeria, 2003)
A case of 36 year old Po+1 with retained abdominal gauze pack following myomectomy necessitating, exploratory laparatomy is presented. The need to pay attention to counting of instruments and gauze packs before closing the abdomen coupled with use of gauze impregnated with radio-detectable material is emphasized.

O.R. Left behind. Counting surgical instruments reduces medical errors. - Erickson, S. (Materials management in health care, 2003)

Auditing and improving the sponge count process. - Farrell, V.; Higbie, V.; Cleveland, S. (OR manager, 2003)

Esophageal perforation caused by a press through pack - Sudo, T.; Sueyoshi, S.; Fujita, H.; Yamana, H.; Shirouzu, K. (Diseases of the Esophagus, 2003)
A 73-year-old woman complaining of sudden hoarseness visited our hospital 17 days after the onset. The upper gastrointestinal contrast study showed a shallow ulcer crater with moderate bulging in the upper thoracic esophagus. Endoscope and computed tomography revealed an esophageal foreign body, a Press Through Pack (PTP), in the esophageal ulcer. The PTP could be removed endoscopically. Two months after extraction of the PTP, the patient was taking normal food orally and was discharged. The esophageal perforation, looking like a diverticle, was still present more than 1 year after the onset.

Identifying lost surgical needles using radiographic techniques. - Macilquham, M.D.; Riley, R.G.; Grossberg, P. (AORN journal, 2003)
Many surgical procedures involve the use of very small surgical needles. In the event that a postoperative needle count is incorrect, traditionally an x-ray has been taken to find the needle. Little data exist to recommend the smallest surgical needle that can be identified with conventional radiographic techniques and the optimum technique for finding lost surgical needles. In this quality assurance project x-rays of various size surgical needles were taken. The smallest seen by the majority of observers was 17 mm. The radiographic technique of choice for optimum detection of lost surgical needles was imaging with a mobile image intensifier.

Transscleral fixation of a foldable intraocular lens in aphakic vitrectomized eyes - Ahn, J.K.; Yu, H.G.; Chung, H.; Wee, W.R.; Lee, J.-H. (Journal of Cataract and Refractive Surgery, 2003)
Purpose: To evaluate the clinical outcomes of transscleral fixation of a foldable intraocular lens (IOL) in eyes that had pars plana lensectomy combined with pars plana vitrectomy for severe vitreoretinal disease. Setting: Seoul National University Hospital, Seoul, Korea. Methods: The medical records of 21 patients who had a transscleral fixation of a foldable IOL after previous vitrectomy combined with lensectomy for severe posterior segment pathology were reviewed. The underlying vitreoretinal diseases were complicated proliferative diabetic retinopathy (n = 9), proliferative vitreoretinopathy (n = 5), traumatic retinal detachment (n = 3), intraocular foreign body (n = 2), and uveitic retinal detachment (n = 2). The postoperative best corrected visual acuity (BCVA) was compared with the preoperative BCVA. Autorefractometry and keratometry measurements and central endothelial cell counts were evaluated 1 day preoperatively and 6 months postoperatively. Results: The mean age of the patients was 54.5 years. The preoperative aphakic period ranged from 2 to 22 months. The visual acuity reached the preoperative BCVA by 2 months after surgery and was better than the preoperative BCVA at 6 months (P = .006) and at the final visit (P = .003). Six months postoperatively, the mean myopic shift by cycloplegic autorefractometry was -1.0 diopter (D) and the mean scalar shift in surgically induced keratometric cylinder, 1.0 D. The mean central corneal endothelial loss at 6 months was 6.7% (range 2.4% to 22.2%). The only vitreoretinal complications were a transient vitreous hemorrhage and a reopened macular hole that was reattached after fluid-gas exchange. Conclusion: Transscleral fixation of a foldable IOL was safe and led to favorable visual outcomes in aphakic vitrectomized eyes with previous severe vitreoretinal disease. © 2003 ASCRS and ESCRS.

Transmural migration of a retained laparotomy sponge - Dhillon, J.S.; Park, A. (American Surgeon, 2002)
The most common surgically retained foreign body is the laparotomy sponge. The clinical presentation of a retained sponge can vary from an incidental finding on plain radiograph to an intense inflammatory response with obstruction or perforation. In the case described here a patient reported abdominal pain 11 months after her hysterectomy. Although two sponge counts appeared in the operative record one laparotomy sponge had been overlooked. Apparently an inflammatory response created an abscess pocket around the sponge between the abdominal wall and the ileum resulting in perforation of the ileum. Through this opening the sponge migrated into the lumen of the small bowel, from which it was surgically removed. The patient recovered without complications. The case highlights the importance of a thorough exploration of all quadrants of the abdomen at the termination of surgical cases.

Artisan phakic iris claw intraocular lens for high primary and secondary hyperopia - Alió, J.L.; Mulet, M.E.; Shalaby, A.M.M. (Journal of Refractive Surgery, 2002)
PURPOSE: To evaluate the efficacy, predictability, and safety of the Artisan iris claw phakic intraocular lens for the correction of high primary and secondary hyperopia. METHODS: Fifty-seven eyes were divided into two groups: 29 eyes had primary hyperopia (mean refraction 6.06 ± 1.26 D, and 28 eyes had secondary hyperopia, (mean refraction 5.88 ± 1.88 D) induced or residual following a previous corneal refractive procedure. Consecutive implantation of the Artisan iris claw phakic intraocular lens was performed. Main outcome measures recorded were BSCVA, UCVA, refraction, and astigmatic change, intraocular inflammation, and endothelial cell loss. RESULTS: Primary hyperopic group: Preoperatively, mean UCVA was 0.4 ± 0.7 and mean BSCVA was 0.2 ± 0.6. After implantation, mean UCVA was 0.3 ± 0.6 and BSCVA was 0.1 ± 0.6. Mean cycloplegic residual spherical refractive error after surgery was 0.10 ± 0.57 D (range -1 to +2 D). Mean surgically induced astigmatism was 1.48 ± 0.89 D. Safety index was 1.11. Efficacy index was 0.83. Secondary hyperopic group: Preoperatively, mean UCVA was 0.5 ± 0.7 and mean BSCVA was 0.2 ± 0.6. Postoperatively, mean UCVA was 0.4 ± 0.7 and mean BSCVA was 0.2 ± 0.6. Mean cycloplegic residual spherical refractive error was 0.55 ± 1.49 D. Mean surgically induced astigmatism was 1.85 ± 1.19 D. Safety index was 1.05. Efficacy index was 0.7. Postoperative iridocyclitis was observed in one eye (3.4%) in the primary group and in three eyes (10.7%) in the secondary group. Overall corneal endothelial cell loss at 1 year of follow-up was 9.4%. CONCLUSION: The Artisan iris claw phakic intraocular lens was reasonably safe and predictable for correcting high hyperopia.

Influence of mesh materials on collagen deposition in a rat model - Junge, K.; Klinge, U.; Klosterhalfen, B.; Mertens, P.R.; Rosch, R.; Schachtrupp, A.; Ulmer, F.; Schumpelick, V. (Journal of Investigative Surgery, 2002)
Alterations of the extracellular matrix (ECM) with its major component collagen are increasingly discussed as possible risk factors implicated in the development of abdominal-wall herniation. Because of the widespread use of alloplastic meshes for the surgical repair of hernias, an animal study was performed to analyze the influence of various mesh materials on the quantity and quality of collagen deposition. In 60 male Sprague-Dawley rats an abdominal replacement was performed using three different kinds of mesh materials: polyester (PE), a pure polypropylene (PP), and a composite mesh made of polypropylene and polyglactin (PG). A simple fascia suture repair served as control. The count of fibroblasts, the collagen/protein ratio, the type I/III collagen ratio, and the ex-pression of basic fibroblast growth factor (b-FGF) at the interface were analyzed after 7, 21, and 90 days. The ratio of collagen to overall protein (μg/mg) showed significant differences comparing different mesh materials (sham controls 38.44 ± 16.33 μg/mg, PE 68.5= 23.8 μg/mg, PP 101.6 ± 32.3 μg/mg, PG 49.6 μ 11.6 μg/mg at day 90). The ratio of collagen type I/III increased over time in all groups. However, 90 days after mesh implantation the ratio was always significantly lowered compared to the controls. No significant difference was found comparing different mesh materials. The alteration of the scar composition is closely connected to an increased b-FGF expression. b-FGF and count of fibroblasts highly correlated (r = .95) and showed significant elevated levels compared to simple suture repair. The results of our study strongly support the notion that wound healing is affected by mesh implantation. The quality of the ECM deposition as determined by collagen type I/III ratio is impaired in general, whereas the quantity of ECM deposition is markedly influenced by the kind of mesh material.
Keywords: b-FGF; Biomaterial; Collagen; Mesh; Wound healing

Results of hydrophilic acrylic, hydrophobic acrylic, and silicone intraocular lenses in uveitic eyes with cataract: Comparison to a control group - Abela-Formanek, C.; Amon, M.; Schauersberger, J.; Kruger, A.; Nepp, J.; Schild, G. (Journal of Cataract and Refractive Surgery, 2002)
Purpose: To evaluate the uveal and capsular biocompatibility of hydrophilic acrylic, hydrophobic acrylic, and silicone intraocular lenses (IOLs) in eyes with uveitis. Setting: Department of Ophthalmology, University of Vienna, Vienna, Austria. Methods: This prospective study comprised 72 eyes with uveitis and 68 control eyes having phacoemulsification and IOL implantation by 1 surgeon. Patients received 1 of the following IOLs: foldable hydrophilic acrylic (Hydroviewr®, Bausch & Lomb), hydrophobic acrylic (AcrySof®, Alcon), or silicone (CeeOn® 911, Pharmacia). Postoperative evaluations were at 1, 3, and 7 days and 1, 3, and 6 months. Cell reaction was evaluated by specular microscopy of the anterior IOL surface and the anterior and posterior capsule reaction, by biomicroscopy. Results: Small round cell deposition was observed on all IOLs in the immediate postoperative period, especially in eyes with uveitis. This reaction decreased 3 to 6 months after surgery. Although the CeeOn 911 had a higher mean grade of small cells, there was no statistical difference between the 3 IOL types after 6 months in the uveitis and control groups. Foreign-body giant cells (FBGCs) increased after 1 week to 1 month. The AcrySof IOLs had the highest number of FBGCs; after 6 months, there was a statistically significant difference between the AcrySof and Hydroview uveitis groups (P = .036) and the AcrySof and CeeOn 911 uveitis groups (P = .003) but there was no difference among the 3 IOL types in the control group. Lens epithelial cell outgrowth persisted on the Hydroview IOLs in control eyes and regressed on all 3 IOL types in uveitic eyes and on the AcrySof and CeeOn 911 IOLs in control eyes (P = .0001). Anterior capsule opacification (ACO) was more severe on all IOL types in uveitic eyes and on the CeeOn 911 IOL in control eyes. Posterior capsule opacification (PCO) was more severe in uveitic eyes. The Hydroview group had more severe PCO than the AcrySof and the CeeOn 911 groups in uveitis and control eyes. Six months postoperatively, the difference was significant (P = .0001). There was no significant difference between the AcrySof and CeeOn 911 IOLs. Conclusions: Intraocular lens biocompatibility is inversely related to inflammation. Hydrophilic acrylic material had good uveal but worse capsular biocompatibility. Hydrophobic acrylic material had lower uveal but better capsular biocompatibility. Silicone showed a higher small cell count (mild) and more severe ACO but achieved PCO results comparable to FBGC results and better than those with the AcrySof lens 6 months after surgery. Despite the differences in IOL biocompatibility, all patients benefited from the surgery. © 2002 ASCRS and ESCRS.

Uveal and capsular biocompatibility of hydrophilic acrylic, hydrophobic acrylic, and silicone intraocular lenses - Abela-Formanek, C.; Amon, M.; Schild, G.; Schauersberger, J.; Heinze, G.; Kruger, A. (Journal of Cataract and Refractive Surgery, 2002)
Purpose: To evaluate the long-term response of 6 types of 3-piece intraocular lenses (IOLs) by assessing the cellular reaction on the anterior IOL surface, the behavior of posterior and anterior capsule fibrosis, and flare. Setting: Department of Ophthalmology, Medical School, University of Vienna, Vienna, Austria. Methods: One hundred eighty eyes were prospectively randomized to receive 1 of 6 IOLs: hydrophilic acrylic Hydroview® (Bausch & Lomb) or MemoryLens® (ORC); hydrophobic acrylic AcrySof® MA60BM (Alcon) or AMO Sensar AR40® (Allergan); hydrophobic silicone CeeOn® 920 or CeeOn 911A (Pharmacia). The patients had standardized cataract surgery, postoperative medication, and follow-up. One year after surgery, 155 eyes were assessed. The cellular reaction was evaluated by specular microscopy of the antenor IOL surface. Anterior and posterior capsule opacification (PCO) was assessed semiquantitatively by biomicroscopy. Flare was measured with a Kowa FC-1000 laser flare-cell meter. Results: Regarding uveal biocompatibility, the hydrophobic acrylic IOLs showed the highest incidence of late foreign-body cell reaction (AcrySof, 30%; AR40, 17%) followed by the hydrophilic acrylic (MemoryLens, 8%; Hydroview, 4%) and silicone (CeeOn 920, 4%; CeeOn 911A, 0%) (P = .0044). In all cases, the cellular reaction was low grade and clinically insignificant. Regarding capsular biocompatibility, some eyes developed lens epithelial cell (LEC) outgrowth on the anterior IOL surface. The highest incidence was in the hydrophilic acrylic group (Hydroview, 85%; MemoryLens, 27%) followed by the hydrophobic acrylic (AcrySof, 4%; AR40, 3%). No silicone IOL had LECs on the anterior surface. The difference among IOL groups was significant (P = .0001). Anterior capsule opacification was more predominant in the hydrophobic IOL groups. Posterior capsule opacification of the central 3.0 mm area was lowest in the groups with a sharp-edged optic (CeeOn 911A, AcrySof) followed by the round-edged silicone (CeeOn 920), hydrophobic acrylic (AR40), and hydrophilic acrylic IOLs (P = .0001). There was a significant difference in flare between the AR40 lens and the Hydroview, MemoryLens, CeeOn 911A, and CeeOn 920 (P < .004). There was no statistically significant difference in the postoperative cell count at 1 year. The power calculation showed that the sample size was sufficient. Conclusions: The differences in cellular reaction, although clinically mild in normal eyes, indicate that there were more giant cells with hydrophobic acrylic IOLs and an increased tendency toward LEC outgrowth with hydrophilic lenses. The incidence of PCO was lowest in the hydrophobic IOL groups, especially in groups with a sharp-edged optic. Second-generation silicone IOLs with a sharp edge had good uveal and capsular biocompatibility 1 year after surgery. © 2002 ASCRS and ESCRS.

Effect of heparin in the irrigation solution on postoperative inflammation and cellular reaction on the intraocular lens surface - Kruger, A.; Amon, M.; Abela-Formanek, C.; Schild, G.; Kolodjaschna, J.; Schauersberger, J. (Journal of Cataract and Refractive Surgery, 2002)
Purpose: To evaluate the influence of heparin sodium in the irrigation solution on postoperative inflammation and cellular reaction on the anterior surface of a hydrophilic intraocular lens (IOL). Setting: Department of Ophthalmology, University of Vienna, Vienna, Austria. Methods: This randomized prospective single-surgeon study included 50 patients with senile cataract only. Half the patients received 1 mL of heparin sodium (concentration 10 IU/mL) in addition to the regular irrigating solution. In all other respects, the procedure was standardized: clear corneal incision, phacoemulsification, and implantation of a Hydroview® foldable hydrogel IOL (Bausch & Lomb). The parameters of inflammation-anterior chamber flare and cells-were evaluated with the pupil dilated in a masked fashion using a Kowa FC-1000 laser flare-cell meter 1, 3, 7, 14, and 28 days and 3, 6 and 12 months postoperatively. The cellular reaction was semiquantitatively examined and analyzed by specular microscopy. Results: In both groups, flare and cell values increased on the first postoperative day and successively decreased thereafter. In the first week, the flare and cell values were significantly higher in the group without heparin sodium in the irrigating solution. Subsequently, there were no differences between the 2 groups in flare or cells. At 1 day, the heparin sodium group had statistically significantly fewer IOLs with no cells on the surface. Subsequently, no differences in cellular reaction on the IOL were observed. Conclusions: Heparin sodium added to the standard irrigating solution reduced disturbances of the blood-aqueous barrier in the early postoperative period. There seemed to be no long-term effect, especially on cellular reaction, on the hydrophilic IOL surface. © 2002 ASCRS and ESCRS.

Conservative management of ingested foreign bodies - Weiland, S.T.; Schurr, M.J. (Journal of Gastrointestinal Surgery, 2002)
We reviewed the clinical benefits of hospitalization, esophagogastroduodenoscopy, and surgical intervention for ingested foreign bodies in adults. Patients with esophageal foreign bodies were not included in the study group. A 10-year experience is reported. Each patient's physical examination findings at presentation, white blood cell count, length of hospital stay, number and types of foreign bodies ingested, endoscopic interventions, surgical interventions, and complications were reviewed. There were 75 separate hospitalizations, all occurring in 22 male prison inmates. A total of 256 foreign bodies were ingested. Patients incurred 281 hospitalization days (average 3.7 days per admission). One patient had signs of peritonitis. White blood cell count was less than 10 K/μL in 85%. Sixty-four endoscopies were performed with removal of 79 of 163 foreign bodies (48% success rate). Five patients required general anesthesia because of a lack of cooperation. Complications occurred in four of them, one requiring laparotomy. Eight additional laparotomies were performed. One was performed for an acute abdomen on admission and one for the development of an acute abdomen after conservative management. Two were performed to remove metal bezoars. Four additional laparotomies were performed because of surgeon preference. Among the 23 patients admitted and managed conservatively, 77 (97%) of 79 foreign bodies passed spontaneously. One patient required laparotomy. Of the 256 ingested foreign bodies, 79 were removed endoscopically, 71 were removed surgically, and 106 passed spontaneously. The size, shape, and number were not predictive of the ability to transit the gastrointestinal tract. Foreign body ingestion is problematic in prison inmates. With conservative management, most foreign bodies will pass spontaneously. Endoscopy has a high failure rate and is associated with significant complications. Surgical intervention should be reserved for those who have acute conditions in the abdomen or large bezoars. © 2002 The Society for Surgery of the Alimentary Tract, Inc.
Keywords: Bezoars; Endoscopy; Laparotomy; Prisoners

Recognized standards and recommended guidelines for the swab, instrument and needle count. - Beesley, J. (British journal of perioperative nursing : the journal of the National Association of Theatre Nurses, 2002)

Foreign body giant cell induction in the CSF-1-deficient osteopetrotic (op/op) mouse - Iizuka, T.; Kohgo, T.; Marks Jr., S.C. (Tissue and Cell, 2002)
The osteopetrosis (op) mutation in mice is characterized by generalized skeletal sclerosis; reduced numbers of osteoclasts, macrophages, and monocytes; and failure to be cured by bone marrow transplantation. This mutation has been shown to result from an absence of colony-stimulating factor-1 (CSF-1) and reported to be cured by treatment with CSF-1. Macrophage polykaryons are known to be formed by fusion of mononuclear precursors and the presence of subcutaneous implants can elicit the formation of macrophage polykaryons. In order to determine if recruitment of foreign body giant cells is also impaired in osteopetrotic mice, tissue reactions to subcutaneously implanted polyvinyl sponges were studied and compared with normal mice. Our result showed that, in the op mouse, recruitment of macrophages and foreign body giant cells in response to the implants was quantitatively not different from that of normal mice. However, these cells were smaller and did not migrate as deeply into the implant as those seen in normal littermates. In contrast, resident macrophages obtained by peritoneal lavage were significantly reduced in op mice. These data indicate that there is a deficiency in the ability of op mice to mount a foreign body giant cell response to an implanted sponge characterized by a deficiency in the recruitment of precursor cells that are capable of either full development and spreading or migration into the implanted sponge. These data add to the emerging appreciation of the regional differences among macrophage populations in their dependence on CSF-1 for differentiation and survival. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Colony-stimulating factor-1; Foreign body giant cell; Implant; Mouse; Osteopetrosis

Metastatic Crohn's disease of the forehead - Biancone, L.; Geboes, K.; Spagnoli, L.G.; Del Vecchio Blanco, G.; Monteleone, I.; Vavassori, P.; Palmieri, G.; Chimenti, S.; Pallone, F. (Inflammatory Bowel Diseases, 2002)
Background: Metastatic Crohn's disease (CD) involves the presence of cutaneous granuloma distant from the intestinal lesions related to the disease, usually observed in colonic CD. Case history: A 35-year-old female with a permanent ileostomy following proctocolectomy for CD presented in 1999 with a 2-month history of an unusual skin lesion of the forehead. A diagnosis of CD of the ileum, colon, and rectum had been made in 1994. In 1997, a proctocolectomy with ileostomy was performed due to fistulizing severe refractory disease. Microscopic aspects of the intestinal lesions showed deep and fissuring ulcers. After surgery, she went into remission, and a small bowel follow-up in 1999 showed no recurrence, when she presented with the skin lesion of the forehead. Microscopic data: Histological analysis of endoscopical and surgical intestinal specimens showed chronic granulomatous inflammation of the ileum, colon, and rectum, confirming the diagnosis of CD. The forehead skin biopsy was examined by three independent histopathologists. The lesion was composed of numerous small granulomas (Ziehl-Nielsen negative), with no foreign bodies, mainly composed of CD68-positive and periodic acid Schiff-negative monocytes. Despite the low number of lymphocytes, the macroscopical and microscopical aspect of the forehead lesion, together with the clinical history, led to a diagnosis of rare metastatic CD of the forehead. Conclusions: This case report describes the development of an unusual granulomatous skin lesion of the forehead in a patient with established CD showing no postoperative recurrence.
Keywords: Crohn's disease; Granulomatous disease; Metastatic Crohn's disease; Skin lesion, forehead

Evaluation of cellular adhesions on silicone and poly(methyl methacrylate) intraocular lenses in monkey eyes: An electron microscopic study - Ohnishi, Y.; Yoshitomi, T.; Sakamoto, T.; Fujisawa, K.; Ishibashi, T. (Journal of Cataract and Refractive Surgery, 2001)
Purpose: To assess the biocompatibility of intraocular lens (IOL) material by studying the number of cells adhering to IOLs in monkey eyes. Setting: Department of Ophthalmology, Kyushu University, Fukuoka, Japan. Methods: Silicone or poly(methyl methacrylate) (PMMA) IOL implantation was performed in 21 monkeys. One eye of each animal had surgery. The IOL-implanted eyes were enucleated 1, 2, 3, 5, and 7 days and 1, 3, 4, 5, and 9 months after the procedure. One eye was studied at each time. Cells on the anterior IOL surface were photographed using a scanning electron microscope, counted and assessed with NEC, Graphtec, and Nikon equipment, and then observed using a transmission electron microscope. Results: Leukocytes, macrophages, and giant cells were found on the anterior IOL surface. Numerous cells were observed on the PMMA IOLs in the early postoperative period; they gradually decreased. Few cells were seen on the silicone IOLs during the course of the study. The giant cells became larger during the postoperative period. Conclusion: The foreign-body reaction to silicone IOLs in monkey eyes was less than that to PMMA IOLs. © 2001 ASCRS and ESCRS.

Isolated Crohn's disease of the vermiform appendix or chronic granulomatous appendicis? - Tsianos, E.; Katsanos, K.; Mpaltayiannis, G.; Christodoulou, D. (Annals of Gastroenterology, 2001)
The etiology of granulomatous appendicitis includes infectious diseases, foreign bodies and diseases of unknown etiology such as Crohn's disease and sarcoidosis. Pain in the right lower guardant is a common symptom of intestinal Crohn's disease but, pain in this area can also be the presenting symptom of acute appendicitis. Crohn's disease affects any part of the gastrointestinal tract including the vermiform appendix. Crohn's disease initially confined to the appendix is rare and there are less than 100 well-documented cases in the literature. A 28-years-old female patient was admitted to our hospital because of fever up to 39°C and abdominal pain in hte right lower quadrant with bloating. Serology and faecal, urine and blood cultures for microbial infection including Yersinia proved negaive. Lower abdomen ultrasonography revealed no evidence of adnexae inflammation but suspected thickness of the bowel wall in the right lower quadrant. Because of no response to conservative treatment two months later surgery was performed. At laparotomy a long, thickened and distended appendix was found and removed. No other lesions were noted in the intestines or mesentery. Histological examination of the removed appendix showed signs compatible with Crohn's disease of the appendix. In case of Crohn's disease of the appendix two clinical possibilities may arise; the first is the presence of mild Crohn's disease in other intestinal parts and the second possibility is the risk of relapse which occured in 7-14% of the published cases. Could this case be regarded as an isolated Crohn's disease of the appendix or as a granulomatous and follicular appendicitis of unknown etiology (idiopathic) and unrelated to a "formal" Crohn's disease according to the accepted definition.
Keywords: Appenditis; Appendix; Crohn's disease; Granuloma

Simultaneous measurement of biopolymer-mediated Mac-1 up-regulation and adherence of neutrophils: A novel flow cytometric approach for predicting initial inflammatory interaction with foreign materials - Peltroche-Llacsahuanga, H.; Schmidt, S.; Schnitzler, N.; Lütticken, R.; Haase, G. (Journal of Immunological Methods, 2001)
Implantation of any medical device normally causes an inflammatory cell interaction with the foreign material. In vitro cell activation of human neutrophils (Mac-1 upregulation) has been taken as one measure to assess the attributable risk of inflammation due to biopolymers before their clinical application. Mac-1 expression has generally been measured by flow cytometric assays, whereas quantification of neutrophil adhesion to the biopolymer surfaces has been performed by separate and time-consuming assays, e.g. microscopically by differential cell counting. However, due to an increasing number of surface-modified novel biopolymers entering clinical usage, effective testing of their inflammatory potential is now mandatory. To facilitate these analyses, we have developed a novel flow cytometric assay permitting simultaneous measurement of biopolymer-mediated neutrophil activation and adhesion. The biopolymers were used as beads (diameter 25 ± 10 μm), and were demonstrated to be non-phagocytosable and non-fluorescent before being co-incubated with whole human blood (range of ratio granulocytes/beads from 5:1 to 1:1). Besides flow cytometric measurement of Mac-1 up-regulated neutrophils as fluorescing events, a fluorescence of the bead population indicates the adherence of activated neutrophils to the biopolymer surface. After establishing this assay, we evaluated it by comparing six different biopolymers. We observed high levels of Mac-1 expression (> 70% of positive control) accompanied by increased adhesiveness (> 60% of neutrophils) for polyurethane (PUR), polymethylmetacrylate (PMMA), and poly-DL-lactide (PDLLA) beads. Low Mac-1 expression levels (< 10%) accompanied by a low percentage of adhering neutrophils (< 10%) were observed for polyethylene (PE), polyisoprene (PI), and silicone (SI) beads. © 2001 Elsevier Science B.V. All rights reserved.
Keywords: Adhesion; Biomaterials; Flow cytometry; Mac-1; Neutrophils

Postoperative inflammation after lens epithelial cell removal: 2 Year results - Kruger, A.J.; Amon, M.; Abela-Formanek, C.; Schild, G.; Kolodjaschna, J.; Schauersberger, J. (Journal of Cataract and Refractive Surgery, 2001)
Purpose: To evaluate the influence on postoperative inflammation of lens epithelial cell (LEO) removal after phacoemulsification. Setting: Department of Ophthalmology, University of Vienna, Vienna, Austria. Methods: This randomized prospective single-surgeon study comprised 60 patients with senile cataract only. After a temporal clear corneal incision was made and phacoemulsification performed, no LEOs were removed in Group A, LEOs in the nasal half were removed in Group B, and LEOs were removed from the entire anterior capsule in Group C. The LEOs were removed with a Rentsch capsule curette (Geuder). In all eyes, a foldable hydrogel intraocular lens (Hydroview®, Bausch & Lomb) was implanted. Anterior chamber flare was evaluated through dilated pupils in a double-masked fashion using a Kowa FC-1000 laser flare-cell meter (LFCM). Measurements were done preoperatively as well as 1, 3, 7, 14, and 28 days and 3, 6, 12, and 24 months postoperatively. Results: In all 3 groups, the flare and cell values increased on the first postoperative day followed by a successive decrease thereafter. One month after surgery, the bloodaqueous barrier (BAB) was nearly restored in all groups. Between the first and fourth week, the flare values in Groups B and C were slightly lower than in Group A; however, mean flare and cell values among groups were not statistically significantly different at any measurement. Conclusion: The removal of LEOs from the anterior capsule with a Rentsch curette did not influence postoperative BAB changes detected using an LFCM. © 2001 ASCRS and ESCRS.

In vivo modulation of host response and macrophage behavior by polymer networks grafted with fibronectin-derived biomimetic oligopeptides: The role of RGD and PHSRN domains - Kao, W.J.; Lee, D. (Biomaterials, 2001)
Polymorphonuclear leukocytes, monocytes/macrophages, foreign body giant cells (FBGC), and lymphocytes are central in directing the host foreign body and inflammatory/immune reactions that impact material biostability, biocompatibility, and device efficacy. We employed the functional architecture of fibronectin to probe the mechanisms of protein-cell interaction in modulating leukocyte behavior. We demonstrated previously that the RGD and PHSRN domain of fibronectin and the spatial orientation between the motifs were crucial in regulating macrophage function in vitro. The current study delineates the role of RGD and PHSRN in modulating the host inflammatory response and macrophage behavior in vivo. Oligopeptides containing RGD and/or PHSRN domains were grafted onto a polyethyleneglycol-based substrate and subcutaneously cage implanted into rats. Peptide identity played a minimal role in modulating the host inflammatory response and adherent macrophage density. The RGD motif, either alone or at the terminal position with the PHSRN-containing flanking sequence, elicited a rapid macrophage fusion to form FBGCs at the early stage of implantation. Both the RGD motif and the PHSRN motif were important in mediating FBGC formation at the later implantation time. However, the PHSRN motif, specifically in the configuration of G3RGDG6PHSRNG, evoked a larger extent of FBGC coverage. Our results indicate the importance of RGD and PHSRN in modulating macrophage function in a time and orientation dependent fashion in vivo. © 2001 Elsevier Science Ltd. All rights reserved.
Keywords: Extracellular matrix proteins; Foreign body giant cells; Inflammation; Leukocytes; Polyethyleneglycols

Cellular reaction on the anterior surface of 4 types of intraocular lenses - Müllner-Eidenböck, A.; Amon, M.; Schauersberger, J.; Kruger, A.; Abela, C.; Petternel, V.; Zidek, T. (Journal of Cataract and Refractive Surgery, 2001)
Purpose: To assess the cellular reaction on the anterior surface of 4 types of foldable intraocular lenses (IOLs). Setting: Department of Ophthalmology, University Hospital of Vienna, Vienna, Austria. Methods: One hundred eyes scheduled for cataract surgery were prospectively randomized into 4 groups of 25 eyes each using random number tables. Group 1 received a Hydroview™ IOL (Bausch & Lomb), Group 2 an AcrySof® IOL (Alcon), Group 3 a MemoryLens® IOL (CRC), and Group 4 a CeeOn® 920 IOL (Pharmacia). Patients were examined 1, 3, 7, 30, 90, and 180 days postoperatively. Postoperative biomicroscopic examinations were done with a slitlamp, and a specular microscope was used to document the presence of cell deposits and identify areas with the highest density of cells. Results: The local tissue response revealed 2 patterns: a nonspecific foreign-body reaction to the IOL (small round, fibroblast-like, epithelioid, and giant cells) and a lens epithelial cell (LEC) reaction. The highest incidence of LECs was in the Hydroview group, in which LECs were present on 81.8% of lenses 180 days postoperatively. During the first postoperative days, small round and fibroblast-like cells were found on all IOLs. From 7 days on, the incidence and density of these cells were less severe in the Hydroview and CeeOn 920 groups. After several weeks, epithelioid cells and foreign-body giant cells were seen on some IOLs. These cells appeared more often on AcrySof, MemoryLens, and CeeOn IOLs. Conclusion: This study found ICL-related differences in cellular reaction after cataract surgery. The incidence of a nonspecific foreign-body reaction to 4 IOLs is consistent with the results of previous studies. The incidence of LECs was highest in the Hydroview group and lowest in the AcrySof group. The CeeOn 920 group had the lowest incidence of all types of cells.

Immunohistochemical characterization of the perivascular infiltrate in tissues adjacent to stainless steel implants compared with titanium implants - Thewes, M.; Kretschmer, R.; Gfesser, M.; Rakoski, J.; Nerlich, M.; Borelli, S.; Ring, J. (Archives of Orthopaedic and Trauma Surgery, 2001)
Metallic orthopaedics implants are composed of elements that are known to be skin sensitizers in the general population. In this study, we analyzed the cells of perivascular infiltration in the tissue adjacent to titanium (n = 23) and steel (n = 8) implants after explantation of the metals by immunohistochemical methods. The following panel of monoclonal antibodies were used as parameters: CD 1a (Langerhans cells), CD 4 (T-helper cells), CD 8 (T-suppressor cells), CD 11c (monocytes and macrophages), CD 45 RO (memory cells), CD 45 RA (naive cells), eosinophil cationic proteins (ECP), neutrophil elastase, and HLA-DR. The number of perivascular total cells did not differ significantly. All cells were identified in both metal subgroups, but a statistical difference was not seen in the above-mentioned parameters. We conclude that sensitization to metals is possible in the tissue adjacent to steel and titanium implants, because all cells which play an important role in allergic delayed-type hypersensitivity (type IV) reactions are present. This phenomenon may be called a 'pre-sensitization' phase, because no sensitization or allergic reactions were seen in our cases. Second, in the present study, a statistical difference was not seen in the number of infiltrate cells in the tissue adjacent to steel compared with titanium implants.
Keywords: Immunohistochemistry; Steel implant; Titanium implant

Histological reaction to hydroxyapatite in the middle ear of rats - Ye, Q.; Ohsaki, K.; Li, K.; Li, D.-J.; Zhu, C.-S.; Ogawa, T.; Tenshin, S.; Takano-Yamamoto, T. (Auris Nasus Larynx, 2001)
Objective: Present study was performed to evaluate the histological response of rat middle ear mucosa following implantation of Apaceram® granules, a synthetic dense hydroxyapatite [Ca10(PO4)6(OH)2], prepared from commercially available synthetic auditory ossicle, and to assess the precise histological response of the rat middle ear to implantation of Apaceram® granules, by microscopic examination of mucosal tissue at various time points after implantation. Methods: Apaceram® granules were implanted in the temporal bulla of 32 rats. As control, sham surgery was performed in a group of ten rats. Bulla specimens were removed at 1, 3, 7, 14, and 30 days after surgery in the implant and control groups, and at 90, 180 and 300 days in the implant group. Specimens were decalcified, sectioned at a thickness of 6 μm, and stained with haematoxylin and eosin, and Mallory's azan for histological examination of mucosal tissue. Results: Evidence of inflammatory reaction was slightly greater in the implant group than in controls. Lymphocyte and macrophage counts were higher in the implant group 1 day after surgery, but decreased to similar levels by day 3, and continued to decrease thereafter, and few were observed in the implant group at 300 days. Neutrophils observed at 1 day after surgery were not evident in either group at 3 days. Gradual fibrosis development continued in both groups over all time points studied. Foreign body giant cells were never observed in either group. No bony reaction was observed in any specimen. Conclusion: The results of this study suggest that Apaceram® is biocompatible and suitable for reconstructive ear surgery. Copyright © 2001 Elsevier Science Ireland Ltd.
Keywords: Bulla of rat; Cell count; Hydroxyapatite; Inflammatory cell

Cutaneous Inflammatory Reaction to a Wood Piece; A Peculiar Case of Implantation Dermatoses - Ueoku, S.; Maekawa, N.; Ishii, M.; Furukawa, M.; Tanii, T. (Skin Research, 2001)
A 55-year-old man was admitted to our hospital with infectious nodules on the right medial orbital area which he had noticed since about a month before. Laboratory tests showed mild liver dysfunction but WBC count, CRP, angiotensin converting enzyme (ACE) and CD4/8 ratio were all within normal limits. Serologic titers for anti-nuclear autoantibodies were negative. The tuberculin reaction was negative, and neither Mycobacterium tuberculosis nor other atypical Mycobacterium sp. were detected from the lesional tissue biopsy specimen. The magnetic resonance imaging suggested an existence of a foreign material in the right orbita. So he was underwent an operation and we found a wood piece which was about 5mm in diameter and about 35mm long. We propose that we should also pay attention to an existence of a foreign body if inflammatory granulomatous lesions are hardly healed by conservative medical treatments. © 2001, Meeting of Osaka Dermatological Association. All rights reserved.
Keywords: foreign body; implantation dermatosis; wood piece

Tissue response to single-polymer fibers of varying diameters: Evaluation of fibrous encapsulation and macrophage density - Sanders, J.E.; Stiles, C.E.; Hayes, C.L. (Journal of Biomedical Materials Research, 2000)
An in vivo study was conducted to assess the sensitivity of fibrous capsule thickness and macrophage density to polymer fiber diameter. Single polypropylene fibers of diameters ranging from 2.1 to 26.7 μm were implanted in the subcutaneous dorsum of Sprague-Dawley rats. Results at 5 weeks demonstrated reduced fibrous capsule thickness for small fibers. Capsule thickness was 0.6 (± 1.8) μm, 11.7 (± 12.0) μm, 20.3 (± 11.6) μm, and 25.5 (μ 10.0) μm for fibers in the ranges of 2.1 to 5.9, 6.5 to 10.6, 11.1 to 15.8, and 16.7 to 26.7 μm, respectively. Fibers very near to blood vessels had smaller capsules than did those with local vasculature further away. The macrophage density in tissue with fiber diameters 2.1 to 5.9 μm (23.03 ± 8.67%) was comparable to that of unoperated contralateral control skin (18.72 ± 10.06%). For fibers with diameters in the ranges of 6.5 to 10.6, 11.1 to 15.8, and 16.7 to 26.7 μm, macrophage densities were 33.90 ± 13.08%, 34.40 ± 15.77%, and 41.68 ± 13.98%, respectively, all of which were significantly larger (p < 0.002) than that for the control. The reduced fibrous capsule thickness and macrophage density for small fibers (< 6 μm) compared with large fibers could be due to the reduced cell-material contact surface area or to a curvature threshold effect that triggers cell signaling. A next step will be to extend the analysis to meshes to evaluate fiber- spacing effects on small-fiber biomaterials. (C) 2000 John Wiley and Sons, Inc. An in vivo study was conducted to assess the sensitivity of fibrous capsule thickness and macrophage density to polymer fiber diameter. Single polypropylene fibers of diameters ranging from 2.1 to 26.7 μm were implanted in the subcutaneous dorsum of Sprague-Dawley rats. Results at 5 weeks demonstrated reduced fibrous capsule thickness for small fibers. Capsule thickness was 0.6 (±1.8) μm, 11.7 (±12.0) μm, 20.3 (±11.6) μm, and 25.5 (±10.0) μm for fibers in the ranges of 2.1 to 5.9, 6.5 to 10.6, 11.1 to 15.8, and 16.7 to 26.7 μm, respectively. Fibers very near to blood vessels had smaller capsules than did those with local vasculature further away. The macrophage density in tissue with fiber diameters 2.1 to 5.9 μm (23.03 ± 8.67%) was comparable to that of unoperated contralateral control skin (18.72 ± 10.06%). For fibers with diameters in the ranges of 6.5 to 10.6, 11.1 to 15.8, and 16.7 to 26.7 μm, macrophage densities were 33.90 ± 13.08%, 34.40 ± 15.77%, and 41.68 ± 13.98%, respectively, all of which were significantly larger (p < 0.002) than that for the control. The reduced fibrous capsule thickness and macrophage density for small fibers (<6 μm) compared with large fibers could be due to the reduced cell-material contact surface area or to a curvature threshold effect that triggers cell signaling. A next step will be extend the analysis to meshes to evaluate fiber-spacing effects on small-fiber biomaterials.
Keywords: Fibro-porous biomaterials; Fibrous encapsulation; Macrophage; Microfibers; Polypropylene

Intraperitoneal gossypibomas: The need to count sponges - Lauwers, P.R.; Van Hee, R.H. (World Journal of Surgery, 2000)
Intraperitoneal forgotten foreign bodies are prone to create adhesions and to encapsulate, or to provoke an exudative response, with or without accompanying bacterial infection. Often a process of self-extrusion is initiated. This is also true for gossypibomas, retained surgical sponges. Presentation is possible as a pseudotumoral, occlusive, or septic syndrome; several cases, however, have remained asymptomatic for as long as several decades. Ultrasonography and radiology (especially computed tomography) contribute significantly to the detection of gossypibomas; magnetic resonance imaging is a less used technique. Detection by plain radiography is difficult. Ultrasonography demonstrates a hyperreflective mass with hypoechoic rim and a strong posterior shadow. Computed tomography shows a well defined mass with internal heterogenous densities. Therapy consists of operative removal of the foreign body in association with resolving its complications. Adding a series of five cases to the existing literature reports, the fate of intraperitoneal forgotten surgical sponges is reviewed.

Increased interleukin-8 (IL-8) expression is related to aseptic loosening of total hip replacement - Lassus, J.; Waris, V.; Xu, J.-W.; Li, T.-F.; Hao, J.; Nietosvaara, Y.; Santavirta, S.; Konttinen, Y.T. (Archives of Orthopaedic and Trauma Surgery, 2000)
Aseptic loosening is an increasing problem in total hip replacement (THR). Chronic inflammatory reaction against implant wear particle results in collageno- and osteolysis, leading to loosening of the implant. Cytokines are known to play a major role in this particular inflammatory process. The aim of the present study was to examine interleukin-8 (IL-8) in the synovial-like interface membrane (SLIM) and pseudocapsular tissue of THRs and to compare it to normal knee synovial membrane. Eleven patients suffering from aseptically loosened THRs were included. All the SLIM and pseudocapsular tissue samples were obtained during revision operations. Ten control samples of normal synovium were collected per arthroscopy from the superior recessus of the knee. For immunohistochemical IL-8 detection, polyclonal mouse anti-human immunoglobulin (Ig)G1 IL-8-primary antibody was used with the alkaline phosphatase anti-alkaline phosphatase (APAAP) method. Results were quantitated using the Vidas image analysis system. The highest count levels (mean ± SEM) were detected in SLIM tissue (386 ± 82 cells/mm2). The difference was statistically significant compared with pseudocapsular tissue (193 ± 36 cells/mm2) and control samples (18 ± 5 cells/mm2). Count levels in control tissue were on average 5% of the SLIM tissues values. The present study determines for the first time the cellular origin of IL-8 in aseptically loosened THRs and also quantitates the IL-8-producing cells in the periprosthetic tissue. The results reveal a high rise in IL-8 concentration in SLIM and in synovial tissues. This finding moves us one step forward in solving the complex network of multiple factors affecting loosening of hip implants.
Keywords: Aseptic loosening; Immunohistochemistry; Interleukin-8; Total hip replacement

Tissue-engineered cartilage using serially passaged articular chondrocytes. Chondrocytes in alginate, combined in vivo with a synthetic (E210) or biologic biodegradable carrier (DBM) - Marijnissen, W.J.C.M.; Van Osch, G.J.V.M.; Aigner, J.; Verwoerd-Verhoef, H.L.; Verhaar, J.A.N. (Biomaterials, 2000)
In vitro multiplication of isolated autologous chondrocytes is required to obtain an adequate number of cells to generate neo-cartilage, but is known to induce cell-dedifferentiation. The aim of this study was to investigate whether multiplied chondrocytes can be used to generate neo-cartilage in vivo. Adult bovine articular chondrocytes, of various differentiation stages, were suspended in alginate at densities of 10 or 50 million/ml, either directly after isolation (P0) or after multiplication in monolayer for one (P1) or three passages (P3). Alginate with cells was seeded in demineralized bovine bone matrix (DBM) or a fleece of polylactic/polyglycolic acid (E210) and implanted in nude mice for 8 weeks. The newly formed tissue was evaluated by Alcian Blue and immunohistochemical staining for collagen type-II and type-I. Structural homogeneity of the tissue, composed of freshly isolated as well as serially passaged cells, was found to be enhanced by high-density seeding (50 million/ml) and the use of E210 as a carrier. The percentage of collagen type-II positive staining P3-cells was generally higher when E210 was used as a carrier. Furthermore, seeding P3-chondrocytes at the highest density (50 million/ml) enhanced collagen type-II expression. This study shows promising possibilities to generate structurally regular neo-cartilage using multiplied chondrocytes in alginate in combination with a fleece of polylactic/polyglycolic acid. Copyright (C) 2000 Elsevier Science B.V. In vitro multiplication of isolated autologous chondrocytes is required to obtain an adequate number of cells to generate neo-cartilage, but is known to induce cell-dedifferentiation. The aim of this study was to investigate whether multiplied chondrocytes can be used to generate neo-cartilage in vivo. Adult bovine articular chondrocytes, of various differentiation stages, were suspended in alginate at densities of 10 or 50 million/ml, either directly after isolation (P0) or after multiplication in monolayer for one (P1) or three passages (P3). Alginate with cells was seeded in demineralized bovine bone matrix (DBM) or a fleece of polylactic/polyglycolic acid (E210) and implanted in nude mice for 8 weeks. The newly formed tissue was evaluated by Alcian Blue and immunohistochemical staining for collagen type-II and type-I. Structural homogeneity of the tissue, composed of freshly isolated as well as serially passaged cells, was found to be enhanced by high-density seeding (50 million/ml) and the use of E210 as a carrier. The percentage of collagen type-II positive staining P3-cells was generally higher when E210 was used as a carrier. Furthermore, seeding P3-chondrocytes at the highest density (50 million/ml) enhanced collagen type-II expression. This study shows promising possibilities to generate structurally regular neo-cartilage using multiplied chondrocytes in alginate in combination with a fleece of polylactic/polyglycolic acid.
Keywords: Alginate; Biomaterials; Cell density; Cultured chondrocytes; Nude mice

Long-term results of out-of-the-bag intraocular lens implantation - Amino, K.; Yamakawa, R. (Journal of Cataract and Refractive Surgery, 2000)
Purpose: To evaluate long-term results of out-of-the-bag intraocular lens (IOL) implantation. Setting: Department of Ophthalmology, Tenri Yorozu Hospital, Nara, Japan. Methods: This study comprised 22 patients, 13 women and 9 men, who had cataract surgery by phacoemulsification and out-of-the-bag IOL implantation because of a posterior lens capsule rupture. Sixteen patients had in-the-bag IOL implantation in the fellow eye, and these eyes were used as a control group. The IOL's position was determined by ultrasound biomicroscopy (UBM). Anterior chamber flare counts were measured by a laser flare meter. The corneal endothelium was observed by specular microscopy. Results: Mean follow-up after cataract surgery was 35 months ± 22 (SD). The UBM revealed that in the 19 eyes with sulcus-to-sulcus IOL fixation, the optics touched the iris. In 3 eyes, 1 haptic was fixated at the sulcus and the other at the ciliary body. In 2 of these eyes, the optics did not touch the iris. Anterior chamber flare counts in eyes with sulcus-to-sulcus IOL fixation were significantly higher than in eyes with in-the-bag or sulcus-to- ciliary-body fixation (P < .05). There were no statistical differences in corneal endothelial cell counts based on haptic placement. Conclusion: Rubbing between the IOL optic and iris seems to contribute to the high flare counts in eyes with a sulcus-to-sulcus IOL fixation. A larger haptic angle may be needed to prevent contact between the iris and IOL optic in such cases. (C) 2000 ASCRS and ESCRS.

In vivo behavior of epoxy-crosslinked porcine heart valve cusps and walls - Van Wachem, P.B.; Brouwer, L.A.; Zeeman, R.; Dijkstra, P.J.; Feijen, J.; Hendriks, M.; Cahalan, P.T.; Van Luyn, M.J.A. (Journal of Biomedical Materials Research, 2000)
Calcification limits the long-term durability of xenograft glutaraldehyde-crosslinked heart valves. In this study, epoxy-crosslinked porcine aortic valve tissue was evaluated after subcutaneous implantation in weanling rats. Non-crosslinked valves and valves crosslinked with glutaraldehyde or carbodiimide functioned as control. Epoxy-crosslinked valves had somewhat lower shrinkage temperatures than the crosslinked controls, and within the series also some macroscopic and microscopic differences were obvious. After 8 weeks implantation, cusps from non- crosslinked valves were not retrieved. The matching walls were more degraded than the epoxy- and control-crosslinked walls. This was observed from the higher cellular ingrowth with fibroblasts, macrophages, and giant cells. Furthermore, non-crosslinked walls showed highest numbers of lymphocytes, which were most obvious in the capsules. Epoxy- and control-crosslinked cusps and walls induced lower reactions. Calcification, measured by von Kossa- staining and by Ca-analysis, was always observed. Crosslinked cusps calcified more than walls. Of all wall samples, the non-crosslinked walls showed the highest calcification. It is concluded that epoxy-crosslinked valve tissue induced a foreign body and calcification reaction similar to the two crosslinked controls. Therefore, epoxy-crosslinking does not represent a solution for the calcification problem of heart valve bioprostheses. Calcification limits the long-term durability of xenograft glutaraldehyde-crosslinked heart valves. In this study, epoxy-crosslinked porcine aortic valve tissue was evaluated after subcutaneous implantation in weanling rats. Non-crosslinked valves and valves crosslinked with glutaraldehyde or carbodiimide functioned as control. Epoxy-crosslinked valves had somewhat lower shrinkage temperatures than the crosslinked controls, and within the series also some macroscopic and microscopic differences were obvious. After 8 weeks implantation, cusps from non-crosslinked valves were not retrieved. The matching walls were more degraded than the epoxy- and control-crosslinked walls. This was observed from the higher cellular ingrowth with fibroblasts, macrophages, and giant cells. Furthermore, non-crosslinked walls showed highest numbers of lymphocytes, which were most obvious in the capsules. Epoxy- and control-crosslinked cusps and walls induced lower reactions. Calcification, measured by von Kossa-staining and by Ca-analysis, was always observed. Crosslinked cusps calcified more than walls. Of all wall samples, the non-crosslinked walls showed the highest calcification. It is concluded that epoxy-crosslinked valve tissue induced a foreign body and calcification reaction similar to the two crosslinked controls. Therefore, epoxy-crosslinking does not represent a solution for the calcification problem of heart valve bioprostheses.
Keywords: Calcification; Crosslinking; Epoxy; Heart valve; Prosthesis

Complications of foreign bodies in the esophagus - Loh, K.S.; Tan, L.K.S.; Smith, J.D.; Yeoh, K.H.; Dong, F. (Otolaryngology - Head and Neck Surgery, 2000)
Major complications of foreign bodies in the esophagus carry significant morbidity and mortality risks. A retrospective case control study was performed to assess the factors associated with major complications. In total, 273 patients seen within a 7-year period were divided into 2 groups; 253 had no or minor complications, and 20 had major complications. Age, sex, duration of the foreign body, total white cell count (TWC), and nature and site of the foreign body were analyzed in the 2 groups. The major complication rate was 7.3%. Duration of the foreign body and TWC were the only statistically significant factors associated with major complications. Six patients required open neck exploration, 1 had an open thoracotomy, and 13 were treated by endoscopic removal. There were 2 deaths. Given the significant morbidity and mortality risks, we conclude that patients with a prolonged history of a foreign body in the esophagus and a raised TWC should be treated urgently.

Imaging of surgical paraphernalia: What belongs in the patient and what does not - Wolfson, K.A.; Seeger, L.L.; Kadell, B.M.; Eckardt, J.J. (Radiographics, 2000)
Many radiologists are not familiar with the names of various instruments, surgical sponges, and needles that may be seen on intraoperative and postoperative radiographs. These devices may be intentionally placed for localization or therapeutic intervention, discovered on radiographs obtained to evaluate incorrect sponge or needle counts, or incidentally encountered on postoperative radiographs. These paraphernalia are usually described in vague nonspecific terms in radiology reports. In this article, photographs and radiographs of several instruments commonly used for intraoperative localization or therapy are presented, as well as examples of sponges, needles, and other devices that should not be found on postoperative radiographs. Familiarity with their appearances will allow a more precise and knowledgeable description in radiology reports.
Keywords: Foreign bodies, 458; Radiology and radiologists, iatrogenic injury; Surgery, complications, 458

Octylcyanoacrylate: A new medical-grade adhesive for otologic surgery - Maw, J.L.; Kartush, J.M.; Bouchard, K.; Raphael, Y. (American Journal of Otology, 2000)
Hypothesis: The adhesive octylcyanoacrylate is not associated with significant inner ear toxicity in a guinea pig model. Background: Many cyanoacrylate adhesives have been investigated for use in otologic surgery, but variable ototoxicity has been reported. Octylcyanoacrylate is a medical- grade adhesive with many properties that make it ideal for use in the ear. It is free of contaminants; it forms a strong, flexible bond; and it inhibits the growth of gram-positive organisms in culture. This is the first study to assess the ototoxicity of this new adhesive. Methods: Fourteen adult guinea pigs were used. Preoperative auditory brainstem responses (ABRs) were determined. Bilateral antrotomies were performed, and the ears were randomized to adhesive and control (saline) groups. In the adhesive ears, 0.5 or 0.1 mL of octylcyanoacrylate was instilled into the middle ear. Eight weeks later, postoperative ABRs were determined, the animals were killed, and the temporal bones were removed. Middle ear changes were noted, and the ossicular chain was assessed. Cochlear hair cell analyses were performed. Histologic assessment of the middle ear mucosa was performed. Results: There was a higher incidence of conductive hearing loss in the adhesive group secondary to fixation of the ossicular chain, but there was no significant difference in bone conduction thresholds. The median postoperative bone conduction thresholds (dB peak sound pressure level) was 15.0 in the control group and 17.5 in the adhesive group, p = 0.89. There was also no significant difference in inner hair cell counts (0.4% vs. 0.5% median hair cell loss, p = 0.72) or outer hair cell counts (3.7% vs. 3.0% median hair cell loss, p = 0.23) for the adhesive and control groups, respectively. Histopathologic analysis of the middle ear mucosa demonstrated variable mild to moderate foreign body reaction with no evidence of mucosal ulceration or necrosis. Conclusions: A large amount of octylcyanoacrylate placed in the middle ear of the guinea pig did not cause any morphologic or functional evidence of inner ear toxicity. This new adhesive is a promising tool for otologic surgery.
Keywords: Cyanoacrylate adhesive; Inner ear toxicity; Otologic surgery; Tissue adhesives

Is endovascular treatment of abdominal aortic aneurysms less invasive regarding the biological responses? - Morikage, N.; Esato, K.; Zenpo, N.; Fujioka, K.; Takenaka, H. (Surgery Today, 2000)
To compare the biological responses following an endoluminal repair and a conventional open repair of abdominal aortic aneurysm (AAA), 14 patients who underwent an endoluminal repair (endograft group) and 26 who underwent an open repair (open group) were investigated. As markers of biological responses, interleukin-6 (IL-6) and -8 (IL-8), granulocyte elastase (GEL), white blood cell count (WBC), and serum C-reactive protein (CRP) were all measured preoperatively as well as on postoperative days (POD) 1, 3, and 6. In addition, the blood loss, duration of surgery, initial oral intake the day after surgery, and length of hospital stay were compared between both groups. The plasma levels of IL-6, GEL, CRP, and WBC were higher in the endograft group than in the open group, while the CRP, WBC, and GEL levels all peaked on POD 3. The plasma level of IL-6 remained high in the endograft group, compared with that in the open group throughout the study period. Conversely, blood loss, initial oral intake the day after surgery, and the length of hospital stay were all significantly greater in the open group than in the endograft group, although there was no significant difference in the duration of surgery between the two groups. These findings indicate that although the endoluminal repair of AAA is supposed to be less invasive, the biological responses tend to be greater because of the manipulation related to the insertion of the stent graft.
Keywords: Abdominal aortic aneurysm; Biological response; Conventional open repair; Endoluminal repair; Stent graft

Sutures alone are sufficient to support regeneration across a gap in the continuity of the sciatic nerve in rats - Scherman, P.; Lundborg, G.; Kanje, M.; Dahlin, L.B. (Scandinavian Journal of Plastic and Reconstructive Surgery and Hand Surgery, 2000)
We have proposed that it is sufficient to provide a simple substratum on which regenerating axone may traverse a gap in a peripheral nerve. To test this hypothesis we set up a new experimental model in which sutures where used to bridge a 10 mm long defect in a peripheral nerve. A defect was created bilaterally in 25 rat sciatic nerves. The cut ends of the nerve were joined by three laps of a continuous suture, on one side with 8/0 polyamide (non-absorbable) and on the other with 8/0 polyglactin (absorbable), leaving a 7 mm gap. At two weeks a matrix that contained capillaries, fibroblast-like cells, and mononuclear cells had formed between the nerve endings, and the sutures were surrounded by foreign-body-like tissue reactions. At four weeks axone had grown into the distal nerve segment on both sides in 65%-90% of the cases as indicated by a response to the pinch reflex test and immunocytochemistry for presence of neurofilament protein. Axons were organised in minifascicles and these tended to grow larger as the demarcation of the entire regenerated segment by a perineurial-like structure improved with time. At 12 weeks axonal counts of cross-sections of the distal tibial trunk showed many myelinated nerve fibres but no significant difference in axonal counts or degree of myelination between the polyamide and polyglactin sides. The results show that conventional sutures alone are sufficient to support regeneration across a short gap in a peripheral nerve, a method that may be of potential clinical value.
Keywords: Absorbable sutures; Axonal growth; Fibrin matrix; Nerve regeneration; Nerve repair; Non-absorbable sutures; Sciatic nerve

Expanded Polytetrafluoroethylene in External Valvuloplasty for Superficial or Deep Vein Incompetence - Belcaro, G.; Nicolaides, A.N.; Errichi, B.M.; Incandela, L.; de Sanctis, M.T.; Laurora, G.; Ricci, A. (Angiology, 2000)
The authors evaluated the long-term safety of expanded polytetrafluoroethylene (ePTFE) implants used in external valvuloplasty for treatment of incompetence of the long saphenous and common and superficial femoral veins. During a 15-year period patients with superficial and/or deep venous disease and hypertension due to pure superficial or deep vein incompetence underwent an external valvuloplasty with ePTFE sutures, or an ePTFE cardiovascular patch placed as a sleeve around the incompetent vein segment, or an ePTFE tubular graft placed around the venous segment. Postoperative follow-up evaluations consisted of clinical examinations, high-resolution ultrasonography, and color duplex scanning, and a complete blood count performed at 1, 3 and 6 months, and repeated for at least 4 years, every 2 years after the procedure. A total of 101 patients (38 men and 63 women; mean [± sd] age, 44 ±12 years) underwent external valvuloplasty between January 1983 and December 1998; 82 of them completed the 4-year follow-up. Forty of the 82 patients had been operated on for superficial vein incompetence, 42 for deep vein incompetence. Overall, the mean follow- up time was 7.8 ± 3.6 years (range, 4 to 13). There were no infections, thromboses, foreign-body reactions to the ePTFE implants, or other prosthesis-related complications requiring explantation. One granuloma (noninfected) developed in association with a tubular ePTFE implant around a long saphenous vein, but it did not necessitate implant removal. Seven patients required (at least after 4 years) a second procedure for recurrent or new venous incompetence. Therefore, in this observational study, ePTFE implants used to treat or correct venous incompetence were well tolerated on a long- term basis. © 2000, Sage Publications. All rights reserved.

Effect of intraperitoneal and extraperitoneal insertion of mesh on bacterial translocation: Does it make a difference? - Baykal, A.; Günbatili, F.; Aran, Ö.; Hasçelik, G.; Korkmaz, A.; Sayek, I. (European Journal of Surgery, 1999)
Objective: To asses the effect of insertion of mesh, with or without contact with the peritoneum, on the induction of bacterial translocation. Design: Open experimental study. Setting: Surgical research laboratory, Turkey. Subjects: 158 Swiss albino mice. Interventions: A defect in the abdominal wall was created. In the control group, the defect was closed primarily. In the extraperitoneal group, polypropylene mesh was sutured over the abdominal wall after primary closure of the peritoneum and in the intraperitoneal group, polypropylene mesh was sutured to close the created defect so that it was in contact with the intestines. Main outcome measures: Bacterial translocation at 4, 24 and 48 hours. Results: Insertion of mesh in contact with the peritoneum led to increased bacterial translocation to mesenteric lymph nodes at 4 (p=0.02) and 48 (p=0.03) hours compared with insertion without contact. Conclusion: Contact between a foreign body and the peritoneum is required to induce bacterial translocation.
Keywords: Bacterial translocation; Mesh; Polypropylene

Histiocyte reaction in rabbit femurs to UHMWPE, metal, and ceramic particles in different sizes - Kubo, T.; Sawada, K.; Hirakawa, K.; Shimizu, C.; Takamatsu, T.; Hirasawa, Y. (Journal of Biomedical Materials Research, 1999)
To assess the histologic reaction caused by biomaterial particles in different sizes around the bone-implant interface, we examined ultra-high molecular weight polyethylene (UHMWPE, average diameter of 11 μm), UHMWPE (99 μm), cobalt-chromium alloy (Co-Cr, 3.9 μm), stainless steel (SUS316L, 3.9 μm), alumina ceramics (3.9 μm), titanium alloy (Ti, 3.5 μm), Co-Cr (0.03 μm), and Ti (0.03 μm). After the longitudinal groove on a polymethylmethacrylate plug was filled with one type of the particles, the plug was inserted into the medullar canal of the distal end of rabbit femurs, and tissue block was resected 4 and 12 weeks after the insertion. Histiocytes were markedly accumulated around the particles of UHMWPE (11 μm), Co-Cr (3.9 μm), SUS316L (3.9 μm), Co-Cr (0.03 μm), and titanium alloy (0.03 μm). Around the UHMWPE particles (99 μm), a slight histiocytic reaction and bone formation were observed. Particles of alumina ceramics (3.9 μm) and titanium alloy (3.5 μm) which were in phagocytosable sizes also had few histiocytic reactions. Statistically, the material difference was more strongly related to the histiocyte reaction than to the particle size and calculated total surface area of particles. Our findings demonstrate that particles of different biomaterials and in different sizes induce different foreign-body histological reactions. A study was conducted to clarify the relationship between histiocyte reaction. For this study, ultra-high molecular weight polyethylene (UHMWPE), cobalt-chromium alloy (Co-Cr), stainless steel, alumina ceramics, titanium alloy, and Ti were examined. As a first step, the longitudinal groove on a polymethacrylate plug was filled with one type of the particles. Following this, the plug was inserted into the medullar canal of the distal end of rabbit femurs, and tissue block was resected four and twelve weeks after the insertion. The data obtained indicate that particles of different biomaterials and in different sizes induce different foreign-body histological reactions.
Keywords: Biomaterials; Histological reaction; Particle; Size; Surface area

In vitro cytotoxicity and in vivo biocompatibility of poly(propylene fumarate-co-ethylene glycol) hydrogels - Suggs, L.J.; Shive, M.S.; Garcia, C.A.; Anderson, J.M.; Mikos, A.G. (Journal of Biomedical Materials Research, 1999)
The in vitro cytotoxicity and in vivo biocompatibility of poly(propylene fumarate-co-ethylene glycol) [P(PF-co-EG)] hydrogels were assessed in order to investigate the influence of poly(ethylene glycol) molecular weight and copolymer composition. These materials have application as injectable cardiovascular implants; cytotoxicity due to leachable products, as well as inflammation caused by the biomaterial itself, may ultimately affect the biocompatibility of the implant. We utilized a 7-day in vitro cytotoxicity assay to quantify cell density and cellular proliferation in the presence of copolymer films. The copolymer films exhibited slight to moderate cytotoxicity toward cultured endothelial cells, showing 20-86% viability relative to controls. Cell viability increased with an increasing weight percent of PEG or, to a lesser extent, the molecular weight of PEG. In vivo biocompatibility was assessed using a cage implantation model over a 21-day time period. This system was used to characterize the local cellular and humoral inflammatory response in the surrounding exudate, as well as the size and density of macrophages adherent to the material itself. All copolymer formulations exhibited excellent biocompatibility relative to controls with no significant differences in total leukocyte count among the different formulations. The in vivo inflammatory reaction displayed normal wound healing over 21 days as shown by a progressive decrease in both leukocyte concentration and enzymatic activity. The surface coverage of the copolymer films remained relatively constant from 7 to 21 days. There were no cells larger than 0.003 mm2, which was previously shown to be the threshold value for foreign-body giant cells. These data suggest that P(PF-co-EG) hydrogels have potential for use as injectable biomaterials. The in vitro cytotoxicity and in vivo biocompatibility of poly(propylene fumarate-co-ethylene glycol) [P(PF-co-EG)] hydrogels were assessed in order to investigate the influence of poly(ethylene glycol) molecular weight and copolymer composition. These materials have application as injectable cardiovascular implants; cytotoxicity due to leachable products, as well as inflammation caused by the biomaterial itself, may ultimately affect the biocompatibility of the implant. We utilized a 7-day in vitro cytotoxicity assay to quantify cell density and cellular proliferation in the presence of copolymer films. The copolymer films exhibited slight to moderate cytotoxicity toward cultured endothelial cells, showing 20-86% viability relative to controls. Cell viability increased with an increasing weight percent of PEG or, to a lesser extent, the molecular weight of PEG. In vivo biocompatibility was assessed using a cage implantation model over a 21-day time period. This system was used to characterize the local cellular and humoral inflammatory response in the surrounding exudate, as well as the size and density of macrophages adherent to the material itself. All copolymer formulations exhibited excellent biocompatibility relative to controls with no significant differences in total leukocyte count among the different formulations. The in vivo inflammatory reaction displayed normal wound healing over 21 days as shown by a progressive decrease in both leukocyte concentration and enzymatic activity. The surface coverage of the copolymer films remained relatively constant from 7 to 21 days. There were no cells larger than 0.003 mm2, which was previously shown to be the threshold value for foreign-body giant cells. These data suggest that P(PF-co-EG) hydrogels have potential for use as injectable biomaterials.
Keywords: Biocompatibility; Cardiovascular stent; Cytotoxicity; Hydrogel; Poly(ethylene glycol); Poly(propylene fumarate); Tissue engineering

Subcutaneous inflammatory reaction to a synthetic auditory ossicle (Bioceram®) in rats - Ye, Q.; Ohsaki, K.; Ii, K.; Li, D.-J.; Zhu, C.-S.; Yamashita, Y.; Tenshin, S.; Takano-Yamamoto, T. (Acta Oto-Laryngologica, 1999)
Cellular response and inflammatory reaction to synthetic auditory ossicle (Bioceram®) made from aluminium oxide are investigated. Local inflammatory effects are important in wound healing and in determining biocompatibility of an implant, necessitating the study of biologic effects of implants, especially inflammation and fibrous capsule formation. Bioceram® discs were implanted subcutaneously in the interscapular region of rats for various periods of time, ranging from 1 day to 300 days. Histological sections 6 μm thick were stained with haematoxylin and eosin. Cell types around the implants were examined quantitatively by light microscopy. Inflammatory cell reaction to Bioceram® decreased rapidly within 14 days, similar to the reaction in control groups. From 30 days to 300 days after implantation, there was continuous reduction to very low levels for macrophages and lymphocytes, but fibrous connective tissue capsule around implants matured. Preliminary results suggest that Bioceram® is a satisfactory biocompatible material for reconstructive surgery from the viewpoint of cellular response. We also briefly discuss the different tissue responses in light of our previous study on hydroxyapatite (Apaceram®).
Keywords: Aluminium oxide; Biocompatibility; Cell count; Ceramics; Histology

Recommended practices for sponge, sharp, and instrument counts. AORN Recommended Practices Committee. Association of periOperative Registered Nurses. (AORN journal, 1999)

Getting the sponge count right. - Langslow, A. (Australian nursing journal (July 1993), 1999)

Deep lamellar keratoplasty versus penetrating keratoplasty for corneal lesions - Panda, A.; Bageshwar, L.M.S.; Ray, M.; Singh, J.P.; Kumar, A. (Cornea, 1999)
Purpose. To compare the effectiveness of deep lamellar keratoplasty (DLK) with that of penetrating keratoplasty (PKP) in cases of corneal lesions not involving the endothelium. Methods. Forty-eight eyes with leukomatous corneal opacity (n = 33), keratoconus with apical scarring (n = 6), granular corneal dystrophy (n = 5), lattice corneal dystrophy (n = 2), and multiple corneal foreign bodies (n = 2) in an age group varying from 16 to 53 years underwent DLK (n = 24) and PKP (n = 24) by utilizing B and (B+ and A) grade M-K preserved donor tissue, respectively. The patients were followed up closely, and the graft clarity, visual achievement, astigmatism and endothelial cell count were evaluated at repeated occasions up to 1 year. Results. Astigmatism of <3 diopters (D) and ≥5D was obtained in 19 eyes and one eye, respectively, after DLK at 6 months, whereas six eyes of the PKP group had astigmatism <3D, and 12 eyes had ≥5D at the end of 6 months. The same at 1 year was observed in 20 and one eye in the DLK and eight and five eyes of the PKP group. Astigmatism of ≥5D at the end of 6 months in both the groups showed highly significant changes (p < 0.001). Best corrected visual acuity of 6/18 or more was achieved in 18 and 12 eyes at 6 months after DLK and PKP, respectively, which were statistically highly significant (p < 0.001), whereas at 1 year, it was seen in 17 and 15 eyes of the DLK and PKP groups, respectively, which was nonsignificant. The mean endothelial cell count was 2,233.3 ± 64.453 cells/mm2 and 2,219.6 ± 102.48 cells/mm2 at 6 months and 1 year, respectively, after DLK, which was nonsignificant. The mean cell count of the donor eyes used for PKP was 2,191 ± 52.164 cells/mm2, 1,902.8 ± 70.346 cells/mm2 at 6 months, and 1,579.0 ± 80.24 cells/ram2 at 1 year. All the values showed highly significant changes (p < 0.001). Further, the graft clarity of ≥3+ was achieved in 20 and 18 eyes at 6 months postoperatively in the DLK and PKP groups, whereas the same was observed in 19 and 13 eyes of both the groups, respectively, at 1-year follow-up. Conclusion. DLK is a promising procedure and should be practiced more frequently for corneal pathology not involving the endothelium.
Keywords: 8 Endothelium; Astigmatism; Deep lamellar keratoplasty; Penetrating keratoplasty; Stroma

Postoperative Textilomas: Review of 14 Cases - Fernandez Lobato, R.; Marin Lucas, F.J.; Fradejas Lopez, J.M.; Diaz Gimenez, L.M.; Camarero Marina, E.; Moreno Azcoita, M. (International Surgery, 1998)
Background. Textile materials of surgical origin are found in the abdominal cavity in between 1/1300 and 1/1500 laparotomies, in spite of preventive measures. It is very difficult to ascertain the exact incidence due to the lack of descriptions in the literature. Methods. Fourteen cases of postoperative foreign bodies or textilomas are reported. The cases were collected from two hospital centers between 1985 and 1997. Results. There were 12 intra-abdominal cases, 1 thoracic and 1 paravertebral. In 8 (57.1%) diagnosis was made preoperatively by radiological techniques. The mortality rate was 142% with 2 deaths due to multiorganic failure in one case and sepsis in the other. Both patients were over 70, with malignant pathology. The morbidity rate was 21.4%, wall abscesses which evolved favorably being the most frequent cause of complications. Conclusions. Prevention of this complication is the best treatment. It is advisable to use textile material with radiopaque contrast, to count the pieces of material to be used and perform an X-ray before the laparotomy is closed specially in emergency (bleeding and trauma patients) because in these complex cases the possibility of material being left behind is more advisable.
Keywords: Gossypibomas; Postoperative foreign bodies; Surgical gauze and compresses; Textilomas

Analysis of the inflammatory response to titanium and PTFE implants in soft tissue by macrophage phenotype quantification - Rosengren, A.; Bjursten, L.M.; Danielsen, N. (Journal of Materials Science: Materials in Medicine, 1998)
Implants of commercially pure titanium and polytetrafluoroethylene (PTFE) were inserted in the rat abdominal wall for 1, 6 or 12 wk. The foreign-body reaction was evaluated by immunohistochemical quantification of monocytes/macrophages and by the thickness of the foreign-body capsule. At all time intervals, the majority of interfacial cells were ED1-positive while ED2-positive cells were localized deeper in the tissue. Neither titanium nor PTFE displayed a significant change in capsule thickness over time. The total cell numbers decreased over time for both types of material. At 12 wk the PTFE implants, compared to titanium, were surrounded by a significantly thicker reactive capsule with larger total cell numbers. No significant differences were seen in the macrophage subset response between the two types of implants. Thus, the present study showed differences between titanium and PTFE at 12 wk but not at earlier time points. Implants of commercially pure titanium and polytetrafluoroethylene (PTFE) were inserted in the rat abdominal wall for 1, 6 or 12 wk. The foreign-body reaction was evaluated by immunohistochemical quantification of monocytes/macrophages and by the thickness of the foreign-body capsule. At all time intervals, the majority of interfacial cells were ED1-positive while ED2-positive cells were localized deeper in the tissue. Neither titanium nor PTFE displayed a significant change in capsule thickness over time. The total cell numbers decreased over time for both types of material. At 12 wk the PTFE implants, compared to titanium, were surrounded by a significantly thicker reactive capsule with larger total cell numbers. No significant differences were seen in the macrophage subset response between the two types of implants. Thus, the present study showed differences between titanium and PTFE at 12 wk but not at earlier time points.

Engineering the tissue which encapsulates subcutaneous implants. II. Plasma-tissue exchange properties - Sharkawy, A.A.; Klitzman, B.; Truskey, G.A.; Reichert, W.M. (Journal of Biomedical Materials Research, 1998)
This study assesses the plasma-tissue exchange characteristics of the capsular tissue that forms around implants and how they are affected by implant porosity. The number of vessels and their permeability to rhodamine were measured by intravascular injection of the fluorophore tracer into Sprague-Dawley rats that hosted for 3-4 months polyvinyl alcohol (PVA) and polytetrafluoroethylene (PTFE) subcutaneous implants. Rats were implanted with four pore sizes of PVA - a nonporous PVA (PVA-skin), and 5, 60, and 700 micron mean pore sizes (PVA-5, PVA-60, and PVA-700, respectively) - and two pore sizes of PTFE: 0.50 (PTFE-0.5) and 5.0 (PTFE-5) mean micron pore sizes. Photodensitometric image analysis was used to quantify the local tracer extravasation and, hence the permeability coefficients of isolated vessels around the implants. The number of functional vessels within 100 μm of the implants highlighted by the lissamine-rhodamine tracer were counted with fluorescence microscopy and with H and E stained sections using brightfield microscopy. The permeability of vessels did not vary substantially with implant pore size but generally were lower than those measured for surrounding subcutis. Pore size, however, had a dramatic effect on the vascular density of tissue-encapsulating implants: the number of microvessels (under 10 μm in radius) within the tissue surrounding the porous implants was higher than the number around nonporous implants. Pore sizes on the order of cellular dimensions incited optimal neovascularization; the vascular density around PVA-60 implants was six times higher (p < .001) and three times higher (p < .001) than those around PVA-0 implants in the fluorescent images and in brightfield, respectively. Moreover, brightfield microscopy showed the number of vessels around PVA-60 implants was almost double those in normal subcutis. The results suggest that optimal vascular density around long-term implants, such as sensors, biofluid cell constructs, and immunoisolated cell systems, may be engineered with pore size. Plasma-tissue exchange properties of the capsular tissue were studied to determine the effects of implant porosity. The number of vessels and permeability to rhodamine were measured by intravascular injection of fluorophore tracer in to rats that hosted polyvinyl alcohol (PVA) and polytetrafluoroethylene (PTFE) implants. The permeability of the vessels did not vary with implant pore size, but pore size had an effect on the vascular density of tissue-encapsulating implants. Pore sized on the order of cellular dimensions incited neovascularizations. Brightfield microscopy showed the number of vessels around PVA-60 implants was almost double those in normal subcutis.
Keywords: Encapsulation; Foreign body response; Permeability; Porosity; PTFE; PVA; Subcutaneous implants; Vasculature

Production of platelet-derived growth factor in aseptic loosening of total hip replacement - Xu, J.-W.; Konttinen, Y.T.; Li, T.-F.; Waris, V.; Lassus, J.; Matucci-Cerinic, M.; Sorsa, T.; Santavirta, S. (Rheumatology International, 1998)
Aseptic loosening is the predominant cause of total hip implant failure. It has been assumed that a layer or membrane, containing macrophages, fibroblasts and vascular endothelial cells, of synovial-like tissue develops at the implant-to-bone interface almost invariably and, with time, somehow leads to loosening of the components from the surrounding bone. These cells produce a variety of cytokines and proteolytic enzymes which stimulate bone resorption. Platelet derived growth factor (PDGF) may be one of the cytokines which stimulate bone resorption and contribute to aseptic loosening in total hip replacement (THR). Synovial-like membrane from the implant or cement-to-bone interface (n = 10) and pseudocapsule (n = 10) were obtained from ten patients operated on for aseptic loosening of THR. As a control, nine samples of connective tissues were obtained from patients who had mandibular or maxillary fractures fixed with bone implant. The avidin-biotin-peroxidase complex (ABC) method with polyclonal rabbit anti-human IgG against the A-chain and B-chain of PDGF was used for staining. ABC-alkaline phosphatase-anti-alkaline-phosphatase double staining with monoclonal mouse anti-human fibroblast IgG, and CD68 antibodies was used to ascertain the cellular origin of PDGF. Results of the PDGF staining were quantitated by a semi-automatic VIDAS image analysis system. The PDGF-A and PDGF-B chain containing cells were found in all periprosthetic tissues, in particular in macrophages with phagocytosed particulate debris, but to some extent also in fibroblasts and in endothelial cells. The numbers of PDGF-A and PDGF-B chain positive cells per mm2 in synovial-like interface membrane (1881 ± 486 and 1877 ± 214) and pseudocapsule (1786 ± 236 and 1676 ± 152) were higher (P < 0.01) around loose THR than in control tissue (821 ± 112 and 467 ± 150), respectively. The results of the present study suggest that PDGF is preferably expressed by macrophages, which to an increased extent produce it in the synovial-like interface membrane and pseudocapsular synovial-like membrane. Because of its role in bone resorption, it may well play a role in periprosthetic bone loss and aseptic loosening and deserves more detailed study as a mediator and potential target in the modulation or prevention of loosening of THR.
Keywords: Aseptic loosening; Platelet-derived growth factor; Synovial-like membrane; Total hip replacement

Differential synthesis of cholesterol esterase by monocyte-derived macrophages cultured on poly(ether or ester)-based poly(urethane)s - Labow, R.S.; Meek, E.; Santerre, J.P. (Journal of Biomedical Materials Research, 1998)
Monocytes adherent to implanted biomaterials differentiate into macrophages while synthesizing large amounts of degradative enzymes, including cholesterol esterase (CE), which previously has been shown to degrade poly(urethane)s. Human peripheral blood monocytes were cultured on tissue culture grade polystyrene (PS), and two model poly(urethane)s were synthesized from (1) polycaprolactone (PCL) and (2) polytetramethylene oxide (PTMO), both with 2,4-toluene diisocyanate (TDI) and ethylene diamine (ED). The increase in CE and total protein per cell were measured on days 8 and 28 in culture and normalized to the DNA content per cell. At day 8 there consistently were fewer cells remaining on the PTMO-based polymer than on the PCL-based polymer or the PS (p < 0.05). When comparing day 28 to day 8, there was more CE activity and protein per cell on all materials. However, there was a disproportionate synthesis of CE per mg of total protein on PS and TDI/PCL/ED whereas on PTMO there was not. Significantly, there was more protein and CE per cell on PTMO than on PS or TDI/PCL/ED (p < 0.05). This in vitro model system of the chronic phase of inflammation has shown that it is possible to culture monocytes for a month and assess the material surface itself as a potent activator of the differentiation into macrophages without secondary stimulation. Since CE has been shown to degrade poly(ether and ester)-based poly(urethane)s, the differential production of this enzyme relative to the total protein on different surfaces may impact on the potential long-term biostability of an implanted material. Monocytes adherent to implanted biomaterials differentiate into macrophages while synthesizing large amounts of degradative enzymes, including cholesterol esterase (CE), which previously has been shown to degrade poly(urethane)s. Human peripheral blood monocytes were cultured on tissue culture grade polystyrene (PS), and two model poly(urethane)s were synthesized from (1) polycaprolactone (PCL) and (2) polytetramethylene oxide (PTMO), both with 2,4-toluene diisocyanate (TDI) and ethylene diamine (ED). The increase in CE and total protein per cell were measured on days 8 and 28 in culture and normalized to the DNA content per cell. At day 8 there consistently were fewer cells remaining on the PTMO-based polymer than on the PCL-based polymer or the PS (p<0.05). When comparing day 28 to day 8, there was more CE activity and protein per cell on all materials. However, there was a disproportionate synthesis of CE per mg of total protein on PS and TDI/PCL/ED whereas on PTMO there was not. Significantly, there was more protein and CE per cell on PTMO than on PS or TDI/PCL/ED (p<0.05). This in vitro model system of the chronic phase of inflammation has shown that it is possible to culture monocytes for a month and assess the material surface itself as a potent activator of the differentiation into macrophages without secondary stimulation. Since CE has been shown to degrade poly(ether and ester)based poly(urethane)s, the differential production of this enzyme relative to the total protein on different surfaces may impact on the potential long-term biostability of an implanted material.
Keywords: Biodegradation; Biostability; Cholesterol esterase; Monocyte-derived macrophages; Poly(urethane)s

A subcutaneous tissue reaction in the early stage to a synthetic auditory ossicle (Bioceram®) in rats - Ye, Q.; Ohsaki, K.; Ii, K.; Li, D.-J.; Matsuoka, H.; Tenshin, S.; Yamamoto, T. (Journal of Medical Investigation, 1998)
The discs of synthetic auditory ossicle (Bioceram®), which are composed of aluminium oxide (Al2O3), were implanted subcutaneously in the interscapular region of 16 rats. The implanted specimens were removed at 1, 3, 7 and 14 days after implantation. The decalcified 6 μm thick sections were stained with H.E. and cell types around the implants were counted microscopically. We found that an acute inflammatory reaction occurred at one day, in which macrophages and neutrophiles predominated, and almost disappeared at about 7 days after implantation. Fibrosis began to be observed at 3 days. During this early stage, foreign body giant cells were found in only one specimen at 3 days. These findings, in comparison with those in the controls, showed that the chemical irritation of Bioceram® to the subcutaneous tissue is slight, although the physical and/or chemical irritation of Bioceram® lasts continuously and induces fibrosis around the bioimplant. The results so far suggest that Bioceram® seems to be a satisfactorily biocompatible material, at least within the extent of 2 weeks.
Keywords: Aluminum oxide ceramics; Biocompatible materials; Cell count; Histology; Rats

Biocompatibility of poly(methylmethacrylate), silicone, and AcrySof intraocular lenses: Randomized comparison of the cellular reaction on the anterior lens surface - Hollick, E.J.; Spalton, D.J.; Ursell, P.G.; Pande, M.V. (Journal of Cataract and Refractive Surgery, 1998)
Purpose: To determine the foreign-body response to three intraocular lens (IOL) biomaterials (poly[methyl methacrylate] [PMMA], silicone, and AcrySof) and use this as an indicator of their comparative biocompatibility postoperatively within the eye. Setting: A British teaching hospital eye department. Methods: Ninety eyes were prospectively randomized to receive a PMMA, silicone, or AcrySof IOL. All lenses had 6.0 mm optics with PMMA haptics. A standardized surgical protocol was performed by a single surgeon using an extracapsular technique with capsulorhexis; eyes that experienced a surgical complications were excluded. All patients had standardized postoperative medication and follow-up. Specular microscopy of the anterior IOL surface was carried small cell and giant cell reactions. Results: All three IOL types produced a mild degree of nonspecific foreign-body response, which resolved over the study period without detrimental effect. The silicone group had significantly higher small cell counts than the PMMA and AcrySof groups (P = .02); the AcrySof group had significantly lower giant cell counts than the other two groups (P = .003). Conclusion: The three IOL types were sufficiently biocompatible to function in normal eyes with age- related cataracts. However, AcrySof of IOLs were associated with lower giant cell counts than PMMA and silicone IOLs and might produce better results in eyes with pre-existing blood-aqueous barrier damage.

Ultrastructure of blood vessel regression in involution of foreign-body granuloma - Honma, T.; Hamasaki, T. (Journal of Submicroscopic Cytology and Pathology, 1998)
The diversity of endothelial cell deletion in regressing blood vessels during involution of granulation tissue was investigated in foreign-body granulomas induced by a collagen sponge implanted into the dorsum of the rat. Small blood vessel density counts were performed to determine the degree of blood vessel regression in the involution of granulation tissue in foreign-body granuloma. The density of these small blood vessels significantly decreased between 100 and 130 days after sponge implantation. The detachment of endothelial cells from their underlying basement membrane and the consequent protrusion into and/or out of the lumen in the vascular network of granulation tissue was observed by electron microscopy. Based on the pattern of manifestation in the endothelium and the characteristic deformation of nuclei, the detached endothelial cells were classified into two groups: 1) the endothelial cell apoptosis group and 2) the endothelial cell degeneration group. The essential difference between the two groups was easily distinguishable as the nucleus of the former group displayed chromatin condensation and margination as the hallmark of early apoptotic changes, while the nucleus of the latter group displayed a pinch structure and intranuclear pocket formation. However, the process by which the detached endothelial cells were shed into the vascular lumen and eventually eliminated from circulation was the same in both groups. The occurrence of both groups increased on the 90th day after sponge implantation and reached a maximum on the 110th day, indicating that the appearance of the groups was synchronized. These results suggest that the two major processes of apoptosis and degeneration of endothelial cells occur during endothelial cell deletion as a mechanism contributing to blood vessel regression.
Keywords: Apoptosis; Degeneration; Endothelial cells; Granulation tissue; Involution

Biocompatibility of polyethylene terephthalate (Trevira® hochfest) augmentation device in repair of the anterior cruciate ligament - Seitz, H.; Marlovits, S.; Schwendenwein, I.; Müller, E.; Vécsei, V. (Biomaterials, 1998)
The biocompatibility of a 3 mm band made of polyethylene terephthalate (Trevira® hochfest) has been tested in an experimental study within right knee joints of 60 sheep. After transsecting the anterior cruciate ligament (ACL), two randomized groups were formed. In group I, the ACL was repaired according to the Marshall technique whilst in group II an additional 3 mm polyethylene terephthalate (PET) augmentation band was implanted using the through-the-condyle (TTC) procedure. To assess the biocompatibility of the augmentation device the knee joints of both groups were punctured and the synovial fluids were analyzed before, as well as 2, 6, 16, 26, and 52 weeks after the operation. In addition, the histologic appearance of excised suprapatellar pouches and ipsilateral inguinal and popliteal lymphatic noduli were examined. Comparing both groups no significant differences were found neither before nor after the augmented and non-augmented ACL repair. No pathological increase in the total protein concentration occurred after operation and no significant differences versus the preoperative analysis were found. No synovitis signalling a decrease in the glucose concentration was observed. The cytological examination revealed no increase of the leukocyte cell count results. Within the synovial specimen neither free nor phagocytosed PET wearparticles could be detected. In groups I and II the histological appearance of excised popliteal and inguinal lymphatic noduli showed a normal result. In 25% of the PET augmented ACL repairs, a slight concentration of PET wearparticles and solitary, multinuclear giant foreign body cells could be seen in the histological preparations of suprapatellar pouches. The biocompatibility of a 3 mm band made of polyethylene terephthalate (Trevira hochfest) has been tested in an experimental study within right knee joints of 60 sheep. After transsecting the anterior cruciate ligament (ACL), two randomized groups were formed. In group I, the ACL was repaired according to the Marshall technique whilst in group II an additional 3 mm polyethylene terephthalate (PET) augmentation band was implanted using the through-the-condyle (TTC) procedure. To assess the biocompatibility of the augmentation device the knee joints of both groups were punctured and the synovial fluids were analyzed before, as well as 2, 6, 16, 26, and 52 weeks after the operation. In addition, the histologic appearance of excised suprapatellar pouches and ipsilateral inguinal and popliteal lymphatic noduli were examined. Comparing both groups no significant differences were found neither before nor after the augmented and non-augmented ACL repair. No pathological increase in the total protein concentration occurred after operation and no significant differences versus the preoperative analysis were found. No synovitis signalling a decrease in the glucose concentration was observed. The cytological examination revealed no increase of the leukocyte cell count results. Within the synovial specimen neither free nor phagocytosed PET wearparticles could be detected. In groups I and II the histological appearance of excised popliteal and inguinal lymphatic noduli showed a normal result. In 25% of the PET augmented ACL repairs, a slight concentration of PET wearparticles and solitary, multinuclear giant foreign body cells could be seen in the histological preparations of suprapatellar pouches.
Keywords: Anterior cruciate ligament repair; Leukocytes; Polyethylene terephthalate augmentation device; Synovial fluid

Alternatives to spinal fusion - Kostuik, J.P. (Orthopedic Clinics of North America, 1998)
An underlying tenet of design in the biologic realm is that the optimal design of the prosthetic device reproduces exactly the healthy, intact biologic situation in every case (geometric, kinetic). Because the optimal solution is unobtainable, however, because of the limited resources available, compromises must be made. Every compromise inevitably produces complications because of the interdependent nature of biologic systems. The goal then becomes to minimize the detrimental effects of the implant system through the best possible use of the technologies available. It is the author's experience that whenever this fundamental tenet is forgotten in the design of an implant, either the system is affected adversely, or unforeseen complications arise in an associated system. An example can be seen in the evolution of solutions to the problem of loosening of the femoral component of hip prostheses. This loosening is caused, in part, by improper load transmission to the femur. Until recently, most hip implants transferred stress to the femur distally through the stem of the implant. Because of the lack of physiologic stress levels in the proximal femur bone, resorption was common, which often led to loosening of the implant. Many current designs are able to provide proximal loading of the femur through well-designed, proximal press fits. Although this seems to be a better solution, these prostheses fall short of the biologic situation in that they impose hoop stress to bone cells that naturally experience primarily axial stresses. The subsequent remodeling of bone because of the change in the load direction may not provide adequate stability for the implant in the long-term. In the same way, a best effort must be made in the present design to maintain near-physiologic load transfer and motion. Therefore, considerable effort was invested in the design stage of this project to consider the solutions available today to duplicate the stiffness (flexibility) of the lumbar disc in its principal plane of motion. This philosophy of restoration of function was also applied in specifying the geometry and the constraints to motion imposed by the prosthesis. The long life span required of an artificial spinal disc poses a significant challenge to the design effort. Plastics available today cannot be counted on to last for 40 years and 100 million cycles. The proposition of 40 years of metal-on-metal, however, was somewhat alarming. Therefore, quantitative wear-simulation testing has accompanied this development project since the second year of the project. Likewise, other factors, such as fatigue stress and corrosion resistance, become increasingly important because of the extended life span of the device. Therefore, as part of this project, standard material fatigue experiments (such as rotating bend tests) have been performed on the hot isostatatically pressed cobalt-chromium and titanium couples. The loads in the quadruped lumbar spine are largely in shear, which is in contrast to the more upright human lumbar spine, in which the loads are mainly in compression. The fact that bone ingrowth occurred in these animals under the worst-case scenario (shear loads) is most encouraging. There was no foreign body reaction in regional tissues and lymph nodes other than a mild fibrous tissue later over the implant. No soft tissue ingrowth was seen histologically in the springs. Although small numbers of animals were analyzed, the results were encouraging and would suggest that human implementation is feasible with little or no likelihood of mechanical failure, loosening, or disaster. A categoric list of design criteria relevant to the development of an articulating spinal disc implant has been presented. Each of these criteria and many of the questions posed are relevant in the synthesis of any new implant system. Constraints imposed by an implant have been discussed at length. A method of constraint analysis that simplifies specification of motion constraints has been described. Specifications of the preclinical trial design of an intervertebral disc prosthesis have been listed and evaluated on the basis of some of the pretrial experimental data. This design is the product of the detailed prospective design technique that has been the focus of this article. It is a design that will undergo future revisions based on clinical trial data, yet the implant's limitations and its in vitro performance has been assessed thoroughly during the past years to minimize the number of revisions necessary because of unsatisfactory results in clinical trials.

Acute inflammatory reaction associated with endoluminal bypass grafts - Hayoz, D.; Do, D.-D.; Mahler, F.; Triller, J.; Spertini, F.; Veith, F.J. (Journal of Endovascular Surgery, 1997)
Purpose: Nonspecific inflammatory reactions characterized by local tenderness, fever, and flu-like discomfort have been seen in patients undergoing endoluminal graft placement in the abdominal aorta or the femoral arteries. We undertook a study to assess the clinical and laboratory parameters of this inflammation. Methods: Ten patients with femoropopliteal artery (n = 9) or aortic (n = 1) lesions were treated with EndoPro System 1 stent-grafts made of nitinol alloy and covered with a polyester (Dacron) fabric. Eleven patients implanted with a bare nitinol stent served as the control group. Results: In the stent-graft group, four patients showed clinical signs of acute inflammation manifested by fever and local tenderness. Three of these patients suffered thrombosis of the stent-grafts during the first month of follow-up. Plasma levels of interleukin-1β and interleukin-6 in all stent-graft patients were markedly increased 1 day after intervention (7.3 ± 2.8 versus 90.2 ± 34.1 pg/mL and 15.6 ± 5.8 versus 175.5 ± 66.3 pg/mL, respectively; p < 0.01). This was followed by an increase in fibrinogen (3.0 ± 0.2 versus 5.0 ± 0.2 g/L; p < 0.05) and C- reactive protein (14.6 ± 3.3 versus 77.5 ± 15.0 mg/L, p < 0.01) at 1 week. No direct correlation between the inflammatory markers and symptoms could be found. In vitro analysis showed that individual components of the stent- graft did not activate human neutrophils, whereas the intact stent-graft itself induced a marked neutrophil activation. Conclusions: The component of the self-expanding stent-graft responsible for the nonspecific inflammatory reaction was not identified in this study. It is likely that the stent-graft itself or some as yet unrecognized element of the device other than the Dacron fabric or metal alloy may be a potent in vivo inducer of cytokine reaction by neutrophils.
Keywords: Cytokines; Dacron graft material; EndoPro System 1; Nitinol stents; Stent-grafts

Postoperative inflammatory reactions to sealed Dracon prostheses. A comparison of Gelseal® and Hemashield® - Utoh, J.; Goto, H.; Hirata, T.; Hara, M.; Kitamura, N. (Journal of Cardiovascular Surgery, 1997)
Objective. The purpose of this study was to assess and compare inflammatory reactions to two types of sealed vascular prostheses used in the repair of abdominal aortic aneurysm. Experimental design. Randomized prospective study with a follow-up period of 21 days. Setting. University hospital study. Patients. Sixty patients admitted for elective abdominal aortic aneurysm repair. Intervention. Each patient underwent repair of abdominal aortic aneurysm with either a gelatin-sealed knitted Dacron prosthesis (Gelseal®, Vascutek, n = 30) or a collagen-sealed woven Dacron prosthesis (Hemashield®, Meadox Medicals, n = 30). Measures. As indicators of the presence of inflammation, the peripheral blood cell count, platelet count, and plasma C-reactive protein (CRP) concentration were determined in each patient on postoperative days (PODs) 1, 7, 14 and 21. Body temperature was measured every 8 hours. Results. Patients in both groups revealed a low-grade fever and leukocytosis during the first 7 PODs. Significantly higher leukocyte counts were demonstrated in the Gelseal group on PODs 7 and 14. However, no difference in the leukocyte count, CRP concentration, or body temperature existed between the two groups on POD 21. Biphasis changes in the platelet count were observed in both groups. No complications were encountered. Conclusion. The Gelseal prosthesis was associated with higher inflammatory response during the second week following implantation, but this difference had resolved by POD 21. This finding may reflect an inflammatory reaction against impregnated gelatin.
Keywords: Blood vessels; Polyethylene terephthalate; Prosthesis

Migration of hydroxyapatite onlays into the mandible and nasal bone and local bone turnover in growing rabbits - Yanagisawa, A.; Nakamura, T.; Arakaki, M.; Yano, H.; Yamashita, S.; Fujii, T. (Plastic and Reconstructive Surgery, 1997)
To determine the effects of local bone turnover on the migration of macroporous hydroxyapatite onlays in the nasal bone and mandibular ramus, we performed histomorphometric analyses of the underlying bone area in 41 New Zealand White rabbits from the age of 4 weeks. The hydroxyapatite implants were placed under the periosteum of the right nasal bone (a depository bone onto its periosteal surface and endosteal resorptive) and the mandibular ramus (resorptive onto its outer surface). The corresponding left sides were sham operated. Following fluorescence bone labeling, composite specimens of the hydroxyapatite block including both sides of the nasal bone and mandible were removed at 0 (m = 1), 3, 6, 9, 12, and 16 weeks postoperatively (n = 8, respectively) and processed to yield undecalcified sections. Bone-bone marrow interfaces in the entire area within 200 μm beneath the base of the hydroxyapatite and in the counter-area on the sham-operated side were measured under a light microscope. In all grafted specimens, the hydroxyapatite matrix was directly united with the underlying tissue by bone ingrowth. However, the sinking of the hydroxyapatite graft in the nasal bone was significant at 3 weeks postoperatively and gradually increased thereafter. In the mandible, the sinking became significant at 6 weeks. In the nasal bone, the bone are density beneath the graft showed a time- dependent decrease during the experimental period, but in the mandibular bone, the value was initially decreased at 3 weeks and then recovered to baseline level. In both bones, parameters of bone resorption, such as osteoclast number and osteoclast surface, were significantly increased from 3 weeks. While the parameters of bone formation, such as osteoblast surface and mineralizing surface, were significantly decreased from 3 weeks in the nasal bone, they were significantly increased in the mandible. Mineral apposition rate showed a significant decrease in both bones. Our data indicate that while the bone area density beneath the hydroxyapatite seemed to depend on bone formation, increased bone resorption would be more critical for the remodeling of underlying bony architecture in the migration of the hydroxyapatite graft.

Inner thyroid foreign body - Esteves, Irapuan (Ultrasound in Medicine and Biology, 1997)
Patient complaining of front left cervical tumoral mass, painful to handling, with approximately three months evolution. Normal physical examination. Diagnostic Investigation: Normal thyroidal hormones, Normal full blood count and biochemistry, Normal chest X-Ray, Normal electrocardiography, Normal carcinoembrionary antigen, Thyroid cintilography:Diffuse goiter, Biopsy:Inflammatory response. Ultrasonographic report of the thyroid presented a linear echogenic structure surrounded by a hypoechoic area at the left lobe, compatible with foreign body and resultant inflammatory response. A fish bone was found after the patient was submitted to a left hand side lobectomy.

Late complication of laparoscopic salpingoophorectomy: retained foreign body presenting as an acute abdomen. - Mendez, L.E.; Medina, C. (JSLS : Journal of the Society of Laparoendoscopic Surgeons / Society of Laparoendoscopic Surgeons, 1997)
BACKGROUND: Laparoscopy is widely used as a tool in many clinical situations allowing for diagnosis and/or surgical management in a minimally invasive fashion. Most laparoscopic cases are ambulatory and allow patients to recover quickly. Nonetheless, attention to surgical technique is paramount to avoid both short and long term complications. CASE: A 32-year-old woman had a laparoscopy and a reported left salpingoophorectomy for benign disease of the ovary in September, 1994. Shortly thereafter, in January, 1995, she was diagnosed with an intrauterine pregnancy and delivered in October of 1995 by spontaneous vaginal delivery. The pregnancy and delivery were both uncomplicated. The patient presented four weeks postpartum with clinical suspicion of appendicitis. However, at the time of laparotomy, the patient was found to have a retained foreign body from her prior laparoscopy in the right lower quadrant with a pelvic abscess and evidence of prior right salpingoophorectomy. The appendix appeared grossly normal. CONCLUSION: Laparoscopy is a safe, effective modality for various surgical and gynecologic conditions. Although laparoscopy is usually done on an outpatient basis, complications can manifest several weeks or months later. This case illustrates and reminds us of the importance of adherence to surgical laparoscopic principles. These include direct visualization when removing equipment and a complete count of surgical instrumentation to confirm the integrity of such at the end of each procedure.

Tissue response to suture materials implanted subcutaneously in a rabbit model - Setzen, G.; Williams III, E.F. (Plastic and Reconstructive Surgery, 1997)
We compared the tissue response to a nonabsorbable monofilamented suture made of expanded polytetrafluoroethylene (ePTFE), which has recently been introduced for use in plastic surgery, with the response to 10 other commercially available absorbable sutures and nonabsorbable monofilamented and multifilamented sutures. The sutures were used to secure a patch of ePTFE implanted in the dorsum of adult New Zealand White rabbits. At 30, 60, and 120 days after implantation, the tissue response to the sutures was assessed with respect to the number of foreign-body giant cells present, the thickness of the fibrous capsule that developed, and the general inflammatory response (n = 4 for each suture for each time period). Analysis of variance revealed that specific suture type was significantly associated with foreign-body giant cell count and fibrous capsule thickness. Tevdek had a significantly higher value for mean number of foreign-body giant cells. Silk and Tevdek had significantly thicker fibrous capsules, and ePTFE suture had a significantly thinner capsule. Absorbable sutures and nonabsorbable multifilamented sutures evoked a more extensive tissue response than monofilamented sutures; the differences between nonabsorbable monofilamented and nonabsorbable multifilamented sutures were significant for capsule thickness. In general, suture made of ePTFE produced a minimal tissue response. It should be a good choice for use in facial plastic surgery, in which excellent functional and aesthetic results are critical.

Histological evidence of an inflammatory reaction to suture material in the dog vas deferens - Fallick, M.L.; Sable, D.B.; Faller, G.; Larock, D.; Sant, G.R.; Schlesinger, R.M.; Schwaitzberg, S.D. (British Journal of Urology, 1997)
Objective. To evaluate changes in histology and semen variables after using an elastomeric-hydrogel matrix plug as a reversible vasectomy device in dogs, and to determine the potential applications for improving fertility after vasectomy reversal. Materials and methods. Semen samples from six adult male dogs were obtained after left vasal ligation, placement of the plug in the right vas deferens, and subsequent removal of the plug. The vasa, epididymides and testes were evaluated histologically in four of the dogs after removal of the implant. Results. No sperm were present in the ejaculate after the plug was removed. Histological sections showed intraluminal spermatids in areas where the plug had been placed. The lumen was occluded, secondary to foreign-body giant-cell reaction, at the vasotomy suture site, but other areas of the vas previously containing the implant remained patent after it was removed. Conclusions. There were no sperm in the ejaculate after the plug was removed because the vasal lumen was occluded as a result of an inflammatory reaction to the suture material. In contrast, areas that had contained the implant but without a vasotomy suture were not inflamed. We suggest that further trials comparing various suture materials are carried out to determine if patency rates can be improved during vasotomy closure or vasovasostomy.
Keywords: Dogs; Sperm count; Sterilization reversal; Vasectomy

Long-term observation of subcutaneous tissue reaction to synthetic auditory ossicle (Apaceram®) in rats - Dong-Jun, L.I.; Ohsaki, K. (Journal of Laryngology and Otology, 1997)
The present study evaluates histological characteristics of the soft tissue response to long-term implantation of Apaceram® discs composed of dense hydroxyapatite in rats. Discs were implanted into the subcutaneous tissue of 76 rats for six to 20 months. Decalcified histological sections stained with haematoxylin and eosin (H and E) and Mallory's azan were examined. Different cell types surrounding implants were counted. The greatest proportion of macrophages was found at six months (13.5 per cent). This proportion gradually decreased to four per cent at 20 months. Small numbers of lymphocytes and foreign body giant cells were observed in every group, but neither neutrophils nor osteogenesis were observed in any specimens. Results of the present study and previous related studies indicate that despite reappearance of a small number of macrophages six months after implantation, Apaceram® is useful for reconstructive surgery.
Keywords: Hydroxyapatites; Rats

The inflammatory potential of surgical glove lubricants: Biosorb, Keoflo, calcium carbonate and Hydrocote after intravitreal injection. - Park, H.S.; Kim, M.S. (Korean journal of ophthalmology : KJO, 1997)
Surgical glove powders have been implicated in serious postoperative foreign body reactions due to contamination of the operative field. Inflammatory responses to glove lubricants or mold release agents have to date been studied to a lesser extent in ocular tissues than other body tissues, although powder contamination of intraocular lenses, with severe postoperative anterior chamber inflammatory responses, have been reported. The object of this study was to grade and quantitate the inflammatory response of surgical glove lubricants, namely Biosorb, Keoflo, calcium carbonate and Hydrocote (a hydrogel polymer film used in powderless gloves), as introduced into the posterior chamber on New Zealand white rabbits. In a double masked GLP study, a total of 150 eyes were evaluated. For each of the four test samples, a dose response curve was obtained at 10 micrograms (Keoflo only), 125 micrograms, 250 micrograms, 500 micrograms, 1000 micrograms, and 1500 micrograms. Study parameters were the quantitation of inflammatory cells in the aqueous and vitreous, and ocular irritation and inflammation, as graded by the rabbit inflammation score system, at 0 and 48 hours post-injection. A Wilcoxen signed-rank test used to evaluate statistical significance (p < 0.05). A test vitreal cell count was less that 50 cells/mm3 and the overall mean clinical response was less than 2.0. This study established that Keoflo at all concentrations 10 micrograms-1000 micrograms), and Biosorb at concentrations greater than 1000 micrograms were inflammatory. Calcium carbonate and Hydrocote were non-inflammatory at concentration of 125 micrograms-1500 micrograms. The unoperated, sham, vehicle and Ocugel controls were all non-inflammatory. The positive Zymozan A controls were defined as inflammatory. In conclusion, no glove powder is totally safe, even small amounts of glove powder (10 micrograms) can elicit an inflammatory immune response. If all glove powder averages 700mg/pair, this should be removed prior to contact with a patients tissue. Powder-free gloves and greatly reduce the potential inflammatory risk associated with powdered gloves.

Foreign Body Reactions to Monofilament and Braided Polypropylene Mesh Used as Preperitoneal Implants in Pigs - Beets, G.L.; Go, P.M.N.Y.H.; Van Mameren, H. (European Journal of Surgery, 1996)
Objective: To compare the foreign body reaction of the monofilament polypropylene (ProleneR) mesh, and the multifilament SurgiproR mesh. Both types of mesh are widely used in laparoscopic inguinal hernia repair. Design: Prospective experimental study. Setting: University hospital, The Netherlands. Material: Six female Yorkshire & Dutch landway pigs. Intervention: Laparoscopic transabdominal implantation of six SurgiproR meshes and six ProleneR meshes in 12 inguinal sites. Main outcome measures: At 3, 6, and 12 weeks after implantation the foreign body reaction was measured by counting multinucleated giant cells at the mesh-tissue interface. Results: At all times the numbers of multinucleated giant cells at the mesh tissue interface were significantly larger with SurgiproR than with ProleneR (p < 0.001). Conclusions: There is significantly more foreign body reaction after implantation of SurgiproR than ProleneR mesh.
Keywords: Foreign body reaction; Inguinal hernia repair; Laparoscopy; Polypropylene mesh; Suture materials

Vitamin E as an antioxidant for poly(etherurethane urea): In vivo studies - Schubert, M.A.; Wiggins, M.J.; DeFife, K.M.; Hiltner, A.; Anderson, J.M. (Journal of Biomedical Materials Research, 1996)
Poly(etherurethane) elastomers are useful materials in medical devices because of their mechanical properties and biocompatibility. However, it is necessary to stabilize these elastomers against the oxidation of their ether soft segments. Synthetic antioxidants such as Santowhite® and Irganox® are often satisfactory; however, particularly for biomedical applications, it was of interest to test the natural antioxidant vitamin E in poly(etherurethane urea) (PEUU) elastomers in vivo. The α-tocopherol form of vitamin E was added to PEUU at 5% by weight. Biaxially strained PEUU specimens with and without vitamin E were tested in vivo in the cage implant system. The influence of vitamin E on PEUU biostability was analyzed by attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy and scanning electron microscopic (SEM) characterization of the PEUU surface. ATR-FTIR results showed that vitamin E prevented chemical degradation of the PEUU surface up to 5 weeks implantation, and at 10 weeks 82% of the ether remained. In contrast, without an antioxidant, only 18% of the ether remained after 10 weeks. No surface pitting or cracking was observed by SEM on PEUU with vitamin E; PEUU without antioxidant ruptured owing to extensive pitting and cracking. It was concluded that the antioxidant properties of vitamin E prevented oxidation of strained PEUU elastomers in vivo. The influence of vitamin E on PEUU biocompatibility was characterized by exudate leukocyte counts, density of leukocytes adherent to the PEUU, and morphology of adherent leukocytes. These results indicated decreased leukocyte counts in the exudate and less active adherent cells on the PEUU with vitamin E compared to PEUU without antioxidant. A proposed cell-polymer feedback system demonstrates how vitamin E improves both biostability and biocompatibility of PEUU elastomers in vivo. Poly(etherurethane) elastomers are useful materials in medical devices because of their mechanical properties and biocompatibility. However, it is necessary to stabilize these elastomers against the oxidation of their ether soft segments. Synthetic antioxidants such as Santowhite and Irganox are often satisfactory; however, particularly for biomedical applications, it was of interest to test the natural antioxidant vitamin E in poly(etherurethane urea) (PEUU) elastomers in vivo. The α-tocopherol form of vitamin E was added to PEUU at 5% by weight. Biaxially strained PEUU specimens with and without vitamin E were tested in vivo in the cage implant system. The influence of vitamin E on PEUU biostability was analyzed by attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy and scanning electron microscopic (SEM) characterization of the PEUU surface. ATR-FTIR results showed that vitamin E prevented chemical degradation of the PEUU surface up to 5 weeks implantation, and at 10 weeks 82% of the ether remained. In contrast, without an antioxidant, only 18% of the ether remained after 10 weeks. No surface pitting or cracking was observed by SEM on PEUU with vitamin E; PEUU without antioxidant ruptured owing to extensive pitting and cracking. It was concluded that the antioxidant properties of vitamin E prevented oxidation of strained PEUU elastomers in vivo. The influence of vitamin E on PEUU biocompatibility was characterized by exudate leukocyte counts, density of leukocytes adherent to the PEUU, and morphology of adherent leukocytes. These results indicated decreased leukocyte counts in the exudate and less active adherent cells on the PEUU with vitamin E compared to PEUU without antioxidant. A proposed cell-polymer feedback system demonstrates how vitamin E improves both biostability and biocompatibility of PEUU elastomers in vivo.

In vivo characterization of a fluoropassivated gelatin-impregnated polyester mesh for hernia repair - Soares, B.M.; Guidoin, R.G.; Marois, Y.; Martin, L.; King, M.W.; Laroche, G.; Zhang, Z.; Charara, J.; Girard, J.-F. (Journal of Biomedical Materials Research, 1996)
The present study was undertaken to evaluate a new prototype mesh that consists of a knitted polyester structure treated with a fluoropolymer and impregnated with gelatin. The Fluoropassiv® mesh, as well as two controls, the Surgipro(TM) polypropylene mesh and the Gore-Tex® expanded polytetrafluoroethylene patch, were used for the repair of experimentally induced abdominal hernias in piglets and followed for scheduled implantation periods of 4, 15, and 60 days. At the sacrifice the mesh and surrounding tissue were excised for histological assessment of the healing sequence, for the identification of changes in hematologic and immunological characteristics, and for the measurement of the mechanical properties. After cleaning to remove the encroaching tissue, the explanted devices were monitored for biostability by infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC). The present study has demonstrated that the Fluoropassiv® mesh provides adequate mechanical strength and compares favorably with the two controls. No exacerbated systemic or in situ hematologic or immunological reactions were observed with either the meshes or the patch material. Histological studies revealed that thick collagenous and vascularized tissue were well anchored to the three biomaterials as early as 15 days after implantation. The degree of tissue penetration differed depending on the device. Chemically, they proved stable over time. The present study was undertaken to evaluate a new prototype mesh that consists of a knitted polyester structure treated with a fluoropolymer and impregnated with gelatin. The Fluoropassiv mesh, as well as two controls, the Surgipro polypropylene mesh and the Gore-Tex expanded polytetrafluoroethylene patch, were used for the repair of experimentally induced abdominal hernias in piglets and followed for scheduled implantation periods of 4, 15, and 60 days. At the sacrifice the mesh and surrounding tissue were excised for histological assessment of the healing sequence, for the identification of changes in hematologic and immunological characteristics, and for the measurement of the mechanical properties. After cleaning to remove the encroaching tissue, the explanted devices were monitored for biostability by infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC). The present study has demonstrated that the Fluoropassiv mesh provides adequate mechanical strength and compares favorably with the two controls. No exacerbated systemic or in situ hematologic or immunological reactions were observed with either the meshes or the patch material. Histological studies revealed that thick collagenous and vascularized tissue were well anchored to the three biomaterials as early as 15 days after implantation. The degree of tissue penetration differed depending on the device. Chemically, they proved stable over time.

The retained surgical sponge - William Kaiser, C.; Friedman, S.; Spurling, K.P.; Slowick, T.; Kaiser, H.A. (Annals of Surgery, 1996)
Objective: A review was performed to investigate the frequency of occurrence and outcome of patients who have retained surgical sponges. Methods: Closed case records from the files of the Medical Professional Mutual Insurance Company (ProMutual, Boston, MA) involving a claim of retained surgical sponges were reviewed for a 7-year period. Results: Retained sponges occurred in 40 patients, comprising 48% of all closed claims for retained foreign bodies. A falsely correct sponge count after an abdominal procedure was documented in 76% of these claims. Ten percent of claims involved vaginal deliveries and minor non-body cavity procedures, for which no sponge count was performed. Total indemnity payments were $2,072,319, and defense costs were $572,079. In three cases, the surgeon was deemed responsible by the court despite the nursing staff's admitting liability and evidence presented that the surgeon complied completely with the standard of care. A wide range of indemnity payments was made despite a remarkable similarity of outcome in the patients studied. Conclusions: Despite the rarity of the reporting of a retained surgical sponge, this occurrence appears to be encountered more commonly than generally is appreciated. Operating teams should ensure that sponges be counted for all vaginal and any incisional procedures at risk for retaining a sponge. In addition, the surgeon should not unquestioningly accept correct count reports, but should develop the habit of performing a brief but thorough routine postprocedure wound/body cavity exploration before wound closure. The strikingly similar outcome for most patients would argue for a standardized indemnity payment being made without the need for adversarial legal procedures.

Inflammatory reactions after vascular prosthesis implantation: A comparison of gelatin-sealed and unsealed dacron prostheses - Utoh, J.; Miyauchi, Y.; Goto, H.; Obayashi, H.; Hirata, T. (Surgery Today, 1996)
Despite widespread use of the gelatin-sealed knitted Dacron prosthesis (GDP) in clinical practice owing to its zero porosity, the biological impacts of this graft are still controversial. We conducted a randomized controlled study on 50 patients undergoing abdominal aortic aneurysm repair to evaluate the inflammatory reaction to GDP (n = 25) and unsealed knitted Dacron prostheses (UDP, n = 25). There were no significant differences in the mean age, size of the aneurysm, operative time, blood loss, or transfusion requirements between the GDP and UDP groups. During the first 7 postoperative days (PODs), slight fever and leukocytosis were noticed in both groups. Significant differences in maximum body temperature, leukocyte count, and plasma C-reactive protein concentration were observed between the GDP and VDP groups on POD 14: 37.2 ± 0.5°C vs 36.9 ± 0.3°C (P = 0.019), 8,151 ± 1,788/μl vs 6,914 ± 1,501/μl (P = 0.015), and 32.6 ± 27.5 mg/l vs 19.0 ± 15.8 mg/l (P = 0.048), respectively. By POD 21, however, there were no detectable differences in these variables. Thus, we concluded that GDP caused an inflammatory reaction in the 2nd week after implantation, but ultimately there were no significant differences from UDP by the 3rd week.
Keywords: biocompatibility; C-reactive protein; gelatin-sealed Dacron prosthesis

Cellular reaction on the anterior surface of poly(methyl methacrylate) intraocular lenses. - Pande, M.V.; Spalton, D.J.; Kerr-Muir, M.G.; Marshall, J. (Journal of cataract and refractive surgery, 1996)
PURPOSE: To assess the cellular reaction on the anterior surface of poly(methyl methacrylate) (PMMA) intraocular lenses (IOLs) implanted by phacoemulsification with continuous curvilinear capsulorhexis (CCC) or by extracapsular cataract extraction (ECCE) with a linear capsulotomy. SETTING: Cataract and Refractive Surgery Research Unit. Department of Ophthalmology, St. Thomas' Hospital, London, United Kingdom. METHODS: To document morphology, topography, and severity of the cellular reaction, specular microscopy of the anterior IOL surface was performed at 1 day, 1 week, and 1 and 3 months postoperatively in two parallel groups of 31 consecutive cataractous eyes operated on by phacoemulsification with CCC or by ECCE with a linear capsulotomy. RESULTS: The local tissue response consisted of a nonspecific foreign-body reaction to the IOL and a lens epithelial cell reaction. The foreign-body reaction was significantly less severe in the phacoemulsification group than in the ECCE group, and the number of IOLs without inflammatory cells was significantly higher. CONCLUSION: The foreign-body reaction to PMMA IOLs is significantly reduced when the lens is implanted by phacoemulsification with CCC. This could be of clinical benefit in high-risk eyes prone to the inflammatory complications of cataract surgery.

Otology through the ages. - Pappas, D.G. (Otolaryngology--head and neck surgery : official journal of American Academy of Otolaryngology-Head and Neck Surgery, 1996)
Recounted are some, not all, of the most significant contributions to otology. The history of otology has, for the most part, followed the history of medicine: Little was known of otology by the ancient physicians, but their work must be reviewed to appreciate the progress that has been made. Most of the otology produced during the Middle Ages was limited to those structures that were readily accessible; otologic surgery was confined to trauma and removal of foreign bodies from the external auditory canals. Examination of the ear began after studies of the ear by Italian anatomists during the seventeenth century. It was not until the end of the eighteenth century that magnification was used so that the minute anatomic details could be observed. The clinical specialty of otology started in France (1850s), emerged as a scientific specialty in England, and received explosive progress from the German-speaking countries at the end of the nineteenth century. Otology has a remarkable background.

The effect of pentoxifylline on the lung during cardiopulmonary bypass - Türköz, R.; Yörükoǧlu, K.; Akcay, A.; Yilik, L.; Baltalarli, A.; Karahan, N.; Adanir, T.; Şaǧban, M. (European Journal of Cardio-thoracic Surgery, 1996)
Cardiopulmonary bypass (CPB) produces an inflammatory response due to the interaction of blood with a foreign body surface. The lungs are most affected by this inflammatory response. Pentoxifylline (PTX), a phosphodiesterase inhibitor and an inhibitor of leukocyte activation, is used to minimize damage in lungs where leukocytes play an important role. Twenty patients with mitral valve stenosis with planned mitral valve surgery were included in the study. The ten patients receiving pentoxifylline (PTX group) were administered 400 mg PTX orally TID for 3 days preoperatively and, following anesthetic induction, a 300 mg PTX infusion was given. The ten patients receiving no PTX were the control group (CT). Platelet and leukocyte counts, mean pulmonary arterial pressure (mPAP), pulmonary capillary wedge pressure (PCWP), cardiac index (CI), pulmonary vascular resistance (PVR), alveolar-arterial PO2 gradient (AaDO2) were measured just before and after CPB,and 2 h postoperatively. The number of the leukocytes increased in the blood samples drawn 15 min after CPB in both groups and 2 h postoperatively showed no statistical change. The number of platelets had decreased significantly at the end of the CPB in both groups and, 2 h postoperatively, there was a further decrease in the blood count in the control group (P < 0.05). There was no significant difference in either the preoperative or postoperative PAP, PAWP, and CI. Pulmonary vascular resistance increased in both groups following the CPB (CT, before: 136±44, after: 177±94 dyne· sec · cm-5; PTX, before: 151±82, after 182±43 dynes · sec · cm-5). Two hours postoperatively, a considerable increase continued in the control group (CT 219±170 dynes · sec · cm-5), while there was an insignificant increase in the PTX group (PTX 193±51 dynes · sec · cm-5) (P < 0.05). The alveolar-arterial PO2 gradient increased after the CPB in both groups but a moderate decrease was observed 2 h postoperatively. In lung biopsy specimens taken before and after the CPB, there was marked leukocyte sequestration in the control group, whereas the number of leukocytes was seen to be insignificant in the PTX group (P < 0.005). This dosage regimen of PTX inhibits the postoperative increase in PVR and greatly minimized leukocyte sequestration in the lung due to CPB. © Springer-Verlag 1996.
Keywords: Cardiopulmonary bypass; Lung; Pentoxifylline

In vivo biocompatibility study of ABA triblock copolymers consisting of poly(L-lactic-eo-glycolic acid) A blocks attached to central poly(oxyethylene) B blocks - Ronneberger, B.; Kao, W.J.; Andersen, J.M.; Kissel, T. (Journal of Biomedical Materials Research, 1996)
Films of three ABA-block copolymers composed of lacticco-glycolic acid A blocks and poly(oxyethylene) (PEO) B blocks and one random lactic-co-glycolic acid copolymer (PLG) were studied to investigate the influence of different polymer compositions and molecular weights on the tissue reaction, appearance of toxic degradation products, and swelling behavior in the cage implant system in rats. The inflammatory tissue reaction was followed over a 21-day implantation period by monitoring the leukocyte concentration, the extracellular acid, and alkaline phosphatase activities in a quantitative manner. Size and density of adherent macrophages and foreign body giant cells on the film surfaces were determined. The ABA and PLG implants caused only a minimal inflammatory reaction, as characterized by a low concentration of leukocytes during the implantation period when compared to empty cage controls. The content of PEO had an influence on the density of the adherent cells on the surface of the polymer film. An increase in PEO content and molecular weight decreased the cellular density during the implantation period. As demonstrated by scanning electron microscopy, no degradation was observed for all polymers during the implantation period. Our results demonstrate that the ABA block copolymers and PLG copolymer are equally well tolerated in the cage implant test system. ©1996 John Wiley & Sons, Inc.

Nafamostat mesilate reduces blood-foreign surface reactions similar to biocompatible materials - Usui, A.; Hiroura, M.; Kawamura, M.; Hibi, M.; Yoshida, K.; Murakami, F.; Tomita, Y.; Ooshima, H.; Murase, M. (Annals of Thoracic Surgery, 1996)
Background. Nafamostat mesilate (FUT-175) is a synthetic serine protease inhibitor that inactivates coagulation, fibrinolysis, and platelet aggregation. Nafamostat mesilate may suppress the blood-foreign surface reaction similar to biocompatible materials by blocking factor XIIa. Methods. We performed an in vitro study of cardiopulmonary bypass (CPB) with fresh human blood among the following three groups: standard CPB sets (C), biocompatible CPB sets (B), and standard CPB sets with FUT-175 (10 mg/L) (F). A clinical study using these same CPB groups also was performed in 45 patients undergoing aortocoronary bypass operations (15 patients each). We injected FUT-175 at 40 mg/h during CPB. Results. In the in vitro study, both groups B and F showed significantly lower levels of coagulation factors, thrombin-antithrombin III complex, fibrinopeptide A, β-thromboglobulin, complement C3a, granulocyte elastase, and free hemoglobin than group C at the conclusion of the study. Thrombin-antithrombin III complex and free hemoglobin in group F also were lower than in group B. The platelet count remained at a higher level in group F than in the other groups. Separation of bradykinin was suppressed most significantly in group F. In the clinical study, group F also showed significantly lower levels of α2-plasmin inhibitor plasmin complex and C3a than both groups C and B. There were minimal levels of free hemoglobin in group F. Conclusions. Nafamostat mesilate may contribute major beneficial effects toward conservation of blood during CPB and prevention of coagulopathy after CPB.

Proposed recommended practices for sponge, sharp, and instrument counts. Association of Operating Room Nurses. (AORN journal, 1995)

Role for interleukin‐4 in foreign‐body giant cell formation on a poly(etherurethane urea) in vivo - Kao, W.J.; McNally, A.K.; Hiltner, A.; Anderson, J.M. (Journal of Biomedical Materials Research, 1995)
Interleukin‐4 (IL‐4) was previously shown to induce extensive macrophage fusion to form foreign‐body giant cells (FBGCs) in vitro. In the present study, our goal was to extend these findings to an in vivo test environment on biomaterials. The subcutaneous cage‐implant system was modified for mice to elucidate IL‐4 participation in mediating FBGC formation in vivo. Exudate leukocyte concentrations from cages containing poly(etherurethane urea) (PEUU A′) and empty cage controls indicated a similar inflammatory response that turned toward resolution by 14 days postimplantation, thus confirming the applicability of the cage‐implant system in mice. FBGC kinetic analysis showed that the formation of mouse FBGCs occurs through the fusion of adherent macrophages at a constant rate up to 14 days of implantation. Purified goat anti‐mouse IL‐4 neutralizing antibody (IL4Ab) or normal goat nonspecific control IgG (gtIgG) at various concentrations, or recombinant murine IL‐4 (muIL4) was injected into the implanted cages containing PEUU A′ every 2 days for 7 days. The injection of IL4Ab significantly decreased the FBGC density on PEUU A′ cage‐implanted in mice, when compared with the nonspecific IgG or PBS injection controls. Conversely, the FBGC density was significantly increased by the injection of muIL4 when compared with nonspecific IgG and PBS injection controls. Adherent macrophage density, FBGC morphology, FBGC average size, and size distribution were not significantly different among IL4Ab, nonspecific control gtIgG, muIL4, and PBS control groups. Our data suggest that IL‐4 participates in FBGC formation on biomaterials in vivo. © 1995 John Wiley & Sons, Inc. Copyright © 1995 John Wiley & Sons, Inc.

Implantation of sepiolite-collagen complexes in surgically created rat calvaria defects - Herrera, JosI.; Olmo, N.; Turnay, J.; Sicilia, A.; Bascones, A.; Gavilanes, JosG.; Lizarbe, M. (Biomaterials, 1995)
The response of osseous tissue to the implantation of sepiolite-collagen complexes has been studied. Sepiolite, sepiolite-collagen complex and 0.5% glutaraldehyde-treated sepiolite-collagen complex were implanted in created circular defects in rat calvaria. The tissue reactions were analysed using light, transmission and scanning electron microscopies. The patterns of bone growth were radiographically analysed and the bone activity was indirectly quantified by using a point-count method. The reaction against the three implanted materials is characteristic of a foreign body reaction with abundant macrophages and giant cells. Implanted products have been detected in macrophages, which suggest the involvement of phagocytosis in the resorptive process. Bone grew at the implantation sites originating excrescences or sometimes a thin bridge at the defect margins. The studied materials, after implantation in contact with bone tissue, did not produce any toxic effect or necrosis, allowing bone activity. © 1995.
Keywords: collagen-based biomaterials; composites; in vivo implantation; Sepiolite-collagen complexes

Subcutaneous tissue reaction to synthetic auditory ossicle (Apaceram®) in rats - Cui, P.-C.; Ohsaki, K.; Ii, K.; Tenshin, S.; Kawata, T. (The Journal of Laryngology & Otology, 1995)
A study was carried out in order to obtain further information about the soft tissue response to thin Apaceram® discs of dense hydroxyapatite (HA) implanted in rats for various periods of time between one day and 10 months. The Apaceram® discs were implanted subcutaneously into the interscapular region of 33 rats. A sham operation was performed on eight rats used as controls. Decalcified histological sections stained with haematoxylin and eosin and Mallory's azan were examined and the different cell types found around the implants were counted. It was found that an acute inflammatory reaction occurred after one day and disappeared at about two weeks after implantation. In the test groups, macrophages and lymphocytes disappeared about one week later, and no inflammatory reaction was observed from one to three months. However, a tissue reaction occurred at six months with the appearance of macrophages and lymphocytes, and decreased gradually at 10 months. Meanwhile, a few foreign body giant cells at the Apaceram®-tissue interface and a thick layer of fibrous connective tissue around the Apaceram® disc were observed at 10 months. No osteogenesis was observed in any specimen. The results obtained so far suggest that Apaceram® is still a useful material for reconstructive surgery, despite the possible appearance of a slight macrophage reaction at six months. © 1995, JLO (1984) Limited. All rights reserved.
Keywords: Biocompatible materials; Cell count; Histology; Hydroxyapatites; Rats

Local immune inflammatory response to infected total hip and knee replacements - Nordström, D.; Santavirta, S.; Antti-Poika, I.; Konttinen, Y.T. (Archives of Orthopaedic and Trauma Surgery, 1994)
We studied the tissue response for periprosthetic pseudosynovial tissue in seven patients with a purulent endoprosthetic infection and six patients with common prosthesis loosening, using specific monoclonal antibodies in avidin-biotin-peroxidase complex staining. In infected cases, proline 4-hydroxylase positive fibroblasts dominated the stroma of the vascularized periprosthetic connective tissue, whereas ;diffuse local infiltrations of mononuclear cells characterized the cellular histological overview. Local cellular response consisted of CD11b and MHC locus II antigen-positive immunoreactive monocytes/macrophages and of T lymphocytes, mostly of the CD4 subset. Only a few CD25-positive cells could be detected. The local cellular response in six patients with prosthesis loosening of nonbacterial origin was mild, showing a sparse perivascular infiltration of CD11b- and Ia-positive monocytes/macrophages and CD4/CD8-positive T lymphocytes in a proportion of 2:1. Only occasional CD15- or lactoferrin-positive neutrophils and CD25-positive lymphocytes could be detected. Our results from chronically infected joint replacements suggest that neutrophils, being virtually absent in the tissue compartment, do not contribute to pathological events in the "pseudojoint" cavity, whereas local tissue response consists of a mononuclear inflammatory cell reaction of a macrophage-dependent foreign-body type. © 1994 Springer-Verlag.

Debridement of bacterial and particulate-contaminated wounds - McDonald, W.S.; Nichter, L.S. (Annals of Plastic Surgery, 1994)
Debridement of contaminated wounds is an essential component of uncomplicated wound healing. Efficient techniques should be capable of removing bacteria as well as foreign matter because of the well-known ability of foreign bodies to potentiate infection. We have compared the ability of current debridement techniques with the relatively new ultrasound debridement to clean wounds contaminated with bacteria and particulate matter. In part I, we prepared dorsal wounds on 15 Sprague-Dawley rats, and 20 mg of Montmorillonite clay soil fraction, a well-known infection-potentiating factor, was placed in each wound. Animals were randomly assigned to one of three treatment groups: ultrasound debridement, soaking, and irrigation. The amount of clay removed from each wound was measured. In part II, 48 Sprague- Dawley rats were given a standard wound and inoculated with a subinfective dose of Staphylococcus aureus bacteria and 10 mg of Montmorillonite clay particles. Each rat was randomly assigned to a debridement technique-soaking, scrubbing, high-pressure irrigation, and ultrasound-and was examined after 7 days for inflammatory responses. Results of part I demonstrated that ultrasound debridement and irrigation remove statistically equal amounts of clay (p < 0.05). In part II, we found that high-pressure irrigation and ultrasound debridement effectively treat contaminated wounds (gross infection, p < 0.05; wound induration, p < 0.0001; bacteria counts, p < 0.002). This study presents ultrasound debridement as effective treatment of contaminated wounds.

Siliconosis: A spectrum of illness - Borenstein, D. (Seminars in Arthritis and Rheumatism, 1994)
The information reported at this symposium presents initial data supporting the notion that patients with exposure to silicone gel are experiencing a new illness. Previously, this disorder was described variously as "human adjuvant disease" and chronic silicone arthropathy.15 During the symposium, the term siliconosis and silicone implant syndrome (SIMS) was used to describe the clinical syndrome associated with patients receiving silicone gel in liquid or encapsulated form. I prefer the term siliconosis because it is inclusive of symptomatic women who were exposed to silicone gel by injection or implant placement. Siliconosis is characterized by a spectrum of illness that may affect a number of organs. In its most common form, siliconosis is a musculoskeletal pain syndrome characterized by overwhelming fatigue, arthralgias, and myalgias. This form of the illness is reminiscent of a chronic flulike state. Influenza patients have overwhelming fatigue, fever, myalgias, and arthalgias. Common laboratory tests, such as complete blood count, erythrocyte sedimentation rate, and ANA are normal in individuals with influenza. It is difficult to document the presence of the virus, although the disease is diagnosed by physicians in the absence of positive viral cultures. Release of immune mediators (cytokines) by mononuclear cells is the most likely mechanism for the presence of constitutional symptoms. A similar circumstance may occur with the release of cytokines by mononuclear cells ingesting silicone. The criteria for classification of fibromylagia include generalized pain in symmetrical areas of the body including those above and below the waist.29 Also included is pain with palpation in 11 of 18 tender point sites. Other factors associated with fibromylagia include nonrestorative sleep, daytime fatigue, chronic headache, and irritable bowel syndrome. Criteria for chronic fatigue syndrome include persistent fatigue sufficient to reduce daily activity by 50% or more for a period over 6 months, along with chills, cervical lymphadenopathy, headaches, myalgias, sleep disturbance, and fever.30 Patients with silicone breast implants have similar but not identical symptoms associated with these other disorders. The severity of fatigue and the presence of a limited number of tender points differentiates this illness from fibromyalgia and chronic fatigue syndrome. Patients with fibromyalgia associated with siliconosis do not have symmetrical tender points. Most tender points are located above the waist, and < 11 are identified in these patients. Siliconosis also differs from chronic fatigue syndrome. Patients with breast implants do not have fever, which is a frequent manifestation of chronic fatigue syndrome. Laboratory tests are normal in chronic fatigue syndrome, whereas a third of symptomatic patients with silicone breast implants have abnormal laboratory tests including ANAs. In addition to the musculoskeletal symptoms associated with siliconosis, a minority of patients also experience skin rash, alopecia, fever, lymphadenopathy, and arthritis. A significant number of patients develop a Sjögren's-like disorder characterized by xerophthalmia and xerostomia. However, there is an absence of autoantibodies and cellular infiltrates associated with classic Sjögren's syndrome. Systemic lupuslike syndrome may appear with arthralgias, skin rash, and fever in the absence of detectable ANA. Rheumatoid arthritis-like disease may be characterized by years of polyarthritis without significant erosions or periarticular osteopenia. Neurological symptoms in the form of shortterm memory loss, paresthesias, and neuropathy have been reported.31. The pathogenesis of this disorder remains to be determined. The report of Kossovsky suggests that the alterations in plasma proteins facilitate the ingestion of silicone by macrophages that initiate an immunological response characterized by a chronic inflammatory state that is associated with the production of autoantibody and cytokines. The capsule surrounding implants is a potential site for production of a number of immunologically active factors that could result in patient symptoms. Inflammatory reaction, including lymphocytes, monocytes, and plasma cells, has been identified in implant patients, with or without overt leakage.32 Increased amounts of interleukin 2 have been detected in capsules surrounding breast implants.33 The presence of these factors may explain the reason for the presence of the syndrome in patients with intact implants. Clinical symptoms associated with this pathological immunological state may occur in genetically predisposed patients. Preliminary studies suggest that genetically predisposed patients may have the DR53 haplotype.34. Patients whose implants were removed have reported improvement in symptoms. The improvement is not immediate in most patients. Some patients report improvement that has its onset 12 months or more after explantation. This time course of improvement does not follow a course expected with placebo effect. One would predict that improvement with explantation would be immediate with placebo effect. Explantation of the implants, along with the surrounding capsule, removes a large amount of silicone from the patient. Improvement over 12 months or longer suggests that an abnormal immune response is decreasing with removal of the silicone. The amount of silicone that remains in patients with enlarged axillary lymph nodes may not be adequate, over time, to sustain the abnormal immune response. In some patients, the residual amounts of silicone may be adequate to sustain the pathological process. This group may contain the third of patients who do not improve with explantation. Finally, the current controversy involving silicone breast implants seems reminiscent of the debate surrounding the original patients with Lyme disease. The physicians who saw these first patients preferred to diagnose juvenile rheumatoid arthritis, a disease that they knew. Superficially, the illness seemed to be juvenile rheumatoid arthritis because it occurred in children and caused arthritis. However, closer scrutiny revealed that the illness occurred in clusters and affected adults as well as children. The illness was not juvenile rheumatoid arthritis, but a new illness caused by Borrelia burgdorferi and transmitted by a tick (Ixodes dammini). Our current understanding of silicone breast implants is that silicone is not inert and has the capability of causing systemic tissue damage. The mechanism by which this agent results in a clinical disease that differs from other rheumatic disorders remains to be determined. The participants of this symposium hope that the data presented will heighten interest in this condition and result in additional studies to further define the disease and improve therapies for women who are symptomatic from silicone breast implants. © 1994.

Tissue response to a braided poly-L-lactide implant in an experimental reconstruction of anterior cruciate ligament - Laitinen, O.; Alitalo, I.; Toivonen, T.; Vasenius, J.; Törmälä, P.; Vainionpää, S. (Journal of Materials Science: Materials in Medicine, 1993)
During follow-up periods of 6, 12, 24 and 48 weeks, the tissue response to a braided poly-L-lactide (PLLA) implant, 3.2 mm in diameter, was investigated in the reconstruction of experimental anterior cruciate ligament (ACL) ruptures in 32 sheep. In 16 sheep the cut ACL was removed and reconstructed with the fascia lata augmented with a PLLA implant. In 16 sheep the ACL was cut from its midportion, sutured, and thereafter augmented with a PLLA implant. The tissue reactions were typical of a scant non-specific-foreign-body reaction. The number of inflammatory and giant cells was greatest at six weeks, decreasing thereafter. Degradation of the PLLA was incomplete at 48 weeks. No signs of synovitis or changes in the cartilaginous surfaces were observed. The reconstructions in both groups were anchored to the bone by fibroconnective tissue, and remodelling of the bone was seen along the drill channels. After 48 weeks the maturation of the fibroconnective tissue and the orientation of the collagen fibres were higher (p<0.01) in the fascia-lata-PLLA group than in the primarysuture-PLLA group. Histologically, the braided PLLA implants proved to be suitable for ACL repair in sheep. The augmentation of the fascia lata with the PLLA implant seemed to be preferable to that of the primary suture of the ACL. © 1993 Chapman & Hall.

Corneal endothelial cell counts after Molteno implantation - McDermott, M.L.; Swendris, R.P.; Shin, D.H.; Juzych, M.S.; Cowden, J.W. (American Journal of Ophthalmology, 1993)
Implantation of a Molteno drainage shunt has been shown to be effective in advanced glaucoma. Foreign substances within the anterior chamber have been known to cause progressive endothelial cell loss. We undertook a study to evaluate the endothelial effects of an indwelling Molteno drainage shunt. Nineteen patients who underwent uneventful implantation of a Molteno drainage shunt for advanced aphakic or pseudophakic glaucoma were followed up. Serial endothelial cell counts were obtained in a masked fashion. During follow-up periods ranging from 5.4 to 25.7 months, endothelial cell loss averaged two cells per square millimeter per postoperative month with a 95% confidence interval of positive seven cells to negative ten cells per square millimeter per postoperative month. No clinically significant progressive trend in endothelial cell loss was seen in patients undergoing uncomplicated Molteno drainage procedures. Larger sample sizes with longer follow-up will be necessary to establish whether a Molteno drainage shunt causes clinically remarkable endothelial cell loss.

Penetrating abdominal trauma - Marx, J.A. (Emergency Medicine Clinics of North America, 1993)
Penetrating trauma of the abdomen no longer warrants mandatory laparotomy. Clinical predictors of the need for operation should first be employed. Patients who do not meet these clinical criteria undergo a selective diagnostic approach on the basis of mechanism and site of injury and the experience and expertise of the institution. Through the use of algorithms, this article reviews the management of stab and gun shot wounds to the abdomen.

The adhesion of labelled neutrophils on synthetic vascular grafts. An experimental porcine study - Pärsson, H.; Jundzill, W.; Jonung, T.; Thörne, J.; Norgren, L. (European Journal of Vascular Surgery, 1993)
The adhesion of neutrophils onto different vascular grafts was studied in vivo in a pig model. In acute experiments autologous 111In-labelled neutrophils were reinfused after end-to-side implantation of 5cm, 6mm internal diameter grafts. The dynamic deposition on each graft was determined for 300min in vivo. Static measurements in vitro concluded the study. The adhesion was greater in Dacron and collagen coated Dacron grafts compared to expanded polytetrafluoroethylene (ePTFE) and to Dacron grafts coated with a polymer. The segmental activity along all the grafts increased towards the distal anastomosis. The results suggest different inflammatory response to various graft materials. © 1993 Grune & Stratton Ltd.
Keywords: Inflammatory reaction; Neutrophils; Vascular grafts

Nurse and the law. Relying on the count. - Langslow, A. (The Australian nurses" journal, 1992)

The tissue-implant interface during degradation of absorbable polyglycolide fracture fixation screws in the rabbit femur - Bostman, O.M.; Paivarinta, U.; Partio, E.; Manninen, M.; Vasenius, J.; Majola, A.; Rokkanen, P. (Clinical Orthopaedics and Related Research, 1992)
A transverse transcondylar osteotomy of the distal femur was fixed with an axially placed absorbable fracture fixation screw made of polyglycolide (PGA) in 25 rabbits. Changes at the tissue-implant interface accompanying degradation of the screw were examined histologically, histomorphometrically, and microradiographically seven, 20, 40, 80, and 250 days after implantation. At seven days postimplantation, a layer of fibroblasts was seen surrounding the implant, and new bone formation was discernible in the host tissues adjacent to this membranous structure. At 20 days postimplantation, the geometry of the screw was still intact and the tissue-implant boundary was distinct. The first signs of invasion of vascular granulation tissue into the implant were observed 40 days after implantation, at which time the osteotomies were united. The apparent walling-off response by formation of new trabecular bone outlining the PGA profile continued, with the greatest mean trabecular bone volume fraction at the interface, 23.9%, measured at 40 days. A significant decrease in the new bone volume occurred between 40 and 80 days postimplantation. The intensity of the foreign-body reaction seen was histologically moderate. The giant cell count was highest at 80 days postimplantation, when the migratory activity of phagocytic cells had transported intracellular particulate polymeric debris 400-800 μm away from the original tissue-implant boundary. At 250 days postimplantation, no birefringent polymeric material could be seen in the specimens. No contraindications for the clinical application of PGA implants emerged in this study.

Intraventricular vancomycin-induced cerebrospinal fluid eosinophila: Report of two patients - Grabb, P.A.; Albright, A.L. (Neurosurgery, 1992)
Pediatric neurosurgeons commonly instill vancomycin into the ventricles to treat shunt infections. This use for vancomycin, however, has not been studied in the laboratory to evaluate possible toxicities and side effects. We report two cases of cerebrospinal fluid eosinophilia (CSFE) secondary to the intraventricular administration of vancomycin. Two other cases of shunt infection during the same time period were treated for only 2 days with intraventricular vancomycin and did not manifest CSFE. We address the clinical problems and possible detrimental effects of CSFE in the setting of shunt infection. We propose a mechanism of vancomycin-induced mast cell degranulation and subsequent release of eosinophil chemotactic factor as a cause of CSFE. An initial dose of intraventricular vancomycin should take into account volume of distribution (ventricular size) to obtain a peak cerebrospinal fluid concentration of 20 to 30 μg/mL. We recommend following daily cell counts and vancomycin peak and trough levels to calculate the amount and frequency of intraventricular vancomycin required to maintain safe and effective concentrations and to monitor for CSFE. © by the Congress of Neurological Surgeons.
Keywords: Cerebrospinal fluid; Eosinophilia; Intraventricular antibiotics; Vancomycin

Scintimetry after total knee arthroplasty: Prospective 2-year study of 18 cases of arthrosis and 15 cases of theumatoid arthritis - Nilsson, K.G.; Björnebrink, J.; Hietala, S.O.; Kärrholm, J. (Acta Orthopaedica, 1992)
33 consecutive patients (18 arthrosis, 15 rheumatoid arthritis), operated on with total knee arthroplasty and randomized to cemented (18 knees) or cementless fixation (15 knees), were investigated with scintimetry 3, 6, 12, and 24 months postoperatively. Migration was evaluated with simultaneous roentgen stereophotogrammetric (RSA) examinations. the scintimetric activity in the ipsilateral femoral diaphy-sis decreased and the activity in the tibial diaphysis increased during the observation period. Constant and low activity was recorded in front of the femoral component. This region was chosen as a reference. Three months after surgery, high activity was noted under the tibial component in knees with a preoperative varus deformity. After 2 years, the activity had decreased to the same level as in the patients with a valgus deformity. Diagnosis and mode of fixation did not influence the activity. Low postoperative activity was recorded in the tibial metaphyses if no rotatory displacement of the tibial component occurred. © 1992 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.

Quantitative comparison of the histological effects of particulate polymethylmethacrylate versus polyethylene in the rabbit tibia - Goodman, S.B.; Fornasier, V.L.; Keil, J. (Archives of Orthopaedic and Trauma Surgery, 1991)
Fourteen mature female New Zealand White rabbits underwent implantation of Simplex polymethylmethacrylate (PMMA) powder or particulate (average 67 μn) ultrahigh-molecular-weight polyethylene (UHMWPE) through a drill hole in the proximal right tibia. The left tibia functioned as a prepared but nonimplanted control. Animals were killed after 16 weeks. Histological examination of the bone-implant interface in the particulate PMMA group disclosed a florid foreign-body reaction with the presence of giant cells and histiocytes. The particulate UHMWPE group demonstrated positively bire-fringent UHMWPE fragments, rimmed by foreign-body giant cells and histiocytes, embedded in a loose connective tissue stroma. UHMWPE interfaces were thicker and contained more histiocytes and fibrocytes; PMMA interfaces contained more marrow cells and lymphocytes. This study underscores the importance of biomaterial debris in the process of aseptic loosening of cemented joint arthroplasties. © 1991 Springer-Verlag.

Macrophage exposure to polymethyl methacrylate leads to mediator release and injury - Horowitz, S.M.; Gautsch, T.L.; Frondoza, C.G.; Riley, L., Jr. (Journal of Orthopaedic Research, 1991)
To understand further the role of macrophages in the loosening of cemented arthroplasty, several in vitro effects of polymethyl methacrylate (PMMA) particle exposure in these cells were studied. The kinetics of arachidonic acid and derived inflammatory mediator release was characterized following macrophage exposure to either PMMA or control polystyrene particles. Temporal release of radiolabeled products by [14C]arachidonate–labeled cells was determined by sequential scintillation counting. Significant dosedependent release of arachidonic acid mediators by macrophages was observed within half an hour of exposure to either PMMA or styrene particles. Unexposed control cells incubated in media alone did not release detectable amounts of radiolabeled products. The leakage of intracellular lactate dehydrogenase (LDH), a marker of cell injury, was detected spectrophotometrically 4 h following exposure to PMMA but not styrene. PMMA‐induced LDH release was dose depedent. In contrast, polystyrene exposure failed to increase LDH release above unexposed control cells. These in vitro studies reveal that macrophages rapidly released arachidonic acid and derived inflammatory mediators in response to both PMMA and styrene particles. However, cells exposed to PMMA are lethally damaged, as reflected by the subsequent leakage of their intracellular LDH. We propose that a similar sequence of events may occur when macrophages encounter PMMA particles at the bone‐cement interface. This is characteristic of a foreign body granulomatous response. Copyright © 1991 Orthopaedic Research Society
Keywords: Aseptic loosening; Cemented arthroplasty; Macrophages; Polymethyl methacrylate

Lymphocyte-macrophage activity in the human endolymphatic sac - Rask-andersen, H.; Danckwardt-lillieström, N.; Friberg, U.; House, W. (Acta Oto-Laryngologica, 1991)
The human endolymphatic sac was analysed electron microscopically in patients undergoing acoustic Schwannoma surgery or vestibular nerve section. In addition, endolymphatic sacs from cadavers were analysed light microscopically. The results show that the human sac is endowed with a variable number of leucocytes and that there is a continuous recirculation of immunocompetent cells in this area of the inner ear that may be of importance for clearance of the inner ear from foreign substances and microorganisms derived from nearby located infection-prone areas. The possibility in Meniere's disease of a disturbed immunological activity in the sac is discussed. © 1991 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.
Keywords: Endolymphatic sac; Human; Inner ear; Meniere's disease; Ultrastructure

Morphofunctional evaluation of fibrin glue versus microsuture nerve repairs - Maragh, H.; Meyer, B.S.; Davenport, D.; Gould, J.D.; Terzis, J.K. (Journal of Reconstructive Microsurgery, 1990)
Complications of microsuture repair of peripheral nerves include mechanical trauma, foreign body reaction, impairment of vascularity, and possible obstruction to successful sprouting. In addition, there are occasions when it is virtually impossible to perform a suture repair because of limited exposure and/or very fine structures, such as are encountered in pediatric cases. These situations have continued to provide the impetus for evaluating alternative methods of nerve coaptation. Recently, the use of tissue glue has gained in popularity as a technique for sutureless nerve repairs. We decided to test the efficacy of fibrin glue repair versus microsuture coaptation in the rat sciatic model. The repair sites were assessed for tensile strength, by quantitative morphometry, and by electrophysiologic studies. Tensile strength findings revealed that at two, four, and eight weeks after surgery, there was no significant difference between the two repair techniques, although there was a trend toward a stronger hold in the microsuture repairs. Electrophysiologic recordings revealed that conventional microsuture repairs had significantly faster conduction velocities, larger area under the curve, and higher peak amplitudes. The onset and peak latencies were comparable, revealing that the axonal quality of at least a certain number of axons was similar electrically. Axonal counts both proximal and distal to the repair showed no significant difference, although there was an overall suggestion of superiority in the number of myelinated axons in the suture repair.

Complications and demographic characteristics of patients undergoing lumbar discectomy in community hospitals - Ramirez, L.F.; Thisted, R.; Sypert, G.W.; Horwitz, N. (Neurosurgery, 1989)
We determined the incidence of acute, major complications in a population of 28,395 patients who underwent lumbar laminectomy for discogenic radiculopathy in the United States in 1980. This population was drawn from a broad cross-section of community hospital and represented 31% of all patients who underwent laminectomy that year for this condition. Our cohort excluded patients with a) operations exceeding two disc levels, b) fusion, c) previous lumbar laminectomy, or d) coexistent discitis, spondylosis, spinal stenosis, myelopathy, or arachnoiditis. The incidence of death was 5.9 per 10,000. The causes of death were septicemia, myocardial infarction, and pulmonary embolus. The incidence of at least one major complication was 157 per 10,000. The incidences of specific complications were as follows: infection requiring intravenously administered antibiotics, 30.7; major neurological deficit, 29.8; pulmonary embolus, 10.7; and myocardial infarction, 5.6. We studied four additional categories of complication. Patients were counted only when a second operation was required to treat the complication. The categories and incidence per 10,000 were as follows: incisional hematoma, 8.7; cerebrospinal fluid fistula, 10.5; ventral perforation, 1.6; and retention of a foreign body, 0.7. Among the patients whose hospitalizations were otherwise normal, 6.7% received a blood transfusion; of the patients whose hospitalizations were complicated, 24% required transfusion. The demographic characteristics of patients with a normal hospitalization were tabulated separately from those whose hospitalizations were complicated. Neurosurgeons performed 60% of the operations, and orthopedic surgeons performed 40%. The speciality of the surgeon was not a factor in determining the risk involved in surgery. Spinal anesthesia was used in 7% of the cases, and no pattern of complications emerged that was uniquely related to that technique.

Pelvic actinomycosis associated with intrauterine devices - O'Connor, K.F.; Bagg, M.N.; Croley, M.R.; Schabel, S.I. (Radiology, 1989)
The authors describe two women with pelvic pain, long-term use of an intrauterine device, and a pelvic mass due to Actinomyces israelii. The diagnostic imaging findings were nonspecific but included mass effect and mucosal irregularity of the rectosigmoid colon at barium enema examination and complex masses and inflammatory changes at computed tomography and magnetic resonance imaging. Radiologists should be aware of the imaging findings of this potentially lethal but curable condition. 2 cases of pelvic Actinomycosis both in women 40 years of age, with IUDs in place for 8 and 10 years respectively, were diagnosed with the aid of radiologic techniques including barium enema, computed tomography (CT) and magnetic resonance imaging (MR). The 1st woman had experienced malaise, night sweats and a weight loss of 15 lb. over 2-3 months, then felt an epigastric mass for 5 days. She has endometritis, elevated white blood cell count, and large, tender, bilateral adnexal masses. Inflammatory changes and multilocular fluid collections were demonstrated by enhanced CT. Aspiration of the epigastric mass yielded sulfur granules and anaerobic bacteria. She was successfully treated with penicillin, gentamycin and clindamycin. The 2nd woman had a 2-month history of abdominal pain, a pelvic mass and an elevated white blood cell count. Enhanced CT, barium enema and sigmoidoscopy demonstrated a mass between the uterus and bowel, with mural invasion of the sigmoid colon. A 5 x 6 cm left-sided tubo-ovarian abscess adhering to the colon, bladder and left pelvic sidewall was excised at laparotomy. She remained asymptomatic at 6 months. This lethal but curable condition is caused by Actinomyces israelii, an opportunistic gram-positive bacteria usually introduced by foreign bodies, surgery or trauma. CT and MR were helpful in diagnosing the relatively nonspecific signs and symptoms in these cases.

EARLY EXPERIENCES WITH SOFT INTRAOCULAR IMPLANTS - STEELE, A.O.McG. (Australian and New Zealand Journal of Ophthalmology, 1988)
The author recounts his early experience with implants for the posterior chamber made of silicone. While the numbers are small the visual results appear to be satisfactory. The results, however, are marred by an as yet unacceptable rate of post‐operative complications. Copyright © 1988, Wiley Blackwell. All rights reserved
Keywords: hydrogel lens; Polymethylmethacrilate; silicone intraocular implant.

Differentiation of aseptic and bacterial meningitis in postoperative neurosurgical patients - Ross, D.; Rosegay, H.; Pons, V. (Journal of Neurosurgery, 1988)
The differentiation of bacterial from aseptic meningitis in postoperative neurosurgical patients has traditionally been based on the clinical setting, a recent history of steroid administration, and cerebrospinal fluid (CSF) studies, including the total and differential leukocyte counts, Gram stain, glucose, and total protein. Recent reports questioning both the validity of a relative CSF lymphocytosis in excluding bacterial meningitis and the usefulness of standard CSF testing prompted the authors to reevaluate these standard criteria. The type of operation, the presence of a foreign body, use of steroids, postoperative day on which symptoms developed, altered mental status, neck stiffness, headache, and nausea were not helpful in the differential diagnosis. High fever, new neurological deficits, and active CSF leak, and elevated leukocyte counts in the CSF and peripheral blood favored a bacterial etiology. The CSF glucose level and the differential leukocyte count were less helpful. No criterion or combination of criteria was sensitive and specific enough to reliably differentiate aseptic from bacterial meningitis in the majority of patients. The possibility of improving diagnostic accuracy with newer tests, such as CSF lactate, ferritin, total amino acids, C-reactive protein, and amyloid-A, should be assessed.

Biological evaluations of zinc hexyl vanillate cement using two in vivo test methods - Keller, J.C.; Hammond, B.D.; Kowalyk, K.K.; Brauer, G.M. (Dental Materials, 1988)
The cellular and tissue responses to 3 dental cements were studied by 2 methodologies, the connective tissue implantation technique (CTI), recommended by the ADA, and the peritoneal cavity implantation technique (PCI), which has emerged as a method to quantitatively study the cellular response to implanted materials. A mixed inflammatory cell response consisting of neutrophils and macrophages occurred at most of the time periods for all the cements examined in the CTI study. Similar cell populations, including lymphocytes, were observed with the PCI study using differential staining techniques. The histopathological observations from both procedures were similar. Each cement elicited a chronic foreign body reaction containing few chronic cells and mature fibroblastic activity. The intensity of the observed tissue reactions for each cement, as determined by capsule thickness in the CTI study and the overall cell counts in the PCI study, did not differ significantly with increasing time. The cellular and connective tissue reactions to the zinc hexyl vanillate (ZHV) cement approximated those of zinc oxide-eugenol (ZOE) and zinc phosphate (ZP) cements for both methodologies utilized in this work. While similar histopathological results were obtained for the implantation of cements using both methodologies, the PCI technique offers a more thorough investigation of cellular and tissue responses to implanted materials. In addition to histopathological evaluations, the PCI techniques allows quantitative investigation of the specific cells responding to the implants, and provides a mechanism, using chemical analysis techniques, to quantify the concentration of specific degradative products within the retrieved cells and host tissue. Finally, the results from these 2 methodologies demonstrated the acceptable biological performance of ZHV cement compared with the clinically acceptable ZP and ZOE cement formulations. © 1988 Munksgaard International Publishers Ltd.
Keywords: dental cement; zinc hexyl vanillate; zinc oxide-eugenol; zinc phosphate

Mechanism of action of intrauterine devices: Biochemical changes - Johannisson, E. (Contraception, 1987)
The mechanism of action of intrauterine devices varies from one type of device to another, although the principle of action is the same, namely, to interfere with the physiology of reproduction at the endometrial level. The biochemical changes of the endometrial tissue and the composition of the uterine fluid have been reviewed in relation to the use of inert, copper-medicated and steroid-releasing IUDs. All IUDs, whether inert or medicated, provoke a significant increase in the number of neutrophils, mononuclear cells and plasma cells, the presence of which is unrelated to the tissue infiltration of inflammatory cells occurring pre-menstrually of the normal menstrual cycle. The increase of leucocytes in IUD-users is compatible with a foreign body reaction which may be related to the antifertility effect. The addition of copper to an inert IUD has been shown to significantly alter the metabolism of the endometrial cells, e.g. the enzymatic activity and the DOVA-synthesis. The steroid-medicated IUDs represent a new approach to intrauterine contraception where the morphology of the endometrium is considerably altered, showing massive decidual changes, atrophic glands and sometimes atrophy of the whole functional layer. In addition, there is an important foreign body reaction, similar to that of the inert IUDs. The enzymatic activity, as well as the proliferative activity was significantly altered in the endometrium of these IUD-users. Changes in the endometrial fibrinolytic activity in IUD-users have been demonstrated to be related to the presence of irregular bleeding. Micro-traumata of the endometrium and the increased fibrinolytic activity may also interfere with the protective processes present in the physiologically normal endometrium. Further studies on the factors influencing the fertilizing ability of the spermatozoa in the female genital tract, as well as on the conditions of the human endometrium required for the implantation of a blastocyst, may yield important information for the improvement of intrauterine contraception. © 1987.

Doctors, nurses and "sponge counts". - Tammelleo, A.D. (The Regan report on nursing law, 1986)

Nurses, doctors and sponge counts: liability. - Tammeleo, A.D. (The Regan report on nursing law, 1986)

Incorrect counts; surgeon's negligence does not absolve nurses from liability. - Murphy, E.K. (AORN journal, 1986)

Current Concepts in the Management of Infections in Bones and Joints - Dickie, A.S. (Drugs, 1986)
Significant changes have taken place in the epidemiology, microbiology and antibiotic therapy of bone and joint infections. Gram-negative bacilli have become an increasingly common cause, particularly in immunocompromised patients; anaerobes have been implicated in osteomyelitis associated with metallic foreign bodies; and there is increasing use of oral antibiotic regimens following an initial period of parenteral treatment. Gram-negative bacilli and anaerobes are found in polymicrobial non-haematogenous osteomyelitis (e.g. post-traumatic, post-surgical), but Staphylococcus aureus remains the most common cause of acute haematogenous osteomyelitis, with streptococci and Haemophilus influenzae responsible for most of the remainder. A precise microbiological diagnosis is essential. Diagnosis is based on Gram stain and culture of bone biopsies or aspirated pus, or on blood cultures. Specimens should be obtained before starting therapy. Any suspected primary foci of infection should be cultured. Parenteral antibiotics are given as soon as specimens are obtained, and continued for at least 3 weeks. The common causative organisms in septic arthritis are the same as in osteomyelitis, with the addition of Neisseria gonorrhoeae in young, sexually active adults. As in osteomyelitis, a precise microbiological diagnosis is of paramount importance, ideally by joint aspiration for cell count, Gram stain, biochemical analysis and culture, or by blood cultures. Optimum therapy is with antibiotics, repeated therapeutic aspirations, and resting the joint. Parenteral antibiotics should be started as soon as specimens are obtained and continued for 4 to 6 weeks. Gonococcal arthritis, however, can be treated successfully with 1 week of antibiotics. When treatment of either osteomyelitis or septic arthritis is continued with oral antibiotics, serum antibiotic concentrations or serum bactericidal levels are mandatory to ensure adequate absorption. © 1986, ADIS Press Limited. All rights reserved.

Sponge count botched--discovery & silence. Case in point: Simon v. Smith (470 So. 2d 941 - LA). - Tammeleo, A.D. (The Regan report on nursing law, 1985)

Macrophages and tumor growth. II. Cell kinetics at the site of allogeneic tumor growth - Barrera, C.N.; Mazzolli, A.B.; Bustuoabad, O.D.; Andreetta, M.; Pasqualini, C.D. (Cancer Investigation, 1985)
The sponge matrix allograft model made possible the growth of an AKR lymphoma in a certain percentage of BALB/c mice making progressors (tumor-bearing) and regressors (tumor-rejecting) simultaneously available. Mice bearing either an AKR kidney allograft or a sponge alone were used as controls. The cell population infiltrating the sponge was evaluated 2, 5, 10, 15, and 21 days after subcutaneous implantation. It consisted of macrophages, lymphocytes, and neutrophils. There was no difference between groups on Day 2 and Day 5. From Day 10 onwards, tumor growth was evident with a clear cut separation between progressors and regressors. The latter behaved like the two control groups except for a significant increase in lymphocytes on Day 21. The progressors showed a striking increase in total cell count from Day 10 onwards. Macrophages were the major population with a maximum value of 201 X 106 as compared to 8 X 106 in the regressors; their phagocytic and lysosomal activity remained similar in all groups. The lymphocytes showed no variation in absolute numbers but, because of the high cell count in progressors, their ratio to macrophages reached 1:50 on Day 10, making up only 2% of the cell population. Neutrophils were significantly increased in progressors as compared with the other groups. It can be concluded that in the presence of a foreign body reaction a marked influx of macrophages accompanies allogeneic tumor growth. © 1985 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.

An in vivo method for the biological evaluation of metal implants - Keller, J.C.; Marshall, G.W.; Kaminski, E.J. (Journal of Biomedical Materials Research, 1984)
The peritoneal cavity of the rat was used as an implantation site in order to study the quantitative, cellular response and the qualitative, histopathological response to three metals (Ag, Sn, Cu). The effects of the metals on the cells were correlated with the cellular concentrations of the metal as determined by chemical analysis. Small variations in the cell population and a minimal foreign body reaction was observed with an implanted control material (silicone polymer). Large increases in the number of cells and an intense foreign body reaction was observed with Cu implants. Decreases in the number of cells were seen with Sn and Ag implants, but only Sn elicited a foreign body reaction. Implantation of Ag failed to elicit a foreign body reaction. Significant concentrations of all three metals were detected in the retrieved cells. Copyright © 1984 John Wiley & Sons, Inc.

In vivo biocompatibility studies. V. In vivo leukocyte interactions with biomer - Marchant, R.E.; Miller, K.M.; Anderson, J.M. (Journal of Biomedical Materials Research, 1984)
A cage implant system was utilized to quantitatively and qualitatively characterize in vivo leukocyte interactions with cast Biomer. Scanning electron microscopy (SEM) in conjunction with cytochemical staining procedures were used to investigate the cellular events at the leukocyte/Biomer interface as well as in the inflammatory exudate over a 21‐day implantation period. SEM was used to characterize leukocyte morphology on the Biomer surface and the cytochemical stains were used to differentially count leukocytes and to demonstrate intracellular alkaline and acid phosphatase activity. The results showed that the population density of leukocytes on the Biomer surface diminished with implantation time. The population density of multinucleated foreign body giant cells remained constant with time, while the numbers of nuclei per giant cell increased. The differential analysis revealed that macrophages preferentially adhered to the Biomer surface compared to other leukocytes in the exudate. The phagocytic capability of all adherent leukocytes, including giant cells, decreased with time and this corresponded to changes in leukocyte morphology observed with SEM. Copyright © 1984 John Wiley & Sons, Inc.

Perforation of the oesophagus : A comparison between surgical and conservative treatment - Erwall, C.; Ejerblad, S.; Lindholm, C.-E.; Aberg, T. (Acta Oto-Laryngologica, 1984)
A series of 48 patients with oesophageal perforations was reviewed retrospectively. Eighty-seven per cent of the perforations were iatrogenic. Twenty-four patients were treated conservatively; 3 of this group died. The other 24 patients were treated surgically and 4 of them died. Patients with alarming symptoms and/or a large perforation underwent operative treatment unless there were contra-indications. Retained foreign bodies after perforation, and malignancy in the perforation area, were considered as indications for operation. Conservative treatment was reserved for patients with minor tears combined with a less turbulent course. The interval between perforation and therapy was not of decisive importance for the mortality in our series. The clinical picture, which was dominated by chest pain, gave the earliest indication of perforation, while the responses of the sedimentation rate, temperature and white blood count occurred later and were less reliable diagnostic signs. © 1984 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.

Evaluation of Pulsating Jet lavage in prevention of surgical wound infection - Lopez, V.; Yague Perez, S.; Llamas Zuniga, P.; Perez Trallero, E. (Journal of Abdominal Surgery, 1984)
Irrigation under pressure of contaminated surgical wounds causes the elimination of bacteria and foreign bodies from the wound. The Pulsating-Jet as an irrigation device, especially under high pressure, represents a useful method for the prevention of wound infections. In this study, the authors evaluate the results in 95 patients with purulent peritonitis who were subdivided in four groups: (a) Control, (b) Manual irrigation, (c) Pressure irrigation at 50 lbs/square inch, (d) Pressure irrigation at 70 lbs/square inch. In groups b, c, and d, semiquantitative evaluation of bacterial contamination was done before and after irrigation. The evaluation of the results was based on the percentage decrease in the bacterial counts after irrigation, the severity of the wound infection and the patients' morbidity understood as number of postoperative hospital days. The results show, with statistical significance, that manual irrigation is not effective when compared to Pulsating-Jet irrigation, especially at high pressures. The usage of of this irrigating method at high pressures and flows entails a reduction of the bacterial count and of the surgical wound infection rate and thus, shortens the postoperative hospital stay.

Approaching the controversies in antibacterial management of cancer patients - Pizzo, P.A.; Commers, J.; Cotton, D.; Gress, J.; Hathorn, J.; Hiemenz, J.; Longo, D.; Marshall, D.; Robichaud, K.J. (The American Journal of Medicine, 1984)
The principles for management of infectious complications in cancer patients are continuing to evolve. The critical element includes the prompt institution of broad-spectrum antibiotic(s) empirically when granulocytopenic patients become febrile and continuation and modification of the regimen in patients with persistent fever and granulocytopenia. The view is presented that antibiotics provide systemic prophylaxis as well as therapy in persistently granulocytopenic patients and that they should be continued until all signs of infection have cleared or the granulocyte count has recovered. Such aggressive therapy, supplemented by continued evaluation and monitoring of the patient, can significantly reduce infection-relation morbidity and mortality. © 1984.

Compressive optic neuropathy following use of intracranial oxidized cellulose hemostat - Dutton, J.J.; Tse, D.T.; Anderson, R.L. (Ophthalmic Surgery, 1983)
A 35-year-old white male sustained head injuries in a motor vehicle accident. He underwent neurosurgical repair of a frontotemporal skull fracture and lacerated left frontal lobe; regenerated oxidized cellulose (Surgicel) was placed into the anterior cranial fossa for hemostasis. Forty-eight hours after surgery he suffered rapid deterioration of vision to no light perception from optic nerve compression. Radiologic and echographic evaluation demonstrated a subperiosteal soft tissue density in the orbital apex consistent with hematoma. At surgery for optic canal decompression, the cellulose hemostat was found in the apex of the left orbit, having migrated through orbital roof fractures, and had apparently caused the compressive optic neuropathy. Decompression resulted in return of vision to the level of counting fingers.

The Neutrophil Response to Polyvinyl Sponge Implantation - Priebat, D.A.; Bradley, P.P.; Christensen, R.D.; Rothstein, G. (Proceedings of the Society for Experimental Biology and Medicine, 1983)
Neutrophil release and migration in mice were studied over a 24-hr period after the sc implantation of a single polyvinyl sponge. The release of neutrophils from the marrow was evaluated by directly counting the residual neutrophils in the femoral marrow of animals with sponges. Sponge and tissue neutrophil content was determined by extraction and assay of myeloperoxidase (MPO), a marker enzyme for neutrophils. A maximum depletion of 48% of the mature neutrophils in the marrow was observed 5 hr after sponge implantation, in keeping with significant release of neutrophils for migration to the sponge. The released cells were not found in the circulating granulocyte pool, since neutropenia was noted. The accumulation of neutrophils in the sponge increased throughout the 24-hr period, whereas in the tissue adjacent to the sponge maximum accumulation of neutrophils occurred within 7 hr. In fact, neutrophils migrated to at least three sites—the sponge, the skin overlying the sponge, and the skin in which an incision had been made to insert the sponge. The sponge content of neutrophils represented 0.3-33% of the neutrophils migrating to the combined lesion (sponge and skin sites). Therefore, if the neutrophil response to foreign body implantation is to be measured in its entirety, it is necessary to quantify not only the neutrophils within the foreign body but also those in the tissues surrounding it. These studies describe an animal model for neutrophil release and migration to tissues following a standard stimulus. It is proposed that this model may be useful in exploring the factors which influence the release and migration of neutrophils in vivo. © 1983, SAGE Publications. All rights reserved.

Wound contamination. Assessment, prevention, and management - Georgiade, G.S. (Postgraduate Medicine, 1983)
The history of a wound and its clinical appearance help the clinician make appropriate decisions on management. The level of contamination in the wound can be determined with the rapid biopsy fixation technique. Extensive wound debridement, high-pressure irrigation, and cautious use of antibiotics should reduce the bacterial count to a level that allows primary healing. The use of sutures of appropriate chemical and physical characteristics should minimize suture contribution to the development of wound infection. Coverage of the wound after closure protects it from external contaminants and allows for completion of epithelialization. Immobilization and, if possible, elevation of the wounded part decrease secondary edema formation.

Legal case briefs for nurses. IN: Pediatrics: pre-discharge injury; ME: Surgery: sponge count error. - Regan, W.A. (The Regan report on nursing law, 1982)

Natural history of the retained surgical sponge - Hyslop, J.W.; Maull, K.I. (Southern Medical Journal, 1982)
Retained surgical sponge is an infrequently reported condition that may be recognized incidentally during the early postoperative period, produce serious complications, or remain dormant for years. Clinical manifestations of the retained surgical sponge are a function of bacterial contamination and of the location of the sponge within the body cavity. Few sequelae follow external extrusion but internal erosion may lead to abscess, fistulas, and intestinal obstruction. Prevention requires constant sensitivity of the surgeon to this potential threat to the safe practice of surgery. The surgeon must account for an incorrect sponge count by adequate examination of the operative Held and by roentgenographic studies when the issue remains in doubt. A correct sponge count does not fully preclude a retained sponge, however, and inspection of the operative field should be routine in all patients at risk. © 1982 Southern Medical Association.

Pelvic actinomycosis associated with use of intrauterine device: A new challenge for the surgeon - Doberneck, R.C. (American Surgeon, 1982)
Pelvic actinomycosis associated with the use of an intrauterine device (IUD) is a recently recognized combination. The usual manifestations of the disease are those of mild pelvic inflammatory disease (PID) in a woman who uses an IUD. The disease is easily recognized on Papanicolaou-stained cervicovaginal smears. Early treatment involves removal of the IUD and administration of penicillin. Rarely, the disease may be serious and may require drainage of intra-abdominal abscesses, hysterectomy with salpingo-oophorectomy, or both. The second known death from pelvic actinomycosis associated with use of an IUD is reported. Recent reports suggest that pelvic inflammatory disease (PID) is more common among users of the IUD than among those using other forms of contraception and that there is an association between IUD use and pelvic actinomycosis. In 1979 a woman at the University of New Mexico Hospital died from pelvic actinomycosis, the 2nd reported death from this disease associated with the use of an IUD, although her death from pulmonary embolus and Candida endocartidis should more appropriately be considered a complication of intravenous hyperalimentation. At least 25 patients are reported to have had serious pelvic actinomycosis associated with the use of an IUD. No particular type of IUD seems less likely to be associated with actinomycosis. Actinomyces are normally present in the gut and oropharynx, so that inoculation of the vagina with stool or saliva in combination with trauma induced by the foreign body such as an IUD may allow the actinomyces to enter tissues. Actinomyces are easily detected by Papanicolaou-stained cervicovaginal smears and are present in as many as 25% of symptomatic women using IUDs. Culture techniques usually fail in detecting actinomyces, the need for an anaerobic environment or overgrowth by bacteria which invariably accompany actinomyces are the usual causes of failure. Usual signs of IUD-associated actinomycosis are pelvic and lower abdominal or back pain, vaginal discharge, fever, and elevation of leukocyte count which are similar to symptoms of mild PID. Therefore these symptoms demand a Papanicolaou-stained cervicovaginal smear and search for actinomyces. Treatment includes removal of the IUD and administration of penicillin. However at least 1 patient after receiving treatment returned later with actinomycotic tubo-ovarian and subphrenic abscesses. A period of at least 4-6 weeks of therapy is usually recommended. Most patients with pelvic masses underwent hysterectomy and bilateral salpingo-oophorectomy in addition to penicillin and IUD removal; a few were successfully treated with drainage of an intra-abdominal abscess.

Silicone-Induced Splenomegaly: Treatment of Pancytopenia by Splenectomy in a Patient on Hemodialysis - Bommer, J.; Ritz, E.; Waldherr, R. (New England Journal of Medicine, 1981)
SPLENIC sequestration of blood cells has been identified by several investigators as one cause of pancytopenia in dialyzed patients.1,2 In the case described below, a foreign-body reaction to silicone in the spleen was identified as a cause of pancytopenia, which responded to splenectomy. Case Report The patient was a woman born in 1920, who had polycystic kidneys. In February 1971, her serum creatinine was 9.1 mg per deciliter, her hemoglobin was 12.8 g per deciliter, her leukocyte count was 6500 per microliter, and her platelet count was 204,000 per microliter. Since November 1971, she has been receiving maintenance hemodialysis —. © 1981, Massachusetts Medical Society. All rights reserved.

Implementing counts in the operating room. - Greaves, J. (NATNews, 1981)

Tumorilysin Collected in Diffusion Chambers and Restraint of Foreign - Ferguson, D.J.; Urban, J.L. (Cancer Research, 1980)
Tumorilysin was found in diffusion chambers implanted s.c. or i.p. in A/BiF/F50+, DBA/2J and C57BL/6J mice. Chambers with 0.45-µm pores implanted s.c. were most densely covered by a syncytium of macrophages and had the most consistently active tumorilysin, compared with smaller-pored chambers or those implanted i.p. The lysin acted on cultures of murine sarcomas induced by foreign bodies, murine and human mammary carcinoma, and human lymphoma. Lysis was demonstrable within 15 min. There was a dose-response relationship between residual cell counts in cultures and concentrations of diffusion chamber fluid between 1.5 and 12.5%. Murine fibroblasts in culture were not lysed by tumorilytic fluid. The incidence of sarcomas induced by 15-mm vinyl squares implanted s.c. in A/BiF/F50+ mice was significantly reduced at 64 weeks in each of 4 experiments by 2 or 3 injections of 0.05 ml diffusion chamber fluid within the capsule on each side at 2 to 42 weeks after implantation. Analyses of the fluid, compared with serum, for the following substances showed no correlation with tumorilysis: cathepsin D; neutral protease; complement C3 fraction; and arginase. Tumorilysin was preserved by lyophilization and was destroyed by heating to 56° it did not pass filters cutting off at m.w. 300,000. © 1980, American Association for Cancer Research. All rights reserved.

Management of the contaminated wound - Edlich, R.F.; Rodeheaver, G.T.; Stevenson, T.R.; Magee, C.M.; Thacker, J.G.; Edgerton, M.T. (COMPR.THER., 1977)
Traumatic wounds are always contaminated by bacteria, soil, and other foreign bodies. There is a delicate balance between the deleterious effects of the contaminants and the resistance of the host wound to infection. Successful management of the contaminated wound must include cleansing techniques that remove these contaminants while inflicting minimal injury to the tissue. The number of residual bacteria in the wound after cleansing is a critical determinant of infection. Most traumatic wounds containing >10 5 bacteria/g tissue are very likely to develop infection. When the bacterial count of a wound is below this level, and after soil and devitalized tissue are removed, wound healing without infection is consistently noted in healthy patients. Fortunately, most soft tissue wounds contain <10 5 organisms/g tissue. Those exhibiting high levels of bacterial inoculum must be subjected to treatments that reduce the bacterial count, remove all nonvital tissue, and prevent the development of infection.

THE STIMULATION OF SHEEP MONOCYTE MITOSIS IN VITRO BY AUTOLOGOUS PLASMA TAKEN AFTER SURGERY AND THE IMPLANTATION OF FOREIGN MATERIAL - Greenwood, B. (Quarterly Journal of Experimental Physiology and Cognate Medical Sciences, 1977)
When blood monocytes from sheep are grown upon glass in 100% autologous plasma they divide with low mitotic indices, but if the plasma is taken from the sheep three or four days after the implantation of a small Teflon or stainless steel cylinder, the maximum mitotic indices of the monocytes cultured in that plasma rise. Plasma collected from the sheep in the first two days after operation is often toxic to cultured autologous monocytes. An equivalent sham operation increases the mitogenicity of the plasma, but without a preceding toxic period. No consistent effects upon the numbers of circulating blood monocytes were noted following implantation operations. A hypothesis is presented which suggests that blood monocyte multiplication in vivo and in vitro is dependent upon (a) a lesion which causes cell attachment, and (b) a humoral component of the plasma which stimulates mitosis. Surgery, and the implantation of foreign materials will increase the concentration of such a substance in plasma. © 1977 The Physiological Society

Management of soft tissue injury. - Edlich, R.F.; Rodeheaver, G.T.; Thacker, J.G.; Winn, H.R.; Edgerton, M.T. (Clinics in Plastic Surgery, 1977)
The fate of a surgical wound is held in a delicate balance between the host's resistance to infection and the causal factors of infection. Considerable insight into this relationship between the host and pathogen can be gained from the results of quantitative bacteriologic measurements. Newer rapid slide techniques have been developed which provide the surgeon with this information within 20 minutes. In most soft tissue injuries, the wound bacterial count gives an accurate prediction of subsequent infection. Wounds combining greater than 10(5) bacteria per gram of tissue are destined to develop infection. When the bacterial count is below that level, the wounds will usually heal per primam without infection. This large number of bacteria required to elicit infection reflects the remarkable ability of soft tissues to resist infection. This state of high resistance to infection can be reduced by several factors which include circulatory embarrassment, tissue injury, dead space, and the presence of foreign bodies (dirt, sutures, drains, etc.). When treating soft tissue injuries, the surgeon must employ specific therapeutic modalities that allow the wound to heal per primam without infection. On the basis of experimental studies supported by clinical experience, the following treatment protocol for soft tissue injuries is recommended. Using strict aseptic technique, the wound must be first anesthetized with 1 per cent Xylocaine to permit painless sound cleansing. All wounds should be subjected to high pressure syringe irrigation to remove bacteria, foreign bodies, and blood clots. When necessary, debridement of all devitalized tissue should be performed with a stainless steel scalpel. Many wounds caused by sharp wounding agents contain no foreign bodies and few bacteria and exhibit considerable resistance to infection. In these wounds, primary closure can be initiated after irrigation without the development of infection. Wounds resulting from impact forces have a diminished resistance to infection and are susceptible to infection by low level of bacterial contamination. Immediate antibiotic treatment of patients with impact injuries subjected to meticulous debridement and cleansing will permit a safe primary closure. In wounds contacted by pus or feces, open wound management followed by delayed primary closure is usually indicated. Antimicrobial prophylaxis is also recommended for patients with such wounds. Ideal postoperative care of all traumatic wounds includes a surgical dressing and immobilization and elevation of the site of injury.

Activation of prolyl hydroxylase in sponge induced granulation tissue: The effect of antineutrophil serum and inhibitor drugs - Wiener, S.L.; Urivetzky, M.; Isenberg, H.D.; Belenko, M.; Talansky, A.; Havier, R.; Meilman, E. (Connective Tissue Research, 1977)
Prolyl hydroxylase activity in rat and rabbit sponge induced granulation tissue was studied as a function of time after implantation. The method of expression of such data was critical in determination of the shape of the curve. The method of data expression used in this paper was, cpm/μg of fibrocyte and fibroblast (F-DNA) or cpm per μg hydroxyproline. Use of other parameters such as extractable protein, wet weight or total DNA changed the shape of the curve and obscured the rapid increases in prolyl hydroxylase activity occurring during the first 48 hours. Giemsa and fast green staining was found to be a useful method for identification of fibroblasts in tissue sections. The use of this stain facilitated the large number of differential counts necessary for the calculation of F-DNA from total DNA values. Rats were treated with cyclophosphamide or antineutrophil serum to deplete them of neutrophils and monocytes. Such treatment failed to inhibit the usual increase in prolyl hydroxylase occurring in granulation tissue by the third day. In the rabbit an early 2-3 fold increase in prolyl hydroxylase activity in vivo was observed four hours after sponge implantation. This early increase in activity was blocked by inhibitors of RNA and protein synthesis and was considered to be dependent on new protein synthesis rather than on activation of a proenzyme. © 1977 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.

Is laminar airflow necessary for prophylaxis against wound infection? - Laufman, H. (Medical Instrumentation, 1976)
Abuse of an otherwise properly installed and maintained operating room system may result in rendering the environment unsatisfactory for critical types of surgery, especially when a patient's resistance is lowered by disease or drugs, or when a large foreign body is implanted. No type of special air handling system will correct these abuses even though it may reduce ambient bioparticle counts. From all available valid evidence, the conclusion is drawn that laminar flow is less effective against wound infection than adherence to proper techniques and correction of abuses of the operating room environment by the surgical team and support personnel. Abuse of an otherwise properly installed and maintained operating room system may result in rendering the environment unsatisfactory for critical types of surgery, especially when a patient's resistance is lowered by disease or drugs, or when a large foreign body is implanted. No type of special air-handling system will correct these abuses even though it may reduce ambient bioparticle counts. From all available valid evidence, the conclusion is drawn that laminar flow is less effective against wound infection than adherence to proper techniques and correction of abuses of the operating room environment by the surgical team and support personnel.

Metrical and Histopathological Studies on 2 Cases of Japanese Schistosomiasis Displaying Tremendous Numbers of Eggs Combined with Colon Cancers - Tokoro, Y.; Koganezawa, S. (Nippon Shokakibyo Gakkai Zasshi, 1976)
In 2 cases of Japanese schistosomiasis associated with colon carcinoma and with a giant polyp suggesting partially malignant changes of the sigmoid colon, respectively, microscopic counting of the total number of eggs distributed throughout the whole operation materials was tried. Thickness of boundary mucosae between cancer lesions and intact parts was measured. Then, constitutions responsible for their mucosal thickness were histologically investigated. As base on these metrical data, the present study was designed to elucidate collaborative findings of carcinogenesis with eggs. The data obtained herein lead to the following conclusions: 1) Complete absence of eggs in tumor lesions and their adjacent areas proximal to anus. 2) Numbers of eggs in submucosal layers of whole area approximately equal to those in the entire wall of rectum. 3) No definite foreign-body reaction on eggs. 4) No intimate relationship between the egg localisation and proliferation of mucosal elements. 5) Various values of thickness and abundant histological aspects in boundary mucosal areas between cancer and intact parts. 6) The mucosal thickness of 6 mm. consistently indicated that of carcinoma, themselves. 7) Values, meas. up to 2 or 4 mm, were expressed as the summation of the thickness of intra- and/or submucosal cancer nests, and intact mucosa, with occasional distinct lateral extension. 8) No transitional pictures between carcinoma and intact mucosal constituents in histology. 9) Scanty numbers of eggs in the boundary areas. 10) Non-specific glandular hyperplasia quite regardless of malignant transformation. © 1976, The Japanese Society of Gastroenterology. All rights reserved.

Foreign body tumorigenesis: number, distribution, and cell density of preneoplastic clones - Thomassen, M.J.; Bouen, L.C.; Brand, K.G. (Journal of the National Cancer Institute, 1975)
Double 15 x 22 mm plastic films (2 films on top of each other) were implanted subcutaneously in CBA/H T6 mice. After 7.5, 8.5 and 9.5 mth the films were removed. Each interior film (next to the abdominal wall), covered by a cell monolayer on one side only, was cut in 4 7 x 10 mm segments. Wiping to 5 x 7, 4 x 4, 3 x 3, or 2 x 2 mm reduced the cell areas on 3 of them. They were then transferred to (CBA/H x CBA/Br)F1 or (CBA/H T6 x CBA/Br)F1 recipient mice. Tumors arising from transferred film segments were analyzed as to chromosome number and morphology, sarcoma type, degree of anaplasticity, and posttransfer latency. These criteria were used to determine whether tumors originated from the same or different clones. From this information it was estimated that preneoplastic clones were present in limited numbers and that they were either widely disseminated or spatially restricted on the implant surfaces. The extent of clone dissemination was related to preneoplastic progression.

Antifertility and uterine response to polyethylene intrauterine devices in rabbits - Davis, R.H.; Kotwal, H.B.; Balin, H. (IRCS MED.SCI.BIOMED.TECH., 1975)

Splenectomy in renal transplantation. - Kauffman, H.M.; Swanson, M.K.; McGregor, W.R.; Rodgers, R.E.; Fox, P.S. (Surgery Gynecology and Obstetrics, 1974)

Medicolegal necessity for counting sharps - Russell, J.B. (Surgery Gynecology and Obstetrics, 1974)
The volume of malpractice litigation is steadily increasing. It is becoming more common for the plaintiff's attorney to include, along with the physician, the hospital and the nurses as defendants in appropriate situations. This is certainly true in any operating room situation. From a defense, or medicolegal point of view, it is essential that all operating room personnel take every reasonable precaution to avoid or minimize the possibility of a lawsuit. It has long been not only accepted practice but also a requirement that sponges, lap sheets and similar items be counted and accounted for before an incision is closed. The leaving of a foreign object, such as a sponge, a hemostat, or a needle in a patient is virtually conclusive proof of negligence of malpractice. Almost without exception, the courts will apply the doctrine of res ipsa loquitur, 'the thing speaks for itself', in such a situation. The general rule must be that the smaller the item, the greater the necessity for counting; all sharps, such as needles, scalpel blades and similar items. These are all items which can be as easily, if not more easily, lost in a patient than a sponge or a laparotomy sheet.

Starch granulomatous peritonitis - Ehrlich, C.E.; Wharton, J.T.; Gallager, H.S. (Southern Medical Journal, 1974)
Two cases of starch granulomatous peritonitis, one symptomatic and one asymptomatic, are presented. Although starch glove powder is usually innocuous, the number of cases of starch peritonitis reported in the literature indicates that it is not always so. The typical syndrome consists of abdominal pain, fever, and signs of peritonitis. The leukocyte count is usually within the normal range, but sometimes eosinophilia is present. Signs and symptoms characteristically develop 10 to 40 days after an uneventful operation. The diagnosis can be confirmed by finding starch granules in the tissue and in foreign body giant cells. Reoperation may be avoided by suspecting the syndrome and searching for starch in ascitic fluid obtained by paracentesis. Therapy consists of steroids or an anti-inflammatory agent such as indomethacin. © 1974 Southern Medical Association.

Immunologic reactivity in rabbits remotely deprived of the Sacculus rotundus - Gieldanowski, J.; Blaszczyk, B.; Teodorczyk, J. (Archivum Immunologiae et Therapiae Experimentalis, 1974)
The influence of remote removal of sacculus rotundus on humoral and cell mediated immunologic response in rabbits was studied. Ability to synthesize precipitins was only slightly impaired, but at the same time the numbers of PF cells were very distinctly reduced. Skin allografts 1-2 yr after the operation survived for somewhat longer periods; the reaction to tuberculin was entirely abolished and the course of allergic encephalitis was entirely suppressed. Removal of the sacculus rotundus in mature animals weakens immunologic reactivity of both classic types. This may be a result of cooperation of the thymus dependent and bursa dependent systems in inducing humoral as well as cell mediated immune reactions.

A quantitative study of the growth of connective tissue: Investigations on implanted polyester-polyurethane sponges - Paulini, K.; Körner, B.; Beneke, G.; Endres, R. (Connective Tissue Research, 1974)
A total of 57 male, 3-month old rats each received 6 implants in the subcutis of the back, each implant consisting of a PVC tube with two polyester-polyurethane sponges. After 1, 2, 3, 4, 6, 8, 12 and 16 weeks, the tubes were removed and the sponges were subjected to morphological, morphometric, chemical (DNA and collagen) autoradiographical and radiochemical examination. On the basis of the test results, it was established that in the particular form of induced tissue growth chosen three phases can bs distinguished: in the first phase which lasts till the end of the first week after implantation, an exudative inflammation arises. This is measurable by the high percental proportion of neutrophile granulocytes and the 3H-thymidine indices of the proliferating cells. The second phase, which lasts from the 2nd to the 4th week, was defined as the reparative phase. After the 4th week, we had a model of a chronic proliferative inflammation. At this time, and continuing until the end of the test period, the labelling index of the proliferating cells was clearly higher than that of unstimulated tissue. Because the duration of the separate phases can be exactly defined, this mcdel is particularly suitable for the testing of various pharmaceutical pxparation. © 1974 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.

Kinetics of multinucleate giant cell formation and their modification by various agents in foreign body reactions - Papadimitriou, J.M.; Sforsina, D.; Papaelias, L. (American Journal of Pathology, 1973)
Foreign body multinucleate giant cells were produced by the implantation of a strip of Melenex in the subcutaneous tissues of mice. The implants were removed at various intervals, and the proportion of multinucleate giant cells as well as the number of nuclei they contained were counted and statistically assessed. The greatest proportion of giant cells were reached 4 wk after implantation, when 25% of the attached cells were multinucleated. The mean nuclear content however was greatest approximately 2 wk after implantation and rapidly fell over the ensuing weeks. The fusion potential, however, remained almost unaltered for the remainder of the experimental period. Transplantation of 7 day implants from normal donors into lethally irradiated recipients demonstrated that the half life of the giant cells is only a few days. Treatment with carrageenin, species specific antisera, actinomycin D and cortisone inhibited, while puromycin enhanced, multinucleate cell formation. Calcium gluconate, EDTA and irradiation had no significant effect. The possible interpretation of some of these findings is discussed.

An experimental study of the effects of drains on colon anastomoses - Crowson, W.N.; Wilson, C.S. (American Surgeon, 1973)
The low canine colon anastomosis heals best when bacterial contamination is minimal, the anastomosis is not drained, and the anastomosis is intraperitoneal. A drain makes intraperitoneal sepsis worse and is harmful to the peritoneal cavity. Silastic drains are less harmful than latex and vinyl drains. Local sepsis interferes with colon healing.

Incarceration of penis by foreign body - Stuppler, S.A.; Walker, J.G.; Kandzari, S.J.; Milam, D.F. (Urology, 1973)
A case report of a remarkably long-term penile incarceration by a foreign body and its management and outcome are examined. © 1973.

Factors of clinical significance affecting wound healing - Dingman, R.O. (Laryngoscope, 1973)
The success of surgical procedures is largely dependent upon an orderly process of repair and wound healing and although we do not recount these daily, understanding of the available knowledge will inf luence the attitudes, techniques, and philosophies of the surgeon and lead to better overall patient care. Some factors of wound healing are entirely beyond the control of the surgeon while many factors of technique and wound management affecting the process of wound healing are within the control of the surgeon and are of practical importance in every surgical procedure. This presentation reviews the current concepts of wound repair, mentions those over which we have little control, and points out factors over which the surgeon does exert an influence and relates these to optimal wound care and satisfactory wound healing. © The American Laryngological, Rhinological & Otological Society, Inc.

Encapsulation of the björk-shiley aortic disc valve prosthesis caused by the lack of anticoagulation treatment - Björk, V.O.; Henze, A. (Scandinavian Cardiovascular Journal, 1973)
We have never experienced encapsulation or massive thrombosis of a Björk-Shiley aortic valve prosthesis in a patient receiving an adequate anticoagulation treatment. An encapsulation has, however, been described after many different types of heart valve replacements. Early diagnosis and emergency operation are mandatory. We have only encountered two cases of massive thrombosis in Björk-Shiley tilting disc valve prostheses in the aortic position out of 300 implants. Anticoagulant treatment was not given in either case. One patient died before final diagnosis was made and the other underwent an emergency operation. It was possible to clean out all thrombus material on both sides of the valve after temporary removal of ths disc and rotation of the valve. This method cannot, however, be recommended for general use. If the surgeons are not experienced in the proper removal of the disc, they will bend the struts so that the disc will not function properly after re-insertion. The insertion of a new prosthesis is a safer procedure. As we have never found encapsulation of an aortic prosthesis after adequate anticoagulation, this treatment is, therefore, recommended. © 1973 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.

Survey into counting precautions in New South Wales operating theatres. - Woodcroft, R. (The Lamp, 1972)

DIAGNOSIS OF STARCH PERITONITIS BY PARACENTESIS - Warshaw, AndrewL. (The Lancet, 1972)
The symptoms of starch peritonitis, a granulomatous reaction to surgical glove powder, may be difficult to distinguish from a complicating bacterial infection and have often led to unnecessary reoperation. This report describes nine suspected cases of starch peritonitis in which the diagnosis was supported by examination of ascitic fluid obtained by paracentesis. Ascitic fluid from these patients was abundant, sterile, and contained mononuclear leucocytes. Starch granules were demonstrated either by iodine staining or by polarised-light microscopy in seven of nine uncentrifuged specimens. Control specimens from ten other postoperative patients contained smaller numbers of mononuclear leucocytes and no starch granules. None of the nine patients with starch peritonitis was re-explored; in each case the peritoneal reaction subsided without complication and did not recur. Although a late postoperative infection must not be lightly dismissed, generally the symptom complex of starch peritonitis is consistent enough to be recognised easily. Examination of ascitic fluid provides a rapid, simple method of confirming the diagnosis and avoiding unnecessary reoperation. © 1972.

The glove starch peritonitis syndrome. - Ignatius, J.A.; Hartmann, W.H. (Annals of surgery, 1972)

Recording of fetal electrocardiogram by means of intrauterine transmitter - Tazawa, H.; Wada, T.; Yoshimoto, C.; Oguni, C. (Japanese journal of medical electronics and biological engineering, 1968)
Fetal heart rate is known as one of the best representations of the fetal situations in labor. The heart rate is counted by means of FECG or FPCG obtained from the maternal abdominal wall or direct ECG from the fetal scalp after rupture of the amnionic sac. However, these methods are not satisfactory by the reasons of poor signal to noise ratio, difficulty in continuous monitoring, and so on. Accordingly, we applied the radiotelemetry to measurement of FHR, in which an adequate size transmitter combined withelectrodes was inserted into the uterine space. The direct FECG was transmitted throughout all stages of labor and received by a commercial short wave radio receiver placed near by. And ECG of the newborn baby was also taken from the axilla with ease by a clip electrodetransmitter consisting a clip electrode for adult limb lead and a small transmitter. The carrier frequency was chosen at about 6 Mc/s and the amplitude was modulated by the signal. The size and the form of the transmitter were determined to allow easy insertion to uterine space, complete contact with the amnionic sac and easy exchange of the battery, and not to behave as a foreign body and not to being exhausted by delivery. After construction on the board of printed wiring, the transmitter was molded by silicon rubber. to prevent from injuring the body and to be insulated from the tissues. The total weight and volume were 15 g and 9 cm3, respectively. Drain current was 200 μA with the receiving range of about 1.5 meter. ECGs of six fetuses including three cases of cesarean section were investigated throughout labor and delivery. Especially interesting results were obtained of FHRs before and after rupture of the amnionic sac, labor, delivery and ligation of the umbilical cord and during cesarean section. © 1968, Japanese Society for Medical and Biological Engineering. All rights reserved.

The effect of 6‐mercaptopurine on the inflammatory response stimulated by subcutaneous implantation of polyvinyl sponge - Bole, G.G., Jr.; Heath, L.E. (Arthritis & Rheumatism, 1967)

XXIX. Perforation of the esophagus with report of six cases - King, E. (Annals of Otology, Rhinology & Laryngology, 1929)
In speaking of the indications for external surgery, we generally find pain as the first symptom. Fever, rapid pulse and difficulty in swallowing rapidly ensue. Swelling of the tissues and emphysema are also accompanying signs. The emphysema may be present in a slight degree and remain unrecognized unless the X-ray is employed, as explained by Iglauer in 1924. The X-ray is an important adjunct for determining the amount of swelling and the progress of the case. With these signs present, and, in addition, a high white count, there is every reason for opening the neck. Of course, each case is a problem in itself, and no set rules should guide the surgeon in handling it. Marscke remarks that it is safer to operate too often than to withhold operation. From my experience with the last case reported this appeals to me. The infection first establishes itself in the loose perioesophageal tissues, and from there spreads out into the fascial planes of the neck, descending between the sheaths into the mediastinum. It is a relatively simple matter in upper esophageal perforations to open the neck and drain this area. It is not essential to remove the foreign body through the incision but it is essential to provide drainage. If the foreign body is found outside the esophagus, as in the case reported by Iglauer and Ransohoff, it can be removed. I believe that Marschik's method is a very effective one for establishing drainage and preventing the descent of the infection. His technic briefly is to open the neck in front of the sternomastoid muscle, bluntly dissecting clown to the anterior margin of the vascular sheath. The omohyroid muscle is divided and, following the course of the vessels, an iodoform gauze strip is packed in place at their lowermost limit to wall off the anterior mediastinum. The thyroid gland is then lifted forward and an iodoform gauze tampon inserted beneath it to wall off the posterior mediastinum. The abscess cavity is then drained. Marschik refers to this procedure as prophylactic mediastinotomy. © 1929, SAGE Publications. All rights reserved.